Abnormal epigenetic modification of lysosome and lipid regulating genes in Alzheimer's disease. - Ruan, Tingting; Ling, Yunxiang; Wu, Can; Niu, Yanfang; Liu, Guili; Xu, Chunshuang; Lv, Zhongyue; Yuan, Yalan; Zhou, Xinkai; Wang, Qinwen; Xu, Shujun (J Alzheimers Dis, 2025)
BackgroundAbnormal lipid metabolism has been identified as a potential pathogenic mechanism of Alzheimer's disease (AD), which might be epigenetically regulated. Lysosomes are critical organelles for lipid metabolism. However, the epigenetic modifications of lysosome and lipid regulating genes remain unclear in AD patients.ObjectiveExplore the role of abnormal epigenetic modifications, especially methylation of lysosome and lipid metabolism-related genes in AD.MethodsMethylation beadchip and MALDI-TOF mass spectrometry were used to detect genome-wide DNA methylation levels and validate key gene methylation, respectively. Clinical data were collected from all participants. Associations between clinical biochemical characteristics and altered DNA methylation in AD patients were analyzed, and a risk factor model of AD was established.Results41 differentially methylated positions (DMPs) corresponding to 33 genes were identified in AD patients, with 18 hypermethylated and 23 hypomethylated positions. Significant alterations were observed in lipid regulating genes () and lysosomal transmembrane gene (). Clinical analysis revealed that TP, ALB, IB, ADA, ALP, HCY, GLU, TC, BUN, HDL-C, LDL-C, and APOA1 levels were significantly higher in AD patients, whereas A/G and DB levels were lower. hypermethylation was further verified and found to correlate with TC, HDL-C, LDL-C, APOA1, IB, and HCY. The AUC of the AD risk model, which integrated clinical lipid markers and methylation, reached 0.9519 (< 0.0001).ConclusionsAbnormal epigenetic regulation of lysosomal gene and lipid dyshomeostasis were high-risk factors in AD. Methylation modifications of lysosome and lipid regulating genes might be key processes in AD pathogenesis.

Associations of dietary protein and amino acid intakes with disability-adjusted life years for Alzheimer's disease in Japanese people. - Ishikawa-Takata, Kazuko; Fujiwara, Kazuki; Tanaka, Takayuki; Nakamura, Keiji; Kobayashi, Hisamine; Okada, Shinobu (J Alzheimers Dis, 2025)
BackgroundThe number of patients with dementia is increasing worldwide. In Japan, dementia is the most significant reason recognized for people requiring nursing care. Protein is one of the possible preventive nutrients for dementia; however, adequate intake levels can differ according to usual protein intakes and protein sources.ObjectiveThis study examined the relationships between disability-adjusted life years (DALYs) for Alzheimer's disease and protein or amino acid intakes.MethodsGlobal Burden of Disease Study data (DALYs for each sex and age group in each year) and de-identified individual records from the National Health and Nutrition Survey Japan (data from 46,831 subjects) from 2001 to 2019 were used. Multiple regression analyses were conducted to assess the relationships between DALYs and protein or amino acid intakes with lifestyle factors and sociodemographic index as confounding factors.ResultsHigher protein-to-energy ratios were correlated with lower DALYs in women in their 70 s (partial regression coefficient [Coeff.] = -349.488,  = 0.034), in men in their 60 s (Coeff. = -51.484), and in both sexes combined in their 60 s (Coeff. = -26.696,  = 0.015) even after adjusting for other possible nutrient intakes. Additionally, elevated isoleucine, lysine, tyrosine, histidine, arginine, alanine, asparagine, and glycine levels were correlated with lower DALYs in women in their 70 s (Coeff. = -2.752 to -0.141).ConclusionsAdequate protein and specific amino acid intakes may be associated with DALYs for Alzheimer's disease.

Brain-penetrant histone deacetylase inhibitor RG2833 improves spatial memory in females of an Alzheimer's disease rat model. - Ndukwe, Kelechi; Serrano, Peter A; Rockwell, Patricia; Xie, Lei; Figueiredo-Pereira, Maria E (J Alzheimers Dis, 2025)
BACKGROUND: Nearly two-thirds of Alzheimer's disease (AD) patients are women. Therapeutics for women are critical to lowering their elevated risk of developing this major cause of adult dementia. Moreover, targeting epigenetic processes such as histone acetylation that regulate multiple cellular pathways is advantageous given the multifactorial nature of AD. Histone acetylation takes part in memory consolidation, and its disruption is linked to AD. OBJECTIVE: Determine whether the investigational drug RG2833 has repurposing potential for AD. RG2833 is a histone deacetylase HDAC1/3 inhibitor that is orally bioavailable and permeates the blood-brain-barrier. METHODS: RG2833 effects were determined on cognition, transcriptome, and AD-like pathology in 11-month TgF344-AD female and male rats. Treatment started early in the course of pathology when therapeutic intervention is predicted to be most effective. RESULTS: RG2833-treatment of 11-month TgF344-AD rats: (1) Significantly improved hippocampal-dependent spatial memory in females but not males. (2) Upregulated expression of immediate early genes, such as Arc, Egr1 and c-Fos, and other genes involved in synaptic plasticity and memory consolidation in females. Remarkably, out of 17,168 genes analyzed for each sex, no significant changes in gene expression were detected in males at p < 0.05, false discovery rate <0.05, and fold-change equal or > 1.5. (3) Failed to improve amyloid beta accumulation and microgliosis in female and male TgF344-AD rats. CONCLUSIONS: Our study highlights the potential of histone-modifying therapeutics such as RG2833 to improve cognitive behavior and drive the expression of immediate early, synaptic plasticity and memory consolidation genes, especially in female AD patients.

Impact of obesity on neuropsychiatric symptoms in Alzheimer's disease: Insights from the ADNI cohort. - Wang, Shuoshi; Ni, Jingnian; Wei, Mingqing; Li, Ting; Shi, Jing; Tian, Jinzhou (J Alzheimers Dis, 2025)
BackgroundObesity is a major global health issue linked to increased risks of dementia, including Alzheimer's disease (AD). While the association between obesity and neuropsychiatric symptoms (NPS) in AD remains underexplored, identifying these links could aid in weight management in AD patients.ObjectiveThis study investigates the relationship between body mass index (BMI) and NPS in AD dementia patients, focusing on the potential mediating role of systemic inflammation.MethodsWe employed Generalized Additive Models (GAMs) to explore the relationship between BMI and NPS, as measured by the Neuropsychiatric Inventory Questionnaire (NPI-Q). Participants were classified into ideal, overweight, and obese groups based on WHO criteria. Longitudinal analyses assessed the trajectory of NPI-Q scores in different groups over a one-year follow-up.ResultsBMI significantly affects NPI-Q total scores and specific symptoms, including delusions, hallucinations, agitation/aggression, elation/euphoria, disinhibition, irritability/lability, aberrant motor behavior, nighttime disturbances, and appetite/eating disturbances. Obese patients exhibited higher NPI-Q total scores and greater severity in symptoms such as hallucinations, agitation/aggression, elation/euphoria, apathy/indifference, disinhibition, aberrant motor behavior, and nighttime disturbances. Additionally, CRP and complement C3 were identified as mediators in the relationship between obesity and NPS, highlighting the role of systemic inflammation.ConclusionsThis study demonstrates that obesity is associated with a heightened burden of NPS in AD dementia patients. The identification of CRP and complement C3 as mediators suggests inflammation plays a crucial role in the association between obesity and NPS. These findings underscore the importance of addressing obesity and its inflammatory consequences in managing NPS among this vulnerable population.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Body Mass Index; Cohort Studies; Female; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Obesity

Lipopolysaccharides from indirectly induce neuronal GSK3β-dependent synaptic defects and cause cognitive decline in a low-amyloid-β-concentration environment in Alzheimer's disease. - Gui, Shuge; Zeng, Fan; Wu, Zhou; Nonaka, Saori; Sano, Tomomi; Ni, Junjun; Nakanishi, Hiroshi; Moriyama, Masafumi; Kanematsu, Takashi (J Alzheimers Dis, 2025)
BackgroundLipopolysaccharides from s (LPS) are involved in the pathology of Alzheimer's disease (AD). However, the effect of LPS on synaptic defects remains unclear.ObjectiveIn this study, we tested our hypothesis that LPS induces synaptic defects in a low-amyloid-beta (Aβ)-concentration environment.MethodsMG6 microglia or N2a neurons was treated with LPS (0.1 μg/mL), soluble Aβ (0.1 μM) or AL (combined LPS and soluble Aβ at 0.1 μM).ResultsIn cultured MG6 microglia, increased the mRNA expression of TNF-α, IL-1β and IL-6 and the TNF-α release in parallel with increased NF-κB activation. In cultured N2a neurons, treatment with Aβ, LPS, and AL did not affect the mRNA expression of synapsin1 (SYN1) or post-synaptic density protein-95 (PSD-95). However, the treatment with conditioned medium from AL-exposed MG6 microglia (AL-MCM) significantly reduced the mRNA and protein expression of SYN1, PSD-95, and nuclear translocation of repressor element-1 silencing transcription factor (REST) but significantly increased the mRNA expression of TNF receptor type I (at 48 h) and glycogen synthase kinase (GSK)3β (at 24 h). TWS119 pretreatment (5 μM), a GSK3β specific inhibitor, significantly reversed the AL-MCM-induced reduction in the mRNA expression of SYN1 and PSD-95 and nuclear translocation of REST in cultured N2a neurons. In APP mice, the immunofluorescence intensity of SYN1 and PSD-95 in cortical neurons was positively correlated with the index of the memory test but negatively correlated with that of TNF-α-positive microglia.ConclusionsThese observations demonstrate that LPS induces neuronal GSK3β-dependent synaptic defects in a low-Aβ concentration environment via microglial activation.

Medications and cognitive decline in Alzheimer's disease: Cohort cluster analysis of 15,428 patients. - Grau-Jurado, Pol; Mostafaei, Shayan; Xu, Hong; Mo, Minjia; Petek, Bojana; Kalar, Irena; Naia, Luana; Kele, Julianna; Maioli, Silvia; Pereira, Joana B; Eriksdotter, Maria; Chatterjee, Saikat; et al. (J Alzheimers Dis, 2025)
BACKGROUND: Medications for comorbid conditions may affect cognition in Alzheimer's disease (AD). OBJECTIVE: To explore the association between common medications and cognition, measured with the Mini-Mental State Examination. METHODS: Cohort study including persons with AD from the Swedish Registry for Cognitive/Dementia Disorders (SveDem). Medications were included if they were used by ≥5% of patients (26 individual drugs). Each follow-up was analyzed independently by performing 100 Monte-Carlo simulations of two steps each 1) k-means clustering of patients according to Mini-Mental State Examination at follow-up and its decline since previous measure, and 2) Identification of medications presenting statistically significant differences in the proportion of users in the different clusters. RESULTS: 15,428 patients (60.38% women) were studied. Four clusters were identified. Medications associated with the best cognition cluster (relative to the worse) were atorvastatin (point estimate 1.44 95% confidence interval [1.15-1.83] at first follow-up, simvastatin (1.41 [1.11-1.78] at second follow-up), warfarin (1.56 [1.22-2.01] first follow-up), zopiclone (1.35 [1.15-1.58], and metformin (2.08 [1.35-3.33] second follow-up. Oxazepam (0.60 [0.50-0.73] first follow-up), paracetamol (0.83 [0.73-0.95] first follow-up), cyanocobalamin, felodipine and furosemide were associated with the worst cluster. Cholinesterase inhibitors were associated with the best cognition clusters, whereas memantine appeared in the worse cognition clusters, consistent with its indication in moderate to severe dementia. CONCLUSIONS: We performed unsupervised clustering to classify patients based on their current cognition and cognitive decline from previous testing. Atorvastatin, simvastatin, warfarin, metformin, and zopiclone presented a positive and statistically significant associations with cognition, while oxazepam, cyanocobalamin, felodipine, furosemide and paracetamol, were associated with the worst cluster.

Social isolation, loneliness, genetic risk, and incident dementia in people with type 2 diabetes mellitus: A population-based cohort study. - He, Zhixuan; Nie, Yu; Zhang, Weijie; Liu, Yue; Liu, Yaping; Xue, Huachen; Ai, Sizhi; Feng, Hongliang; Zhou, Yujing; Zhang, Jihui; Liang, Yan Yannis; Ning, Yuping (J Alzheimers Dis, 2025)
BackgroundSocial isolation and loneliness, two independent constructs of social disengagement, are becoming increasingly recognized factors for dementia risk.ObjectiveWe aimed to investigate whether these two constructs also associate with dementia risk in individuals with type 2 diabetes mellitus (T2DM), which is becoming more prevalent.MethodsThe longitudinal study included 24,986 participants (mean age: 60.0 ± 6.9 years, median follow-up: 12.0 years) with T2DM at baseline from the UK Biobank. Social isolation and loneliness were assessed using self-reported questionnaires. Genetic risk factors for dementia including polygenic risk score (PRS) and genotype were extracted. We identified incident dementia cases by linking hospital records and death registries.ResultsSocial isolation (most versus least: hazard ratio, HR: 1.46 [95% confidence intervals, CI: 1.22-1.75]) and loneliness (yes versus no: 1.56 [1.25-1.95]) were associated with an increased risk of incident dementia after adjusting for demographic factors; however, such associations attenuated when further adjusting for health behaviors, psychological factors, or diabetes-related characteristics. The social isolation-dementia association was predominantly attributable to health behaviors (48% for the most social isolation), while the loneliness-dementia association was largely explained by psychological factors (46%). Significant modification effects of dementia genetic risk were observed in these associations.ConclusionsSocial isolation and loneliness were associated with a greater risk for incident dementia among T2DM individuals, with differential explanatory factors. The genetic risk for dementia modified these associations. The findings underscore the importance of strengthening social connections to mitigate diabetes-related dementia risk.

White matter lesions rather than amyloid-β burden are associated with cognitive decline in Alzheimer's disease. - Kasahara, Hiroo; Ikeda, Masaki; Makioka, Kouki; Nakamura, Takumi; Takahashi, Ryoma; Kawarabayashi, Takeshi; Sanada, Etsuko; Suto, Takayuki; Higuchi, Tetsuya; Tsushima, Yoshito; Ikeda, Yoshio (J Alzheimers Dis, 2025)
We assessed the severity of amyloid-β accumulation and white matter lesions (WML) in the brain, and their association with cognitive decline, in patients (n = 47) with Alzheimer's disease (AD). The mean cortical standardized uptake value ratio (mcSUVR) was derived from amyloid positron emission tomography, while the percentage of WML area relative to brain parenchymal area was determined using magnetic resonance imaging. Cognitive decline was positively correlated with WML severity (= 0.50, = 0.042) but not mcSUVR (Aβ accumulation). Managing vascular risk factors can prevent cognitive decline in patients with AD.

Alzheimer DataLENS: An Open Data Analytics Portal for Alzheimer's Disease Research. - Noori, Ayush; Jayakumar, Rojashree; Moturi, Vaishnavi; Li, Zhaozhi; Liu, Rongxin; Serrano-Pozo, Alberto; Hyman, Bradley T; Das, Sudeshna (J Alzheimers Dis, 2024)
BACKGROUND: Recent Alzheimer's disease (AD) discoveries are increasingly based on studies from a variety of omics technologies on large cohorts. Currently, there is no easily accessible resource for neuroscientists to browse, query, and visualize these complex datasets in a harmonized manner. OBJECTIVE: Create an online portal of public omics datasets for AD research. METHODS: We developed Alzheimer DataLENS, a web-based portal, using the R Shiny platform to query and visualize publicly available transcriptomics and genetics studies of AD on human cohorts. To ensure consistent representation of AD findings, all datasets were processed through a uniform bioinformatics pipeline. RESULTS: Alzheimer DataLENS currently houses 2 single-nucleus RNA sequencing datasets, over 30 bulk RNA sequencing datasets from 19 brain regions and 3 cohorts, and 2 genome-wide association studies (GWAS). Available visualizations for single-nucleus data include bubble plots, heatmaps, and UMAP plots; for bulk expression data include box plots and heatmaps; for pathways include protein-protein interaction network plots; and for GWAS results include Manhattan plots. Alzheimer DataLENS also links to two other knowledge resources: the AD Progression Atlas and the Astrocyte Atlas. CONCLUSIONS: Alzheimer DataLENS is a valuable resource for investigators to quickly and systematically explore omics datasets and is freely accessible at https://alzdatalens.partners.org.
Keywords: Alzheimer Disease; Brain; Computational Biology; Genome-Wide Association Study; Humans; Internet

Amnestic Syndrome in Memory Clinics: Similar Morphological Brain Patterns in Older Adults with and without Alzheimer's Disease. - Lalive, Hadrien M; Griffa, Alessandra; Carlier, Sabrina; Nasuti, Mirco; Di Noto, Tommaso; Maréchal, Bénédicte; Rouaud, Olivier; Allali, Gilles (J Alzheimers Dis, 2024)
BACKGROUND: Amnestic syndrome of the hippocampal type (ASHT) in Memory Clinics is a presentation common to Alzheimer's disease (AD). However, ASHT can be found in other neurodegenerative disorders. OBJECTIVE: To compare brain morphometry including hippocampal volumes between amnestic older adults with and without AD pathology and investigate their relationship with memory performance and cerebrospinal fluid (CSF) biomarkers. METHODS: Brain morphometry of 92 consecutive patients (72.5±6.8 years old; 39% female) with Free and Cued Selective Recall Reminding Test (FCSRT) total recall < 40/48 was assessed with an automated algorithm and compared between AD and non-AD patients, as defined by CSF biomarkers. RESULTS: AD and non-AD patients presented comparable brain morphology. Total recall was associated to hippocampal volume irrespectively from AD pathology. CONCLUSIONS: Brain morphometry, including hippocampal volumes, is similar between AD and non-AD older adults with ASHT evaluated in a Memory Clinic, underlying the importance of using molecular biomarkers for the diagnosis of AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amnesia; Amyloid beta-Peptides; Biomarkers; Brain; Female; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Mental Recall; Neuropsychological Tests; Organ Size

Amyloid-Directed Antibodies: Past, Present, and Future. - Noorda, Keith; Noorda, Kevin; Sabbagh, Marwan N; Bertelson, John; Singer, Jonathan; Decourt, Boris (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is the most common neurodegenerative disorder in patient demographics over 65 years old causing debilitating cognitive impairment. Most commonly, AD is diagnosed clinically as "probable AD", and definitive diagnosis is confirmed through postmortem brain autopsies to detect extracellular amyloid-β (Aβ) plaques and intraneuronal hyperphosphorylated tau tangles. The exact mechanism causing AD is still unknown, but treatments for AD have been actively investigated. Currently, immunotherapies have shown substantial promise in reducing the pathologic and clinical signs of AD. OBJECTIVE: This review aims to evaluate passive immunotherapies deemed to have promise for further development and use in the treatment of AD. METHODS: Immunotherapies were selected via a narrative review of medications that have potential clinical effectiveness with a status of FDA accepted, FDA fast-track, FDA status pending, or emerging therapies poised to pursue FDA approval. RESULTS: This review has yielded two anti-Aβ monoclonal antibodies (mAb) that are currently fully FDA approved, one mAb granted FDA fast-track status, two therapies on hold, three discontinued medications, and three promising emerging therapies. CONCLUSIONS: We conclude that, in the near future, passive immunotherapies will be the preferred and evidence-based method of treatment for AD with the presence of brain Aβ deposits for both symptom management and potential slowing of disease progression. Specifically, lecanemab and donanemab will require further clinical studies to optimize patient selection based on safety profiles. Despite some key limitations, these two drugs are paving the way for disease-modifying treatments in patients displaying early signs of amyloid pathology.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal; Antibodies, Monoclonal, Humanized; Humans; Immunotherapy

The Association Between Distinct Delusional Ideations and Depressive Symptoms in Alzheimer's Disease: A Re-Analysis of CATIE-AD. - Nagata, Tomoyuki; Nakajima, Shinichiro; Kito, Shinsuke; Shinagawa, Shunichiro (J Alzheimers Dis, 2024)
BACKGROUND: Delusional ideations, one of neuropsychiatric symptoms (NPSs), are frequently shown in the long-term progression of Alzheimer's disease (AD), and comorbid with other NPSs including depression or agitation. Despite various types of delusional ideations, the comorbidity between each delusional ideation and depressive symptoms has not been discussed. OBJECTIVE: The present cross-sectional study is aimed at testing the hypothetical mechanism of comorbid pattern in AD. METHODS: Among 421 patients with AD, we analyzed the dataset of the Clinical Antipsychotic Trials of Intervention Effectiveness-Alzheimer's Disease to compare age, sex, racial type, Mini-Mental State Examination (MMSE) scores, and Neuropsychiatric Inventory (NPI) depression score of between the presence and absence of each delusional ideation (delusion of persecution, theft, jealousy, abandonment, phantom boarder, Capgras syndrome, misidentification of place, or television sign). Next, with the stratification based on MMSE score of < or > = 15 points, we further explored association between delusional ideation and depressive symptom that was found significances in the primary analysis. RESULTS: Among eight subtypes of delusional ideations, depression score was higher in those with persecution delusion or Capgras syndrome. Moreover, the Capgras syndrome was associated with presence of depression in severer global cognitive impairment status. CONCLUSIONS: As comorbid NPSs of delusional ideation in AD, depressive severity is associated with specific delusional subtype: persecution delusion and Capgras syndrome. Capgras syndrome may be attributable to severe cognitive impairment in addition to depressive symptom. The consideration of pathogenetic differences in the distinct delusional ideations may be helpful for clinicians to select the treatment strategy.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cross-Sectional Studies; Delusions; Depression; Female; Humans; Male; Mental Status and Dementia Tests

Blood Pressure Variability and Plasma Alzheimer's Disease Biomarkers in the SPRINT Trial. - Sible, Isabel J; Nation, Daniel A (J Alzheimers Dis, 2024)
BACKGROUND: Recent observational studies suggest higher blood pressure (BP) variability (BPV) is associated with Alzheimer's disease (AD) biomarkers amyloid-beta (Aβ) and tau. Less is known about relationships in interventional cohorts with strictly controlled mean BP levels. OBJECTIVE: Investigate the longitudinal relationship between BPV and change in plasma AD biomarkers under standard versus intensive BP treatment. METHODS: In this post hoc analysis of the SPRINT trial, 457 participants (n = 206 in standard group, n = 251 in intensive group) underwent repeated BP measurement between baseline and 12-months follow-up, and venipuncture at baseline and median (IQR) 3.5 (3.0-4.0) years later to determine plasma AD biomarkers total tau and Aβ1-42:Aβ1-40 ratio. BPV was calculated as tertiles of variability independent of mean. Linear mixed models investigated the effect of BPV×time on AD biomarker levels. RESULTS: Higher BPV was associated with increased levels of total tau in the standard group (β [95% CI] 1st versus 3rd tertiles of BPV: 0.21 [0.02, 0.41], p = 0.035), but not in the intensive group (β [95% CI] 1st versus 3rd tertiles of BPV: -0.02 [-0.19, 0.16], p = 0.843). BPV was not associated with Aβ 1-42:Aβ 1-40 ratio in either group. Mean BP was not associated with biomarkers. CONCLUSIONS: Higher BPV was associated with increased plasma total tau under standard BP treatment. Findings add new evidence to prior observational work linking BPV to AD pathophysiology and suggest that, despite strict control of mean BP, BPV remains a risk for pathophysiological change underlying risk for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Blood Pressure; Humans; tau Proteins

Cerebrospinal Fluid Proteomics Identifies Potential Biomarkers for Early-Onset Alzheimer's Disease. - Li, Dazhi; Xie, Qiang; Xie, Jikui; Ni, Ming; Wang, Jinliang; Gao, Yuru; Wang, Yaxin; Tang, Qiqiang (J Alzheimers Dis, 2024)
BACKGROUND: Early-onset Alzheimer's disease (EOAD) exhibits a notable degree of heterogeneity as compared to late-onset Alzheimer's disease (LOAD). The proteins and pathways contributing to the pathophysiology of EOAD still need to be completed and elucidated. OBJECTIVE: Using correlation network analysis and machine learning to analyze cerebrospinal fluid (CSF) proteomics data to identify potential biomarkers and pathways associated with EOAD. METHODS: We employed mass spectrometry to conduct CSF proteomic analysis using the data-independent acquisition method in a Chinese cohort of 139 CSF samples, including 40 individuals with normal cognition (CN), 61 patients with EOAD, and 38 patients with LOAD. Correlation network analysis of differentially expressed proteins was performed to identify EOAD-associated pathways. Machine learning assisted in identifying crucial proteins differentiating EOAD. We validated the results in an Western cohort and examined the proteins expression by enzyme-linked immunosorbent assay (ELISA) in additional 9 EOAD, 9 LOAD, and 9 CN samples from our cohort. RESULTS: We quantified 2,168 CSF proteins. Following adjustment for age and sex, EOAD exhibited a significantly greater number of differentially expressed proteins than LOAD compared to CN. Additionally, our data indicates that EOAD may exhibit more pronounced synaptic dysfunction than LOAD. Three potential biomarkers for EOAD were identified: SH3BGRL3, LRP8, and LY6 H, of which SH3BGRL3 also accurately classified EOAD in the Western cohort. LY6 H reduction was confirmed via ELISA, which was consistent with our proteomic results. CONCLUSIONS: This study provides a comprehensive profile of the CSF proteome in EOAD and identifies three potential EOAD biomarker proteins.

Cognitive Outcomes in Autosomal-Dominant Alzheimer's Disease: A Comprehensive Review from a Colombian Kindred with the Presenilin-1 E280A Mutation. - Giudicessi, Averi; McDowell, Celina Pluim; Martinez, Jairo E; Baena, Ana; Vila-Castelar, Clara; Norton, Daniel; Aguirre-Acevedo, Daniel C; Tirado, Victoria; Bocanegra, Yamile; Guzmán-Vélez, Edmarie; Lopera, Francisco; Cronin-Golomb, Alice; et al. (J Alzheimers Dis, 2024)
BACKGROUND: The largest identified kindred worldwide with a single mutation causing autosomal-dominant Alzheimer's disease (ADAD) is a family from Antioquia, Colombia, carrying the Presenilin-1 (PSEN1) E280A (Paisa) mutation. The majority of mutation carriers develop dementia, typically commencing in their late 30 s, with a median onset age of 49 years. Cognitive decline is a hallmark feature. OBJECTIVE: This review synthesizes the existing literature on neuropsychological assessments in PSEN1 E280A mutation carriers throughout their lifespan. We provide a comprehensive overview of cognitive outcomes in this unique population. METHODS: We reviewed and integrated the published research, analyzing studies on neuropsychological assessments in PSEN1 E280A carriers. Our focus was on measures of verbal, semantic, episodic, and spatial memory, and encompassed other cognitive domains such as language, attention, visuospatial memory, and executive functioning. RESULTS: Verbal, semantic, episodic, and spatial memory emerged as the most sensitive indicators of preclinical changes in PSEN1 E280A carriers. Inconsistencies were noted in findings from tests assessing language, attention, visuospatial memory, and executive functioning, suggesting potential limitations in detecting early cognitive changes in PSEN1 mutation carriers. Specific cognitive tasks developed for this population proved effective but underutilized. CONCLUSIONS: The review underscores the importance of continued test development tailored to detect early cognitive changes in PSEN1 E280A carriers, potentially enhancing ADAD screening. Furthermore, investigating ADAD mutations in children may identify early changes in AD and enhance our understanding of neuropsychological functioning across the lifespan. This synthesis provides valuable insights for researchers, clinicians, and policymakers engaged in the study and management of ADAD.

Dementia Ideal Care: Ecosystem Map of Best Practices and Care Pathways Enhanced by Technology and Community. - Dombrowski, Wen; Mims, Adrienne; Kremer, Ian; Cano Desandes, Pedro; Rodrigo-Herrero, Silvia; Epps, Fayron; Snow, Teepa; Gutierrez, Myrna; Nasta, Anil; Epperly, Mikele Bunce; Manaloto, Katrina; Hansen, Jennie Chin (J Alzheimers Dis, 2024)
BACKGROUND: Globally, much work has been done by nonprofit, private, and academic groups to develop best practices for the care of people living with dementia (PLWD), including Alzheimer's disease. However, these best practices reside in disparate repositories and tend to focus on one phase of the patient journey or one relevant group. OBJECTIVE: To fill this gap, we developed a Dementia Ideal Care Map that everyone in the dementia ecosystem can use as an actionable tool for awareness, policy development, funding, research, training, service delivery, and technology design. The intended audience includes (and not limited to) policymakers, academia, industry, technology developers, health system leaders, clinicians, social service providers, patient advocates, PLWD, their families, and communities at large. METHODS: A search was conducted for published dementia care best practices and quality measures, which were then summarized in a visual diagram. The draft diagram was analyzed to identify barriers to ideal care. Then, additional processes, services, technologies, and quality measures to overcome those challenges were brainstormed. Feedback was then obtained from experts. RESULTS: The Dementia Ideal Care Map summarizes the ecosystem of over 200 best practices, nearly 100 technology enablers, other infrastructure, and enhanced care pathways in one comprehensive diagram. It includes psychosocial interventions, care partner support, community-based organizations; awareness, risk reduction; initial detection, diagnosis, ongoing medical care; governments, payers, health systems, businesses, data, research, and training. CONCLUSIONS: Dementia Ideal Care Map is a practical tool for planning and coordinating dementia care. This visualized ecosystem approach can be applied to other conditions.
Keywords: Delivery of Health Care; Dementia; Humans; Practice Guidelines as Topic

Early Astrocytic Dysfunction Is Associated with Mistuned Synapses as well as Anxiety and Depressive-Like Behavior in the AppNL-F Mouse Model of Alzheimer's Disease. - Portal, Benjamin; Södergren, Moa; Parés I Borrell, Teo; Giraud, Romain; Metzendorf, Nicole G; Hultqvist, Greta; Nilsson, Per; Lindskog, Maria (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is the most common neurodegenerative disease. Unfortunately, efficient and affordable treatments are still lacking for this neurodegenerative disorder, it is therefore urgent to identify new pharmacological targets. Astrocytes are playing a crucial role in the tuning of synaptic transmission and several studies have pointed out severe astrocyte reactivity in AD. Reactive astrocytes show altered physiology and function, suggesting they could have a role in the early pathophysiology of AD. OBJECTIVE: We aimed to characterize early synaptic impairments in the AppNL-F knock-in mouse model of AD, especially to understand the contribution of astrocytes to early brain dysfunctions. METHODS: The AppNL-F mouse model carries two disease-causing mutations inserted in the amyloid precursor protein gene. This strain does not start to develop amyloid-β plaques until 9 months of age. Thanks to electrophysiology, we investigated synaptic function, at both neuronal and astrocytic levels, in 6-month-old animals and correlate the synaptic activity with emotional behavior. RESULTS: Electrophysiological recordings in the hippocampus revealed an overall synaptic mistuning at a pre-plaque stage of the pathology, associated to an intact social memory but a stronger depressive-like behavior. Astrocytes displayed a reactive-like morphology and a higher tonic GABA current compared to control mice. Interestingly, we here show that the synaptic impairments in hippocampal slices are partially corrected by a pre-treatment with the monoamine oxidase B blocker deprenyl or the fast-acting antidepressant ketamine (5 mg/kg). CONCLUSIONS: We propose that reactive astrocytes can induce synaptic mistuning early in AD, before plaques deposition, and that these changes are associated with emotional symptoms.

Functional Connectivity Favors Aberrant Visual Network c-Fos Expression Accompanied by Cortical Synapse Loss in a Mouse Model of Alzheimer's Disease. - L'Esperance, Oliver J; McGhee, Joshua; Davidson, Garett; Niraula, Suraj; Smith, Adam S; Sosunov, Alexandre A; Yan, Shirley ShiDu; Subramanian, Jaichandar (J Alzheimers Dis, 2024)
BACKGROUND: While Alzheimer's disease (AD) has been extensively studied with a focus on cognitive networks, visual network dysfunction has received less attention despite compelling evidence of its significance in AD patients and mouse models. We recently reported c-Fos and synaptic dysregulation in the primary visual cortex of a pre-amyloid plaque AD-model. OBJECTIVE: We test whether c-Fos expression and presynaptic density/dynamics differ in cortical and subcortical visual areas in an AD-model. We also examine whether aberrant c-Fos expression is inherited through functional connectivity and shaped by light experience. METHODS: c-Fos+ cell density, functional connectivity, and their experience-dependent modulation were assessed for visual and whole-brain networks in both sexes of 4-6-month-old J20 (AD-model) and wildtype (WT) mice. Cortical and subcortical differences in presynaptic vulnerability in the AD-model were compared using ex vivo and in vivo imaging. RESULTS: Visual cortical, but not subcortical, networks show aberrant c-Fos expression and impaired experience-dependent modulation. The average functional connectivity of a brain region in WT mice significantly predicts aberrant c-Fos expression, which correlates with impaired experience-dependent modulation in the AD-model. We observed a subtle yet selective weakening of excitatory visual cortical synapses. The size distribution of cortical boutons in the AD-model is downscaled relative to those in WT mice, suggesting a synaptic scaling-like adaptation of bouton size. CONCLUSIONS: Visual network structural and functional disruptions are biased toward cortical regions in pre-plaque J20 mice, and the cellular and synaptic dysregulation in the AD-model represents a maladaptive modification of the baseline physiology seen in WT conditions.
Keywords: Alzheimer Disease; Animals; Disease Models, Animal; Female; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Proto-Oncogene Proteins c-fos; Synapses; Visual Cortex

An Insertion Within SIRPβ1 Shows a Dual Effect Over Alzheimer's Disease Cognitive Decline Altering the Microglial Response. - García-Alberca, José María; de Rojas, Itziar; Sanchez-Mejias, Elisabeth; Garrido-Martín, Diego; Gonzalez-Palma, Laura; Jimenez, Sebastian; Pino-Angeles, Almudena; Cruz-Gamero, Jose Manuel; Mendoza, Silvia; Alarcón-Martín, Emilio; Muñoz-Castro, Clara; Real, Luis Miguel; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Microglial dysfunction plays a causative role in Alzheimer's disease (AD) pathogenesis. Here we focus on a germline insertion/deletion variant mapping SIRPβ1, a surface receptor that triggers amyloid-β(Aβ) phagocytosis via TYROBP. OBJECTIVE: To analyze the impact of this copy-number variant in SIRPβ1 expression and how it affects AD molecular etiology. METHODS: Copy-number variant proxy rs2209313 was evaluated in GERALD and GR@ACE longitudinal series. Hippocampal specimens of genotyped AD patients were also examined. SIRPβ1 isoform-specific phagocytosis assays were performed in HEK393T cells. RESULTS: The insertion alters the SIRPβ1 protein isoform landscape compromising its ability to bind oligomeric Aβ and its affinity for TYROBP. SIRPβ1 Dup/Dup patients with mild cognitive impairment show an increased cerebrospinal fluid t-Tau/Aβ ratio (p = 0.018) and a higher risk to develop AD (OR = 1.678, p = 0.018). MRIs showed that Dup/Dup patients exhibited a worse initial response to AD. At the moment of diagnosis, all patients showed equivalent Mini-Mental State Examination scores. However, AD patients with the duplication had less hippocampal degeneration (p < 0.001) and fewer white matter hyperintensities. In contrast, longitudinal studies indicate that patients bearing the duplication allele show a slower cognitive decline (p = 0.013). Transcriptional analysis also shows that the SIRPβ1 duplication allele correlates with higher TREM2 expression and an increased microglial activation. CONCLUSIONS: The SIRPβ1 internal duplication has opposite effects over MCI-to-Dementia conversion risk and AD progression, affecting microglial response to Aβ. Given the pharmacological approaches focused on the TREM2-TYROBP axis, we believe that SIRPβ1 structural variant might be considered as a potential modulator of this causative pathway.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Humans; Microglia; Phagocytosis; Receptors, Cell Surface

Long-Term Safety of Gantenerumab in Participants with Alzheimer's Disease: A Phase III, Double-Blind, and Open-Label Extension Study (Marguerite RoAD). - Neve, Anuja; Das, Bibha; Wojtowicz, Jakub; Huang, Zhiyue; Bullain, Szofia; Watkin, Michelle; Lott, Dominik; Bittner, Tobias; Delmar, Paul; Klein, Gregory; Hofmann, Carsten; Kerchner, Geoffrey A; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Gantenerumab is an anti-amyloid-β immunoglobulin G1 monoclonal antibody for subcutaneous (SC) administration. The efficacy and safety of low-dose (105 mg or 225 mg) gantenerumab were investigated in Marguerite RoAD (MR; NCT02051608), a Phase III, double-blind (DB), placebo-controlled study in participants with mild Alzheimer's disease (AD) dementia. Following a preplanned futility analysis of the SCarlet RoAD study (NCT01224106), MR was converted into an open-label extension (OLE). OBJECTIVE: The DB study aimed to assess the efficacy of gantenerumab compared with placebo from baseline to Week 104 in participants with mild AD dementia. Following conversion to an OLE, this objective became exploratory, as the OLE assessed the long-term safety and tolerability of SC gantenerumab at doses of up to 1,200 mg every 4 weeks (Q4W) in OLE participants. METHODS: Eligible DB study participants were offered the opportunity to receive gantenerumab up-titrated to 1,200 mg Q4W. Safety and tolerability were assessed using magnetic resonance imaging (MRI), physical and neurologic examinations, and adverse event monitoring. RESULTS: Overall, 225 participants were rolled over from the DB part of MR and received ≥1 gantenerumab dose in the OLE. The median treatment duration was 123 weeks. Fifty-nine (26.2%) and 41 (18.2%) participants had amyloid-related imaging abnormality (ARIA)-edema and ARIA-hemorrhage MRI findings, respectively. ARIA findings were manageable with MRI monitoring and dose intervention; most were asymptomatic. There were no unexpected safety findings. CONCLUSIONS: SC gantenerumab at doses of up to 1,200 mg Q4W were well tolerated in participants with mild AD dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antibodies, Monoclonal, Humanized; Double-Blind Method; Female; Humans; Male; Middle Aged; Treatment Outcome

Memory consolidation, temporal and parietal atrophy, and metabolism in amyloid-β positive and negative mild cognitive impairment. - Keith, Cierra M; Haut, Marc W; Vieira Ligo Teixeira, Camila; Mehta, Rashi I; Phelps, Holly; Ward, Melanie; Miller, Mark; Navia, R Osvaldo; Coleman, Michelle M; Marano, Gary; Wang, Xiaofei; Pockl, Stephanie; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is classically characterized by alterations in memory consolidation. With the advent of diagnostic biomarkers, some patients clinically diagnosed with AD display biomarkers inconsistent with the diagnosis. OBJECTIVE: We aimed to explore differences in memory consolidation and neurodegeneration of the temporal and parietal lobes as a function of amyloid-β status in amnestic mild cognitive impairment (aMCI). METHODS: We examined differences in memory consolidation and neurodegeneration between patients diagnosed with amyloid-β positive aMCI (Aβ+ N = 78), amyloid-β negative aMCI (Aβ- N = 48), and healthy participants (HP; N = 41), within a well-characterized clinical cohort. RESULTS: Aβ+ exhibited more pronounced consolidation impairments compared to Aβ-, while Aβ- faced more consolidation challenges than HP. Both Aβ+ and Aβ- were similar in hippocampal volume and entorhinal thickness, but Aβ+ had thinner inferior parietal cortex than Aβ-. Using F-fluoro-deoxyglucose-positron emission tomography, metabolism in both temporal and parietal regions was lower in Aβ+ relative to Aβ-. CONCLUSIONS: These findings suggest pathologies other than AD likely contribute to memory consolidation difficulties in aMCI, and neurodegeneration of the parietal cortex in combination with hypometabolism may contribute to more pronounced consolidation problems in Aβ+.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Atrophy; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Memory Consolidation; Middle Aged; Neuropsychological Tests; Parietal Lobe; Positron-Emission Tomography; Temporal Lobe

Parkinson's Disease and Other Alzheimer's Disease and Related Dementia Pathologies and the Progression of Parkinsonism in Older Adults. - Buchman, Aron S; Yu, Lei; Oveisgharan, Shahram; Zammit, Andrea R; Wang, Tianhao; Shulman, Joshua M; VanderHorst, Veronique; Nag, Sukrit; Bennett, David A (J Alzheimers Dis, 2024)
BACKGROUND: The interrelationship of parkinsonism, Parkinson's disease (PD) and other Alzheimer's disease (AD) and Alzheimer's disease and related dementias (ADRD) pathologies is unclear. OBJECTIVE: We examined the progression of parkinsonian signs in adults with and without parkinsonism, and their underlying brain pathologies. METHODS: Annual parkinsonian signs were based on a modified Unified Parkinson's Disease Rating Scale. We used linear mixed effects models to compare the progression of parkinsonian signs in 3 groups categorized based on all available clinical evaluations: Group1 (never parkinsonism or clinical PD), Group2 (ever parkinsonism, but never clinical PD), Group3 (ever clinical PD). In decedents, we examined the progression of parkinsonian signs with PD and eight other AD/ADRD pathologies. RESULTS: During average follow-up of 8 years, parkinsonian signs on average increased by 7.3% SD/year (N = 3,807). The progression of parkinsonian signs was slowest in Group1 (never parkinsonism or clinical PD), intermediate in Group2, and fastest in Group3. In decedents (n = 1,717) pathologic PD and cerebrovascular (CVD) pathologies were associated with a faster rate of progressive parkinsonian signs (all p values <0.05). However, pathologic PD was rare in adults without clinical PD (Group1, 5%; Group2, 7% versus Group3, 55%). Yet, 70% of adults in Group2 without pathologic PD showed one or more CVD pathologies. In Group2, adults with pathologic PD showed faster progression of parkinsonian signs compared with those without evidence of pathologic PD and their rate of progression was indistinguishable from adults with clinical PD. CONCLUSIONS: Parkinsonism in old age is more commonly related to cerebrovascular pathologies relative to pathologic PD and only a minority manifest prodromal PD.

Recent Advances in Drug Delivery Systems Targeting Insulin Signalling for the Treatment of Alzheimer's Disease. - Sachdeva, Punya; Narayanan, Kannan Badri; Sinha, Jitendra Kumar; Gupta, Saurabh; Ghosh, Shampa; Singh, Krishna Kumar; Bhaskar, Rakesh; Almutary, Abdulmajeed G; Zothantluanga, James H; Kotta, Kranthi Kumar; Nelson, Vinod Kumar; Paiva-Santos, Ana Cláudia; et al. (J Alzheimers Dis, 2024)
Alzheimer's disease (AD) is a complex neurodegenerative disorder characterized by the accumulation of neurofibrillary tangles and amyloid-β plaques. Recent research has unveiled the pivotal role of insulin signaling dysfunction in the pathogenesis of AD. Insulin, once thought to be unrelated to brain function, has emerged as a crucial factor in neuronal survival, synaptic plasticity, and cognitive processes. Insulin and the downstream insulin signaling molecules are found mainly in the hippocampus and cortex. Some molecules responsible for dysfunction in insulin signaling are GSK-3β, Akt, PI3K, and IRS. Irregularities in insulin signaling or insulin resistance may arise from changes in the phosphorylation levels of key molecules, which can be influenced by both stimulation and inactivity. This, in turn, is believed to be a crucial factor contributing to the development of AD, which is characterized by oxidative stress, neuroinflammation, and other pathological hallmarks. Furthermore, this route is known to be indirectly influenced by Nrf2, NF-κB, and the caspases. This mini-review delves into the intricate relationship between insulin signaling and AD, exploring how disruptions in this pathway contribute to disease progression. Moreover, we examine recent advances in drug delivery systems designed to target insulin signaling for AD treatment. From oral insulin delivery to innovative nanoparticle approaches and intranasal administration, these strategies hold promise in mitigating the impact of insulin resistance on AD. This review consolidates current knowledge to shed light on the potential of these interventions as targeted therapeutic options for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Drug Delivery Systems; Glycogen Synthase Kinase 3 beta; Humans; Insulin; Insulin Resistance

Regional differences in glucose metabolic decline and tau deposition in the Alzheimer's continuum brain. - Ishii, Kazunari; Yamada, Takahiro; Hanaoka, Kohei; Kaida, Hayato; Kojita, Yasuyuki; Kono, Atsushi; Hanada, Kazushi; Saigoh, Kazumasa; Sakuta, Shizuka; Hashimoto, Mamoru; Kato, Takashi; Nakamura, Akinori (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is characterized by the accumulation of amyloid-β and tau proteins, leading to neurofibrillary tangles. A biomarker-based diagnostic method called the ATN system categorizes AD pathology into amyloid-β (A), tau (T), and neurodegeneration (N). The relationship between regional tau deposition and reduced glucose metabolism in the preclinical AD stage is not well understood. OBJECTIVE: We presented voxel-by-voxel metabolic/tau deposition ratio (MTR) images to investigate the effects of tau deposition on metabolism in AD brains on a stage-by-stage basis. METHODS: We selected 174 subjects who underwent 3D-MRI, FDG-PET, amyloid PET, and tau PET scans. MTR images were created by normalizing FDG-PET toMK6240 PET images. Voxel-wise comparisons among 63 cognitively normal amyloid-negative (CNA) subjects, 49 subjects with AD dementia (ADD), 23 subjects with mild cognitive impairment due to AD (MCA), and 39 preclinical AD (PRC) subjects were conducted. RESULTS: There was reduced glucose metabolism in ADD and MCA groups compared to CNA, predominantly in parietotemporal areas. Tau deposition was observed in wider areas in ADD and restricted to the medial temporal lobes in MCA. MTR exhibited significant reductions in broader regions in ADD and MCA, indicating simultaneous glucose metabolism decrease and tau deposition. At the MCA and PRC stages, glucose metabolism impairment and tau deposition were shown in separate regions by FDG PET and tau PET, respectively, while MTR images showed impairment in both regions. CONCLUSIONS: Our findings suggest that MTR imaging provides insights into AD pathophysiology by simultaneously assessing glucose metabolism and tau deposition. In the early stage of the AD continuum (MCA and PRC), metabolic decline and tau deposition occur independently in different brain regions.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Brain; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Glucose; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Positron-Emission Tomography; tau Proteins

Senescence Targeting Methods Impact Alzheimer's Disease Features in 3xTg Mice. - Ng, Pei Y; Zhang, Cheng; Li, Hu; Baker, Darren J (J Alzheimers Dis, 2024)
BACKGROUND: Cellular senescence has been associated with neurodegenerative disease and clearance of senescent cells using genetic or pharmaceutical strategies (senolytics) has demonstrated beneficial effects in mouse models investigating individual disease etiologies of Alzheimer's disease (AD). However, it has remained unclear if senescent cell clearance in a mouse model exhibiting both plaque and tau pathologies modifies the disease state (3xTg). OBJECTIVE: To investigate the effects of senescent cell clearance in the 3xTg mouse model. METHODS: 3xTg mice were treated with senolytics (ABT263 (navitoclax; NAVI), a combination of dasatinib and quercetin (D+Q)), or subjected to transgene-mediated removal of p16-expressing cells (via INK-ATTAC). RESULTS: Senolytic treatments consistently reduced microgliosis and ameliorated both amyloid and tau pathology in 3xTg mice. Using RNA sequencing, we found evidence that synaptic dysfunction and neuroinflammation were attenuated with treatment. These beneficial effects were not observed with short-term senolytic treatment in mice with more advanced disease. CONCLUSIONS: Overall, our results further corroborate the beneficial effects senescent cell clearance could have on AD and highlight the importance of early intervention for the treatment of this debilitating disease.
Keywords: Alzheimer Disease; Animals; Cellular Senescence; Disease Models, Animal; Mice; Mice, Transgenic; Neurodegenerative Diseases; Senotherapeutics; tau Proteins

Serial Cerebrospinal Fluid Sampling Reveals Trajectories of Potential Synaptic Biomarkers in Early Stages of Alzheimer's Disease. - Duits, Flora H; Nilsson, Johanna; Zetterberg, Henrik; Blennow, Kaj; van der Flier, Wiesje M; Teunissen, Charlotte E; Brinkmalm, Ann (J Alzheimers Dis, 2024)
BACKGROUND: Synaptic dysfunction is closely associated with cognitive function in Alzheimer's disease (AD), and is present already in an early stage of the disease. OBJECTIVE: Using serial cerebrospinal fluid (CSF) sampling, we aimed to investigate slopes of CSF synaptic proteins, and their relation with cognition along the AD continuum. METHODS: We included subjects with subjective cognitive decline (SCD) or mild cognitive impairment (MCI) (n = 50 amyloid-β+ [A +], n = 50 A-) and 50 patients with AD dementia from the Amsterdam dementia cohort, with CSF at two time points (median[IQR] 2.1[1.4-2.7] years). We analyzed 17 synaptic proteins and neurofilament light (NfL). Using linear mixed models we assessed trajectories of protein levels, and associations with cognitive decline (repeated Mini-Mental State Examination). We used Cox regression models to assess predictive value of protein levels for progression to AD dementia. RESULTS: At baseline most proteins showed increased levels in AD dementia compared to the other groups. In contrast NPTX2 levels were lower in AD dementia. Higher baseline levels of SNAP25, β-syn, and 14-3-3 proteins were associated with faster cognitive decline (St.B[SE] -0.27[0.12] to -0.61[0.12]). Longitudinal analyses showed that SYT1 and NPTX levels decreased over time in AD dementia (st.B[SE] -0.10[0.04] to -0.15[0.05]) and SCD/MCI-A+ (St.B[SE] -0.07[0.03] to -0.12[0.03]), but not in SCD/MCI-A- (pinteraction < 0.05). Increase over time in NfL levels was associated with faster cognitive decline in AD dementia (St.B[SE] -1.75[0.58]), but not in the other groups (pinteraction < 0.05). CONCLUSIONS: CSF synaptic proteins showed different slopes over time, suggesting complex synaptic dynamics. High levels of especially SNAP-25 may have value for prediction of cognitive decline in early AD stages, while increase in NfL over time correlates better with cognitive decline in later stages.

There are dementia patients in Gaza too. - Irfan, Bilal; Abu Shammala, Abdallah; Alshaer, Nour; Nasser, Elias; Wajahath, Muaaz; Hamawy, Adam; Tahir, Mohammed; Khawaja, Haseeb; Khan, Osaama; Fikry, Karim; Kaleem, Arshad; Nasser, Mosab; et al. (J Alzheimers Dis, 2024)
This editorial highlights the devastating impact of the ongoing Israeli military assault in Gaza on dementia patients, whose fragile care systems have collapsed, leaving them vulnerable and without essential medical support. Through harrowing stories of displacement, medication shortages, and tragic deaths, the piece underscores the profound moral failure in protecting Gaza's most vulnerable, calling for urgent global action to address the humanitarian crisis and ensure dignity and healthcare for all affected individuals.
Keywords: Dementia; Humans; Middle East

Accumulation of pTau231 at the Postsynaptic Density in Early Alzheimer's Disease. - Lilek, Jaclyn; Ajroud, Kaouther; Feldman, Alexander Z; Krishnamachari, Sesha; Ghourchian, Shadi; Gefen, Tamar; Spencer, Callen L; Kawles, Allegra; Mao, Qinwen; Tranovich, Jessica F; Jack, Clifford R; Mesulam, M-Marsel; et al. (J Alzheimers Dis, 2023)

Activation of TNF Receptor 2 Improves Synaptic Plasticity and Enhances Amyloid-β Clearance in an Alzheimer's Disease Mouse Model with Humanized TNF Receptor 2. - Ortí-Casañ, Natalia; Wajant, Harald; Kuiperij, H Bea; Hooijsma, Annelien; Tromp, Leon; Poortman, Isabelle L; Tadema, Norick; de Lange, Julia H E; Verbeek, Marcel M; De Deyn, Peter P; Naudé, Petrus J W; Eisel, Ulrich L M (J Alzheimers Dis, 2023)
BACKGROUND: Tumor necrosis factor-alpha (TNF-α) is a master cytokine involved in a variety of inflammatory and neurological diseases, including Alzheimer's disease (AD). Therapies that block TNF-α proved ineffective as therapeutic for neurodegenerative diseases, which might be explained by the opposing functions of the two receptors of TNF (TNFRs): while TNFR1 stimulation mediates inflammatory and apoptotic pathways, activation of TNFR2 is related to neuroprotection. Despite the success of targeting TNFR2 in a transgenic AD mouse model, research that better mimics the human context is lacking. OBJECTIVE: The aim of this study is to investigate whether stimulation of TNFR2 with a TNFR2 agonist is effective in activating human TNFR2 and attenuating AD neuropathology in the J20xhuTNFR2-k/i mouse model. METHODS: Transgenic amyloid-β (Aβ)-overexpressing mice containing a human extracellular TNFR2 domain (J20xhuTNFR2-k/i) were treated with a TNFR2 agonist (NewStar2). After treatment, different behavioral tests and immunohistochemical analysis were performed to assess different parameters, such as cognitive functions, plaque deposition, synaptic plasticity, or microglial phagocytosis. RESULTS: Treatment with NewStar2 in J20xhuTNFR2-k/i mice resulted in a drastic decrease in plaque load and beta-secretase 1 (BACE-1) compared to controls. Moreover, TNFR2 stimulation increased microglial phagocytic activity, leading to enhanced Aβ clearance. Finally, activation of TNFR2 rescued cognitive impairments and improved synaptic plasticity. CONCLUSION: Our findings demonstrate that activation of human TNFR2 ameliorates neuropathology and improves cognitive functions in an AD mouse model. Moreover, our study confirms that the J20xhuTNFR2-k/i mouse model is suitable for testing human TNFR2-specific compounds.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Humans; Mice; Mice, Transgenic; Neuronal Plasticity; Receptors, Tumor Necrosis Factor, Type II; Tumor Necrosis Factor-alpha

Alzheimer's Disease and Neurosyphilis: Meaningful Commonalities and Differences of Clinical Phenotype and Pathophysiological Biomarkers. - Milano, Chiara; Hoxhaj, Domeniko; Del Chicca, Marta; Pascazio, Alessia; Paoli, Davide; Tommasini, Luca; Vergallo, Andrea; Pizzanelli, Chiara; Tognoni, Gloria; Nuti, Angelo; Ceravolo, Roberto; Siciliano, Gabriele; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Neurosyphilis-associated cognitive and behavioral impairment- historically coined as "general paralysis of the insane"- share clinical and neuroradiological features with the neurodegenerative disease spectrum, in particular Alzheimer's disease (AD). Anatomopathological similarities have been extensively documented, i.e., neuronal loss, fibrillary alterations, and local amyloid-β deposition. Consequently, accurate classification and timely differential diagnosis may be challenging. OBJECTIVE: To describe clinical, bio-humoral, brain MRI, FDG-PET, and amyloid-PET features in cases of neurosyphilis with an AD-like phenotypical presentation, as well as clinical outcome in terms of response to antibiotic therapy. METHODS: We selected the studies comparing patients with AD and with neurosyphilis associated cognitive impairment, to investigate candidate biomarkers classifying the two neurological diseases. RESULTS: The neuropsychological phenotype of general paralysis, characterized by episodic memory impairment and executive disfunction, substantially mimics clinical AD features. Neuroimaging often shows diffuse or medial temporal cortical atrophy, thus contributing to a high rate of misdiagnosis. Cerebrospinal fluid (CSF)-based analysis may provide supportive diagnostic value, since increased proteins or cells are often found in neurosyphilis, while published data on pathophysiological AD candidate biomarkers are controversial. Finally, psychometric testing using cross-domain cognitive tests, may highlight a wider range of compromised functions in neurosyphilis, involving language, attention, executive function, and spatial ability, which are atypical for AD. CONCLUSION: Neurosyphilis should be considered a potential etiological differential diagnosis of cognitive impairment whenever imaging, neuropsychological or CSF features are atypical for AD, in order to promptly start antibiotic therapy and delay or halt cognitive decline and disease progression.

Alzheimer's Disease Pathology Outside of the Cerebrum Is Related to a Higher Odds of Dementia. - Buchman, Aron S; Leurgans, Sue E; Kim, Namhee; Agrawal, Sonal; Oveisgharan, Shahram; Zammit, Andrea R; VanderHorst, Veronique; Nag, Sukrit; Bennett, David A (J Alzheimers Dis, 2023)
BACKGROUND: Assessments of Alzheimer's disease pathology do not routinely include lower brainstem, olfactory bulb, and spinal cord. OBJECTIVE: Test if amyloid-β (Aβ) and paired helical filament (PHF) tau-tangles outside the cerebrum are associated with the odds of dementia. METHODS: Autopsies were obtained in decedents with cognitive testing (n = 300). Aβ plaques and PHF tau-tangles were assessed in 24 sites: cerebrum (n = 14), brainstem (n = 5), olfactory bulb, and four spinal cord levels. Since spinal Aβ were absent in the first 165 cases, it was not assessed in the remaining cases. RESULTS: Age at death was 91 years old. About 90% had Aβ in cerebrum and of these, half had Aβ in the brainstem. Of the latter, 85% showed Aβ in the olfactory bulb. All but one participant had tau-tangles in the cerebrum and 86% had brainstem tau-tangles. Of the latter, 80% had tau-tangles in olfactory bulb and 36% tau-tangles in one or more spinal cord levels. About 90% of adults with tau-tangles also had Aβ in one or more regions. In a logistic model controlling for demographics, Aβ and tau-tangles within the cerebrum, the presence of Aβ in olfactory bulb [OR, 1.74(1.00, 3.05)]; tau-tangles in brainstem [OR, 4.00(1.1.57,10.21)]; and spinal cord [OR, 1.87 (1.21,3.11)] were independently associated with higher odds of dementia. CONCLUSION: Regional differences in Aβ and tau-tangle accumulation extend beyond cerebrum to spinal cord and their presence outside the cerebrum are associated with a higher odds of dementia. Further studies are needed to clarify the extent, burden, and consequences of AD pathology outside of cerebrum.

The Anti-Amyloid Monoclonal Antibody Lecanemab: 16 Cautionary Notes. - Kepp, Kasper P; Sensi, Stefano L; Johnsen, Kasper B; Barrio, Jorge R; Høilund-Carlsen, Poul F; Neve, Rachael L; Alavi, Abass; Herrup, Karl; Perry, George; Robakis, Nikolaos K; Vissel, Bryce; Espay, Alberto J (J Alzheimers Dis, 2023)
After the CLARITY-AD clinical trial results of lecanemab were interpreted as positive, and supporting the amyloid hypothesis, the drug received accelerated Food and Drug Administration approval. However, we argue that benefits of lecanemab treatment are uncertain and may yield net harm for some patients, and that the data do not support the amyloid hypothesis. We note potential biases from inclusion, unblinding, dropouts, and other issues. Given substantial adverse effects and subgroup heterogeneity, we conclude that lecanemab's efficacy is not clinically meaningful, consistent with numerous analyses suggesting that amyloid-β and its derivatives are not the main causative agents of Alzheimer's disease dementia.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloidogenic Proteins; Antibodies, Monoclonal; Humans; United States

Association of Alcohol Consumption with Cognition in Older Population: The A4 Study. - Nallapu, Bhargav T; Petersen, Kellen K; Lipton, Richard B; Grober, Ellen; Sperling, Reisa A; Ezzati, Ali (J Alzheimers Dis, 2023)
BACKGROUND: Alcohol use disorders have been categorized as a 'strongly modifiable' risk factor for dementia. OBJECTIVE: To investigate the cross-sectional association between alcohol consumption and cognition in older adults and if it is different across sexes or depends on amyloid-β (Aβ) accumulation in the brain. METHODS: Cognitively unimpaired older adults (N = 4387) with objective and subjective cognitive assessments and amyloid positron emission tomography (PET) imaging were classified into four categories based on their average daily alcohol use. Multivariable linear regression was then used to test the main effects and interactions with sex and Aβ levels. RESULTS: Individuals who reported no alcohol consumption had lower scores on the Preclinical Alzheimer Cognitive Composite (PACC) compared to those consuming one or two drinks/day. In sex-stratified analysis, the association between alcohol consumption and cognition was more prominent in females. Female participants who consumed two drinks/day had better performance on PACC and Cognitive Function Index (CFI) than those who reported no alcohol consumption. In an Aβ-stratified sample, the association between alcohol consumption and cognition was present only in the Aβ- subgroup. The interaction between Aβ status and alcohol consumption on cognition was not significant. CONCLUSION: Low or moderate consumption of alcohol was associated with better objective cognitive performance and better subjective report of daily functioning in cognitively unimpaired individuals. The association was present only in Aβ- individuals, suggesting that the pathophysiologic mechanism underlying the effect of alcohol on cognition is independent of Aβ pathology. Further investigation is required with larger samples consuming three or more drinks/day.

BACE2: A Promising Neuroprotective Candidate for Alzheimer's Disease. - Yeap, Yee Jie; Kandiah, Nagaendran; Nizetic, Dean; Lim, Kah-Leong (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) is the most common cause of dementia that affects millions of predominantly elderly individuals worldwide. Despite intensive research over several decades, controversies still surround the etiology of AD and the disease remains incurable. Meanwhile, new molecular players of the central amyloid cascade hypothesis have emerged and among these is a protease known as β-site APP cleavage enzyme 2 (BACE2). Unlike BACE1, BACE2 cleaves the amyloid-β protein precursor within the Aβ domain that accordingly prevents the generation of Aβ42 peptides, the aggregation of which is commonly regarded as the toxic entity that drives neurodegeneration in AD. Given this non-amyloidogenic role of BACE2, it is attractive to position BACE2 as a therapeutic target for AD. Indeed, several groups including ours have demonstrated a neuroprotective role for BACE2 in AD. In this review, we discuss emerging evidence supporting the ability of BACE2 in mitigating AD-associated pathology in various experimental systems including human pluripotent stem cell-derived cerebral organoid disease models. Alongside this, we also provide an update on the identification of single nucleotide polymorphisms occurring in the BACE2 gene that are linked to increased risk and earlier disease onset in the general population. In particular, we highlight a recently identified point mutation on BACE2 that apparently leads to sporadic early-onset AD. We believe that a better understanding of the role of BACE2 in AD would provide new insights for the development of viable therapeutic strategies for individuals with dementia.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Aspartic Acid Endopeptidases; Humans

Cerebrospinal Fluid Panel of Synaptic Proteins in Cerebral Amyloid Angiopathy and Alzheimer's Disease. - van den Berg, Emma; Nilsson, Johanna; Kersten, Iris; Brinkmalm, Gunnar; de Kort, Anna M; Klijn, Catharina J M; Schreuder, Floris H B M; Jäkel, Lieke; Gobom, Johan; Portelius, Erik; Zetterberg, Henrik; Brinkmalm, Ann; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) and cerebral amyloid angiopathy (CAA) share pathogenic pathways related to amyloid-β deposition. Whereas AD is known to affect synaptic function, such an association for CAA remains yet unknown. OBJECTIVE: We therefore aimed to investigate synaptic dysfunction in CAA. METHODS: Multiple reaction monitoring mass spectrometry was used to quantify cerebrospinal fluid (CSF) concentrations of 15 synaptic proteins in CAA and AD patients, and age- and sex-matched cognitively unimpaired controls. RESULTS: We included 25 patients with CAA, 49 patients with AD, and 25 controls. Only neuronal pentraxin-2 levels were decreased in the CSF of CAA patients compared with controls (p = 0.04). CSF concentrations of 12 other synaptic proteins were all increased in AD compared with CAA or controls (all p≤0.01) and were unchanged between CAA and controls. Synaptic protein concentrations in the subgroup of CAA patients positive for AD biomarkers (CAA/ATN+; n = 6) were similar to AD patients, while levels in CAA/ATN- (n = 19) were comparable with those in controls. A regression model including all synaptic proteins differentiated CAA from AD at high accuracy levels (area under the curve 0.987). CONCLUSION: In contrast to AD, synaptic CSF biomarkers were found to be largely unchanged in CAA. Moreover, concomitant AD pathology in CAA is associated with abnormal synaptic protein levels. Impaired synaptic function in AD was confirmed in this independent cohort. Our findings support an apparent differential involvement of synaptic dysfunction in CAA and AD and may reflect distinct pathological mechanisms.

Cerebrospinal Fluid sTREM-2, GFAP, and β-S100 in Symptomatic Sporadic Alzheimer's Disease: Microglial, Astrocytic, and APOE Contributions Along the Alzheimer's Disease Continuum. - Bonomi, Chiara Giuseppina; Assogna, Martina; Di Donna, Martina Gaia; Bernocchi, Francesca; De Lucia, Vincenzo; Nuccetelli, Marzia; Fiorelli, Denise; Loizzo, Stefano; Mercuri, Nicola Biagio; Koch, Giacomo; Martorana, Alessandro; Motta, Caterina (J Alzheimers Dis, 2023)
BACKGROUND: Many transversal mechanisms act synergistically at different time-points in the cascade of Alzheimer's disease (AD), since amyloid-β (Aβ) deposition, tau pathology, and neuroinflammation influence each other. OBJECTIVE: We explored the contributions of microglia and astrocytes in patients with symptomatic sporadic AD stratified according to AT(N) system and APOE genotype. METHODS: We compared the cerebrospinal fluid (CSF) levels of sTREM-2 and markers of astrocytic activation (GFAP; β-S100) from 71 patients with AD (23 A+T-,48 A+T+; 38 APOEɛ3, 33 APOEɛ4) and 30 healthy controls (HC). With multivariate analyses we investigated associations between glial biomarkers, Aβ42, and p-tau in all subgroups. RESULTS: CSF sTREM-2 was higher in A+T+ [1.437 (0.264)] and A+T- [1.355 (0.213)] than in HC [1.042 (0.198); both p < 0.001]; GFAP and β-S100 were comparable across groups. Considering all patients, sTREM-2 positively associated with Aβ42 (p = 0.04) and p-tau (=0.016), with the first being present only in the A+T- subgroup (p = 0.023). GFAP positively associated with Aβ42 in all patients (p = 0.020) and in the A+T+ subgroup (p = 0.04). Stratifying by APOE, a positive association of sTREM-2 and p-tau was confirmed selectively in carriers of ɛ4 (p = 0.018). Finally, sTREM-2 positively correlated with β-S100 in all subgroups, and with GFAP in A+T+ (p = 0.042). CONCLUSION: Our results confirm the increase of CSF sTREM-2 in AD, which associates with reduced amyloidopathy in A+T- patients. Moreover, microglial activation seems to increase CSF tau levels in carriers of APOEɛ4, is associated with astrocytic reactivity (GFAP) in A+T+, and likely leads the acquisition of a more neurotoxic astrocytic phenotype (β-S100).
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Astrocytes; Biomarkers; Humans; Microglia; Peptide Fragments; tau Proteins

Characterizing Limbic-Predominant Age-Related TDP-43 Encephalopathy Without Alzheimer's Disease and Lewy Body Dementia in the Oldest Old: A Case Series. - Leiby, Anne-Marie C; Scambray, Kiana A; Nguyen, Hannah L; Basith, Farheen; Fakhraee, Shahrzad; Melikyan, Zarui A; Bukhari, Syed A; Montine, Thomas J; Corrada, Maria M; Kawas, Claudia H; Sajjadi, S Ahmad (J Alzheimers Dis, 2023)
BACKGROUND: Limbic-predominant age-related TDP-43 encephalopathy neuropathologic change (LATE-NC) is a clinicopathological construct proposed to facilitate studying TDP-43 pathology in older individuals. OBJECTIVE: Our aim was to describe clinical and cognitive characteristics of LATE-NC without Alzheimer's disease neuropathologic change (ADNC) and Lewy body (LB) and to compare this with ADNC and primary age related tauopathy (PART). METHODS: In 364 autopsies of the oldest old of The 90+ Study, we identified those with LATE-NC without ADNC and LB. Control groups were participants with ADNC and PART. RESULTS: Of 31% of participants who had LATE-NC, only 5 (1.4%) had LATE-NC without ADNC and LB, all of whom had tau. These participants had a gradual and progressive cognitive decline. Four (80%) had dementia at death, a rate that was higher than ADNC (50%) and PART (21.7%). Mean duration of cognitive impairment was twice as long in LATE-NC without ADNC and LB (6.2 years) compared to ADNC (2.9 years) and PART (3 years). LATE-NC without ADNC and LB group had a higher prevalence of syncope, depression, and extrapyramidal signs than the ADNC and PART groups. CONCLUSIONS: Despite the high prevalence of LATE-NC, LATE-NC without ADNC and LB was rare in this large oldest-old cohort, highlighting the very high prevalence of multiple pathologic changes in the oldest old. Slowly progressive cognitive decline, ubiquitous memory impairment, history of syncope and depression, and extrapyramidal signs were prominent features among our LATE-NC without ADNC and LB group.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; DNA-Binding Proteins; Humans; Lewy Body Disease; Syncope; Tauopathies; TDP-43 Proteinopathies

Chronic Sleep Disturbances Alters Sleep Structure and Tau Phosphorylation in AβPP/PS1 AD Mice and Their Wild-Type Littermates. - Zhang, Feng; Niu, Long; Zhong, Rujia; Li, Song; Le, Weidong (J Alzheimers Dis, 2023)
BACKGROUND: Emerging evidence indicates that sleep disorders are the common non-cognitive symptoms of Alzheimer's disease (AD), and they may contribute to the pathogenesis of this disease. OBJECTIVE: In this study, we aim to investigate the effect of chronic sleep deprivation (CSD) on AD-related pathologies with a focus on tau phosphorylation and the underlying DNA methylation regulation. METHODS: AβPPswe/PS1ΔE9 AD mice and their wild-type (WT) littermates were subjected to a two-month CSD followed by electroencephalography and electromyography recording. The mice were examined for learning and memory evaluation, then pathological, biochemical, and epigenetic assessments including western blotting, immunofluorescence, dot blotting, and bisulfite sequencing. RESULTS: The results show that CSD caused sleep disorders shown as sleep pattern change, poor sleep maintenance, and increased sleep fragmentation. CSD increased tau phosphorylation at different sites and increased the level of tau kinases in AD and WT mice. The increased expression of cyclin-dependent kinase 5 (CDK5) may result from decreased DNA methylation of CpG sites in the promoter region of CDK5 gene, which might be associated with the downregulation of DNA methyltransferase 3A and 3B. CONCLUSION: CSD altered AD-related tau phosphorylation through epigenetic modification of tau kinase gene. The findings in this study may give insights into the mechanisms underlying the effects of sleep disorders on AD pathology and provide new therapeutic targets for the treatment of this disease.

Is Dementia Associated with COVID-19 Mortality? A Multicenter Retrospective Cohort Study Conducted in 50 Hospitals in Germany. - Kostev, Karel; Gessler, Nele; Wohlmuth, Peter; Arnold, Dirk; Bein, Berthold; Bohlken, Jens; Herrlinger, Klaus; Jacob, Louis; Koyanagi, Ai; Nowak, Lorenz; Smith, Lee; Wesseler, Claas; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Dementia has been identified as a major predictor of mortality associated with COVID-19. OBJECTIVE: The objective of this study was to investigate the association between dementia and mortality in COVID-19 inpatients in Germany across a longer interval during the pandemic. METHODS: This retrospective study was based on anonymized data from 50 hospitals in Germany and included patients with a confirmed COVID-19 diagnosis hospitalized between March 11, 2020 and July, 20, 2022. The main outcome of the study was the association of mortality during inpatient stays with dementia diagnosis, which was studied using multivariable logistic regression adjusted for age, sex, and comorbidities as well as univariate logistic regression for matched pairs. RESULTS: Of 28,311 patients diagnosed with COVID-19, 11.3% had a diagnosis of dementia. Prior to matching, 26.5% of dementia patients and 11.5% of non-dementia patients died; the difference decreased to 26.5% of dementia versus 21.7% of non-dementia patients within the matched pairs (n = 3,317). This corresponded to an increase in the risk of death associated with dementia (OR = 1.33; 95% CI: 1.16-1.46) in the univariate regression conducted for matched pairs. CONCLUSION: Although dementia was associated with COVID-19 mortality, the association was weaker than in previously published studies. Further studies are needed to better understand whether and how pre-existing neuropsychiatric conditions such as dementia may impact the course and outcome of COVID-19.
Keywords: COVID-19; COVID-19 Testing; Dementia; Germany; Hospitalization; Hospitals; Humans; Mortality; Retrospective Studies

Effect of Metabolic Syndrome Risk Factors on Processing Speed and Executive Function in Three Racialized Groups. - Bouges, Shenikqua; Fischer, Barbara; Norton, Derek L; Wyman, Mary F; Lambrou, Nickolas; Zuelsdorff, Megan; Van Hulle, Carol A; Ennis, Gilda E; James, Taryn T; Johnson, Adrienne L; Chin, Nathaniel; Carlsson, Cynthia M; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Metabolic syndrome (MetS) has been associated with increased risk for Alzheimer's disease and related dementias (ADRD). Understanding the association of MetS risk factors to processing speed and executive function in the pre-clinical stages of ADRD in under-represented groups would offer insight on potential mechanisms through which MetS associates with ADRD risk. OBJECTIVE: Examine association of MetS features and processing speed and executive function across three racial groups. METHODS: Cognitively unimpaired adults from the Wisconsin Alzheimer's Disease Research Center and the Wisconsin Registry for Alzheimer's Disease Prevention completed blood-draws and neuropsychological testing. Six cognitive outcomes were assessed in association to MetS risk factors: Trailmaking Tests A and B, Animal Fluency, Digit Symbol, and composite scores for Processing Speed and Executive Function. Linear mixed effect models were used to assess the relationship between MetS risk factor count and longitudinal cognitive performance across three racialized groups. RESULTS: Participant sample sizes varied by outcome analyzed (N = 714-1,088). African American and Native American groups exhibited higher rates of MetS than non-Hispanic Whites. MetS was associated with processing speed and executive function across all racialized groups. Three-way interaction by racialized group was limited to one cognitive outcome: Trailmaking Test A. CONCLUSION: Metabolic dysfunction incrementally affects cognitive trajectory, with generally similar associations across racial groups. Since racialized groups exhibit higher levels of both MetS and ADRD, MetS may represent a driving factor for increased ADRD risk experience by racialized group and an important and modifiable target through which to reduce risk of ADRD.

Effects of Brain Pathologies on Spatiotemporal Gait Parameters in Patients with Mild Cognitive Impairment. - Lindh-Rengifo, Magnus; Jonasson, Stina B; Ullén, Susann; Palmqvist, Sebastian; van Westen, Danielle; Stomrud, Erik; Mattsson-Carlgren, Niklas; Nilsson, Maria H; Hansson, Oskar (J Alzheimers Dis, 2023)
BACKGROUND: Impaired gait can precede dementia. The associations between gait parameters and brain pathologies are therefore of interest. OBJECTIVE: To explore how different brain pathologies (i.e., vascular and Alzheimer's) are associated with specific gait parameters from various gait components in persons with mild cognitive impairment (MCI), who have an increased risk of developing dementia. METHODS: This cross-sectional study included 96 patients with MCI (mean 72, ±7.5 years; 52% women). Gait was evaluated by using an electronic walkway, GAITRite®. Four gait parameters (step velocity variability; step length; step time; stance time asymmetry) were used as dependent variables in multivariable linear regression analyses. Independent variables included Alzheimer's disease pathologies (amyloid-β and tau) by using PET imaging and white matter hyperintensities (WMH) by using MRI. Covariates included age, sex, comorbidities (and intracranial volume in analyses that includedWMH). RESULTS: Increased tau-PET (Braak I-IV region of interest [ROI]) was associated with step velocity variability (standardized regression coefficient, β= 0.383, p < 0.001) and step length (β= 0.336, p < 0.001), which remained significant when using different Braak ROIs (I-II, III-IV, V-VI). The associations remained significant when adjusting for WMH (p < 0.001). When also controlling for gait speed, tau was no longer significantly (p = 0.168) associated with an increased step length. No significant associations between gait and Aβ-PET load or WMH were identified. CONCLUSIONS: The results indicate that one should pay specific attention to assess step velocity variability when targeting single task gait in patients with MCI. Future studies should address additional gait variability measures and dual tasking in larger cohorts.

Emotional Dysregulation in Mild Behavioral Impairment Is Associated with Reduced Cortical Thickness in the Right Supramarginal Gyrus. - Imai, Ayu; Matsuoka, Teruyuki; Narumoto, Jin (J Alzheimers Dis, 2023)
BACKGROUND: Mild behavioral impairment (MBI) has attracted attention as a possible precursor symptom of dementia, but its neural basis has not been fully investigated. OBJECTIVE: We aimed to investigate the relationship between MBI and surface area, cortical thickness, and volume in the temporal and parietal lobes, which are strongly associated with dementia and emotional disorders. METHODS: This retrospective study evaluated 123 participants: 90 with mild cognitive impairment (MCI), 13 with subjective cognitive decline (SCD), and 20 cognitively healthy (CH). Using analysis of covariance (ANCOVA) with sex, age, and MMSE score as covariates, cortical thickness, surface area, and volume in 10 regions were compared between groups with and without MBI. Groups with MBI emotional dysregulation were also compared with groups without MBI. RESULTS: ANCOVA revealed significantly smaller cortical thickness in the MBI group's right parahippocampal (p = 0.01) and supramarginal gyri (p = 0.002). After multiple comparison correction, only the right supramarginal gyrus was significantly smaller (p = 0.02). When considering only MBI emotional dysregulation, the right parahippocampal and supramarginal gyrus' cortical thicknesses were significantly smaller in this MBI group (p = 0.03, 0.01). However, multiple comparison correction identified no significant differences (p = 0.14, 0.11). CONCLUSION: Overall MBI and the emotional dysregulation domains were associated with reduced cortical thickness in the right parahippocampal and supramarginal gyri. Since neurodegeneration in the medial temporal and parietal lobe precedes early Alzheimer's disease (AD), MBI, particularly emotion dysregulation, may predict early AD below the diagnostic threshold.
Keywords: Alzheimer Disease; Attention; Cognitive Dysfunction; Dementia; Humans; Neuropsychological Tests; Parietal Lobe; Retrospective Studies

Evaluation of Blood-Based Plasma Biomarkers as Potential Markers of Amyloid Burden in Preclinical Alzheimer's Disease. - Winston, Charisse N; Langford, Oliver; Levin, Natalie; Raman, Rema; Yarasheski, Kevin; West, Tim; Abdel-Latif, Sara; Donohue, Michael; Nakamura, Akinori; Toba, Kenji; Masters, Colin L; Doecke, James; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Participant eligibility for the A4 Study was determined by amyloid PET imaging. Given the disadvantages of amyloid PET imaging in accessibility and cost, blood-based biomarkers may serve as a sufficient biomarker and more cost-effective screening tool for patient enrollment into preclinical AD trials. OBJECTIVE: To determine if a blood-based screening test can adequately identify amyloid burden in participants screened into a preclinical AD trial. METHODS: In this cross-sectional study, 224 participants from the A4 Study received an amyloid PET scan (18Florbetapir) within 90 days of blood sample collection. Blood samples from all study participants were processed within 2 h after phlebotomy. Plasma amyloid measures were quantified by Shimazdu and C2 N Diagnostics using mass spectrometry-based platforms. A corresponding subset of blood samples (n = 100) was processed within 24 h after phlebotomy and analyzed by C2 N. RESULTS: Plasma Aβ42/Aβ40 demonstrated the highest association for Aβ accumulation in the brain with an AUC 0.76 (95%CI = 0.69, 0.82) at C2 N and 0.80 (95%CI = 0.75, 0.86) at Shimadzu. Blood samples processed to plasma within 2 h after phlebotomy provided a better prediction of amyloid PET status than blood samples processed within 24 h (AUC 0.80 versus 0.64; p < 0.001). Age, sex, and APOE ɛ4 carrier status did not the diagnostic performance of plasma Aβ42/Aβ40 to predict amyloid PET positivity in A4 Study participants. CONCLUSION: Plasma Aβ42/Aβ40 may serve as a potential biomarker for predicting elevated amyloid in the brain. Utilizing blood testing over PET imaging may improve screening efficiency into clinical trials.
Keywords: Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidogenic Proteins; Biomarkers; Cross-Sectional Studies; Humans; Peptide Fragments; Positron-Emission Tomography

Exercise-Related Physical Activity Relates to Brain Volumes in 10,125 Individuals. - Raji, Cyrus A; Meysami, Somayeh; Hashemi, Sam; Garg, Saurabh; Akbari, Nasrin; Ahmed, Gouda; Chodakiewitz, Yosef Gavriel; Nguyen, Thanh Duc; Niotis, Kellyann; Merrill, David A; Attariwala, Rajpaul (J Alzheimers Dis, 2023)
BACKGROUND: The potential neuroprotective effects of regular physical activity on brain structure are unclear, despite links between activity and reduced dementia risk. OBJECTIVE: To investigate the relationships between regular moderate to vigorous physical activity and quantified brain volumes on magnetic resonance neuroimaging. METHODS: A total of 10,125 healthy participants underwent whole-body MRI scans, with brain sequences including isotropic MP-RAGE. Three deep learning models analyzed axial, sagittal, and coronal views from the scans. Moderate to vigorous physical activity, defined by activities increasing respiration and pulse rate for at least 10 continuous minutes, was modeled with brain volumes via partial correlations. Analyses adjusted for age, sex, and total intracranial volume, and a 5% Benjamini-Hochberg False Discovery Rate addressed multiple comparisons. RESULTS: Participant average age was 52.98±13.04 years (range 18-97) and 52.3% were biologically male. Of these, 7,606 (75.1%) reported engaging in moderate or vigorous physical activity approximately 4.05±3.43 days per week. Those with vigorous activity were slightly younger (p < 0.00001), and fewer women compared to men engaged in such activities (p = 3.76e-15). Adjusting for age, sex, body mass index, and multiple comparisons, increased days of moderate to vigorous activity correlated with larger normalized brain volumes in multiple regions including: total gray matter (Partial R = 0.05, p = 1.22e-7), white matter (Partial R = 0.06, p = 9.34e-11), hippocampus (Partial R = 0.05, p = 5.96e-7), and frontal, parietal, and occipital lobes (Partial R = 0.04, p≤1.06e-5). CONCLUSIONS: Exercise-related physical activity is associated with increased brain volumes, indicating potential neuroprotective effects.

Exposure to World Trade Center Dust Exacerbates Cognitive Impairment and Evokes a Central and Peripheral Pro-Inflammatory Transcriptional Profile in an Animal Model of Alzheimer's Disease. - Iban-Arias, Ruth; Trageser, Kyle J; Yang, Eun-Jeong; Griggs, Elizabeth; Radu, Aurelian; Naughton, Sean; Al Rahim, Md; Tatsunori, Oguchi; Raval, Urdhva; Palmieri, Joshua; Huang, Zerlina; Chen, Lung-Chi; et al. (J Alzheimers Dis, 2023)
BACKGROUND: The terrorist attacks on September 11, 2001, on the World Trade Center (WTC) led to intense fires and a massive dense cloud of toxic gases and suspended pulverized debris. In the subsequent years, following the attack and cleanup efforts, a cluster of chronic health conditions emerged among First Responders (FR) who were at Ground Zero for prolonged periods and were repeatedly exposed to high levels of WTC particulate matter (WTCPM). Among those are neurological complications which may increase the risk for the development of Alzheimer's disease (AD) later in life. OBJECTIVE: We hypothesize that WTCPM dust exposure affects the immune cross-talking between the periphery and central nervous systems that may induce brain permeability ultimately promoting AD-type phenotype. METHODS: 5XFAD and wild-type mice were intranasally administered with WTCPM dust collected at Ground Zero within 72 h after the attacks. Y-maze assay and novel object recognition behavioral tests were performed for working memory deficits and learning and recognition memory, respectively. Transcriptomic analysis in the blood and hippocampus was performed and confirmed by RT qPCR. RESULTS: Mice exposed to WTCPM dust exhibited a significant impairment in spatial and recognition short and long-term memory. Furthermore, the transcriptomic analysis in the hippocampal formation and blood revealed significant changes in genes related to immune-inflammatory responses, and blood-brain barrier disruption. CONCLUSION: These studies suggest a putative peripheral-brain immune inflammatory cross-talking that may potentiate cognitive decline, identifying for the first time key steps which may be therapeutically targetable in future studies in WTC FR.
Keywords: Alzheimer Disease; Animals; Cognitive Dysfunction; Dust; Mice; Models, Animal; September 11 Terrorist Attacks

Impact of Computerized Cognitive Training on Default Mode Network Connectivity in Subjects at Risk for Alzheimer's Disease: A 78-week Randomized Controlled Trial. - Petrella, Jeffrey R; Michael, Andrew M; Qian, Min; Nwosu, Adaora; Sneed, Joel; Goldberg, Terry E; Devanand, Davangere P; Doraiswamy, P Murali (J Alzheimers Dis, 2023)
BACKGROUND: Mild cognitive impairment (MCI) represents a high risk group for Alzheimer's disease (AD). Computerized Cognitive Games Training (CCT) is an investigational strategy to improve targeted functions in MCI through the modulation of cognitive networks. OBJECTIVE: The goal of this study was to examine the effect of CCT versus a non-targeted active brain exercise on functional cognitive networks. METHODS: 107 patients with MCI were randomized to CCT or web-based crossword puzzles. Resting-state functional MRI (fMRI) was obtained at baseline and 18 months to evaluate differences in fMRI measured within- and between-network functional connectivity (FC) of the default mode network (DMN) and other large-scale brain networks: the executive control, salience, and sensorimotor networks. RESULTS: There were no differences between crosswords and games in the primary outcome, within-network DMN FC across all subjects. However, secondary analyses suggest differential effects on between-network connectivity involving the DMN and SLN, and within-network connectivity of the DMN in subjects with late MCI. Paradoxically, in both cases, there was a decrease in FC for games and an increase for the crosswords control (p < 0.05), accompanied by lesser cognitive decline in the crosswords group. CONCLUSION: Results do not support a differential impact on within-network DMN FC between games and crossword puzzle interventions. However, crossword puzzles might result in cognitively beneficial remodeling between the DMN and other networks in more severely impaired MCI subjects, parallel to the observed clinical benefits.
Keywords: Alzheimer Disease; Brain; Cognitive Dysfunction; Cognitive Training; Default Mode Network; Humans; Magnetic Resonance Imaging; Nerve Net

Impact of Yoga Versus Memory Enhancement Training on Hippocampal Connectivity in Older Women at Risk for Alzheimer's Disease. - Kilpatrick, Lisa A; Siddarth, Prabha; Krause-Sorio, Beatrix; Milillo, Michaela M; Aguilar-Faustino, Yesenia; Ercoli, Linda; Narr, Katherine L; Khalsa, Dharma S; Lavretsky, Helen (J Alzheimers Dis, 2023)
BACKGROUND: Yoga may be an ideal early intervention for those with modifiable risk factors for Alzheimer's disease (AD) development. OBJECTIVE: To examine the effects of Kundalini yoga (KY) training versus memory enhancement training (MET) on the resting-state connectivity of hippocampal subregions in women with subjective memory decline and cardiovascular risk factors for AD. METHODS: Participants comprised women with subjective memory decline and cardiovascular risk factors who participated in a parent randomized controlled trial (NCT03503669) of 12-weeks of KY versus MET and completed pre- and post-intervention resting-state magnetic resonance imaging scans (yoga: n = 11, age = 61.45±6.58 years; MET: n = 11, age = 64.55±6.41 years). Group differences in parcellated (Cole-anticevic atlas) hippocampal connectivity changes (post- minus pre-intervention) were evaluated by partial least squares analysis, controlling for age. Correlations between hippocampal connectivity and perceived stress and frequency of forgetting (assessed by questionnaires) were also evaluated. RESULTS: A left anterior hippocampal subregion assigned to the default mode network (DMN) in the Cole-anticevic atlas showed greater increases in connectivity with largely ventral visual stream regions with KY than with MET (p < 0.001), which showed associations with lower stress (p < 0.05). Several posterior hippocampal subregions assigned to sensory-based networks in the Cole-anticevic atlas showed greater increases in connectivity with regions largely in the DMN and frontoparietal network with MET than with KY (p < 0.001), which showed associations with lower frequency of forgetting (p < 0.05). CONCLUSION: KY training may better target stress-related hippocampal connectivity, whereas MET may better target hippocampal sensory-integration supporting better memory reliability, in women with subjective memory decline and cardiovascular risk factors.

Medial Temporal Lobe Atrophy in Predementia Alzheimer's Disease: A Longitudinal Multi-Site Study Comparing Staging and A/T/N in a Clinical Research Cohort. - Jarholm, Jonas Alexander; Bjørnerud, Atle; Dalaker, Turi Olene; Akhavi, Mehdi Sadat; Kirsebom, Bjørn Eivind; Pålhaugen, Lene; Nordengen, Kaja; Grøntvedt, Gøril Rolfseng; Nakling, Arne; Kalheim, Lisa F; Almdahl, Ina S; Tecelao, Sandra; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Atrophy of the medial temporal lobe (MTL) is a biological characteristic of Alzheimer's disease (AD) and can be measured by segmentation of magnetic resonance images (MRI). OBJECTIVE: To assess the clinical utility of automated volumetry in a cognitively well-defined and biomarker-classified multi-center longitudinal predementia cohort. METHODS: We used Automatic Segmentation of Hippocampal Subfields (ASHS) to determine MTL morphometry from MRI. We harmonized scanner effects using the recently developed longitudinal ComBat. Subjects were classified according to the A/T/N system, and as normal controls (NC), subjective cognitive decline (SCD), or mild cognitive impairment (MCI). Positive or negative values of A, T, and N were determined by cerebrospinal fluid measurements of the Aβ42/40 ratio, phosphorylated and total tau. From 406 included subjects, longitudinal data was available for 206 subjects by stage, and 212 subjects by A/T/N. RESULTS: Compared to A-/T-/N- at baseline, the entorhinal cortex, anterior and posterior hippocampus were smaller in A+/T+orN+. Compared to NC A- at baseline, these subregions were also smaller in MCI A+. Longitudinally, SCD A+ and MCI A+, and A+/T-/N- and A+/T+orN+, had significantly greater atrophy compared to controls in both anterior and posterior hippocampus. In the entorhinal and parahippocampal cortices, longitudinal atrophy was observed only in MCI A+ compared to NC A-, and in A+/T-/N- and A+/T+orN+ compared to A-/T-/N-. CONCLUSION: We found MTL neurodegeneration largely consistent with existing models, suggesting that harmonized MRI volumetry may be used under conditions that are common in clinical multi-center cohorts.
Keywords: Alzheimer Disease; Atrophy; Cognitive Dysfunction; Entorhinal Cortex; Hippocampus; Humans; Magnetic Resonance Imaging; Temporal Lobe

Mediation of Reduced Hippocampal Volume by Cerebral Amyloid Angiopathy in Pathologically Confirmed Patients with Alzheimer's Disease. - Nagaraja, Nandakumar; Wang, Wei-En; Duara, Ranjan; DeKosky, Steven T; Vaillancourt, David (J Alzheimers Dis, 2023)
BACKGROUND: Hippocampal atrophy in cerebral amyloid angiopathy (CAA) has been reported to be similar to that in Alzheimer's disease (AD). OBJECTIVE: To evaluate if CAA pathology partly mediates reduced hippocampal volume in patients with AD. METHODS: Patients with a clinical diagnosis of AD and neuropathological confirmation of AD+/-CAA in the National Alzheimer's Coordinating Center database were included in the study. The volumes of temporal lobe structures were calculated on T1-weighted imaging (T1-MRI) using automated FreeSurfer software, from images acquired on average 5 years prior to death. Multivariate regression analysis was performed to compare brain volumes in four CAA groups. The hippocampal volume on T1-MRI was correlated with Clinical Dementia Rating sum of boxes (CDRsb) score, apolipoprotein E (APOE) genotype, and hippocampal atrophy at autopsy. RESULTS: The study included 231 patients with no (n = 45), mild (n = 70), moderate (n = 67), and severe (n = 49) CAA. Among the four CAA groups, patients with severe CAA had a smaller mean left hippocampal volume (p = 0.023) but this was not significant when adjusted for APOE ɛ4 (p = 0.07). The left hippocampal volume on MRI correlated significantly with the hippocampal atrophy grading on neuropathology (p = 0.0003). Among patients with severe CAA, the left hippocampal volume on T1-MRI: (a) decreased with an increase in the number of APOE ɛ4 alleles (p = 0.04); but (b) had no evidence of correlation with CDRsb score (p = 0.57). CONCLUSION: Severe CAA was associated with smaller left hippocampal volume on T1-MRI up to five years prior to death among patients with neuropathologically confirmed AD. This relationship was dependent on APOE ɛ4 genotype.

Mitochondria Profoundly Influence Apolipoprotein E Biology. - Gabrielli, Alexander P; Weidling, Ian; Ranjan, Amol; Wang, Xiaowan; Novikova, Lesya; Chowdhury, Subir Roy; Menta, Blaise; Berkowicz, Alexandra; Wilkins, Heather M; Peterson, Kenneth R; Swerdlow, Russell H (J Alzheimers Dis, 2023)
BACKGROUND: Mitochondria can trigger Alzheimer's disease (AD)-associated molecular phenomena, but how mitochondria impact apolipoprotein E (APOE; apoE) is not well known. OBJECTIVE: Consider whether and how mitochondrial biology influences APOE and apoE biology. METHODS: We measured APOE expression in human SH-SY5Y neuronal cells with different forms of mitochondrial dysfunction including total, chronic mitochondrial DNA (mtDNA) depletion (ρ0 cells); acute, partial mtDNA depletion; and toxin-induced mitochondrial dysfunction. We further assessed intracellular and secreted apoE protein levels in the ρ0 cells and interrogated the impact of transcription factors and stress signaling pathways known to influence APOE expression. RESULTS: SH-SY5Y ρ0 cells exhibited a 65-fold increase in APOE mRNA, an 8-fold increase in secreted apoE protein, and increased intracellular apoE protein. Other models of primary mitochondrial dysfunction including partial mtDNA-depletion, toxin-induced respiratory chain inhibition, and chemical-induced manipulations of the mitochondrial membrane potential similarly increased SH-SY5Y cell APOE mRNA. We explored potential mediators and found in the ρ0 cells knock-down of the C/EBPα and NFE2L2 (Nrf2) transcription factors reduced APOE mRNA. The activity of two mitogen-activated protein kinases, JNK and ERK, also strongly influenced ρ0 cell APOE mRNA levels. CONCLUSION: Primary mitochondrial dysfunction either directly or indirectly activates APOE expression in a neuronal cell model by altering transcription factors and stress signaling pathways. These studies demonstrate mitochondrial biology can influence the biology of the APOE gene and apoE protein, which are implicated in AD.
Keywords: Alzheimer Disease; Apolipoproteins E; Biology; Cell Line, Tumor; DNA, Mitochondrial; Humans; Mitochondria; Neuroblastoma; RNA, Messenger; Transcription Factors

Mortality Risks and Causes of Death by Dementia Types in a Japanese Cohort with Dementia: NCGG-STORIES. - Ono, Rei; Sakurai, Takashi; Sugimoto, Taiki; Uchida, Kazuaki; Nakagawa, Takeshi; Noguchi, Taiji; Komatsu, Ayane; Arai, Hidenori; Saito, Tami (J Alzheimers Dis, 2023)
BACKGROUND: Prognosis-related information regarding dementia needs to be updated, as changes in medical and long-term care environments for patients with dementia in recent decades may be improving the prognosis of the disease. OBJECTIVE: We aimed to investigate the mortality, cause of death, and prognostic factors by types of dementia in a Japanese clinic-based cohort. METHODS: The National Center for Geriatrics and Gerontology-Life Stories of People with Dementia consists of clinical records and prognostic data of patients who visited the Memory Clinic in Japan. Patients who attended the clinic between July 2010 and September 2018, or their close relatives, were asked about death information via a postal survey. A cohort of 3,229 patients (mean age, 76.9; female, 1,953) was classified into six groups: normal cognition (NC), mild cognitive impairment (MCI), Alzheimer's disease (AD), vascular dementia, dementia with Lewy bodies (DLB), and frontotemporal lobar degeneration. A Cox proportional hazards model was employed to compare the mortality of each type of dementia, MCI, and NC. RESULTS: Patients with all types of dementia and MCI had higher mortality rates than those with NC (hazard risks: 2.61-5.20). The most common cause of death was pneumonia, followed by cancer. In the MCI, AD, and DLB groups, older age, male sex, and low cognitive function were common prognostic factors but not presence of apolipoprotein E ɛ4 allele. CONCLUSION: Our findings suggest important differences in the mortality risk and cause of death among patients with dementia, which will be useful in advanced care planning and policymaking.
Keywords: Aged; Alzheimer Disease; Cause of Death; Cognitive Dysfunction; Dementia; East Asian People; Female; Humans; Lewy Body Disease; Male

Neuroprotective Properties of Eudesmin on a Cellular Model of Amyloid-β Peptide Toxicity. - Castillo, Carolina; Bravo-Arrepol, Gastón; Wendt, Aline; Saez-Orellana, Francisco; Millar, Camila; Burgos, Carlos F; Gavilán, Javiera; Pacheco, Carla; Ahumada-Rudolph, Ramón; Napiórkowska, Mariola; Pérez, Claudia; Becerra, José; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by progressive cognitive impairment and memory loss. One of the hallmarks in AD is amyloid-β peptide (Aβ) accumulation, where the soluble oligomers of Aβ (AβOs) are the most toxic species, deteriorating the synaptic function, membrane integrity, and neuronal structures, which ultimately lead to apoptosis. Currently, there are no drugs to arrest AD progression, and current scientific efforts are focused on searching for novel leads to control this disease. Lignans are compounds extracted from conifers and have several medicinal properties. Eudesmin (Eu) is an extractable lignan from the wood of Araucaria araucana, a native tree from Chile. This metabolite has shown a range of biological properties, including the ability to control inflammation and antibacterial effects. OBJECTIVE: In this study, the neuroprotective abilities of Eu on synaptic failure induced by AβOs were analyzed. METHODS: Using neuronal models, PC12 cells, and in silico simulations we evaluated the neuroprotective effect of Eu (30 nM) against the toxicity induced by AβOs. RESULTS: In primary cultures from mouse hippocampus, Eu preserved the synaptic structure against AβOs toxicity, maintaining stable levels of the presynaptic protein SV2 at the same concentration. Eu also averted synapsis failure from the AβOs toxicity by sustaining the frequencies of cytosolic Ca2+ transients. Finally, we found that Eu (30 nM) interacts with the Aβ aggregation process inducing a decrease in AβOs toxicity, suggesting an alternative mechanism to explain the neuroprotective activity of Eu. CONCLUSION: We believe that Eu represents a novel lead that reduces the Aβ toxicity, opening new research venues for lignans as neuroprotective agents.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Lignans; Mice; Neuroprotective Agents; PC12 Cells; Rats

Pathological and Therapeutic Advances in Parkinson's Disease: Mitochondria in the Interplay. - Naren, Padmashri; Cholkar, Anjali; Kamble, Suchita; Khan, Sabiya Samim; Srivastava, Saurabh; Madan, Jitender; Mehra, Neelesh; Tiwari, Vinod; Singh, Shashi Bala; Khatri, Dharmendra Kumar (J Alzheimers Dis, 2023)
Parkinson's disease (PD) is the second most common neurodegenerative illness majorly affecting the population between the ages of 55 to 65 years. Progressive dopaminergic neuronal loss and the collective assemblage of misfolded alpha-synuclein in the substantia nigra, remain notable neuro-pathological hallmarks of the disease. Multitudes of mechanistic pathways have been proposed in attempts to unravel the pathogenesis of PD but still, it remains elusive. The convergence of PD pathology is found in organelle dysfunction where mitochondria remain a major contributor. Mitochondrial processes like bioenergetics, mitochondrial dynamics, and mitophagy are under strict regulation by the mitochondrial genome and nuclear genome. These processes aggravate neurodegenerative activities upon alteration through neuroinflammation, oxidative damage, apoptosis, and proteostatic stress. Therefore, the mitochondria have grabbed a central position in the patho-mechanistic exploration of neurodegenerative diseases like PD. The management of PD remains a challenge to physicians to date, due to the variable therapeutic response of patients and the limitation of conventional chemical agents which only offer symptomatic relief with minimal to no disease-modifying effect. This review describes the patho-mechanistic pathways involved in PD not only limited to protein dyshomeostasis and oxidative stress, but explicit attention has been drawn to exploring mechanisms like organelle dysfunction, primarily mitochondria and mitochondrial genome influence, while delineating the newer exploratory targets such as GBA1, GLP, LRRK2, and miRNAs and therapeutic agents targeting them.
Keywords: Aged; alpha-Synuclein; Humans; Mitochondria; Oxidative Stress; Parkinson Disease

Plasma ApoE4 Levels Are Lower than ApoE2 and ApoE3 Levels, and Not Associated with Plasma Aβ 40/42 Ratio as a Biomarker of Amyloid-β Amyloidosis in Alzheimer's Disease. - Nakamura, Takumi; Kawarabayashi, Takeshi; Ueda, Tetsuya; Shimomura, Sachiko; Hoshino, Masaki; Itoh, Ken; Ihara, Kazushige; Nakaji, Shigeyuki; Takatama, Masamitsu; Ikeda, Yoshio; Shoji, Mikio (J Alzheimers Dis, 2023)
BACKGROUND: APOE4 is the strongest risk factor for Alzheimer's disease (AD). However, limited information is currently available on APOE4 and the pathological role of plasma apolipoprotein E (ApoE) 4 remains unclear. OBJECTIVE: The aims of the present study were to measure plasma levels of total ApoE (tE), ApoE2, ApoE3, and ApoE4 using mass spectrometry and elucidate the relationships between plasma ApoE and blood test items. METHODS: We herein examined plasma levels of tE, ApoE2, ApoE3, and ApoE4 in 498 subjects using liquid chromatograph-mass spectrometry (LC-MS/MS). RESULTS: Among 498 subjects, mean age was 60 years and 309 were female. tE levels were distributed as ApoE2/E3 = ApoE2/E4 >ApoE3/E3 = ApoE3/E4 >ApoE4/E4. In the heterozygous group, ApoE isoform levels were distributed as ApoE2 >ApoE3 >ApoE4. ApoE levels were not associated with aging, the plasma amyloid-β (Aβ) 40/42 ratio, or the clinical diagnosis of AD. Total cholesterol levels correlated with the level of each ApoE isoform. ApoE2 levels were associated with renal function, ApoE3 levels with low-density lipoprotein cholesterol and liver function, and ApoE4 levels with triglycerides, high-density lipoprotein cholesterol, body weight, erythropoiesis, and insulin metabolism. CONCLUSION: The present results suggest the potential of LC-MS/MS for the phenotyping and quantitation of plasma ApoE. Plasma ApoE levels are regulated in the order of ApoE2 >ApoE3 >ApoE4 and are associated with lipids and multiple metabolic pathways, but not directly with aging or AD biomarkers. The present results provide insights into the multiple pathways by which peripheral ApoE4 influences the progression of AD and atherosclerosis.

Plasma Soluble ST2 Levels Are Higher in Neurodegenerative Disorders and Associated with Poorer Cognition. - Tan, Yi Jayne; Siow, Isabel; Saffari, Seyed Ehsan; Ting, Simon K S; Li, Zeng; Kandiah, Nagaendran; Tan, Louis C S; Tan, Eng King; Ng, Adeline S L (J Alzheimers Dis, 2023)
BACKGROUND: Suppressor of tumorgenicity 2 (ST2) is highly expressed in brain tissue and is a receptor for interleukin 33 (IL-33). ST2 exists in two forms, a transmembrane receptor (ST2L) and a soluble decoy receptor (sST2). IL-33 binds to ST2L, triggering downstream signaling pathways involved in amyloid plaque clearance. Conversely, sST2 binds competitively to IL-33, attenuating its neuroprotective effects. High sST2 levels have been reported in mild cognitive impairment (MCI) and Alzheimer's disease (AD), suggesting that the IL-33/ST2 signaling pathway may be implicated in neurodegenerative diseases. OBJECTIVE: To investigate plasma sST2 levels in controls and patients with MCI, AD, frontotemporal dementia (FTD), and Parkinson's disease (PD). METHODS: Plasma sST2 levels were measured using ELISA in 397 subjects (91 HC, 46 MCI, 38 AD, 28 FTD, and 194 PD). Cerebrospinal fluid (CSF) levels of sST2 were measured in 22 subjects. Relationship between sST2 and clinical outcomes were analyzed. RESULTS: Plasma sST2 levels were increased across all disease groups compared to controls, with highest levels seen in FTD followed by AD and PD. Dementia patients with higher sST2 had lower cross-sectional cognitive scores in Frontal Assessment Battery and Digit Span Backward. At baseline, PD-MCI patients had higher sST2, associated with worse attention. In the longitudinal PD cohort, higher sST2 significantly associated with decline in global cognition and visuospatial domains. Plasma sST2 levels correlated with CSF sST2 levels. CONCLUSION: Plasma sST2 is raised across neurodegenerative diseases and is associated with poorer cognition. Higher baseline sST2 is a potential biomarker of disease severity in neurodegeneration.
Keywords: Alzheimer Disease; Biomarkers; Cognition; Cross-Sectional Studies; Frontotemporal Dementia; Humans; Interleukin-1 Receptor-Like 1 Protein; Interleukin-33; Parkinson Disease

PM2.5 and Dementia in a Low Exposure Setting: The Influence of Odor Identification Ability and APOE. - Andersson, John; Sundström, Anna; Nordin, Maria; Segersson, David; Forsberg, Bertil; Adolfsson, Rolf; Oudin, Anna (J Alzheimers Dis, 2023)
BACKGROUND: Growing evidence show that long term exposure to air pollution increases the risk of dementia. OBJECTIVE: The aim of this study was to investigate associations between PM2.5 exposure and dementia in a low exposure area, and to investigate the role of olfaction and the APOE ɛ4 allele in these associations. METHODS: Data were drawn from the Betula project, a longitudinal study on aging, memory, and dementia in Sweden. Odor identification ability was assessed using the Scandinavian Odor Identification Test (SOIT). Annual mean PM2.5 concentrations were obtained from a dispersion-model and matched at the participants' residential address. Proportional hazard regression was used to calculate hazard ratios. RESULTS: Of 1,846 participants, 348 developed dementia during the 21-year follow-up period. The average annual mean PM2.5 exposure at baseline was 6.77μg/m3, which is 1.77μg/m3 above the WHO definition of clean air. In a fully adjusted model (adjusted for age, sex, APOE, SOIT, cardiovascular diseases and risk factors, and education) each 1μg/m3 difference in annual mean PM2.5-concentration was associated with a hazard ratio of 1.23 for dementia (95% CI: 1.01-1.50). Analyses stratified by APOE status (ɛ4 carriers versus non-carriers), and odor identification ability (high versus low), showed associations only for ɛ4 carriers, and for low performance on odor identification ability. CONCLUSION: PM2.5 was associated with an increased risk of dementia in this low pollution setting. The associations between PM2.5 and dementia seemed stronger in APOE carriers and those with below average odor identification ability.
Keywords: Air Pollutants; Air Pollution; Apolipoproteins E; Cohort Studies; Dementia; Environmental Exposure; Humans; Longitudinal Studies; Odorants; Particulate Matter

The Potential Role of Selection Bias in the Association Between Coronary Atherosclerosis and Cognitive Impairment. - Yahagi-Estevam, Maristella; Farias-Itao, Daniela Souza; Leite, Renata Elaine Paraizo; Rodriguez, Roberta Diehl; Pasqualucci, Carlos Augusto; Nitrini, Ricardo; Jacob-Filho, Wilson; Power, Melinda C; Suemoto, Claudia Kimie (J Alzheimers Dis, 2023)
BACKGROUND: Coronary atherosclerosis assessed in vivo was associated with cognitive impairment; however, conflicting findings have been reported in autopsy samples. OBJECTIVE: Our aims were to assess the association between atherosclerotic stenosis in the coronary arteries and cognitive impairment and to investigate the possibility of selection bias in an autopsy study. METHODS: Coronary arteries were collected, and the largest luminal stenosis was measured. Sociodemographic, clinical, and cognitive information were reported by a reliable next-of-kin. The association was tested using logistic and linear regressions adjusted for sociodemographic and clinical variables. We restricted the sample to individuals that were born in 1935 or earlier and stratified the analysis by cause of death to investigate the role of selection bias. RESULTS: In 253 participants (mean age = 78.0±8.5 years old, 48% male), stenosis was not associated with cognitive impairment (OR = 0.85, 95% CI = 0.69; 1.06, p = 0.15). In individuals who were born before 1936 in the absence of cardiovascular disease as the cause of death, greater stenosis was associated with cognitive impairment (OR = 4.02, 95% CI = 1.39; 11.6, p = 0.01). On the other hand, this association was not present among those born in 1935 or earlier who died of cardiovascular diseases (OR = 0.83, 95% CI = 0.60; 1.16, p = 0.28). CONCLUSION: We found that higher coronary stenosis was associated with cognitive impairment only in individuals born in 1935 or earlier and who had not died from cardiovascular diseases. Selection bias may be an important issue when investigating risk factors for chronic degenerative diseases in older individuals using autopsy samples.

Re-Addressing Dementia by Network Medicine and Mechanism-Based Molecular Endotypes. - Pacheco Pachado, Mayra; Casas, Ana I; Elbatreek, Mahmoud H; Nogales, Cristian; Guney, Emre; Espay, Alberto J; Schmidt, Harald H H W (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) and other forms of dementia are together a leading cause of disability and death in the aging global population, imposing a high personal, societal, and economic burden. They are also among the most prominent examples of failed drug developments. Indeed, after more than 40 AD trials of anti-amyloid interventions, reduction of amyloid-β (Aβ) has never translated into clinically relevant benefits, and in several cases yielded harm. The fundamental problem is the century-old, brain-centric phenotype-based definitions of diseases that ignore causal mechanisms and comorbidities. In this hypothesis article, we discuss how such current outdated nosology of dementia is a key roadblock to precision medicine and articulate how Network Medicine enables the substitution of clinicopathologic phenotypes with molecular endotypes and propose a new framework to achieve precision and curative medicine for patients with neurodegenerative disorders.
Keywords: Aging; Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Brain; Humans

Safety, Feasibility, and Potential Clinical Efficacy of 40 Hz Invisible Spectral Flicker versus Placebo in Patients with Mild-to-Moderate Alzheimer's Disease: A Randomized, Placebo-Controlled, Double-Blinded, Pilot Study. - Agger, Mikkel Pejstrup; Danielsen, Else Rubæk; Carstensen, Marcus Schultz; Nguyen, N Mai; Horning, Maibritt; Henney, Mark Alexander; Jensen, Christopher Boe Ravn; Baandrup, Anders Ohlhues; Kjær, Troels Wesenberg; Madsen, Kristoffer Hougaard; Miskowiak, Kamilla; Petersen, Paul Michael; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Recent studies suggested induction of 40 Hz neural activity as a potential treatment for Alzheimer's disease (AD). However, prolonged exposure to flickering light raises adherence and safety concerns, encouraging investigation of tolerable light stimulation protocols. OBJECTIVE: To investigate the safety, feasibility, and exploratory measures of efficacy. METHODS: This two-stage randomized placebo-controlled double-blinded clinical trial, recruited first cognitive healthy participants (n = 3/2 active/placebo), and subsequently patients with mild-to-moderate AD (n = 5/6, active/placebo). Participants were randomized 1:1 to receive either active intervention with 40 Hz Invisible Spectral Flicker (ISF) or placebo intervention with color and intensity matched non-flickering white light. RESULTS: Few and mild adverse events were observed. Adherence was above 86.1% of intended treatment days, with participants remaining in front of the device for >51.3 min (60 max) and directed gaze >34.9 min. Secondary outcomes of cognition indicate a tendency towards improvement in the active group compared to placebo (mean: -2.6/1.5, SD: 6.58/6.53, active/placebo) at week 6. Changes in hippocampal and ventricular volume also showed no tendency of improvement in the active group at week 6 compared to placebo. At week 12, a potential delayed effect of the intervention was seen on the volume of the hippocampus in the active group compared to placebo (mean: 0.34/-2.03, SD: 3.26/1.18, active/placebo), and the ventricular volume active group (mean: -0.36/2.50, SD: 1.89/2.05, active/placebo), compared to placebo. CONCLUSION: Treatment with 40 Hz ISF offers no significant safety or adherence concerns. Potential impact on secondary outcomes must be tested in larger scale clinical trials.
Keywords: Alzheimer Disease; Cognition; Double-Blind Method; Feasibility Studies; Humans; Pilot Projects; Treatment Outcome

Senescent Microglia Represent a Subset of Disease-Associated Microglia in P301S Mice. - Ng, Pei Y; Zhang, Cheng; Li, Hu; Baker, Darren J (J Alzheimers Dis, 2023)
BACKGROUND: The existence and contribution of microglia with senescent-like alterations in the pathogenesis of age-related neurodegenerative diseases like Alzheimer's disease (AD) have been suggested in recent years. However, the identification of this distinct microglial population in vivo has proven challenging, largely due to overlaps in the inflammatory phenotype of activated and senescent microglia. Furthermore, attempts at recapitulating senescence in microglia in vitro are limited. OBJECTIVE: To identify and characterize senescent microglia that occur in vivo in an animal model of neurodegeneration driven by pathologic tau. METHODS: We analyzed the RNA expression patterns of individual microglia from normal mice and the pathogenic tau P301 S PS19 mouse model. We have previously demonstrated that p16-expressing senescent microglia occur in these mice when neurodegeneration has occurred. RESULTS: Here we identify a subset of disease-associated microglia with senescent features, notably characterized by the expression of Ccl4. This signature overlaps with established markers of senescence from other cell types. CONCLUSION: Our characterization of senescent microglia can be used to better understand the role of senescent microglia in various age-related contexts, including whether clearance of senescent microglia represents a viable therapeutic option.

Serotonin Degeneration and Amyloid-β Deposition in Mild Cognitive Impairment: Relationship to Cognitive Deficits. - Smith, Gwenn S; Kuwabara, Hiroto; Yan, Haijuan; Nassery, Najlla; Yoon, Mark; Kamath, Vidya; Kraut, Michael; Gould, Neda F; Savonenko, Alena; Coughlin, Jennifer M; Lodge, Martin; Pomper, Martin G; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Neuropathological and neuroimaging studies have demonstrated degeneration of the serotonin system in Alzheimer's disease (AD). Neuroimaging studies have extended these observations to the preclinical stages of AD, mild cognitive impairment (MCI). Serotonin degeneration has been observed also in transgenic amyloid mouse models, prior to widespread cortical distribution of amyloid-β (Aβ). OBJECTIVE: The present study evaluated the regional distribution of the serotonin transporter (5-HTT) and of Aβ in individuals with MCI and healthy older controls, as well as the contribution of 5-HTT and Aβ to cognitive deficits. METHODS: Forty-nine MCI participants and 45 healthy older controls underwent positron emission tomography (PET) imaging of 5-HTT and Aβ, structural magnetic resonance imaging and neuropsychological assessments. RESULTS: Lower cortical, striatal, and limbic 5-HTT and higher cortical Aβ was observed in MCIs relative to healthy controls. Lower 5-HTT, mainly in limbic regions, was correlated with greater deficits in auditory-verbal and visual-spatial memory and semantic, not phonemic fluency. Higher cortical A β was associated with greater deficits in auditory-verbal and visual-spatial memory and in semantic, not phonemic fluency. When modeling the association between cognition, gray matter volumes and Aβ, inclusion of 5-HTT in limbic and in select cortical regions significantly improved model fit for auditory-verbal and visual-spatial memory and semantic, but not phonemic fluency. CONCLUSIONS: These results support the role of serotonin degeneration in the memory and semantic fluency deficits observed in MCI.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Cognition; Cognition Disorders; Cognitive Dysfunction; Humans; Mice; Positron-Emission Tomography; Serotonin

Alzheimer's Disease with Epileptiform EEG Activity: Abnormal Cortical Sources of Resting State Delta Rhythms in Patients with Amnesic Mild Cognitive Impairment. - Babiloni, Claudio; Noce, Giuseppe; Di Bonaventura, Carlo; Lizio, Roberta; Eldellaa, Ali; Tucci, Federico; Salamone, Enrico M; Ferri, Raffaele; Soricelli, Andrea; Nobili, Flavio; Famá, Francesco; Arnaldi, Dario; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Patients with amnesic mild cognitive impairment due to Alzheimer's disease (ADMCI) typically show a "slowing" of cortical resting-state eyes-closed electroencephalographic (rsEEG) rhythms. Some of them also show subclinical, non-convulsive, and epileptiform EEG activity (EEA) with an unclear relationship with that "slowing." OBJECTIVE: Here we tested the hypothesis that the "slowing" of rsEEG rhythms is related to EEA in ADMCI patients. METHODS: Clinical and instrumental datasets in 62 ADMCI patients and 38 normal elderly (Nold) subjects were available in a national archive. No participant had received a clinical diagnosis of epilepsy. The eLORETA freeware estimated rsEEG cortical sources. The area under the receiver operating characteristic curve (AUROCC) indexed the accuracy of eLORETA solutions in the classification between ADMCI-EEA and ADMCI-noEEA individuals. RESULTS: EEA was observed in 15% (N = 8) of the ADMCI patients. The ADMCI-EEA group showed: 1) more abnormal Aβ 42 levels in the cerebrospinal fluid as compared to the ADMCI-noEEA group and 2) higher temporal and occipital delta ( CONCLUSION: It can be speculated that in ADMCI-EEA patients, AD-related amyloid neuropathology may be related to an over-excitation in neurophysiological low-frequency (delta) oscillatory mechanisms underpinning cortical arousal and quiet vigilance.

APOEɛ4 Allele Moderates the Association Between Basal Forebrain Nuclei Volumes and Allocentric Navigation in Older Adults Without Dementia. - Lerch, Ondřej; Pařízková, Martina; Vyhnálek, Martin; Nedelska, Zuzana; Hort, Jakub; Laczó, Jan (J Alzheimers Dis, 2022)
BACKGROUND: Cholinergic deficit and medial temporal lobe (MTL) atrophy are hallmarks of Alzheimer's disease (AD) leading to early allocentric spatial navigation (aSN) impairment. APOEɛ4 allele (E4) is a major genetic risk factor for late-onset AD and contributes to cholinergic dysfunction. Basal forebrain (BF) nuclei, the major source of acetylcholine, project into multiple brain regions and, along with MTL and prefrontal cortex (PFC), are involved in aSN processing. OBJECTIVE: We aimed to determine different contributions of individual BF nuclei atrophy to aSN in E4 positive and E4 negative older adults without dementia and assess whether they operate on aSN through MTL and PFC or independently from these structures. METHODS: 120 participants (60 E4 positive, 60 E4 negative) from the Czech Brain Aging Study underwent structural MRI and aSN testing in real-space arena setting. Hippocampal and BF nuclei volumes and entorhinal cortex and PFC thickness were obtained. Associations between brain regions involved in aSN were assessed using MANOVA and complex model of mutual relationships was built using structural equation modelling (SEM). RESULTS: Path analysis based on SEM modeling revealed that BF Ch1-2, Ch4p, and Ch4ai nuclei volumes were indirectly associated with aSN performance through MTL (pch1 - 2 = 0.039; pch4p = 0.042) and PFC (pch4ai = 0.044). In the E4 negative group, aSN was indirectly associated with Ch1-2 nuclei volumes (p = 0.015), while in the E4 positive group, there was indirect effect of Ch4p nucleus (p = 0.035). CONCLUSION: Our findings suggest that in older adults without dementia, BF nuclei affect aSN processing indirectly, through MTL and PFC, and that APOE E4 moderates these associations.

Automated Early Detection of Alzheimer's Disease by Capturing Impairments in Multiple Cognitive Domains with Multiple Drawing Tasks. - Kobayashi, Masatomo; Yamada, Yasunori; Shinkawa, Kaoru; Nemoto, Miyuki; Nemoto, Kiyotaka; Arai, Tetsuaki (J Alzheimers Dis, 2022)
BACKGROUND: Automatic analysis of the drawing process using a digital tablet and pen has been applied to successfully detect Alzheimer's disease (AD) and mild cognitive impairment (MCI). However, most studies focused on analyzing individual drawing tasks separately, and the question of how a combination of drawing tasks could improve the detection performance thus remains unexplored. OBJECTIVE: We aimed to investigate whether analysis of the drawing process in multiple drawing tasks could capture different, complementary aspects of cognitive impairments, with a view toward combining multiple tasks to effectively improve the detection capability. METHODS: We collected drawing data from 144 community-dwelling older adults (27 AD, 65 MCI, and 52 cognitively normal, or CN) who performed five drawing tasks. We then extracted motion- and pause-related drawing features for each task and investigated the statistical associations of the features with the participants' diagnostic statuses and cognitive measures. RESULTS: The drawing features showed gradual changes from CN to MCI and then to AD, and the changes in the features for each task were statistically associated with cognitive impairments in different domains. For classification into the three diagnostic categories, a machine learning model using the features from all five tasks achieved a classification accuracy of 75.2%, an improvement by 7.8% over that of the best single-task model. CONCLUSION: Our results demonstrate that a common set of drawing features from multiple drawing tasks can capture different, complementary aspects of cognitive impairments, which may lead to a scalable way to improve the automated detection of AD and MCI.

Behavioral and Psychological Symptoms of Dementia in Different Dementia Disorders: A Large-Scale Study of 10,000 Individuals. - Schwertner, Emilia; Pereira, Joana B; Xu, Hong; Secnik, Juraj; Winblad, Bengt; Eriksdotter, Maria; Nägga, Katarina; Religa, Dorota (J Alzheimers Dis, 2022)
BACKGROUND: The majority of individuals with dementia will suffer from behavioral and psychological symptoms of dementia (BPSD). These symptoms contribute to functional impairment and caregiver burden. OBJECTIVE: To characterize BPSD in Alzheimer's disease (AD), vascular dementia (VaD), mixed (Mixed) dementia, Parkinson's disease dementia (PDD), dementia with Lewy bodies (DLB), frontotemporal dementia (FTD), and unspecified dementia in individuals residing in long-term care facilities. METHODS: We included 10,405 individuals with dementia living in long-term care facilities from the Swedish registry for cognitive/dementia disorders (SveDem) and the Swedish BPSD registry. BPSD was assessed with the Neuropsychiatric Inventory - Nursing Home Version (NPI-NH). Multivariate logistic regression models were used to evaluate the associations between dementia diagnoses and different BPSDs. RESULTS: The most common symptoms were aberrant motor behavior, agitation, and irritability. Compared to AD, we found a lower risk of delusions (in FTD, unspecified dementia), hallucinations (FTD), agitation (VaD, PDD, unspecified dementia), elation/euphoria (DLB), anxiety (Mixed, VaD, unspecified dementia), disinhibition (in PDD), irritability (in DLB, FTD, unspecified dementia), aberrant motor behavior (Mixed, VaD, unspecified dementia), and sleep and night-time behavior changes (unspecified dementia). Higher risk of delusions (DLB), hallucinations (DLB, PDD), apathy (VaD, FTD), disinhibition (FTD), and appetite and eating abnormalities (FTD) were also found in comparison to AD. CONCLUSION: Although individuals in our sample were diagnosed with different dementia disorders, they all exhibited aberrant motor behavior, agitation, and irritability. This suggests common underlying psychosocial or biological mechanisms. We recommend prioritizing these symptoms while planning interventions in long-term care facilities.
Keywords: Alzheimer Disease; Behavioral Symptoms; Dementia, Vascular; Frontotemporal Dementia; Hallucinations; Humans; Parkinson Disease

Brain Tissue-Derived Extracellular Vesicles in Alzheimer's Disease Display Altered Key Protein Levels Including Cell Type-Specific Markers. - Huang, Yiyao; Driedonks, Tom A P; Cheng, Lesley; Rajapaksha, Harinda; Routenberg, David A; Nagaraj, Rajini; Redding, Javier; Arab, Tanina; Powell, Bonita H; Pletniková, Olga; Troncoso, Juan C; Zheng, Lei; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Brain tissue-derived extracellular vesicles (bdEVs) play neurodegenerative and protective roles, including in Alzheimer's disease (AD). Extracellular vesicles (EVs) may also leave the brain to betray the state of the CNS in the periphery. Only a few studies have profiled the proteome of bdEVs and source brain tissue. Additionally, studies focusing on bdEV cell type-specific surface markers are rare. OBJECTIVE: We aimed to reveal the pathological mechanisms inside the brain by profiling the tissue and bdEV proteomes in AD patients. In addition, to indicate targets for capturing and molecular profiling of bdEVs in the periphery, CNS cell-specific markers were profiled on the intact bdEV surface. METHODS: bdEVs were separated and followed by EV counting and sizing. Brain tissue and bdEVs from age-matched AD patients and controls were then proteomically profiled. Total tau (t-tau), phosphorylated tau (p-tau), and antioxidant peroxiredoxins (PRDX) 1 and 6 were measured by immunoassay in an independent bdEV separation. Neuron, microglia, astrocyte, and endothelia markers were detected on intact EVs by multiplexed ELISA. RESULTS: Overall, concentration of recovered bdEVs was not affected by AD. Proteome differences between AD and control were more pronounced for bdEVs than for brain tissue. Levels of t-tau, p-tau, PRDX1, and PRDX6 were significantly elevated in AD bdEVs compared with controls. Release of certain cell-specific bdEV markers was increased in AD. CONCLUSION: Several bdEV proteins are involved in AD mechanisms and may be used for disease monitoring. The identified CNS cell markers may be useful tools for peripheral bdEV capture.

"Captive by the Uncertainty"-Experiences with Anticipatory Guidance for People Living with Dementia and Their Caregivers at a Specialty Dementia Clinic. - Shafir, Adi; Ritchie, Christine S; Garrett, Sarah B; Bernstein Sideman, Alissa; Naasan, Georges; Merrilees, Jennifer; Widera, Eric; Flint, Lynn; Harrison, Krista L (J Alzheimers Dis, 2022)
BACKGROUND: After a diagnosis of Alzheimer's disease and related disorders, people living with dementia (PWD) and caregivers wonder what disease trajectory to expect and how to plan for functional and cognitive decline. This qualitative study aimed to identify patient and caregiver experiences receiving anticipatory guidance about dementia from a specialty dementia clinic. OBJECTIVE: To examine PWD and caregiver perspectives on receiving anticipatory guidance from a specialty dementia clinic. METHODS: We conducted semi-structured interviews with PWD, and active and bereaved family caregivers, recruited from a specialty dementia clinic. Interviews were recorded, transcribed, and systematically summarized. Thematic analysis identified anticipatory guidance received from clinical or non-clinical sources and areas where respondents wanted additional guidance. RESULTS: Of 40 participants, 9 were PWD, 16 were active caregivers, and 15 were bereaved caregivers. PWD had a mean age of 75 and were primarily male (n = 6/9); caregivers had a mean age of 67 and were primarily female (n = 21/31). Participants felt they received incomplete or "hesitant" guidance on prognosis and expected disease course via their clinicians and filled the gap with information they found via the internet, books, and support groups. They appreciated guidance on behavioral, safety, and communication issues from clinicians, but found more timely and advance guidance from other non-clinical sources. Guidance on legal and financial planning was primarily identified through non-clinical sources. CONCLUSION: PWD and caregivers want more information about expected disease course, prognosis, and help planning after diagnosis. Clinicians have an opportunity to improve anticipatory guidance communication and subsequent care provision.
Keywords: Aged; Alzheimer Disease; Caregivers; Dementia; Female; Humans; Male; Qualitative Research; Uncertainty

Caregiver Tele-Assistance for Reduction of Emotional Distress During the COVID-19 Pandemic. Psychological Support to Caregivers of People with Dementia: The Italian Experience. - Rotondo, Emanuela; Galimberti, Daniela; Mercurio, Matteo; Giardinieri, Giulia; Forti, Sara; Vimercati, Roberto; Borracci, Vittoria; Fumagalli, Giorgio G; Pietroboni, Anna M; Carandini, Tiziana; Nobili, Alessandro; Scarpini, Elio; et al. (J Alzheimers Dis, 2022)
BACKGROUND: COVID-19 pandemic worsened vulnerability of patients with dementia (PWD). This new reality associated with government restriction and isolation worsened stress burden and psychological frailties in PWD caregivers. OBJECTIVE: To give tele-psychological support to caregivers and evaluate the effect of this intervention by quantifying stress burden and quality of life during the first COVID-19 lockdown. METHODS: 50 caregivers were divided into two groups: "Caregiver-focused group" (Cg) and "Patient-focused group" (Pg). Both groups received telephone contact every 2 weeks over a 28-week period, but the content of the call was different: in Cg, caregivers answered questions about the state of the PWD but also explored their own emotional state, stress burden, and quality of life. In Pg instead, telephone contacts were focused only on the PWD, and no evaluation regarding the caregiver mood or state of stress was made. Psychometric scales were administered to evaluate COVID-19 impact, stress burden, and quality of life. RESULTS: Considering the time of intervention, from baseline (W0) to W28, Zarit Burden Interview and Quality of Life-caregiver questionnaires remained unchanged in Cg as compared with baseline (p > 0.05), whereas they worsened significantly in Pg (p < 0.01), showing increased stress over time and decreased quality of life in this group. Moreover, Impact on Event Scale values improved over the weeks in Cg (p = 0.015), while they remained unchanged in Pg (p = 0.483). CONCLUSION: Caregivers who received telephone support about their mood and stress burden did not worsen their psychological state during the time of intervention, as did instead those who did not get such support.
Keywords: Aged; Aged, 80 and over; Caregiver Burden; Caregivers; COVID-19; Dementia; Female; Humans; Italy; Male; Middle Aged; Psychological Distress; Psychosocial Support Systems; Quality of Life; Surveys and Questionnaires; Telephone

Circulating Cell-Free Genomic DNA Is Associated with an Increased Risk of Dementia and with Change in Cognitive and Physical Function. - Nidadavolu, Lolita S; Feger, Danielle; Wu, Yuqiong; Grodstein, Francine; Gross, Alden L; Bennett, David A; Walston, Jeremy D; Oh, Esther S; Abadir, Peter M (J Alzheimers Dis, 2022)
BACKGROUND: Altered cell homeostasis, seen in cognitive decline and frailty, leads to cell death and turnover, releasing circulating cell-free DNA (ccf-DNA). OBJECTIVE: The goal of this study is to determine if serum genomic cell-free DNA (ccf-gDNA) is associated with physical and cognitive decline in older adults. METHODS: We used serum from 631 community-dwelling individuals from the Religious Orders Study or Rush Memory and Aging Project who were without cognitive impairment at baseline. ccf-gDNA fragments in serum were quantified using digital PCR. An array of cognitive and physical traits, risk of dementia, global cognition, and frailty at or nearest the time of blood draw were regressed on ccf-DNA, with adjustment for age, sex, race, and education. RESULTS: Cross-sectionally, higher ccf-gDNA levels were associated with lower global cognition score and slower gait speed at the evaluation nearest to blood draw. Higher ccf-gDNA levels were associated with increased odds of incident dementia (OR 1.27, 95% CI 1.05, 1.54). Longitudinally, higher levels of ccf-gDNA were associated with steeper general cognitive decline and worsening frailty over eight years of follow up. CONCLUSION: This study demonstrates that ccf-gDNA fragments have utility for identifying persons at higher risk of developing dementia and worsening cognition and frailty.

Combinational Drug Repurposing from Genetic Networks Applied to Alzheimer's Disease. - Nabirotchkin, Serguei; Bouaziz, Jan; Glibert, Fabrice; Mandel, Jonas; Foucquier, Julie; Hajj, Rodolphe; Callizot, Noëlle; Cholet, Nathalie; Guedj, Mickaël; Cohen, Daniel (J Alzheimers Dis, 2022)
BACKGROUND: Human diseases are multi-factorial biological phenomena resulting from perturbations of numerous functional networks. The complex nature of human diseases explains frequently observed marginal or transitory efficacy of mono-therapeutic interventions. For this reason, combination therapy is being increasingly evaluated as a biologically plausible strategy for reversing disease state, fostering the development of dedicated methodological and experimental approaches. In parallel, genome-wide association studies (GWAS) provide a prominent opportunity for disclosing human-specific therapeutic targets and rational drug repurposing. OBJECTIVE: In this context, our objective was to elaborate an integrated computational platform to accelerate discovery and experimental validation of synergistic combinations of repurposed drugs for treatment of common human diseases. METHODS: The proposed approach combines adapted statistical analysis of GWAS data, pathway-based functional annotation of genetic findings using gene set enrichment technique, computational reconstruction of signaling networks enriched in disease-associated genes, selection of candidate repurposed drugs and proof-of-concept combinational experimental screening. RESULTS: It enables robust identification of signaling pathways enriched in disease susceptibility loci. Therapeutic targeting of the disease-associated signaling networks provides a reliable way for rational drug repurposing and rapid development of synergistic drug combinations for common human diseases. CONCLUSION: Here we demonstrate the feasibility and efficacy of the proposed approach with an experiment application to Alzheimer's disease.

Effect of Probiotic Bifidobacterium breve in Improving Cognitive Function and Preventing Brain Atrophy in Older Patients with Suspected Mild Cognitive Impairment: Results of a 24-Week Randomized, Double-Blind, Placebo-Controlled Trial. - Asaoka, Daisuke; Xiao, Jinzhong; Takeda, Tsutomu; Yanagisawa, Naotake; Yamazaki, Takahiro; Matsubara, Yoichiro; Sugiyama, Hideki; Endo, Noemi; Higa, Motoyuki; Kasanuki, Koji; Ichimiya, Yosuke; Koido, Shigeo; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Probiotics have been reported to ameliorate cognitive impairment. OBJECTIVE: We investigated the effect of the probiotic strain Bifidobacterium breve MCC1274 (A1) in enhancing cognition and preventing brain atrophy of older patients with mild cognitive impairment (MCI). METHODS: In this RCT, 130 patients aged from 65 to 88 years old with suspected MCI received once daily either probiotic (B. breve MCC1274, 2×1010 CFU) or placebo for 24 weeks. Cognitive functions were assessed by ADAS-Jcog and MMSE tests. Participants underwent MRI to determine brain atrophy changes using Voxel-based Specific Regional Analysis System for Alzheimer's disease (VSRAD). Fecal samples were collected for the analysis of gut microbiota composition. RESULTS: Analysis was performed on 115 participants as the full analysis set (probiotic 55, placebo 60). ADAS-Jcog subscale "orientation" was significantly improved compared to placebo at 24 weeks. MMSE subscales "orientation in time" and "writing" were significantly improved compared to placebo in the lower baseline MMSE (< 25) subgroup at 24 weeks. VSRAD scores worsened in the placebo group; probiotic supplementation tended to suppress the progression, in particular among those subjects with progressed brain atrophy (VOI Z-score ≥1.0). There were no marked changes in the overall composition of the gut microbiota by the probiotic supplementation. CONCLUSION: Improvement of cognitive function was observed on some subscales scores only likely due to the lower sensitiveness of these tests for MCI subjects. Probiotics consumption for 24 weeks suppressed brain atrophy progression, suggesting that B. breve MCC1274 helps prevent cognitive impairment of MCI subjects.
Keywords: Aged; Aged, 80 and over; Atrophy; Bifidobacterium breve; Brain; Cognition; Cognitive Dysfunction; Double-Blind Method; Humans; Probiotics

Evoked Cortical Depolarizations Before and After the Amyloid Plaque Accumulation: Voltage Imaging Study. - Zhu, Mei Hong; Jogdand, Aditi H; Jang, Jinyoung; Nagella, Sai C; Das, Brati; Milosevic, Milena M; Yan, Riqiang; Antic, Srdjan D (J Alzheimers Dis, 2022)
BACKGROUND: In Alzheimer's disease (AD), synaptic dysfunction is thought to occur many years before the onset of cognitive decline. OBJECTIVE: Detecting synaptic dysfunctions at the earliest stage of AD would be desirable in both clinic and research settings. METHODS: Population voltage imaging allows monitoring of synaptic depolarizations, to which calcium imaging is relatively blind. We developed an AD mouse model (APPswe/PS1dE9 background) expressing a genetically-encoded voltage indicator (GEVI) in the neocortex. GEVI was restricted to the excitatory pyramidal neurons (unlike the voltage-sensitive dyes). RESULTS: Expression of GEVI did not disrupt AD model formation of amyloid plaques. GEVI expression was stable in both AD model mice and Control (healthy) littermates (CTRL) over 247 days postnatal. Brain slices were stimulated in layer 2/3. From the evoked voltage waveforms, we extracted several parameters for comparison AD versus CTRL. Some parameters (e.g., temporal summation, refractoriness, and peak latency) were weak predictors, while other parameters (e.g., signal amplitude, attenuation with distance, and duration (half-width) of the evoked transients) were stronger predictors of the AD condition. Around postnatal age 150 days (P150) and especially at P200, synaptically-evoked voltage signals in brain slices were weaker in the AD groups versus the age- and sex-matched CTRL groups, suggesting an AD-mediated synaptic weakening that coincides with the accumulation of plaques. However, at the youngest ages examined, P40 and P80, the AD groups showed differentially stronger signals, suggesting "hyperexcitability" prior to the formation of plaques. CONCLUSION: Our results indicate bidirectional alterations in cortical physiology in AD model mice; occurring both prior (P40-80), and after (P150-200) the amyloid deposition.

High Soluble Amyloid-β42 Predicts Normal Cognition in Amyloid-Positive Individuals with Alzheimer's Disease-Causing Mutations. - Sturchio, Andrea; Dwivedi, Alok K; Malm, Tarja; Wood, Matthew J A; Cilia, Roberto; Sharma, Jennifer S; Hill, Emily J; Schneider, Lon S; Graff-Radford, Neill R; Mori, Hiroshi; Nübling, Georg; El Andaloussi, Samir; et al. (J Alzheimers Dis, 2022)
BACKGROUND: In amyloid-positive individuals at risk for Alzheimer's disease (AD), high soluble 42-amino acid amyloid-β (Aβ42) levels are associated with normal cognition. It is unknown if this relationship applies longitudinally in a genetic cohort. OBJECTIVE: To test the hypothesis that high Aβ42 preserves normal cognition in amyloid-positive individuals with Alzheimer's disease (AD)-causing mutations (APP, PSEN1, or PSEN2) to a greater extent than lower levels of brain amyloid, cerebrospinal fluid (CSF) phosphorylated tau (p-tau), or total tau (t-tau). METHODS: Cognitive progression was defined as any increase in Clinical Dementia Rating (CDR = 0, normal cognition; 0.5, very mild dementia; 1, mild dementia) over 3 years. Amyloid-positivity was defined as a standard uptake value ratio (SUVR) ≥1.42 by Pittsburgh compound-B positron emission tomography (PiB-PET). We used modified Poisson regression models to estimate relative risk (RR), adjusted for age at onset, sex, education, APOE4 status, and duration of follow-up. The results were confirmed with multiple sensitivity analyses, including Cox regression. RESULTS: Of 232 mutation carriers, 108 were PiB-PET-positive at baseline, with 43 (39.8% ) meeting criteria for progression after 3.3±2.0 years. Soluble Aβ42 levels were higher among CDR non-progressors than CDR progressors. Higher Aβ42 predicted a lower risk of progression (adjusted RR, 0.36; 95% confidence interval [CI], 0.19-0.67; p = 0.002) better than lower SUVR (RR, 0.81; 95% CI, 0.68-0.96; p = 0.018). CSF Aβ42 levels predicting lower risk of progression increased with higher SUVR levels. CONCLUSION: High CSF Aβ42 levels predict normal cognition in amyloid-positive individuals with AD-causing genetic mutations.

Importance of Accounting for Regional Differences in Modifiable Risk Factors for Alzheimer's Disease and Related Dementias: The Case for Tailored Interventions. - Hoffmann, Coles M; Nianogo, Roch A; Yaffe, Kristine; Rosenwohl-Mack, Amy; Carrasco, Anna; Barnes, Deborah E (J Alzheimers Dis, 2022)
BACKGROUND: We recently estimated that 36.9% of Alzheimer's disease and related dementias (ADRD) cases in the US may be attributable to modifiable risk factors, but it is not known whether national estimates generalize to specific states or regions. OBJECTIVE: To compare national estimates of modifiable risk factors of ADRD to California, overall and by sex and race/ethnicity, and to estimate number of cases potentially preventable by reducing the prevalence of key risk factors by 25%. METHODS: Adults ≥18 years who participated in the Behavioral Risk Factor Surveillance Survey in California (n = 9,836) and the US (n = 378,615). We calculated population attributable risks (PARs) for eight risk factors (physical inactivity, current smoking, depression, low education, diabetes mellitus, midlife obesity, midlife hypertension, and hearing loss) and compared estimates in California and the U.S. RESULTS: In California, overall, 28.9% of ADRD cases were potentially attributable to the combination of risk factors, compared to 36.9% in the U.S. The top three risk factors were the same in California and the U.S., although their relative importance differed (low education [CA:14.9%; U.S.:11.7% ], midlife obesity [CA:14.9%; U.S.:17.7% ], and physical inactivity [CA:10.3%; U.S.:11.8% ]). The number of ADRD cases attributable to the combined risk factors was 199,246 in California and 2,287,683 in the U.S. If the combined risk factors were reduced by 25%, we could potentially prevent more than 40,000 cases in California and 445,000 cases in the U.S. CONCLUSION: Our findings highlight the importance of examining risk factors of ADRD regionally, and within sex and race/ethnic groups to tailor dementia risk reduction strategies.

Improved Alzheimer's Disease versus Frontotemporal Lobar Degeneration Differential Diagnosis Combining EEG and Neurochemical Biomarkers: A Pilot Study. - Laton, Jorne; Van Schependom, Jeroen; Goossens, Joery; Wiels, Wietse; Sieben, Anne; De Deyn, Peter Paul; Goeman, Johan; Streffer, Johannes; van der Zee, Julie; Martin, Jean-Jacques; Van Broeckhoven, Christine; De Vos, Maarten; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Distinguishing between Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD) results in poor diagnostic accuracy. OBJECTIVE: To investigate the utility of electroencephalography (EEG)-based biomarkers in comparison and in addition to established cerebrospinal fluid (CSF) biomarkers in the AD versus FTLD differential diagnosis. METHODS: The study cohort comprised 37 AD and 30 FTLD patients, of which 17 AD and 9 FTLD patients had definite diagnoses. All participants had CSF neurochemical (NCM) biomarker analyses (Aβ1-42, T-tau, P-tau181, and Nf-L) and underwent 19-channel resting-state EEG. From the EEG spectra, dominant frequency peaks were extracted in four regions resulting in four dominant frequencies. This produced eight features (4 NCM + 4 EEG). RESULTS: When NCM and EEG markers were combined, the diagnostic accuracy increased significantly. In the whole group, the accuracy went up from 79% (NCM) to almost 82%, while in the definite group only, it went up from around 85% to almost 95% . Two differences in the occurrence of the dominant EEG frequency were discovered: people lacking a clear dominant peak almost all had definite AD, while people with two peaks more often had FTLD. CONCLUSION: Combining EEG with NCM biomarkers resulted in differential diagnostic accuracies of 82% in clinically diagnosed AD and FTD patients and of 95% in patients having a definite diagnosis, which was significantly better than with EEG or NCM biomarkers alone. This suggests that NCM and EEG markers are complementary, revealing different aspects of the disease and therefore confirms again their relevance in developing additional diagnosis tools.

Insulin-Like Growth Factor, Inflammation, and MRI Markers of Alzheimer's Disease in Predominantly Middle-Aged Adults. - Wittfeld, Katharina; Raman, Mekala R; Conner, Sarah C; Aslam, Asra; Teumer, Alexander; Nauck, Matthias; Hosten, Norbert; Habes, Mohamad; DeCarli, Charles; Vasan, Ramachandran S; Beiser, Alexa S; Himali, Jayandra J; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Insulin-like growth factor 1 (IGF-1) signaling has been implicated in Alzheimer's disease pathogenesis, and further evidence suggests inflammation can be a moderator of this association. However, most research to date has been conducted on older adults. OBJECTIVE: To investigate the association of serum IGF-1 and IGF binding protein 3 (IGFBP-3) concentrations with MRI markers of Alzheimer's disease in predominantly middle-aged adults, and further assess moderation by chronic inflammation. METHODS: We included participants from the Framingham Heart Study (n = 1,852, mean age 46±8, 46% men) and the Study of Health in Pomerania (n = 674, mean age 50±13, 42% men) with available serum IGF-1, IFGBP-3, as well as brain MRI. IGF-1 and IFGBP-3 were related to MRI outcomes (i.e., total brain, cortical gray matter, white matter, white matter hyperintensities (WMH), and hippocampal volumes) using multivariable regression models adjusting for potential confounders. Subgroup analyses by C-reactive protein (CRP) concentrations were also performed. Cohort-specific summary statistics were meta-analyzed using random-effects models and corrected for multiple comparisons. RESULTS: Meta-analysis results revealed that higher IGF-1 concentrations were associated with lower WMH (estimate [β] [95% CI], -0.05 [-0.09, -0.02], p = 0.006) and larger hippocampal volumes (0.07 [0.02, 0.12], p = 0.01), independent of vascular risk factors. These associations occurred predominantly in individuals with CRP concentrations < 75th percentile. We did not observe associations between IGFBP-3 and MRI outcomes. CONCLUSION: Our findings suggest that IGF-1-related signaling may be implicated in brain health as early as midlife.

Interaction Between Diet and Microbiota in the Pathophysiology of Alzheimer's Disease: Focus on Polyphenols and Dietary Fibers. - Ticinesi, Andrea; Mancabelli, Leonardo; Carnevali, Luca; Nouvenne, Antonio; Meschi, Tiziana; Del Rio, Daniele; Ventura, Marco; Sgoifo, Andrea; Angelino, Donato (J Alzheimers Dis, 2022)
Animal studies increasingly indicate that the gut microbiota composition and function can be involved in the pathophysiology and progression of Alzheimer's disease (AD) at multiple levels. However, few studies have investigated this putative gut-brain axis in human beings, and none of them considered diet as a determinant of intestinal microbiota composition. Epidemiological studies highlight that a high intake of fruit and vegetables, such as that typical of the Mediterranean diet, can modulate AD progression. Thus, nutritional interventions are being increasingly studied as a possible non-pharmacological strategy to slow down the progression of AD. In particular, polyphenols and fibers represent the nutritional compounds with the higher potential of counterbalancing the pathophysiological mechanisms of dementia due to their antioxidant, anti-inflammatory, and anti-apoptotic properties. These actions are mediated by the gut microbiota, that can transform polyphenols and fibers into biologically active compounds including, among others, phenyl-γ-valerolactones, urolithins, butyrate, and other short-chain fatty acids. In this review, the complex mechanisms linking nutrition, gut microbiota composition, and pathophysiology of cognitive decline in AD are discussed, with a particular focus on the role of polyphenols and fibers. The gaps between pre-clinical and clinical studies are particularly emphasized, as well as the urgent need for studies comprehensively evaluating the link between nutrition, microbiome, and clinical aspects of AD.
Keywords: Alzheimer Disease; Animals; Diet; Diet, Mediterranean; Dietary Fiber; Humans; Microbiota; Polyphenols

Investigating Casual Associations Among Gut Microbiota, Metabolites, and Neurodegenerative Diseases: A Mendelian Randomization Study. - Ning, Jing; Huang, Shu-Yi; Chen, Shi-Dong; Zhang, Ya-Ru; Huang, Yu-Yuan; Yu, Jin-Tai (J Alzheimers Dis, 2022)
BACKGROUND: Recent studies had explored that gut microbiota was associated with neurodegenerative diseases (including Alzheimer's disease (AD), Parkinson's disease (PD), and amyotrophic lateral sclerosis (ALS)) through the gut-brain axis, among which metabolic pathways played an important role. However, the underlying causality remained unclear. OBJECTIVE: Our study aimed to evaluate potential causal relationships between gut microbiota, metabolites, and neurodegenerative diseases through Mendelian randomization (MR) approach. METHODS: We selected genetic variants associated with gut microbiota traits (N = 18,340) and gut microbiota-derived metabolites (N = 7,824) from genome-wide association studies. Summary statistics of neurodegenerative diseases were obtained from IGAP (AD, 17,008 cases; 37,154 controls), IPDGC (PD, 37,688 cases; 141,779 controls), and IALSC (ALS, 20,806 cases; 59,804 controls) respectively. RESULTS: Greater abundance of Ruminococcus (OR, 1.245; 95% CI, 1.103-1.405; p = 0.0004) was found significantly related to higher risk of ALS. Besides, our study found suggestive associations of Actinobacteria, Lactobacillaceae, Faecalibacterium, Ruminiclostridium, and Lachnoclostridium with AD, of Lentisphaerae, Lentisphaeria, Oxalobacteraceae, Victivallales, Bacillales, Eubacteriumhalliigroup, Anaerostipes, and Clostridiumsensustricto1 with PD, and of Lachnospira, Fusicatenibacter, Catenibacterium, and Ruminococcusgnavusgroup with ALS. Our study also revealed suggestive associations between 12 gut microbiome-dependent metabolites and neurodegenerative diseases. Glutamine was related to lower risk of AD. For the serotonin pathway, serotonin was found as a protective factor of PD, while kynurenine as a risk factor for ALS. CONCLUSION: Our study firstly applied a two-sample MR approach to detect causal relationships among gut microbiota, gut metabolites, and neurodegenerative diseases. Our findings may provide new targets for treatments and may offer valuable insights for further studies on the underlying mechanisms.
Keywords: Alzheimer Disease; Amyotrophic Lateral Sclerosis; Gastrointestinal Microbiome; Genome-Wide Association Study; Humans; Mendelian Randomization Analysis; Neurodegenerative Diseases; Parkinson Disease; Risk Factors; Serotonin

Late-Onset Alcohol Abuse as a Presenting Symptom of Neurodegenerative Diseases. - de Paula França Resende, Elisa; Ketelle, Robin; Karydas, Anna; Allen, Isabel; Grinberg, Lea T; Spina, Salvatore; Seeley, William W; Perry, David C; Miller, Bruce; Naasan, Georges (J Alzheimers Dis, 2022)
BACKGROUND: The association between lifetime alcohol abuse and a higher risk to develop dementia is well known. However, it is unknown whether older adults who begin abusing alcohol late in life have an underlying neurodegenerative disease. OBJECTIVE: Identify the frequency of lifelong alcohol abuse (L-AA), late-onset alcohol abuse (LO-AA), and alcohol abuse as a first symptom of dementia (AA-FS) in patients with neurodegenerative diseases. METHODS: Cross-sectional retrospective study of patients evaluated at an academic referral center with a clinical diagnosis of behavioral variant frontotemporal dementia (bvFTD), Alzheimer-type dementia (AD), and semantic variant primary progressive aphasia (svPPA) (n = 1,518). The presence of alcohol abuse was screened with the National Alzheimer's Coordinating Center questionnaire. L-AA was defined as onset <  40 years, LO-AA as onset ≥40 years, and AA-FS was defined when the abuse started within the first three years from symptom onset. RESULTS: The frequency of LO-AA was 2.2% (n = 33/1,518). LO-AA was significantly more frequent in patients with bvFTD than AD (7.5%, n = 13/173 versus 1.3%, n = 16/1,254, CI:1.0;11.4%), but not svPPA (4.4%, n = 4/91, CI: -4.4;10.7%). Similarly, AA-FS was more frequent in bvFTD patients than AD (5.7%, n = 10/173 versus 0.7%, n = 9/1,254, CI:0.5% ;9.5%), but not svPPA (2.2%, n = 2/91, CI:-2.4;9.1%). CONCLUSION: LO-AA can be a presenting symptom of dementia, especially bvFTD. Alcohol abuse onset later in life should prompt a clinical investigation into the possibility of an underlying neurodegenerative process because delay in diagnosis and treatment may increase patient and caregiver burden. The results need to be interpreted with caution due to the limitations of the study.

Lipid Rafts Act as a Common Platform for Amyloid-β Oligomer-Induced Alzheimer's Disease Pathology. - Kawarabayashi, Takeshi; Nakamura, Takumi; Sato, Kaoru; Seino, Yusuke; Ichii, Sadanobu; Nakahata, Naoko; Takatama, Masamitsu; Westaway, David; George-Hyslop, Peter St; Shoji, Mikio (J Alzheimers Dis, 2022)
BACKGROUND: Amyloid-β (Aβ) oligomers induce the overproduction of phosphorylated tau and neurodegeneration. These cascades gradually cause cognitive impairment in Alzheimer's disease (AD). While each pathological event in AD has been studied in detail separately, the spatial and temporal relationships between pathological events in AD remain unclear. OBJECTIVE: We demonstrated that lipid rafts function as a common platform for the pathological cascades of AD. METHODS: Cellular and synaptosomal lipid rafts were prepared from the brains of Aβ amyloid model mice (Tg2576 mice) and double transgenic mice (Tg2576 x TgTauP301L mice) and longitudinally analyzed. RESULTS: Aβ dimers, the cellular prion protein (PrPc), and Aβ dimer/PrPc complexes were detected in the lipid rafts. The levels of Fyn, the phosphorylated NR2B subunit of the N-methyl-D-aspartate receptor, glycogen synthase kinase 3β, total tau, phosphorylated tau, and tau oligomers increased with Aβ dimer accumulation in both the cellular and synaptosomal lipid rafts. Increases in the levels of these molecules were first seen at 6 months of age and corresponded with the early stages of Aβ accumulation in the amyloid model mice. CONCLUSION: Lipid rafts act as a common platform for the progression of AD pathology. The findings of this study suggest a novel therapeutic approach to AD, involving the modification of lipid raft components and the inhibition of their roles in the sequential pathological events of AD.

Novel Invisible Spectral Flicker Induces 40 Hz Neural Entrainment with Similar Spatial Distribution as 40 Hz Stroboscopic Light. - Agger, Mikkel Pejstrup; Carstensen, Marcus Schultz; Henney, Mark Alexander; Hansen, Luna Skytte; Baandrup, Anders Ohlhues; Nguyen, Mai; Petersen, Paul Michael; Madsen, Kristoffer Hougaard; Kjær, Troels Wesenberg (J Alzheimers Dis, 2022)
BACKGROUND: Exposure to 40 Hz stroboscopic light, for one hour a day, has previously been published as a potential treatment option for Alzheimer's disease in animal models. However, exposure for an hour a day to 40 Hz stroboscopic light can be strenuous and examining other types of 40 Hz inducing stimuli is paramount if chronic treatment is wanted. OBJECTIVE: A core assumption behind ensuring a therapeutic outcome is that the visual stimuli can induce 40 Hz gamma entrainment. Here, we examine whether a specific visual stimulus, 40 Hz invisible spectral flicker (ISF), can induce gamma entrainment and how it differs from both continuous light (CON) and 40 Hz stroboscopic light (STROBE). METHODS: The study included non-simultaneous EEG-fMRI neuroimaging of 13 young healthy volunteers during light exposure. Each light condition (i.e., CON, ISF, or STROBE) was active for 30 seconds followed immediately by the next. RESULTS: Entrainment of 40 Hz neural activity were significantly higher signal-to-noise ratio during exposure to ISF (mean: 3.03, 95% CI 2.07 to 3.99) and STROBE (mean: 12.04, 95% CI 10.18 to 13.87) compared to CON. Additionally STROBE had a higher entrainment than ISF (mean: 9.01, 95% CI 7.16 to 12.14). CONCLUSION: This study presents a novel method of 40 Hz entrainment using ISF. This enables the possibility of future randomized placebo-controlled clinical trials with acceptable double blinding due to the essentially imperceivable flicker, which is expected to substantially reduce discomfort compared to interventions with stroboscopic flicker.

Perivascular Space Predicts Brain Hypometabolism of Individuals with Underlying Amyloid Pathology. - Shi, Xiaolei; Zhou, Nan; Sun, Bin; Wu, Yongshun; Hu, Yachun; Ning, Yuping (J Alzheimers Dis, 2022)
BACKGROUND: Reduced signal on fluorodeoxyglucose-positron emission tomography (FDG-PET) is a valid proxy for neurodegeneration in Alzheimer's disease (AD). Perivascular space (PVS) is believed to be associated with AD pathology and cognitive decline. OBJECTIVE: This study aimed to investigate the associations of PVS with FDG-PET and cognitive performance based on the burden of amyloid pathology. METHODS: We used magnetic resonance imaging (MRI) data from the Alzheimer's Disease Neuroimaging Initiative (ADNI). MRI-visible PVS in basal ganglia (BG) and centrum semi-oval (CSO) were visually classified as: none/mild, moderate or frequent/severe. The association of PVS with brain FDG-PET was explored based on the burden of amyloid pathology, where a cerebrospinal fluid (CSF) t-tau/Aβ42 with the ratio≥0.27 was defined as high amyloid pathology. Moreover, the relationships between PVS and cognitive performance variables (ADNI-MEM and ADNI-EF) were studied. RESULTS: For participants with higher tau/Aβ42 ratio, CSO-PVS severity was independently associated with lower FDG-PET. There were significant interaction effects between moderate or frequent/severe CSO-PVS and time on FDG decline in people with high amyloid pathology. The interaction between CSO-PVS and time (follow-up) was consistently associated with ADNI-MEM and ADNI-EF decline in individuals with high amyloid pathology. CONCLUSION: The study established the differential utility of PVS in BG and CSO for predicting brain metabolism. These findings suggest that CSO-PVS serves as a contributing factor to brain metabolism and cognitive decline associated with amyloid pathology.

Progression from Subjective Cognitive Decline to Mild Cognitive Impairment or Dementia: The Role of Baseline Cognitive Performance. - Jester, Dylan J; Vyhnálek, Martin; Andel, Ross; Marková, Hana; Nikolai, Tomas; Laczó, Jan; Matuskova, Veronika; Cechova, Katerina; Sheardova, Katerina; Hort, Jakub (J Alzheimers Dis, 2022)
BACKGROUND: Older adults with subjective cognitive decline (SCD) are at an increased risk of progression to mild cognitive impairment (MCI) or dementia. However, few have examined the specific cognitive tests that are associated with progression. OBJECTIVE: This study examined performance on 18 neuropsychological tests among participants with SCD who later progressed to MCI or dementia. METHODS: We included 131 participants from the Czech Brain Aging Study that had SCD at baseline. They completed a comprehensive neuropsychological battery including cognitive tests from the Uniform Data Set 2.0 enriched by the verbal memory test Rey Auditory Verbal Learning Test (RAVLT) and Rey-Osterrieth Complex Figure Test (ROCFT). RESULTS: Fifty-five participants progressed: 53% to non-amnestic MCI (naMCI), 44% to amnestic MCI (aMCI), and 4% to dementia. Scoring one SD below the mean at baseline on the RAVLT 1 and RAVLT 1-5 was associated with 133% (RAVLT 1; HR: 2.33 [1.50, 3.62]) and 122% (RAVLT 1-5; HR: 2.22 [1.55, 3.16]) greater risk of progression to MCI or dementia over 3.84 years on average. Worse performance on the RAVLT 5, RAVLT 1-5, RAVLT 30, and ROCFT-Recall was associated with progression to aMCI whereas worse performance on the RAVLT 1, TMT B, and Boston Naming Test was associated with progression to naMCI. CONCLUSION: At baseline, lower verbal memory performance was most strongly associated with progression to aMCI whereas lower executive or language performance was most strongly associated with progression to naMCI.

Psychosis as a Treatment Target in Dementia: A Roadmap for Designing Interventions. - Agüera-Ortiz, Luis; Babulal, Ganesh M; Bruneau, Marie-Andrée; Creese, Byron; D'Antonio, Fabrizia; Fischer, Corinne E; Gatchel, Jennifer R; Ismail, Zahinoor; Kumar, Sanjeev; McGeown, William J; Mortby, Moyra E; Nuñez, Nicolas A; et al. (J Alzheimers Dis, 2022)
Psychotic phenomena are among the most severe and disruptive symptoms of dementias and appear in 30% to 50% of patients. They are associated with a worse evolution and great suffering to patients and caregivers. Their current treatments obtain limited results and are not free of adverse effects, which are sometimes serious. It is therefore crucial to develop new treatments that can improve this situation. We review available data that could enlighten the future design of clinical trials with psychosis in dementia as main target. Along with an explanation of its prevalence in the common diseases that cause dementia, we present proposals aimed at improving the definition of symptoms and what should be included and excluded in clinical trials. A review of the available information regarding the neurobiological basis of symptoms, in terms of pathology, neuroimaging, and genomics, is provided as a guide towards new therapeutic targets. The correct evaluation of symptoms is transcendental in any therapeutic trial and these aspects are extensively addressed. Finally, a critical overview of existing pharmacological and non-pharmacological treatments is made, revealing the unmet needs, in terms of efficacy and safety. Our work emphasizes the need for better definition and measurement of psychotic symptoms in dementias in order to highlight their differences with symptoms that appear in non-dementing diseases such as schizophrenia. Advances in neurobiology should illuminate the development of new, more effective and safer molecules for which this review can serve as a roadmap in the design of future clinical trials.
Keywords: Caregivers; Dementia; Hallucinations; Humans; Psychotic Disorders; Schizophrenia

Relationships Between the Deposition of Amyloid-β and Tau Protein and Glymphatic System Activity in Alzheimer's Disease: Diffusion Tensor Image Study. - Ota, Miho; Sato, Noriko; Nakaya, Moto; Shigemoto, Yoko; Kimura, Yukio; Chiba, Emiko; Yokoi, Yuma; Tsukamoto, Tadashi; Matsuda, Hiroshi (J Alzheimers Dis, 2022)
BACKGROUND: Amyloid-β (Aβ) and tau protein accumulation in the brain is thought to be one of the causes of Alzheimer's disease (AD). Recent study found that the glymphatic system was waste drainage system in the brain and promoting the elimination of Aβ and tau protein. OBJECTIVE: Objective: We evaluated the relationships between the glymphatic system activity and Aβ and tau protein deposition. METHODS: Subjects were 21 patients with AD and 36 healthy subjects who underwent diffusion tensor imaging (DTI) scan and the positron emission tomography using with the Aβ tracer: 11C-PiB and the tau/inflammatory tracer: 18F-THK5351. We computed diffusion tensor image analysis along the perivascular space (DTI-ALPS) index as the proxy of glymphatic system activity and estimated the relationships between the DTI-ALPS index and Aβ and tau protein/inflammatory deposition. RESULTS: We found significant negative correlations between DTI-ALPS index and the standard uptake value ratio (SUVR) of 11C-PiB in the bilateral temporal and left parietal cortices and left posterior cingulate gyrus in all subjects. Further, we detected significant negative correlations between DTI-ALPS index and the SUVR of 18F-THK5351 in the bilateral temporal cortices and right parietal cortex in all participants, too. CONCLUSION: Our data suggested that DTI-ALPS index was a good biomarker for the evaluation of Aβ and tau deposition and neuroinflammation, and this marker might be effective to estimate the glymphatic system activity.

Rheumatoid Arthritis, Cognitive Impairment, and Neuroimaging Biomarkers: Results from the Mayo Clinic Study of Aging. - Vassilaki, Maria; Crowson, Cynthia S; Davis Iii, John M; Duong, Stephanie Q; Jones, David T; Nguyen, Aivi; Mielke, Michelle M; Vemuri, Prashanthi; Myasoedova, Elena (J Alzheimers Dis, 2022)
BACKGROUND: Observational studies suggested that dementia risk in patients with rheumatoid arthritis (RA) is higher than in the general population. OBJECTIVE: To examine the associations of RA with cognitive decline and dementia, and neuroimaging biomarkers of aging, Alzheimer's disease, and vascular pathology in adult participants in the Mayo Clinic Study of Aging (MCSA). METHODS: Participants with RA were matched 1:3 on age, sex, education, and baseline cognitive diagnosis to participants without RA. RA cases with MRI were also matched with non-cases with available MRI. All available imaging studies (i.e., amyloid and FDG PET, sMRI, and FLAIR) were included. The study included 104 participants with RA and 312 without RA (mean age (standard deviation, SD) 75.0 (10.4) years, 33% male and average follow-up (SD) 4.2 (3.8) years). RESULTS: Groups were similar in cognitive decline and risk of incident dementia. Among participants with neuroimaging, participants with RA (n = 33) and without RA (n = 98) had similar amyloid burden and neurodegeneration measures, including regions sensitive to aging and dementia, but greater mean white matter hyperintensity volume relative to the total intracranial volume (mean (SD)% : 1.12 (0.57)% versus 0.76 (0.69)% of TIV, p = 0.01), and had higher mean (SD) number of cortical infarctions (0.24 (0.44) versus 0.05 (0.33), p = 0.02). CONCLUSION: Although cognitive decline and dementia risk were similar in participants with and without RA, participants with RA had more abnormal cerebrovascular pathology on neuroimaging. Future studies should examine the mechanisms underlying these changes and potential implications for prognostication and prevention of cognitive decline in RA.
Keywords: Aged; Aging; Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidosis; Arthritis, Rheumatoid; Biomarkers; Brain; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Neuroimaging; Positron-Emission Tomography

Supplementation With Carotenoids, Omega-3 Fatty Acids, and Vitamin E Has a Positive Effect on the Symptoms and Progression of Alzheimer's Disease. - Nolan, John M; Power, Rebecca; Howard, Alan N; Bergin, Paula; Roche, Warren; Prado-Cabrero, Alfonso; Pope, George; Cooke, John; Power, Tommy; Mulcahy, Riona (J Alzheimers Dis, 2022)
BACKGROUND: Preliminary work by our center has reported behavior and functional benefits in patients with Alzheimer's disease (AD) following targeted micronutritional supplementation. OBJECTIVE: To build on the existing exploratory research and investigate the impact of these micronutrients on the natural progression of AD in a randomized controlled trial. METHODS: Patients with mild-moderate AD consumed daily 1 g fish oil (of which 500 mg DHA, 150 mg EPA), 22 mg carotenoids (10 mg lutein, 10 mg meso-zeaxanthin, 2 mg zeaxanthin), and 15 mg vitamin E or placebo for 12 months in a double-blind, placebo-controlled, randomized clinical trial. Carotenoids, ω-3FAs, and vitamin E were quantified in blood. Carotenoids were also measured in skin. AD severity was measured using the mini-mental state examination and dementia severity rating scale tools. Behavior, mood, and memory were measured using an informant-based questionnaire. RESULTS: Following 12 months of supplementation, the active group (n = 50) compared to the placebo group (n = 27), demonstrated statistically significant improvements in skin carotenoid measurements, blood carotenoids, ω-3FAs, and vitamin E concentrations (p <  0.05, for all). The active group also performed better in objective measures of AD severity (i.e., memory and mood), with a statistically significant difference reported in the clinical collateral for memory (p <  0.001). CONCLUSION: Exponential increases in the prevalence of AD and its relentless progressive nature is driving the need for interventions that help to ameliorate symptoms and improve quality of life in AD patients. Given the positive outcomes demonstrated in this trial, this combined micronutrient dietary supplement should be considered in the overall management of AD.

Yoga Prevents Gray Matter Atrophy in Women at Risk for Alzheimer's Disease: A Randomized Controlled Trial. - Krause-Sorio, Beatrix; Siddarth, Prabha; Kilpatrick, Lisa; Milillo, Michaela M; Aguilar-Faustino, Yesenia; Ercoli, Linda; Narr, Katherine L; Khalsa, Dharma S; Lavretsky, Helen (J Alzheimers Dis, 2022)
BACKGROUND: Female sex, subjective cognitive decline (SCD), and cardiovascular risk factors (CVRFs) are known risk factors for developing Alzheimer's disease (AD). We previously demonstrated that yoga improved depression, resilience, memory and executive functions, increased hippocampal choline concentrations, and modulated brain connectivity in older adults with mild cognitive impairment. OBJECTIVE: In this study (NCT03503669), we investigated brain gray matter volume (GMV) changes in older women with SCD and CVRFs following three months of yoga compared to memory enhancement training (MET). METHODS: Eleven women (mean age = 61.45, SD = 6.58) with CVRF and SCD completed twelve weeks of Kundalini Yoga and Kirtan Kriya (KY + KK) while eleven women (mean age = 64.55, SD = 6.41) underwent MET. Anxiety, resilience, stress, and depression were assessed at baseline and 12 weeks, as were T1-weighted MRI scans (Siemens 3T Prisma scanner). We used Freesurfer 6.0 and tested group differences in GMV change, applying Monte-Carlo simulations with alpha = 0.05. Region-of-interest analysis was performed for hippocampus and amygdala. RESULTS: Compared to KY + KK, MET showed reductions in GMV in left prefrontal, pre- and post-central, supramarginal, superior temporal and pericalcarine cortices, right paracentral, postcentral, superior and inferior parietal cortices, the banks of the superior temporal sulcus, and the pars opercularis. Right hippocampal volume increased after yoga but did not survive corrections. CONCLUSION: Yoga training may offer neuroprotective effects compared to MET in preventing neurodegenerative changes and cognitive decline, even over short time intervals. Future analyses will address changes in functional connectivity in both groups.

Acute Exercise and Cognitive Function in Alzheimer's Disease. - Ben Ayed, Ines; Castor-Guyonvarch, Naomie; Amimour, Souad; Naija, Salma; Aouichaoui, Chirine; Ben Omor, Sana; Tabka, Zouhair; El Massioui, Farid (J Alzheimers Dis, 2021)
BACKGROUND: Many studies have shown the impact of acute aerobic exercises (AAE) on cognition in healthy adults or at a pre-dementia stage. Few studies, however, have explored the positive effects of AAE in moderate Alzheimer's disease (ADM) patients. OBJECTIVE: Evaluating the effect of AAE on cognitive functions in ADM patients. METHODS: Overall, 79 (age: 69.62±0.99) ADM patients were recruited. Participants were divided into three groups according to the task: aerobic exercises done alone or combined with cognitive games presented on a screen, and a control group who performed a reading task. The aerobic exercise protocol consisted of a 20-min cycling exercise of moderate intensity, corresponding to 60%of the individual target maximal heart rate recorded in a 6-minute walking test. The participants' cognition was monitored before and after the intervention using the Tower of Hanoi, Digit Span, and Stroop tasks. RESULTS: After the exercise, the participants' attention in both the physical and combined groups improved for the Stroop, the forward and backward Digit Span tasks, as well as the time taken to solve the Tower of Hanoi, although no significant differences were found in the number of moves taken in the latter. By contrast, the control group did not show any significant improvement for most of the cognitive tasks after the reading session. CONCLUSION: Current evidence suggests that AAE may help to improve cognitive functions in ADM patients. This improvement is enhanced when the exercise is combined with cognitive games. Safe and progressive types of exercises should be promoted among ADM patients.

ANMerge: A Comprehensive and Accessible Alzheimer's Disease Patient-Level Dataset. - Birkenbihl, Colin; Westwood, Sarah; Shi, Liu; Nevado-Holgado, Alejo; Westman, Eric; Lovestone, Simon; Hofmann-Apitius, Martin (J Alzheimers Dis, 2021)
BACKGROUND: Accessible datasets are of fundamental importance to the advancement of Alzheimer's disease (AD) research. The AddNeuroMed consortium conducted a longitudinal observational cohort study with the aim to discover AD biomarkers. During this study, a broad selection of data modalities was measured including clinical assessments, magnetic resonance imaging, genotyping, transcriptomic profiling, and blood plasma proteomics. Some of the collected data were shared with third-party researchers. However, this data was incomplete, erroneous, and lacking in interoperability. OBJECTIVE: To provide the research community with an accessible, multimodal, patient-level AD cohort dataset. METHODS: We systematically addressed several limitations of the originally shared resources and provided additional unreleased data to enhance the dataset. RESULTS: In this work, we publish and describe ANMerge, a new version of the AddNeuroMed dataset. ANMerge includes multimodal data from 1,702 study participants and is accessible to the research community via a centralized portal. CONCLUSION: ANMerge is an information rich patient-level data resource that can serve as a discovery and validation cohort for data-driven AD research, such as, for example, machine learning and artificial intelligence approaches.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Datasets as Topic; Female; Gene Expression Profiling; Genotype; Humans; Magnetic Resonance Imaging; Male; Proteomics

The Association Between Homocysteine and Memory in Older Adults. - Nelson, Monica E; Andel, Ross; Nedelska, Zuzana; Martinkova, Julie; Cechova, Katerina; Marková, Hana; Matuskova, Veronika; Nikolai, Tomas; Lerch, Ondřej; Pařízková, Martina; Laczó, Jan; Vyhnálek, Martin; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Identifying modifiable risk factors for cognitive decline can reduce burden of dementia. OBJECTIVE: We examined whether homocysteine was associated with memory performance, mediated by entorhinal volume, hippocampal volume, total gray matter volume, or white matter lesions, and moderated by APOE ɛ4 allele, B vitamins, creatinine, total cholesterol, or triglycerides. METHODS: All 204 members of the Czech Brain Aging Study with subjective cognitive decline (SCD; n = 60) or amnestic mild cognitive impairment (aMCI; n = 144) who had valid data were included. Linear regression was used, followed by conditional process modeling to examine mediation and moderation. RESULTS: Controlling for age, sex, and education, higher homocysteine was related to poorer memory performance overall (b = -0.03, SE = 0.01, p = 0.017) and in participants with SCD (b = -0.06, SE = 0.03, p = 0.029), but less so in aMCI (b = -0.03, SE = 0.02, p = 0.074); though sensitivity analyses revealed a significant association when sample was reduced to aMCI patients with more complete cognitive data (who were also better functioning; b = -0.04, SE = 0.02, p = 0.022). Results were unchanged in fully adjusted models. Neither mediation by markers of brain integrity nor moderation by APOE ɛ4, B vitamins, creatinine, and cardiovascular factors were significant. Memory sub-analyses revealed that results for SCD were likely driven by non-verbal memory. The homocysteine-memory relationship was significant when hippocampal volume was below the median (b = -0.04, SE = 0.02, p = 0.046), but not at/above the median (p = 0.247). CONCLUSION: Higher homocysteine levels may adversely influence memory performance, particularly in those without cognitive impairment. Results appear to be independent of brain health, suggesting that homocysteine may represent a good target for intervention.

Cerebrospinal Fluid Amyloid-β Oligomer Levels in Patients with Idiopathic Normal Pressure Hydrocephalus. - Kawamura, Kaito; Miyajima, Masakazu; Nakajima, Madoka; Kanai, Mitsuyasu; Motoi, Yumiko; Nojiri, Shuko; Akiba, Chihiro; Ogino, Ikuko; Xu, Hanbing; Kamohara, Chihiro; Yamada, Shinya; Karagiozov, Kostadin; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The amyloid-β oligomers, consisting of 10-20 monomers (AβO10-20), have strong neurotoxicity and are associated with cognitive impairment in Alzheimer's disease (AD). However, their role in patients with idiopathic normal pressure hydrocephalus (iNPH) is poorly understood. OBJECTIVE: We hypothesized that cerebrospinal fluid (CSF) AβO10-20 accumulates in patients with iNPH, and its clearance after CSF shunting contributes to neurological improvement. We measured CSF AβO10-20 levels before and after CSF shunting in iNPH patients evaluating their diagnostic and prognostic role. METHODS: We evaluated two iNPH cohorts: "evaluation" (cohort-1) with 32 patients and "validation" (cohort-2) with 13 patients. Comparison cohorts included: 27 neurologically healthy controls (HCs), and 16 AD, 15 Parkinson's disease (PD), and 14 progressive supranuclear palsy (PSP) patients. We assessed for all cohorts CSF AβO10-20 levels and their comprehensive clinical data. iNPH cohort-1 pre-shunting data were compared with those of comparison cohorts, using cohort-2 for validation. Next, we compared cohort-1's clinical and CSF data: 1) before and after CSF shunting, and 2) increased versus decreased AβO10-20 levels at baseline, 1 and 3 years after shunting. RESULTS: Cohort-1 had higher CSF AβO10-20 levels than the HCs, PD, and PSP cohorts. This result was validated with data from cohort-2. CSF AβO10-20 levels differentiated cohort-1 from the PD and PSP groups, with an area under receiver operating characteristic curve of 0.94. AβO10-20 levels in cohort-1 decreased after CSF shunting. Patients with AβO10-20 decrease showed better cognitive outcome than those without. CONCLUSION: AβO10-20 accumulates in patients with iNPH and is eliminated by CSF shunting. AβO10-20 can be an applicable diagnostic and prognostic biomarker.

Clinical Features and Outcomes of Patients with Dementia Compared to an Aging Cohort Hospitalized During the Initial New York City COVID-19 Wave. - Harb, Amro A; Chen, RuiJun; Chase, Herbert S; Natarajan, Karthik; Noble, James M (J Alzheimers Dis, 2021)
BACKGROUND: Patients with dementia are vulnerable during the coronavirus disease 2019 (COVID-19) pandemic, yet few studies describe their hospital course and outcomes. OBJECTIVE: To describe and compare the hospital course for COVID-19 patients with dementia to an aging cohort without dementia in a large New York City academic medical center. METHODS: This was a single-center retrospective cohort study describing all consecutive patients age 65 or older with confirmed COVID-19 who presented to the emergency department or were hospitalized at New York-Presbyterian/Columbia University Irving Medical Center between March 6 and April 7, 2020. RESULTS: A total of 531 patients were evaluated, including 116 (21.8%) with previously diagnosed dementia, and 415 without dementia. Patients with dementia had higher mortality (50.0%versus 35.4%, p = 0.006); despite similar comorbidities and complications, multivariate analysis indicated the association was dependent on age, sex, comorbidities, and code status. Patients with dementia more often presented with delirium (36.2%versus 11.6%, p <  0.001) but less often presented with multiple other COVID-19 symptoms, and these findings remained after adjusting for age and sex. CONCLUSION: Hospitalized COVID-19 patients with dementia had higher mortality, but dementia was not an independent risk factor for death. These patients were approximately 3 times more likely to present with delirium but less often manifested or communicated other common COVID-19 symptoms. For this high-risk population in a worsening pandemic, understanding the unique manifestations and course in dementia and aging populations may help guide earlier diagnosis and optimize medical management.

Cognitive Effects of Aerobic Exercise in Alzheimer's Disease: A Pilot Randomized Controlled Trial. - Yu, Fang; Vock, David M; Zhang, Lin; Salisbury, Dereck; Nelson, Nathaniel W; Chow, Lisa S; Smith, Glenn; Barclay, Terry R; Dysken, Maurice; Wyman, Jean F (J Alzheimers Dis, 2021)
BACKGROUND: Aerobic exercise has shown inconsistent cognitive effects in older adults with Alzheimer's disease (AD) dementia. OBJECTIVE: To examine the immediate and longitudinal effects of 6-month cycling on cognition in older adults with AD dementia. METHODS: This randomized controlled trial randomized 96 participants (64 to cycling and 32 to stretching for six months) and followed them for another six months. The intervention was supervised, moderate-intensity cycling for 20-50 minutes, 3 times a week for six months. The control was light-intensity stretching. Cognition was assessed at baseline, 3, 6, 9, and 12 months using the AD Assessment Scale-Cognition (ADAS-Cog). Discrete cognitive domains were measured using the AD Uniform Data Set battery. RESULTS: The participants were 77.4±6.8 years old with 15.6±2.9 years of education, and 55%were male. The 6-month change in ADAS-Cog was 1.0±4.6 (cycling) and 0.1±4.1 (stretching), which were both significantly less than the natural 3.2±6.3-point increase observed naturally with disease progression. The 12-month change was 2.4±5.2 (cycling) and 2.2±5.7 (control). ADAS-Cog did not differ between groups at 6 (p = 0.386) and 12 months (p = 0.856). There were no differences in the 12-month rate of change in ADAS-Cog (0.192 versus 0.197, p = 0.967), memory (-0.012 versus -0.019, p = 0.373), executive function (-0.020 versus -0.012, p = 0.383), attention (-0.035 versus -0.033, p = 0.908), or language (-0.028 versus -0.026, p = 0.756). CONCLUSION: Exercise may reduce decline in global cognition in older adults with mild-to-moderate AD dementia. Aerobic exercise did not show superior cognitive effects to stretching in our pilot trial, possibly due to the lack of power.

Cognitive Effects of the BET Protein Inhibitor Apabetalone: A Prespecified Montreal Cognitive Assessment Analysis Nested in the BETonMACE Randomized Controlled Trial. - Cummings, Jeffrey; Schwartz, Gregory G; Nicholls, Stephen J; Khan, Aziz; Halliday, Chris; Toth, Peter P; Sweeney, Michael; Johansson, Jan O; Wong, Norman C W; Kulikowski, Ewelina; Kalantar-Zadeh, Kamyar; Lebioda, Kenneth; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Epigenetic changes may contribute importantly to cognitive decline in late life including Alzheimer's disease (AD) and vascular dementia (VaD). Bromodomain and extra-terminal (BET) proteins are epigenetic "readers" that may distort normal gene expression and contribute to chronic disorders. OBJECTIVE: To assess the effects of apabetalone, a small molecule BET protein inhibitor, on cognitive performance of patients 70 years or older participating in a randomized trial of patients at high risk for major cardiovascular events (MACE). METHODS: The Montreal Cognitive Assessment (MoCA) was performed on all patients 70 years or older at the time of randomization. 464 participants were randomized to apabetalone or placebo in the cognition sub-study. In a prespecified analysis, participants were assigned to one of three groups: MoCA score≥26 (normal performance), MoCA score 25-22 (mild cognitive impairment), and MoCA score≤21 (dementia). Exposure to apabetalone was equivalent in the treatment groups in each MoCA-defined group. RESULTS: Apabetalone was associated with an increased total MoCA score in participants with baseline MoCA score of≤21 (p = 0.02). There was no significant difference in change from baseline in the treatment groups with higher MoCA scores. In the cognition study, more patients randomized to apabetalone discontinued study drug for adverse effects (11.3% versus 7.9%). CONCLUSION: In this randomized controlled study, apabetalone was associated with improved cognition as measured by MoCA scores in those with baseline scores of 21 or less. BET protein inhibitors warrant further investigation for late life cognitive disorders.
Keywords: Aged; Cardiovascular Diseases; Cognitive Dysfunction; Epigenesis, Genetic; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Quinazolinones

Combining Multimodal Behavioral Data of Gait, Speech, and Drawing for Classification of Alzheimer's Disease and Mild Cognitive Impairment. - Yamada, Yasunori; Shinkawa, Kaoru; Kobayashi, Masatomo; Caggiano, Vittorio; Nemoto, Miyuki; Nemoto, Kiyotaka; Arai, Tetsuaki (J Alzheimers Dis, 2021)
BACKGROUND: Gait, speech, and drawing behaviors have been shown to be sensitive to the diagnosis of Alzheimer's disease (AD) and mild cognitive impairment (MCI). However, previous studies focused on only analyzing individual behavioral modalities, although these studies suggested that each of these modalities may capture different profiles of cognitive impairments associated with AD. OBJECTIVE: We aimed to investigate if combining behavioral data of gait, speech, and drawing can improve classification performance compared with the use of individual modality and if each of these behavioral data can be associated with different cognitive and clinical measures for the diagnosis of AD and MCI. METHODS: Behavioral data of gait, speech, and drawing were acquired from 118 AD, MCI, and cognitively normal (CN) participants. RESULTS: Combining all three behavioral modalities achieved 93.0% accuracy for classifying AD, MCI, and CN, and only 81.9% when using the best individual behavioral modality. Each of these behavioral modalities was statistically significantly associated with different cognitive and clinical measures for diagnosing AD and MCI. CONCLUSION: Our findings indicate that these behaviors provide different and complementary information about cognitive impairments such that classification of AD and MCI is superior to using either in isolation.
Keywords: Aged; Alzheimer Disease; Cognitive Dysfunction; Female; Gait; Humans; Male; Neuropsychological Tests; Speech

Cortical Thickness and Its Association with Clinical Cognitive and Neuroimaging Markers in Cerebral Amyloid Angiopathy. - Subotic, Arsenije; McCreary, Cheryl R; Saad, Feryal; Nguyen, Amanda; Alvarez-Veronesi, Ana; Zwiers, Angela M; Charlton, Anna; Beaudin, Andrew E; Ismail, Zahinoor; Bruce Pike, G; Smith, Eric E (J Alzheimers Dis, 2021)
BACKGROUND: Cerebral amyloid angiopathy (CAA) contributes to brain neurodegeneration and cognitive decline, but the relationship between these two processes is incompletely understood. OBJECTIVE: The purpose of this study is to examine cortical thickness and its association with cognition and neurodegenerative biomarkers in CAA. METHODS: Data were collected from the Functional Assessment of Vascular Reactivity study and the Calgary Normative Study. In total, 48 participants with probable CAA, 72 cognitively normal healthy controls, and 24 participants with mild dementia due to AD were included. Participants underwent an MRI scan, after which global and regional cortical thickness measurements were obtained using FreeSurfer. General linear models, adjusted for age and sex, were used to compare cortical thickness globally and in an AD signature region. RESULTS: Global cortical thickness was lower in CAA compared to healthy controls (mean difference (MD) -0.047 mm, 95% confidence interval (CI) -0.088, -0.005, p = 0.03), and lower in AD compared to CAA (MD -0.104 mm, 95% CI -0.165, -0.043, p = 0.001). In the AD signature region, cortical thickness was lower in CAA compared to healthy controls (MD -0.07 mm, 95% CI -0.13 to -0.01, p = 0.02). Within the CAA group, lower cortical thickness was associated with lower memory scores (R2 = 0.10; p = 0.05) and higher white matter hyperintensity volume (R2 = 0.09, p = 0.04). CONCLUSION: CAA contributes to neurodegeneration in the form of lower cortical thickness, and this could contribute to cognitive decline. Regional overlap with an AD cortical atrophy signature region suggests that co-existing AD pathology may contribute to lower cortical thickness observed in CAA.

Deaths with Dementia in Indigenous and Non-Indigenous Australians: A Nationwide Study. - Waller, Michael; Buckley, Rachel F; Masters, Colin L; Nona, Francis R; Eades, Sandra; Dobson, Annette J (J Alzheimers Dis, 2021)
BACKGROUND: The prevalence of dementia is generally reported to be higher among Indigenous peoples. OBJECTIVE: The rates and coding of dementia mortality were compared between Indigenous and non-Indigenous Australians. METHODS: De-identified individual records on causes of death for all people aged 40 years or more who died in Australia between 2006 and 2014 (n = 1,233,084) were used. There were 185,237 records with International Classification of Diseases, Tenth Revision, codes for dementia (Alzheimer's Disease, vascular dementia, or unspecified dementia) as the underlying cause of death or mentioned elsewhere on the death certificate. Death rates were compared using Poisson regression. Logistic regression was used to assess whether dementia was more likely to be classified as 'unspecified' type in Indigenous Australians. RESULTS: The rates of death with dementia were 57% higher in Indigenous Australians, compared to non-Indigenous, relative rate (RR) 1.57, 95% confidence interval (CI) (1.48, 1.66), p <  0.0001. This excess of deaths was highest at ages below 75 (RRs >  2, test for interaction p <  0.0001), and among men (test for interaction p <  0.0001). When the underreporting of Indigenous status on the death certificate was taken into account the relative rate increased to 2.17, 95% CI (2.07, 2.29). Indigenous Australians were also more likely to have their dementia coded as 'unspecified' on their death certificate (Odds Ratio 1.92, 95% CI (1.66, 2.21), p <  0.0001), compared to the non-Indigenous group. CONCLUSION: This epidemiological analysis based on population level mortality data demonstrates the higher dementia-related mortality rate for Indigenous Australians especially at younger ages.

Dementia and COVID-19, a Bidirectional Liaison: Risk Factors, Biomarkers, and Optimal Health Care. - Toniolo, Sofia; Scarioni, Marta; Di Lorenzo, Francesco; Hort, Jakub; Georges, Jean; Tomic, Svetlana; Nobili, Flavio; Frederiksen, Kristian Steen (J Alzheimers Dis, 2021)
Cognitive impairment following SARS-CoV-2 infection is being increasingly recognized as an acute and possibly also long-term sequela of the disease. Direct viral entry as well as systemic mechanisms such as cytokine storm are thought to contribute to neuroinflammation in these patients. Biomarkers of COVID-19-induced cognitive impairment are currently lacking, but there is some limited evidence that SARS-CoV-2 could preferentially target the frontal lobes, as suggested by behavioral and dysexecutive symptoms, fronto-temporal hypoperfusion on MRI, EEG slowing in frontal regions, and frontal hypometabolism on 18F-FDG-PET. Possible confounders include cognitive impairment due to hypoxia and mechanical ventilation and post-traumatic stress disorder. Conversely, patients already suffering from dementia, as well as their caregivers, have been greatly impacted by the disruption of their care caused by COVID-19. Patients with dementia have experienced worsening of cognitive, behavioral, and psychological symptoms, and the rate of COVID-19-related deaths is disproportionately high among cognitively impaired people. Multiple factors, such as difficulties in remembering and executing safeguarding procedures, age, comorbidities, residing in care homes, and poorer access to hospital standard of care play a role in the increased morbidity and mortality. Non-pharmacological interventions and new technologies have shown a potential for the management of patients with dementia, and for the support of their caregivers.
Keywords: Alzheimer Disease; Biomarkers; Brain; Cognitive Dysfunction; Comorbidity; COVID-19; Humans; Neuroimaging; Neuroimmunomodulation; Patient Care; SARS-CoV-2

Event-Related Potentials, Inhibition, and Risk for Alzheimer's Disease Among Cognitively Intact Elders. - Elverman, Kathleen H; Paitel, Elizabeth R; Figueroa, Christina M; McKindles, Ryan J; Nielson, Kristy A (J Alzheimers Dis, 2021)
BACKGROUND: Despite advances in understanding Alzheimer's disease (AD), prediction of AD prior to symptom onset remains severely limited, even when primary risk factors such as the apolipoprotein E (APOE) ɛ4 allele are known. OBJECTIVE: Although executive dysfunction is highly prevalent and is a primary contributor to loss of independence in those with AD, few studies have examined neural differences underlying executive functioning as indicators of risk for AD prior to symptom onset, when intervention might be effective. METHODS: This study examined event-related potential (ERP) differences during inhibitory control in 44 cognitively intact older adults (20 ɛ4+, 24 ɛ4-), relative to 41 young adults. All participants completed go/no-go and stop-signal tasks. RESULTS: Overall, both older adult groups exhibited slower reaction times and longer ERP latencies compared to young adults. Older adults also had generally smaller N200 and P300 amplitudes, except at frontal electrodes and for N200 stop-signal amplitudes, which were larger in older adults. Considered with intact task accuracy, these findings suggest age-related neural compensation. Although ɛ4 did not distinguish elders during go or no-go tasks, this study uniquely showed that the more demanding stop-signal task was sensitive to ɛ4 differences, despite comparable task and neuropsychological performance with non-carriers. Specifically, ɛ4+ elders had slower frontal N200 latency and larger N200 amplitude, which was most robust at frontal sites, compared with ɛ4-. CONCLUSION: N200 during a stop-signal task is sensitive to AD risk, prior to any evidence of cognitive dysfunction, suggesting that stop-signal ERPs may be an important protocol addition to neuropsychological testing.

Five-Year Change in Body Mass Index Predicts Conversion to Mild Cognitive Impairment or Dementia Only in APOE ɛ4 Allele Carriers. - Kadey, Kylie R; Woodard, John L; Moll, Allison C; Nielson, Kristy A; Smith, J Carson; Durgerian, Sally; Rao, Stephen M (J Alzheimers Dis, 2021)
BACKGROUND: Body mass index (BMI) has been identified as an important modifiable lifestyle risk factor for dementia, but less is known about how BMI might interact with Apolipoprotein E ɛ4 (APOE ɛ4) carrier status to predict conversion to mild cognitive impairment (MCI) and dementia. OBJECTIVE: The aim of this study was to investigate the interaction between APOE ɛ4 status and baseline (bBMI) and five-year BMI change (ΔBMI) on conversion to MCI or dementia in initially cognitively healthy older adults. METHODS: The associations between bBMI, ΔBMI, APOE ɛ4 status, and conversion to MCI or dementia were investigated among 1,289 cognitively healthy elders from the National Alzheimer's Coordinating Center (NACC) database. RESULTS: After five years, significantly more carriers (30.6%) converted to MCI or dementia than noncarriers (17.6%), p <  0.001, OR = 2.06. Neither bBMI (OR = 0.99, 95%CI = 0.96-1.02) nor the bBMI by APOE interaction (OR = 1.02, 95%CI = 0.96-1.08) predicted conversion. Although ΔBMI also did not significantly predict conversion (OR = 0.90, 95%CI = 0.78-1.04), the interaction between ΔBMI and carrier status was significant (OR = 0.72, 95%CI = 0.53-0.98). For carriers only, each one-unit decline in BMI over five years was associated with a 27%increase in the odds of conversion (OR = 0.73, 95%CI = 0.57-0.94). CONCLUSION: A decline in BMI over five years, but not bBMI, was strongly associated with conversion to MCI or dementia only for APOE ɛ4 carriers. Interventions and behaviors aimed at maintaining body mass may be important for long term cognitive health in older adults at genetic risk for AD.

Is the Frontal Lobe the Primary Target of SARS-CoV-2? - Toniolo, Sofia; Di Lorenzo, Francesco; Scarioni, Marta; Frederiksen, Kristian Steen; Nobili, Flavio (J Alzheimers Dis, 2021)
Acute delirium and other neuropsychiatric symptoms have frequently been reported in COVID-19 patients and are variably referred to as acute encephalopathy, COVID-19 encephalopathy, SARS-CoV-2 encephalitis, or steroid-responsive encephalitis. COVID-19 specific biomarkers of cognitive impairment are currently lacking, but there is some evidence that SARS-CoV-2 could preferentially and directly target the frontal lobes, as suggested by behavioral and dysexecutive symptoms, fronto-temporal hypoperfusion on MRI, EEG slowing in frontal regions, and frontal hypometabolism on 18F-FDG-PET imaging. We suggest that an inflammatory parainfectious process targeting preferentially the frontal lobes (and/or frontal networks) could be the underlying cause of these shared clinical, neurophysiological, and imaging findings in COVID-19 patients. We explore the biological mechanisms and the clinical biomarkers that might underlie such disruption of frontal circuits and highlight the need of standardized diagnostic procedures to be applied when investigating patients with these clinical findings. We also suggest the use of a unique label, to increase comparability across studies.
Keywords: Acute Febrile Encephalopathy; Biomarkers; COVID-19; Delirium; Electroencephalography; Frontal Lobe; Humans; Magnetic Resonance Imaging; Nerve Net; SARS-CoV-2; Virulence

Hippocampal Functional Connectivity and Memory Performance After Exercise Intervention in Older Adults with Mild Cognitive Impairment. - Won, Junyeon; Callow, Daniel D; S Pena, Gabriel; Jordan, Leslie S; Arnold-Nedimala, Naomi A; Nielson, Kristy A; Smith, J Carson (J Alzheimers Dis, 2021)
BACKGROUND: Exercise training (ET) has neuroprotective effects in the hippocampus, a key brain region for memory that is vulnerable to age-related dysfunction. OBJECTIVE: We investigated the effects of ET on functional connectivity (FC) of the hippocampus in older adults with mild cognitive impairment (MCI) and a cognitively normal (CN) control group. We also assessed whether the ET-induced changes in hippocampal FC (Δhippocampal-FC) are associated with changes in memory task performance (Δmemory performance). METHODS: 32 older adults (77.0±7.6 years; 16 MCI and 16 CN) participated in the present study. Cardiorespiratory fitness tests, memory tasks (Rey Auditory Verbal Learning Test (RAVLT) and Logical Memory Test (LM)), and resting-state fMRI were administered before and after a 12-week walking ET intervention. We utilized a seed-based correlation analysis using the bilateral anterior and posterior hippocampi as priori seed regions of interest. The associations of residualized ET-induced Δhippocampal-FC and Δmemory performance were assessed using linear regression. RESULTS: There were significant improvements in RAVLT Trial 1 and LM test performance after ET across participants. At baseline, MCI, compared to CN, demonstrated significantly lower posterior hippocampal FC. ET was associated with increased hippocampal FC across groups. Greater ET-related anterior and posterior hippocampal FC with right posterior cingulate were associated with improved LM recognition performance in MCI participants. CONCLUSION: Our findings indicate that hippocampal FC is significantly increased following 12-weeks of ET in older adults and, moreover, suggest that increased hippocampal FC may reflect neural network plasticity associated with ET-related improvements in memory performance in individuals diagnosed with MCI.

Impact of 40 Hz Transcranial Alternating Current Stimulation on Cerebral Tau Burden in Patients with Alzheimer's Disease: A Case Series. - Dhaynaut, Maeva; Sprugnoli, Giulia; Cappon, Davide; Macone, Joanna; Sanchez, Justin S; Normandin, Marc; Guehl, Nicolas; Koch, Giacomo; Paciorek, Rachel; Connor, Ann; Press, Daniel; Johnson, Keith; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) is characterized by diffuse amyloid-β (Aβ) and phosphorylated Tau (p-Tau) aggregates as well as neuroinflammation. Exogenously-induced 40 Hz gamma oscillations have been showing to reduce Aβ and p-Tau deposition presumably via microglia activation in AD mouse models. OBJECTIVE: We aimed to translate preclinical data on gamma-induction in AD patients by means of transcranial alternating current stimulation (tACS). METHODS: Four participants with mild-to-moderate AD received 1 h of daily 40 Hz (gamma) tACS for 4 weeks (Monday to Friday) targeting the bitemporal lobes (20 h treatment duration). Participant underwent Aβ, p-Tau, and microglia PET imaging with [11C]-PiB, [18F]-FTP, and [11C]-PBR28 respectively, before and after the intervention along with electrophysiological assessment. RESULTS: No adverse events were reported, and an increase in gamma spectral power on EEG was observed after the treatment. [18F]-FTP PET revealed a significant decrease over 2% of p-Tau burden in 3/4 patients following the tACS treatment, primarily involving the temporal lobe regions targeted by tACS and especially mesial regions (e.g., entorhinal cortex). The amount of intracerebral Aβ as measured by [11C]-PiB was not significantly influenced by tACS, whereas 1/4 reported a significant decrease of microglia activation as measured by [11C]-PBR28. CONCLUSION: tACS seems to represent a safe and feasible option for gamma induction in AD patients, with preliminary evidence of a possible effect on protein clearance partially mimicking what is observed in animal models. Longer interventions and placebo control conditions are needed to fully evaluate the potential for tACS to slow disease progression.

Impacts of Iron Metabolism Dysregulation on Alzheimer's Disease. - Jouini, Najla; Saied, Zakaria; Ben Sassi, Samia; Nebli, Fatma; Messaoud, Taieb; Hentati, Faycel; Belal, Samir (J Alzheimers Dis, 2021)
BACKGROUND: Iron plays an important role in maintaining cell survival, with normal iron trafficking known to be regulated by the ceruloplasmin-transferrin (Cp-Tf) antioxidant system. Disruption to this system is thought to be detrimental to normal brain function. OBJECTIVE: To determine whether an imbalance of iron and the proteins involved in its metabolism (ceruloplasmin and transferrin) are linked to Alzheimer's disease (AD) and to the expression of amyloid-beta (Aβ) peptide 1-42 (Aβ 1-42), which is a major species of Aβ, and the most toxic. METHODS: We evaluated the concentrations of iron, calcium, magnesium, and Aβ 1-42 in the cerebrospinal fluid (CSF) of patients with AD and cognitively normal controls. Correlations between the components of the Cp-Tf antioxidant system in plasma were studied to determine the role of peripheral blood in the onset and/or development of AD. We used commercial ELISA immunoassays to measure Aβ 1-42, immunoturbidimetry to quantify ceruloplasmin and transferrin, and colorimetry to quantify iron, calcium, and magnesium. RESULTS: We found that the AD group had lower CSF concentrations of Aβ 1-42 (p <  0.001) and calcium (p <  0.001), but a higher CSF concentration of iron (p <  0.001). Significantly lower plasma concentrations of ceruloplasmin (p = 0.003), transferrin (mean, p <  0.001), and iron (p <  0.001) were observed in the AD group than in cognitively normal adults. Moreover, we found a strong interdependence between most of these components. CONCLUSION: Iron dyshomeostasis has a crucial role in the onset of AD and/or its development. Correcting metal misdistribution is an appealing therapeutic strategy for AD.

Incremental Healthcare Utilization and Cost Burden of Comorbid Insomnia in Alzheimer's Disease Patients. - Qureshi, Zaina P; Thiel, Ellen; Nelson, James; Khandker, Rezaul (J Alzheimers Dis, 2021)
BACKGROUND: Insomnia is associated with worsened clinical outcomes among Alzheimer's disease dementia (AD) patients, increased caregiver burden, and healthcare utilization. OBJECTIVE: This study aimed to characterize the incremental healthcare burden of insomnia in AD using real-world data. METHODS: A retrospective observational study was conducted on AD patients selected from the IBM® MarketScan Commercial and Medicare Supplemental Databases. AD patients with claims-based evidence of insomnia were direct matched to a non-insomnia cohort based on demographic factors. Healthcare utilization and associated costs were assessed for a 12-month follow-up period. RESULTS: A total of 3,500 insomnia AD patients and 9,884 non-insomnia AD patients were analyzed. The insomnia cohort had a higher comorbidity burden at baseline (mean score on Charlson Comorbidity Index 2.5 versus 2.2, p < 0.001) and higher proportions of patients with baseline diagnoses for other conditions including depression: 40%, insomnia cohort versus 25%, non-insomnia (p < 0.001). AD patients with insomnia were more likely to have a claim for inpatient hospitalizations (39.8%versus 32.3%), emergency room services (56.4%versus 48.0%), and skilled-nursing services (42.6%versus 31.9%) (all p < 0.05). Mean total annual healthcare costs during the 12-month follow-up period were significantly higher among AD patients with insomnia as compared to those without. (Mean costs: $37,356 versus $27,990, p < 0.001). CONCLUSION: AD patients with comorbid insomnia are more likely to use higher-cost healthcare services such as inpatient hospitalization, and skilled nursing, and have higher total healthcare costs. This real-world analysis provides evidence that AD disease management should consider proper treatment of comorbid insomnia due to the incremental burden and cost implications.
Keywords: Aged, 80 and over; Alzheimer Disease; Comorbidity; Databases, Factual; Female; Health Care Costs; Humans; Male; Medicare; Patient Acceptance of Health Care; Retrospective Studies; Sleep Initiation and Maintenance Disorders; United States

Inhibitory Fcγ Receptor and Paired Immunoglobulin Type 2 Receptor Alpha Genotypes in Alzheimer's Disease. - Pandey, Janardan P; Namboodiri, Aryan M; Nietert, Paul J; Barnes, Lisa L; Bennett, David A (J Alzheimers Dis, 2021)
We investigated whether FCGRIIB (rs1050501 C/T) and PILRA (rs1859788 A/G) genotypes contributed to the development of Alzheimer's disease (AD). We genotyped 209 African American (AA) and 638 European American participants for the FCGRIIB and PILRA alleles. In the AA cohort, subjects homozygous for the C allele of FCGRIIB were more than 4 times as likely to develop AD as those homozygous for the alternative T allele. This SNP also interacted with PILRA: participants who were the carriers of the FCGRIIB C allele and PILRA A allele were 3 times as likely to develop AD as those who lacked these alleles.

Iron Responsive Element-Mediated Responses to Iron Dyshomeostasis in Alzheimer's Disease. - Hin, Nhi; Newman, Morgan; Pederson, Stephen; Lardelli, Michael (J Alzheimers Dis, 2021)
BACKGROUND: Iron trafficking and accumulation is associated with Alzheimer's disease (AD) pathogenesis. However, the role of iron dyshomeostasis in early disease stages is uncertain. Currently, gene expression changes indicative of iron dyshomeostasis are not well characterized, making it difficult to explore these in existing datasets. OBJECTIVE: To identify sets of genes predicted to contain iron responsive elements (IREs) and use these to explore possible iron dyshomeostasis-associated gene expression responses in AD. METHODS: Comprehensive sets of genes containing predicted IRE or IRE-like motifs in their 3' or 5' untranslated regions (UTRs) were identified in human, mouse, and zebrafish reference transcriptomes. Further analyses focusing on these genes were applied to a range of cultured cell, human, mouse, and zebrafish gene expression datasets. RESULTS: IRE gene sets are sufficiently sensitive to distinguish not only between iron overload and deficiency in cultured cells, but also between AD and other pathological brain conditions. Notably, changes in IRE transcript abundance are among the earliest observable changes in zebrafish familial AD (fAD)-like brains, preceding other AD-typical pathologies such as inflammatory changes. Unexpectedly, while some IREs in the 3' untranslated regions of transcripts show significantly increased stability under iron deficiency in line with current assumptions, many such transcripts instead display decreased stability, indicating that this is not a generalizable paradigm. CONCLUSION: Our results reveal IRE gene expression changes as early markers of the pathogenic process in fAD and are consistent with iron dyshomeostasis as an important driver of this disease. Our work demonstrates how differences in the stability of IRE-containing transcripts can be used to explore and compare iron dyshomeostasis-associated gene expression responses across different species, tissues, and conditions.

Mortality After Ischemic Stroke in Patients with Alzheimer's Disease Dementia and Other Dementia Disorders. - Zupanic, Eva; von Euler, Mia; Winblad, Bengt; Xu, Hong; Secnik, Juraj; Kramberger, Milica Gregoric; Religa, Dorota; Norrving, Bo; Garcia-Ptacek, Sara (J Alzheimers Dis, 2021)
BACKGROUND: Stroke and dementia are interrelated diseases and risk for both increases with age. Even though stroke incidence and age-standardized death rates have decreased due to prevention of stroke risk factors, increased utilization of reperfusion therapies, and other changes in healthcare, the absolute numbers are increasing due to population growth and aging. OBJECTIVE: To analyze predictors of death after stroke in patients with dementia and investigate possible time and treatment trends. METHODS: A national longitudinal cohort study 2007-2017 using Swedish national registries. We compared 12,629 ischemic stroke events in patients with dementia with matched 57,954 stroke events in non-dementia controls in different aspects of patient care and mortality. Relationship between dementia status and dementia type (Alzheimer's disease and mixed dementia, vascular dementia, other dementias) and death was analyzed using Cox regressions. RESULTS: Differences in receiving intravenous thrombolysis between patients with and without dementia disappeared after the year 2015 (administered to 11.1% dementia versus 12.3% non-dementia patients, p = 0.117). One year after stroke, nearly 50% dementia and 30% non-dementia patients had died. After adjustment for demographics, mobility, nursing home placement, and comorbidity index, dementia was an independent predictor of death compared with non-dementia patients (HR 1.26 [1.23-1.29]). CONCLUSION: Dementia before ischemic stroke is an independent predictor of death. Over time, early and delayed mortality in patients with dementia remained increased, regardless of dementia type. Patients with≤80 years with prior Alzheimer's disease or mixed dementia had higher mortality rates after stroke compared to patients with prior vascular dementia.
Keywords: Aged; Aged, 80 and over; Comorbidity; Dementia; Female; Fibrinolytic Agents; Humans; Incidence; Ischemic Stroke; Male; Registries; Survival Rate; Sweden; Thrombolytic Therapy

A Novel Cognitive Function Scale Using Functional Near-Infrared Spectroscopy for Evaluating Cognitive Dysfunction. - Nakamura, Shin; Yomota, Satoshi; Ito, Hitomi; Akinaga, Nobuyuki; Hori, Ayaka; Chinomi, Kenta; Suzuki, Hideaki; Uchida, Kazuhiko; Asada, Takashi (J Alzheimers Dis, 2021)
BACKGROUND: Maintaining cognitive function is integral to a healthy social life in the aged. Although neuropsychological tests and brain imaging methods can assess cognitive dysfunction, these techniques are subjective, psychologically burdensome, and cannot be conducted easily. OBJECTIVE: We sought to develop an objective, low-burden novel cognitive function scale based on functional near-infrared spectroscopy (fNIRS) of hemodynamic changes in the cerebral cortex during daily task performance. METHODS: A total of 63 participants (aged 60-80 years) identified as non-dementia controls (NDC) or with mild cognitive impairment (MCI) were recruited and randomly assigned to training and test data sets. Explanatory variables were hemodynamic responses during low-burden sensory and simple tasks without higher-order brain functioning. RESULTS: A logistic regression analysis of the fNIRS index in NDCs and MCI patients revealed area under the curve, sensitivity, specificity, and holdout results of 0.98, 94%, 88%, and 62% respectively. Correlation between fNIRS index and MCI odds showed positive linearity (R2 = 0.96). CONCLUSION: Positive correlation between the fNIRS index and MCI odds indicated effectiveness of this fNIRS measurement. Although additional experiments are necessary, the fNIRS index representing degree of cognitive decline can be an onsite monitoring tool to assess cognitive status.

Plasma Biomarkers of Alzheimer's Disease in African Americans. - Deniz, Kaancan; Ho, Charlotte C G; Malphrus, Kimberly G; Reddy, Joseph S; Nguyen, Thuy; Carnwath, Troy P; Crook, Julia E; Lucas, John A; Graff-Radford, Neill R; Carrasquillo, Minerva M; Ertekin-Taner, Nilufer (J Alzheimers Dis, 2021)
BACKGROUND/OBJECTIVE: The aim of this study was to determine if plasma concentrations of 5 surrogate markers of Alzheimer's disease (AD) pathology and neuroinflammation are associated with disease status in African Americans. METHODS: We evaluated 321 African Americans (159 AD, 162 controls) from the Florida Consortium for African-American Alzheimer's Disease Studies (FCA3DS). Five plasma proteins reflecting AD neuropathology or inflammation (Aβ42, tau, IL6, IL10, TNFα) were tested for associations with AD, age, sex, APOE and MAPT genotypes, and for pairwise correlations. RESULTS: Plasma tau levels were higher in AD when adjusted for biological and technical covariates. APOEɛ4 was associated with lower plasma Aβ42 and tau levels. Older age was associated with higher plasma Aβ42, tau, and TNFα. Females had lower IL10 levels. Inflammatory proteins had strong pairwise correlations amongst themselves and with Aβ42. CONCLUSION: We identified effects of demographic and genetic variants on five potential plasma biomarkers in African Americans. Plasma inflammatory biomarkers and Aβ42 may reflect correlated pathologies and elevated plasma tau may be a biomarker of AD in this population.
Keywords: African Americans; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Case-Control Studies; Female; Humans; Interleukin-10; Interleukin-6; Male; Middle Aged; Peptide Fragments; tau Proteins; Tumor Necrosis Factor-alpha

Porphyromonas Gingivalis Infection Induces Synaptic Failure via Increased IL-1β Production in Leptomeningeal Cells. - Huang, Wanyi; Zeng, Fan; Gu, Yebo; Jiang, Muzhou; Zhang, Xinwen; Yan, Xu; Kadowaki, Tomoko; Mizutani, Shinsuke; Kashiwazaki, Haruhiko; Ni, Junjun; Wu, Zhou (J Alzheimers Dis, 2021)
BACKGROUND: Studies have reported that synaptic failure occurs before the Alzheimer's disease (AD) onset. The systemic Porphyromonas gingivalis (P. gingivalis) infection is involved in memory decline. We previously showed that leptomeningeal cells, covering the brain, activate glial cells by releasing IL-1β in response to systemic inflammation. OBJECTIVE: In the present study, we focused on the impact of leptomeningeal cells on neurons during systemic P. gingivalis infection. METHODS: The responses of leptomeningeal cells and cortical neurons to systemic P. gingivalis infection were examined in 15-month-old mice. The mechanism of IL-1β production by P. gingivalis infected leptomeningeal cells was examined, and primary cortical neurons were treated with P. gingivalis infected leptomeningeal cells condition medium (Pg LCM). RESULTS: Systemic P. gingivalis infection increased the expression of IL-1β in leptomeninges and reduced the synaptophysin (SYP) expression in leptomeninges proximity cortex in mice. Leptomeningeal cells phagocytosed P. gingivalis resulting in lysosomal rupture and Cathepsin B (CatB) leakage. Leaked CatB mediated NLRP3 inflammasome activation inducing IL-1β secretion in leptomeningeal cells. Pg LCM decreased the expression of synaptic molecules, including SYP, which was inhibited by an IL-1 receptor antagonist pre-treatment. CONCLUSION: These observations demonstrate that P. gingivalis infection is involved in synaptic failure by inducing CatB/NLRP3 inflammasome-mediated IL-1β production in leptomeningeal cells. The periodontal bacteria-induced synaptic damage may accelerate the onset and cognitive decline of AD.

Porphyromonas gingivalis Outer Membrane Vesicles as the Major Driver of and Explanation for Neuropathogenesis, the Cholinergic Hypothesis, Iron Dyshomeostasis, and Salivary Lactoferrin in Alzheimer's Disease. - Nara, Peter L; Sindelar, Daniel; Penn, Marc S; Potempa, Jan; Griffin, W Sue T (J Alzheimers Dis, 2021)
Porphyromonas gingivalis (Pg) is a primary oral pathogen in the widespread biofilm-induced "chronic" multi-systems inflammatory disease(s) including Alzheimer's disease (AD). It is possibly the only second identified unique example of a biological extremophile in the human body. Having a better understanding of the key microbiological and genetic mechanisms of its pathogenesis and disease induction are central to its future diagnosis, treatment, and possible prevention. The published literature around the role of Pg in AD highlights the bacteria's direct role within the brain to cause disease. The available evidence, although somewhat adopted, does not fully support this as the major process. There are alternative pathogenic/virulence features associated with Pg that have been overlooked and may better explain the pathogenic processes found in the "infection hypothesis" of AD. A better explanation is offered here for the discrepancy in the relatively low amounts of "Pg bacteria" residing in the brain compared to the rather florid amounts and broad distribution of one or more of its major bacterial protein toxins. Related to this, the "Gingipains Hypothesis", AD-related iron dyshomeostasis, and the early reduced salivary lactoferrin, along with the resurrection of the Cholinergic Hypothesis may now be integrated into one working model. The current paper suggests the highly evolved and developed Type IX secretory cargo system of Pg producing outer membrane vesicles may better explain the observed diseases. Thus it is hoped this paper can provide a unifying model for the sporadic form of AD and guide the direction of research, treatment, and possible prevention.
Keywords: Alzheimer Disease; Anti-Infective Agents; Bacterial Outer Membrane Proteins; Bacteroidaceae Infections; Brain; Cholinergic Agents; Extremophiles; Humans; Iron; Lactoferrin; Porphyromonas gingivalis; Saliva

Promoting Successful Cognitive Aging: A Ten-Year Update. - Krivanek, Taylor J; Gale, Seth A; McFeeley, Brittany M; Nicastri, Casey M; Daffner, Kirk R (J Alzheimers Dis, 2021)
A decade has passed since we published a comprehensive review in this journal addressing the topic of promoting successful cognitive aging, making this a good time to take stock of the field. Because there have been limited large-scale, randomized controlled trials, especially following individuals from middle age to late life, some experts have questioned whether recommendations can be legitimately offered about reducing the risk of cognitive decline and dementia. Despite uncertainties, clinicians often need to at least make provisional recommendations to patients based on the highest quality data available. Converging lines of evidence from epidemiological/cohort studies, animal/basic science studies, human proof-of-concept studies, and human intervention studies can provide guidance, highlighting strategies for enhancing cognitive reserve and preventing loss of cognitive capacity. Many of the suggestions made in 2010 have been supported by additional research. Importantly, there is a growing consensus among major health organizations about recommendations to mitigate cognitive decline and promote healthy cognitive aging. Regular physical activity and treatment of cardiovascular risk factors have been supported by all of these organizations. Most organizations have also embraced cognitively stimulating activities, a heart-healthy diet, smoking cessation, and countering metabolic syndrome. Other behaviors like regular social engagement, limiting alcohol use, stress management, getting adequate sleep, avoiding anticholinergic medications, addressing sensory deficits, and protecting the brain against physical and toxic damage also have been endorsed, although less consistently. In this update, we review the evidence for each of these recommendations and offer practical advice about behavior-change techniques to help patients adopt brain-healthy behaviors.
Keywords: Cognition; Cognitive Aging; Diet, Healthy; Exercise; Healthy Aging; Healthy Lifestyle; Humans

Rats Display Sexual Dimorphism in Phosphorylation of Brain Tau with Age. - Niu, Jiahui; Iqbal, Khalid; Liu, Fei; Hu, Wen (J Alzheimers Dis, 2021)
BACKGROUND: Women have a two-fold higher risk than men to Alzheimer's disease (AD) at midlife. Larger brain tau burden was consistently shown in older women than age-matched men. The biological basis for this gender disparity remains elusive. OBJECTIVE: We sought to know whether tau expression and phosphorylation physiologically differ between males and females. METHODS: We used western blots and immunohistochemistry to compare the levels of total tau and phosphorylated tau in the hippocampus and entorhinal cortex (EC) between sexes in Wistar rats at 40 days, and 8 and 20 months of age. RESULTS: We detected no statistically significant difference in total tau, 3R-tau, and 4R-tau between sexes. However, female rats exhibited lower levels of tau unphosphorylated at the Tau-1 site at 40 days of age. At 8 months of age, females showed higher levels of tau phosphorylated at Ser190, Ser387, and Ser395 (Ser199, Ser396, and Ser404 of human tau, respectively) than males in EC. At 20 months of age, both brain regions of female rats consistently showed higher levels than males of tau phosphorylated at Ser253, Ser387, PHF-1 (Ser387/395), and Ser413 sites, which correspond to Ser262, Ser396, Ser396/404, and Ser422 of human tau, respectively. CONCLUSION: Rats of both sexes have comparable levels of total tau, 3R-tau, and 4R-tau, whereas females exhibit higher levels of tau phosphorylated at multiple sites that are implicated in AD tau pathology, indicating a sexual dimorphism of tau phosphorylation that may potentially underlie the disparity in brain tau burden and risk for AD between sexes.

Relation of a Socioeconomic Index with Cognitive Function and Neuroimaging in Hypertensive Individuals. - Paradela, Regina Silva; Ferreira, Naomi Vidal; Nucci, Mariana Penteado; Cabella, Brenno; Martino, Luiza Menoni; Torres, Laura Aló; Costa, Danielle Irigoyen da; Consolim-Colombo, Fernanda Marciano; Suemoto, Claudia Kimie; Irigoyen, Maria Claudia (J Alzheimers Dis, 2021)
BACKGROUND: Socioeconomic factors are important contributors to brain health. However, data from developing countries (where social inequalities are the most prominent) are still scarce, particularly about hypertensive individuals. OBJECTIVE: To evaluate the relationship between socioeconomic index, cognitive function, and cortical brain volume, as well as determine whether white matter hyperintensities are mediators of the association of the socioeconomic index with cognitive function in hypertensive individuals. METHODS: We assessed 92 hypertensive participants (mean age = 58±8.6 years, 65.2%female). Cognitive evaluation and neuroimaging were performed and clinical and sociodemographic data were collected using questionnaires. A socioeconomic index was created using education, income, occupation (manual or non-manual work), and race. The associations of the socioeconomic index with cognitive performance and brain volume were investigated using linear regression models adjusted for age, sex, time of hypertension since diagnosis, and comorbidities. A causal mediation analysis was also conducted. RESULTS: Better socioeconomic status was associated with better visuospatial ability, executive function, and global cognition. We found associations between a better socioeconomic index and a higher parietal lobe volume. White matter hyperintensities were also not mediators in the relationship between the socioeconomic index and cognitive performance. CONCLUSION: Socioeconomic disadvantages are associated with worse cognitive performance and brain volume in individuals with hypertension.

Relationships Between Cognition and Neuropathological Tau in Alzheimer's Disease Assessed by 18F Flortaucipir PET. - Devous, Michael D; Fleisher, Adam S; Pontecorvo, Michael J; Lu, Ming; Siderowf, Andrew; Navitsky, Michael; Kennedy, Ian; Southekal, Sudeepti; Harris, Thomas S; Mintun, Mark A (J Alzheimers Dis, 2021)
BACKGROUND: Tau neurofibrillary tangle burden increases with Alzheimer's disease (AD) stage and correlates with degree of cognitive impairment. Tau PET imaging could facilitate understanding the relationship between tau pathology and cognitive impairment. OBJECTIVE: Evaluate the relationship between 18F flortaucipir uptake patterns and cognition across multiple cognitive domains. METHODS: We acquired flortaucipir PET scans in 84 amyloid-positive control, mild cognitive impairment (MCI), and AD subjects. Flortaucipir standardized uptake value ratio (SUVr) values were obtained from a neocortical volume of interest (VOI), a precuneus VOI, and VOIs defined by the correlation between flortaucipir SUVr images and domain-specific cognitive tests. Cognitive assessments included Mini-Mental State Exam (MMSE), Alzheimer's Disease Assessment Scale-Cognitive Subscale (ADAS-cog), and a neuropsychological test battery (i.e., Wechsler Memory Scale-Revised Logical Memory (WMS-R), Trail Making Test, Boston Naming Test, Digit Symbol Substitution Test, Animal List Generation, WMS-R Digit Span, American National Adult Reading Test, Clock Drawing Test, Judgment of Line Orientation, and WMS-R Logical Memory II (Delayed Recall)) and the Functional Activities Questionnaire (FAQ). Correlation analyses compared regional and voxel-wise VOIs to cognitive scores. RESULTS: Subjects included 5 controls, 47 MCI, and 32 AD subjects. Significant correlations were seen between both flortaucipir and florbetapir SUVrs and MMSE, ADAS-Cog, and FAQ. Cognitive impairment was associated with increased flortaucipir uptake in regionally specific patterns consistent with the neuroanatomy underlying specific cognitive tests. CONCLUSION: Flortaucipir SUVr values demonstrated significant inverse correlations with cognitive scores in domain-specific patterns. Findings support the hypothesis that PET imaging of neuropathologic tau deposits may reflect underlying neurodegeneration in AD.

Relevance of a Truncated PRESENILIN 2 Transcript to Alzheimer's Disease and Neurodegeneration. - Moussavi Nik, Seyyed Hani; Porter, Tenielle; Newman, Morgan; Bartlett, Benjamin; Khan, Imran; Sabale, Miheer; Eccles, Melissa; Woodfield, Amy; Groth, David; Doré, Vincent; Villemagne, Victor L; Masters, Colin L; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The PRESENILIN genes (PSEN1, PSEN2) encoding for their respective proteins have critical roles in many aspects of Alzheimer's disease (AD) pathogenesis. The PS2V transcript of PSEN2 encodes a truncated protein and is upregulated in AD brains; however, its relevance to AD and disease progression remains to be determined. OBJECTIVE: Assess transcript levels in postmortem AD and non-AD brain tissue and in lymphocytes collected under the Australian Imaging Biomarker and Lifestyle (AIBL) study. METHODS: Full length PSEN2 and PS2V transcript levels were assessed by quantitative digital PCR in postmortem brain tissue (frontal cortex and hippocampus) from control, AD, frontotemporal dementia (FTD), and Lewy body dementia (LBD). Transcript levels were also assessed in lymphocytes obtained from the Perth subset of the AIBL study (n = 160). Linear regression analysis was used to assess correlations between transcript copy number and brain volume and neocortical amyloid load. RESULTS: PS2V levels increased in AD postmortem brain but PS2V was also present at significant levels in FTD and LBD brains. PS2V transcript was detected in lymphocytes and PS2V/PSEN2 ratios were increased in mild cognitive impairment (p = 0.024) and AD (p = 0.019) groups compared to control group. Increased ratios were significantly correlated with hippocampal volumes only (n = 62, β= -0.269, p = 0.03). CONCLUSION: Taken together, these results suggest that PS2V may be a marker of overall neurodegeneration.

Research Attitudes and Interest Among Elderly Latinxs: The Impact of a Collaborative Video and Community Peers. - Sewell, Margaret C; Neugroschl, Judith; Umpierre, Mari; Chin, Shehan; Zhu, Carolyn W; Velasco, Nelly; Gonzalez, Sabrina; Acabá-Berrocal, Alexandra; Bianchetti, Luca; Silva, Gabriela; Collazo, Alma; Sano, Mary (J Alzheimers Dis, 2021)
BACKGROUND: Latinx elders are underrepresented in dementia research. In a previous study we assessed research attitudes in urban minority elders and found a significant minority expressed neutral to negative attitudes relating to trust, safety, and personal responsibility to help research. OBJECTIVE: To assess the impact of a composite intervention on attitudes toward research and research participation among elderly Latinx. The intervention was a collaboratively produced research participation video shown during presentations with our elderly community advisory board (CAB) as co-presenters. METHODS: The video was created by the ADRC and CAB. All senior center attendees were eligible to participate. Afterwards, the Research Attitudes Questionnaire (RAQ) and a brief questionnaire on the impact of the video were administered. Using Wilcoxon Rank Sum Tests, Chi Square, and OLS regressions, RAQ responses were compared to those from a historical cohort from similar centers. RESULTS: 74 in the "Historical Cohort 1" and 104 in "Intervention Cohort 2" were included. RAQ total score was higher in Cohort 2 than Cohort 1 (28.5 versus 26.1, p <  0.05) after controlling for age, education, and country of origin. In response to the question "Has the video influenced your willingness and interest to participate in research", 88.7%of the participants in Cohort 2 reported being "more" or "much more" interested in research. CONCLUSION: Tailoring community research recruitment programs to include relatable peers using novel recruitment techniques may have positive implications for improving enrollment of diverse elderly individuals in research.

The Right Temporal Variant of Frontotemporal Dementia Is Not Genetically Sporadic: A Case Series. - Ulugut Erkoyun, Hulya; van der Lee, Sven J; Nijmeijer, Bas; van Spaendonk, Rosalina; Nelissen, Anne; Scarioni, Marta; Dijkstra, Anke; Samancı, Bedia; Gürvit, Hakan; Yıldırım, Zerrin; Tepgeç, Fatih; Bilgic, Basar; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Right temporal variant frontotemporal dementia (rtvFTD) has been generally considered as a right sided variant of semantic variant primary progressive aphasia (svPPA), which is a genetically sporadic disorder. Recently, we have shown that rtvFTD has a unique clinical syndrome compared to svPPA and behavioral variant frontotemporal dementia. OBJECTIVE: We challenge the assumption that rtvFTD is a sporadic, non-familial variant of FTD by identifying potential autosomal dominant inheritance and related genes in rtvFTD. METHODS: We collected all subjects with a diagnosis of FTD or primary progressive aphasia who had undergone genetic screening (n = 284) and subsequently who had a genetic variant (n = 48) with a diagnosis of rtvFTD (n = 6) in 2 specialized memory clinics. RESULTS: Genetic variants in FTD related genes were found in 33% of genetically screened rtvFTD cases; including MAPT (n = 4), GRN (n = 1), and TARDBP (n = 1) genes, whereas only one svPPA case had a genetic variant in our combined cohorts. Additionally, 4 out of 6 rtvFTD subjects had a strong family history for dementia. CONCLUSION: Our results demonstrate that rtvFTD, unlike svPPA, is not a pure sporadic, but a heterogeneous potential genetic variant of FTD, and screening for genetic causes for FTD should be performed in patients with rtvFTD.
Keywords: Aphasia, Primary Progressive; DNA-Binding Proteins; Female; Frontotemporal Dementia; Functional Laterality; Genetic Testing; Genetic Variation; Gyrus Cinguli; Humans; Male; Middle Aged; Progranulins; tau Proteins

Spiritual Fitness: A New Dimension in Alzheimer's Disease Prevention. - Khalsa, Dharma Singh; Newberg, Andrew B (J Alzheimers Dis, 2021)
BACKGROUND: Religious and spiritual interventions may have an effect on Alzheimer's disease prevention. Kirtan Kriya meditation has been shown to mitigate the deleterious effects of chronic stress on cognition, reverse memory loss, and create psychological and spiritual wellbeing, which may reduce multiple drivers of Alzheimer's disease risk. OBJECTIVE: To detail a new concept in medicine called Spiritual Fitness, a merging of stress reduction, basic wellbeing, and psycho/spiritual wellbeing to prevent Alzheimer's disease. METHODS: The literature on the topics mentioned above is described, including an in-depth discussion on why and how each are critical to advancing the future of Alzheimer's disease prevention. The many negative effects of chronic stress, and the benefits of Kirtan Kriya, are reviewed. The four pillars of basic wellbeing, six practical aspects of psychological wellbeing, and the four new non-sectarian features of spiritual fitness are then disclosed. Moreover, instructions on practicing Kirtan Kriya are offered in the Supplementary Material. CONCLUSION: Religious and spiritual practices, including Kirtan Kriya, are crucial components in the development of enhanced cognition and well-being, which may help prevent and, in some cases, reverse cognitive decline. The key point of this review is that making a commitment to live a brain longevity lifestyle including spiritual fitness is a critically important way for aging Alzheimer's disease free. We hope that this article will inspire scientists, clinicians, and patients to embrace this new concept of spiritual fitness and make it a part of every multidomain program for the prevention of cognitive disability.
Keywords: Alzheimer Disease; Humans; Life Style; Love; Meditation; Spirituality

Synaptic Molecular and Neurophysiological Markers Are Independent Predictors of Progression in Alzheimer's Disease. - Smailovic, Una; Kåreholt, Ingemar; Koenig, Thomas; Ashton, Nicholas J; Winblad, Bengt; Höglund, Kina; Nilsson, Per; Zetterberg, Henrik; Blennow, Kaj; Jelic, Vesna (J Alzheimers Dis, 2021)
BACKGROUND: Cerebrospinal fluid (CSF) neurogranin and quantitative electroencephalography (qEEG) are potential molecular and functional markers of synaptic pathology in Alzheimer's disease (AD). Synaptic markers have emerged as candidate prognostic indicators of AD since synaptic degeneration was shown to be an early event and the best correlate of cognitive deficits in patients along the disease continuum. OBJECTIVE: The present study investigated the association between CSF neurogranin and qEEG measures as well as their potential to predict clinical deterioration in mild cognitive impairment (MCI) patients. METHODS: Patients diagnosed with MCI (n = 99) underwent CSF conventional AD biomarkers and neurogranin analysis and resting-state EEG recordings. The study population was further stratified into stable (n = 41) and progressive MCI (n = 31), based on the progression to AD dementia during two years follow-up. qEEG analysis included computation of global field power and global field synchronization in four conventional frequency bands. RESULTS: CSF neurogranin levels were associated with theta power and synchronization in the progressive MCI group. CSF neurogranin and qEEG measures were significant predictors of progression to AD dementia, independent of baseline amyloid status in MCI patients. A combination of CSF neurogranin with global EEG power in theta and global EEG synchronization in beta band exhibited the highest classification accuracy as compared to either of these markers alone. CONCLUSION: qEEG and CSF neurogranin are independent predictors of progression to AD dementia in MCI patients. Molecular and neurophysiological synaptic markers may have additive value in a multimodal diagnostic and prognostic approach to dementia.

Taking the A Train? Limited Consistency of Aβ42 and the Aβ42/40 Ratio in the AT(N) Classification. - Gouilly, Dominique; Tisserand, Camille; Nogueira, Leonor; Saint-Lary, Laura; Rousseau, Vanessa; Benaiteau, Marie; Rafiq, Marie; Carlier, Jasmine; Milongo-Rigal, Emilie; Pagès, Jean-Christophe; Pariente, Jérémie (J Alzheimers Dis, 2021)
The consistency of cerebrospinal fluid amyloid-β (Aβ)42/40 ratio and Aβ 42 has not been assessed in the AT(N) classification system. We analyzed the classification changes of the dichotomized amyloid status (A+/A-) in 363 patients tested for Alzheimer's disease biomarkers after Aβ 42 was superseded by the Aβ 42/40 ratio. The consistency of Aβ 42 and the Aβ 42/40 ratio was very low. Notably, the proportions of "false" A+T-patients were considerable (74-91%) and corresponded mostly to patients not clinically diagnosed with Alzheimer's disease. Our results suggest that the interchangeability of Aβ 42/40 ratio and Aβ 42 is limited for classifying patients in clinical setting using the AT(N) scheme.

Age-Specific Retinal and Cerebral Immunodetection of Amyloid-β Plaques and Oligomers in a Rodent Model of Alzheimer's Disease. - Habiba, Umma; Merlin, Sam; Lim, Jeremiah K H; Wong, Vickie H Y; Nguyen, Christine T O; Morley, John W; Bui, Bang V; Tayebi, Mourad (J Alzheimers Dis, 2020)
BACKGROUND: Amyloid-β soluble oligomers (Aβo) are believed to be the cause of the pathophysiology underlying Alzheimer's disease (AD) and are normally detected some two decades before clinical onset of the disease. Retinal pathology associated with AD pathogenesis has previously been reported, including ganglion cell loss, accumulation of Aβ deposits in the retina, and reduction of nerve fiber layer thickness as well as abnormalities of the microvasculature. OBJECTIVE: This study's aim is to better understand the relationship between brain and retinal Aβo deposition and in particular to quantify levels of the toxic Aβo as a function of age in the retina of a rodent model of AD. METHODS: Retinas and brain tissue from 5×FAD mice were stained with Congo red, Thioflavin-T (Th-T), and Aβ plaque-specific and Aβo-specific antibodies. RESULTS: We show that retinas displayed an age-dependent increase of Th-T-specific amyloid fibrils. Staining with anti-Aβ antibody confirmed the presence of the Aβ plaques in all 5×FAD retinas tested. In contrast, staining with anti-Aβo antibody showed an age-dependent decrease of retinal Aβo. Of note, Aβo was observed mainly in the retinal nuclear layers. Finally, we confirmed the localization of Aβo to neurons, typically accumulating in late endosomes, indicating possible impairment of the endocytic pathway. CONCLUSION: Our results demonstrate the presence of intraneuronal Aβo in the retina and its accumulation inversely correlated with retinal Aβ plaque deposition, indicating an age-related conversion in this animal model. These results support the development of an early AD diagnostic test targeting Aβo in the eye.

Aggregates of RNA Binding Proteins and ER Chaperones Linked to Exosomes in Granulovacuolar Degeneration of the Alzheimer's Disease Brain. - Yamoah, Alfred; Tripathi, Priyanka; Sechi, Antonio; Köhler, Christoph; Guo, Haihong; Chandrasekar, Akila; Nolte, Kay Wilhelm; Wruck, Christoph Jan; Katona, Istvan; Anink, Jasper; Troost, Dirk; Aronica, Eleonora; et al. (J Alzheimers Dis, 2020)
Granulovacuolar degeneration (GVD) occurs in Alzheimer's disease (AD) brain due to compromised autophagy. Endoplasmic reticulum (ER) function and RNA binding protein (RBP) homeostasis regulate autophagy. We observed that the ER chaperones GRP78/BiP, Sigma receptor 1 (SigR1), and VAPB were elevated in many AD patients' subicular neurons. However, those neurons which were affected by GVD showed lower chaperone levels, and there was only minor co-localization of chaperones with GVD bodies (GVBs), suggesting that neurons lacking sufficient chaperone-mediated proteostasis enter the GVD pathway. Consistent with this notion, granular, incipient pTau aggregates in human AD and pR5 tau transgenic mouse neurons were regularly co-localized with increased chaperone immunoreactivity, whereas neurons with mature neurofibrillary tangles lacked both the chaperone buildup and significant GVD. On the other hand, APP/PS1 (APPswe/PSEN1dE9) transgenic mouse hippocampal neurons that are devoid of pTau accumulation displayed only few GVBs-like vesicles, which were still accompanied by prominent chaperone buildup. Identifying a potential trigger for GVD, we found cytoplasmic accumulations of RBPs including Matrin 3 and FUS as well as stress granules in GVBs of AD patient and pR5 mouse neurons. Interestingly, we observed that GVBs containing aggregated pTau and pTDP-43 were consistently co-localized with the exosomal marker Flotillin 1 in both AD and pR5 mice. In contrast, intraneuronal 82E1-immunoreactive amyloid-β in human AD and APP/PS1 mice only rarely co-localized with Flotillin 1-positive exosomal vesicles. We conclude that altered chaperone-mediated ER protein homeostasis and impaired autophagy manifesting in GVD are linked to both pTau and RBP accumulation and that some GVBs might be targeted to exocytosis.

Is Alzheimer's Disease a Liver Disease of the Brain? - Bassendine, Margaret F; Taylor-Robinson, Simon D; Fertleman, Michael; Khan, Michael; Neely, Dermot (J Alzheimers Dis, 2020)
Clinical specialization is not only a force for progress, but it has also led to the fragmentation of medical knowledge. The focus of research in the field of Alzheimer's disease (AD) is neurobiology, while hepatologists focus on liver diseases and lipid specialists on atherosclerosis. This article on AD focuses on the role of the liver and lipid homeostasis in the development of AD. Amyloid-β (Aβ) deposits accumulate as plaques in the brain of an AD patient long before cognitive decline is evident. Aβ generation is a normal physiological process; the steady-state level of Aβ in the brain is determined by balance between Aβ production and its clearance. We present evidence suggesting that the liver is the origin of brain Aβ deposits and that it is involved in peripheral clearance of circulating Aβ in the blood. Hence the liver could be targeted to decrease Aβ production or increase peripheral clearance.

Alzheimer's Disease-Like Neurodegeneration in Porphyromonas gingivalis Infected Neurons with Persistent Expression of Active Gingipains. - Haditsch, Ursula; Roth, Theresa; Rodriguez, Leo; Hancock, Sandy; Cecere, Thomas; Nguyen, Mai; Arastu-Kapur, Shirin; Broce, Sean; Raha, Debasish; Lynch, Casey C; Holsinger, Leslie J; Dominy, Stephen S; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Porphyromonas gingivalis (P. gingivalis) and its gingipain virulence factors have been identified as pathogenic effectors in Alzheimer's disease (AD). In a recent study we demonstrated the presence of gingipains in over 90% of postmortem AD brains, with gingipains localizing to the cytoplasm of neurons. However, infection of neurons by P. gingivalis has not been previously reported. OBJECTIVE: To demonstrate intraneuronal P. gingivalis and gingipain expression in vitro after infecting neurons derived from human inducible pluripotent stem cells (iPSC) with P. gingivalis for 24, 48, and 72 h. METHODS: Infection was characterized by transmission electron microscopy, confocal microscopy, and bacterial colony forming unit assays. Gingipain expression was monitored by immunofluorescence and RT-qPCR, and protease activity monitored with activity-based probes. Neurodegenerative endpoints were assessed by immunofluorescence, western blot, and ELISA. RESULTS: Neurons survived the initial infection and showed time dependent, infection induced cell death. P. gingivalis was found free in the cytoplasm or in lysosomes. Infected neurons displayed an accumulation of autophagic vacuoles and multivesicular bodies. Tau protein was strongly degraded, and phosphorylation increased at T231. Over time, the density of presynaptic boutons was decreased. CONCLUSION: P. gingivalis can invade and persist in mature neurons. Infected neurons display signs of AD-like neuropathology including the accumulation of autophagic vacuoles and multivesicular bodies, cytoskeleton disruption, an increase in phospho-tau/tau ratio, and synapse loss. Infection of iPSC-derived mature neurons by P. gingivalis provides a novel model system to study the cellular mechanisms leading to AD and to investigate the potential of new therapeutic approaches.

Alzheimer's/Vascular Spectrum Dementia: Classification in Addition to Diagnosis. - Emrani, Sheina; Lamar, Melissa; Price, Catherine C; Wasserman, Victor; Matusz, Emily; Au, Rhoda; Swenson, Rodney; Nagele, Robert; Heilman, Kenneth M; Libon, David J (J Alzheimers Dis, 2020)
Alzheimer's disease (AD) and vascular dementia (VaD) are the two most common types of dementia. Although the combination of these disorders, called 'mixed' dementia, is recognized, the prevailing clinical and research perspective continues to consider AD and VaD as independent disorders. A review of recent neuropathological and neuropsychological literature reveals that these two disorders frequently co-occur and so-called 'pure' AD or VaD is comparatively rare. In addition, recent research shows that vascular dysfunction not only potentiates AD pathology, but that pathological changes in AD may subsequently induce vascular disorders. On the basis of these data, we propose that the neurobiological underpinnings underlying AD/VaD dementia and their neuropsychological phenotypes are best understood as existing along a clinical/pathological continuum or spectrum. We further propose that in conjunction with current diagnostic criteria, statistical modeling techniques using neuropsychological test performance should be leveraged to construct a system to classify AD/VaD spectrum dementia in order to test hypotheses regarding how mechanisms related to AD and VaD pathology interact and influence each other.

Amyloid Hypothesis: The Emperor's New Clothes? - Høilund-Carlsen, Poul F; Barrio, Jorge R; Werner, Tom J; Newberg, Andrew; Alavi, Abass (J Alzheimers Dis, 2020)
The lengthy debate on the validity of the amyloid hypothesis and the usefulness of amyloid imaging and anti-amyloid therapeutic interventions in dementia continues unabated, even though none of them have been able to convince the medical world of their correctness and clinical value. There are huge financial interests associated with promoting both, but in spite of the large sums of money in their support, no effective anti-amyloid treatments or diagnostic use of amyloid imaging have emerged. There are solid scientific reasons that explain these negative results, and it is time to move forward to other promising options for the benefit of the patients.

Analysis of Taste Sensitivities in App Knock-In Mouse Model of Alzheimer's Disease. - Narukawa, Masataka; Takahashi, Suzuka; Saito, Takashi; Saido, Takaomi C; Misaka, Takumi (J Alzheimers Dis, 2020)
BACKGROUND: Some studies have reported a decline in taste sensitivities in patients with Alzheimer's disease. However, the detail remains unknown. OBJECTIVE: We investigated the effect of cognitive impairment on taste sensitivity using an App knock-in mouse model of Alzheimer's disease. METHODS: Behavioral assays, a brief access test, and a 48 h two-bottle preference test, to assess taste sensitivities were started from 12 months of age in mice that were confirmed to have impaired cognition. RESULTS: In the assays, there was no significant difference in taste sensitivities between wild type and App knock-in mice. Additionally, no apparent difference was observed in the expression of taste markers in their taste bud cells. CONCLUSION: We concluded that cognitive impairment might not greatly affect taste sensitivity.

Association of Peripheral Insulin Resistance and Other Markers of Type 2 Diabetes Mellitus with Brain Amyloid Deposition in Healthy Individuals at Risk of Dementia. - Pekkala, Timo; Hall, Anette; Mangialasche, Francesca; Kemppainen, Nina; Mecocci, Patrizia; Ngandu, Tiia; Rinne, Juha O; Soininen, Hilkka; Tuomilehto, Jaakko; Kivipelto, Miia; Solomon, Alina (J Alzheimers Dis, 2020)
We explored the association of type 2 diabetes related blood markers with brain amyloid accumulation on PiB-PET scans in 41 participants from the FINGER PET sub-study. We built logistic regression models for brain amyloid status with12 plasma markers of glucose and lipid metabolism, controlled for diabetes and APOEɛ4 carrier status. Lower levels of insulin, insulin resistance index (HOMA-IR), C-peptide, and plasminogen activator (PAI-1) were associated with amyloid positive status, although the results were not significant after adjusting for multiple testing. None of the models found evidence for associations between amyloid status and fasting glucose or HbA1c.

Comparative Cognitive Effects of Choreographed Exercise and Multimodal Physical Therapy in Older Adults with Amnestic Mild Cognitive Impairment: Randomized Clinical Trial. - Bisbe, Marta; Fuente-Vidal, Andrea; López, Elisabet; Moreno, Marta; Naya, Marian; de Benetti, Claudio; Milà, Raimon; Bruna, Olga; Boada, Merce; Alegret, Montserrat (J Alzheimers Dis, 2020)
BACKGROUND: Recent research on mild cognitive impairment (MCI) has primarily focused on searching for measures to prevent or delay the progression of MCI to dementia. Physical exercise has shown to be effective in the prevention of age-related cognitive decline in elderly adults with MCI. However, the most effective type and dose of exercise for the improvement of cognition are yet to be determined. OBJECTIVE: To compare the cognitive effects of choreographed exercise (Choreography group) with a multimodal physical therapy program (Physical Therapy group) in elderly adults with amnestic MCI, a population with an increased risk of developing dementia. METHODS: We conducted a randomized clinical trial with two parallel groups under allocation concealment and assessor blinding. Participants were allocated into Choreography or Physical Therapy group and performed exercises twice per week in 60-minute sessions during 12 weeks. RESULTS: Thirty-six participants with amnestic MCI, ages 65 to 85, were assessed at baseline and after 12 weeks of intervention, by comprehensive validated neuropsychological and physical assessments. A Repeated measures General Lineal Model showed statistically significant differences in cognitive and physical outcomes. Both groups significantly improved in visual delayed recall. The Choreography group exhibited significantly more benefits on verbal recognition memory than the Physical Therapy group. CONCLUSION: Greater cognitive benefits were achieved in the choreographic intervention than in the multimodal physical therapy, mainly in those functions more related to the risk of conversion to dementia. Additional studies are needed to confirm whether the observed effects are related to delayed onset of Alzheimer's disease in elderly adults with amnestic MCI.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Combined Modality Therapy; Dance Therapy; Exercise Therapy; Female; Humans; Linear Models; Male; Neuropsychological Tests; Physical Therapy Modalities; Single-Blind Method

Costs and Resource Use Associated with Community-Dwelling Patients with Alzheimer's Disease in Japan: Baseline Results from the Prospective Observational GERAS-J Study. - Nakanishi, Miharu; Igarashi, Ataru; Ueda, Kaname; Brnabic, Alan J M; Treuer, Tamas; Sato, Masayo; Kahle-Wrobleski, Kristin; Meguro, Kenichi; Yamada, Masahito; Mimura, Masaru; Arai, Heii (J Alzheimers Dis, 2020)
BACKGROUND: As the Japanese population ages, caring for people with Alzheimer's disease (AD) dementia is becoming a major socioeconomic issue. OBJECTIVE: To determine the contribution of patient and caregiver costs to total societal costs associated with AD dementia. METHODS: Baseline data was used from the longitudinal, observational GERAS-J study. Using the Mini-Mental State Examination (MMSE) score, patients routinely visiting memory clinics were stratified into three groups based on AD severity. Health care resource utilizationwas recorded using the Resource Utilization in Dementia questionnaire. Total monthly societal costs were estimated using Japan-specific unit costs of services and products (patient direct health care use, patient social care use, and informal caregiving time). Uncertainty around mean costs was estimated using bootstrapping methods. RESULTS: Overall, 553 community-dwelling patients withADdementia (28.3% mild[MMSE21-26], 37.8% moderate[MMSE 15-20], and 34.0% moderately severe/severe [MMSE < 14]) and their caregivers were enrolled. Patient characteristics were: mean age 80.3 years, 72.7% female, and 13.6% living alone. Caregiver characteristics were: mean age 62.1 years, 70.7% female, 78.8% living with patient, 49.0% child of patient, and 39.2% sole caregiver. Total monthly societal costs of AD dementia (Japanese yen) were: 158,454 (mild), 211,301 (moderate), and 294,224 (moderately severe/severe). Informal caregiving costs comprised over 50% of total costs. CONCLUSION: Baseline results of GERAS-J showed that total monthly societal costs associated with AD dementia increased with AD severity. Caregiver-related costs were the largest cost component. Interventions are needed to decrease informal costs and decrease caregiver burden.

Dickkopf-1 Overexpression in vitro Nominates Candidate Blood Biomarkers Relating to Alzheimer's Disease Pathology. - Shi, Liu; Winchester, Laura M; Liu, Benjamine Y; Killick, Richard; Ribe, Elena M; Westwood, Sarah; Baird, Alison L; Buckley, Noel J; Hong, Shengjun; Dobricic, Valerija; Kilpert, Fabian; Franke, Andre; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Previous studies suggest that Dickkopf-1 (DKK1), an inhibitor of Wnt signaling, plays a role in amyloid-induced toxicity and hence Alzheimer's disease (AD). However, the effect of DKK1 expression on protein expression, and whether such proteins are altered in disease, is unknown. OBJECTIVE: We aim to test whether DKK1 induced protein signature obtained in vitro were associated with markers of AD pathology as used in the amyloid/tau/neurodegeneration (ATN) framework as well as with clinical outcomes. METHODS: We first overexpressed DKK1 in HEK293A cells and quantified 1,128 proteins in cell lysates using aptamer capture arrays (SomaScan) to obtain a protein signature induced by DKK1. We then used the same assay to measure the DKK1-signature proteins in human plasma in two large cohorts, EMIF (n = 785) and ANM (n = 677). RESULTS: We identified a 100-protein signature induced by DKK1 in vitro. Subsets of proteins, along with age and apolipoprotein E ɛ4 genotype distinguished amyloid pathology (A + T-N-, A+T+N-, A+T-N+, and A+T+N+) from no AD pathology (A-T-N-) with an area under the curve of 0.72, 0.81, 0.88, and 0.85, respectively. Furthermore, we found that some signature proteins (e.g., Complement C3 and albumin) were associated with cognitive score and AD diagnosis in both cohorts. CONCLUSIONS: Our results add further evidence for a role of DKK regulation of Wnt signaling in AD and suggest that DKK1 induced signature proteins obtained in vitro could reflect theATNframework as well as predict disease severity and progression in vivo.

Epilepsy in Neurodegenerative Dementias: A Clinical, Epidemiological, and EEG Study. - Arnaldi, Dario; Donniaquio, Andrea; Mattioli, Pietro; Massa, Federico; Grazzini, Matteo; Meli, Riccardo; Filippi, Laura; Grisanti, Stefano; Famá, Francesco; Terzaghi, Michele; Girtler, Nicola; Brugnolo, Andrea; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Seizures are common in patients with dementia but precise epidemiologic data of epilepsy in neurodegenerative dementia is lacking. OBJECTIVE: The first aim of the study was to investigate prevalence and clinical characteristics of epilepsy in a large cohort of patients with neurodegenerative dementias. Subsequently, we explored clinical, neuropsychological, and quantitative electroencephalogram (qEEG) data of Alzheimer's disease (AD) patients with epilepsy (AD-EPI) as compared to AD patients without epilepsy (AD-CTR). METHODS: We retrospectively evaluated consecutive patients with a diagnosis of a neurodegenerative dementia and a clinically diagnosed epilepsy that required antiepileptic drugs (AED). All patients underwent baseline comprehensive neuropsychological assessment. A follow-up of at least one year was requested to confirm the dementia diagnosis. In AD patients, qEEG power band analysis was performed. AD-CTR and AD-EPI patients were matched for age, Mini-Mental State Examination score, and gender. RESULTS: Thirty-eight out of 2,054 neurodegenerative dementia patients had epilepsy requiring AED. The prevalence of epilepsy was 1.82% for AD, 1.28% for the behavioral variant of frontotemporal dementia (bvFTD), 2.47% for dementia with Lewy bodies (DLB), and 12% for primary progressive aphasia. Epilepsy were more drug-responsive in AD than in non-AD dementias. Finally, no significant differences were found in neuropsychological and qEEG data between AD-EPI and AD-CTR patients. CONCLUSION: In our cohort, AD, FTD, and DLB dementias have similar prevalence of epilepsy, even if AD patients were more responsive to AED. Moreover, AD-EPI patients did not have significant clinical, neuropsychological qEEG differences compared with AD-CTR patients.

Functional Integrity of Synapses in the Central Nervous System of Cognitively Intact Individuals with High Alzheimer's Disease Neuropathology is Associated with Absence of Synaptic Tau Oligomers. - Singh, Ayush; Allen, Dyron; Fracassi, Anna; Tumurbaatar, Batbayar; Natarajan, Chandramouli; Scaduto, Pietro; Woltjer, Randy; Kayed, Rakez; Limon, Agenor; Krishnan, Balaji; Taglialatela, Giulio (J Alzheimers Dis, 2020)
BACKGROUND: Certain individuals, here referred to as Non-Demented with Alzheimer Neuropathology (NDAN), do not show overt neurodegeneration (N - ) and remain cognitively intact despite the presence of plaques (A+) and tangles (T+) that would normally be consistent with fully symptomatic Alzheimer's disease (AD). OBJECTIVE: The existence of NDAN (A + T +N - ) subjects suggests that the human brain utilizes intrinsic mechanisms that can naturally evade cognitive decline normally associated with the symptomatic stages of AD (A + T +N +). Deciphering the underlying mechanisms would prove relevant to develop complementing therapeutics to prevent progression of AD-related cognitive decline. METHODS: Previously, we have reported that NDAN present with preserved neurogenesis and synaptic integrity paralleled by absence of amyloid oligomers at synapses. Using postmortem brain samples from age-matched control subjects, demented AD patients and NDAN individuals, we performed immunofluorescence, western blots, micro transplantation of synaptic membranes in Xenopus oocytes followed by twin electrode voltage clamp electrophysiology and fluorescence assisted single synaptosome-long term potentiation studies. RESULTS: We report decreased tau oligomers at synapses in the brains of NDAN subjects. Furthermore, using novel approaches we report, for the first time, that such absence of tau oligomers at synapses is associated with synaptic functional integrity in NDAN subjects as compared to demented AD patients. CONCLUSION: Overall, these results give further credence to tau oligomers as primary actors of synaptic destruction underscoring cognitive demise in AD and support their targeting as a viable therapeutic strategy for AD and related tauopathies.

Generation of Transgenic Cynomolgus Monkeys Overexpressing the Gene for Amyloid-β Precursor Protein. - Seita, Yasunari; Morimura, Toshifumi; Watanabe, Naoki; Iwatani, Chizuru; Tsuchiya, Hideaki; Nakamura, Shinichiro; Suzuki, Toshiharu; Yanagisawa, Daijiro; Tsukiyama, Tomoyuki; Nakaya, Masataka; Okamura, Eiichi; Muto, Masanaga; et al. (J Alzheimers Dis, 2020)
Alzheimer's disease (AD) is the most common cause of dementia and understanding its pathogenesis should lead to improved therapeutic and diagnostic methods. Although several groups have developed transgenic mouse models overexpressing the human amyloid-β precursor protein (APP) gene with AD mutations, with and without presenilin mutations, as well as APP gene knock-in mouse models, these animals display amyloid pathology but do not show neurofibrillary tangles or neuronal loss. This presumably is due to differences between the etiology of the aged-related human disease and the mouse models. Here we report the generation of two transgenic cynomolgus monkeys overexpressing the human gene for APP with Swedish, Artic, and Iberian mutations, and demonstrated expression of gene tagged green fluorescent protein marker in the placenta, amnion, hair follicles, and peripheral blood. We believe that these nonhuman primate models will be very useful to study the pathogenesis of dementia and AD. However, generated Tg monkeys still have some limitations. We employed the CAG promoter, which will promote gene expression in a non-tissue specific manner. Moreover, we used transgenic models but not knock-in models. Thus, the inserted transgene destroys endogenous gene(s) and may affect the phenotype(s). Nevertheless, it will be of great interest to determine whether these Tg monkeys will develop tauopathy and neurodegeneration similar to human AD.

The GSM BPN-15606 as a Potential Candidate for Preventative Therapy in Alzheimer's Disease. - Prikhodko, Olga; Rynearson, Kevin D; Sekhon, Travis; Mante, Mike M; Nguyen, Phuong D; Rissman, Robert A; Tanzi, Rudolph E; Wagner, Steven L (J Alzheimers Dis, 2020)
BACKGROUND: In the amyloid hypothesis of Alzheimer's disease (AD), the dysregulation of amyloid-β protein (Aβ) production and clearance leads to amyloid deposits, tau tangles, neuronal loss, and cognitive dysfunction. Thus far, therapies targeting the enzymes responsible for Aβ production have been found ineffective or having significant side effects. OBJECTIVE: To test whether a γ-secretase modulator, BPN-15606, is an effective disease-modifying or preventative treatment in the PSAPP mouse model of AD. METHODS: We treated pre-plaque (3-month-old) and post-plaque (6-month-old) PSAPP AD transgenic mice for 3 months and examined behavioral, biochemical, and pathological end points. RESULTS: BPN-15606 attenuated cognitive impairment and reduced amyloid plaque load, microgliosis, and astrogliosis associated with the AD phenotype of PSAPP mice when administered to pre-plaque (3-month-old) but was ineffective when administered to post-plaque (6-month-old) mice. No treatment-related toxicity was observed. CONCLUSION: BPN-15606 appears efficacious when administered prior to significant pathology.

The Impact of Amyloid-β or Tau on Cognitive Change in the Presence of Severe Cerebrovascular Disease. - Jang, Hyemin; Kim, Hee Jin; Sim Choe, Yeong; Kim, Soo-Jong; Park, Seongbeom; Kim, Yeshin; Woon Kim, Ko; Hyoung Lyoo, Chul; Cho, Hanna; Hoon Ryu, Young; Choi, Jae Yong; DeCarli, Charles; et al. (J Alzheimers Dis, 2020)
BACKGROUND: As Alzheimer's disease (AD) and cerebral small vessel disease (CSVD) commonly coexist, the interaction between two has been of the considerable interest. OBJECTIVE: We determined whether the association of Aβ and tau with cognitive decline differs by the presence of significant CSVD. METHODS: We included 60 subcortical vascular cognitive impairment (SVCI) from Samsung Medical Center and 82 Alzheimer's disease-related cognitive impairment (ADCI) from ADNI, who underwent Aβ (florbetaben or florbetapir) and tau (flortaucipir, FTP) PET imaging. They were retrospectively assessed for 5.0±3.9 and 5.6±1.9 years with Clinical Dementia Rating-sum of boxes (CDR-SB)/Mini-Mental State Examination (MMSE). Mixed effects models were used to investigate the interaction between Aβ/tau and group on CDR-SB/MMSE changes. RESULTS: The frequency of Aβ positivity (45% versus 54.9%, p = 0.556) and mean global FTP SUVR (1.17±0.21 versus 1.16±0.17, p = 0.702) were not different between the two groups. We found a significant interaction effect of Aβ positivity and SVCI group on CDR-SB increase/MMSE decrease (p = 0.013/p <  0.001) change, and a significant interaction effect of global FTP uptake and SVCI group on CDR-SB increase/MMSE decrease (p <  0.001 and p = 0.030) change. Finally, the interaction effects of regional tau and group were prominent in the Braak III/IV (p = 0.001) and V/VI (p = 0.003) not in Braak I/II region (p = 0.398). CONCLUSION: The association between Aβ/tau and cognitive decline is stronger in SVCI than in ADCI. Therefore, our findings suggested that Aβ positivity or tau burden (particularly in the Braak III/IV or V/VI regions) and CSVD might synergistically affect cognitive decline.

Impact of APOE and BDNF Val66Met Gene Polymorphisms on Cognitive Functions in Patients with Amnestic Mild Cognitive Impairment. - Cechova, Katerina; Andel, Ross; Angelucci, Francesco; Chmatalova, Zuzana; Marková, Hana; Laczó, Jan; Vyhnálek, Martin; Matoska, Vaclav; Kaplan, Vojtech; Nedelska, Zuzana; Ward, David D; Hort, Jakub (J Alzheimers Dis, 2020)
Apolipoprotein (APOE) ɛ4 is a well-known risk factor for late-onset Alzheimer's disease (AD), but other AD-related gene polymorphisms might also be important, such as the polymorphism within the brain-derived neurotrophic factor (BDNF) gene. Carriage of BDNF Val66Met has been associated with faster cognitive decline and greater hippocampal atrophy in cognitively normal elderly. Thus, we examined the effects of the concurrent presence of APOE and BDNF polymorphisms on cognitive functions and brain morphometry in amnestic mild cognitive impairment (aMCI) patients. 107 aMCI patients (mean age = 72.2) were recruited from the Czech Brain Aging Study and, based on APOE and BDNF genes polymorphisms, were divided into four groups: ɛ4-BDNFVal/Val (n = 37), ɛ4-BDNFMet (n = 19), ɛ4+BDNFVal/Val (n = 35), and ɛ4+BDNFMet (n = 16). All patients underwent clinical examination, magnetic resonance imaging, and complex neuropsychological battery. The combination of APOEɛ4+ and BDNF Met was associated with significantly worse memory performance in immediate and delayed recall compared to other polymorphism groups. We did not observe increased atrophy in areas related to memory function in the ɛ4+BDNFMet group. Our findings suggest that carriage of ɛ4+BDNFMet is associated with more pronounced memory dysfunction, a typical feature of early AD, but not with structural brain changes in aMCI patients. These findings suggest that in APOEɛ4/BDNF Met carriers, synaptic dysfunction affecting memory may precede pronounced structural changes.

Levels of Retinal Amyloid-β Correlate with Levels of Retinal IAPP and Hippocampal Amyloid-β in Neuropathologically Evaluated Individuals. - Schultz, Nina; Byman, Elin; Wennström, Malin (J Alzheimers Dis, 2020)
BACKGROUND: Previous studies have used immunohistology to demonstrate Alzheimer's disease (AD) characteristic accumulation of amyloid-β (Aβ) in the retina of AD patients, a finding indicating retina examination as a potential diagnostic tool for AD pathology. OBJECTIVE: To further explore this idea by investigating whether levels of Aβ42 and Aβ40 in retina are associated with corresponding levels in hippocampus, neuropathological assessments, apolipoprotein E (APOE) genotype, and levels of islet amyloid polypeptide (IAPP). METHODS: Levels of high molecular weight (HMW) Aβ42, Aβ40, and IAPP in ultra-centrifuged homogenates of retina and hippocampus from patients with AD, multiple sclerosis, AD with Lewy bodies, and non-demented controls were analyzed using Mesoscale Discovery electrochemiluminescence technology employing immunoassay and enzyme-linked immunosorbent assay. RESULTS: Higher levels of retinal and hippocampal Aβ42-HMW, Aβ40-HMW, and IAPP-HMW were found in individuals with high neuropathological scores of Aβ plaques and in individuals carrying the APOEɛ4 allele. The retinal levels of Aβ42-HMW and Aβ40-HMW correlated with corresponding levels in hippocampus as well as with neurofibrillary tangles (NFT) and Aβ scores. Retinal IAPP-HMW correlated with retinal levels of Aβ42-HMW and with NFT and Aβ scores. CONCLUSION: These results show that different isoforms of Aβ can be detected in the human retina and moreover support the growing number of studies indicating that AD-related pathological changes occurring in the brain could be reflected in the retina.

A New Serum Biomarker Set to Detect Mild Cognitive Impairment and Alzheimer's Disease by Peptidome Technology. - Abe, Koji; Shang, Jingwei; Shi, Xiaowen; Yamashita, Toru; Hishikawa, Nozomi; Takemoto, Mami; Morihara, Ryuta; Nakano, Yumiko; Ohta, Yasuyuki; Deguchi, Kentaro; Ikeda, Masaki; Ikeda, Yoshio; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Because dementia is an emerging problem in the world, biochemical markers of cerebrospinal fluid (CSF) and radio-isotopic analyses are helpful for diagnosing Alzheimer's disease (AD). Although blood sample is more feasible and plausible than CSF or radiological biomarkers for screening potential AD, measurements of serum amyloid- β (Aβ), plasma tau, and serum antibodies for Aβ1 - 42 are not yet well established. OBJECTIVE: We aimed to identify a new serum biomarker to detect mild cognitive impairment (MCI) and AD in comparison to cognitively healthy control by a new peptidome technology. METHODS: With only 1.5μl of serum, we examined a new target plate "BLOTCHIP®" plus a matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF/MS) to discriminate control (n = 100), MCI (n = 60), and AD (n = 99). In some subjects, cognitive Mini-Mental State Examination (MMSE) were compared to positron emission tomography (PET) with Pittsburgh compound B (PiB) and the serum probability of dementia (SPD). The mother proteins of candidate serum peptides were examined in autopsied AD brains. RESULTS: Apart from Aβ or tau, the present study discovered a new diagnostic 4-peptides-set biomarker for discriminating control, MCI, and AD with 87% of sensitivity and 65% of specificity between control and AD (***p < 0.001). MMSE score was well correlated to brain Aβ deposition and to SPD of AD. The mother proteins of the four peptides were upregulated for coagulation, complement, and plasticity (three proteins), and was downregulated for anti-inflammation (one protein) in AD brains. CONCLUSION: The present serum biomarker set provides a new, rapid, non-invasive, highly quantitative and low-cost clinical application for dementia screening, and also suggests an alternative pathomechanism of AD for neuroinflammation and neurovascular unit damage.

Partial Inhibition of Mitochondrial Complex I Reduces Tau Pathology and Improves Energy Homeostasis and Synaptic Function in 3xTg-AD Mice. - Stojakovic, Andrea; Chang, Su-Youne; Nesbitt, Jarred; Pichurin, Nicholas P; Ostroot, Mark A; Aikawa, Tomonori; Kanekiyo, Takahisa; Trushina, Eugenia (J Alzheimers Dis, 2020)
BACKGROUND: Accumulation of hyperphosphorylated tau (pTau) protein is associated with synaptic dysfunction in Alzheimer's disease (AD). We previously demonstrated that neuroprotection in familial mouse models of AD could be achieved by targeting mitochondria complex I (MCI) and activating the adaptive stress response. Efficacy of this strategy on pTau-related pathology remained unknown. OBJECTIVE: To investigate the effect of specific MCI inhibitor tricyclic pyrone compound CP2 on levels of human pTau, memory function, long term potentiation (LTP), and energy homeostasis in 18-month-old 3xTg-AD mice and explore the potential mechanisms. METHODS: CP2 was administered to male and female 3xTg-AD mice from 3.5-18 months of age. Cognitive function was assessed using the Morris water maze. Glucose metabolism was measured in periphery using a glucose tolerance test and in the brain using fluorodeoxyglucose F18 positron-emission tomography (FDG-PET). LTP was evaluated using electrophysiology in the hippocampus. The expression of key proteins associated with neuroprotective mechanisms were assessed by western blotting. RESULTS: Chronic CP2 treatment restored synaptic activity in female 3xTg-AD mice; cognitive function, levels of synaptic proteins, glucose metabolism, and energy homeostasis were improved in male and female 3xTg-AD mice. Significant reduction of human pTau in the brain was associated with increased activity of protein phosphatase of type 2A (PP2A), and reduced activity of cyclin-dependent kinase 5 (CDK5) and glycogen synthase kinase 3β (GSK3β). CONCLUSION: CP2 treatment protected against synaptic dysfunction and memory impairment in symptomatic 3xTg-AD mice, and reduced levels of human pTau, indicating that targeting mitochondria with small molecule specific MCI inhibitors represents a promising strategy for treating AD.

Patterns of Regional Cerebral Blood Flow as a Function of Obesity in Adults. - Amen, Daniel G; Wu, Joseph; George, Noble; Newberg, Andrew (J Alzheimers Dis, 2020)
BACKGROUND: While obesity has been shown to be a risk factor for Alzheimer's disease, the potential mechanisms underlying this risk may be clarified with better understanding of underlying physiology in obese persons. OBJECTIVE: To identify patterns of cerebral perfusion abnormality in adults as a function of body mass index (BMI) defined weight categories, including overweight or obese status. METHODS: A large psychiatric cohort of 35,442 brain scans across 17,721 adults (mean age 40.8±16.2 years, range 18-94 years) were imaged with SPECT during baseline and concentration scans, the latter done after each participant completed the Connors Continuous Performance Test II. ANOVA was done to identify patterns of perfusion abnormality in this cohort across BMI designations of underweight (BMI < 18.5), normal weight (BMI = 18.5 to 24.9), overweight (BMI 24.9 to 29.9), obesity (BMI≥30), and morbid obesity (BMI≥40). This analysis was done for 128 brain regions quantifying SPECT perfusion using the automated anatomical labeling (AAL) atlas. RESULTS: Across adulthood, higher BMI correlated with decreased perfusion on both resting and concentration brain SPECT scans. These are seen in virtually all brain regions, including those influenced by AD pathology such as the hippocampus. CONCLUSION: Greater BMI is associated with cerebral perfusion decreases in both resting and concentration SPECT scans across adulthood.

Potential Novel Role of COVID-19 in Alzheimer's Disease and Preventative Mitigation Strategies. - Naughton, Sean X; Raval, Urdhva; Pasinetti, Giulio M (J Alzheimers Dis, 2020)
There are a number of potential implications for the field of Alzheimer's disease (AD) stemming from the global spread of SARS-CoV-2. Neuroinflammation is known to be a prominent feature of neurodegeneration and plays a major role in AD pathology. Immune response and excessive inflammation in COVID-19 may also accelerate the progression of brain inflammatory neurodegeneration, and elderly individuals are more susceptible to severe outcomes after SARS-CoV-2 infection. Individuals with type 2 diabetes (T2D) are at an increased risk for AD as well as severe outcomes after SARS-CoV-2 infection. Genetic and socioeconomic factors influencing the rates of T2D, AD, and COVID-19 severity may create an exceptionally high-risk profile for certain demographics such as African Americans and Hispanic Americans. Type I interferon response plays an important role in both host response to viral infection, as well as AD pathology and may be a sensible therapeutic target in both AD and COVID-19.
Keywords: Aged; Alzheimer Disease; Betacoronavirus; Coronavirus Infections; COVID-19; Diabetes Mellitus, Type 2; Humans; Interferon Type I; Pandemics; Pneumonia, Viral; SARS-CoV-2; Synapses

Potential of FTIR Spectroscopy Applied to Exosomes for Alzheimer's Disease Discrimination: A Pilot Study. - Martins, Tânia Soares; Magalhães, Sandra; Rosa, Ilka Martins; Vogelgsang, Jonathan; Wiltfang, Jens; Delgadillo, Ivonne; Catita, José; da Cruz E Silva, Odete A B; Nunes, Alexandra; Henriques, Ana Gabriela (J Alzheimers Dis, 2020)
Alzheimer's disease (AD) diagnosis is based on psychological and imaging tests but can also include monitoring cerebrospinal fluid (CSF) biomarkers. However, CSF based-neurochemical approaches are expensive and invasive, limiting their use to well-equipped settings. In contrast, blood-based biomarkers are minimally invasive, cost-effective, and a widely accessible alternative. Blood-derived exosomes have recently emerged as a reliable AD biomarker source, carrying disease-specific cargo. Fourier-transformed infrared (FTIR) spectroscopy meets the criteria for an ideal diagnostic methodology since it is rapid, easy to implement, and has high reproducibility. This metabolome-based technique is useful for diagnosing a broad range of diseases, although to our knowledge, no reports for FTIR spectroscopy applied to exosomes in AD exist. In this ground-breaking pilot study, FTIR spectra of serum and serum-derived exosomes from two independent cohorts were acquired and analyzed using multivariate analysis. The regional UA-cohort includes 9 individuals, clinically diagnosed with AD, mean age of 78.7 years old; and the UMG-cohort comprises 12 individuals, clinically diagnosed with AD (based on molecular and/or imaging data), mean age of 73.2 years old. Unsupervised principal component analysis of FTIR spectra of serum-derived exosomes revealed higher discriminatory value for AD cases when compared to serum as a whole. Consistently, the partial least-squares analysis revealed that serum-derived exosomes present higher correlations than serum. In addition, the second derivative peak area calculation also revealed significant differences among Controls and AD cases. The results obtained suggest that this methodology can discriminate cases from Controls and thus be potential useful to assist in AD clinical diagnosis.

Quantitative Mass Spectrometric Assay of Whole and CNBr-Cleaved Amyloid-β Peptides in Human Brain. - Furman, Ran; Ng, Sharon C W; Komatsu, Hiroaki; Axelsen, Paul H (J Alzheimers Dis, 2020)
Various amyloid-β (Aβ) peptides accumulate in brain in Alzheimer's disease, and the amounts of specific peptide variants may have pathological significance. The quantitative determination of these variants is challenging because losses inevitably occur during tissue processing and analysis. This report describes the use of stable-isotope-labeled Aβ peptides as internal standards for quantitative mass spectrometric assays, and the use of cyanogen bromide (CNBr) to remove C-terminal residues beyond Met35. The removal of residues beyond Met35 reduces losses due to aggregation, and facilitates the detection of post-translationally modified Aβ peptides. Results from 8 human brain samples suggest that the tissue concentrations of the 42-residue Aβ peptide tend to be similar in different patients. Concentrations of the 40-residue Aβ peptide are more variable, and may be greater or lesser than the 42-residue peptide. The concentration of the CNBr cleavage product closely matches the sum of the 40-residue and 42-residue peptide concentrations, indicating that these two Aβ peptides account for most of the C-terminal variants in these patients. CNBr treatment facilitated the detection of post-translational modifications such as pyroglutamyl and hexose-modified Aβ peptides.

Short-Chain Fatty Acids and Lipopolysaccharide as Mediators Between Gut Dysbiosis and Amyloid Pathology in Alzheimer's Disease. - Marizzoni, Moira; Cattaneo, Annamaria; Mirabelli, Peppino; Festari, Cristina; Lopizzo, Nicola; Nicolosi, Valentina; Mombelli, Elisa; Mazzelli, Monica; Luongo, Delia; Naviglio, Daniele; Coppola, Luigi; Salvatore, Marco; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Metagenomic data support an association between certain bacterial strains and Alzheimer's disease (AD), but their functional dynamics remain elusive. OBJECTIVE: To investigate the association between amyloid pathology, bacterial products such as lipopolysaccharide (LPS) and short chain fatty acids (SCFAs: acetate, valerate, butyrate), inflammatory mediators, and markers of endothelial dysfunction in AD. METHODS: Eighty-nine older persons with cognitive performance from normal to dementia underwent florbetapir amyloid PET and blood collection. Brain amyloidosis was measured with standardized uptake value ratio versus cerebellum. Blood levels of LPS were measured by ELISA, SCFAs by mass spectrometry, cytokines by using real-time PCR, and biomarkers of endothelial dysfunction by flow cytometry. We investigated the association between the variables listed above with Spearman's rank test. RESULTS: Amyloid SUVR uptake was positively associated with blood LPS (rho≥0.32, p≤0.006), acetate and valerate (rho≥0.45, p < 0.001), pro-inflammatory cytokines (rho≥0.25, p≤0.012), and biomarkers of endothelial dysfunction (rho≥0.25, p≤0.042). In contrast, it was negatively correlated with butyrate (rho≤-0.42, p≤0.020) and the anti-inflammatory cytokine IL10 (rho≤-0.26, p≤0.009). Endothelial dysfunction was positively associated with pro-inflammatory cytokines, acetate and valerate (rho≥0.25, p≤0.045) and negatively with butyrate and IL10 levels (rho≤-0.25, p≤0.038). CONCLUSION: We report a novel association between gut microbiota-related products and systemic inflammation with brain amyloidosis via endothelial dysfunction, suggesting that SCFAs and LPS represent candidate pathophysiologic links between the gut microbiota and AD pathology.

Sleep-Wake Cycle in Alzheimer's Disease Is Associated with Tau Pathology and Orexin Dysregulation. - Liguori, Claudio; Spanetta, Matteo; Izzi, Francesca; Franchini, Flaminia; Nuccetelli, Marzia; Sancesario, Giulia Maria; Di Santo, Simona; Bernardini, Sergio; Mercuri, Nicola Biagio; Placidi, Fabio (J Alzheimers Dis, 2020)
BACKGROUND: Alzheimer's disease (AD) is the most common form of dementia. It is mainly characterized by a progressive deterioration of cognition, but sleep-wake cycle disturbances frequently occur. Irregular sleep-wake cycle, insomnia, and daytime napping usually occur in patients with AD in the course of the disease. OBJECTIVE: The aim of the present study was to verify the sleep-wake cycle in mild to moderate AD patients compared to controls, and to evaluate the relationship between the sleep-wake cycle impairment and the neuropsychological testing, CSF AD biomarkers, and CSF orexin concentrations. METHODS: Mild to moderate AD patients were enrolled and underwent 14-day actigraphic recording, sleep diary, neuropsychological testing, and CSF biomarkers analysis. All patients were compared to controls. RESULTS: Eighteen AD patients were compared to ten controls. AD patients showed the alteration of the sleep-wake cycle, featured by sleep dysregulation and daytime wake fragmentation, with respect to controls. Considering the correlation analysis, we documented the correlation between tau proteins and orexin CSF levels and sleep-wake cycle dysregulation. CONCLUSION: This study confirmed the dysregulation of sleep-wake cycle in AD patients, as reflected by the daytime wake fragmentation, irregular sleep-wake rhythm, and nocturnal sleep impairment. This sleep-wake cycle disorder correlates with AD neuropathological in vivo features and brain orexin activity. Hence, we suppose that a more marked AD pathology coupled with orexinergic system dysregulation may promote sleep-wake cycle impairment in AD patients.

Structural Brain Magnetic Resonance Imaging to Rule Out Comorbid Pathology in the Assessment of Alzheimer's Disease Dementia: Findings from the Ontario Neurodegenerative Disease Research Initiative (ONDRI) Study and Clinical Trials Over the Past 10 Years. - Kapoor, Arunima; Bartha, Robert; Black, Sandra E; Borrie, Michael; Freedman, Morris; Gao, Fuqiang; Herrmann, Nathan; Mandzia, Jennifer; Ozzoude, Miracle; Ramirez, Joel; Scott, Christopher J M; Symons, Sean; et al. (J Alzheimers Dis, 2020)
BACKGROUND/OBJECTIVE: Structural brain magnetic resonance imaging (MRI) is not mandatory in Alzheimer's disease (AD) research or clinical guidelines. We aimed to explore the use of structural brain MRI in AD/mild cognitive impairment (MCI) trials over the past 10 years and determine the frequency with which inclusion of standardized structural MRI acquisitions detects comorbid vascular and non-vascular pathologies. METHODS: We systematically searched ClinicalTrials.gov for AD clinical trials to determine their neuroimaging criteria and then used data from an AD/MCI cohort who underwent standardized MRI protocols, to determine type and incidence of clinically relevant comorbid pathologies. RESULTS: Of 210 AD clinical trials, 105 (50%) included structural brain imaging in their eligibility criteria. Only 58 (27.6%) required MRI. 16,479 of 53,755 (30.7%) AD participants were in trials requiring MRI. In the observational AD/MCI cohort, 141 patients met clinical criteria; 22 (15.6%) had relevant MRI findings, of which 15 (10.6%) were exclusionary for the study. DISCUSSION: In AD clinical trials over the last 10 years, over two-thirds of participants could have been enrolled without brain MRI and half without even a brain CT. In a study sample, relevant comorbid pathology was found in 15% of participants, despite careful screening. Standardized structural MRI should be incorporated into NIA-AA diagnostic guidelines (when available) and research frameworks routinely to reduce diagnostic heterogeneity.

Synaptic Vesicle Protein 2B Negatively Regulates the Amyloidogenic Processing of AβPP as a Novel Interaction Partner of BACE1. - Miyamoto, Masakazu; Kuzuya, Akira; Noda, Yasuha; Ueda, Sakiho; Asada-Utsugi, Megumi; Ito, Shinji; Fukusumi, Yoshiyasu; Kawachi, Hiroshi; Takahashi, Ryosuke; Kinoshita, Ayae (J Alzheimers Dis, 2020)
BACKGROUND: Given that amyloid-β (Aβ) peptide is produced and released at synapses, synaptic Aβ is one of the promising therapeutic targets to prevent synaptic dysfunction in Alzheimer's disease (AD). Although Aβ production begins with the cleavage of the amyloid-β protein precursor (AβPP) by β-site AβPP cleaving enzyme 1 (BACE1), the mechanism on how BACE1 is involved in AβPP processing at synapses remains unclear. OBJECTIVE: This study aimed to identify novel BACE1 interacting proteins regulating Aβ production at the synapse. METHODS: BACE1 interacting proteins were pulled down using a mass spectrometry-based proteomics of wild-type (WT) rat brain synaptoneurosome lysates utilizing anti-BACE1 antibody. Then, a novel BACE1 interactor was identified and characterized using experimental systems that utilized transfected cells and knockout (KO) mice. RESULTS: Synaptic vesicle protein 2B (SV2B) was identified as a novel presynaptic interaction partner of BACE1. In HEK293 cells, co-overexpression of SV2B with BACE1 significantly reduced the sAβPPβ and Aβ levels released in the media; thus, SV2B overexpression negatively affected the AβPP cleavage by BACE1. Compared with those of WT mice, the hippocampal lysates of SV2B knockout mice had significantly elevated Aβ levels, whereas the β-secretase activity and the AβPP and BACE1 protein levels remained unchanged. Finally, a fractionation assay revealed that BACE1 was mislocalized in SV2B KO mice; hence, SV2B may be involved in BACE1 trafficking downregulating the amyloidogenic pathway of AβPP. CONCLUSION: SV2B has a novel role of negatively regulating the amyloidogenic processing of AβPP at the presynapses.

Ultra-High Field MRI in Alzheimer's Disease: Effective Transverse Relaxation Rate and Quantitative Susceptibility Mapping of Human Brain In Vivo and Ex Vivo Compared to Histology. - Tuzzi, Elisa; Balla, David Z; Loureiro, Joana R A; Neumann, Manuela; Laske, Christoph; Pohmann, Rolf; Preische, Oliver; Scheffler, Klaus; Hagberg, Gisela E (J Alzheimers Dis, 2020)
Alzheimer's disease (AD) is the most common cause of dementia worldwide. So far, diagnosis of AD is only unequivocally defined through postmortem histology. Amyloid plaques are a classical hallmark of AD and amyloid load is currently quantified by Positron Emission tomography (PET) in vivo. Ultra-high field magnetic resonance imaging (UHF-MRI) can potentially provide a non-invasive biomarker for AD by allowing imaging of pathological processes at a very-high spatial resolution. The first aim of this work was to reproduce the characteristic cortical pattern previously observed in vivo in AD patients using weighted-imaging at 7T. We extended these findings using quantitative susceptibility mapping (QSM) and quantification of the effective transverse relaxation rate (R2*) at 9.4T. The second aim was to investigate the origin of the contrast patterns observed in vivo in the cortex of AD patients at 9.4T by comparing quantitative UHF-MRI (9.4T and 14.1T) of postmortem samples with histology. We observed a distinctive cortical pattern in vivo in patients compared to healthy controls (HC), and these findings were confirmed ex vivo. Specifically, we found a close link between the signal changes detected by QSM in the AD sample at 14.1T and the distribution pattern of amyloid plaques in the histological sections of the same specimen. Our findings showed that QSM and R2* maps can distinguish AD from HC at UHF by detecting cortical alterations directly related to amyloid plaques in AD patients. Furthermore, we provided a method to quantify amyloid plaque load in AD patients at UHF non-invasively.

Validation of Plasma Proteomic Biomarkers Relating to Brain Amyloid Burden in the EMIF-Alzheimer's Disease Multimodal Biomarker Discovery Cohort. - Westwood, Sarah; Baird, Alison L; Anand, Sneha N; Nevado-Holgado, Alejo J; Kormilitzin, Andrey; Shi, Liu; Hye, Abdul; Ashton, Nicholas J; Morgan, Angharad R; Bos, Isabelle; Vos, Stephanie J B; Baker, Susan; et al. (J Alzheimers Dis, 2020)
We have previously investigated, discovered, and replicated plasma protein biomarkers for use to triage potential trials participants for PET or cerebrospinal fluid measures of Alzheimer's disease (AD) pathology. This study sought to undertake validation of these candidate plasma biomarkers in a large, multi-center sample collection. Targeted plasma analyses of 34 proteins with prior evidence for prediction of in vivo pathology were conducted in up to 1,000 samples from cognitively healthy elderly individuals, people with mild cognitive impairment, and in patients with AD-type dementia, selected from the EMIF-AD catalogue. Proteins were measured using Luminex xMAP, ELISA, and Meso Scale Discovery assays. Seven proteins replicated in their ability to predict in vivo amyloid pathology. These proteins form a biomarker panel that, along with age, could significantly discriminate between individuals with high and low amyloid pathology with an area under the curve of 0.74. The performance of this biomarker panel remained consistent when tested in apolipoprotein E ɛ4 non-carrier individuals only. This blood-based panel is biologically relevant, measurable using practical immunocapture arrays, and could significantly reduce the cost incurred to clinical trials through screen failure.

18F-FDG Is a Superior Indicator of Cognitive Performance Compared to 18F-Florbetapir in Alzheimer's Disease and Mild Cognitive Impairment Evaluation: A Global Quantitative Analysis. - Khosravi, Mohsen; Peter, Jonah; Wintering, Nancy A; Serruya, Mijail; Shamchi, Sara Pourhassan; Werner, Thomas J; Alavi, Abass; Newberg, Andrew B (J Alzheimers Dis, 2019)
BACKGROUND: 18F-Fluorodeoxyglucose (18F-FDG) positron emission tomography (PET) and 18F-florbetapir PET are approved neuroimaging biomarkers for the Alzheimer's disease (AD) and mild cognitive impairment (MCI). OBJECTIVES: This study aims to compare the efficacy of 18F-FDG and 18F-florbetapir PET at evaluating the cognitive performance of patients with AD, MCI, and normal controls (NCs). METHODS: 63 subjects (36 male/27 female, mean age = 68.3) including 19 AD, 23 MCI, and 21 NCs underwent 18F-FDG and 18F-florbetapir PET imaging. A global quantification approach was applied on supra-tentorial, frontal, parieto-occipital, temporal, and cerebellar brain regions by calculating the global SUVmean ratios (GSUVr) as the weighted average of all regional SUVmean. 18F-FDG and 18F-florbetapir GSUVr of each region were subsequently correlated with the Mini-Mental Status Examination (MMSE). RESULTS: Subjects were studied in five categories as NC, MCI patients, AD patients, MCI and AD patients grouped together (MCI/AD), and a group including all the subjects (NC/MCI/AD). Both 18F-FDG and 18F-florbetapir could successfully detect subjects with dementia (p <  0.001). Studied in all regions and groups, the correlation analysis of 18F-FDG GSUVr with MMSE scores was significant in more regions and groups compared to that of 18F-florbetapir. We also demonstrated that the correlation of 18F-FDG GSUVr with MMSE is stronger than that of 18F-florbetapir in the supra-tentorial and temporal regions. CONCLUSIONS: This study reveals how 18F-FDG-PET global quantification is a superior indicator of cognitive performance in AD and MCI patients compared to 18F-florbetapir PET. Accordingly, we still recommend 18F-FDG-PET over amyloid imaging in the evaluation for AD and MCI.

The Association between Mushroom Consumption and Mild Cognitive Impairment: A Community-Based Cross-Sectional Study in Singapore. - Feng, Lei; Cheah, Irwin Kee-Mun; Ng, Maisie Mei-Xi; Li, Jialiang; Chan, Sue Mei; Lim, Su Lin; Mahendran, Rathi; Kua, Ee-Heok; Halliwell, Barry (J Alzheimers Dis, 2019)
We examined the cross-sectional association between mushroom intake and mild cognitive impairment (MCI) using data from 663 participants aged 60 and above from the Diet and Healthy Aging (DaHA) study in Singapore. Compared with participants who consumed mushrooms less than once per week, participants who consumed mushrooms >2 portions per week had reduced odds of having MCI (odds ratio = 0.43, 95% CI 0.23-0.78, p = 0.006) and this association was independent of age, gender, education, cigarette smoking, alcohol consumption, hypertension, diabetes, heart disease, stroke, physical activities, and social activities. Our cross-sectional data support the potential role of mushrooms and their bioactive compounds in delaying neurodegeneration.

Association of Cognitive Function with Amyloid-β and Tau Proteins in the Vitreous Humor. - Wright, Lauren M; Stein, Thor D; Jun, Gyungah; Chung, Jaeyoon; McConnell, Kate; Fiorello, Marissa; Siegel, Nicole; Ness, Steven; Xia, Weiming; Turner, Kelley L; Subramanian, Manju L (J Alzheimers Dis, 2019)
BACKGROUND: The eye may serve as source for diagnostic testing for early detection of Alzheimer's disease (AD). Examination of amyloid-β (Aβ) and tau protein content in human vitreous and its correlation to neuro-cognition may improve ocular-based AD detection methods. OBJECTIVE: To evaluate levels of Aβ and tau protein in human vitreous humor and investigate the clinical predictive role of these proteins as early diagnostic markers of AD. METHODS: A prospective, single-center, multi-surgeon cohort study. Vitreous humor samples from 80 eyes were measured quantitatively for Aβ40-42, pTau, and tTau. Linear regression was used to test associations between AD biomarker levels, Mini-Mental State Exam (MMSE), and serum apolipoprotein E (APOE) allele status, with adjustment for age, sex, and education level of patients. RESULTS: Lower MMSE scores were significantly associated with lower levels of vitreous Aβ40 (p = 0.015), Aβ42 (p = 0.0066), and tTau (p = 0.0085), and these biomarkers were not associated with any pre-existing eye conditions. Presence of the ɛ4 allele and the ɛ2 allele approached significance with reduced Aβ40 level (p = 0.053) and increased p-Tau level (p = 0.056), respectively. CONCLUSION: Patients with poor cognitive function have significantly lower vitreous humor levels of AD-related biomarkers Aβ40, Aβ42, and tTau. These biomarkers do not correlate with underlying eye conditions, suggesting their specificity in association with cognitive change. This is the first study to our knowledge to correlate cognition with AD-related proteins in the vitreous humor. Results suggest ocular proteins may have a role for early dementia detection in individuals at risk for AD.

Clinico-Neuropathological Findings in the Oldest Old from the Georgia Centenarian Study. - Tanprasertsuk, Jirayu; Johnson, Elizabeth J; Johnson, Mary Ann; Poon, Leonard W; Nelson, Peter T; Davey, Adam; Martin, Peter; Barbey, Aron K; Barger, Kathryn; Wang, Xiang-Dong; Scott, Tammy M (J Alzheimers Dis, 2019)
BACKGROUND: Centenarian studies are important sources for understanding of factors that contribute to longevity and healthy aging. Clinico-neuropathological finding is a key in identifying pathology and factors contributing to age-related cognitive decline and dementia in the oldest old. OBJECTIVE: To characterize the cross-sectional relationship between neuropathologies and measures of premortem cognitive performance in centenarians. METHODS: Data were acquired from 49 centenarians (≥98 years) from the Georgia Centenarian Study. Cognitive assessment from the time point closest to mortality was used ( RESULTS: Wide ranges of AD-type neuropathological changes were observed in both non-demented and demented subjects. Neocortical NFT and Braak staging were related to clinical dementia rating. Neocortical NFT and NP, Braak and NIARI staging, cerebral and ventricular atrophy, HS, CAA, and TDP-43 proteinopathy were differentially associated with poor performance in multiple cognitive domains and activities of daily living. CONCLUSION: AD-type pathology was associated with severe dementia and poor cognition but was not the only variable that explained cognitive impairment, indicating the complexity and heterogeneity of pathophysiology of dementia in the oldest old.

Gender and Educational Differences in the Association between Lifestyle and Cognitive Decline over 10 Years: The Doetinchem Cohort Study. - Deckers, Kay; Nooyens, Astrid; van Boxtel, Martin; Verhey, Frans; Verschuren, Monique; Köhler, Sebastian (J Alzheimers Dis, 2019)
BACKGROUND: Several modifiable risk factors for cognitive decline have been identified, but whether differences by gender and educational level exist is unclear. OBJECTIVE: The present study aims to clarify this by prospectively investigating the relationship between health and lifestyle factors and cognitive functioning in different subgroups defined by gender and educational level. METHODS: 2,347 cognitive healthy individuals (mean age = 54.8, SD = 6.8, range: 41-71; 51.8% female; 26.2% low education) from the Doetinchem Cohort Study were examined for cognitive function at baseline, and at 5- and 10-year follow-up. Health- and lifestyle factors were captured by a poly-environmental risk score labelled 'LIfestyle for BRAin Health' (LIBRA). This score consists of 12 modifiable risk and protective factors for cognitive decline and dementia, with higher scores indicating greater risk (range: -2.7 to +12.7). Heterogeneity in associations between LIBRA and decline in verbal memory, cognitive flexibility, and mental speed between males and females and individuals with different levels of education were assessed in linear mixed models. RESULTS: Overall, higher LIBRA scores predicted faster decline in verbal memory, cognitive flexibility, and mental speed over 10 years. Higher LIBRA scores were further associated with increased risk for incident cognitive impairment (one-point increase in LIBRA: HR = 1.09, 1.04-1.14, p = 0.001). In general, these effects were similar across gender and educational level. CONCLUSION: A composite risk score comprising unhealthy lifestyle and relatively poor health in midlife is significantly associated with a worse course of cognition 10 years later. These associations were for the most part unrelated to gender or educational differences.

Geographical Variation in the Diagnostic Rate and Quality of Dementia Diagnoses. - Zakarias, Johanne Købstrup; Jensen-Dahm, Christina; Nørgaard, Ane; Roos, Peter; Gasse, Christiane; Phung, Thien Kieu Thi; Waldemar, Gunhild (J Alzheimers Dis, 2019)
BACKGROUND: Early and accurate diagnosis of dementia opens the door to appropriate treatment, support, and counseling. Despite availability of evidence-based guidelines for diagnostic evaluation of dementia, the diagnostic rate in people with dementia is low and the quality of dementia diagnoses is unknown. OBJECTIVE: The overall aim of this register-based study was to analyze the quality of diagnostic evaluation of dementia by assessing nationwide geographical variations in a range of indicators. METHODS: A register-based cross-sectional study of the entire Danish population aged 65 years or older in 2015 was conducted. The surrogate indicators for diagnostic quality included 1) prevalence rates of dementia diagnoses, 2) incidence rates of dementia diagnoses, 3) age at first diagnosis of dementia, 4) medical specialty responsible for diagnosis, 5) diagnostic rate of dementia subtypes, and 6) use of anti-dementia medication. The indicators were compared across the five Danish regions. RESULTS: The national prevalence and incidence of registered dementia diagnoses was 3.0% and 0.5%, respectively. The proportion of patients diagnosed at a dementia specialist department ranged from 60.9% to 90.5% across the five regions, subtype specific diagnosis ranged from 45.3% to 75.5%, and use of anti-dementia medication ranged from 29.2% to 58.3%. CONCLUSION: The observed geographical variations in dementia diagnoses and treatment indicate inequality in the access to appropriate diagnostic evaluation and care for patients with dementia. Our findings call for more awareness of the benefits of timely diagnosis and for improvement in the quality of diagnostic evaluation of dementia.

Glial Fibrillary Acidic Protein in Serum is Increased in Alzheimer's Disease and Correlates with Cognitive Impairment. - Oeckl, Patrick; Halbgebauer, Steffen; Anderl-Straub, Sarah; Steinacker, Petra; Huss, André M; Neugebauer, Hermann; von Arnim, Christine A F; Diehl-Schmid, Janine; Grimmer, Timo; Kornhuber, Johannes; Lewczuk, Piotr; Danek, Adrian; et al. (J Alzheimers Dis, 2019)
Reliable blood biomarkers for Alzheimer's disease (AD) are missing. We measured astroglial GFAP in patients with AD (n = 28), frontotemporal dementia (bvFTD, n = 35), Parkinson's disease (n = 11), Lewy body dementias (n = 19), and controls (n = 34). Serum GFAP was increased in AD (p < 0.001) and DLB/PDD (p < 0.01), and cerebrospinal fluid GFAP was increased in all neurodegenerative diseases (p < 0.001). Serum GFAP correlated with the Mini-Mental State Examination score (r= -0.42, p < 0.001) and might be a follow-up marker in clinical trials. Sensitivity and specificity of serum GFAP for AD versus bvFTD was 89% and 79% and might be the first blood biomarker in the differential diagnosis of AD and bvFTD.

Herpes Simplex Virus, APOEɛ4, and Cognitive Decline in Old Age: Results from the Betula Cohort Study. - Lövheim, Hugo; Norman, Tove; Weidung, Bodil; Olsson, Jan; Josefsson, Maria; Adolfsson, Rolf; Nyberg, Lars; Elgh, Fredrik (J Alzheimers Dis, 2019)
BACKGROUND: Herpes simplex virus (HSV) has been suggested to play a role in Alzheimer's disease (AD) development. OBJECTIVE: The aim of the present study was to investigate the early AD-related symptom episodic memory decline in relation to HSV and carriage of allele 4 of the apolipoprotein E gene (APOEɛ4) in a large population-based cohort with a long follow-up time. METHODS: The study included 3,413 persons, with longitudinal data available for 1,293 persons with a mean follow-up time of 11.6 years. The associations between HSV carriage, APOEɛ4 carriage, and episodic memory was investigated at baseline, as well as in longitudinal analyses where individuals with and without HSV antibodies (HSV1/2 non-specific) were matched and episodic memory decline compared. RESULTS: Cross-sectional analyses revealed an age-dependent association of HSV carriage with lower episodic memory function, particularly among APOEɛ4 carriers (p = 0.008). Longitudinal analyses showed an increased risk of episodic memory decline in HSV carriers (≥65 years: p < 0.001, all ages: non-significant), and a significant interaction between HSV and APOEɛ4 for episodic memory decline (p < 0.001). CONCLUSION: In this large population-based cohort study, both cross-sectional and longitudinal results support an association between HSV carriage and declining episodic memory function, especially among APOEɛ4 carriers. The results strengthen the hypothesis that HSV is associated with AD development.

Improved Differential Diagnosis of Alzheimer's Disease by Integrating ELISA and Mass Spectrometry-Based Cerebrospinal Fluid Biomarkers. - Khoonsari, Payam Emami; Shevchenko, Ganna; Herman, Stephanie; Remnestål, Julia; Giedraitis, Vilmantas; Brundin, RoseMarie; Degerman Gunnarsson, Malin; Kilander, Lena; Zetterberg, Henrik; Nilsson, Peter; Lannfelt, Lars; Ingelsson, Martin; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Alzheimer's disease (AD) is diagnosed based on a clinical evaluation as well as analyses of classical biomarkers: Aβ42, total tau (t-tau), and phosphorylated tau (p-tau) in cerebrospinal fluid (CSF). Although the sensitivities and specificities of the classical biomarkers are fairly good for detection of AD, there is still a need to develop novel biochemical markers for early detection of AD. OBJECTIVE: We explored if integration of novel proteins with classical biomarkers in CSF can better discriminate AD from non-AD subjects. METHODS: We applied ELISA, mass spectrometry, and multivariate modeling to investigate classical biomarkers and the CSF proteome in subjects (n = 206) with 76 AD patients, 74 mild cognitive impairment (MCI) patients, 11 frontotemporal dementia (FTD) patients, and 45 non-dementia controls. The MCI patients were followed for 4-9 years and 21 of these converted to AD, whereas 53 remained stable. RESULTS: By combining classical CSF biomarkers with twelve novel markers, the area of the ROC curves (AUROCS) of distinguishing AD and MCI/AD converters from non-AD were 93% and 96%, respectively. The FTDs and non-dementia controls were identified versus all other groups with AUROCS of 96% and 87%, respectively. CONCLUSIONS: Integration of new and classical CSF biomarkers in a model-based approach can improve the identification of AD, FTD, and non-dementia control subjects.

Influx of Tau and Amyloid-β Proteins into the Blood During Hemodialysis as a Therapeutic Extracorporeal Blood Amyloid-β Removal System for Alzheimer's Disease. - Kitaguchi, Nobuya; Tatebe, Harutsugu; Sakai, Kazuyoshi; Kawaguchi, Kazunori; Matsunaga, Shinji; Kitajima, Tomoko; Tomizawa, Hiroshi; Kato, Masao; Sugiyama, Satoshi; Suzuki, Nobuo; Mizuno, Masao; Takechi, Hajime; et al. (J Alzheimers Dis, 2019)
The accumulation of amyloid-β protein (Aβ) and tau in the brain is a major pathological change related to Alzheimer's disease. We have continued to develop Extracorporeal Blood Aβ Removal Systems (E-BARS) as a method for enhancing Aβ clearance from the brain. Our previous report revealed that dialyzers effectively remove blood Aβ and evoke large Aβ influxes into the blood, resulting in a decrease in brain Aβ accumulation after initiating hemodialysis, and that patients who underwent hemodialysis had lower brain Aβ accumulation than those who did not. Here, plasma total tau concentrations from 30 patients undergoing hemodialysis were measured using an ultrasensitive immunoassay and compared to those from 11 age-matched controls. Plasma total tau concentrations were higher in patients with renal failure regardless of whether they underwent hemodialysis, suggesting the involvement of the kidneys in tau degradation and excretion. Hemodialyzers effectively removed blood Aβ but not extracorporeal blood tau. The influx of tau into the blood was observed at around the 1 h period during hemodialysis sessions. However, the influx amount of tau was far smaller than that of Aβ. Furthermore, histopathological analysis revealed similar, not significantly less, cerebral cortex phosphorylated tau accumulation between the 17 patients who underwent hemodialysis and the 16 age-matched subjects who did not, although both groups showed sparse accumulation. These findings suggest that hemodialysis may induce both tau and Aβ migration into the blood. However, as a therapeutic strategy for Alzheimer's disease, it may only be effective for removing Aβ from the brain.

Long-Term Trazodone Use and Cognition: A Potential Therapeutic Role for Slow-Wave Sleep Enhancers. - La, Alice L; Walsh, Christine M; Neylan, Thomas C; Vossel, Keith A; Yaffe, Kristine; Krystal, Andrew D; Miller, Bruce L; Karageorgiou, Elissaios (J Alzheimers Dis, 2019)
BACKGROUND: Recent studies reveal an association between slow-wave sleep (SWS), amyloid-β aggregation, and cognition. OBJECTIVE: This retrospective study examines whether long-term use of trazodone, an SWS enhancer, is associated with delayed cognitive decline. METHODS: We identified 25 regular trazodone users (mean age 75.4±7.5; 9 women, 16 men) who carried a diagnosis of Alzheimer's dementia, mild cognitive impairment, or normal cognition, and 25 propensity-matched trazodone non-users (mean age 74.5±8.0; 13 women, 12 men), accounting for age, sex, education, type of sleep deficit (hypersomnia, insomnia, parasomnia), diagnosis, and baseline Mini-Mental State Examination (MMSE). Longitudinal group differences in cognitive testing were evaluated through repeated measures tests over an average inter-evaluation interval of four years. RESULTS: Trazodone non-users had 2.6-fold faster decline MMSE (primary outcome) compared to trazodone users, 0.27 (95% confidence interval [CI]: 0.07-0.48) versus 0.70 (95% CI: 0.50-0.90) points per year (p = 0.023). The observed effects were especially associated with subjective improvement of sleep complaints in post-hoc analyses (p = 0.0006). Secondary outcomes of other cognitive and functional scores had variable worsening in non-users and varied in significance when accounting for co-administered medications and multiple comparisons. Trazodone effects on MMSE remained significant within participants with AD-predicted pathology, with 2.4-fold faster decline in non-users (p = 0.038). CONCLUSIONS: These results suggest an association between trazodone use and delayed cognitive decline, adding support for a potentially attractive and cost-effective intervention in dementia. Whether the observed relationship of trazodone to cognitive function is causal or an indirect marker of other effects, such as treated sleep disruption, and if such effects are mediated through SWS enhancement requires confirmation through prospective studies.

Maintain Your Brain: Protocol of a 3-Year Randomized Controlled Trial of a Personalized Multi-Modal Digital Health Intervention to Prevent Cognitive Decline Among Community Dwelling 55 to 77 Year Olds. - Heffernan, Megan; Andrews, Gavin; Fiatarone Singh, Maria A; Valenzuela, Michael; Anstey, Kaarin J; Maeder, Anthony J; McNeil, John; Jorm, Louisa; Lautenschlager, Nicola T; Sachdev, Perminder S; Ginige, Jeewani A; Hobbs, Megan J; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Maintain Your Brain (MYB) is a randomized controlled trial of an online multi-modal lifestyle intervention targeting modifiable dementia risk factors with its primary aim being to reduce cognitive decline in an older age cohort. METHODS: MYB aims to recruit 8,500 non-demented community dwelling 55 to 77 year olds from the Sax Institute's 45 and Up Study in New South Wales, Australia. Participants will be screened for risk factors related to four modules that comprise the MYB intervention: physical activity, nutrition, mental health, and cognitive training. Targeting risk factors will enable interventions to be personalized so that participants receive the most appropriate modules. MYB will run for three years and up to four modules will be delivered sequentially each quarter during year one. Upon completing a module, participants will continue to receive less frequent booster activities for their eligible modules (except for the mental health module) until the end of the trial. DISCUSSION: MYB will be the largest internet-based trial to attempt to prevent cognitive decline and potentially dementia. If successful, MYB will provide a model for not just effective intervention among older adults, but an intervention that is scalable for broad use.

The MemTrax Test Compared to the Montreal Cognitive Assessment Estimation of Mild Cognitive Impairment. - van der Hoek, Marjanne D; Nieuwenhuizen, Arie; Keijer, Jaap; Ashford, J Wesson (J Alzheimers Dis, 2019)
Cognitive impairment is a leading cause of dysfunction in the elderly. When mild cognitive impairment (MCI) occurs in elderly, it is frequently a prodromal condition to dementia. The Montreal Cognitive Assessment (MoCA) is a commonly used tool to screen for MCI. However, this test requires a face-to-face administration and is composed of an assortment of questions whose responses are added together by the rater to provide a score whose precise meaning has been controversial. This study was designed to evaluate the performance of a computerized memory test (MemTrax), which is an adaptation of a continuous recognition task, with respect to the MoCA. Two outcome measures are generated from the MemTrax test: MemTraxspeed and MemTraxcorrect. Subjects were administered the MoCA and the MemTrax test. Based on the results of the MoCA, subjects were divided in two groups of cognitive status: normal cognition (n = 45) and MCI (n = 37). Mean MemTrax scores were significantly lower in the MCI than in the normal cognition group. All MemTrax outcome variables were positively associated with the MoCA. Two methods, computing the average MTX score and linear regression were used to estimate the cutoff values of the MemTrax test to detect MCI. These methods showed that for the outcome MemTraxspeed a score below the range of 0.87 - 91 s-1 is an indication of MCI, and for the outcome MemTraxcorrect a score below the range of 85 - 90% is an indication for MCI.

A Meta-Analysis of Alzheimer's Disease Brain Transcriptomic Data. - Patel, Hamel; Dobson, Richard J B; Newhouse, Stephen J (J Alzheimers Dis, 2019)
BACKGROUND: Microarray technologies have identified imbalances in the expression of specific genes and biological pathways in Alzheimer's disease (AD) brains. However, there is a lack of reproducibility across individual AD studies, and many related neurodegenerative and mental health disorders exhibit similar perturbations. OBJECTIVE: Meta-analyze publicly available transcriptomic data from multiple brain-related disorders to identify robust transcriptomic changes specific to AD brains. METHODS: Twenty-two AD, eight schizophrenia, five bipolar disorder, four Huntington's disease, two major depressive disorder, and one Parkinson's disease dataset totaling 2,667 samples and mapping to four different brain regions (temporal lobe, frontal lobe, parietal lobe, and cerebellum) were analyzed. Differential expression analysis was performed independently in each dataset, followed by meta-analysis using a combining p-value method known as Adaptively Weighted with One-sided Correction. RESULTS: Meta-analysis identified 323, 435, 1,023, and 828 differentially expressed genes specific to the AD temporal lobe, frontal lobe, parietal lobe, and cerebellum brain regions, respectively. Seven of these genes were consistently perturbed across all AD brain regions with SPCS1 gene expression pattern replicating in RNA-Seq data. A further nineteen genes were perturbed specifically in AD brain regions affected by both plaques and tangles, suggesting possible involvement in AD neuropathology. In addition, biological pathways involved in the "metabolism of proteins" and viral components were significantly enriched across AD brains. CONCLUSION: This study identified transcriptomic changes specific to AD brains, which could make a significant contribution toward the understanding of AD disease mechanisms and may also provide new therapeutic targets.

Neuropsychological Deficit Profiles, Vascular Risk Factors, and Neuropathological Findings in Hispanic Older Adults with Autopsy-Confirmed Alzheimer's Disease. - Weissberger, Gali H; Gollan, Tamar H; Bondi, Mark W; Nation, Daniel A; Hansen, Lawrence A; Galasko, Douglas; Salmon, David P (J Alzheimers Dis, 2019)
This study aimed to determine if patterns of neuropsychological deficits, vascular risk factors, and neuropathology differ in Hispanic and Non-Hispanic patients with autopsy-confirmed Alzheimer's disease (AD). Participants were enrolled in a longitudinal study at the Shiley-Marcos AD Research Center at the University of California, San Diego. Hispanic (n = 14) and Non-Hispanic (n = 20) patients with autopsy-confirmed AD who scored ≥95 on the Dementia Rating Scale (DRS) were included. Patient groups were matched on age, education, global mental status, and severity of functional decline; they were compared to Hispanic (n = 14) or Non-Hispanic (n = 20) cognitively-normal controls of similar age and education. Ethnicity (Hispanic, Non-Hispanic) by disease state (autopsy-confirmed AD or cognitively normal) comparisons were made for cognitive test performance and vascular risk factors. Patient groups were further compared on measures of AD (Braak stage, neuritic plaques, neurofibrillary tangles), vascular neuropathology, and performance across cognitive domains of memory, language, attention, executive functions, and visuospatial abilities after scores were z-transformed based on respective culturally-appropriate control groups. Patient groups had similar overall AD pathology burden, whereas Hispanics with AD had more small parenchymal arteriolar disease and amyloid angiopathy than Non-Hispanics with AD. Despite largely similar pathology, Hispanics with AD were less cognitively impaired (relative to respective NC groups) than Non-Hispanics with AD, and exhibited a different pattern of deficits across cognitive domains. Findings suggest that cognitive deficits that are usually prominent in AD may be less salient in Hispanic patients and this may adversely impact the ability to clinically detect the disease in mild to moderate stages.

The Pathology of Rapid Cognitive Decline in Clinically Diagnosed Alzheimer's Disease. - Nance, Christin; Ritter, Aaron; Miller, Justin B; Lapin, Brittany; Banks, Sarah J (J Alzheimers Dis, 2019)
BACKGROUND: Variable rate of cognitive decline among individuals with Alzheimer's disease (AD) is an important consideration for disease management, but risk factors for rapid cognitive decline (RCD) are without consensus. OBJECTIVE: To investigate demographic, clinical, and pathological differences between RCD and normal rates of cognitive decline (NCD) in AD. METHODS: Neuropsychology test and autopsy data was pulled from the National Alzheimer's Coordinating Center database from individuals with a clinical diagnosis of AD. Individuals with average decline of 3 or more points on the Mini-Mental Status Examination (MMSE) per year over 3 years were labeled RCD; all others were NCD. RESULTS: Sixty individuals identified as RCD; 230 as NCD. These neuropsychology tests differed at baseline (RCD versus NCD): WMS-LM Immediate Recall (4.35[3.39] versus 6.31[3.97], p < 0.001), Animal Naming (12.1[4.83] versus 13.9[4.83], p = 0.007), TMT Part B (187[86.1] versus 159[79.0], p = 0.02), WAIS-Digit Symbol (29.5[11.3] versus 29.5[11.3], p = 0.04), and the BNT (21.5[7.05] versus 23.6[5.09], p = 0.04). RCD had more thyroid disease (30% versus 16%, p = 0.01) and greater usage of AD medication at baseline (80% versus 62%, p = 0.01). RCD had more severe cerebral amyloid angiopathy (1.62(1.0) versus1.13(1.0), p = 0.002), more neocortical Lewy bodies (20% versus 10%, p = 0.04), and more atrophy (1.54[0.92] versus 1.17[0.83], p = 0.04). A model combining select variables was significant above chance (χ2 = 25.8, p = 0.002), but not to clinical utility (AUC < 0.70; 95% CI). CONCLUSION: Individuals with RCD have more severe pathology, more comorbidities, and lower baseline neuropsychology test scores of language and executive function.

Porphyromonas gingivalis Infection Induces Amyloid-β Accumulation in Monocytes/Macrophages. - Nie, Ran; Wu, Zhou; Ni, Junjun; Zeng, Fan; Yu, Weixian; Zhang, Yufeng; Kadowaki, Tomoko; Kashiwazaki, Haruhiko; Teeling, Jessica L; Zhou, Yanmin (J Alzheimers Dis, 2019)
Abnormal accumulation of amyloid-β (Aβ) in the brain is the most significant pathological hallmark of Alzheimer's disease (AD). We have found that chronic systemic exposure to lipopolysaccharide of Porphyromonas gingivalis (P. gingivalis) induces the accumulation of Aβ in the brain of middle-aged mice. On the other hand, recent research has shown that circulating Aβ is transferred into the brain; however, the involvement of chronic systemic P. gingivalis infection in the peripheral Aβ metabolism is unknown. We hypothesized that chronic P. gingivalis infection expands Aβ pools in peripheral inflammatory tissues and thereby contributes to the accumulation of Aβ in the brain of patients with periodontitis. We showed that the increased expression of IL-1β, AβPP770, CatB, Aβ1-42, and Aβ3-42 was mainly co-localized with macrophages in the liver of P. gingivalis infected mice. Blocking CatB and NF-κB significantly inhibited the P. gingivalis-induced expression of IL-1β, AβPP770, Aβ1-42, and Aβ3-42 in RAW264.7 cells. Aβ3-42, but not Aβ1-42, induced the significant death of macrophages, and the reduction of phagocytic abilities induced by Aβ3-42 tended to be higher than that induced by Aβ1-42. Additionally, the expression of AβPP770, CatB, Aβ1-42, and Aβ3-42 was determined in the macrophages of gingival tissues from periodontitis patients. These findings indicate that chronic systemic P. gingivalis infection induces the Aβ accumulation in inflammatory monocytes/macrophages via the activation of CatB/NF-κB signaling, thus suggesting monocytes/macrophages serve as a circulating pool of Aβ in patients with periodontitis. Taken together, CatB may be a novel therapeutic target for preventing the periodontitis-related AD initiation and pathological progression.

Self and Informant Memory Reports in FINGER: Associations with Two-Year Cognitive Change. - Vaskivuo, Laura; Hokkanen, Laura; Hänninen, Tuomo; Antikainen, Riitta; Bäckman, Lars; Laatikainen, Tiina; Paajanen, Teemu; Stigsdotter-Neely, Anna; Strandberg, Timo; Tuomilehto, Jaakko; Soininen, Hilkka; Kivipelto, Miia; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Subjective memory complaints (SMCs) may be the first sign of cognitive decline in aging. OBJECTIVE: To examine whether SMCs reported by oneself and informant predict cognitive change over 2 years among at-risk elderly people, and to determine the relationship of different types of SMCs (prospective and retrospective memory complaints) and change in cognitive function. METHODS: This investigation is part of the FINGER project, which is a multicenter randomized controlled trial aiming at preventing cognitive decline in cognitively healthy older adults with increased risk of dementia. A subsample of 303 control-group participants (aged 60-80 years) and their informants (n = 261) rated the frequency of SMCs, using the Prospective and Retrospective Memory Questionnaire (PRMQ). Cognitive performance was measured at baseline and at 1- and 2-year follow-up visits using a neuropsychological test battery. RESULTS: Participants who reported more SMCs improved less in global cognition, executive function, and memory during the subsequent 2 years in the fully-adjusted analyses. Self-reported retrospective memory problems predicted less improvement in all cognitive domains, whereas prospective memory problems did not. Informant-reported memory problems were not linked to subsequent change in cognition. CONCLUSION: Our results indicate that self-reported SMCs, measured with PRMQ, predict future cognitive change in several cognitive domains. By contrast, reports by informants were not linked to changes in cognition. Among cognitively healthy at-risk elderly individuals, the persons themselves observe more easily problems relevant for their future cognitive trajectories than their informants.

Serum Insulin-Like Growth Factor I Deficiency Associates to Alzheimer's Disease Co-Morbidities. - Zegarra-Valdivia, Jonathan A; Santi, Andrea; Fernández de Sevilla, Maria Estrella; Nuñez, Angel; Torres Aleman, Ignacio (J Alzheimers Dis, 2019)
Increasing evidence supports the notion that Alzheimer's disease (AD), a condition that presents heterogeneous pathological disturbances, is also associated to perturbed metabolic function affecting insulin and insulin-like growth factor I (IGF-I). While impaired insulin activity leading to insulin resistance has been associated to AD, whether altered IGF-I function affects the disease is not entirely clear. Despite the limitations of mouse models to mimic AD pathology, we took advantage that serum IGF-I deficient mice (LID mice) present many functional perturbations present in AD, most prominently cognitive loss, which is reversed by treatment with systemic IGF-I. We analyzed whether these mice display other pathological traits that are usual co-morbidities of AD. We found that LID mice not only display cognitive disturbances, but also show altered mood and sociability, increased susceptibility to epileptiform activity, and a disturbed sleep/wake cycle. Collectively, these data suggest that reduced IGF-I activity contributes to heterogeneous deficits commonly associated to AD. We suggest that impaired IGF-I activity needs to be taken into consideration when modeling this condition.

Sirtuin 3 Mediates Tau Deacetylation. - Li, Shiping; Yin, Junxiang; Nielsen, Megan; Beach, Thomas G; Guo, Li; Shi, Jiong (J Alzheimers Dis, 2019)
BACKGROUND: Emerging evidence shows tau acetylation has been observed in Alzheimer's disease (AD) brain at early Braak stages and is involved in regulating tau early accumulation. However, the effects of deacetylase Sirtuin 3 (Sirt3) on tau acetylation and its aggregations are unclear. OBJECTIVE: We studied the effects of Sirt3 on tau acetylation and its aggregations. METHODS: We investigated the protein levels of Sirt3 and tangle tau in human postmortem brains slices from AD, mild cognitive impairment, and age- and education-matched cognitively normal subjects, and AD model mice. We also measured tau acetylation levels in hippocampal HT22 cells after Sirt3 knockdown or overexpression. RESULTS: The level of Sirt3 was inversely related with tau protein in brain slices from both human being and AD model mice. Mechanistically, tau acetylation decreased dramatically with Sirt3 overexpression, while tau acetylation increased after Sirt3 knockdown in hippocampal HT22 cells. CONCLUSIONS: Sirt3 may play a role in tau acetylation and could be a potential target for novel therapy to alleviate tau accumulation.

Tau and Amyloid-β Pathology in Japanese Forensic Autopsy Series Under 40 Years of Age: Prevalence and Association with APOE Genotype and Suicide Risk. - Yoshida, Koji; Hata, Yukiko; Ichimata, Shojiro; Nishida, Naoki (J Alzheimers Dis, 2019)
BACKGROUND: Aggregation of abnormal phosphorylated tau in brain stem areas may be a possible early pathological manifestation of Alzheimer's disease (AD). OBJECTIVE: This study aimed to explore the prevalence of cases with AD-related pathology in subjects METHOD: We conducted brain immunohistochemistry for 189 cases RESULTS: Tau pathology was detected in 135 cases (71.4%; 13-39 years; only LC, 23 cases; only RN, 4 cases; only ErC, 35 cases; LC+RN, 3 cases; LC+ErC, 57 cases; all three regions, 10 cases). The prevalence of thread pathology was higher than that of cellular inclusions. Significantly higher prevalence of the APOEɛ2 allele were found in 10-39 years of age natural death cases (p < 0.05). Amyloid-β deposition was found in only 7 cases, along with a significantly high frequency of the ɛ4 allele (p < 0.05). While a past history of psychiatric disease was a significant risk factor for suicide, AD-related pathology was not associated with suicide. CONCLUSIONS: Both the brain stem and entorhinal cortex was the initial site of tau pathology in many younger subjects. AD-related pathology may not be a significant accelerating factor for suicide in younger subjects.

Telomere Shortening in the Alzheimer's Disease Neuroimaging Initiative Cohort. - Nudelman, Kelly N H; Lin, Jue; Lane, Kathleen A; Nho, Kwangsik; Kim, Sungeun; Faber, Kelley M; Risacher, Shannon L; Foroud, Tatiana M; Gao, Sujuan; Davis, Justin W; Weiner, Michael W; Saykin, Andrew J (J Alzheimers Dis, 2019)
BACKGROUND: Although shorter telomeres have been associated with Alzheimer's disease (AD), it is unclear whether longitudinal change in telomere length is associated with AD progression. OBJECTIVE: To investigate the association of telomere length change with AD diagnosis and progression. METHODS: In 653 individuals from the Alzheimer's Disease Neuroimaging Initiative (ADNI) cohort, T/S ratio (telomere versus single copy gene), a proxy of telomere length, was measured for up to five visits per participant (N = 1918 samples post-QC) using quantitative PCR (qPCR). T/S ratio was adjusted for batch effects and DNA storage time. A mixed effects model was used to evaluate association of telomere length with AD diagnostic group and interaction of age and diagnosis. Another mixed effects model was used to compare T/S ratio changes pre- to post-conversion to MCI or AD to telomere change in participants with stable diagnoses. RESULTS: Shorter telomeres were associated with older age (Effect Size (ES) = -0.23) and male sex (ES = -0.26). Neither baseline T/S ratio (ES = -0.036) nor T/S ratio change (ES = 0.046) differed significantly between AD diagnostic groups. MCI/AD converters showed greater, but non-significant, telomere shortening compared to non-converters (ES = -0.186). CONCLUSIONS: Although AD compared to controls showed small, non-significant effects for baseline T/S ratio and T/S ratio shortening, we did observe a larger, though still non-significant effect for greater telomere shortening in converters compared to non-converters. Although our results do not support telomere shortening as a robust biomarker of AD progression, further investigation in larger samples and for subgroups of participants may be informative.

Traffic-Related Air Pollution as a Risk Factor for Dementia: No Clear Modifying Effects of APOEɛ4 in the Betula Cohort. - Oudin, Anna; Andersson, John; Sundström, Anna; Nordin Adolfsson, Annelie; Oudin Åström, Daniel; Adolfsson, Rolf; Forsberg, Bertil; Nordin, Maria (J Alzheimers Dis, 2019)
It is widely known that the apolipoprotein E (APOE) ɛ4 allele imposes a higher risk for Alzheimer's disease (AD). Recent evidence suggests that exposure to air pollution is also a risk factor for AD, and results from a few studies indicate that the effect of air pollution on cognitive function and dementia is stronger in APOEɛ4 carriers than in non-carriers. Air pollution and interaction with APOEɛ4 on AD risk thus merits further attention. We studied dementia incidence over a 15-year period from the longitudinal Betula study in Northern Sweden. As a marker for long-term exposure to traffic-related air pollution, we used modelled annual mean nitrogen oxide levels at the residential address of the participants at start of follow-up. Nitrogen oxide correlate well with fine particulate air pollution levels in the study area. We had full data on air pollution, incidence of AD and vascular dementia (VaD), APOEɛ4 carrier status, and relevant confounding factors for 1,567 participants. As expected, air pollution was rather clearly associated with dementia incidence. However, there was no evidence for a modifying effect by APOEɛ4 on the association (p-value for interaction > 0.30 for both total dementia (AD+VaD) and AD). The results from this study do not imply that adverse effects of air pollution on dementia incidence is limited to, or stronger in, APOEɛ4 carriers than in the total population.

Transcriptome Changes in the Alzheimer's Disease Middle Temporal Gyrus: Importance of RNA Metabolism and Mitochondria-Associated Membrane Genes. - Piras, Ignazio S; Krate, Jonida; Delvaux, Elaine; Nolz, Jennifer; Mastroeni, Diego F; Persico, Antonio M; Jepsen, Wayne M; Beach, Thomas G; Huentelman, Matthew J; Coleman, Paul D (J Alzheimers Dis, 2019)
We used Illumina Human HT-12 v4 arrays to compare RNA expression of middle temporal gyrus (MTG; BA21) in Alzheimer's disease (AD = 97) and non-demented controls (ND = 98). A total of 938 transcripts were highly differentially expressed (adj p < 0.01; log2 FC ≥ |0.500|, with 411 overexpressed and 527 underexpressed in AD. Our results correlated with expression profiling in neurons from AD and ND obtained by laser capture microscopy in MTG from an independent dataset (log2 FC correlation: r = 0.504; p = 2.2e-16). Additionally, selected effects were validated by qPCR. ANOVA analysis yielded no difference between genders in response to AD, but some gender specific genes were detected (e.g., IL8 and AGRN in males, and HSPH1 and GRM1 in females). Several transcripts were associated with Braak staging (e.g., AEBP1 and DNALI1), antemortem MMSE (e.g., AEBP1 and GFAP), and tangle density (e.g., RNU1G2, and DNALI1). At the pathway level, we detected enrichment of synaptic vesicle processes and GABAergic transmission genes. Finally, applying the Weighted Correlation Network Analysis, we identified four expression modules enriched for neuronal and synaptic genes, mitochondria-associated membrane, chemical stimulus and olfactory receptor and non-coding RNA metabolism genes. Our results represent an extensive description of MTG mRNA profiling in a large sample of AD and ND. These data provide a list of genes associated with AD, and correlated to neurofibrillary tangles density. In addition, these data emphasize the importance of mitochondrial membranes and transcripts related to olfactory receptors in AD.

Two Year Outcomes, Cognitive and Behavioral Markers of Decline in Healthy, Cognitively Normal Older Persons with Global Deterioration Scale Stage 2 (Subjective Cognitive Decline with Impairment). - Reisberg, Barry; Torossian, Carol; Shulman, Melanie B; Monteiro, Isabel; Boksay, Istvan; Golomb, James; Guillo Benarous, Francoise; Ulysse, Anaztasia; Oo, Thet; Vedvyas, Alok; Rao, Julia A; Marsh, Karyn; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Little is known with respect to behavioral markers of subjective cognitive decline (SCD), a condition initially described in association with Global Deterioration Scale (GDS) stage 2. OBJECTIVE: Two-year interval behavioral markers were investigated herein. METHODS: Subjects from a published 7-year outcome study of GDS stage 2 subjects were selected. This study had demonstrated a hazard ratio of 4.5 for progression of GDS stage 2, in comparison with GDS stage 1 (no subjective or objective cognitive decline) subjects, after controlling for demographic and temporal variables. Because GDS 2 subjects have previously demonstrated impairment in comparison with healthy persons free of complaints, we herein suggest the terminology "SCD(I)" for these persons. 98 SCD(I) persons, 63 women and 35 men, mean baseline age, 67.12±8.75 years, with a mean educational background of 15.55±2.60 years, and mean baseline MMSE scores of 28.9±1.24 were followed for 2.13±0.30 years. RESULTS: Observed annual decline on the GDS was 6.701% per annum, very close to a 1986 published estimate. At follow up, the MMSE, and 7 of 8 psychometric tests did not decline significantly. Of 21 Hamilton Depression Scale items, 2 improved and the remainder were unchanged. Anxieties declined from multiple perspectives. The Brief Cognitive Rating Scale (BCRS) declined significantly (p < 0.001), with component declines in Remote memory (p < 0.01), and Functioning/self-care (p = 0.01). CONCLUSION: SCD(I) persons decline at an annual rate of approximately 6.7% /year from several recent studies. The BCRS assessments and the Digit Symbol Substitution Test can be sensitive measures for future studies of progression mitigation.

Upregulation of Thioredoxin-Interacting Protein in Brain of Amyloid-β Protein Precursor/Presenilin 1 Transgenic Mice and Amyloid-β Treated Neuronal Cells. - Wang, Yiran; Wang, Ying; Bharti, Veni; Zhou, Hong; Hoi, Vanessa; Tan, Hua; Wu, Zijian; Nagakannan, Pandian; Eftekharpour, Eftekhar; Wang, Jun-Feng (J Alzheimers Dis, 2019)
Oxidative stress has been hypothesized to play a role in the pathophysiology of Alzheimer's disease (AD). Previously, we found that total nitrosylated protein levels were increased in the brain of amyloid-β protein precursor (AβPP) and presenilin 1 (PS1) double transgenic mice, an animal model for AD, suggesting that cysteine oxidative protein modification may contribute to this disease. Thioredoxin (Trx) is a major oxidoreductase that can reverse cysteine oxidative modifications such as sulfenylation and nitrosylation, and inhibit oxidative stress. Thioredoxin-interacting protein (Txnip) is an endogenous Trx inhibitor. To understand the involvement of Trx and Txnip in AD development, we investigated Trx and Txnip in the brain of AβPP/PS1 mice. Using immunoblotting analysis, we found that although Trx protein levels were not changed, Txnip protein levels were significantly increased in hippocampus and frontal cortex of 9- and 12-month-old AβPP/PS1 mice when compared to wild-type mice. Txnip protein levels were also increased by amyloid-β treatment in primary cultured mouse cerebral cortical neurons and HT22 mouse hippocampal cells. Using biotin switch and dimedone conjugation methods, we found that amyloid-β treatment increased protein nitrosylation and sulfenylation in HT22 cells. We also found that downregulation of Txnip, using CRISPR/Cas9 method in HT22 cells, attenuated amyloid-β-induced protein nitrosylation and sulfenylation. Our findings suggest that amyloid-β may increase Txnip levels, subsequently inhibiting Trx reducing capability and enhancing protein cysteine oxidative modification. Our findings also indicate that Txnip may be a potential target for the treatment of AD.

Vital Exhaustion and Incidence of Dementia: Results from the Copenhagen City Heart Study. - Islamoska, Sabrina; Ishtiak-Ahmed, Kazi; Hansen, Åse Marie; Grynderup, Matias Brødsgaard; Mortensen, Erik Lykke; Garde, Anne Helene; Gyntelberg, Finn; Prescott, Eva Irene Bossano; Török, Eszter; Waldemar, Gunhild; Nabe-Nielsen, Kirsten (J Alzheimers Dis, 2019)
BACKGROUND: Psychological distress is potentially linked to the risk of dementia through neurologic and cardiovascular mechanisms. Vital exhaustion (VE) is a mental state of psychological distress, which could be a risk factor for dementia. OBJECTIVE: To investigate whether VE is a risk factor for dementia in later life. METHODS: We used data from 6,807 participants attending the third survey of the Copenhagen City Heart Study in 1991-1994. VE was assessed by 17 symptoms (score: 0-17) from the Maastricht Questionnaire. Information on dementia was obtained from national registers. Risk time for dementia was counted from five years after VE assessment for participants > 55 years at the time of VE assessment. For younger participants, risk time for dementia was counted from the year they turned 60 years and onwards. Participants were followed until 2016. We used Poisson regression to calculate incidence rate ratios (IRR) and their 95% confidence intervals (CI). RESULTS: During an average follow-up of 10 years, 872 participants were registered with dementia. We found a dose-response relation between the number of VE symptoms and the incidence of dementia. For every additional VE symptom, the dementia incidence increased by 2% (IRR = 1.024; 95% CI: 1.004-1.043). Adjustment for socio-demographic and health-related factors did not change the results substantially. Neither did stratification by age, sex, educational level, and marital status. CONCLUSION: We found evidence that VE is a risk factor for dementia. Our sensitivity analyses supported that this association was not only due to VE being a potential prodromal sign of dementia.

Why Is Amyloid-β PET Requested After Performing Cerebrospinal Fluid Biomarkers? - Reimand, Juhan; Groot, Colin; Teunissen, Charlotte E; Windhorst, Albert D; Boellaard, Ronald; Barkhof, Frederik; Nazarenko, Sergei; van der Flier, Wiesje M; van Berckel, Bart N M; Scheltens, Philip; Ossenkoppele, Rik; Bouwman, Femke (J Alzheimers Dis, 2019)
BACKGROUND: Amyloid-β PET and cerebrospinal fluid (CSF) Aβ42 are considered interchangeable for clinical diagnosis of Alzheimer's disease. OBJECTIVE: To explore the clinical reasoning for requesting additional amyloid-β PET after performing CSF biomarkers. METHODS: We retrospectively identified 72 memory clinic patients who underwent amyloid-β PET after CSF biomarkers analysis for clinical diagnostic evaluation between 2011 and 2019. We performed patient chart reviews to identify factors which led to additional amyloid-β PET. Additionally, we assessed accordance with appropriate-use-criteria (AUC) for amyloid-β PET. RESULTS: Mean patient age was 62.0 (SD = 8.1) and mean Mini-Mental State Exam score was 23.6 (SD = 3.8). CSF analysis conflicting with the clinical diagnosis was the most frequent reason for requesting an amyloid-β PET scan (n = 53, 74%), followed by incongruent MRI (n = 16, 22%), unusual clinical presentation (n = 11, 15%) and young age (n = 8, 11%). An amyloid-β PET scan was rarely (n = 5, 7%) requested in patients with a CSF Aβ+/tau+ status. Fifteen (47%) patients with a post-PET diagnosis of AD had a predominantly non-amnestic presentation. In n = 11 (15%) cases, the reason that the clinician requested amyloid-β was not covered by AUC. This happened most often (n = 7) when previous CSF analysis did not support current clinical diagnosis, which led to requesting amyloid-β PET. CONCLUSION: In this single-center study, the main reason for requesting an amyloid-β PET scan after performing CSF biomarkers was the occurrence of a mismatch between the primary clinical diagnosis and CSF Aβ/tau results.

Aberrant Cortical Event-Related Potentials During Associative Learning in Rat Models for Presymptomatic Stages of Alzheimer's Disease. - Nouriziabari, Bardia; Sarkar, Susmita; Tanninen, Stephanie E; Dayton, Robert D; Klein, Ronald L; Takehara-Nishiuchi, Kaori (J Alzheimers Dis, 2018)
Trace eyeblink conditioning is a hippocampus-dependent associative learning paradigm which is impaired in patients with Alzheimer's disease (AD) and animal AD models. Learning in this paradigm accompanies changes in oscillatory activity in forebrain regions, some of which are loci of pathogenic changes in prodromal AD stages. These observations motivated us to examine how cortical event-related potentials (ERPs) during this paradigm are affected by two features of the asymptomatic, AD-related brain abnormality, entorhinal tau accumulation and mild cholinergic deficit. Adult rats received viral overexpression of P301L mutant human tau in the entorhinal cortex, low-dose scopolamine treatment, or both. Electroencephalograms were recorded with epidural electrodes on the surface of the frontal, parietal, and temporal cortices during differential and reversal trace eyeblink conditioning. All rats developed conditioned responses to one of two stimuli (auditory or visual) paired with mild eyelid shock (CS+), but not to the other stimulus presented alone (CS-). They were also able to adjust the response when the stimulus contingency was reversed. With learning, the amplitude of several ERP components in the frontal and temporal cortices came to differentiate the CS+ from CS-. Scopolamine affected the learning-related change in temporal P2 and other learning-unrelated components in three regions. Entorhinal tau overexpression primary affected the amplitude of temporal visual ERPs and learning-unrelated frontal and temporal auditory ERP components. The double manipulation only affected two components of temporal auditory ERPs. Thus, cortical ERPs during differential associative learning are sensitive to asymptomatic brain abnormality associated with AD.

Abnormal Functional Brain Networks in Mild Cognitive Impairment and Alzheimer's Disease: A Minimum Spanning Tree Analysis. - Wang, Bin; Miao, Liwen; Niu, Yan; Cao, Rui; Li, Dandan; Yan, Pengfei; Guo, Hao; Yan, Tianyi; Wu, Jinglong; Xiang, Jie (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) disrupts the topological architecture of whole-brain connectivity. Minimum spanning tree (MST), which captures the most important connections in a network, has been considered an unbiased method for brain network analysis. However, the alterations in the MST of functional brain networks during the progression of AD remain unclear. Here, we performed an MST analysis to examine the alterations in functional networks among normal controls (NCs), mild cognitive impairment (MCI) patients, and AD patients. We identified substantial differences in the connections among the three groups. The maximum betweenness centrality, leaf number, and tree hierarchy of the MSTs showed significant group differences, indicating a more star-like topology in the MCI patients and a more line-like topology in the NCs and AD patients. These findings may correspond to changes in the core of the functional brain networks. For nodal properties (degree and betweenness centrality), we determined that brain regions around the cingulate gyrus, occipital lobes, subcortex, and inferior temporal gyrus showed significant differences among the three groups and contributed to the global topological alterations. The leaf number and tree hierarchy, as well as the nodal properties, were significantly correlated with clinical features in the MCI and AD patients, which demonstrated that more star-to-line topology changes were associated with worse cognitive performance in these patients. These findings indicated that MST properties could capture slight alterations in network topology, particularly for the differences between NCs and MCI patients, and may be applicable as neuroimaging markers of the early stage of AD.

Abnormalities of Resting State Cortical EEG Rhythms in Subjects with Mild Cognitive Impairment Due to Alzheimer's and Lewy Body Diseases. - Babiloni, Claudio; Del Percio, Claudio; Lizio, Roberta; Noce, Giuseppe; Lopez, Susanna; Soricelli, Andrea; Ferri, Raffaele; Pascarelli, Maria Teresa; Catania, Valentina; Nobili, Flavio; Arnaldi, Dario; Famá, Francesco; et al. (J Alzheimers Dis, 2018)
The present study tested the hypothesis that cortical sources of resting state eyes-closed electroencephalographic (rsEEG) rhythms reveal different abnormalities in cortical neural synchronization in groups of patients with mild cognitive impairment due to Alzheimer's disease (ADMCI) and dementia with Lewy bodies (DLBMCI) as compared to cognitively normal elderly (Nold) subjects. Clinical and rsEEG data in 30 ADMCI, 23 DLBMCI, and 30 Nold subjects were available in an international archive. Age, gender, and education were carefully matched in the three groups. The Mini-Mental State Evaluation (MMSE) score was matched between the ADMCI and DLBMCI groups. Individual alpha frequency peak (IAF) was used to determine the delta, theta, alpha1, alpha2, and alpha3 frequency band ranges. Fixed beta1, beta2, and gamma bands were also considered. eLORETA estimated the rsEEG cortical sources. Receiver operating characteristic curve (ROCC) classified these sources across individuals. Compared to Nold, IAF showed marked slowing in DLBMCI and moderate in ADMCI. Furthermore, the posterior alpha 2 and alpha 3 source activities were more abnormal in the ADMCI than the DLBMCI group, while widespread delta source activities were more abnormal in the DLBMCI than the ADMCI group. The posterior delta and alpha sources correlated with the MMSE score and correctly classified the Nold and MCI individuals (area under the ROCC >0.85). In conclusion, the ADMCI and DLBMCI patients showed different features of cortical neural synchronization at delta and alpha frequencies underpinning brain arousal and vigilance in the quiet wakefulness. Future prospective cross-validation studies will have to test the clinical validity of these rsEEG markers.

Accuracy of Inferred APOE Genotypes for a Range of Genotyping Arrays and Imputation Reference Panels. - Lupton, Michelle K; Medland, Sarah E; Gordon, Scott D; Goncalves, Tabatha; MacGregor, Stuart; Mackey, David A; Young, Terri L; Duffy, David L; Visscher, Peter M; Wray, Naomi R; Nyholt, Dale R; Bain, Lisa; et al. (J Alzheimers Dis, 2018)
Cohort studies investigating aging and dementia require APOE genotyping. We compared directly measured APOE genotypes to 'hard-call' genotypes derived from imputing genome-wide genotyping data from a range of platforms using several imputation panels. Older GWAS arrays imputed to 1000 Genomes Project (1KGP) phases and the Haplotype Reference Consortium (HRC) reference panels were able to achieve concordance rates of over 98% with stringent quality control (hard-call-threshold 0.8). However, this resulted in high levels of missingness (>12% with 1KGP and 5% with HRC). With recent GWAS arrays, concordance of 99% could be obtained with relatively lenient QC, resulting in no missingness.

Acute Stroke Care in Dementia: A Cohort Study from the Swedish Dementia and Stroke Registries. - Zupanic, Eva; Kåreholt, Ingemar; Norrving, Bo; Secnik, Juraj; von Euler, Mia; Winblad, Bengt; Religa, Dorota; Kramberger, Milica Gregoric; Johnell, Kristina; Eriksdotter, Maria; Garcia-Ptacek, Sara (J Alzheimers Dis, 2018)
BACKGROUND: Previous studies have shown that patients with dementia receive less testing and treatment for stroke. OBJECTIVES: Our aim was to investigate hospital management of acute ischemic stroke in patients with and without dementia. METHODS: Retrospective analysis of prospectively collected data 2010-2014 from the Swedish national dementia registry (SveDem) and the Swedish national stroke registry (Riksstroke). Patients with dementia who suffered an acute ischemic stroke (AIS) (n = 1,356) were compared with matched non-dementia AIS patients (n = 6,755). Outcomes included length of stay in a stroke unit, total length of hospitalization, and utilization of diagnostic tests and assessments. RESULTS: The median age at stroke onset was 83 years. While patients with dementia were equally likely to be directly admitted to a stroke unit as their non-dementia counterparts, their stroke unit and total hospitalization length were shorter (10.5 versus 11.2 days and 11.6 versus 13.5, respectively, p < 0.001). Dementia patients were less likely to receive carotid ultrasound (OR 0.36, 95% CI [0.30-0.42]) or undergo assessments by the interdisciplinary team members (physiotherapists, speech therapists, occupational therapists; p < 0.05 for all adjusted models). However, a similar proportion of patients received CT imaging (97.4% versus 98.6%, p = 0.001) and a swallowing assessment (90.7% versus 91.8%, p = 0.218). CONCLUSIONS: Patients with dementia who suffer an ischemic stroke have equal access to direct stroke unit care compared to non-dementia patients; however, on average, their stay in a stroke unit and total hospitalization are shorter. Dementia patients are also less likely to receive specific diagnostic tests and assessments by the interdisciplinary stroke team.

Added Diagnostic Value of Cerebrospinal Fluid Biomarkers for Differential Dementia Diagnosis in an Autopsy-Confirmed Cohort. - Niemantsverdriet, Ellis; Feyen, Bart F E; Le Bastard, Nathalie; Martin, Jean-Jacques; Goeman, Johan; De Deyn, Peter Paul; Bjerke, Maria; Engelborghs, Sebastiaan (J Alzheimers Dis, 2018)
BACKGROUND: Differential dementia diagnosis remains a challenge due to overlap of clinical profiles, which often results in diagnostic doubt. OBJECTIVE: Determine the added diagnostic value of cerebrospinal fluid (CSF) biomarkers for differential dementia diagnosis as compared to autopsy-confirmed diagnosis. METHODS: Seventy-one dementia patients with autopsy-confirmed diagnoses were included in this study. All neuropathological diagnoses were established according to standard neuropathological criteria and consisted of Alzheimer's disease (AD) or other dementias (NONAD). CSF levels of Aβ1 - 42, T-tau, and P-tau181 were determined and interpreted based on the IWG-2 and NIA-AA criteria, separately. A panel of three neurologists experienced with dementia made clinical consensus dementia diagnoses. Clinical and CSF biomarker diagnoses were compared to the autopsy-confirmed diagnoses. RESULTS: Forty-two patients (59%) had autopsy-confirmed AD, whereas 29 patients (41%) had autopsy-confirmed NONAD. Of the 24 patients with an ambiguous clinical dementia diagnosis, a correct diagnosis would have been established in 67% of the cases applying CSF biomarkers in the context of the IWG-2 or the NIA-AA criteria respectively. CONCLUSION: AD CSF biomarkers have an added diagnostic value in differential dementia diagnosis and can help establishing a correct dementia diagnosis in case of ambiguous clinical dementia diagnoses.

Advanced Circadian Timing and Sleep Fragmentation Differentially Impact on Memory Complaint Subtype in Subjective Cognitive Decline. - Manousakis, Jessica E; Scovelle, Anna J; Rajaratnam, Shantha M W; Naismith, Sharon L; Anderson, Clare (J Alzheimers Dis, 2018)
BACKGROUND: Increased sleep fragmentation and advanced circadian timing are hallmark phenotypes associated with increased age-related cognitive decline. Subjective cognitive decline (SCD) is considered a prodromal stage of neurodegeneration and dementia; however, little is known about how sleep and circadian timing impact on memory complaints in SCD. OBJECTIVE: To determine how sleep and circadian timing impact on memory complaint subtypes in older adults with SCD. METHODS: Twenty-five older adults with SCD (mean age = 69.97, SD = 5.33) completed the Memory Functioning Questionnaire to characterize their memory complaints. They also underwent neuropsychological assessment, and completed 1 week of at-home monitoring of sleep with actigraphy and sleep diaries. This was followed by a two-night laboratory visit with overnight polysomnography and a dim light melatonin onset assessment to measure circadian timing. RESULTS: Advanced circadian timing was associated with greater memory complaints, specifically poorer memory of past events (r = -0.688, p = 0.002), greater perceived decline over time (r = -0.568, p = 0.022), and increased reliance on mnemonic tools (r = -0.657, p = 0.004). Increased sleep fragmentation was associated with reduced self-reported memory decline (r = 0.529, p = 0.014), and reduced concern about everyday forgetfulness (r = 0.435, p = 0.038). CONCLUSION: Advanced circadian timing was associated with a number of subjective memory complaints and symptoms. By contrast, sleep fragmentation was linked to lowered perceptions of cognitive decline, and less concern about memory failures. As circadian disruption is apparent in both MCI and Alzheimer's disease, and plays a key role in cognitive function, our findings further support a circadian intervention as a potential therapeutic tool for cognitive decline.

Alterations of Effective Connectivity Patterns in Mild Cognitive Impairment: An MEG Study. - Gómez, Carlos; Juan-Cruz, Celia; Poza, Jesús; Ruiz-Gómez, Saúl J; Gomez-Pilar, Javier; Núñez, Pablo; García, María; Fernández, Alberto; Hornero, Roberto (J Alzheimers Dis, 2018)
Neuroimaging techniques have demonstrated over the years their ability to characterize the brain abnormalities associated with different neurodegenerative diseases. Among all these techniques, magnetoencephalography (MEG) stands out by its high temporal resolution and noninvasiveness. The aim of the present study is to explore the coupling patterns of resting-state MEG activity in subjects with mild cognitive impairment (MCI). To achieve this goal, five minutes of spontaneous MEG activity were acquired with a 148-channel whole-head magnetometer from 18 MCI patients and 26 healthy controls. Inter-channel relationships were investigated by means of two complementary coupling measures: coherence and Granger causality. Coherence is a classical method of functional connectivity, while Granger causality quantifies effective (or causal) connectivity. Both measures were calculated in the five conventional frequency bands: delta (δ, 1-4 Hz), theta (θ, 4-8 Hz), alpha (α, 8-13 Hz), beta (β, 13-30 Hz), and gamma (γ, 30-45 Hz). Our results showed that connectivity values were lower for MCI patients than for controls in all frequency bands. However, only Granger causality revealed statistically significant differences between groups (p-values < 0.05, FDR corrected Mann-Whitney U-test), mainly in the beta band. Our results support the role of MCI as a disconnection syndrome, which elicits early alterations in effective connectivity patterns. These findings can be helpful to identify the neural substrates involved in prodromal stages of dementia.

Alzheimer's Disease Progression: Factors Influencing Cognitive Decline. - Ferrari, Camilla; Lombardi, Gemma; Polito, Cristina; Lucidi, Giulia; Bagnoli, Silvia; Piaceri, Irene; Nacmias, Benedetta; Berti, Valentina; Rizzuto, Debora; Fratiglioni, Laura; Sorbi, Sandro (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) patients present high variability in the rate of cognitive decline. Despite the wide knowledge on factors influencing dementia risk, little is known on what accounts for AD progression. Previous studies on this topic have mainly analyzed each factor separately without taking into account the interaction between genetic and non-genetic factors. OBJECTIVE: The aim of the present study is to evaluate the role of demographic, clinical, therapeutic, and genetic factors and their interaction on cognitive decline among newly diagnosed AD patients. METHODS: We retrospectively selected 160 AD patients diagnosed at the Neurology Unit of Careggi University Hospital of Florence. We evaluated the occurrence of rapid cognitive changes defined as the worsening of more than four points at the Mini-Mental State Examination after 2-year follow up period. RESULTS: Among the 160 AD patients, 50% presented rapid disease progression. Extrapyramidal signs at disease onset were predictors of worse outcome (OR 2.2), especially among Apolipoprotein E (APOE) ɛ4 allele carriers, while the presence of family history for dementia decreased the risk of rapid progression by about 50%. Higher educated ɛ4-carriers showed a slower AD progression. We identified the chronic use of aspirin as potential secondary preventative strategy for the non ɛ4-carriers. CONCLUSION: At dementia onset, some clinical and demographic data can be predictors of future progression. The outcomes of the present study support the already hypothesized interaction between genetic and non-genetic factors during disease course and suggest genetic-based approaches.
Keywords: Aged; Aged, 80 and over; Alleles; Alzheimer Disease; Apolipoprotein E4; Aspirin; Cognitive Dysfunction; Disease Progression; Female; Heterozygote; Humans; Italy; Male; Middle Aged; Neuropsychological Tests; Retrospective Studies; Secondary Prevention

Amyloid-β and Tau in Alzheimer's Disease: Novel Pathomechanisms and Non-Pharmacological Treatment Strategies. - Nisbet, Rebecca M; Götz, Jürgen (J Alzheimers Dis, 2018)
Accumulation of the peptide amyloid-β (Aβ) and the protein tau in Alzheimer's disease (AD) brains is a gradual process that involves the post-translational modification and assembly of monomeric forms into larger structures that eventually form fibrillar inclusions. This process is thought to both drive and initiate AD. However, why the axonally enriched tau in the course of AD accumulates in the somatodendritic domain is not fully understood. We discuss new data that provide a possible explanation that involves de novo protein synthesis, induced by Aβ and mediated through the kinase Fyn. We further discuss how in a pathological state, tau, being a scaffolding protein, impairs nuclear and mitochondrial functions and reduces action potential generation at the axon initial segment. Pathological tau can further be packaged into exosomes, released by one neuron and taken up by another, contributing to its pathogenicity. We also present our new work that suggests ultrasound as a new treatment modality to clear pathological Aβ and tau. We put this work into perspective, discussing current vaccination strategies and improved brain delivery methods involving antibody engineering and viral approaches. We propose that rather than reducing post-translational modifications of tau, its levels and de novo synthesis need to be reduced. We anticipate a surge in combinatorial strategies, simultaneously targeting multiple pathologies, and an improved drug delivery to the brain facilitated by emerging technologies such as ultrasound.

Amyloid-β/Drug Interactions from Computer Simulations and Cell-Based Assays. - Nguyen, Phuong H; Del Castillo-Frias, Maria P; Berthoumieux, Olivia; Faller, Peter; Doig, Andrew J; Derreumaux, Philippe (J Alzheimers Dis, 2018)
Targeting the early oligomers formed by the amyloid-β (Aβ) peptide of 40 and 42 amino acids is considered one promising therapeutic approach for Alzheimer's disease (AD). In vitro experiments and computer simulations are often used in synergy to reveal the modes of interactions of drugs. In this account, we present our contribution to understanding how small molecules bind to Aβ40/Aβ42 peptides, based either on extensive coarse-grained and all-atom simulations, or a variety of experimental techniques. We conclude by offering several perspectives on the future of this field to design more efficient drugs.

Antibodies to Multiple Receptors are Associated with Neuropsychiatric Symptoms and Mortality in Alzheimer's Disease: A Longitudinal Study. - Giil, Lasse M; Aarsland, Dag; Hellton, Kristoffer; Lund, Anders; Heidecke, Harald; Schulze-Forster, Kai; Riemekasten, Gabriela; Vik-Mo, Audun Osland; Kristoffersen, Einar K; Vedeler, Christian A; Nordrehaug, Jan Erik (J Alzheimers Dis, 2018)
BACKGROUND: Endogenous antibodies to signaling molecules and receptors (Abs) are associated with Alzheimer's disease (AD). OBJECTIVES: To investigate the association of 33 Abs to dopaminergic, serotoninergic, muscarinic, adrenergic, vascular, and immune receptors with cognitive, neuropsychiatric, and mortality outcomes. METHODS: Ninety-one patients with mild AD were followed annually for 5 years with the Mini-Mental State Examination (MMSE) and the Neuropsychiatric Inventory (NPI; composite outcomes: "psychosis" (item 1 + 2), "mood" (item 4 + 5 + 7), and "agitation" (item 3 + 8 + 9)). Abs were quantified in sera obtained at baseline by ELISA and reduced to principal components (PCs). Associations between Abs and outcomes were assessed by a mixed model (MMSE decline), zero-inflated fixed effects count models (composite NPI scores), and Cox regression (mortality). The resulting p-values were adjusted for multiple testing according to a false discovery rate of 0.05 (Benjamini-Hochberg). RESULTS: The measured levels of the 33 Abs formed four PCs. PC1 (dopaminergic and serotonergic Abs) was associated with increased mortality (Hazard ratio 2.57, p < 0.001), PC2 (serotonergic, immune, and vascular Abs) with decreased agitation symptoms (β - 0.19, p < 0.001), and PC3 (cholinergic receptor Abs) with increased mood symptoms (β 0.04, p = 0.002), over time. There were no associations between Abs and MMSE decline. CONCLUSION: The associations between Abs, mortality, and neuropsychiatric symptoms reported in this cohort are intriguing. They cannot, however, be generalized. Validation in independent sample sets is required.

Anti-Tau Monoclonal Antibodies Derived from Soluble and Filamentous Tau Show Diverse Functional Properties in vitro and in vivo. - Vandermeeren, Marc; Borgers, Marianne; Van Kolen, Kristof; Theunis, Clara; Vasconcelos, Bruno; Bottelbergs, Astrid; Wintmolders, Cindy; Daneels, Guy; Willems, Roland; Dockx, Koen; Delbroek, Lore; Marreiro, André; et al. (J Alzheimers Dis, 2018)
The tau spreading hypothesis provides rationale for passive immunization with an anti-tau monoclonal antibody to block seeding by extracellular tau aggregates as a disease-modifying strategy for the treatment of Alzheimer's disease (AD) and potentially other tauopathies. As the biochemical and biophysical properties of the tau species responsible for the spatio-temporal sequences of seeding events are poorly defined, it is not yet clear which epitope is preferred for obtaining optimal therapeutic efficacy. Our internal tau antibody collection has been generated by immunizations with different tau species: aggregated- and non-aggregated tau and human postmortem AD brain-derived tau fibrils. In this communication, we describe and characterize a set of these anti-tau antibodies for their biochemical and biophysical properties, including binding, tissue staining by immunohistochemistry, and epitope. The antibodies bound to different domains of the tau protein and some were demonstrated to be isoform-selective (PT18 and hTau56) or phospho-selective (PT84). Evaluation of the antibodies in cellular- and in vivo seeding assays revealed clear differences in maximal efficacy. Limited proteolysis experiments support the hypothesis that some epitopes are more exposed than others in the tau seeds. Moreover, antibody efficacy seems to depend on the structural properties of fibrils purified from tau Tg mice- and postmortem human AD brain.

Aortic Stiffness is Associated with Increased Risk of Incident Dementia in Older Adults. - Cui, Chendi; Sekikawa, Akira; Kuller, Lewis H; Lopez, Oscar L; Newman, Anne B; Kuipers, Allison L; Mackey, Rachel H (J Alzheimers Dis, 2018)
Cardiovascular disease risk factors, including age, hypertension, and diabetes, contribute to aortic stiffness and subclinical cardiovascular and brain disease, increasing dementia risk. Aortic stiffness, measured by carotid-femoral pulse wave velocity (cfPWV), reduces the buffering of pulsatile blood flow, exposing cerebral small arteries to microvascular damage. High cfPWV is related to white matter hyperintensities and brain amyloid deposition, and to cognitive decline, but it is unclear whether cfPWV independently predicts incident dementia. Therefore, we tested the hypothesis that cfPWV predicts incident dementia in older adults, independent of potential confounders. The Cardiovascular Health Study Cognition Study followed 532 non-demented older adults with annual cognitive exams from 1998-99 through 2013. CfPWV was measured on 356 (mean age = 78, 59% women) between 1996-2000. Over 15 years, 212 (59.6%) developed dementia (median time from cfPWV measurement = 4 years). In age and sex-adjusted Cox models, cfPWV was significantly associated with increased risk of dementia, but systolic blood pressure, mean arterial pressure and pulse pressure were not. CfPWV (transformed as - 1/cfPWV) remained significantly associated with dementia risk when further adjusted for education, race, APOEɛ4, diabetes, body mass index, mean arterial pressure, and anti-hypertensive medication (hazard ratio = 1.60, 95% CI = 1.02, 2.51). Results were similar when further adjusted for baseline global cognition, subclinical brain measures, and coronary artery calcification. Finally, higher cfPWV was related to lower physical activity intensity and higher systolic blood pressure, heart rate, and waist circumference measured 5 years prior. An important unanswered question is whether interventions to slow arterial stiffening can reduce the risk of dementia.

Assessing Working Memory in Mild Cognitive Impairment with Serial Order Recall. - Emrani, Sheina; Libon, David J; Lamar, Melissa; Price, Catherine C; Jefferson, Angela L; Gifford, Katherine A; Hohman, Timothy J; Nation, Daniel A; Delano-Wood, Lisa; Jak, Amy; Bangen, Katherine J; Bondi, Mark W; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Working memory (WM) is often assessed with serial order tests such as repeating digits backward. In prior dementia research using the Backward Digit Span Test (BDT), only aggregate test performance was examined. OBJECTIVE: The current research tallied primacy/recency effects, out-of-sequence transposition errors, perseverations, and omissions to assess WM deficits in patients with mild cognitive impairment (MCI). METHODS: Memory clinic patients (n = 66) were classified into three groups: single domain amnestic MCI (aMCI), combined mixed domain/dysexecutive MCI (mixed/dys MCI), and non-MCI where patients did not meet criteria for MCI. Serial order/WM ability was assessed by asking participants to repeat 7 trials of five digits backwards. Serial order position accuracy, transposition errors, perseverations, and omission errors were tallied. RESULTS: A 3 (group)×5 (serial position) repeated measures ANOVA yielded a significant group×trial interaction. Follow-up analyses found attenuation of the recency effect for mixed/dys MCI patients. Mixed/dys MCI patients scored lower than non-MCI patients for serial position 3 (p < 0.003) serial position 4 (p < 0.002); and lower than both group for serial position 5 (recency; p < 0.002). Mixed/dys MCI patients also produced more transposition errors than both groups (p < 0.010); and more omissions (p < 0.020), and perseverations errors (p < 0.018) than non-MCI patients. CONCLUSIONS: The attenuation of a recency effect using serial order parameters obtained from the BDT may provide a useful operational definition as well as additional diagnostic information regarding working memory deficits in MCI.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Executive Function; Female; Humans; Male; Memory Disorders; Memory, Short-Term; Mental Recall; Neuropsychological Tests; Regression Analysis; Serial Learning

Assessment of the Genetic Architecture of Alzheimer's Disease Risk in Rate of Memory Decline. - Del-Aguila, Jorge L; Fernández, Maria Victoria; Schindler, Suzanne; Ibanez, Laura; Deming, Yuetiva; Ma, Shengmei; Saef, Ben; Black, Kathleen; Budde, John; Norton, Joanne; Chasse, Rachel; Harari, Oscar; et al. (J Alzheimers Dis, 2018)
Many genetic studies for Alzheimer's disease (AD) have been focused on the identification of common genetic variants associated with AD risk and not on other aspects of the disease, such as age at onset or rate of dementia progression. There are multiple approaches to untangling the genetic architecture of these phenotypes. We hypothesized that the genetic architecture of rate of progression is different than the risk for developing AD dementia. To test this hypothesis, we used longitudinal clinical data from ADNI and the Knight-ADRC at Washington University, and we calculated PRS (polygenic risk score) based on the IGAP study to compare the genetic architecture of AD risk and dementia progression. Dementia progression was measured by the change of Clinical Dementia Rating Sum of Boxes (CDR)-SB per year. Out of the 21 loci for AD risk, no association with the rate of dementia progression was found. The PRS rate was significantly associated with the rate of dementia progression (β= 0.146, p = 0.03). In the case of rare variants, TREM2 (β= 0.309, p = 0.02) was also associated with the rate of dementia progression. TREM2 variant carriers showed a 23% faster rate of dementia compared with non-variant carriers. In conclusion, our results indicate that the recently identified common and rare variants for AD susceptibility have a limited impact on the rate of dementia progression in AD patients.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Dementia; Disease Progression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Heterozygote; Humans; Longitudinal Studies; Male; Membrane Glycoproteins; Memory Disorders; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Immunologic; Risk Assessment

Association between Hippocampal Shape, Neuroinflammation, and Cognitive Decline in Alzheimer's Disease. - Cabinio, Monia; Saresella, Marina; Piancone, Federica; LaRosa, Francesca; Marventano, Ivana; Guerini, Franca; Nemni, Raffaello; Baglio, Francesca; Clerici, Mario (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is a neurodegenerative condition characterized by memory impairment and general decrease in cognitive functions and daily living competences, that leads to a complete loss of autonomy. The pathogenesis of AD is characterized by the deposition of amyloid-β plaques (Aβ plaques) and neurofibrillary tangles, initially involving cortical and hippocampal structures, and neuroinflammation. To date, no studies have investigated the topological association between neuroinflammation and hippocampal shape in AD. OBJECTIVE: The aim of the present study is to assess the association between hippocampal shape, cognitive profile, and neuroinflammation in a group of AD patients in the mild stage of the disease. METHODS: Thirty-one patients with typical onset AD (mild stage) underwent MRI examination (1.5T scanner); hippocampal structures were segmented using a vertex-wise analysis (FSL-FIRST). Immune parameters were evaluated on peripheral blood mononuclear cells by flow-cytometry. Correlation analyses were performed between hippocampal shape and both cognitive profile (ADAS-Cog and MMSE scores), and neuro-inflammatory variables (i.e., circulating monocytes, cytokines). RESULTS: Statistically significant correlations (p < 0.05FWE) between right hippocampal shape and cognitive measurements and between left hippocampal shape and inflammatory indices were detected. The hippocampal field mostly involved was the lateral portion of bilateral hippocampi, mainly overlapping with Cornu Ammonis, extending along the entire longitudinal axis. CONCLUSIONS: A topological relationship between hippocampal atrophy and both cognitive profile and neuroinflammation is found; the association with neuroinflammatory indices is in line with the pattern of AD-associated neuronal death, whereas the association with cognitive test might account for residual cognitive functions.

Association between Neuropsychiatric Improvement and Neurocognitive Change in Alzheimer's Disease: Analysis of the CATIE-AD Study. - Nagata, Tomoyuki; Shinagawa, Shunichiro; Nakajima, Shinichiro; Mimura, Masaru; Shigeta, Masahiro (J Alzheimers Dis, 2018)
BACKGROUND/OBJECTIVE: To assess associations between improvements in neuropsychiatric symptoms (NPS) and neurocognitive change in patients with Alzheimer's disease (AD) during treatment using the Clinical Antipsychotic Trials of Intervention Effectiveness-Alzheimer Disease (CATIE-AD) dataset. METHODS: AD outpatients with NPS who needed pharmacological treatment (n = 421) were followed up with antipsychotics, citalopram, or placebo for up to 36 weeks (mean±SD = 252±52 days). The study aim was to investigate associations between improvement in each NPS evaluating scale (by Clinical Global Impression of Change [CGI-C], Neuropsychiatric Inventory [NPI], or Brief Psychiatric Scale [BPRS]) at endpoint (week 36 or early termination [ET], n = 340) and neurocognitive change (change score in the Mini-Mental State Examination [MMSE] between endpoint and baseline during the treatment). Multiple logistic regression analyses were performed on the associations between each NPS improvement and neurocognitive change as well as socio-clinico-demographic variables of interest. RESULTS: At endpoint, NPS improvement rates were 76.1%, 70.8%, and 58.1% in CGI-C, NPI, and BPRS, respectively, while MMSE score change was -2.3±3.8. NPS improvement was significantly related to more severe psychotic symptoms at baseline and preserved levels of neurocognition (smaller MMSE score change) among several variables. CONCLUSIONS: Our findings suggested that neurocognitive preservation may be associated with attaining optimal benefits from any treatment against NPSs in a longitudinal treatment course of patients with AD.

Association between α-Klotho and Deep White Matter Lesions in the Brain: A Pilot Case Control Study Using Brain MRI. - Kuriyama, Nagato; Ozaki, Etsuko; Mizuno, Toshiki; Ihara, Masafumi; Mizuno, Shigeto; Koyama, Teruhide; Matsui, Daisuke; Watanabe, Isao; Akazawa, Kentaro; Takeda, Kazuo; Takada, Akihiro; Inaba, Masaaki; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The anti-aging protein, α-Klotho, may be involved in cognitive decline and has potential as a surrogate marker that reflects dementia. However, the role of α-Klotho in the brain has not been sufficiently investigated. OBJECTIVE: Here, we investigated the association between α-Klotho and cognitive decline that is associated with cerebral deep white matter lesions (DWMLs). METHODS: Two hundred-eighty participants (187 males and 93 females, mean age: 70.8 years old) were evaluated for DWMLs, and the Fazekas scale (Grade) was assessed following brain magnetic resonance imaging. A questionnaire concerning lifestyle and neuropsychological tests was administered, and their associations with the blood α-Klotho level were retrospectively investigated. RESULTS: The α-Klotho level was 685.1 pg/mL in Grade 0 (68 subjects), 634.1 in G1 (134), 596.0 in G2 (62), and 571.6 in G3 (16), showing that the level significantly decreased with advanced grades. Significant correlations were noted between the α-Klotho level and higher brain function tests including the Mini-Mental State Examination and word fluency tests (p < 0.05). When a 90th percentile value of the level in the G0 group (400 pg/mL) or lower was defined as a low α-Klotho level, the odds ratio of the high-grade G3 group was 2.9 (95% confidence interval: 1.4-7.8) (after correction for age, sex, hypertension, and chronic kidney disease), which was significant. CONCLUSION: A reduced blood α-Klotho level was correlated with grading of cerebral DWMLs and was accompanied by cognitive decline as an independent risk factor. The α-Klotho level may serve as a useful clinical index of vascular cognitive impairment.
Keywords: Aged; Aged, 80 and over; Apolipoprotein E4; Brain; C-Reactive Protein; Case-Control Studies; Cognition Disorders; Female; Glucuronidase; Humans; Image Processing, Computer-Assisted; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Pilot Projects; Severity of Illness Index

Association of the New Variant Tyr424Asp at TBK1 Gene with Amyotrophic Lateral Sclerosis and Cognitive Decline. - Piaceri, Irene; Bessi, Valentina; Matà, Sabrina; Polito, Cristina; Tedde, Andrea; Berti, Valentina; Bagnoli, Silvia; Braccia, Arianna; Del Mastio, Monica; Pignone, Alberto Moggi; Pupi, Alberto; Sorbi, Sandro; et al. (J Alzheimers Dis, 2018)
A new risk gene associated with amyotrophic lateral sclerosis (ALS) has recently been identified: the Tank-binding kinase 1 (TBK1) gene. Up to now, 90 TBK1 variants have been described in ALS patients with or without frontotemporal dementia (FTD), thus making TBK1 the third or fourth most frequent genetic cause of ALS and FTD. A point mutation analysis in a cohort of 69 Italian ALS patients was performed in order to analyze the frequency of TBK1 mutations and the correlation with clinical phenotypes. The analysis identified the novel variant p.Tyr424Asp in a patient with a rapid progression of the disease. Our data supports the implication of TBK1 in ALS pathogenesis in Italy.
Keywords: Aged; Amyotrophic Lateral Sclerosis; Aspartic Acid; C9orf72 Protein; Cognitive Dysfunction; DNA Mutational Analysis; Female; Fluorodeoxyglucose F18; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Italy; Male; Mental Status and Dementia Tests; Middle Aged; Mutation; Neuropsychological Tests; Positron-Emission Tomography; Protein-Serine-Threonine Kinases; Tyrosine

Biallelic Loss of Function of SORL1 in an Early Onset Alzheimer's Disease Patient. - Le Guennec, Kilan; Tubeuf, Hélène; Hannequin, Didier; Wallon, David; Quenez, Olivier; Rousseau, Stéphane; Richard, Anne-Claire; Deleuze, Jean-François; Boland, Anne; Frebourg, Thierry; Gaildrat, Pascaline; Campion, Dominique; et al. (J Alzheimers Dis, 2018)
Heterozygous SORL1 protein truncating variants (PTV) are a strong risk factor for early-onset Alzheimer's disease (EOAD). In case control studies performed at the genome-wide level, PTV definition is usually straightforward. Regarding splice site variants, only those affecting canonical sites are typically included. Some other variants, not annotated as PTV, could, however, affect splicing and hence result in a loss of SORL1 function. We took advantage of the whole exome sequencing data from the 9/484 patients with a previously reported SORL1 PTV in the French EOAD series and searched for a second variant which may affect splicing and eventually result in more than 50% loss of function overall. We found that one patient, known to carry a variant predicted to disrupt the canonical 5' splice site of exon 8, also carried a second novel intronic variant predicted to affect SORL1 splicing of exon 29. Segregation analysis showed that the second variant was located in trans from the known PTV. We performed ex vivo minigene splicing assays and showed that both variants led to the generation of transcripts containing a premature stop codon. This is therefore the first evidence of a human carrying biallelic SORL1 PTV. This patient had a family history of dementia in both maternal and paternal lineages with later ages of onset than the proband himself. However, his 55 years age at onset was in the same ranges as previously published SORL1 heterozygous PTV carriers. This suggests that biallelic loss of SORL1 function is an extremely rare event that was not associated with a dramatically earlier age at onset than heterozygous SORL1 loss-of-function variant carriers, in this single patient.
Keywords: Alzheimer Disease; Case-Control Studies; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Humans; LDL-Receptor Related Proteins; Male; Membrane Transport Proteins; Middle Aged; Risk Factors

Bone-Marrow-Derived Microglia-Like Cells Ameliorate Brain Amyloid Pathology and Cognitive Impairment in a Mouse Model of Alzheimer's Disease. - Kawanishi, Shohei; Takata, Kazuyuki; Itezono, Shouma; Nagayama, Hiroko; Konoya, Sayaka; Chisaki, Yugo; Toda, Yuki; Nakata, Susumu; Yano, Yoshitaka; Kitamura, Yoshihisa; Ashihara, Eishi (J Alzheimers Dis, 2018)
Microglia, the primary immune cells in the brain, sense pathogens and tissue damage, stimulate cytokine production, and phagocytosis to maintain homeostasis. Accumulation of amyloid-β peptides (Aβ) in the brain triggers the onset of Alzheimer's disease (AD). Accordingly, promotion of Aβ clearance represents a promising strategy for AD therapy. We previously demonstrated that primary-cultured rat microglia phagocytose Aβ, and that transplantation of these cells ameliorates the Aβ burden in brains of Aβ-injected rats. In this study, we demonstrate that stimulation with colony-stimulating factor-1 efficiently differentiates mouse bone marrow cells into bone marrow-derived microglia-like (BMDML) cells that express markers for microglia, including the recently identified transmembrane protein 119. BMDML cells effectively phagocytose Aβ in vitro, with effects comparable to primary-cultured mouse microglia and greater than peritoneal macrophages. RT-qPCR analysis for cytokine mRNA levels revealed that BMDML cells polarize to a relatively anti-inflammatory state under non-stimulated and inflammatory conditions but exert a pro-inflammatory reaction after lipopolysaccharide treatment. Moreover, BMDML cells hippocampally injected into a mouse model of AD are morphologically similar to the ramified and amoeboid types of residential microglia. Comparisons with simulations assuming a uniform distribution of cells suggest that BMDML cells migrate directionally toward Aβ plaques. We also detected Aβ phagocytosis by BMDML cells, concomitant with a reduction in the number and area of Aβ plaques. Finally, we observed amelioration of cognitive impairment in a mouse model of AD after hippocampal injection of BMDML cells. Our results suggest that BMDML cells have potential as a cell-based disease-modifying therapy against AD.

Brazilian Green Propolis Prevents Cognitive Decline into Mild Cognitive Impairment in Elderly People Living at High Altitude. - Zhu, Aiqin; Wu, Zhou; Zhong, Xin; Ni, Junjun; Li, Yinglan; Meng, Jie; Du, Can; Zhao, Xue; Nakanishi, Hiroshi; Wu, Shizheng (J Alzheimers Dis, 2018)
BACKGROUND: Systemic inflammation is known as a risk factor of cognitive decline. OBJECTIVE: To investigate the effects of propolis on cognitive decline and systemic inflammation in elderly people living at high altitude. METHODS: Sixty participants (average 72.8 years) living at altitude (2,260 meters) were randomized to receive propolis (0.83 g, n = 30) or placebo (n = 30) for 24 months. Cognitive outcomes were assessed using MMSE and serum cytokine levels were measured for 24 months in a double-blind study. RESULTS: MMSE scores were 26.17 at baseline and 23.87 at 24 months in placebo group. Compared to placebo group, improvements of MMSE scores were significant in propolis-treated subjects (p = 0.007) with a response emerging over time (time points×group interaction, p = 0.016). In addition, the serum IL-1β and IL-6 levels were significantly different across treatments (p < 0.0001) showing upward and downward trends in placebo- and propolis-treated subjects, respectively (p < 0.0001). Serum levels of TNF-α were not significantly different across treatment (p = 0.0528) but with a response emerging over time (time points×group interaction, p = 0.016). In contrast, serum levels of TGFβ1 were significantly different across treatments (p < 0.0001) showing downward and upward trends in placebo- and propolis-treated subjects, respectively. Serum levels of IL-10 were significant for the effect of groups (p = 0.0411). Furthermore, MMSE scores correlated with the decrease in IL-1β and the increase in TGFβ1 in serum. CONCLUSION: Elderly people living at high altitude developed to MCI in 24 months with exacerbation of systemic inflammation. Ingestion of propolis (>12 months) protected against cognitive decline after systemic inflammation was reduced.

Can a Novel High-Density EEG Approach Disentangle the Differences of Visual Event Related Potential (N170), Elicited by Negative Facial Stimuli, in People with Subjective Cognitive Impairment? - Lazarou, Ioulietta; Adam, Katerina; Georgiadis, Kostas; Tsolaki, Anthoula; Nikolopoulos, Spiros; Yiannis Kompatsiaris, Ioannis; Tsolaki, Magda (J Alzheimers Dis, 2018)
BACKGROUND: Studies on subjective cognitive impairment (SCI) and neural activation report controversial results. OBJECTIVE: To evaluate the ability to disentangle the differences of visual N170 ERP, generated by facial stimuli (Anger & Fear) as well as the cognitive deterioration of SCI, mild cognitive impairment (MCI), and Alzheimer's disease (AD) compared to healthy controls (HC). METHOD: 57 people took part in this study. Images corresponding to facial stimuli of "Anger" and "Fear" were presented to 12 HC, 14 SCI, 17 MCI and 14 AD participants. EEG data were recorded by using a HD-EEG HydroCel with 256 channels. RESULTS: Results showed that the amplitude of N170 can contribute in distinguishing the SCI group, since statistically significant differences were observed with the HC (p < 0.05) and the MCI group from HC (p < 0.001), as well as AD from HC (p = 0.05) during the processing of facial stimuli. Noticeable differences were also observed in the topographic distribution of the N170 amplitude, while localization analysis by using sLORETA images confirmed the activation of superior, middle-temporal, and frontal lobe brain regions. Finally, in the case of "Fear", SCI and HC demonstrated increased activation in the orbital and inferior frontal gyrus, respectively, MCI in the inferior temporal gyrus, and AD in the lingual gyrus. CONCLUSION: These preliminary findings suggest that the amplitude of N170 elicited after negative facial stimuli could be modulated by the decline related to pathological cognitive aging and can contribute in distinguishing HC from SCI, MCI, and AD.

Cardiorespiratory Fitness and Cognitive Function are Positively Related Among Participants with Mild and Subjective Cognitive Impairment. - Stuckenschneider, Tim; Askew, Christopher David; Rüdiger, Stefanie; Polidori, Maria Cristina; Abeln, Vera; Vogt, Tobias; Krome, Andreas; Olde Rikkert, Marcel; Lawlor, Brian; Schneider, Stefan (J Alzheimers Dis, 2018)
BACKGROUND: By 2030, about 74 million people will be diagnosed with dementia, and many more will experience subjective (SCI) or mild cognitive impairment (MCI). As physical inactivity has been identified to be a strong modifiable risk factor for dementia, exercise and physical activity (PA) may be important parameters to predict the progression from MCI to dementia, but might also represent disease trajectory modifying strategies for SCI and MCI. OBJECTIVE: A better understanding of the relationship between activity, fitness, and cognitive function across the spectrum of MCI and SCI would provide an insight into the potential utility of PA and fitness as early markers, and treatment targets to prevent cognitive decline. METHODS: 121 participants were stratified into three groups, late MCI (LMCI), early MCI (EMCI), and SCI based on the Montreal Cognitive Assessment (MoCA). Cognitive function assessments also included the Trail Making Test A+B, and a verbal fluency test. PA levels were evaluated with an interviewer-administered questionnaire (LAPAQ) and an activity monitor. An incremental exercise test was performed to estimate cardiorespiratory fitness and to determine exercise capacity relative to population normative data. RESULTS: ANCOVA revealed that LMCI subjects had the lowest PA levels (LAPAQ, p = 0.018; activity monitor, p = 0.041), and the lowest exercise capacity in relation to normative values (p = 0.041). Moreover, a modest correlation between MoCA and cardiorespiratory fitness (r = 0.25; p < 0.05) was found. CONCLUSION: These findings suggest that during the earliest stages of cognitive impairment PA and exercise capacity might present a marker for the risk of further cognitive decline. This finding warrants further investigation using longitudinal cohort studies.

Cerebrospinal Fluid and Plasma Levels of Inflammation Differentially Relate to CNS Markers of Alzheimer's Disease Pathology and Neuronal Damage. - Bettcher, Brianne M; Johnson, Sterling C; Fitch, Ryan; Casaletto, Kaitlin B; Heffernan, Kate S; Asthana, Sanjay; Zetterberg, Henrik; Blennow, Kaj; Carlsson, Cynthia M; Neuhaus, John; Bendlin, Barbara B; Kramer, Joel H (J Alzheimers Dis, 2018)
Inflammatory markers have been shown to predict neurocognitive outcomes in aging adults; however, the degree to which peripheral markers mirror the central nervous system remains unknown. We investigated the association between plasma and cerebrospinal fluid (CSF) markers of inflammation, and explored whether these markers independently predict CSF indicators of Alzheimer's disease (AD) pathology or neuronal damage. Plasma and CSF samples were analyzed for inflammatory markers in a cohort of asymptomatic older adults (n = 173). CSF samples were analyzed for markers of AD pathology (Aβ42, phosphorylated tau [p-tau], sAβPPβ) or neuronal damage (total tau; neurofilament light chain) (n = 147). Separate linear models for each analyte were conducted with CSF and plasma levels entered simultaneously as predictors and markers of AD pathology or neuronal damage as outcome measures. Strong associations were noted between CSF and plasma MIP-1β levels, and modest associations were observed for remaining analytes. With respect to AD pathology, higher levels of plasma and CSF IL-8, CSF MIP-1β, and CSF IP-10 were associated with higher levels of p-tau. Higher levels of CSF IL-8 were associated with higher levels of CSF Aβ42. Higher CSF sAβPPβ levels were associated with higher plasma markers only (IL-8; MCP-1). In terms of neuronal injury, higher levels of plasma and CSF IL-8, CSF IP-10, and CSF MIP-1β were associated with higher levels of CSF total tau. Exploratory analyses indicated that CSF Aβ42 modifies the relationship between plasma inflammatory levels and CSF tau levels. Results suggest that both plasma and CSF inflammatory markers independently relay integral information about AD pathology and neuronal damage.

Cerebrospinal Fluid Orexin Levels and Nocturnal Sleep Disruption in Alzheimer's Disease Patients Showing Neuropsychiatric Symptoms. - Liguori, Claudio; Mercuri, Nicola Biagio; Nuccetelli, Marzia; Izzi, Francesca; Bernardini, Sergio; Placidi, Fabio (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is the most common form of dementia. It is characterized by a progressive deterioration of cognition, frequently associated with neuropsychiatric symptoms (NPS). Among NPS, sleep disturbances often affect AD patients. Orexinergic system dysregulation has been associated with sleep impairment in AD patients. OBJECTIVE: The present study investigated CSF orexin levels in AD patients and their relationship with both NPS, measured by the neuropsychiatric inventory (NPI), and sleep, measured via polysomnography. METHODS: This is a secondary analysis of a previous study investigating CSF biomarkers, sleep impairment and cognitive decline in AD patients. AD patients completing the NPI were included in this analysis and distributed in two groups based on the presence (NPI score ≥4, AD/NPS+) or absence (NPI score <4, AD/NPS-) of NPS. RESULTS: Twenty-two AD patients constituted the AD/NPS+ group and 20 patients constituted the AD/NPS-group. We observed higher CSF orexin levels in AD/NPS+ than AD/NPS-patients. Moreover, AD/NPS+ showed a more fragmented and the reduction of REM sleep compared to AD/NPS-patients. Notably, higher NPI scores correlated with a more altered sleep structure, higher CSF orexin levels and lower MMSE scores. CONCLUSION: This study documented that AD patients showing NPS present a more fragmented sleep coupled with higher CSF orexin levels compared to AD patients not affected by NPS. This finding showing the increased orexinergic tone in AD patients affected by NPS suggests the possible influence of the orexinergic system dysregulation not only on sleep impairment but also on neurobehavioral disturbances.

Cerebrovascular Disease and Neurodegeneration in Alzheimer's Disease with and without a Strong Family History: A Pilot Magnetic Resonance Imaging Study in Dominican Republic. - Piriz, Angel; Reyes, Dolly; Narkhede, Atul; Guzman, Vanessa A; Viqar, Fawad; Meier, Irene B; Budge, Mariana; Mena, Pedro; Dashnaw, Stephen; Lee, Joseph; Reitz, Christiane; Gutierrez, Jose; et al. (J Alzheimers Dis, 2018)
The incidence and prevalence of Alzheimer's disease (AD) dementia are higher among Caribbean Hispanics than among non-Hispanic Whites. The causes of this health disparity remain elusive, partially because of the relative limited capacity for biomedical research in the developing countries that comprise Caribbean Latin America. To begin to address this issue, we were awarded a Development Research Award from the US NIH and Fogarty International Center in order to establish the local capacity to integrate magnetic resonance imaging (MRI) into studies of cognitive aging and dementia in Dominican Republic, establish collaborations with Dominican investigators, and conduct a pilot study on the role of cerebrovascular markers in the clinical expression of AD. Ninety older adult participants with and without AD dementia and with and without a strong family history of AD dementia received MRI scans and clinical evaluation. We quantified markers of cerebrovascular disease (white matter hyperintensities [WMH], presence of infarct, and presence of microbleed) and neurodegeneration (entorhinal cortex volume) and compared them across groups. Patients with AD dementia had smaller entorhinal cortex and greater WMH volumes compared with controls, regardless of family history status. This study provides evidence for the capacity to conduct MRI studies of cognitive aging and dementia in Dominican Republic. The results are consistent with the hypothesis that small vessel cerebrovascular disease represents a core feature of AD dementia, as affected participants had elevated WMH volumes irrespective of family history status.

Change of Amyloid-β 1-42 Toxic Conformer Ratio After Cerebrospinal Fluid Diversion Predicts Long-Term Cognitive Outcome in Patients with Idiopathic Normal Pressure Hydrocephalus. - Akiba, Chihiro; Nakajima, Madoka; Miyajima, Masakazu; Ogino, Ikuko; Motoi, Yumiko; Kawamura, Kaito; Adachi, Satoshi; Kondo, Akihide; Sugano, Hidenori; Tokuda, Takahiko; Irie, Kazuhiro; Arai, Hajime (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) pathology in idiopathic normal pressure hydrocephalus (iNPH) contributes to poor shunt responses. Amyloid-β 1- 42 (Aβ42) toxic conformer was recently identified with features of rapid oligomerization, strong neurotoxicity and synaptotoxicity. OBJECTIVE: This observational study points to Aβ42 toxic conformer as a biomarker for AD pathology and for poor postoperative prognosis in patients with iNPH. METHODS: The first cohort consisted of patients with AD (n = 17) and iNPH (n = 17), and cognitively normal individuals (CN, n = 12). The second cohort, consisted of 51 patients with iNPH, was divided into two groups according to phosphorylated Tau (pTau) level (low- and high-pTau groups); the low-pTau group was further subdivided according to one-year postoperative change in Aβ42 toxic conformer ratio (%) [Aβ42 toxic conformer/Aβ42×100] (decreased- and increased-conformer subgroups). Enzyme-linked immunosorbent assay was used to measure pTau, Aβ42, and Aβ42 toxic conformer in cerebrospinal fluid. Outcomes were evaluated using neuropsychological tests one- and two-years postoperatively. RESULTS: In the first cohort, Aβ42 toxic conformer ratio in the iNPH group (10.8%) was significantly higher than that in the CN group (6.3%) and significantly lower than that in the AD group (17.2%). In the second cohort, the high-pTau group showed cognitive decline two-years postoperatively compared to baseline. However, the low-pTau group showed favorable outcomes one-year postoperatively; furthermore, the increased-conformer subgroup showed cognitive decline two-years postoperatively while the decreased-conformer subgroup maintained the improvement. CONCLUSIONS: Change in Aβ42 toxic conformer ratio predicts long-term cognitive outcome in iNPH, even in the low-pTau group.

Circulating Progenitor Cells Correlate with Memory, Posterior Cortical Thickness, and Hippocampal Perfusion. - Nation, Daniel A; Tan, Alick; Dutt, Shubir; McIntosh, Elissa C; Yew, Belinda; Ho, Jean K; Blanken, Anna E; Jang, Jung Yun; Rodgers, Kathleen E; Gaubert, Aimée (J Alzheimers Dis, 2018)
BACKGROUND: Bone marrow-derived progenitor cells survey the vasculature and home to sites of tissue injury where they can promote repair and regeneration. It has been hypothesized that these cells may play a protective role neurodegenerative and vascular cognitive impairment. OBJECTIVE: To evaluate progenitor cell levels in older adults with and without mild cognitive impairment (MCI), and to relate circulating levels to memory, brain volume, white matter lesion volume, and cerebral perfusion. METHOD: Thirty-two older adults, free of stroke and cardiovascular disease, were recruited from the community and evaluated for diagnosis of MCI versus cognitively normal (CN). Participants underwent brain MRI and blood samples were taken to quantify progenitor reserve using flow cytometry (CD34+, CD34+CD133+, and CD34+CD133+CD309+ cells). RESULTS: Participants with MCI (n = 10) exhibited depletion of all CPC markers relative to those who were CN (n = 22), after controlling for age, sex, and education. Post-hoc age, sex, and education matched comparisons (n = 10 MCI, n = 10 CN) also revealed the same pattern of results. Depletion of CD34+ cells correlated with memory performance, left posterior cortical thickness, and bilateral hippocampal perfusion. Participants exhibited low levels of vascular risk and white matter lesion burden that did not correlate with progenitor levels. CONCLUSIONS: Circulating progenitor cells are associated with cognitive impairment, memory, cortical atrophy, and hippocampal perfusion. We hypothesize that progenitor depletion contributes to, or is triggered by, cognitive decline and cortical atrophy. Further study of progenitor cell depletion in older adults may benefit efforts to prevent or delay dementia.
Keywords: Aged; Aged, 80 and over; Antigens, CD; Apolipoproteins E; Cerebral Cortex; Cognitive Dysfunction; Female; Flow Cytometry; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Perfusion; Stem Cells; White Matter

Cognitive Variability Predicts Incident Alzheimer's Disease and Mild Cognitive Impairment Comparable to a Cerebrospinal Fluid Biomarker. - Gleason, Carey E; Norton, Derek; Anderson, Eric D; Wahoske, Michelle; Washington, Danielle T; Umucu, Emre; Koscik, Rebecca L; Dowling, N Maritza; Johnson, Sterling C; Carlsson, Cynthia M; Asthana, Sanjay (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) biomarkers are emerging as critically important for disease detection and monitoring. Most biomarkers are obtained through invasive, resource-intense procedures. A cognitive marker, intra-individual cognitive variability (IICV) may provide an alternative or adjunct marker of disease risk for individuals unable or disinclined to undergo lumbar puncture. OBJECTIVE: To contrast risk of incident AD and mild cognitive impairment (MCI) associated with IICV to risk associated with well-established biomarkers: cerebrospinal fluid (CSF) phosphorylated tau protein (p-tau181) and amyloid-β 42 (Aβ42) peptide. METHODS: Dispersion in cognitive performance, IICV, was estimated with a published algorithm, and included Trail Making Test A and B, Rey Auditory Verbal Learning Test (RAVLT), and the American National Adult Reading Test (ANART). CSF biomarkers were expressed as a ratio: p-tau181/Aβ42, wherein high values signified pathognomonic profiles. Logistic regression models included longitudinal data from 349 Alzheimer's Disease Neuroimaging Initiative (ADNI) participants who completed lumbar puncture. All subjects were cognitively healthy (n = 105) or diagnosed with MCI (n = 244) at baseline. We examined odds of conversion associated with baseline elevations in IICV and/or ratio of CSF p-tau181/Aβ42. RESULTS: When included in models alone or in combination with CSF p-tau181/Aβ42, one standard IICV unit higher was associated with an estimated odds ratio for incident AD or MCI of 2.81 (95% CI: 1.83-4.33) in the most inclusive sample, and an odds ratio of 3.41 (95% CI: 2.03-5.73) when restricted to participants with MCI. Iterative analyses suggested that IICV independently improved model fit even when individual index components were included in comparative models. CONCLUSIONS: These analyses provide preliminary support for IICV as a marker of incident AD and MCI. This easily-disseminated, non-invasive marker compared favorably to well-established CSF biomarkers.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Female; Humans; Incidence; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Statistics, Nonparametric; tau Proteins

Comparing the Electronic and Standard Versions of the Montreal Cognitive Assessment in an Outpatient Memory Disorders Clinic: A Validation Study. - Berg, Jody-Lynn; Durant, January; Léger, Gabriel C; Cummings, Jeffrey L; Nasreddine, Ziad; Miller, Justin B (J Alzheimers Dis, 2018)
The Montreal Cognitive Assessment (MoCA) has become widely used as a brief test of cognitive function in patients with neurological disease. More convenient application of the MoCA might increase its use and enhance its utility. An electronic version of the MoCA has recently been developed. To establish validity of the electronic version (eMoCA), discrepancy scores, concordance correlation coefficients (CCC), and root mean squared differences (RMSD) were calculated between each administration method in a sample of 43 new adult patients presenting with primary memory complaints. The CCC was 0.84 and the RMSD was 2.27, with 76% of the sample having a difference score within 2 points. Overall, this study establishes adequate convergent validity between the MoCA and eMoCA among an adult population presenting with memory concerns.

Complexity and Selectivity of γ-Secretase Cleavage on Multiple Substrates: Consequences in Alzheimer's Disease and Cancer. - Medoro, Alessandro; Bartollino, Silvia; Mignogna, Donatella; Passarella, Daniela; Porcile, Carola; Pagano, Aldo; Florio, Tullio; Nizzari, Mario; Guerra, Germano; Di Marco, Roberto; Intrieri, Mariano; Raimo, Gennaro; et al. (J Alzheimers Dis, 2018)
The processing of the amyloid-β protein precursor (AβPP) by β- and γ-secretases is a pivotal event in the genesis of Alzheimer's disease (AD). Besides familial mutations on the AβPP gene, or upon its overexpression, familial forms of AD are often caused by mutations or deletions in presenilin 1 (PSEN1) and 2 (PSEN2) genes: the catalytic components of the proteolytic enzyme γ-secretase (GS). The "amyloid hypothesis", modified over time, states that the aberrant processing of AβPP by GS induces the formation of specific neurotoxic soluble amyloid-β (Aβ) peptides which, in turn, cause neurodegeneration. This theory, however, has recently evidenced significant limitations and, in particular, the following issues are debated: 1) the concept and significance of presenilin's "gain of function" versus "loss of function"; and 2) the presence of several and various GS substrates, which interact with AβPP and may influence Aβ formation. The latter consideration is suggestive: despite the increasing number of GS substrates so far identified, their reciprocal interaction with AβPP itself, even in the AD field, is significantly unexplored. On the other hand, GS is also an important pharmacological target in the cancer field; inhibitors or GS activity are investigated in clinical trials for treating different tumors. Furthermore, the function of AβPP and PSENs in brain development and in neuronal migration is well known. In this review, we focused on a specific subset of GS substrates that directly interact with AβPP and are involved in its proteolysis and signaling, by evaluating their role in neurodegeneration and in cell motility or proliferation, as a possible connection between AD and cancer.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Humans; Neoplasms; Presenilin-1

Contribution of Bilingualism to Cognitive Reserve of an Italian Literature Professor at High Risk for Alzheimer's Disease. - Lombardi, Gemma; Polito, Cristina; Berti, Valentina; Bagnoli, Silvia; Nacmias, Benedetta; Pupi, Alberto; Sorbi, Sandro (J Alzheimers Dis, 2018)
Bilingualism is an independent component of cognitive reserve that permits to delay dementia onset up to 5 years. We describe a case of a bilingual Italian man affected by mild cognitive impairment with high cognitive reserve that, despite the presence of multiple risk factors (ApoE ɛ4/ɛ4 genotype, older age, untreated Obstructive Sleep Apnea Syndrome, AD-like biomarker alterations) did not convert to Alzheimer's disease up to 5 years follow-up. The present case confirms the role of bilingualism as a strong protective factor for dementia, even in the occurrence of multiple risk factors.

Decoupling of Local Metabolic Activity and Functional Connectivity Links to Amyloid in Alzheimer's Disease. - Scherr, Martin; Pasquini, Lorenzo; Benson, Gloria; Nuttall, Rachel; Gruber, Martin; Neitzel, Julia; Brandl, Felix; Sorg, Christian (J Alzheimers Dis, 2018)
BACKGROUND: Both ongoing local metabolic activity (LMA) and corresponding functional connectivity (FC) with remote brain regions are progressively impaired in Alzheimer's disease (AD), particularly in the posterior default mode network (pDMN); however, it is unknown how these impairments interact. It is well known that decreasing mean synaptic activity of a region, i.e., decreasing LMA, reduces the region's sensitivity to afferent input from other regions, i.e., FC. OBJECTIVE: We hypothesized progressive decoupling between LMA and FC in AD, which is linked to amyloid-β pathology (Aβ). METHODS: Healthy adults (n=20) and Aβ+patients without memory impairment (n=9), early MCI (n=21), late MCI (n=18) and AD (n=22) were assessed by resting-state fMRI, FDG-PET, and AV-45-PET to measure FC, LMA, and Aβ of the pDMN. Coupling between LMA and FC (rLA/FC) was estimated by voxelwise correlation. RESULTS: RLMA/FC decreased with disease severity (F=20.09, p<0.001). This decrease was specifically associated with pDMN Aβ (r=-0.273, p=0.029) but not global Aβ (r=-0.112, p=0.378) and with the impact of Aβ on FC (i.e., rAβ/FC,r=-0.339; p=0.006). In multiple regression models rLMA/FC was also associated with memory impairment, reduced cognitive speed and flexibility, outperforming global Aβ, pDMN Aβ, pDMN LMA, and pDMN FC, respectively. CONCLUSION: Results demonstrate increasing decoupling of LMA from its FC in AD. Data suggest that decoupling is driven by local Aβ and contributes to memory decline.

Decreased Parietal Beta Power as a Sign of Disease Progression in Patients with Mild Cognitive Impairment. - Musaeus, Christian Sandøe; Nielsen, Malene Schjønning; Østerbye, Natascha Nellum; Høgh, Peter (J Alzheimers Dis, 2018)
BACKGROUND: Electroencephalography (EEG) power has previously been used to compare mild cognitive impairment (MCI) patients who progress to Alzheimer's disease (pMCI) with patients with MCI who remain stable (sMCI) by using beta power. However, the beta band is very broad and smaller frequency bands may improve accuracy. OBJECTIVE: In the present study, we wanted to investigate whether it was possible to find any differences between pMCI and sMCI using relative power and whether these differences were correlated to cognitive function or neuropathology markers. METHODS: 17 patients with AD, 27 patients with MCI, and 38 older healthy controls were recruited from two memory clinics and followed for three years. EEGs were recorded at baseline for all participants and relative power was calculated. All participants underwent adjusted batteries of standardized cognitive tests and lumbar puncture. RESULTS: We found that pMCI showed decreased baseline relative power in the parietal electrodes in the beta1 band (13-17.99 Hz). At 2-year follow-up, we found changes in all baseline beta bands but most pronounced in the beta1 band. In addition, we found that qEEG parietal power was correlated with amyloid-β42 and anterograde memory. CONCLUSION: These findings suggests that relative power in the parietal electrodes in the beta1 band may be a better way to discriminate between pMCI and sMCI at the time of diagnosis than the broad beta band. Similar findings have also been found with resting state fMRI. In addition, we found that anterograde memory was correlated to qEEG parietal beta1 power.

Deep Brain Stimulation of Frontal Lobe Networks to Treat Alzheimer's Disease. - Scharre, Douglas W; Weichart, Emily; Nielson, Dylan; Zhang, Jun; Agrawal, Punit; Sederberg, Per B; Knopp, Michael V; Rezai, Ali R (J Alzheimers Dis, 2018)
The study objective was to evaluate the safety and efficacy of deep brain stimulation (DBS) at the ventral capsule/ventral striatum (VC/VS) region to specifically modulate frontal lobe behavioral and cognitive networks as a novel treatment approach for Alzheimer's disease (AD) patients. This is a non-randomized phase I prospective open label interventional trial of three subjects with matched comparison groups. AD participants given DBS for at least 18 months at the VC/VS target were compared on the Clinical Dementia Rating-Sum of Boxes (CDR-SB), our primary outcome clinical measure, to matched groups without DBS from the AD Neuroimaging Initiative (ADNI) cohort. Serial 2-Deoxy-2-[18F]fluoro-D-glucose (FDG) positron emission tomography (PET) images of AD participants were also compared longitudinally over time. Three AD DBS participants were matched to subjects from the ADNI cohort. All participants tolerated DBS well without significant adverse events. All three AD DBS participants had less performance decline and two of them meaningfully less decline over time on our primary outcome measure, CDR-SB, relative to matched comparison groups from the ADNI using score trajectory slopes. Minimal changes or increased metabolism on FDG-PET were seen in frontal cortical regions after chronic DBS at the VC/VS target. The first use of DBS in AD at a frontal lobe behavior regulation target (VC/VS) was well-tolerated and revealed less performance decline in CDR-SB. Frontal network modulation to improve executive and behavioral deficits should be furthered studied in AD.
Keywords: Aged; Alzheimer Disease; Deep Brain Stimulation; Female; Frontal Lobe; Humans; Male; Middle Aged; Ohio; Pilot Projects; Positron-Emission Tomography; Prospective Studies

Dementia Care Competence Among Care Professionals and Reduced Challenging Behavior of Home-Dwelling Persons with Dementia: A Pre- and Post-Intervention Data Analysis. - Nakanishi, Miharu; Hirooka, Kayo; Imai, Yasuaki; Inoue, Shintaro; Yukari, Yukio; Katayama, Chie; Miyamoto, Yuki; Shindo, Yumi; Ueno, Hideki; Toya, Junichiro; Takano, Yosuke; Nishida, Atsushi (J Alzheimers Dis, 2018)
BACKGROUND: We developed a psychosocial dementia care program to help care managers and professional caregivers manage challenging behavior in home-dwelling persons with dementia in Japan. The program consists of a web-based tool for ongoing monitoring and assessment for challenging behavior, and multi-agency discussion meetings. Results of a cluster-randomized controlled trial indicate a reduction in challenging behavior through this program. OBJECTIVES: The present study aimed to identify a key component of the developed program that is associated with a reduction in challenging behavior. METHODS: We used consecutive data of the intervention and examined the association between challenging behavior in home-dwelling persons with dementia, professionals' competence, and the frequency of revision of action plans. Challenging behavior was assessed using the total score of the Neuropsychiatric Inventory. A baseline and follow-up questionnaire was completed by care professionals using a Japanese version of the Sense of Competence in Dementia Care Staff scale. RESULTS: A total of 86 care professionals completed a 6-month intervention with 219 persons with dementia. The 86 care professionals significantly improved in their dementia care competence. Challenging behavior was significantly reduced among the 219 persons with dementia at follow-up regardless of the level of professionals' competence or the frequency of revision of action plans. Less pain was significantly related to the lower levels of challenging behavior. CONCLUSION: The ongoing multi-agency discussion meetings, with a focus on challenging behavior, may have been the key component in the psychosocial dementia care program. Pain management should be emphasized in action plans for challenging behavior.

Designing an Internet-Based Multidomain Intervention for the Prevention of Cardiovascular Disease and Cognitive Impairment in Older Adults: The HATICE Trial. - Barbera, Mariagnese; Mangialasche, Francesca; Jongstra, Susan; Guillemont, Juliette; Ngandu, Tiia; Beishuizen, Cathrien; Coley, Nicola; Brayne, Carol; Andrieu, Sandrine; Richard, Edo; Soininen, Hilkka; Kivipelto, Miia (J Alzheimers Dis, 2018)
BACKGROUND: Many dementia and cardiovascular disease (CVD) cases in older adults are attributable to modifiable vascular and lifestyle-related risk factors, providing opportunities for prevention. In the Healthy Aging Through Internet Counselling in the Elderly (HATICE) randomized controlled trial, an internet-based multidomain intervention is being tested to improve the cardiovascular risk (CVR) profile of older adults. OBJECTIVE: To design a multidomain intervention to improve CVR, based on the guidelines for CVR management, and administered through a coach-supported, interactive, platform to over 2500 community-dwellers aged 65+ in three European countries. METHODS: A comparative analysis of national and European guidelines for primary and secondary CVD prevention was performed. Results were used to define the content of the intervention. RESULTS: The intervention design focused on promoting awareness and self-management of hypertension, dyslipidemia, diabetes mellitus, and overweight, and supporting smoking cessation, physical activity, and healthy diet. Overall, available guidelines lacked specific recommendations for CVR management in older adults. The comparative analysis of the guidelines showed general consistency for lifestyle-related recommendations. Key differences, identified mostly in methods used to assess the overall CVR, did not hamper the intervention design. Minor country-specific adaptations were implemented to maximize the intervention feasibility in each country. CONCLUSION: Despite differences in CVR management within the countries considered, it was possible to design and implement the HATICE multidomain intervention. The study can help define preventative strategies for dementia and CVD that are applicable internationally.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cognitive Dysfunction; Counseling; Europe; Exercise; Female; Healthy Aging; Humans; Internet; Life Style; Male; Practice Guidelines as Topic; Risk Factors; Telemedicine

Development of a High-Sensitivity Method for the Measurement of Human Nasal Aβ42, Tau, and Phosphorylated Tau. - Liu, Ziyi; Kameshima, Naoko; Nanjo, Toshifumi; Shiino, Akihiko; Kato, Tomoko; Shimizu, Shino; Shimizu, Takeshi; Tanaka, Sachiko; Miura, Katsuyuki; Tooyama, Ikuo (J Alzheimers Dis, 2018)
Cost-effective and feasible methods for early diagnosis of Alzheimer's disease (AD) are needed. We present two methods to measure AD-related biomarkers simultaneously from one nasal smear for the purpose of diagnosing AD. Japanese men and women aged 63-85 years old were recruited in 2015-2016 for this case-control study. A total of 25 AD cases and 25 controls (22 men and 28 women) participated in this research. Nasal smears were collected from the common nasal meatus, inferior concha, middle nasal meatus, and olfactory cleft, and the proteins in the samples were analyzed by two methods, which we named PGD (Pre-treatment with guanidine- n-Dodecyl-beta-D-maltoside solution) method 1 (PGD-I) and 2 (PGD-II). The PGD-I method measured total tau and amyloid-β (Aβ)42, but no differences in median levels of total tau and Aβ42 between AD cases and controls were found in any of the nasal locations. The PGD-II method measured Aβ42, total tau, and phosphorylated tau, but levels of Aβ40 in all nasal locations of both groups were near zero. Median levels of phosphorylated tau to total tau (p-tau/t-tau) ratios in the middle nasal meatus and in the olfactory cleft were significantly higher in AD cases than in controls, and could significantly predict AD. To assess diagnostic reliability, areas under the ROC curve were 0.74 (95% CL = 0.52-0.95, p = 0.030) for the middle nasal meatus and 0.72 (95% CL = 0.52-0.92, p = 0.029) for the olfactory cleft. Thus, PGD-I and PGD-II can detect AD-related biomarkers in nasal smears and PGD-II may be a useful tool for diagnosing AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Case-Control Studies; Female; Humans; Male; Middle Aged; Nasal Mucosa; Peptide Fragments; Phosphorylation; Reproducibility of Results; ROC Curve; tau Proteins

The Diagnostic and Prognostic Value of a Dual-Tasking Paradigm in a Memory Clinic. - Nielsen, Malene Schjnning; Simonsen, Anja Hviid; Siersma, Volkert; Hasselbalch, Steen Gregers; Hoegh, Peter (J Alzheimers Dis, 2018)
BACKGROUND: Daily living requires the ability to perform dual-tasking. As cognitive skills decrease in dementia, performing a cognitive and motor task simultaneously become increasingly challenging and subtle gait abnormalities may even be present in pre-dementia stages. Therefore, a dual-tasking paradigm, such as the Timed Up and Go-Dual Task (TUG-DT), may be useful in the diagnostic assessment of mild cognitive impairment (MCI). OBJECTIVE: To investigate the diagnostic and prognostic ability of a dual-tasking paradigm in patients with MCI or mild Alzheimer's disease (AD) and to evaluate the association between the dual-tasking paradigm and cerebrospinal fluid (CSF) AD biomarkers. METHODS: The study is a prospective cohort study conducted in a clinical setting in two memory clinics. Eighty-six patients were included (28 MCI, 17 AD, 41 healthy controls (HC)). The ability to perform dual-tasking was evaluated by the TUG-DT. Patients underwent a standardized diagnostic assessment and were evaluated to determine progression yearly. RESULTS: ROC curve analysis illustrated a high discriminative ability of the dual-tasking paradigm in separating MCI patients from HC (AUC: 0.78, AUC: 0.82) and a moderate discriminative ability in separating MCI from AD (AUC: 0.73, AUC: 0.55). Performance discriminated clearly between all groups (p < 0.01). Logistic regression analyses revealed a low prognostic value of the dual-tasking paradigm for progression and rate of cognitive decline. A moderately strong correlation between the dual-tasking paradigm and CSF AD biomarkers was observed. CONCLUSION: In our study, we found that patients with MCI and mild AD have increasing difficulties in dual-tasking compared to healthy elderly. Hence, the dual-tasking paradigm may be a potential complement in the diagnostic assessment in a typical clinical setting.
Keywords: Aged; Alzheimer Disease; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Disease Progression; Female; Humans; Logistic Models; Male; Memory; Middle Aged; Neuropsychological Tests; Prognosis; Prospective Studies; ROC Curve

Diet Supplementation with Hydroxytyrosol Ameliorates Brain Pathology and Restores Cognitive Functions in a Mouse Model of Amyloid-β Deposition. - Nardiello, Pamela; Pantano, Daniela; Lapucci, Andrea; Stefani, Massimo; Casamenti, Fiorella (J Alzheimers Dis, 2018)
Alzheimer's disease is the most common form of dementia affecting a large proportion of aged people. Plant polyphenols have been reported to be potentially useful in the prevention of AD due to their multiple pharmacological activities. The aim of the present study was to assess whether the previously reported neuroprotective and anti-inflammatory effects resulting from oleuropein aglycone administration were reproduced by diet supplementation with similar amounts of its metabolite hydoxytyrosol (HT). Four-month-old TgCRND8 and wild type mice were treated for 8 weeks with a low-fat diet (5%) supplemented with HT (50 mg/kg of diet). We found that HT supplementation significantly improved cognitive functions of TgCRND8 mice and significantly reduced Aβ42 and pE3-Aβ plaque area and number in the cortex; in the hippocampal areas of HT-fed TgCRND8 mice, we found a significant reduction in the pE3-Aβ plaque number together with a tendency toward a reduction in Aβ42 load and pE3-Aβ plaque area, associated with a marked reduction of TNF-α expression and astrocyte reaction. Macroautophagy induction and modulation of MAPKs signaling were found to underlie the beneficial effects of HT. Our findings indicate that HT administration reproduces substantially the beneficial effects on behavioral performance and neuropathology previously reported in TgCRND8 mice fed with oleuropein aglycone, resulting in comparable neuroprotection.

Differences in Dementia Beliefs between Non-Demented Public Screeners and In-Home Screeners and Their Potential Impact on Future Dementia Screening Intention: The Nakajima Study. - Yuki-Nozaki, Sohshi; Noguchi-Shinohara, Moeko; Domoto, Chiaki; Ikeda, Yoshihisa; Samuraki, Miharu; Iwasa, Kazuo; Yokogawa, Masami; Asai, Kimiko; Komai, Kiyonobu; Nakamura, Hiroyuki; Yamada, Masahito (J Alzheimers Dis, 2018)
In many cohort studies of dementia, while differences in sociodemographic characters between responders and non-responders of dementia screening have been reported, differences in dementia beliefs have been relatively less known. The aims of this study were to clarify dementia beliefs and to explore potential impacts on an intention to attend a future dementia screening in public screeners and in-home screeners, respectively. We performed a cross-sectional population-based study using a question about an intention to attend a future dementia screening and a questionnaire on dementia beliefs. Subjects were all residents aged 65 years or older in the north area of Nakajima, Japan (n = 385). All subjects were asked to attend a public dementia screening first. An in-home dementia screening was subsequently conducted in subjects with non-responders to a public screening. The questionnaire consisted of four dementia beliefs: "perceived susceptibility," "perceived severity," "perceived barriers," and "perceived benefits." Public screeners significantly expressed an intention to attend a future dementia screening more than in-home screeners (p = 0.002). In in-home screeners, low "perceived severity" were significantly associated with an intention to attend a future dementia screening [adjusted OR (95% CI) = 0.51 (0.32-0.80)]. In both public and in-home screeners, high "perceived benefits" were significantly associated with an intention to attend a future dementia screening [adjusted OR (95% CI) = 2.13 (1.46-3.10); adjusted OR (95% CI) = 2.56 (1.22-5.35), respectively]. It is necessary to reduce "perceived severity" among in-home screeners to increase dementia screening participants.

Different Abnormalities of Cortical Neural Synchronization Mechanisms in Patients with Mild Cognitive Impairment due to Alzheimer's and Chronic Kidney Diseases: An EEG Study. - Lizio, Roberta; Babiloni, Claudio; Del Percio, Claudio; Losurdo, Antonia; Vernò, Lucia; De Tommaso, Marina; Montemurno, Anna; Dalfino, Giuseppe; Cirillo, Pietro; Soricelli, Andrea; Ferri, Raffaele; Noce, Giuseppe; et al. (J Alzheimers Dis, 2018)
This study tested whether resting state alpha rhythms (8-13 Hz) may characterize mild cognitive impairment due to Alzheimer's disease (ADMCI) compared with MCI due to chronic kidney disease (CKDMCI). Clinical and resting state eyes-closed electroencephalographic (rsEEG) rhythms from 40 ADMCI, 29 CKDMCI, and 45 cognitively normal elderly (Nold) subjects were available in a national archive. Age, gender, and education were matched in the three groups, and Mini-Mental State Evaluation (MMSE) score was paired in the ADMCI and CKDMCI groups. Delta (<4 Hz), theta (4-8 Hz), alpha 1 (8-10.5 Hz), alpha 2 (10.5-13 Hz), beta 1 (13-20 Hz), beta 2 (20-30 Hz), and gamma (30-40 Hz) cortical sources were estimated by eLORETA freeware and classified across individuals by area under the receiver operating characteristic curve (AUROCC). Compared with Nold group, posterior alpha 1 source activities were more reduced in ADMCI than CKDMCI group. In contrast, widespread delta source activities were greater in CKDMCI than ADMCI group. These source activities correlated with the MMSE score and correctly classified between Nold and all MCI individuals (AUROCC = 0.8-0.85) and between ADMCI and CKDMCI subjects (AUROCC = 0.75). These results suggest that early AD affects cortical neural synchronization at alpha frequencies underpinning brain arousal and low vigilance in the quiet wakefulness. In contrast, CKD may principally affect cortical neural synchronization at the delta frequencies. Future prospective cross-validation studies will have to test these candidate rsEEG markers for clinical applications and drug discovery.

Differential Effect of APOE ɛ4 Status and Elevated Pulse Pressure on Functional Decline in Cognitively Normal Older Adults. - Werhane, Madeleine L; Thomas, Kelsey R; Edmonds, Emily C; Bangen, Katherine J; Tran, My; Clark, Alexandra L; Nation, Daniel A; Gilbert, Paul E; Bondi, Mark W; Delano-Wood, Lisa (J Alzheimers Dis, 2018)
BACKGROUND/OBJECTIVE: The APOE ɛ4 allele and increased vascular risk have both been independently linked to cognitive impairment and dementia. Since few studies have characterized how these risk factors affect everyday functioning, we investigated the relationship between APOE ɛ4 genotype and elevated pulse pressure (PP) on functional change in cognitively normal participants from the Alzheimer's Disease Neuroimaging Initiative (ADNI). METHODS: 738 normally aging participants underwent APOE genotyping, and baseline PP was calculated from blood pressure indices. The Functional Activities Questionnaire (FAQ) was completed by participants' informant at baseline and 6, 12, 24, 36, and 48-month follow-up visits. Multiple linear regression and multilevel modeling were used to examine the effects of PP and APOE ɛ4 genotype on cross-sectional and longitudinal FAQ scores, respectively. RESULTS: Adjusting for demographic and clinical covariates, results showed that both APOE ɛ4 status and elevated PP predicted greater functional difficulty trajectories across four years of follow-up. Interestingly, however, elevated PP was associated with greater functional decline over time in ɛ4 non-carriers versus carriers. CONCLUSION: Results show that, although APOE ɛ4 status is the prominent predictor of functional difficulty for ɛ4 carriers, an effect of arterial stiffening on functional difficulty was observed in non-carriers. Future studies are needed in order to clarify the etiology of the association between PP and different brain aging processes, and further explore its utility as a marker of dementia risk. The present study underscores the importance of targeting modifiable risk factors such as elevated PP to prevent or slow functional decline and pathological brain aging.

Diffuse Amyloid-β Plaques, Neurofibrillary Tangles, and the Impact of APOE in Elderly Persons' Brains Lacking Neuritic Amyloid Plaques. - Abner, Erin L; Neltner, Janna H; Jicha, Gregory A; Patel, Ela; Anderson, Sonya L; Wilcock, Donna M; Van Eldik, Linda J; Nelson, Peter T (J Alzheimers Dis, 2018)
Data from a large autopsy series were analyzed to address questions pertinent to primary age-related tauopathy (PART) and Alzheimer's disease (AD): what factors are associated with increased severity of neurofibrillary degeneration in brains that lack neuritic amyloid plaques?; is there an association between Apolipoprotein E (APOE) alleles and PART pathologic severity independent of amyloid-β (Aβ) deposits?; and, how do the stains used to detect plaques and tangles impact the experimental results? Neuropathologic data were evaluated from elderly research volunteers whose brain autopsies were performed at University of Kentucky Alzheimer's Disease Center (UK-ADC; N = 145 subjects). All of the included subjects' brains lacked neuritic amyloid plaques according to the CERAD diagnostic criteria and the average final MMSE score before death was 26.8±4.6 stdev. The study incorporated evaluation of tissue with both silver histochemical stains and immunohistochemical stains to compare results; the immunohistochemical stains (Aβ and phospho-tau) were scanned and quantified using digital pathologic methods. Immunohistochemical stains provided important advantages over histochemical stains due to sensitivity and detectability via digital methods. When AD-type pathology was in its presumed earliest phases, neocortical parenchymal Aβ deposits were associated with increased medial temporal lobe neurofibrillary tangles. The observation supports the NIA-AA consensus recommendation for neuropathologic diagnoses, because even these "diffuse" Aβ deposits signal that AD pathobiologic mechanisms are occurring. Further, the data were most compatible with the hypothesis that the APOEɛ4 allele exerts its effect(s) via driving Aβ deposition, i.e., an "upstream" influence, rather than being associated directly with Aβ- independent PART pathology.

Distinct White Matter Changes Associated with Cerebrospinal Fluid Amyloid-β1-42 and Hypertension. - Al-Janabi, Omar M; Brown, Christopher A; Bahrani, Ahmed A; Abner, Erin L; Barber, Justin M; Gold, Brian T; Goldstein, Larry B; Murphy, Ronan R; Nelson, Peter T; Johnson, Nathan F; Shaw, Leslie M; Smith, Charles D; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) pathology and hypertension (HTN) are risk factors for development of white matter (WM) alterations and might be independently associated with these alterations in older adults. OBJECTIVE: To evaluate the independent and synergistic effects of HTN and AD pathology on WM alterations. METHODS: Clinical measures of cerebrovascular disease risk were collected from 62 participants in University of Kentucky Alzheimer's Disease Center studies who also had cerebrospinal fluid (CSF) sampling and MRI brain scans. CSF Aβ1-42 levels were measured as a marker of AD, and fluid-attenuated inversion recovery imaging and diffusion tensor imaging were obtained to assess WM macro- and microstructural properties. Linear regression analyses were used to assess the relationships among WM alterations, cerebrovascular disease risk, and AD pathology. Voxelwise analyses were performed to examine spatial patterns of WM alteration associated with each pathology. RESULTS: HTN and CSF Aβ1-42 levels were each associated with white matter hyperintensities (WMH). Also, CSF Aβ1-42 levels were associated with alterations in normal appearing white matter fractional anisotropy (NAWM-FA), whereas HTN was marginally associated with alterations in NAWM-FA. Linear regression analyses demonstrated significant main effects of HTN and CSF Aβ1-42 on WMH volume, but no significant HTN×CSF Aβ1-42 interaction. Furthermore, voxelwise analyses showed unique patterns of WM alteration associated with hypertension and CSF Aβ1-42. CONCLUSION: Associations of HTN and lower CSF Aβ1-42 with WM alteration were statistically and spatially distinct, suggesting independent rather than synergistic effects. Considering such spatial distributions may improve diagnostic accuracy to address each underlying pathology.

EEG Theta Power Is an Early Marker of Cognitive Decline in Dementia due to Alzheimer's Disease. - Musaeus, Christian Sandøe; Engedal, Knut; Høgh, Peter; Jelic, Vesna; Mørup, Morten; Naik, Mala; Oeksengaard, Anne-Rita; Snaedal, Jon; Wahlund, Lars-Olof; Waldemar, Gunhild; Andersen, Birgitte Bo (J Alzheimers Dis, 2018)
BACKGROUND: Quantitative EEG (qEEG) power could potentially be used as a diagnostic tool for Alzheimer's disease (AD) and may further our understanding of the pathophysiology. However, the early qEEG power changes of AD are not well understood. OBJECTIVE: To investigate the early changes in qEEG power and the possible correlation with memory function and cerebrospinal fluid biomarkers. In addition, whether qEEG power could discriminate between AD, mild cognitive impairment (MCI), and older healthy controls (HC) at the individual level. METHODS: Standard EEGs from 138 HC, 117 MCI, and 117 AD patients were included from six Nordic memory clinics. All EEGs were recorded consecutively before the diagnosis and were not used for the consensus diagnosis. Absolute and relative power was calculated for both eyes closed and open condition. RESULTS: At group level using relative power, we found significant increases globally in the theta band and decreases in high frequency power in the temporal regions for eyes closed for AD and, to a lesser extent, for MCI compared to HC. Relative theta power was significantly correlated with multiple neuropsychological measures and had the largest correlation coefficient with total tau. At the individual level, the classification rate for AD and HC was 72.9% for relative power with eyes closed. CONCLUSION: Our findings suggest that the increase in relative theta power may be the first change in patients with dementia due to AD. At the individual level, we found a moderate classification rate for AD and HC when using EEGs alone.

Effect of Cilostazol on Incident Dementia in Elderly Men and Women with Ischemic Heart Disease. - Kim, Mi-Young; Noh, Yoojin; Son, Sang Joon; Shin, Sooyoung; Paik, Hee-Young; Lee, Sukhyang; Jung, Yi-Sook (J Alzheimers Dis, 2018)
BACKGROUND: Ischemic heart disease (IHD) is associated with cognitive decline and may contribute to an increased risk of dementia. OBJECTIVE: The goal of the present study was to investigate whether cilostazol use is associated with a lower risk of incident dementia in Asian patients with IHD, and whether these effects differed based on sex. METHODS: This retrospective cohort study was performed using the Korean National Insurance Claim Data of the Health Insurance Review and Assessment Service; the duration of the study was from January 1, 2007 to December 31, 2015. The study group comprised 66,225 patients with IHD, aged >65 years, who had received cilostazol. Age- and sex-matched IHD patients without cilostazol exposure were selected as the control group. The risk of dementia was compared between the cilostazol and control groups. RESULTS: Compared to the control group, total cilostazol users had a marginally significant lower risk of incident dementia. After stratification by sex, the reducing effect of cilostazol on incident dementia was significant in female participants, but not in male participants. Female patients who had cilostazol for over 2 years showed a clinically meaningful preventive effect (HR, 0.85; 95% CI, 0.82-0.88). CONCLUSIONS: This study suggested that cilostazol treatment may reduce the risk of incident dementia in Korean patients with IHD. Its beneficial effect was remarkably significant in female patients who received cilostazol for over a 2-year period.

Effect of Education on Alzheimer's Disease-Related Neuroimaging Biomarkers in Healthy Controls, and Participants with Mild Cognitive Impairment and Alzheimer's Disease: A Cross-Sectional Study. - Wada, Masataka; Noda, Yoshihiro; Shinagawa, Shunichiro; Chung, Jun Ku; Sawada, Kyosuke; Ogyu, Kamiyu; Tarumi, Ryosuke; Tsugawa, Sakiko; Miyazaki, Takahiro; Yamagata, Bun; Graff-Guerrero, Ariel; Mimura, Masaru; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Cognitive reserve is the acquired capacity reflecting a functional brain adaptability/flexibility in the context of aging. Educational attainment is thought to be among the most important factors that contribute to cognitive reserve. OBJECTIVE: The aim of this study is to investigate the relationships among duration of education and Alzheimer's disease (AD) related neuroimaging biomarkers such as amyloid-β deposition, glucose metabolism, and brain volumes in each stage of AD. METHODS: We reanalyzed a part of the datasets of the Alzheimer's Disease Neuroimaging Initiative. Participants were between 55 and 90 years of age and diagnosed as one of the following: healthy controls (HC), mild cognitive impairment (MCI), or AD. Multiple regression analyses were conducted to examine the relationships among duration of education and amyloid-β deposition (n = 825), brain metabolism (n = 1,304), and brain volumes (n = 1,606) among three groups using data for 18F-Florbetapir (AV-45) imaging, fludeoxyglucose (FDG) positron emission tomography, and T1-weighted magnetic resonance imaging. RESULTS: Duration of education had no correlations with amyloid-β deposition or brain metabolism in any groups. However, duration of education was positively associated with the total brain volume only in participants with MCI. CONCLUSIONS: Our findings suggest that education may exert a protective effect on total brain volume in the MCI stage but not in HC or AD. Thus, education may play an important role in preventing the onset of dementia through brain reserve in MCI.

Effectiveness of a Personalized Brain-Computer Interface System for Cognitive Training in Healthy Elderly: A Randomized Controlled Trial. - Yeo, Si Ning; Lee, Tih Shih; Sng, Wei Theng; Heo, Min Quan; Bautista, Dianne; Cheung, Yin Bun; Zhang, Hai Hong; Wang, Chuanchu; Chin, Zheng Yang; Feng, Lei; Zhou, Juan; Chong, Mei Sian; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Cognitive training has been demonstrated to improve cognitive performance in older adults. To date, no study has explored personalized training that targets the brain activity of each individual. OBJECTIVE: This is the first large-scale trial that examines the usefulness of personalized neurofeedback cognitive training. METHODS: We conducted a randomized-controlled trial with participants who were 60-80 years old, with Clinical Dementia Rating (CDR) score of 0-0.5, Mini-Mental State Examination (MMSE) score of 24 and above, and with no neuropsychiatric diagnosis. Participants were randomly assigned to the Intervention or Waitlist-Control group. The training system, BRAINMEM, has attention, working memory, and delayed recall game components. The intervention schedule comprised 24 sessions over eight weeks and three monthly booster sessions. The primary outcome was the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) total score after the 24-session training. RESULTS: There were no significant between-subjects differences in overall cognitive performance post-intervention. However, a sex moderation effect (p = 0.014) was present. Men in the intervention group performed better than those in the waitlist group (mean difference, +4.03 (95% CI 0.1 to 8.0), p = 0.046. Among females, however, both waitlist-control and intervention participants improved from baseline, although the between-group difference in improvement did not reach significance. BRAINMEM also received positive appraisal and intervention adherence from the participants. CONCLUSION: A personalized neurofeedback intervention is potentially feasible for use in cognitive training for older males. The sex moderation effect warrants further investigation and highlights the importance of taking sex into account during cognitive training.

Effectiveness of Anti-Dementia Drugs in Extremely Severe Alzheimer's Disease: A 12-Week, Multicenter, Randomized, Single-Blind Study. - Hong, Yun Jeong; Choi, Seong Hye; Jeong, Jee Hyang; Park, Kyung Won; Na, Hae Ri (J Alzheimers Dis, 2018)
BACKGROUND/OBJECTIVE: There is insufficient evidence to guide decisions concerning how long anti-dementia drug (ADD) regimens should be maintained in severe Alzheimer's disease (AD). We investigated whether patients with extremely severe AD who were already receiving donepezil or memantine benefited from continuing treatment. METHODS: In this randomized and rater-blinded trial, 65 AD patients with a Mini-Mental State Examination score from 0 to 5 and a score of 6c or worse on Functional Assessment Staging were randomly assigned to an ADD-continuation group (N = 30) or an ADD-discontinuation group (N = 35). The current use of donepezil or memantine was maintained for 12 weeks in the ADD-continuation group and was discontinued after baseline in the ADD-discontinuation group. Efficacy measures were obtained at baseline and 12 weeks. The primary efficacy variable was the change from baseline to the end of the study in Baylor Profound Mental State Examination (BPMSE) scores. RESULTS: The change in the BPMSE from baseline to the end of the study in the ADD-continuation group (a 0.4-point improvement) was not equivalent to that in the ADD-discontinuation group (a 0.5-point decline), as determined by two one-sided tests of equivalence. Study withdrawals due to adverse events (11.4% versus 6.7%) were more frequent in the ADD-discontinuation group than in the ADD-continuation group. CONCLUSION: Continued treatment with donepezil or memantine seems unequal and might be superior to withdrawal of the drugs in terms of the effects on global cognition in patients with extremely severe AD. Current Controlled Trials number: KCT0000874 (CRIS).

Establishing a New Screening System for Mild Cognitive Impairment and Alzheimer's Disease with Mental Rotation Tasks that Evaluate Visuospatial Function. - Suzuki, Ayuko; Shinozaki, Jun; Yazawa, Shogo; Ueki, Yoshino; Matsukawa, Noriyuki; Shimohama, Shun; Nagamine, Takashi (J Alzheimers Dis, 2018)
BACKGROUND: The mental rotation task is well-known for the assessment of visuospatial function; however, it has not been used for screening of dementia patients. OBJECTIVE: The aim of this study was to create a simple screening test for patients with mild cognitive impairment (MCI) and Alzheimer's disease (AD) by focusing on non-amnestic symptoms. METHODS: Age-matched healthy controls (age 75.3±6.8), patients with MCI (76.5±5.5), and AD (78.2±5.0) participated in this study. They carried out mental rotation tasks targeting geometric graphics or alphabetical characters with three rotating angles (0°, 90°, and 180°) and indicated the correct answer. Response accuracy and reaction time were recorded along with their eye movements using an eye tracker. To quantify their visual processing strategy, the run count ratio (RC ratio) was calculated by dividing the mean number of fixations in incorrect answers by that in correct answers. RESULTS: AD patients showed lower accuracy and longer reaction time than controls. They also showed a significantly greater number of fixation and smaller saccade amplitude than controls, while fixation duration did not differ significantly. The RC ratio was higher for AD, followed by MCI and control groups. By setting the cut-off value to 0.47 in the 180° rotating angle task, we could differentiate MCI patients from controls with a probability of 80.0%. CONCLUSIONS: We established a new screening system for dementia patients by evaluating visuospatial function. The RC ratio during a mental rotation task is useful for discriminating MCI patients from controls.
Keywords: Aged; Aged, 80 and over; Agnosia; Alzheimer Disease; Case-Control Studies; Cognition; Cognitive Dysfunction; Disease Progression; Early Diagnosis; Eye Movements; Female; Humans; Male; Mental Status Schedule; Reaction Time; ROC Curve

Evaluating Peripersonal Space through the Functional Transcranial Doppler: Are We Paving the Way for Early Detecting Mild Cognitive Impairment to Dementia Conversion? - Marra, Angela; Naro, Antonino; Chillura, Antonino; Bramanti, Alessia; Maresca, Giuseppa; De Luca, Rosaria; Manuli, Alfredo; Bramanti, Placido; Calabrò, Rocco Salvatore (J Alzheimers Dis, 2018)
BACKGROUND: Identifying the patients with mild cognitive impairment (MCI) who may develop dementia (MDC) is challenging. The study of peripersonal space (PPS) by using functional transcranial Doppler (fTCD) could be used for this purpose. OBJECTIVE: To identify changes in cerebral blood flow (CBF) during motor tasks targeting PPS, which can predict MDC. METHODS: We evaluated the changes in CBF in 22 patients with MCI and 23 with dementia [Alzheimer's disease (AD) and vascular dementia (VaD)] during a motor task (passive mobilization, motor imagery, and movement observation) in which the hand of the subject moved forward and backward the face. RESULTS: CBF increased when the hand approached the face and decreased when the hand moved from the face in the healthy controls (HCs). CBF changed were detectable only in patients with MCI but not in those with the AD and those who were MDC after 8-month follow-up. On the other hand, the patients with VaD presented a paradoxical response to the motor task (i.e., a decrease of CBF rather than an increase, as observed in HCs and MCI). Therefore, we found a modulation of PPS-related CBF only in HCs and patients with stable MCI (at the 8-month follow-up). CONCLUSIONS: fTCD may allow preliminarily differentiating and following-up the patients with MCI and MDC, thus allowing the physician to plan beforehand more individualized cognitive rehabilitative training.

Frequency and Correlates of Subjective Memory Complaints in Parkinson's Disease with and without Mild Cognitive Impairment: Data from the Parkinson's Disease Cognitive Impairment Study. - Baschi, Roberta; Nicoletti, Alessandra; Restivo, Vincenzo; Recca, Deborah; Zappia, Mario; Monastero, Roberto (J Alzheimers Dis, 2018)
Subjective memory complaints (SMC) may represent the preclinical phase of mild cognitive impairment (MCI) due to Alzheimer's disease. Dementia/MCI have been described with a high prevalence in Parkinson's disease (PD), but whether SMC may predict the development of cognitive impairment has been barely explored. To evaluate the frequency and clinical correlates of isolated SMC (PD-SMC) or within the construct of MCI in subjects with PD, 147 PD patients from the PArkinson's disease COgnitive impairment Study (PACOS) were consecutively recruited for the study. This is a multicenter study involving two Movement Disorder Centers in south Italy. All subjects underwent comprehensive neuropsychological evaluation and PD-MCI was diagnosed according to Litvan's criteria. The Memory Assessment Clinics Questionnaire was used to assess SMC. Logistic regression analysis, adjusted for demographics and significant covariates, was used to evaluate clinical differences between groups. Forty-two (28.6%) individuals presented with PD without SMC and/or MCI (PDw), 40 (27,2%) with PD-SMC, 48 (32,6%) PD-SMC-MCI, and 17 (11,6%) PD-MCI without SMC (PD-MCI). When compared to PDw, PD-SMC was significantly associated with anxiety (OR = 3.93, 95% CI = 1.18-13.03), while PD-SMC-MCI related to motor progression (OR = 5.29, 95% CI = 1.12-24.86), and instrumental disability (OR = 6.98, 95% CI = 2.08-23.38). About 60% of patients showed SMC, in isolation or within the MCI frame. The role of SMC in PD seems to have a different etiology depending on the presence/absence of MCI. In particular, PD-SMC would represent a subjective reaction to the disease, while PD-SMC-MCI would depict motor progression and disability.

From Subjective Cognitive Decline to Alzheimer's Disease: The Predictive Role of Neuropsychological Assessment, Personality Traits, and Cognitive Reserve. A 7-Year Follow-Up Study. - Bessi, Valentina; Mazzeo, Salvatore; Padiglioni, Sonia; Piccini, Carolina; Nacmias, Benedetta; Sorbi, Sandro; Bracco, Laura (J Alzheimers Dis, 2018)
The aim of this study was to evaluate the accuracy of neuropsychological assessment in predicting conversion from subjective cognitive decline (SCD) and mild cognitive impairment (MCI) to Alzheimer's disease (AD) and the effect of personality traits and cognitive reserve in progression from SCD to MCI. As part of a longitudinal, clinical-neuropsychological-genetic survey on SCD and MCI, 284 patients referred to our hospital between 1990 and 2017 were included. All patients underwent clinical-extensive neuropsychological evaluation and Apolipoprotein E genotyping; personality traits were assessed in a subgroup. Each patient underwent clinical-neuropsychological follow-up. Subjects with a follow-up shorter than two years were excluded. A total of 212 subjects were, after exclusions, considered: 26 out of 109 SCD subjects progressed to MCI (SCD-p), 15 converted to AD (SCD-c), and 68 remained stable (SCD-s). Of 103 MCI subjects, 39 converted to AD (MCI-c) and 64 remained stable (MCI-s). At baseline, SCD-c performed significantly worse than SCD-s in tests assessing long-term verbal memory. MCI-c showed worse performance on neuropsychological tests for short- and long-term verbal memory and for ecological evaluation of memory (RBMT). These tests provided good accuracy in distinguishing MCI-c and MCI-s. Emotional stability was significantly lower in SCD-s than in SCD-p while higher intellectual activities were associated with a lower risk of conversion to MCI. Our results suggest that memory neuropsychological tests may represent a reliable tool to estimate the risk of progression to AD. Personality and lifestyle factors could provide useful information to identify SCD subjects who may develop an objective cognitive impairment.

Frontal Cortex Epigenetic Dysregulation During the Progression of Alzheimer's Disease. - Mahady, Laura; Nadeem, Muhammad; Malek-Ahmadi, Michael; Chen, Kewei; Perez, Sylvia E; Mufson, Elliott J (J Alzheimers Dis, 2018)
Although the frontal cortex plays an important role in cognitive function and undergoes neuronal dysfunction in Alzheimer's disease (AD), the factors driving these cellular alterations remain unknown. Recent studies suggest that alterations in epigenetic regulation play a pivotal role in this process in AD. We evaluated frontal cortex histone deacetylase (HDAC) and sirtuin (SIRT) levels in tissue obtained from subjects with a premortem diagnosis of no-cognitive impairment (NCI), mild cognitive impairment (MCI), mild to moderate AD (mAD), and severe AD (sAD) using quantitative western blotting. Immunoblots revealed significant increases in HDAC1 and HDAC3 in MCI and mAD, followed by a decrease in sAD compared to NCI. HDAC2 levels remained stable across clinical groups. HDAC4 was significantly increased in MCI and mAD, but not in sAD compared to NCI. HDAC6 significantly increased during disease progression, while SIRT1 decreased in MCI, mAD, and sAD compared to NCI. HDAC1 levels negatively correlated with perceptual speed, while SIRT1 positively correlated with perceptual speed, episodic memory, global cognitive score, and Mini-Mental State Examination. HDAC1 positively, while SIRT1 negatively correlated with cortical neurofibrillary tangle counts. These findings suggest that dysregulation of epigenetic proteins contribute to neuronal dysfunction and cognitive decline in the early stage of AD.

Genetic Heterogeneity of Alzheimer's Disease: Embracing Research Partnerships. - Nacmias, Benedetta; Bagnoli, Silvia; Piaceri, Irene; Sorbi, Sandro (J Alzheimers Dis, 2018)
Studies on the genetics of Alzheimer's disease (AD) have revealed the complexity and heterogeneity of the disease. All our studies have supported this evidence and contribute to the current understanding of the genetic architecture of AD. This report reviews the success of our investigations, focusing on the implications and importance of the genetics of AD, and demonstrates the relevance of research strategies embracing partnerships.

The GWAS Risk Genes for Depression May Be Actively Involved in Alzheimer's Disease. - Ni, Hua; Xu, Min; Zhan, Gui-Lai; Fan, Yu; Zhou, Hejiang; Jiang, Hong-Yan; Lu, Wei-Hong; Tan, Liwen; Zhang, Deng-Feng; Yao, Yong-Gang; Zhang, Chen (J Alzheimers Dis, 2018)
Depression is one of the most frequent psychiatric symptoms observed in people during the development of Alzheimer's disease (AD). We hypothesized that genetic factors conferring risk of depression might affect AD development. In this study, we screened 31 genes, which were located in 19 risk loci for major depressive disorder (MDD) identified by two recent large genome-wide association studies (GWAS), in AD patients at the genomic and transcriptomic levels. Association analysis of common variants was performed by using summary statistics of the International Genomics of Alzheimer's Project (IGAP), and association analysis of rare variants was conducted by sequencing the entire coding region of the 31 MDD risk genes in 107 Han Chinese patients with early-onset and/or familial AD. We also quantified the mRNA expression alterations of these MDD risk genes in brain tissues of AD patients and AD mouse models, followed by protein-protein interaction network prediction to show their potential effects in AD pathways. We found that common and rare variants of L3MBTL2 were significantly associated with AD. mRNA expression levels of 18 MDD risk genes, in particular SORCS3 and OAT, were differentially expressed in AD brain tissues. 13 MDD risk genes were predicted to physically interact with core AD genes. The involvement of HACE1, NEGR1, and SLC6A15 in AD was supported by convergent lines of evidence. Taken together, our results showed that MDD risk genes might play an active role in AD pathology and supported the notion that depression might be the "common cold" of psychiatry.

High Caregiver Burden in Young Onset Dementia: What Factors Need Attention? - Lim, Linda; Zhang, Angeline; Lim, Levinia; Choong, Tanya-Marie; Silva, Eveline; Ng, Adeline; Kandiah, Nagaendran (J Alzheimers Dis, 2018)
BACKGROUND: There is an increase in prevalence of young onset dementia (YOD). The specific problems among YOD patients and levels of caregiver burden (CB) in this group warrants further evaluation. OBJECTIVE: To evaluate and compare level of CB in YOD and late onset dementia (LOD). Also, we sought to understand the specific factors, such as neuropsychiatric symptoms, that may affect the levels of caregiver burden in the YOD group. METHODS: Patient-caregiver dyads with YOD and LOD were recruited from a tertiary neurology center. Levels of CB between YOD and LOD were compared among 183 patient-caregiver dyads. CB was quantified using the Zarit Burden Inventory (ZBI). Neuropsychological evaluations as well as the Neuropsychiatric Inventory were performed. Factors that influenced level of CB in YOD group was investigated with regression analyses. RESULTS: There were 57 YOD and 126 LOD dyads. Caregivers of YOD subjects reported significantly higher levels of burden compared to caregivers of LOD subjects (ZBI: 17.3 versus 13.94; p = 0.015). 52.6% of YOD caregivers reported a high caregiver burden. When compared to caregivers of LOD, the odds of a caregiver of YOD reporting high caregiver burden was 2.34 (95% CI: 1.22-4.49: p = 0.010). YOD dyads with a high caregiver burden had significantly higher neuropsychiatric inventory scores. Risk factors for high caregiver burden in YOD included family history of dementia and behavioral symptoms including disinhibited behavior, delusions, and apathy. CONCLUSION: Targeted support for caregivers of patients with YOD is needed to address the higher CB in this group.
Keywords: Adaptation, Psychological; Age of Onset; Aged; Aged, 80 and over; Behavioral Symptoms; Caregivers; Cost of Illness; Cross-Sectional Studies; Dementia; Female; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Stress, Psychological; Surveys and Questionnaires

High-Density Lipoprotein Subclasses and Mild Cognitive Impairment: Study of Outcome and aPolipoproteins in Dementia (STOP-Dementia)1. - Ohtani, Ryo; Nirengi, Shinsuke; Nakamura, Michikazu; Murase, Nagako; Sainouchi, Makoto; Kuwata, Yasuhiro; Takata, Masaki; Masuda, Yuuichi; Kotani, Kazuhiko; Sakane, Naoki (J Alzheimers Dis, 2018)
BACKGROUND: High-density lipoprotein (HDL) containing apolipoprotein A-I is associated with the pathogenesis of Alzheimer's disease (AD). HDL particle size is modified in the presence of pathological conditions, while the significance of the HDL particle size remains controversial. OBJECTIVE: The aim of this study was to investigate the HDL lipoprotein subclasses in mild cognitive impairment (MCI) and AD. METHODS: This cross-sectional study included 20 AD patients, 17 MCI patients, and 17 age-matched controls without cognitive impairment, selected from the database of the Study of Outcome and aPolipoproteins in Dementia (STOP-Dementia) registry. The diagnoses of AD and MCI were performed by expert neurologists according to the Diagnostic and Statistical Manual of Mental Disorders-Fifth Edition criteria. Serum HDL subclasses were measured by electrophoretic separation of lipoproteins using the Lipoprint System. The neutrophil-lymphocyte ratio (NLR), a marker of inflammation, was calculated by dividing the neutrophil count by the lymphocyte count. RESULTS: Small-sized HDL particle levels in the MCI group were significantly higher than in the control group, although there was no difference in serum HDL-cholesterol levels between MCI and control groups. NLR in the MCI group was higher than in the control group, but this difference was non-significant (p = 0.09). There was no difference in HDL subclasses or NLR between the AD and control groups. CONCLUSION: These findings suggest that HDL subclasses might be associated with the development of MCI.

Higher Blood Vitamin C Levels are Associated with Reduction of Apolipoprotein E E4-related Risks of Cognitive Decline in Women: The Nakajima Study. - Noguchi-Shinohara, Moeko; Abe, Chiemi; Yuki-Nozaki, Sohshi; Dohmoto, Chiaki; Mori, Ayaka; Hayashi, Koji; Shibata, Syutaro; Ikeda, Yoshihisa; Sakai, Kenji; Iwasa, Kazuo; Yokogawa, Masami; Ishimiya, Mai; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Antioxidants like vitamins C and E may minimize the risk for Alzheimer's disease. OBJECTIVE: We examined whether vitamins C and E modify the apolipoprotein E (APOE) E4-related risks for developing cognitive decline. METHODS: We conducted a population-based prospective study including Japanese residents aged 65 years from Nakajima, Japan. The participants received an evaluation of cognitive function and underwent blood tests including tests for vitamins C and E levels and APOE phenotypes. The APOE E4-by-gender-by-vitamin C or E interactions on developing cognitive decline were analyzed. RESULTS: Of 606 participants with normal cognitive function determined using a baseline survey (2007-2008), 349 completed the follow up survey between 2014 and 2016. In women with APOE E4, significantly reduced risk for cognitive decline was observed for the highest blood vitamin C concentration tertile [multivariate OR 0.10 (95% CI 0.01-0.93)] compared with the lowest tertile. In men without APOE E4, significantly reduced risk for cognitive decline was observed for the highest blood vitamin E concentration tertile [multivariate OR 0.19 (0.05-0.74)] as compared with the lowest tertile. CONCLUSION: Our results demonstrate significant beneficial effects of vitamins C and E in reducing the risk of cognitive decline in women with APOE E4 and men without APOE E4, respectively.

HSV-1-Specific IgG Subclasses Distribution and Serum Neutralizing Activity in Alzheimer's Disease and in Mild Cognitive Impairment. - Agostini, Simone; Mancuso, Roberta; Hernis, Ambra; Costa, Andrea Saul; Nemni, Raffaello; Clerici, Mario (J Alzheimers Dis, 2018)
Human Herpes Simplex Virus type 1 (HSV-1) infection is suggested to play a role in the development of Alzheimer's disease (AD). Immunoglobulin G (IgG) neutralize HSV-1 activity, but the virus can evade IgG-mediated immune responses by expressing receptor that efficiently binds the Fc portion of all IgG subclasses with the exception of IgG3. We analyzed HSV-1-specific IgG subclasses and IgG-mediated serum neutralization activity against HSV-1 in individuals with a diagnosis of either AD or mild cognitive impairment (MCI), comparing the results with those obtained in age-matched healthy controls (HC). 186 individuals were enrolled in the study: 67 AD, 58 MCI, and 61 HC. HSV-1 IgG titers and subclasses, neutralizing antibody (NAb) titers, and complement C3 concentration-critical component of antibody-mediated effector activity-were measured in sera by ELISA; IgG neutralizing activity was performed on HSV-1 infected Vero cells. Results showed that, whereas HSV-1-specific IgG1, IgG2, and IgG4 titers as well as complement C3 serum concentration were comparable in all groups of individuals, IgG3 were more frequently detected in MCI (89%) compared to AD (75%; p < 0.05) and HC (68%; p = 0.003), whereas the titer is similar among the three groups (AD: 0.66±0.21 OD; MCI: 0.68±0.24 OD; HC: 0.72±0.28 OD). Notably, HSV-1 specific neutralizing ability of AD sera was reduced even in the presence of high quantity of IgG3. As IgG3 plays a key role in counteracting the ability of HSV-1 to evade immune responses, these data reinforce the hypothesis of a pathogenetic role of HSV-1 in AD.

The Impact of APOE ɛ4 in Alzheimer's Disease Differs According to Age. - Kim, Jaeho; Park, Seongbeom; Yoo, Heejin; Jang, Hyemin; Kim, Yeshin; Kim, Ko Woon; Jang, Young Kyoung; Lee, Jin San; Kim, Sung Tae; Kim, Seonwoo; Lee, Jong Min; Ki, Chang-Seok; et al. (J Alzheimers Dis, 2018)
We evaluated how the impact of apolipoprotein E4 (APOE4) differs according to age in Alzheimer's disease (AD) patients. We recruited 846 AD patients and 815 cognitively normal controls and categorized into three groups with respect to their age (<65, 65-74, and ≥75 years). We evaluated the risk of AD in APOE4 carriers and compared cortical thickness and cognitive function according to APOE4 status in each age group. At the point of this study, in young (<65 years) AD, APOE4 noncarriers had the most severe frontal and perisylvian atrophy, while in old (≥75 years) AD, APOE4 carriers had the most severe medial temporal atrophy. In AD under 75 years, APOE4 noncarriers and heterozygotes showed worse performance in language, visuospatial, and frontal function compared to homozygotes, while, in old (≥75 years) AD, APOE4 homozygotes showed worse performance in memory compared to noncarriers. As the detrimental effects of APOE4 seen in older AD patients were not found in younger AD patients, we suggest that some unrevealed factors are associated with cortical atrophy and non-amnestic cognitive dysfunction in young AD with APOE4 noncarriers.
Keywords: Age Factors; Aged; Alzheimer Disease; Apolipoprotein E4; Atrophy; Brain; Case-Control Studies; Cognition; Female; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Memory; Middle Aged; Republic of Korea

Implementation of an Occupational Therapy Program for Alzheimer's Disease Patients in France: Patients' and Caregivers' Perspectives. - Corvol, Aline; Netter, Alix; Campeon, Arnaud; Somme, Dominique (J Alzheimers Dis, 2018)
BACKGROUND: The French National Alzheimer Plan 2008-2012 created specialized Alzheimer teams, which provide up to 15 sessions of cognitive rehabilitation in the patient's home for 3 months. Sessions are conducted by an occupational therapist and a gerontological nursing assistant. OBJECTIVES: As the patient's experience is one determinant of successful implementation, we explored the usefulness of these teams as viewed by the patient and his or her main caregiver. METHODS: Thirteen patients and their caregiver, previously assisted by a specialized Alzheimer team, were individually given semi-structured interviews (n = 26, duration 20 to 180 minutes). RESULTS: Our study showed that although patients and caregiver had no initial expectations, most of them appreciated the support provided by the specialized Alzheimer teams. Patients valued the "human" component, and favored interventions that improved quality of life over those intended to maintain functional capacities. Caregivers observed improved mood and behavior in patients. Those involved in sessions felt empowered by contact with a specialized Alzheimer team. We discuss how patients' and caregivers' feedback influenced the implementation process through comprehensive use of the five dimensions of the RE-AIM framework. CONCLUSION: Whereas intervention by specialized Alzheimer teams was largely accepted by health care professionals, patients, and caregivers, its effectiveness is questioned in view of its deviation from the evidence-based model. Interviews with patients and caregivers shed light on some reasons for this deviation, as what they value in the intervention differs from the functional focus of the model.

In Vitro Potency and Preclinical Pharmacokinetic Comparison of All-D-Enantiomeric Peptides Developed for the Treatment of Alzheimer's Disease. - Schartmann, Elena; Schemmert, Sarah; Niemietz, Nicole; Honold, Dominik; Ziehm, Tamar; Tusche, Markus; Elfgen, Anne; Gering, Ian; Brener, Oleksandr; Shah, Nadim Joni; Langen, Karl-Josef; Kutzsche, Janine; et al. (J Alzheimers Dis, 2018)
Diffusible amyloid-β (Aβ) oligomers are currently presumed to be the most cytotoxic Aβ assembly and held responsible to trigger the pathogenesis of Alzheimer's disease (AD). Thus, Aβ oligomers are a prominent target in AD drug development. Previously, we reported on our solely D-enantiomeric peptide D3 and its derivatives as AD drug candidates. Here, we compare one of the most promising D3 derivatives, ANK6, with its tandem version (tANK6), and its head-to-tail cyclized isoform (cANK6r). In vitro tests investigating the D-peptides' potencies to inhibit Aβ aggregation, eliminate Aβ oligomers, and reduce Aβ-induced cytotoxicity revealed that all three D-peptides efficiently target Aβ. Subsequent preclinical pharmacokinetic studies of the three all-D-peptides in wildtype mice showed promising blood-brain barrier permeability with cANK6r yielding the highest levels in brain. The peptides' potencies to lower Aβ toxicity and their remarkable brain/plasma ratios make them promising AD drug candidates.

In vivo Depiction of α7 Nicotinic Receptor Loss for Cognitive Decline in Alzheimer's Disease. - Nakaizumi, Kyoko; Ouchi, Yasuomi; Terada, Tatsuhiro; Yoshikawa, Etsuji; Kakimoto, Akihiro; Isobe, Takashi; Bunai, Tomoyasu; Yokokura, Masamichi; Suzuki, Katsuaki; Magata, Yasuhiro (J Alzheimers Dis, 2018)
BACKGROUND: The α7 subtype of the nicotinic acetylcholine receptor (nAChR) is considered important in higher cognitive functions, and cholinergic loss underpins the pathophysiology of Alzheimer's disease (AD). However, the relationships between α7 nAChR function and clinical functions or amyloid-β (Aβ) deposition remain to be explored in the living AD brain. OBJECTIVE: We aimed to elucidate the relationship between α7 nAChR availability in the specific cholinergic region and cognitive decline in the Aβ-confirmed AD brain. METHODS: Twenty AD patients and ten age-matched healthy subjects were examined. The α7-nAChR availability and Aβ deposition were evaluated using positron emission tomography with an α7 nAChR radiotracer 11C-(R)-MeQAA and 11C-Pittsburg compound B (11C-PiB), respectively. Semi-quantified values of tracer binding were estimated with a simplified reference tissue method for BPND of 11C-(R)-MeQAA and a tissue ratio method for SUVR of 11C-PiB. These parameters and clinical scores were compared voxel-wise using a statistical parametric mapping method. RESULTS: The levels of 11C-(R)-MeQAA BPND in the temporal and prefrontal cholinergic projection regions were significantly lower in AD, and negative correlations were found between 11C-PiB SUVR and 11C-(R)-MeQAA BPND in the region of the nucleus basalis magnocellularis and medial prefrontal cortex. Levels of 11C-(R)-MeQAA BPND were significantly correlated with memory and frontal function scores in AD. CONCLUSION: The association between Aβ burden and α7-nAChR reduction in the basal forebrain cholinergic system was highlighted in relation to cognitive decline in AD. This suggests that Aβ-linked α7-nAChR reduction is clinico-pathophyisologically important for considering a good therapeutic target in AD.
Keywords: Adult; Aged; alpha7 Nicotinic Acetylcholine Receptor; Alzheimer Disease; Brain; Case-Control Studies; Cognitive Dysfunction; Female; Humans; Male; Middle Aged; Positron-Emission Tomography; Young Adult

In Vivo Visualization of Tau Accumulation, Microglial Activation, and Brain Atrophy in a Mouse Model of Tauopathy rTg4510. - Ishikawa, Ai; Tokunaga, Masaki; Maeda, Jun; Minamihisamatsu, Takeharu; Shimojo, Masafumi; Takuwa, Hiroyuki; Ono, Maiko; Ni, Ruiqing; Hirano, Shigeki; Kuwabara, Satoshi; Ji, Bin; Zhang, Ming-Rong; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Tau imaging using PET is a promising tool for the diagnosis and evaluation of tau-related neurodegenerative disorders, but the relationship among PET-detectable tau, neuroinflammation, and neurodegeneration is not yet fully understood. OBJECTIVE: We aimed to elucidate sequential changes in tau accumulation, neuroinflammation, and brain atrophy by PET and MRI in a tauopathy mouse model. METHODS: rTg4510 transgenic (tg) mice expressing P301L mutated tau and non-tg mice were examined with brain MRI and PET imaging (analyzed numbers: tg = 17, non-tg = 13; age 2.5∼14 months). As PET probes, [11C]PBB3 (Pyridinyl-Butadienyl-Benzothiazole 3) and [11C]AC-5216 were used to visualize tau pathology and 18-kDa translocator protein (TSPO) neuroinflammation. Tau pathology and microglia activation were subsequently analyzed by histochemistry. RESULTS: PET studies revealed age-dependent increases in [11C]PBB3 and [11C]AC-5216 signals, which were correlated with age-dependent volume reduction in the forebrain on MRI. However, the increase in [11C]PBB3 signals reached a plateau at age 7 months, and therefore its significant correlation with [11C]AC-5216 disappeared after age 7 months. In contrast, [11C]AC-5216 showed a strong correlation with both age and volume reduction until age 14 months. Histochemical analyses confirmed the relevance of pathological tau accumulation and elevated TSPO immunoreactivity in putative microglia. CONCLUSION: Our results showed that tau accumulation is associated with neuroinflammation and brain atrophy in a tauopathy mouse model. The time-course of the [11C]PBB3- and TSPO-PET finding suggests that tau deposition triggers progressive neuroinflammation, and the sequential changes can be evaluated in vivo in mouse brains.
Keywords: Animals; Atrophy; Benzothiazoles; Brain; Disease Models, Animal; Female; Magnetic Resonance Imaging; Male; Mice; Mice, Transgenic; Microglia; Positron-Emission Tomography; Receptors, GABA; tau Proteins; Tauopathies

The In-Hospital Length of Stay after Hip Fracture in Octogenarians: Do Delirium and Dementia Shape a New Care Process? - Monacelli, Fiammetta; Pizzonia, Monica; Signori, Alessio; Nencioni, Alessio; Giannotti, Chiara; Minaglia, Cecilia; Granello di Casaleto, Tommaso; Podestà, Silvia; Santolini, Federico; Odetti, Patrizio (J Alzheimers Dis, 2018)
BACKGROUND: Hip fracture is a major health problem and a patient's biological age, comorbidity, and cognitive vulnerability have an impact on its related outcomes. Length of stay (LOS) for these highly vulnerable patients is rather long and the possible causes have not been clearly identified yet. OBJECTIVE: We aimed to assess the main clinical factors associated with protracted LOS, focusing on delirium with or without dementia in older age hip fractured patients. METHODS: 218 subjects (mean age 86.70±6.18 years), admitted to the Orthogeriatric Unit of the Ospedale Policlinico San Martino (Italy), were recruited. All patients received physical and comprehensive geriatric assessment. Days to surgery, days from surgery to rehabilitation, and LOS were recorded. In-hospital and three months' mortality were reported. RESULTS: Prevalent delirium at hospital admission was of 3.1%. 35% of patients developed incident delirium. 56.4% were affected by dementia of Alzheimer-type. In addition, 52% of patients developed delirium superimposed to dementia. Mean LOS was 13.5±4.99 days. Namely, delirium, time to surgery, and complication rate disproportionally affected LOS. The analysis with 3 months mortality, based on cognitive vulnerability profiles, showed how delirium mainly affect short-term mortality in patients with dementia. CONCLUSION: Our exploratory study originally pointed out the high incidence of delirium superimposed to dementia in orthogeriatric wards and how delirium turns to be a moderator of LOS. The results meet the need for additional research by virtue of a deeper understanding of the impact of delirium and dementia on orthogeriatric clinical management and outcomes.

Integrating Sleep and Alzheimer's Disease Pathophysiology: Hints for Sleep Disorders Management. - Proserpio, Paola; Arnaldi, Dario; Nobili, Flavio; Nobili, Lino (J Alzheimers Dis, 2018)
Sleep represents an active phenomenon regulated by a highly integrated network of cortical and subcortical structures. This complex model results in disruptions at various levels during physiological aging and more deeply during neurodegenerative disorders, thus leading to different sleep alterations. In Alzheimer's disease (AD), sleep-wake abnormalities were described to occur even in the preclinical phase, thus suggesting they could be a possible AD biomarker. On the other hand, they also favor the progression of the disease. In this paper, we review current theories regarding sleep regulations and functions to highlight the pathophysiological mechanisms at the basis of the bidirectional relationship between sleep and AD. A better understanding of these complex interactions might also be useful to target both sleep disorder management and AD-related symptoms.

Interactive Effect of Depression and Cognitive Impairment on Olfactory Identification in Elderly People. - Chen, Ben; Zhong, Xiaomei; Mai, Naikeng; Peng, Qi; Zhang, Min; Chen, Xinru; Wu, Zhangying; Zou, Laiquan; Liang, Wanyuan; Ouyang, Cong; Wu, Yujie; Ning, Yuping (J Alzheimers Dis, 2018)
Olfactory identification (OI) deficits have been regarded as an indicator of cognitive impairment in the elderly, but few studies have analyzed the mixed effect of depression on OI. Since depression is common in the elderly and strongly associated with OI, we aimed to explore whether the comorbidity of depression and cognitive impairment may be associated with worse outcomes. In total, 153 elderly patients with depression and 154 normal elderly were recruited. Subjects underwent assessments of depression, cognitive function, and OI. Information on the factors that may affect OI performance was collected (age, sex, smoking history, diabetes, etc.). Correlation analysis showed that several factors had a significant influence on OI performance in the elderly, including severity of depression, cognitive scores, age, sex, and years of education (p < 0.05). Among the different cognitive domains, OI was positively associated with global cognition, memory, language, executive function, and attention performance (p < 0.05). The multiple linear regression analysis indicated that memory scores, age, HAMD scores, and sex were the most relevant factors to OI scores across all elderly participants. The factorial analysis suggested that elderly with comorbidity of depression and cognitive impairment (memory deficits or language deficits) had worse OI impairment, and there was an interactive effect of depression and memory deficits on OI in elderly people. The present study suggested that the coexistence of depressive symptoms and cognitive impairment was associated with worse OI in the elderly. Studies exploring the association between OI and cognitive function should include an assessment of depression and adjust the interactive effects of depression.

Ketogenic Medium Chain Triglycerides Increase Brain Energy Metabolism in Alzheimer's Disease. - Croteau, Etienne; Castellano, Christian-Alexandre; Richard, Marie Anne; Fortier, Mélanie; Nugent, Scott; Lepage, Martin; Duchesne, Simon; Whittingstall, Kevin; Turcotte, Éric E; Bocti, Christian; Fülöp, Tamás; Cunnane, Stephen C (J Alzheimers Dis, 2018)
BACKGROUND: In Alzheimer's disease (AD), it is unknown whether the brain can utilize additional ketones as fuel when they are derived from a medium chain triglyceride (MCT) supplement. OBJECTIVE: To assess whether brain ketone uptake in AD increases in response to MCT as it would in young healthy adults. METHODS: Mild-moderate AD patients sequentially consumed 30 g/d of two different MCT supplements, both for one month: a mixture of caprylic (55%) and capric acids (35%) (n = 11), followed by a wash-out and then tricaprylin (95%; n = 6). Brain ketone (11C-acetoacetate) and glucose (FDG) uptake were quantified by PET before and after each MCT intervention. RESULTS: Brain ketone consumption doubled on both types of MCT supplement. The slope of the relationship between plasma ketones and brain ketone uptake was the same as in healthy young adults. Both types of MCT increased total brain energy metabolism by increasing ketone supply without affecting brain glucose utilization. CONCLUSION: Ketones from MCT compensate for the brain glucose deficit in AD in direct proportion to the level of plasma ketones achieved.

Lifetime Risk Factors for Functional and Cognitive Outcomes in Patients with Alzheimer's Disease. - de Oliveira, Fabricio Ferreira; de Almeida, Sandro Soares; Chen, Elizabeth Suchi; Smith, Marilia Cardoso; Naffah-Mazzacoratti, Maria da Graça; Bertolucci, Paulo Henrique Ferreira (J Alzheimers Dis, 2018)
Lifetime risk factors for cognitive and functional decline in Alzheimer's disease (AD) are not fully understood, and were prospectively evaluated in patients with low mean schooling from São Paulo, Brazil. Consecutive outpatients with late-onset AD were assessed for APOE haplotypes and the following potential baseline predictors: gender, schooling, age at dementia onset, lifetime urban living and sanitary conditions, occupational complexity, cognitive and physical activities, cerebrovascular risk factors (obesity, lifetime alcohol use and smoking, length of arterial hypertension, diabetes mellitus, and a dyslipidemic profile), use of a pacemaker, creatinine clearance, body mass index, waist circumference, head traumas with unconsciousness, treated systemic bacterial infections, amount of surgical procedures under general anesthesia, and family history of AD. Participants were followed from October 2010 to May 2017 for baseline risk factor associations with time since dementia onset for Clinical Dementia Rating and Mini-Mental State Examination score changes. For 227 patients (154 women, 119 APOE ε 4 carriers), later AD onset (mean 73.60±6.4 years-old, earlier for APOE ε 4/ε 4 carriers, p < 0.001) was the only variable hastening all endpoints, baseline creatinine clearance and lifetime alcohol use were hazardous for earlier cognitive and functional endpoints, women had earlier cognitive endpoints only, and schooling had a cumulative protective effect over later cognitive endpoints, particularly for carriers of APOE ε 4. Exclusively for carriers of APOE ε 4, head traumas with unconsciousness were hazardous for earlier cognitive endpoints, while lifetime sanitary conditions were protective regarding later cognitive endpoints. Functional and cognitive outcomes in AD represent probable interactions between effects of brain reserve and cerebral perfusion over neurodegeneration.

Longitudinal Modeling of Functional Decline Associated with Pathologic Alzheimer's Disease in Older Persons without Cognitive Impairment. - Wang, Dai; Schultz, Tim; Novak, Gerald P; Baker, Susan; Bennett, David A; Narayan, Vaibhav A (J Alzheimers Dis, 2018)
BACKGROUND: Therapeutic research on Alzheimer's disease (AD) has moved to intercepting the disease at the preclinical phase. Most drugs in late development have focused on the amyloid hypothesis. OBJECTIVE: To understand the magnitude of amyloid-related functional decline and to identify the functional domains sensitive to decline in a preclinical AD population. METHODS: Data were from the Religious Orders Study and the Rush Memory and Aging Project. Cognitive decline was measured by a modified version of the Alzheimer's Disease Cooperative Study Preclinical Alzheimer Cognitive Composite. The trajectories of functional decline, as measured by the instrumental and basic activities of daily living, were longitudinally modeled in 484 participants without cognitive impairment at baseline and having both a final clinical and a postmortem neuropathology assessment of AD. RESULTS: Individuals with different final clinical diagnoses had different trajectories of cognitive and functional decline. Individuals with AD dementia, minor cognitive impairment, and no cognitive impairment had the most, intermediate, and least declines. While individuals with pathologic AD had significantly more cognitive decline over time than those without, the magnitude of difference in functional decline between these two groups was small. Functional domains such as handling finance and handling medications were more sensitive to decline. CONCLUSION: Demonstrating the functional benefit of an amyloid-targeting drug represents a significant challenge as elderly people experience functional decline due to a wide range of reasons with limited manifestation attributable to AD neuropathology. More sensitive functional scales focusing on the functional domains sensitive to decline in preclinical AD are needed.

Longitudinal Neuroimaging Analysis in Mild-Moderate Alzheimer's Disease Patients Treated with Plasma Exchange with 5% Human Albumin. - Cuberas-Borrós, Gemma; Roca, Isabel; Boada, Merce; Tárraga, Lluís; Hernandez, Isabel; Buendia, Mar; Rubio, Lourdes; Torres, Gustavo; Bittini, Ángel; Guzmán-de-Villoria, Juan A; Pujadas, Francesc; Torres, Mireia; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Recently, modifications of Aβ1-42 levels in CSF and plasma associated with improvement in memory and language functions have been observed in patients with mild-moderate Alzheimer's disease (AD) treated with plasma exchange (PE) with albumin replacement. OBJECTIVE: To detect structural and functional brain changes in PE-treated AD patients as part of a Phase II clinical trial. METHODS: Patients received between 3 and 18 PE with albumin (Albutein® 5%, Grifols) or sham-PE (controls) for 21 weeks (divided in one intensive and two maintenance periods) followed by 6-month follow-up. Brain perfusion assessed by SPECT scans using an automated software (NeuroGam®) and brain structural changes assessed by MRI were performed at weeks 0 (baseline), 21, and 44 (with additional SPECT at weeks 9 and 33). Statistical parametric mapping (voxel-based analysis, SPM) and Z-scores calculations were applied to investigate changes to baseline. RESULTS: 42 patients were recruited (39 evaluable; 37 analyzed: 18 PE-treated; 19 controls). There was a trend toward decreasing hippocampi and total intracranial volume for both patient groups during the study (p < 0.05). After six months, PE-treated patients had less cerebral perfusion loss than controls in frontal, temporal, and parietal areas, and perfusion stabilization in Brodmann area BA38-R during the PE-treatment period (p < 0.05). SPM analysis showed stabilization or absence of progression of perfusion loss in PE-treated patients until week 21, not observed in controls. CONCLUSIONS: Mild-moderate AD patients showed decreased brain volume and impairment of brain perfusion as expected for the progression of the disease. PE-treatment with albumin replacement favored the stabilization of perfusion.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuroimaging; Plasma Exchange; Serum Albumin, Human; Time Factors; Tomography, Emission-Computed, Single-Photon; Treatment Outcome

Loss in PKC Epsilon Causes Downregulation of MnSOD and BDNF Expression in Neurons of Alzheimer's Disease Hippocampus. - Sen, Abhik; Nelson, Thomas J; Alkon, Daniel L; Hongpaisan, Jarin (J Alzheimers Dis, 2018)
Oxidative stress and amyloid-β (Aβ) oligomers have been implicated in Alzheimer's disease (AD). The growth and maintenance of neuronal networks are influenced by brain derived neurotrophic factor (BDNF) expression, which is promoted by protein kinase C epsilon (PKCɛ). We investigated the reciprocal interaction among oxidative stress, Aβ, and PKCɛ levels and subsequent PKCɛ-dependent MnSOD and BDNF expression in hippocampal pyramidal neurons. Reduced levels of PKCɛ, MnSOD, and BDNF and an increased level of Aβ were also found in hippocampal neurons from autopsy-confirmed AD patients. In cultured human primary hippocampal neurons, spherical aggregation of Aβ (amylospheroids) decreased PKCɛ and MnSOD. Treatment with t-butyl hydroperoxide (TBHP) increased superoxide, the oxidative DNA/RNA damage marker, 8-OHG, and Aβ levels, but reduced PKCɛ, MnSOD, BDNF, and cultured neuron density. These changes were reversed with the PKCɛ activators, bryostatin and DCPLA-ME. PKCɛ knockdown suppressed PKCɛ, MnSOD, and BDNF but increased Aβ. In cultured neurons, the increase in reactive oxygen species (ROS) associated with reduced PKCɛ during neurodegeneration was inhibited by the SOD mimetic MnTMPyP and the ROS scavenger NAc, indicating that strong oxidative stress suppresses PKCɛ level. Reduction of PKCɛ and MnSOD was prevented with the PKCɛ activator bryostatin in 5-6-month-old Tg2576 AD transgenic mice. In conclusion, oxidative stress and Aβ decrease PKCɛ expression. Reciprocally, a depression of PKCɛ reduces BDNF and MnSOD, resulting in oxidative stress. These changes can be prevented with the PKCɛ-specific activators.

Mapping the Proxies of Memory and Learning Function in Senior Adults with High-performing, Normal Aging and Neurocognitive Disorders. - Lu, Hanna; Ni, Xi; Fung, Ada W T; Lam, Linda C W (J Alzheimers Dis, 2018)
BACKGROUND: Memory and learning, as the core brain function, shows controversial results across studies focusing on aging and dementia. One of the reasons is because of the multi-faceted nature of memory and learning. However, there is still a dearth of comparable proxies with psychometric and morphometric portrait in clinical and non-clinical populations. OBJECTIVE: We aim to investigate the proxies of memory and learning function with direct and derived measures and examine their associations with morphometric features in senior adults with different cognitive status. METHODS: Based on two modality-driven tests, we assessed the component-specific memory and learning in the individuals with high performing (HP), normal aging, and neurocognitive disorders (NCD) (n = 488). Structural magnetic resonance imaging was used to measure the regional cortical thickness with surface-based morphometry analysis in a subsample (n = 52). METHODS: Compared with HP elderly, the ones with normal aging and minor NCD showed declined recognition memory and working memory, whereas had better learning performance (derived scores). Meanwhile, major NCD patients showed more breakdowns of memory and learning function. The correlation between proxies of memory and learning and cortical thickness exhibited the overlapped and unique neural underpinnings. CONCLUSIONS: The proxies of memory and learning could be characterized by component-specific constructs with psychometric and morphometric bases. Overall, the constructs of memory are more likely related to the pathological changes, and the constructs of learning tend to reflect the cognitive abilities of compensation.

Metabolic Syndrome, Brain Insulin Resistance, and Alzheimer's Disease: Thioredoxin Interacting Protein (TXNIP) and Inflammasome as Core Amplifiers. - Nasoohi, Sanaz; Parveen, Kehkashan; Ishrat, Tauheed (J Alzheimers Dis, 2018)
Empirical evidence indicates a strong association between insulin resistance and pathological alterations related to Alzheimer's disease (AD) in different cerebral regions. While cerebral insulin resistance is not essentially parallel with systemic metabolic derangements, type 2 diabetes mellitus (T2DM) has been established as a risk factor for AD. The circulating "toxic metabolites" emerging in metabolic syndrome may engage several biochemical pathways to promote oxidative stress and neuroinflammation leading to impair insulin function in the brain or "type 3 diabetes". Thioredoxin-interacting protein (TXNIP) as an intracellular amplifier of oxidative stress and inflammasome activation may presumably mediate central insulin resistance. Emerging data including those from our recent studies has demonstrated a sharp TXNIP upregulation in stroke, aging and AD and well underlining the significance of this hypothesis. With the main interest to illustrate TXNIP place in type 3 diabetes, the present review primarily briefs the potential mechanisms contributing to cerebral insulin resistance in a metabolically deranged environment. Then with a particular focus on plausible TXNIP functions to drive and associate with AD pathology, we present the most recent evidence supporting TXNIP as a promising therapeutic target in AD as an age-associated dementia.

Naturalistic Driving Study Investigating Self-Regulation Behavior in Early Alzheimer's Disease: A Pilot Study. - Paire-Ficout, Laurence; Lafont, Sylviane; Conte, Fanny; Coquillat, Amandine; Fabrigoule, Colette; Ankri, Joël; Blanc, Frédéric; Gabel, Cécilia; Novella, Jean-Luc; Morrone, Isabella; Mahmoudi, Rachid (J Alzheimers Dis, 2018)
BACKGROUND: Because cognitive processes decline in the earliest stages of Alzheimer's disease (AD), the driving abilities are often affected. The naturalistic driving approach is relevant to study the driving habits and behaviors in normal or critical situations in a familiar environment of participants. OBJECTIVE: This pilot study analyzed in-car video recordings of naturalistic driving in patients with early-stage AD and in healthy controls, with a special focus on tactical self-regulation behavior. METHODS: Twenty patients with early-stage AD (Diagnosis and Statistical Manual of Mental Disorders, Fourth Edition [DSM-IV] criteria), and 21 healthy older adults were included in the study. Data collection equipment was installed in their personal vehicles. Two expert psychologists assessed driving performance using a specially designed Naturalistic Driving Assessment Scale (NaDAS), paying particular attention to tactical self-regulation behavior, and they recorded all critical safety events. RESULTS: Poorer driving performance was observed among AD drivers: their tactical self-regulation behavior was of lower quality. AD patients had also twice as many critical events as healthy drivers and three times more "unaware" critical events. CONCLUSION: This pilot study used a naturalistic approach to accurately show that AD drivers have poorer tactical self-regulation behavior than healthy older drivers. Future deployment of assistance systems in vehicles should specifically target tactical self-regulation components.

Neural Correlates of Sleep Disturbance in Alzheimer's Disease: Role of the Precuneus in Sleep Disturbance. - Matsuoka, Teruyuki; Imai, Ayu; Fujimoto, Hiroshi; Kato, Yuka; Shibata, Keisuke; Nakamura, Kaeko; Yokota, Hajime; Yamada, Kei; Narumoto, Jin (J Alzheimers Dis, 2018)
BACKGROUND: Sleep disturbance may affect the development of Alzheimer's disease (AD), but the neural correlates of sleep disturbance in AD have not been fully clarified. OBJECTIVE: To examine the factors associated with sleep disturbance in AD. METHODS: A retrospective study was performed in 63 patients with AD. None of the patients had been prescribed antidementia or psychoactive drugs, and all underwent brain magnetic resonance imaging (MRI) before medication. Sleep disturbance was defined as a score of at least 1 point on the sleep disturbance subscale of the Neuropsychiatric Inventory (NPI). Whole brain image analysis was performed using SPM8 and VBM8. A two-sample t-test was used to compare patients with AD with (n = 19) and without (n = 44) sleep disturbance, with age and gender included as covariates. The statistical thresholds were set to an uncorrected p-value of 0.001 at the voxel level and a corrected p-value of 0.05 at the cluster level. In addition, pineal gland volume (PGV) measured using MRI, and white matter hyperintensity (WMH) assessed with the modified Fazekas scale were compared between patients with AD with and without sleep disturbance using independent group t-tests. RESULTS: In whole brain analysis, the precuneus volume in patients with AD with sleep disturbance was significantly smaller than those without sleep disturbance. There were no significant differences in PGV and WMH between the two groups. CONCLUSION: Sleep disturbance in AD was associated with reduction of precuneus volume. This suggests that the precuneus might be an important region in sleep disturbance in AD.

Neuropathologic Correlates of Psychiatric Symptoms in Alzheimer's Disease. - Ehrenberg, Alexander J; Suemoto, Claudia K; França Resende, Elisa de Paula; Petersen, Cathrine; Leite, Renata Elaine Paraizo; Rodriguez, Roberta Diehl; Ferretti-Rebustini, Renata Eloah de Lucena; You, Michelle; Oh, Jun; Nitrini, Ricardo; Pasqualucci, Carlos Augusto; Jacob-Filho, Wilson; et al. (J Alzheimers Dis, 2018)
Clarifying the relationships between neuropsychiatric symptoms and Alzheimer's disease (AD)-related pathology may open avenues for effective treatments. Here, we investigate the odds of developing neuropsychiatric symptoms across increasing burdens of neurofibrillary tangle and amyloid-β pathology. Participants who passed away between 2004 and 2014 underwent comprehensive neuropathologic evaluation at the Biobank for Aging Studies from the Faculty of Medicine at the University of São Paulo. Postmortem interviews with reliable informants were used to collect information regarding neuropsychiatric and cognitive status. Of 1,092 cases collected, those with any non-Alzheimer pathology were excluded, bringing the cohort to 455 cases. Braak staging was used to evaluate neurofibrillary tangle burden, and the CERAD neuropathology score was used to evaluate amyloid-β burden. The 12-item neuropsychiatric inventory was used to evaluate neuropsychiatric symptoms and CDR-SOB score was used to evaluate dementia status. In Braak I/II, significantly increased odds were detected for agitation, anxiety, appetite changes, depression, and sleep disturbances, compared to controls. Increased odds of agitation continue into Braak III/IV. Braak V/VI is associated with higher odds for delusions. No increased odds for neuropsychiatric symptoms were found to correlate with amyloid-β pathology. Increased odds of neuropsychiatric symptoms are associated with early neurofibrillary tangle pathology, suggesting that subcortical neurofibrillary tangle accumulation with minimal cortical pathology is sufficient to impact quality of life and that neuropsychiatric symptoms are a manifestation of AD biological processes.

Neuropsychiatric and Cognitive Subtypes among Community-Dwelling Older Persons and the Association with DSM-5 Mild Neurocognitive Disorder: Latent Class Analysis. - Liew, Tau Ming; Yu, Junhong; Mahendran, Rathi; Ng, Tze-Pin; Kua, Ee-Heok; Feng, Lei (J Alzheimers Dis, 2018)
BACKGROUND: Neuropsychiatric symptoms (NPS) have been shown to increase the risk of neurocognitive disorders (NCD), leading to the recently-published criteria of mild behavioral impairment (MBI) to identify pre-dementia using NPS alone. However, MBI drew concerns about over-diagnosing subclinical psychiatric disorders. OBJECTIVE: We hypothesized that the specificity of NPS in predicting NCD may be improved by considering NPS together with various domains of cognitive deficits. We tested this hypothesis by identifying subtypes based on the combination of NPS and cognitive deficits among community-dwelling older persons, and evaluating how the identified subtypes were associated with mild NCD. METHODS: Our participants were from a community-based cohort study. They completed assessments such as Geriatric Depression Scale (GDS), Geriatric Anxiety Inventory (GAI), and Montreal Cognitive Assessment (MoCA). Those with possible cognitive impairment underwent further evaluations for mild NCD. Latent class analysis was conducted using GDS, GAI, and MoCA domains. Logistic regression was performed to investigate the association between the latent-classes and mild NCD. RESULTS: We included 825 participants, and identified four distinct subtypes: Subtype 1 (no NPS or cognitive deficits), Subtype 2 (NPS alone), Subtype 3 (cognitive deficits alone), and Subtype 4 (both NPS and cognitive deficits). Subtype 1 and 2 had low risk of prevalent mild NCD (OR 0.92- 1.00), while Subtype 3 conferred a moderate risk (OR 4.47- 4.85) and Subtype 4 had the highest risk (OR 7.95- 8.63). CONCLUSION: We demonstrated the benefits of combining NPS and cognitive deficits to predict those at highest risk of prevalent mild NCD. Our findings highlighted the relevance of subclinical psychiatric symptoms in predicting NCD, and indirectly supported the need for longer durations of NPS to improve its specificity.
Keywords: Aged; Cognition; Cognitive Dysfunction; Diagnostic and Statistical Manual of Mental Disorders; Female; Humans; Latent Class Analysis; Logistic Models; Longitudinal Studies; Male; Middle Aged; Neuropsychological Tests; Sensitivity and Specificity

A Nomogram for Predicting Amyloid PET Positivity in Amnestic Mild Cognitive Impairment. - Kim, Si Eun; Woo, Sookyoung; Kim, Seon Woo; Chin, Juhee; Kim, Hee Jin; Lee, Byung In; Park, Jinse; Park, Kyung Won; Kang, Do-Young; Noh, Young; Ye, Byoung Seok; Yoo, Han Soo; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Most clinical trials focus on amyloid-β positive (Aβ+) amnestic mild cognitive impairment (aMCI), but screening failures are high because only a half of patients with aMCI are positive on Aβ PET. Therefore, it becomes necessary for clinicians to predict which patients will have Aβ biomarker. OBJECTIVE: We aimed to compare clinical factors, neuropsychological (NP) profiles, and apolipoprotein E (APOE) genotype between Aβ+ aMCI and Aβ-aMCI and to develop a clinically useful prediction model of Aβ positivity on PET (PET-Aβ+) in aMCI using a nomogram. METHODS: We recruited 523 aMCI patients who underwent Aβ PET imaging in a nation-wide multicenter cohort. The results of NP measures were divided into following subgroups: 1) Stage (Early and Late-stage), 2) Modality (Visual, Verbal, and Both), 3) Recognition failure, and 4) Multiplicity (Single and Multiple). A nomogram for PET-Aβ+ in aMCI patients was constructed using a logistic regression model. RESULTS: PET-Aβ+ had significant associations with NP profiles for several items, including high Clinical Dementia Rating Scale Sum of Boxes score (OR 1.47, p = 0.013) and impaired memory modality (impaired both visual and verbal memories compared with visual only, OR 3.25, p = 0.001). Also, presence of APOEɛ4 (OR 4.14, p < 0.001) was associated with PET-Aβ+. These predictors were applied to develop the nomogram, which showed good prediction performance (C-statistics = 0.79). Its prediction performances were 0.77/0.74 in internal/external validation. CONCLUSIONS: The nomogram consisting of NP profiles, especially memory domain, and APOEɛ4 genotype may provide a useful predictive model of PET-Aβ+ in patients with aMCI.

A Novel Antibody Targeting Tau Phosphorylated at Serine 235 Detects Neurofibrillary Tangles. - Brici, David; Götz, Jürgen; Nisbet, Rebecca M (J Alzheimers Dis, 2018)
Alzheimer's disease is characterized by two main pathological hallmarks in the human brain: the extracellular deposition of amyloid-β as plaques and the intracellular accumulation of the hyperphosphorylated protein tau as neurofibrillary tangles (NFTs). Phosphorylated tau (p-tau) specific-antibodies and silver staining have been used to reveal three morphological stages of NFT formation: pre-NFTs, intraneuronal NFTs (iNFTs), and extraneuronal NFTs (eNFTs). Here we characterize a novel monoclonal antibody, RN235, which is specific for tau phosphorylated at serine 235, and detects iNFTs and eNFTs in brain tissue, suggesting that phosphorylation at this site is indicative of late stage changes in tau.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Animals; Antibodies, Monoclonal; Antibody Specificity; Brain; Disease Models, Animal; Humans; Mice; Neurofibrillary Tangles; Phosphorylation; Plaque, Amyloid; tau Proteins

Novel GRN Mutations in Alzheimer's Disease and Frontotemporal Lobar Degeneration. - Piaceri, Irene; Imperiale, Daniele; Ghidoni, Enrico; Atzori, Cristiana; Bagnoli, Silvia; Ferrari, Camilla; Ungari, Silvana; Ambrogio, Luca; Sorbi, Sandro; Nacmias, Benedetta (J Alzheimers Dis, 2018)
BACKGROUND: During the twentieth century, frontotemporal dementia (FTD) was often misdiagnosed, confused with Alzheimer's disease or psychiatric disorders, jeopardizing care and research. OBJECTIVE: To analyze the FTD genes in the DNA samples of patients belonging to families clinically classified as probable Alzheimer's disease (FAD) in the early 1990s and not carrying mutation in the three main genes linked to FAD (Presenilin 1, Presenilin 2, and Amyloid precursor protein). METHODS: The genetic screening was performed on 63 probands diagnosed as FAD before the early 2000s. RESULTS: Four patients out of the 63 studied (4/63, 6.3%) resulted as carrying four different GRN genetic variations: p.T272SfsX10, p.R110X, p.C149LfsX10, and p.W304C. The first two mutations (p.T272SfsX10, p.R110X) are the most frequent ones in Italy in FTD patients; the latter two (p.C149LfsX10 and p.W304C) are not described in the scientific literature. CONCLUSION: Our data suggest that it can be important to re-examine FAD patients diagnosed when the FTD spectrum was not well recognized and the causative FTD genes had not yet been identified. Moreover, we propose initially analyzing genes associated with the first form of suspected dementia and, if the results are negative, studying genes implicated in the other form of dementia.

Novel Lipidized Analog of Prolactin-Releasing Peptide Improves Memory Impairment and Attenuates Hyperphosphorylation of Tau Protein in a Mouse Model of Tauopathy. - Popelová, Andrea; Pražienková, Veronika; Neprašová, Barbora; Kasperová, Barbora Judita; Hrubá, Lucie; Holubová, Martina; Zemenová, Jana; Blum, David; Železná, Blanka; Galas, Marie-Christine; Kuneš, Jaroslav; Maletínská, Lenka (J Alzheimers Dis, 2018)
Obesity and type 2 diabetes mellitus (T2DM) were characterized as risk factors for Alzheimer's disease (AD) development. Subsequently, T2DM drugs, such as liraglutide, were proven to be neuroprotective compounds attenuating levels of amyloid deposits, and tau hyperphosphorylation, both hallmarks of AD. The central anorexigenic effects of liraglutide inspired us to examine the potential neuroprotective effects of palm11-PrRP31, a strong anorexigenic analog with glucose-lowering properties, in THY-Tau22 mice overexpressing mutated human tau, a model of AD-like tau pathology. Seven-month-old THY-Tau22 mice were subcutaneously infused with palm11-PrRP31 for 2 months. Spatial memory was tested before and after the treatment, using a Y-maze. At the end of the treatment, mice were sacrificed by decapitation and hippocampi were dissected and analyzed by immunoblotting with specific antibodies. Treatment with palm11-PrRP31 resulted in significantly improved spatial memory. In the hippocampi of palm11-PrRP31-treated THY-Tau22 mice, tau protein phosphorylation was attenuated at Thr231, Ser396, and Ser404, the epitopes linked to AD progression. The mechanism of this attenuation remains unclear, since the activation of those kinases most implicated in tau hyperphosphorylation, such as GSK-3β, JNK, or MAPK/ERK1/2, remained unchanged by palm11-PrRP31 treatment. Furthermore, we observed a significant increase in the amount of postsynaptic density protein PSD95, and a non-significant increase of synaptophysin, both markers of increased synaptic plasticity, which could also result in improved spatial memory of THY-Tau22 mice treated with palm11-PrRP31. Palm11-PrRP31 seems to be a potential tool for the attenuation of neurodegenerative disorders in the brain. However, the exact mechanism of its action must be elucidated.

Nutritional Intervention to Prevent Alzheimer's Disease: Potential Benefits of Xanthophyll Carotenoids and Omega-3 Fatty Acids Combined. - Nolan, John M; Mulcahy, Riona; Power, Rebecca; Moran, Rachel; Howard, Alan N (J Alzheimers Dis, 2018)
BACKGROUND: A growing body of scientific evidence suggests that enrichment of certain nutritional compounds in the brain may reduce the risk of Alzheimer's disease (AD). OBJECTIVE: To investigate the impact of supplemental xanthophyll carotenoids plus omega-3 fatty acids on disease progression in patients with AD. METHODS: Three trial experiments were performed. In Trials 1 and 2 (performed on patients with AD over an 18-month period), 12 patients (AD status at baseline: 4 mild and 8 moderate) were supplemented with a xanthophyll carotenoid only formulation (Formulation 1; lutein:meso-zeaxanthin:zeaxanthin 10:10:2 mg/day) and 13 patients (AD status at baseline: 2 mild, 10 moderate, and 1 severe) were supplemented with a xanthophyll carotenoid and fish oil combination (Formulation 2; lutein:meso-zeaxanthin:zeaxanthin 10:10:2 mg/day plus 1 g/day of fish oil containing 430 mg docohexaenoic acid [DHA] and 90 mg eicopentaenoic acid [EPA]), respectively. In Trial 3, 15 subjects free of AD (the control group) were supplemented for 6 months with Formulation 1. Blood xanthophyll carotenoid response was measured in all trials by HPLC. Omega-3 fatty acids were profiled by direct infusion mass spectrometry. RESULTS: Xanthophyll carotenoid concentration increases were significantly greater for Formulation 2 compared to Formulation 1 (p < 0.05), and progression of AD was less for this group (p = 0.003), with carers reporting functional benefits in memory, sight, and mood. CONCLUSION: This preliminary report suggests positive outcomes for patients with AD who consumed a combination of xanthophyll carotenoids plus fish oil, but further study is required to confirm this important observation.

Parietal Involvement in the Semantic Variant of Primary Progressive Aphasia with Alzheimer's Disease Cerebrospinal Fluid Profile. - Bera, Géraldine; Migliaccio, Raffaella; Michelin, Thibaut; Lamari, Foudil; Ferrieux, Sophie; Nogues, Marie; Bertin, Hugo; Habert, Marie Odile; Dubois, Bruno; Teichmann, Marc; Kas, Aurélie (J Alzheimers Dis, 2018)
Semantic variant of primary progressive aphasia (svPPA) is typically associated with non-Alzheimer's disease (AD) pathology. However, some anatomopathological studies have found AD lesions in those patients. We compared brain perfusion SPECT of 18 svPPA patients with cerebrospinal fluid (CSF) biomarkers indicative of non-AD pathology (svPPA-nonAD) and three svPPA patients with CSF biomarkers indicative of underlying AD (svPPA-AD). All svPPA patients had severe left temporopolar hypoperfusion. SvPPA-nonAD had additional anterior cingulate and mediofrontal hypoperfusion, whereas svPPA-AD had greater left parietal and posterior cingulate involvement. Parietal damage in svPPA constitutes a biomarker for underlying Alzheimer pathology thus refining the classification of this PPA variant.

Polypharmacy and Potentially Inappropriate Medication in People with Dementia: A Nationwide Study. - Kristensen, Rachel Underlien; Nørgaard, Ane; Jensen-Dahm, Christina; Gasse, Christiane; Wimberley, Theresa; Waldemar, Gunhild (J Alzheimers Dis, 2018)
BACKGROUND: Polypharmacy (use of ≥5 different medications) and potentially inappropriate medication (PIM) are well-known risk factors for numerous negative health outcomes. However, the use of polypharmacy and PIM in people with dementia is not well-described. OBJECTIVE: To examine the prevalence of polypharmacy and PIM in older people with and without dementia in a nationwide population. METHODS: Cross-sectional study of the Danish population aged ≥65 in 2014 (n = 1,032,120) based on register data, including information on diagnoses and dispensed prescriptions. Polypharmacy and PIM use among people with (n = 35,476) and without dementia (n = 994,231) were compared, stratified by living situation and adjusted for age, sex, and comorbidity. The red-yellow-green list from the Danish Institute for Rational Pharmacotherapy and the German PRISCUS list were used to define PIM. RESULTS: People with dementia were more frequently exposed to polypharmacy (dementia: 62.6% versus no-dementia: 35.1%, p < 0.001) and likewise PIM (red-yellow-green: 45.0% versus 29.7%, p < 0.001; PRISCUS: 24.4% versus 13.2%, p < 0.001). After adjustments for age, sex, and comorbidity, the likelihood of polypharmacy and PIM was higher for community-dwelling people with dementia than without dementia (odds ratio (OR); [95% confidence interval (CI)] polypharmacy: 1.50 [1.45-1.55]; red-yellow-green: 1.27 [1.23-1.31]; PRISCUS: 1.25 [1.20-1.30]). In contrast, dementia slightly decreased the odds of polypharmacy and PIM in nursing home residents. CONCLUSION: Use of polypharmacy and PIM were widespread in the older population and more so in people with dementia. This could have negative implications for patient-safety and demonstrates the need for interventions to improve drug therapy in people with dementia.

Postmortem T2*- Weighted MRI Imaging of Cortical Iron Reflects Severity of Alzheimer's Disease. - Bulk, Marjolein; Kenkhuis, Boyd; Graaf, Linda M van der; Goeman, Jelle J; Natté, Remco; Weerd, Louise van der (J Alzheimers Dis, 2018)
The value of iron-based MRI changes for the diagnosis and staging of Alzheimer's disease (AD) depends on an association between cortical iron accumulation and AD pathology. Therefore, this study determined the cortical distribution pattern of MRI contrast changes in cortical regions selected based on the known distribution pattern of tau pathology and investigated whether MRI contrast changes reflect the underlying AD pathology in the different lobes. T2*-weighted MRI was performed on postmortem cortical tissue of controls, late-onset AD (LOAD), and early-onset AD (EOAD) followed by histology and correlation analyses. Combining ex vivo high-resolution MRI and histopathology revealed that: 1) LOAD and EOAD have a different distribution pattern of AD pathological hallmarks and MRI contrast changes over the cortex, with EOAD showing more severe MRI changes; 2) per lobe, severity of AD pathological hallmarks correlates with iron accumulation, and hence with MRI. Therefore, iron-sensitive MRI sequences allow detection of the cortical distribution pattern of AD pathology ex vivo.

Predicting and Tracking Short Term Disease Progression in Amnestic Mild Cognitive Impairment Patients with Prodromal Alzheimer's Disease: Structural Brain Biomarkers. - Marizzoni, Moira; Ferrari, Clarissa; Jovicich, Jorge; Albani, Diego; Babiloni, Claudio; Cavaliere, Libera; Didic, Mira; Forloni, Gianluigi; Galluzzi, Samantha; Hoffmann, Karl-Titus; Molinuevo, José Luis; Nobili, Flavio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Early Alzheimer's disease (AD) detection using cerebrospinal fluid (CSF) biomarkers has been recommended as enrichment strategy for trials involving mild cognitive impairment (MCI) patients. OBJECTIVE: To model a prodromal AD trial for identifying MRI structural biomarkers to improve subject selection and to be used as surrogate outcomes of disease progression. METHODS: APOE ɛ4 specific CSF Aβ42/P-tau cut-offs were used to identify MCI with prodromal AD (Aβ42/P-tau positive) in the WP5-PharmaCog (E-ADNI) cohort. Linear mixed models were performed 1) with baseline structural biomarker, time, and biomarker×time interaction as factors to predict longitudinal changes in ADAS-cog13, 2) with Aβ42/P-tau status, time, and Aβ42/P-tau status×time interaction as factors to explain the longitudinal changes in MRI measures, and 3) to compute sample size estimation for a trial implemented with the selected biomarkers. RESULTS: Only baseline lateral ventricle volume was able to identify a subgroup of prodromal AD patients who declined faster (interaction, p = 0.003). Lateral ventricle volume and medial temporal lobe measures were the biomarkers most sensitive to disease progression (interaction, p≤0.042). Enrichment through ventricular volume reduced the sample size that a clinical trial would require from 13 to 76%, depending on structural outcome variable. The biomarker needing the lowest sample size was the hippocampal subfield GC-ML-DG (granule cells of molecular layer of the dentate gyrus) (n = 82 per arm to demonstrate a 20% atrophy reduction). CONCLUSION: MRI structural biomarkers can enrich prodromal AD with fast progressors and significantly decrease group size in clinical trials of disease modifying drugs.

Predictors of Age of Diagnosis and Survival of Alzheimer's Disease in Down Syndrome. - Sinai, Amanda; Mokrysz, Claire; Bernal, Jane; Bohnen, Ingrid; Bonell, Simon; Courtenay, Ken; Dodd, Karen; Gazizova, Dina; Hassiotis, Angela; Hillier, Richard; McBrien, Judith; McCarthy, Jane; et al. (J Alzheimers Dis, 2018)
BACKGROUND: People with Down syndrome (DS) are an ultra-high risk population for Alzheimer's disease (AD). Understanding the factors associated with age of onset and survival in this population could highlight factors associated with modulation of the amyloid cascade. OBJECTIVE: This study aimed to establish the typical age at diagnosis and survival associated with AD in DS and the risk factors associated with these. METHODS: Data was obtained from the Aging with Down Syndrome and Intellectual Disabilities (ADSID) research database, consisting of data extracted from clinical records of patients seen by Community Intellectual Disability Services (CIDS) in England. Survival times when considering different risk factors were calculated. RESULTS: The mean age of diagnosis was 55.80 years, SD 6.29. Median survival time after diagnosis was 3.78 years, and median age at death was approximately 60 years. Survival time was associated with age of diagnosis, severity of intellectual disability, living status, anti-dementia medication status, and history of epilepsy. Age at diagnosis and treatment status remained predictive of survival time following adjustment. CONCLUSION: This study provides the best estimate of survival in dementia within the DS population to date, and is in keeping with previous estimates from smaller studies in the DS population. This study provides important estimates and insights into possible predictors of survival and age of diagnosis of AD in adults with DS, which will inform selection of participants for treatment trials in the future.
Keywords: Age of Onset; Alzheimer Disease; Down Syndrome; England; Female; Humans; Male; Middle Aged; Risk Factors; Survival Analysis

Preoperative Phosphorylated Tau Concentration in the Cerebrospinal Fluid Can Predict Cognitive Function Three Years after Shunt Surgery in Patients with Idiopathic Normal Pressure Hydrocephalus. - Nakajima, Madoka; Miyajima, Masakazu; Ogino, Ikuko; Akiba, Chihiro; Kawamura, Kaito; Kamohara, Chihiro; Fusegi, Keiko; Harada, Yoshinao; Hara, Takeshi; Sugano, Hidenori; Tange, Yuichi; Karagiozov, Kostadin; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Idiopathic normal pressure hydrocephalus (iNPH) is commonly treated by cerebrospinal fluid (CSF) shunting. However, the long-term efficacy of shunt intervention in the presence of comorbid Alzheimer's disease (AD) pathology is debated. OBJECTIVE: To identify AD-associated CSF biomarkers predictive of shunting surgery outcomes in patients with iNPH. METHODS: Preoperative levels of total and phosphorylated Tau (p-Tau) were measured in 40 patients with iNPH divided into low (<30 pg/mL) and high (≥30 pg/mL) p-Tau groups and followed up for three years after lumboperitoneal shunting. The modified Rankin Scale (mRS), Mini-Mental State Examination (MMSE), Frontal Assessment Battery, and iNPH Grading Scale scores were compared between the age-adjusted low (n = 24; mean age 75.7 years [SD 5.3]) and high (n = 11; mean age 76.0 years [SD 5.6]) p-Tau groups. RESULTS: Cognitive function improved early in the low p-Tau group and was maintained thereafter (p = 0.005). In contrast, the high p-Tau group showed a gradual decline to baseline levels by the third postoperative year (p = 0.040). Although the p-Tau concentration did not correlate with the preoperative MMSE score, a negative correlation appeared and strengthened during follow-up (R2 = 0.352, p < 0.001). Furthermore, the low p-Tau group showed rapid and sustained mRS grade improvement, whereas mRS performance gradually declined in the high p-Tau group. CONCLUSIONS: Preoperative CSF p-Tau concentration predicted some aspects of cognitive function after shunt intervention in patients with iNPH. The therapeutic effects of shunt treatment were shorter-lasting in patients with coexisting AD pathology.

Psychological and Mnemonic Benefits of Nostalgia for People with Dementia. - Ismail, Sanda; Christopher, Gary; Dodd, Emily; Wildschut, Tim; Sedikides, Constantine; Ingram, Tom A; Jones, Roy W; Noonan, Krist A; Tingley, Danielle; Cheston, Richard (J Alzheimers Dis, 2018)
BACKGROUND: Studies with non-clinical populations show that nostalgia increases psychological resources, such as self-esteem and social connectedness. OBJECTIVES: Our objectives were to find out if the benefits of nostalgia in non-clinical populations generalize to people with dementia and if nostalgia facilitates recall of dementia-related information. METHODS: All three experiments recruited participants with mild or moderate levels of dementia. Experiment 1 tested whether nostalgia (compared to control) enhances psychological resources among 27 participants. Experiment 2 used music to induce nostalgia (compared to control) in 29 participants. Experiment 3 compared recall for self-referent dementia statements among 50 participants randomized to either a nostalgia or control condition. Findings across experiments were synthesized with integrative data analysis. RESULTS: Nostalgia (compared to control) significantly increased self-reported social connectedness, meaning in life, self-continuity, optimism, self-esteem, and positive (but not negative) affect (Experiments 1-3). Compared to controls, nostalgic participants also recalled significantly more self-referent dementia-related information (Experiment 3). CONCLUSION: This series of experiments extends social psychological research with non-clinical populations into dementia care, providing evidence that nostalgia significantly enhances psychological resources. The finding that nostalgia increased recall of self-referent statements about dementia suggests that this emotion lends participants the fortitude to face the threat posed by their illness. The finding has potentially important clinical implications both for the development of reminiscence therapy and for facilitating adjustment to a diagnosis of dementia.

Putative Gonadotropin-Releasing Hormone Agonist Therapy and Dementia: An Application of Medicare Hospitalization Claims Data. - Smith, Mark A; Bowen, Richard L; Nguyen, Richard Q; Perry, George; Atwood, Craig S; Rimm, Alfred A (J Alzheimers Dis, 2018)
BACKGROUND: Estrogen and hormone replacement therapies to reduce Alzheimer's disease (AD) have yielded conflicting results. However, this study proposes that the well-characterized increase in serum gonadotropins following menopause or andropause are accountable for the increased risk of developing AD among the elderly population. OBJECTIVE: To determine the role of gonadotropins in the development of AD and investigate gonadotropin-releasing hormone (GnRH) agonist therapy as a potential preventative and/or disease-modifying approach to AD management. METHODS: Male Medicare beneficiaries aged 67 to 75 and hospitalized with prostate cancer (n = 115,789) were compared to three control groups: men of the same demographics undergoing a cholecystectomy (n = 97,267), herniorrhaphy (n = 68,778), or transurethral prostatectomy (n = 267,691). A proportion of the patients hospitalized with prostate cancer were assumed to have low concentrations of serum gonadotropins and sex steroids as a result of GnRH agonist therapy, while those in the control groups were assumed to have elevated gonadotropin but lowered sex steroid levels that are associated with andropause in this age group. RESULTS: The rates of development of select diagnoses of dementia, including AD, over a twelve-year follow-up period following surgery. When compared to control patients, men hospitalized with prostate cancer have a protection against dementia after twelve years of follow-up, with relative risks ranging from 0.48 to 0.83. CONCLUSION: Patients with prostate cancer are treated with the GnRH analogue leuprolide acetate, our data suggest that leuprolide acetate may be therapeutic for AD via its downregulation of serum gonadotropins.

Quantitative Genetics Validates Previous Genetic Variants and Identifies Novel Genetic Players Influencing Alzheimer's Disease Cerebrospinal Fluid Biomarkers. - Ramos de Matos, Mafalda; Ferreira, Catarina; Herukka, Sanna-Kaisa; Soininen, Hilkka; Janeiro, André; Santana, Isabel; Baldeiras, Ines; Almeida, Maria Rosário; Lleo, Alberto; Dols-Icardo, Oriol; Alcolea, Daniel; Benussi, Luisa; et al. (J Alzheimers Dis, 2018)
Cerebrospinal fluid (CSF) biomarkers have been extensively investigated in the Alzheimer's disease (AD) field, and are now being applied in clinical practice. CSF amyloid-beta (Aβ1-42), total tau (t-tau), and phosphorylated tau (p-tau) reflect disease pathology, and may be used as quantitative traits for genetic analyses, fostering the identification of new genetic factors and the proposal of novel biological pathways of the disease. In patients, the concentration of CSF Aβ1-42 is decreased due to the accumulation of Aβ1-42 in amyloid plaques in the brain, while t-tau and p-tau levels are increased, indicating the extent of neuronal damage. To better understand the biological mechanisms underlying the regulation of AD biomarkers, and its relation to AD, we examined the association between 36 selected single nucleotide polymorphisms (SNPs) and AD biomarkers Aβ1-42, t-tau, and p-tau in CSF in a cohort of 672 samples (571 AD patients and 101 controls) collected within 10 European consortium centers.Our results highlighted five genes, APOE, LOC100129500, PVRL2, SNAR-I, and TOMM40, previously described as main players in the regulation of CSF biomarkers levels, further reinforcing a role for these in AD pathogenesis. Three new AD susceptibility loci, INPP5D, CD2AP, and CASS4, showed specific association with CSF tau biomarkers. The identification of genes that specifically influence tau biomarkers point out to mechanisms, independent of amyloid processing, but in turn related to tau biology that may open new venues to be explored for AD treatment.

Quantitative Susceptibility Mapping of Amyloid-β Aggregates in Alzheimer's Disease with 7T MR. - Tiepolt, Solveig; Schäfer, Andreas; Rullmann, Michael; Roggenhofer, Elisabeth; Gertz, Hermann-Josef; Schroeter, Matthias L; Patt, Marianne; Bazin, Pierre-Louis; Jochimsen, Thies H; Turner, Robert; Sabri, Osama; Barthel, Henryk (J Alzheimers Dis, 2018)
BACKGROUND: PET imaging is an established technique to detect cerebral amyloid-β (Aβ) plaques in vivo. Some preclinical and postmortem data report an accumulation of redox-active iron near Aβ plaques. Quantitative susceptibility mapping (QSM) at high-field MRI enables iron deposits to be depicted with high spatial resolution. OBJECTIVE: Aim of this study was to examine whether iron and Aβ plaque accumulation is related and thus, whether 7T MRI might be an additive diagnostic tool to Aβ PET imaging. METHODS: Postmortem human Alzheimer's disease (AD) and healthy control (HC) frontal gray matter (GM) was imaged with 7T MRI which resulted in T1 maps and QSM. Aβ plaque load was determined by histopathology. In vivo, 10 Aβ PET-positive AD patients (74.1±6.0a) and 10 Aβ PET-negative HCs (67.1±4.4a) underwent 7T MR examination and QSM maps were analyzed. Severity of cognitive deficits was determined by MMSE. RESULTS: Postmortem, the susceptibility of Aβ plaque-containing GM were higher than those of Aβ plaque-free GM (0.011±0.002 versus - 0.008±0.003 ppm, p < 0.001). In vivo, only the bilateral globus pallidus showed significantly higher susceptibility in AD patients compared to HCs (right: 0.277±0.018 versus - 0.009±0.009 ppm; left: 0.293±0.014 versus - 0.007±0.012 ppm, p < 0.0001). The pallidal QSM values were negatively correlated with those of the MMSE (r = - 0.69, p = 0.001). CONCLUSION: The postmortem study revealed significant susceptibility differences between the Aβ plaque-containing and Aβ plaque-free GM, whereas in vivo only the QSM values of the globus pallidus differed significantly between AD and HC group. The pallidal QSM values correlated with the severity of cognitive deficits. These findings encourage efforts to optimize the 7T-QSM methodology.

Real World Recruiting of Older Subjects with Mild Cognitive Impairment for Exercise Trials: Community Readiness is Pivotal. - Sanders, Marit L; Stuckenschneider, Tim; Devenney, Kate E; Lawlor, Brian; Schneider, Stefan; Olde Rikkert, Marcel G M (J Alzheimers Dis, 2018)
Prevention trials in subjects with mild cognitive impairment (MCI), especially lifestyle interventions, can be difficult to carry out, particularly the recruitment and retention of subjects. We experienced these challenges in our multi-site one-year exercise trial in MCI, NeuroExercise. Trial recruitment rates differed significantly across sites; the non-medical sport university site, providing free access to a range of group exercise in a sports environment, proved far more successful than memory clinics linked to hospitals. This suggests that non-medical settings and a non-medical research community facilitating physical activities may be important factors in recruitment of subjects with MCI for large prevention trials.
Keywords: Aged; Cognitive Dysfunction; Europe; Exercise; Female; Humans; Life Style; Male; Middle Aged; Patient Selection

Regional White Matter Hyperintensity Influences Grey Matter Atrophy in Mild Cognitive Impairment. - Vipin, Ashwati; Foo, Heidi Jing Ling; Lim, Joseph Kai Wei; Chander, Russell Jude; Yong, Ting Ting; Ng, Adeline Su Lyn; Hameed, Shahul; Ting, Simon Kang Seng; Zhou, Juan; Kandiah, Nagaendran (J Alzheimers Dis, 2018)
The association between cerebrovascular disease pathology (measured by white matter hyperintensities, WMH) and brain atrophy in early Alzheimer's disease (AD) remain to be elucidated. Thus, we investigated how WMH influence neurodegeneration and cognition in prodromal and clinical AD. We examined 51 healthy controls, 35 subjects with mild cognitive impairment (MCI), and 30 AD patients. We tested how total and regional WMH is related to specific grey matter volume (GMV) reductions in MCI and AD compared to controls. Stepwise regression analysis was further performed to investigate the association of GMV and regional WMH volume with global cognition. We found that total WMH volume was highest in AD but showed the strongest association with lower GMV in MCI. Frontal and parietal WMH had the most extensive influence on GMV loss in MCI. Additionally, parietal lobe WMH volume (but not hippocampal atrophy) was significantly associated with global cognition in MCI while smaller hippocampal volume (but not WMH volume) was associated with lower global cognition in AD. Thus, although WMH volume was highest in AD subjects, it had a more pervasive influence on brain structure and cognitive impairment in MCI. Our study thus highlights the importance of early detection of cerebrovascular disease, as its intervention at the MCI stage might potentially slow down neurodegeneration.

A Retrospective Belgian Multi-Center MRI Biomarker Study in Alzheimer's Disease (REMEMBER). - Niemantsverdriet, Ellis; Ribbens, Annemie; Bastin, Christine; Benoit, Florence; Bergmans, Bruno; Bier, Jean-Christophe; Bladt, Roxanne; Claes, Lene; De Deyn, Peter Paul; Deryck, Olivier; Hanseeuw, Bernard; Ivanoiu, Adrian; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Magnetic resonance imaging (MRI) acquisition/processing techniques assess brain volumes to explore neurodegeneration in Alzheimer's disease (AD). OBJECTIVE: We examined the clinical utility of MSmetrix and investigated if automated MRI volumes could discriminate between groups covering the AD continuum and could be used as a predictor for clinical progression. METHODS: The Belgian Dementia Council initiated a retrospective, multi-center study and analyzed whole brain (WB), grey matter (GM), white matter (WM), cerebrospinal fluid (CSF), cortical GM (CGM) volumes, and WM hyperintensities (WMH) using MSmetrix in the AD continuum. Baseline (n = 887) and follow-up (FU, n = 95) T1-weighted brain MRIs and time-linked neuropsychological data were available. RESULTS: The cohort consisted of cognitively healthy controls (HC, n = 93), subjective cognitive decline (n = 102), mild cognitive impairment (MCI, n = 379), and AD dementia (n = 313). Baseline WB and GM volumes could accurately discriminate between clinical diagnostic groups and were significantly decreased with increasing cognitive impairment. MCI patients had a significantly larger change in WB, GM, and CGM volumes based on two MRIs (n = 95) compared to HC (FU>24months, p = 0.020). Linear regression models showed that baseline atrophy of WB, GM, CGM, and increased CSF volumes predicted cognitive impairment. CONCLUSION: WB and GM volumes extracted by MSmetrix could be used to define the clinical spectrum of AD accurately and along with CGM, they are able to predict cognitive impairment based on (decline in) MMSE scores. Therefore, MSmetrix can support clinicians in their diagnostic decisions, is able to detect clinical disease progression, and is of help to stratify populations for clinical trials.

A Review of the Familial Alzheimer's Disease Locus PRESENILIN 2 and Its Relationship to PRESENILIN 1. - Jiang, Haowei; Jayadev, Suman; Lardelli, Michael; Newman, Morgan (J Alzheimers Dis, 2018)
PRESENILIN 1 (PSEN1) and PRESENILIN 2 (PSEN2) genes are loci for mutations causing familial Alzheimer's disease (fAD). However, the function of these genes and how they contribute to fAD pathogenesis has not been fully determined. This review provides a summary of the overlapping and independent functions of the PRESENILINS with a focus on the lesser studied PSEN2. As a core component of the γ-secretase complex, the PSEN2 protein is involved in many γ-secretase-related physiological activities, including innate immunity, Notch signaling, autophagy, and mitochondrial function. These physiological activities have all been associated with AD progression, indicating that PSEN2 plays a particular role in AD pathogenesis.

Revolution of Alzheimer Precision Neurology. Passageway of Systems Biology and Neurophysiology. - Hampel, Harald; Toschi, Nicola; Babiloni, Claudio; Baldacci, Filippo; Black, Keith L; Bokde, Arun L W; Bun, René S; Cacciola, Francesco; Cavedo, Enrica; Chiesa, Patrizia A; Colliot, Olivier; Coman, Cristina-Maria; et al. (J Alzheimers Dis, 2018)
The Precision Neurology development process implements systems theory with system biology and neurophysiology in a parallel, bidirectional research path: a combined hypothesis-driven investigation of systems dysfunction within distinct molecular, cellular, and large-scale neural network systems in both animal models as well as through tests for the usefulness of these candidate dynamic systems biomarkers in different diseases and subgroups at different stages of pathophysiological progression. This translational research path is paralleled by an "omics"-based, hypothesis-free, exploratory research pathway, which will collect multimodal data from progressing asymptomatic, preclinical, and clinical neurodegenerative disease (ND) populations, within the wide continuous biological and clinical spectrum of ND, applying high-throughput and high-content technologies combined with powerful computational and statistical modeling tools, aimed at identifying novel dysfunctional systems and predictive marker signatures associated with ND. The goals are to identify common biological denominators or differentiating classifiers across the continuum of ND during detectable stages of pathophysiological progression, characterize systems-based intermediate endophenotypes, validate multi-modal novel diagnostic systems biomarkers, and advance clinical intervention trial designs by utilizing systems-based intermediate endophenotypes and candidate surrogate markers. Achieving these goals is key to the ultimate development of early and effective individualized treatment of ND, such as Alzheimer's disease. The Alzheimer Precision Medicine Initiative (APMI) and cohort program (APMI-CP), as well as the Paris based core of the Sorbonne University Clinical Research Group "Alzheimer Precision Medicine" (GRC-APM) were recently launched to facilitate the passageway from conventional clinical diagnostic and drug development toward breakthrough innovation based on the investigation of the comprehensive biological nature of aging individuals. The APMI movement is gaining momentum to systematically apply both systems neurophysiology and systems biology in exploratory translational neuroscience research on ND.
Keywords: Alzheimer Disease; Animals; Brain; Humans; Neurology; Neurophysiology; Precision Medicine; Systems Biology; Translational Medical Research

Risk Factors Associated with Cortical Thickness and White Matter Hyperintensities in Dementia Free Okinawan Elderly. - Silbert, Lisa C; Lahna, David; Promjunyakul, Nutta-On; Boespflug, Erin; Ohya, Yusuke; Higashiuesato, Yasushi; Nishihira, Junko; Katsumata, Yuriko; Tokashiki, Takashi; Dodge, Hiroko H (J Alzheimers Dis, 2018)
BACKGROUND: Cortical gray matter (GM) and white matter (WM) deterioration are signals of neurodegeneration and increased dementia risk; however, their specific etiologies in dementia-free aging is unclear. OBJECTIVE: The objective of this study was to examine potentially modifiable risk factors of GM and WM degeneration in a well-characterized cohort of dementia-free elderly. METHODS: 96 Okinawan elderly participants (age 83.6) from the Keys to Optimal Cognitive Aging Project (KOCOA) underwent MRI and cognitive evaluation. Serum markers of inflammation (interleukin-6 (IL-6), high sensitivity C-reactive protein), cerebrovascular disease (systolic blood pressure (SBP) 140+, hemoglobin A1C (HgbA1C), total cholesterol), and essential minerals (copper (Cu), magnesium, and calcium) were examined in relation to mean cortical thickness (MCT) and white matter hyperintensities (WMH), adjusting for age and gender. Voxel-based morphometry (VBM) analyses identified relationships between regional GM density and the above markers. RESULTS: Decreased MCT was associated with SBP 140 + (p = 0.029) and increased serum IL-6 (p = 0.036), HgbA1C (p = 0.002), and Cu (p = 0.025). In VBM analyses, increased IL-6, HgbA1C, and Cu were associated with decreased GM density in temporal lobe regions. HgbA1C (p = 0.004) was associated with greater WMH volume. CONCLUSIONS: Peripheral markers of Cu, CVD risk, and inflammation are associated with MRI-markers of decreased brain health in dementia-free Okinawan elderly, with regional cortical thinning in areas involved in early accumulation of Alzheimer's disease pathology. Results identify potentially modifiable biomarkers as targets in the prevention of dementia in older individuals.

Sally-Anne Test in Patients with Alzheimer's Disease Dementia. - Takenoshita, Shintaro; Terada, Seishi; Yokota, Osamu; Kutoku, Yumiko; Wakutani, Yosuke; Nakashima, Makoto; Maki, Yohko; Hattori, Hideyuki; Yamada, Norihito (J Alzheimers Dis, 2018)
Social cognition has recently been recognized as one of the essential cognitive domains. Some reports suggested that patients with Alzheimer's disease dementia (ADD) presented significant theory of mind deficits even in the mild condition. However, most previous studies included only small numbers of patients with ADD. The present study administered the first-order false belief (Sally-Anne) test to 116 consecutive patients with ADD from the outpatient units of the Memory Clinic and compared the characteristics of the two groups with correct and incorrect answers on the test. Then various clinical characteristics were evaluated. Only 37.1% of patients with ADD correctly answered the Sally-Anne test with the right explanation. Comparison between the two groups of correct and incorrect answers revealed a significant association between the frontal assessment battery score and the result of the Sally-Anne test in the multiple logistic regression analyses. Thus, patients with ADD presented a significant deficit in social cognition even in the mild condition. Frontal dysfunction was thought to be related to the deficits in mild ADD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition Disorders; Disease Progression; Female; Humans; Logistic Models; Male; Neuropsychological Tests; Social Behavior Disorders; Theory of Mind

Separating Symptomatic Alzheimer's Disease from Depression based on Structural MRI. - Klöppel, Stefan; Kotschi, Maria; Peter, Jessica; Egger, Karl; Hausner, Lucrezia; Frölich, Lutz; Förster, Alex; Heimbach, Bernhard; Normann, Claus; Vach, Werner; Urbach, Horst; Abdulkadir, Ahmed (J Alzheimers Dis, 2018)
Older patients with depression or Alzheimer's disease (AD) at the stage of early dementia or mild cognitive impairment may present with objective cognitive impairment, although the pathology and thus therapy and prognosis differ substantially. In this study, we assessed the potential of an automated algorithm to categorize a test set of 65 T1-weighted structural magnetic resonance images (MRI). A convenience sample of elderly individuals fulfilling clinical criteria of either AD (n = 28) or moderate and severe depression (n = 37) was recruited from different settings to assess the potential of the pattern recognition method to assist in the differential diagnosis of AD versus depression. We found that our algorithm learned discriminative patterns in the subject's grey matter distribution reflected by an area under the receiver operator characteristics curve of up to 0.83 (confidence interval ranged from 0.67 to 0.92) and a balanced accuracy of 0.79 for the separation of depression from AD, evaluated by leave-one-out cross validation. The algorithm also identified consistent structural differences in a clinically more relevant scenario where the data used during training were independent from the data used for evaluation and, critically, which included five possible diagnoses (specifically AD, frontotemporal dementia, Lewy body dementia, depression, and healthy aging). While the output was insufficiently accurate to use it directly as a means for classification when multiple classes are possible, the continuous output computed by the machine learning algorithm differed between the two groups that were investigated. The automated analysis thus could complement, but not replace clinical assessments.

Sex-Related Reserve Hypothesis in Alzheimer's Disease: Changes in Cortical Thickness with a Five-Year Longitudinal Follow-Up. - Lee, Juyoun; Cho, Hanna; Jeon, Seun; Kim, Hee Jin; Kim, Yeo Jin; Lee, Jeongmin; Kim, Sung Tae; Lee, Jong-Min; Chin, Juhee; Lockhart, Samuel N; Lee, Ae Young; Na, Duk L; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Sex effects on the progression of Alzheimer's disease (AD) have received less attention than other demographic factors, including onset age and education. OBJECTIVE: The aim of this study was to investigate whether sex affected cortical thinning in the disease progression of AD. METHODS: We prospectively recruited 36 patients with early-stage AD and 14 people with normal cognition. All subjects were assessed with magnetic resonance imaging at baseline, Year 1, Year 3, and Year 5. We performed cortical thickness analyses using surface-based morphometry on magnetic resonance imaging. RESULTS: Women with AD showed more rapid cortical thinning in the left dorsolateral frontal cortex, left superior temporal gyrus, bilateral temporo-parietal association cortices, bilateral anterior cingulate gyri, bilateral medial frontal cortices, and bilateral occipital cortices over 5 years than men with AD, even though there was no difference in cortical thickness at baseline. In contrast, there were no regions of significantly more rapid atrophy in men with AD. CONCLUSIONS: Our findings suggest that women deteriorate faster than men in the progression of AD.

Sleep and EEG Power Spectral Analysis in Three Transgenic Mouse Models of Alzheimer's Disease: APP/PS1, 3xTgAD, and Tg2576. - Kent, Brianne A; Strittmatter, Stephen M; Nygaard, Haakon B (J Alzheimers Dis, 2018)
BACKGROUND: Sleep disturbances have long been associated with Alzheimer's disease (AD), and there is a growing interest in how these disturbances might impact AD pathophysiology. Despite this growing interest, surprisingly little is known about how sleep architecture and the broader neuronal network are affected in widely used transgenic mouse models of AD. OBJECTIVE: We analyzed sleep and electroencephalography (EEG) power in three transgenic mouse models of AD, using identical and commercially available hardware and analytical software. The goal was to assess the suitability of these mouse lines to model sleep and the broader neuronal network dysfunction measured by EEG in AD. METHODS: Tg2576, APP/PS1, and 3xTgAD transgenic AD mice were studied using in vivo EEG recordings for sleep/wake time and power spectral analysis. RESULTS: Both the APP/PS1 model at 8- 10 months and the Tg2576 model at 12 months of age exhibited stage-dependent decreases in theta and delta power, and shifts in the power spectra toward higher frequencies. Stage-dependent power spectral analyses showed no changes in the 3xTgAD model at 18 months of age. The percentage of time spent awake, in non-rapid eye movement sleep (NREM), or in rapid-eye-movement sleep (REM) was not different between genotypes in any of the transgenic lines. CONCLUSION: Our findings are consistent with data from several other transgenic AD models as well as certain studies in patients with mild cognitive impairment. Further studies will be needed to better understand the correlation between EEG spectra and AD pathophysiology, both in AD models and the human condition.

Stabilized Low-n Amyloid-β Oligomers Induce Robust Novel Object Recognition Deficits Associated with Inflammatory, Synaptic, and GABAergic Dysfunction in the Rat. - Watremez, William; Jackson, Joshua; Almari, Bushra; McLean, Samantha L; Grayson, Ben; Neill, Joanna C; Fischer, Nicolas; Allouche, Ahmad; Koziel, Violette; Pillot, Thierry; Harte, Michael K (J Alzheimers Dis, 2018)
BACKGROUND: With current treatments for Alzheimer's disease (AD) only providing temporary symptomatic benefits, disease modifying drugs are urgently required. This approach relies on improved understanding of the early pathophysiology of AD. A new hypothesis has emerged, in which early memory loss is considered a synapse failure caused by soluble amyloid-β oligomers (Aβo). These small soluble Aβo, which precede the formation of larger fibrillar assemblies, may be the main cause of early AD pathologies. OBJECTIVE: The aim of the current study was to investigate the effect of acute administration of stabilized low-n amyloid-β1-42 oligomers (Aβo1-42) on cognitive, inflammatory, synaptic, and neuronal markers in the rat. METHODS: Female and male Lister Hooded rats received acute intracerebroventricular (ICV) administration of either vehicle or 5 nmol of Aβo1-42 (10μL). Cognition was assessed in the novel object recognition (NOR) paradigm at different time points. Levels of inflammatory (IL-1β, IL-6, TNF-α), synaptic (PSD-95, SNAP-25), and neuronal (n-acetylaspartate, parvalbumin-positive cells) markers were investigated in different brain regions (prefrontal and frontal cortex, striatum, dorsal and ventral hippocampus). RESULTS: Acute ICV administration of Aβo1-42 induced robust and enduring NOR deficits. These deficits were reversed by acute administration of donepezil and rolipram but not risperidone. Postmortem analysis revealed an increase in inflammatory markers, a decrease in synaptic markers and parvalbumin containing interneurons in the frontal cortex, with no evidence of widespread neuronal loss. CONCLUSION: Taken together the results suggest that acute administration of soluble low-n Aβo may be a useful model to study the early mechanisms involved in AD and provide us with a platform for testing novel therapeutic approaches that target the early underlying synaptic pathology.

Supplemental Retinal Carotenoids Enhance Memory in Healthy Individuals with Low Levels of Macular Pigment in A Randomized, Double-Blind, Placebo-Controlled Clinical Trial. - Power, Rebecca; Coen, Robert F; Beatty, Stephen; Mulcahy, Riona; Moran, Rachel; Stack, Jim; Howard, Alan N; Nolan, John M (J Alzheimers Dis, 2018)
BACKGROUND: There is a biologically plausible rationale whereby the dietary carotenoids lutein (L), zeaxanthin (Z), and meso-zeaxanthin (MZ), which are collectively referred to as macular pigment (MP) in the central retina (macula), support the maintenance of cognition via their antioxidant and anti-inflammatory properties. OBJECTIVE: To investigate the impact of supplemental L, Z, and MZ on memory, executive function, and verbal fluency among healthy individuals with low MP levels. METHODS: In this double-blind, placebo-controlled, randomized clinical trial, subjects (n = 91; mean±SD age = 45.42±12.40; % male = 51.6) consumed a daily formulation of 10 mg L, 10 mg MZ, and 2 mg Z (n = 45) or placebo (n = 46) for 12 months. Cognitive domains assessed included verbal and visual learning, immediate and delayed memory, executive function, and verbal fluency. MP and serum carotenoid concentrations of L, Z, and MZ were also measured. RESULTS: Following 12-month supplementation, individuals in the active group exhibited statistically significant improvements in memory when compared to the placebo group (paired associated learning [PAL] memory score [rANOVA, p = 0.009]; PAL errors [rANOVA, p = 0.017]). Furthermore, the observed reduction in the number of errors made in the PAL task among those in the intervention group was positively and significantly related to observed increases in MP volume (p = 0.005) and observed increases in serum concentrations of L (p = 0.009). CONCLUSION: This randomized, double-blind, placebo-controlled clinical trial demonstrates a memory-enhancing effect of daily supplementation with L, Z, and MZ in healthy subjects with low MP at baseline. The implications of these findings for intellectual performance throughout life, and for risk of cognitive decline in later life, warrant further study.
Keywords: Adult; Cognition; Dietary Supplements; Double-Blind Method; Executive Function; Female; Healthy Volunteers; Humans; Lutein; Macular Pigment; Male; Memory, Episodic; Middle Aged; Retina; Vision Tests; Zeaxanthins

Synthetic Fragment of Receptor for Advanced Glycation End Products Prevents Memory Loss and Protects Brain Neurons in Olfactory Bulbectomized Mice. - Volpina, Olga M; Samokhin, Alexandr N; Koroev, Dmitriy O; Nesterova, Inna V; Volkova, Tatyana D; Medvinskaya, Natalia I; Nekrasov, Pavel V; Tatarnikova, Olga G; Kamynina, Anna V; Balasanyants, Samson M; Voronina, Tamara A; Kulikov, Alexey M; et al. (J Alzheimers Dis, 2018)
Activation of receptor for advanced glycation end products (RAGE) plays an essential role in the development of Alzheimer's disease (AD). It is known that the soluble isoform of the receptor binds to ligands and prevents negative effects of the receptor activation. We proposed that peptide fragments from RAGE prevent negative effects of the receptor activation during AD neurodegeneration. We have synthesized peptide fragments from surface-exposed regions of RAGE. Peptides were intranasally administrated into olfactory bulbectomized (OBX) mice, which developed some characteristics similar to AD neurodegeneration. We have found that only insertion of fragment (60-76) prevents the memory of OBX mice. Immunization of OBX mice with peptides showed that again only (60-76) peptide protected the memory of animals. Both intranasal insertion and immunization decreased the amyloid-β (Aβ) level in the brain. Activity of shortened fragments of (60-76) peptide was tested and showed only the (60-70) peptide is responsible for manifestation of activity. Intranasal administration of (60-76) peptide shows most protective effect on morpho-functional characteristics of neurons in the cortex and hippocampal areas. Using Flu-(60-76) peptide, we revealed its penetration in the brain of OBX mice as well as colocalization of Flu-labeled peptide with Aβ in the brain regions in transgenic mice. Flu-(60-76) peptide complex with trimer of Aβ was detected by SDS-PAGE. These data indicate that Aβ can be one of the molecular target of (60-70) peptide. These findings provide a new peptide molecule for design of anti-AD drug and for investigation of RAGE activation ways in progression of AD neurodegeneration.
Keywords: Administration, Intranasal; Animals; Behavior, Animal; Brain; Disease Models, Animal; Male; Maze Learning; Memory Disorders; Mice; Mice, Transgenic; Neurons; Olfactory Bulb; Peptide Fragments; Receptor for Advanced Glycation End Products

Targeting Alzheimer's Disease at the Right Time and the Right Place: Validation of a Personalized Approach to Diagnosis and Treatment. - Gauthier, Serge; Ng, Kok Pin; Pascoal, Tharick A; Zhang, Hua; Rosa-Neto, Pedro (J Alzheimers Dis, 2018)
Cautious optimism is appropriate for a near future (five years) time frame for a number of drugs acting on the different pathophysiological components of Alzheimer's disease (amyloid deposition, tau hyperphosphorylation, neuroinflammation, vascular changes, to name the most important known so far). Since the relative weight of these components will be different between individuals and will even change over time for each individual, a 'one drug fit for all' approach is no longer defensible. Precision medicine using biomarkers in the diagnosis and treatment of Alzheimer's disease is the new strategy.

Tau Conformation as a Target for Disease-Modifying Therapy: The Role of Truncation. - Novak, Petr; Cehlar, Ondrej; Skrabana, Rostislav; Novak, Michal (J Alzheimers Dis, 2018)
Tau protein plays a major role in the pathogenesis of Alzheimer's disease. Despite many decades of intensive research, the cause of the conformational switch that leads to the remodeling of the highly flexible conformational ensemble of intrinsically disordered protein tau into insoluble filaments is still elusive. We show here that truncation of tau may play a causative role in this conformational change, as evidenced by results obtained from in vitro experiments and from transgenic animal models. This conformational change is a common denominator of pathological tau protein assemblies, and a salient drug target. The long-running research of truncated tau has led to the generation of the first active tau vaccine that has entered clinical trials.

Three VCP Mutations in Patients with Frontotemporal Dementia. - Wong, Tsz Hang; Pottier, Cyril; Hondius, David C; Meeter, Lieke H H; van Rooij, Jeroen G J; Melhem, Shami; van Minkelen, Rick; van Duijn, Cornelia M; Rozemuller, Annemieke J M; Seelaar, Harro; Rademakers, Rosa; van Swieten, John C (J Alzheimers Dis, 2018)
Valosin-containing protein (VCP) is involved in multiple cellular activities. Mutations in VCP lead to heterogeneous clinical presentations including inclusion body myopathy with Paget's disease of the bone, frontotemporal dementia and amyotrophic lateral sclerosis, even in patients carrying the same mutation. We screened a cohort of 48 patients with familial frontotemporal dementia (FTD) negative for MAPT, GRN, and C9orf72 mutations for other known FTD genes by using whole exome sequencing. In addition, we carried out targeted sequencing of a cohort of 37 patients with frontotemporal lobar degeneration with Transactive response DNA-binding protein 43 (TDP-43) subtype from the Netherlands Brain bank. Two novel (p.Thr262Ser and p.Arg159Ser) and one reported (p.Met158Val) VCP mutations in three patients with a clinical diagnosis of FTD were identified, and were absence in population-match controls. All three patients presented with behavioral changes, with additional semantic deficits in one. No signs of Paget or muscle disease were observed. Pathological examination of the patient with VCP p.Arg159Ser mutation showed numerous TDP-43 immunoreactive (IR) neuronal intranuclear inclusions (NII) and dystrophic neurites (DN), while a lower number of NII and DN were observed in the patient with the VCP p.Thr262Ser mutation. Pathological findings of both patients were consistent with FTLD-TDP subtype D. Furthermore, only rare VCP-IR NII was observed in both cases. Our study expands the clinical heterogeneity of VCP mutations carriers, and indicates that other additional factors, such as genetic modifiers, may determine the clinical phenotype.

A Three-Factor Structure of Cognitive Functioning Among Unimpaired Carriers and Non-Carriers of Autosomal-Dominant Alzheimer's Disease. - Guzmán-Vélez, Edmarie; Jaimes, Sehily; Aguirre-Acevedo, Daniel C; Norton, Daniel J; Papp, Kathryn V; Amariglio, Rebecca; Rentz, Dorene; Baena, Ana; Henao, Eliana; Tirado, Victoria; Munoz, Claudia; Giraldo, Margarita; et al. (J Alzheimers Dis, 2018)
BACKGROUND: There is a need to find cognitive markers that can help identify individuals at risk for Alzheimer's disease (AD), and that can be used to reliably measure cognitive decline. OBJECTIVE: We tested whether a theoretically driven three-factor structure would characterize cognitive functioning in individuals who are genetically-determined to develop AD due to a mutation in Presenilin-1 (PSEN1) gene. We also examined whether these factors could distinguish cognitively unimpaired PSEN1 mutation carriers from age-matched non-carrier family members. METHODS: 1,395 cognitively unimpaired members of a Colombian kindred with the PSEN1 E280A mutation were included in the study. A confirmatory factor analysis examined the fit of the three-factor model comprising episodic memory (MMSE memory recall, CERAD-COL Word list recall, and Constructional praxis recall), executive function (Phonemic fluency and WCST perseverative errors), and psychomotor processing speed (TMT-A and WAIS-III Digit Symbol). RESULTS: The three-factor model provided an excellent fit for all participants (p = 0.24; RMSEA = 0.01). Further, the episodic memory (p = 0.0004, d = 0.25) and executive functioning (p = 0.001, d = 0.18) factors distinguished cognitively unimpaired carriers from non-carriers. The episodic memory factor provided the earliest indication of preclinical cognitive decline at 35 years of age, nine years before individuals' estimated age of clinical onset. CONCLUSIONS: The three theoretically derived cognitive factors provide a reliable measure of cognition and may be useful for the early detection of AD, as well as for measuring disease progression. However, longitudinal studies are needed to confirm that these factors can be used to track the progression of cognitive decline in preclinical AD.

Tocotrienol-Rich Fraction of Palm Oil Improves Behavioral Impairments and Regulates Metabolic Pathways in AβPP/PS1 Mice. - Durani, Lina Wati; Hamezah, Hamizah Shahirah; Ibrahim, Nor Faeizah; Yanagisawa, Daijiro; Nasaruddin, Muhammad Luqman; Mori, Masaki; Azizan, Kamalrul Azlan; Damanhuri, Hanafi Ahmad; Makpol, Suzana; Wan Ngah, Wan Zurinah; Tooyama, Ikuo (J Alzheimers Dis, 2018)
We have recently shown that the tocotrienol-rich fraction (TRF) of palm oil, a mixture of vitamin E analogs, improves amyloid pathology in vitro and in vivo. However, precise mechanisms remain unknown. In this study, we examined the effects of long-term (10 months) TRF treatment on behavioral impairments and brain metabolites in (15 months old) AβPP/PS1 double transgenic (Tg) Alzheimer's disease (AD) mice. The open field test, Morris water maze, and novel object recognition tasks revealed improved exploratory activity, spatial learning, and recognition memory, respectively, in TRF-treated Tg mice. Brain metabolite profiling of wild-type and Tg mice treated with and without TRF was performed using ultrahigh performance liquid chromatography (UHPLC) coupled to high-resolution accurate mass (HRAM)-orbitrap tandem mass spectrometry (MS/MS). Metabolic pathway analysis found perturbed metabolic pathways that linked to AD. TRF treatment partly ameliorated metabolic perturbations in Tg mouse hippocampus. The mechanism of this pre-emptive activity may occur via modulation of metabolic pathways dependent on Aβ interaction or independent of Aβ interaction.

Total MRI Small Vessel Disease Burden Correlates with Cognitive Performance, Cortical Atrophy, and Network Measures in a Memory Clinic Population. - Banerjee, Gargi; Jang, Hyemin; Kim, Hee Jin; Kim, Sung Tae; Kim, Jae Seung; Lee, Jae Hong; Im, Kiho; Kwon, Hunki; Lee, Jong Min; Na, Duk L; Seo, Sang Won; Werring, David John (J Alzheimers Dis, 2018)
BACKGROUND: Recent evidence suggests that combining individual imaging markers of cerebral small vessel disease (SVD) may more accurately reflect its overall burden and better correlate with clinical measures. OBJECTIVE: We wished to establish the clinical relevance of the total SVD score in a memory clinic population by investigating the association with SVD score and cognitive performance, cortical atrophy, and structural network measures, after adjusting for amyloid-β burden. METHODS: We included 243 patients with amnestic mild cognitive impairment (MCI), Alzheimer's disease dementia, subcortical vascular MCI, or subcortical vascular dementia. All underwent MR and [11C] PiB-PET scanning and had standardized cognitive testing. Multiple linear regression was used to evaluate the relationships between SVD score and cognition, cortical thickness, and structural network measures. Path analyses were performed to evaluate whether network disruption mediates the effects of SVD score on cortical thickness and cognition. RESULTS: Total SVD score was associated with the performance of frontal (β - 4.31, SE 2.09, p = 0.040) and visuospatial (β - 0.95, SE 0.44, p = 0.032) tasks, and with reduced cortical thickness in widespread brain regions. Total SVD score was negatively correlated with nodal efficiency, as well as changes in brain network organization, with evidence of reduced integration and increasing segregation. Path analyses showed that the associations between SVD score and frontal and visuospatial scores were partially mediated by decreases in their corresponding nodal efficiency and cortical thickness. CONCLUSION: Total SVD burden has clinical relevance in a memory clinic population and correlates with cognition, and cortical atrophy, as well as structural network disruption.

Trajectories of Physiological Brain Aging and Related Factors in People Aged from 20 to over-80. - Lee, Jin San; Kim, Seonwoo; Yoo, Heejin; Park, Seongbeom; Jang, Young Kyoung; Kim, Hee Jin; Kim, Ko Woon; Kim, Yeshin; Jang, Hyemin; Park, Key-Chung; Yaffe, Kristine; Yang, Jin-Ju; et al. (J Alzheimers Dis, 2018)
BACKGROUND/OBJECTIVE: In this study, we investigated a long-term trajectory of brain aging (from the 20 s to over-80) in cognitively normal (CN) individuals. We further determined whether differences in sex, education years, and apolipoprotein E ε 4 status affect age-related cortical thinning. METHODS: A total of 2,944 CN individuals who underwent high-resolution (3.0-Tesla) magnetic resonance imaging were included in this study. Cortical thickness was measured using a surface-based method. Multiple linear regression analyses were performed to evaluate age-related cortical thinning and related factors. RESULTS: Compared to those in their 20 s/30 s, participants in their 40 s showed thinning primarily in the medial and lateral frontal and inferior parietal regions, and cortical thinning occurred across most of the cortices with increasing age. Notably, the precuneus, inferior temporal and lateral occipital regions were relatively spared until later in life. Male and lower education years were associated with greater cortical thinning with distinct regional specificity. CONCLUSION: Our findings provide an important clue to understanding the mechanism of age-related cognitive decline and new strategies for preventing the acceleration of pathological brain aging.

Traumatic Brain Injury and Age of Onset of Dementia with Lewy Bodies. - Nguyen, Trung P; Schaffert, Jeff; LoBue, Christian; Womack, Kyle B; Hart, John; Cullum, C Munro (J Alzheimers Dis, 2018)
BACKGROUND: Traumatic brain injury (TBI) with loss of consciousness (LOC) has been associated with earlier onset of mild cognitive impairment, frontotemporal dementia, Parkinson's disease, and Alzheimer's disease (AD), but has not been examined as a risk factor for earlier onset of dementia with Lewy bodies (DLB). OBJECTIVE: The purpose of this study was to assess the association between a history of TBI and the age of onset of DLB. METHOD: Data from 576 subjects with a clinical diagnosis of DLB were obtained from the National Alzheimer's Coordinating Center (NACC). Analyses of Covariance examined whether self-reported history of remote TBI with LOC (i.e., >1 year prior to the first Alzheimer's Disease Center visit) was associated with earlier DLB symptom onset. RESULTS: Controlling for sex, those with a history of remote TBI had an approximately 1.5-year earlier clinician-estimated age of onset (F = 0.87, p = 0.35) and 0.75-years earlier age of diagnosis (F = 0.14, p = 0.71) of DLB compared to those without a history of TBI, though the differences did not reach statistical significance. Analysis of subjects with autopsy-confirmed diagnoses was underpowered due to the low number of TBI+ subjects. CONCLUSIONS: Remote TBI with LOC was not significantly associated with DLB onset, despite being a significant risk factor for cognitive decline and earlier age of onset in other neurodegenerative conditions. Replication of these results using a larger cohort of DLB subjects with and without a TBI history who have undergone autopsy is indicated, as our TBI+ subjects did show a slightly earlier onset of about 1.5 years. Further investigations into other potential DLB risk factors are also warranted.

The Uniform Data Set, Czech Version: Normative Data in Older Adults from an International Perspective. - Nikolai, Tomas; Stepankova, Hana; Kopecek, Miloslav; Sulc, Zdenek; Vyhnálek, Martin; Bezdicek, Ondrej (J Alzheimers Dis, 2018)
BACKGROUND: Outside of the United States, international perspectives on normative data for neuropsychological test performance, within diverse populations, have been scarce. The neuropsychological test battery from the Uniform Data Set (UDS) of the Alzheimer's Disease Centers (ADC) program of the United States National Institute on Aging (NIA) is one of the most sensitive batteries for the evaluation of both normal cognitive aging and pathological cognitive decline. OBJECTIVE: This study aimed to determine the feasibility of the Czech Neuropsychological Test Battery from the Uniform Data Set (UDS-Cz 2.0), while also evaluating the results obtained from an international perspective. METHODS: This paper describes data from 520 cognitively normal participants. Regression analyses were used to describe the influence of demographic variables on UDS-Cz test performance. RESULTS: Cognitive performance on all measures declined with age, with patient education level serving as a protective factor. Therefore, the present study provides normative data for the UDS-Cz, adjusted for the demographic variables of age and education. CONCLUSION: The present study determines the psychometric properties of the UDS-Cz and establishes normative values in the aging Czech population, which can be used in clinical settings.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Czech Republic; Female; Humans; Internationality; Male; Middle Aged; National Institute on Aging (U.S.); Neuropsychological Tests; Psychometrics; Reference Values; Regression Analysis; United States

Urine-Based Biomarkers for Alzheimer's Disease Identified Through Coupling Computational and Experimental Methods. - Yao, Fang; Hong, Xiaoyu; Li, Shuiming; Zhang, Yan; Zhao, Qing; Du, Wei; Wang, Yong; Ni, Jiazuan (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a chronic neurodegenerative disorder contributing to nearly 70% of dementia cases. However, no diagnostic protein biomarkers are available in urine. In this study, we combined computational and experimental methods to identify urinary biomarkers for AD. First, by analyzing brain tissue-based gene expression data of AD, 2,754 differentially expressed genes were identified, 559 of which were predicted to encode urine-excretory proteins that might act as candidate protein biomarkers of AD. GO enrichment analyses implied that they were mainly involved in microtubule-based process, myelin sheath, and calcium ion binding, suggesting that they might be associated with AD pathogenesis. In order to verify these proteins in urine, an iTRAQ experiment was carried out to analyze urine samples from AD patients and healthy controls, and 15 proteins were detected. Based on the expression changes of these proteins, 4 proteins were chosen for further validation by ELISA experiment, and SPP1, GSN, and IGFBP7 were found to be differentially expressed in the urine of AD patients. After a literature survey, we found that they were involved in AD pathophysiology and might serve as new urine biomarkers for AD. To our knowledge, this is the first time that urine biomarkers for AD were identified by combining computational and experimental methods. Furthermore, this is the first time SPP1, GSN, and IGFBP7 have been reported as potential urine protein biomarkers for AD. Therefore, our findings might provide significant guidance for finding early biomarkers of AD in urine.

Utility of the LIBRA Index in Relation to Cognitive Functioning in a Clinical Health Seeking Sample. - Pons, Anke; LaMonica, Haley M; Mowszowski, Loren; Köhler, Sebastian; Deckers, Kay; Naismith, Sharon L (J Alzheimers Dis, 2018)
BACKGROUND: Dementia prevalence is expected to increase substantially over the next few decades. Since there is currently no cure for dementia available, there is an urgent need for the early identification of individuals at high risk for dementia, so that primary and secondary prevention strategies can be implemented. Recently, the LIfestyle for BRAin health (LIBRA) index was developed as a new dementia risk algorithm. It specifically focuses on modifiable risk and protective factors that can be targeted in midlife. OBJECTIVE: The objective of this study was to evaluate the LIBRA index in relation to markers of cognitive functioning in a clinical, health-seeking sample of community-based older adults. METHODS: 484 participants (mean age 62.7 years) were recruited from the Healthy Brain Ageing Clinic at the Brain and Mind Centre, Sydney. Participants underwent comprehensive clinical and neuropsychological assessment and completed a self-report survey pack. Participants were rated via consensus as having either subjective cognitive complaints (SCC) or meeting criteria for mild cognitive impairment (MCI). The LIBRA score was calculated based on 11 available risk and protective factors. RESULTS: 65.4% of the sample met criteria for MCI. People with MCI showed a significantly higher LIBRA score compared to people with SCC. Furthermore, multiple cognitive domains, in particular executive functioning, were associated with a higher LIBRA score, with stronger correlations in people with MCI. CONCLUSION: The LIBRA index might be a useful tool to determine lifestyle-attributable risk of cognitive decline in an older health-seeking population, including people with MCI.

Vascular Effects on Depressive Symptoms in Cognitive Impairment. - Kim, Yeshin; Jang, Hyemin; Kim, Seung Joo; Cho, Soo Hyun; Kim, Si Eun; Kim, Sung Tae; Kim, Hee Jin; Moon, Seung Hwan; Ewers, Michael; Im, Kiho; Kwon, Hunki; Na, Duk L; et al. (J Alzheimers Dis, 2018)
Late life depression is related to pathologic burdens, such as cerebral small vascular disease (CSVD) and amyloid, which are associated with brain network changes and cortical thinning. To examine the associations of various CSVD imaging markers, amyloid, and network changes with depression in cognitively impaired patients, we prospectively recruited 228 cognitively impaired patients having various degrees of amyloid and CSVD who underwent diffuse tensor image and PiB PET. Greater CSVD burden was associated with greater Geriatric Depression Scale (GDS) (white matter hyperintensities, WMH: p = 0.025, lacunes: p < 0.001) but not with amyloid (p = 0.095), and cortical thinning (p = 0.630) was not associated with greater GDS. The changes in white matter networks were related to GDS with decreasing integration (global efficiency: p < 0.001) and increasing segregation (clustering coefficient: p = 0.009). The network changes mediated the relationships of WMH and lacunes with GDS. Our findings provide insight to better understand how CSVD burdens contribute to depression in cognitively impaired patients having varying degrees of amyloid and vascular burdens.

Visual Processing of Emotional Faces is Preserved in Mild Cognitive Impairment. - McCade, Donna L; Guastella, Adam J; Chen, Nigel T M; Lewis, Simon J G; Naismith, Sharon L (J Alzheimers Dis, 2018)
BACKGROUND: Research suggests that deficits in emotion recognition are evident in individuals with amnestic mild cognitive impairment (aMCI), a group 'at risk' of developing dementia. The mechanisms underlying this deficit, however, are unclear. OBJECTIVE: In this study, we sought to determine whether there are alterations in the way in which individuals with MCI visually explore emotional facial stimuli. METHODS: Eighteen healthy older controls (mean age = 64.6 years) and 32 individuals with MCI were recruited including 18 with the non-amnestic multiple domain (naMCI-md) subtype (mean age = 63.8 years) and 14 with the amnestic multiple domain (aMCI-md) subtype (mean age = 67.9 years). All participants were given a novel eye-tracking paradigm to investigate eye gaze while viewing images of emotional faces on a computer screen. RESULTS: Analyses of eye gaze revealed no significant difference in the percentage of time that groups spent fixating on facial and peripheral facial regions when viewing emotional faces. All participants showed a relative preference for the eye region of faces relative to all other regions. Individuals with aMCI-md were found to be less accurate than controls and naMCI-md on emotion recognition measures. For naMCI-md individuals, significant relationships were found between efficiencies in visual scanning and increased fixation time on the eye region. CONCLUSIONS: Visual processing strategies adopted by aMCI-md individuals when exploring emotional faces do not significantly differ from those of healthy controls or naMCI-md individuals. This suggests that impaired facial emotion recognition in aMCI-md is not likely accounted for by visual processing differences, but rather may reflect an eroded ability to extract meaningful cues from the eye region.

White Matter Hyperintensities and Cognition in Mild Cognitive Impairment and Alzheimer's Disease: A Domain-Specific Meta-Analysis. - van den Berg, Esther; Geerlings, Mirjam I; Biessels, Geert Jan; Nederkoorn, Paul J; Kloppenborg, Raoul P (J Alzheimers Dis, 2018)
BACKGROUND: White matter hyperintensities (WMHs) are related to cognitive dysfunction in the general population. The clinical relevance of WMHs in patients with Alzheimer's disease (AD) and mild cognitive impairment (MCI) is, however, unclear. OBJECTIVE: This meta-analysis aimed to quantify the association of WMHs and specific cognitive domains in patients with MCI or AD. METHODS: PubMed (January 1990-January 2017) was searched for studies that used MRI to quantify WMHs, and measured cognitive functioning (≥1 predefined cognitive domain with ≥1 test) in a well-defined population of persons diagnosed with MCI or AD. Fischer's Z was used as the common metric for effect size. Modifying effects of demographics, MMSE, and WMH location were examined. RESULTS: Twelve cross-sectional studies on AD (total n = 1,370, median age 75 years) and 10 studies on MCI (9 cross-sectional, 1 longitudinal; total n = 2,286, median age 73 years) were included. The association between WMHs and overall cognition was significantly stronger for MCI (-0.25, -0.36 to -0.14) than for AD (-0.11, -0.14 to -0.08; QM = 10.7, p < 0.05). For both groups, largest effect sizes were found in attention and executive functions (-0.26, -0.36 to -0.15) and processing speed (-0.21, -0.35 to -0.12). No significant modifying effects of age and gender were found. CONCLUSION: WMHs have a medium-sized association with different cognitive functions in patients with MCI and a small, but statistically significant, association with cognition in AD. These result underscore the role of co-occurring vascular brain damage in MCI and AD.

18F-AV-1451 PET Imaging in Three Patients with Probable Cerebral Amyloid Angiopathy. - Kim, Hee Jin; Cho, Hanna; Werring, David J; Jang, Young Kyoung; Kim, Yeo Jin; Lee, Jin San; Lee, Juyoun; Jun, Soomin; Park, Seongbeom; Ryu, Young Hoon; Choi, Jae Yong; Cho, Young Seok; et al. (J Alzheimers Dis, 2017)
Cerebrovascular deposition of amyloid-β, known as cerebral amyloid angiopathy (CAA), is associated with MRI findings of lobar hemorrhage, cerebral microbleeds, and cortical superficial siderosis. Although pathological studies suggest that tau may co-localize with vascular amyloid, this has not yet been investigated in CAA in vivo. Three patients with probable CAA underwent 11C-Pittsburgh Compound B (PiB) PET or 18F-florbetaben PET to evaluate amyloid burden, and 18F-AV-1451 PET to evaluate paired helical filament tau burden. Regions that had cerebral microbleeds or cortical superficial siderosis largely overlapped with those showing increased 18F-AV-1451. Our preliminary study raised the possibility that lobar cerebral microbleeds, and cortical superficial siderosis, which are characteristic markers of vascular amyloid, may be associated with local production of paired helical filament tau.
Keywords: Aged; Aged, 80 and over; Aniline Compounds; Brain; Carbolines; Cerebral Amyloid Angiopathy; Female; Humans; Image Processing, Computer-Assisted; Male; Positron-Emission Tomography; Thiazoles

Abnormalities of Cortical Neural Synchronization Mechanisms in Subjects with Mild Cognitive Impairment due to Alzheimer's and Parkinson's Diseases: An EEG Study. - Babiloni, Claudio; Del Percio, Claudio; Lizio, Roberta; Noce, Giuseppe; Cordone, Susanna; Lopez, Susanna; Soricelli, Andrea; Ferri, Raffaele; Pascarelli, Maria Teresa; Nobili, Flavio; Arnaldi, Dario; Famá, Francesco; et al. (J Alzheimers Dis, 2017)
The aim of this retrospective and exploratory study was that the cortical sources of resting state eyes-closed electroencephalographic (rsEEG) rhythms might reveal different abnormalities in cortical neural synchronization in groups of patients with mild cognitive impairment due to Alzheimer's disease (ADMCI) and Parkinson's disease (PDMCI) as compared to healthy subjects. Clinical and rsEEG data of 75 ADMCI, 75 PDMCI, and 75 cognitively normal elderly (Nold) subjects were available in an international archive. Age, gender, and education were carefully matched in the three groups. The Mini-Mental State Evaluation (MMSE) was matched between the ADMCI and PDMCI groups. Individual alpha frequency peak (IAF) was used to determine the delta, theta, alpha1, alpha2, and alpha3 frequency band ranges. Fixed beta1, beta2, and gamma bands were also considered. eLORETA estimated the rsEEG cortical sources. Receiver operating characteristic curve (ROC) classified these sources across individuals. Results showed that compared to the Nold group, the posterior alpha2 and alpha3 source activities were more abnormal in the ADMCI than the PDMCI group, while the parietal delta source activities were more abnormal in the PDMCI than the ADMCI group. The parietal delta and alpha sources correlated with MMSE score and correctly classified the Nold and diseased individuals (area under the ROC = 0.77-0.79). In conclusion, the PDMCI and ADMCI patients showed different features of cortical neural synchronization at delta and alpha frequencies underpinning brain arousal and vigilance in the quiet wakefulness. Future prospective cross-validation studies will have to test these rsEEG markers for clinical applications and drug discovery.

Adult-Onset Epilepsy in Presymptomatic Alzheimer's Disease: A Retrospective Study. - DiFrancesco, Jacopo C; Tremolizzo, Lucio; Polonia, Valeria; Giussani, Giorgia; Bianchi, Elisa; Franchi, Carlotta; Nobili, Alessandro; Appollonio, Ildebrando; Beghi, Ettore; Ferrarese, Carlo (J Alzheimers Dis, 2017)
BACKGROUND: The prevalence of epilepsy with onset in adulthood increases with age, mainly due to the accumulation of brain damage. However, a significant proportion of patients experience seizures of unknown cause. Alzheimer's disease (AD) is associated with an increased risk of seizures. Seizure activity is interpreted as a secondary event related to hyperexcitability caused by amyloid-β aggregation. OBJECTIVE: Since neurodegenerative processes begin several years before clinical symptoms, epilepsy could be more frequent in the presymptomatic stages of dementia. METHODS: We retrospectively reviewed the prevalence of epilepsy of unknown origin with adult onset before cognitive decline in a large cohort of AD patients (EPS-AD) recruited based on clinical and neuropsychological data. Data of patients with epilepsy followed by AD were compared with two control groups: patients with AD without seizures (no EPS-AD) and a large reference population (RP). RESULTS: In AD patients, the prevalence of epilepsy of unknown origin, with onset in the adulthood before cognitive decline is 17.1 times higher compared with the RP (95% CI: 10.3-28.3). In EPS-AD, seizures begin on average 4.6 years (median 2.0) before the onset of cognitive symptoms and cognitive decline starts 3.6 years earlier compared with noEPS-AD. CONCLUSIONS: Neurodegenerative processes of dementia could play a key role in the pathogenesis of epilepsy in a subgroup of individuals intended to develop cognitive decline. Adult-onset epilepsy of undefined cause could thus represent a risk factor for the ongoing neurodegenerative damage, even preceding by years the onset of clinical symptoms of dementia.

Age and Graphomotor Decision Making Assessed with the Digital Clock Drawing Test: The Framingham Heart Study. - Piers, Ryan J; Devlin, Kathryn N; Ning, Boting; Liu, Yulin; Wasserman, Ben; Massaro, Joseph M; Lamar, Melissa; Price, Catherine C; Swenson, Rod; Davis, Randall; Penney, Dana L; Au, Rhoda; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Digital Clock Drawing Test (dCDT) technology enables the examination of detailed neurocognitive behavior as behavior unfolds in real time; a capability that cannot be obtained using a traditional pen and paper testing format. OBJECTIVE: Parameters obtained from the dCDT were used to investigate neurocognitive constructs related to higher-order neurocognitive decision making and information processing speed. The current research sought to determine the effect of age as related to combined motor and non-motor components of drawing, and higher-order decision making latencies. METHODS: A large group of stroke- and dementia- free Framingham Heart Study participants were administered the dCDT to command and copy with hands set for "10 after 11". Six age groups (age range 28-98) were constructed. RESULTS: Differences between age groups were found for total time to completion, total pen stroke count, and higher-order decision making latencies in both command and copy test conditions. CONCLUSION: Longer age-related decision making latencies may reflect a greater need for working memory and increased self-monitoring in older subjects. These latency measures have potential to serve as neurocognitive biomarkers of Alzheimer's disease and other insidious neurodegenerative disorders.

Algoplus® Scale in Older Patients with Dementia: A Reliable Real-World Pain Assessment Tool. - Monacelli, Fiammetta; Signori, Alessio; Roffredo, Laura; Pace, Katiuscia; Nencioni, Alessio; Pickering, Gisele; Nicolas, Macian; Odetti, Patrizio (J Alzheimers Dis, 2017)
Pain is still a neglected clinical issue in elderly people with dementia and/or communicative disorders, with an unacceptable higher rate of under diagnosis and under treatment. Cognitive deficit and emotional and psychological disturbances entangle pain symptoms, affecting patient self-report. So far, observational pain tools do not have fully adequate clinimetric properties and quality requirements for easy-to-use daily rating. Older patients with dementia represent a clinical challenge. The assessment of pain is important for improving clinical outcomes, such as functional status, frailty trajectories, comorbidity, and quality of life. The PAINAID scale appears to be the most accurate pain tool in people with dementia along with the Algoplus® scale, a recently developed tool to rapidly assess acute pain in hospitals settings. The present study aimed to assess the clinimetric properties of the Algoplus®, as compared to PAINAID, for detecting acute pain in a real-world cohort of hospitalized older patients with dementia.

Alzheimer's Disease Diagnosis Relies on a Twofold Clinical-Biological Algorithm: Three Memory Clinic Case Reports. - Levy Nogueira, Marcel; Samri, Dalila; Epelbaum, Stéphane; Lista, Simone; Suppa, Per; Spies, Lothar; Hampel, Harald; Dubois, Bruno; Teichmann, Marc (J Alzheimers Dis, 2017)
The International Working Group recently provided revised criteria of Alzheimer's disease (AD) proposing that the diagnosis of typical amnesic AD should be established by a clinical-biological signature, defined by the phenotype of an "amnesic syndrome of the hippocampal type" (ASHT) combined with positive in vivo evidence of AD pathophysiology in the cerebrospinal fluid (CSF) or on amyloid PET imaging. The application and clinical value of this refined diagnostic algorithm, initially intended for research purposes, is explored in three memory clinic cases presenting with different cognitive profiles including an ASHT, hippocampal atrophy, and CSF AD-biomarker data. The case reports highlight that the isolated occurrence of one of the two proposed AD criteria, ASHT or positive pathophysiological markers, does not provide a reliable diagnosis of typical AD. It is proposed that the twofold diagnostic IWG algorithm can be applied and operationalized in memory clinic settings to improve the diagnostic accuracy of typical amnesic AD in clinical practice.

Analytical Strategy to Prioritize Alzheimer's Disease Candidate Genes in Gene Regulatory Networks Using Public Expression Data. - Kawalia, Shweta Bagewadi; Raschka, Tamara; Naz, Mufassra; de Matos Simoes, Ricardo; Senger, Philipp; Hofmann-Apitius, Martin (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) progressively destroys cognitive abilities in the aging population with tremendous effects on memory. Despite recent progress in understanding the underlying mechanisms, high drug attrition rates have put a question mark behind our knowledge about its etiology. Re-evaluation of past studies could help us to elucidate molecular-level details of this disease. Several methods to infer such networks exist, but most of them do not elaborate on context specificity and completeness of the generated networks, missing out on lesser-known candidates. In this study, we present a novel strategy that corroborates common mechanistic patterns across large scale AD gene expression studies and further prioritizes potential biomarker candidates. To infer gene regulatory networks (GRNs), we applied an optimized version of the BC3Net algorithm, named BC3Net10, capable of deriving robust and coherent patterns. In principle, this approach initially leverages the power of literature knowledge to extract AD specific genes for generating viable networks. Our findings suggest that AD GRNs show significant enrichment for key signaling mechanisms involved in neurotransmission. Among the prioritized genes, well-known AD genes were prominent in synaptic transmission, implicated in cognitive deficits. Moreover, less intensive studied AD candidates (STX2, HLA-F, HLA-C, RAB11FIP4, ARAP3, AP2A2, ATP2B4, ITPR2, and ATP2A3) are also involved in neurotransmission, providing new insights into the underlying mechanism. To our knowledge, this is the first study to generate knowledge-instructed GRNs that demonstrates an effective way of combining literature-based knowledge and data-driven analysis to identify lesser known candidates embedded in stable and robust functional patterns across disparate datasets.

Anomalous White Matter Structure and the Effect of Age in Down Syndrome Patients. - Fenoll, Raquel; Pujol, Jesus; Esteba-Castillo, Susanna; de Sola, Susana; Ribas-Vidal, Núria; García-Alba, Javier; Sánchez-Benavides, Gonzalo; Martínez-Vilavella, Gerard; Deus, Joan; Dierssen, Mara; Novell-Alsina, Ramón; de la Torre, Rafael (J Alzheimers Dis, 2017)
BACKGROUND: Neural tissue alterations in Down syndrome are fully expressed at relatively late developmental stages. In addition, there is an early presence of neurodegenerative changes in the late life stages. OBJECTIVE: The aims of this study were both to characterize white matter abnormalities in the brain of adult Down syndrome patients using diffusion tensor imaging (DTI) and to investigate whether degenerative alterations in white matter structure are detectable before dementia is clinically evident. METHODS: Forty-five adult non-demented Down syndrome patients showing a wide age range (18-52 years) and a matched 45-subject control group were assessed. DTI fractional anisotropy (FA) brain maps were generated and selected cognitive tests were administered. RESULTS: Compared with healthy controls, non-demented Down syndrome patients showed lower DTI FA in white matter involving the major pathways, but with more severe alterations in the frontal-subcortical circuits. White matter FA decreased with age at a similar rate in both DS and control groups. CONCLUSIONS: Our results contribute to characterizing the expression of white matter structural alterations in adult Down syndrome. However, an accelerated aging effect was not demonstrated, which may suggest that the FA measurements used are not sufficiently sensitive or, alternatively, age-related white matter neurodegeneration is not obvious prior to overt clinical dementia.

Antibodies to Signaling Molecules and Receptors in Alzheimer's Disease are Associated with Psychomotor Slowing, Depression, and Poor Visuospatial Function. - Giil, Lasse M; Vedeler, Christian A; Kristoffersen, Einar K; Nordrehaug, Jan Erik; Heidecke, Harald; Dechend, Ralf; Schulze-Forster, Kai; Muller, Dominik N; von Goetze, Victoria S; Cabral-Marques, Otavio; Riemekasten, Gabriela; Vogelsang, Petra; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is associated with several antibodies as well as signaling molecules and receptors. These may be detrimental in the presence of a disrupted blood-brain barrier (BBB). OBJECTIVE: To investigate whether the levels of antibodies toward 33 signaling molecules involved in neurotransmitter, vascular, and immune functions were associated with AD and, within the AD group; cognitive function and mood. METHODS: Antibodies in sera from patients with mild AD [(n = 91) defined as a Mini-Mental State Examination ≥ 20 or a Clinical Dementia Rating Scale≤1] and healthy controls (n = 102) were measured with enzyme-linked immunosorbent assays. Levels in AD and controls were compared by Mann-Whitney test. In the AD group, associations between antibodies and psychometric test scores were analyzed by robust regression. The false discovery threshold was set to 0.05. RESULTS: Antibodies to serotonin receptors [5-HT2AR (effect size (r) = 0.21, p = 0.004), 5-HT2CR (r = 0.25, p = 0.0005) and 5-HT7R (r = 0.21, p = 0.003)], vascular endothelial growth factor receptor 1 [VEGFR1 (r = 0.29, p < 0.001)] and immune-receptors (Stabilin-1 (r = 0.23, p = 0.001) and C5aR1 (r = 0.21, p = 0.004) were higher in AD. Psychomotor speed was associated with D1R-abs (β 0.49, p < 0.001), depression with ETAR-abs (β 0.31, p < 0.001), and visuospatial function with 5-HT1AR-abs (β 0.27, p = 0.004) despite similar antibody levels compared to controls. CONCLUSIONS: Antibody levels to VEGFR1, serotonergic receptors, and receptors in the immune system were increased in AD. Antibodies at similar levels as in controls were associated cognitive dysfunction and depression in AD.

Antihypertensive Treatment is associated with MRI-Derived Markers of Neurodegeneration and Impaired Cognition: A Propensity-Weighted Cohort Study. - Edwards, Jodi D; Ramirez, Joel; Callahan, Brandy L; Tobe, Sheldon W; Oh, Paul; Berezuk, Courtney; Lanctôt, Krista; Swardfager, Walter; Nestor, Sean; Kiss, Alexander; Strother, Stephen; Black, Sandra E (J Alzheimers Dis, 2017)
BACKGROUND: Hypertension is an important risk factor for Alzheimer's disease (AD) and cerebral small vessel disease. Angiotensin converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) are common anti-hypertensive treatments, but have differential effects on cortical amyloid. OBJECTIVE: The objective of this study was to evaluate associations between anti-hypertensive treatment, brain volume, and cognition, using a propensity-weighted analysis to account for confounding by indication. METHODS: We identified a cohort of normal elderly adults and individuals with mild cognitive impairment (MCI) or AD (N = 886; mean age = 75.0) from the Alzheimer's Disease Neuroimaging Initiative. Primary outcomes were brain parenchymal fraction, total hippocampal volume, and white matter hyperintensity (WMH) volume. Secondary outcomes were standardized scores on neuropsychological tests. Propensity-weighted adjusted multivariate linear regression was used to estimate associations between anti-hypertensive treatment class and MRI volumes and cognition. RESULTS: Individuals treated with ARBs showed larger hippocampal volumes (R2 = 0.83, p = 0.05) and brain parenchymal fraction (R2 = 0.83, p = 0.01) than those treated with ACEIs. When stratified by diagnosis, this effect remained only in normal elderly adults and MCI patients, and a significant association between ARBs and lower WMH volume (R2 = 0.83, p = 0.03) emerged for AD patients only. ARBs were also associated with significantly better performance on tests of episodic and verbal memory, language, and executive function (all p < 0.05). CONCLUSIONS: Findings are consistent with evidence for a neuroprotective effect of treatment with ARBs for brain structure and cognition. This study has potential implications for the treatment of hypertension, particularly in elderly adults at risk of cognitive decline and AD.

Apolipoprotein E Isoforms Differentially Regulate Alzheimer's Disease and Amyloid-β-Induced Inflammatory Response in vivo and in vitro. - Dorey, Evan; Bamji-Mirza, Michelle; Najem, Dema; Li, Yan; Liu, Hong; Callaghan, Debbie; Walker, Douglas; Lue, Lih-Fen; Stanimirovic, Danica; Zhang, Wandong (J Alzheimers Dis, 2017)
Neuroinflammation plays a critical role in neuronal dysfunction and death of Alzheimer's disease (AD). ApoE4 is a major risk factor of AD, while ApoE2 is neuroprotective. Little is known about the roles of ApoE isoforms in the neuroinflammation seen in AD. Their roles and mechanisms in Aβ-induced/neuroinflammation were investigated in this study using in vivo and in vitro models. Rat astrocytes were treated with lipid-poor recombinant hApoE and/or Aβ42. Mouse astrocyte lines-expressing lipidated hApoE were treated with Aβ42 and/or vitamin D receptor (VDR) agonist, 1α,25-dihydroxyvitamin D3. Cells and media were harvested for cytokine ELISA, RNA isolated for qRT-PCR, and nuclear protein for transcription factor (TF) arrays and EMSA. hApoE-transgenic and AD mice were mated to generate hApoE2/AD and hApoE4/AD mice. Mice were euthanized at 6 months of age. Brain tissues were collected for cytokine ELISA array, Aβ ELISA, immunoblotting, and immunohistochemistry. hApoE4/AD mice had significantly higher levels of inflammatory cytokines than hApoE2/AD mice. Lipidated hApoE4 significantly promoted inflammatory gene expression induced by Aβ42 but not recombinant hApoE4 in astrocytes as compared to controls. Lipidated hApoE3 provided a certain degree of protection against Aβ42-induced inflammatory response but not recombinant hApoE3 as compared to controls. Both lipidated and recombinant hApoE2 provided protection against Aβ42-induced inflammatory response compared to controls. TF array revealed that ApoE2 strongly activated VDR in Aβ42-treated astrocytes. Application of 1α,25-dihydroxyvitamin D3 completely inhibited Aβ-induced inflammatory gene expression in hApoE4-expressing astrocytes. The results suggest that ApoE4 promotes, but ApoE2 inhibits, AD/Aβ-induced neuroinflammation via VDR signaling. Targeting VDR signaling or active form of VD3 may relieve AD neuroinflammation or/and neurodegeneration.

Apomorphine Therapy for Neuronal Insulin Resistance in a Mouse Model of Alzheimer's Disease. - Nakamura, Norimichi; Ohyagi, Yasumasa; Imamura, Tomohiro; Yanagihara, Yuki T; Iinuma, Kyoko M; Soejima, Naoko; Murai, Hiroyuki; Yamasaki, Ryo; Kira, Jun-Ichi (J Alzheimers Dis, 2017)
Apomorphine (APO) promotes intraneuronal amyloid-β (Aβ) degradation and improves memory function in an Alzheimer's disease (AD) model, 3xTg-AD mice. Since insulin resistance is increased in AD neurons, we investigated the effects of APO on brain insulin resistance in 3xTg-AD mice at early and late stages. After 1-month subcutaneous injection of Apokyn® to 3xTg-AD mice at 6 or 12 months of age, memory function was significantly improved in both age groups. Protein levels of insulin-degrading enzyme (IDE), which is linked to insulin signaling and degrades Aβ, significantly increased in the 3xTg-AD mice brain compared with non-transgenic mice, and were further increased by APO. Protein levels of two types of serine-phosphorylated insulin receptor substrate-1 (IRS-1), pS616 and pS636/639, significantly decreased following APO treatment in the 13-month-old 3xTg-AD mice brain, suggesting improved brain insulin resistance. Immunostaining of the IDE, pS616 and pS636/639 IRS-1 demonstrated similar changes due to APO treatment. Thus, brain insulin resistance is considered an important therapeutic target in AD, and APO may provide improved neuronal insulin resistance.

APP Mutations in Cerebral Amyloid Angiopathy with or without Cortical Calcifications: Report of Three Families and a Literature Review. - Sellal, François; Wallon, David; Martinez-Almoyna, Laurent; Marelli, Cecilia; Dhar, Abhinav; Oesterlé, Héléne; Rovelet-Lecrux, Anne; Rousseau, Stéphane; Kourkoulis, Christina E; Rosand, Jon; DiPucchio, Zora Y; Frosch, Matthew; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Specific APP mutations cause cerebral amyloid angiopathy (CAA) with or without Alzheimer's disease (AD). OBJECTIVE: We aimed at reporting APP mutations associated with CAA, describe the clinical, cerebrospinal fluid AD biomarkers, and neuroimaging features, and compare them with the data from the literature. METHODS: We performed a retrospective study in two French genetics laboratories by gathering all clinical and neuroimaging data from patients referred for a genetic diagnosis of CAA with an age of onset before 66 years and fulfilling the other Boston revised criteria. We studied the segregation of mutations in families and performed a comprehensive literature review of all cases reported with the same APP mutation. RESULTS: We screened APP in 61 unrelated French patients. Three mutations, located in the Aβ coding region, were detected in five patients from three families: p.Ala692Gly (Flemish), p.Glu693Lys (Italian), and p.Asp694Asn (Iowa). Patients exhibited CAA and progressive cognitive impairment associated with cortical calcifications in the Iowa and Italian mutation carriers, but not the patient carrying the Flemish mutation. CONCLUSIONS: This is the first evidence of cortical calcification in patients with an APP mutation other than the Iowa mutation. We discuss the radiological, cerebrospinal fluid, and clinical phenotype of patients carrying these mutations in the literature.

Association between Cognitive Status before Surgery and Outcomes in Elderly Patients with Hip Fracture in a Dedicated Orthogeriatric Care Pathway. - Zerah, Lorene; Cohen-Bittan, Judith; Raux, Mathieu; Meziere, Anthony; Tourette, Cendrine; Neri, Christian; Verny, Marc; Riou, Bruno; Khiami, Frederic; Boddaert, Jacques (J Alzheimers Dis, 2017)
BACKGROUND: Dementia is associated with a worse prognosis of hip fracture, but the impact of a dedicated geriatric care pathway on the prognosis of these patients has not been evaluated. OBJECTIVE: According to the cognitive status before surgery, our main objective was to compare mortality rate at 6 months; secondary outcomes were to compare in-hospital complications, the risk of new institutionalization, and the ability to walk at 6 months. METHODS: Between 2009 and 2015, all patients (>70 years) admitted after hip fracture surgery into a dedicated unit of peri-operative geriatric care were included: patients with dementia (DP), without dementia (NDP), and with cognitive status not determined (CSND). Data are expressed as hazard ratio (HR) for multivariate cox analysis or odds ratio (OR) for multivariate logistic regression analysis and their 95% confidence interval (CI). RESULTS: We included 650 patients (86±6 years): 168 DP, 400 NDP, and 82 CSND. After adjustment for age, sex, comorbidities, polypharmacy, pre-fracture autonomy, time-to-surgery, and delirium, there were no significant differences for 6-month mortality (DP versus NDP: HR = 0.7[0.4-1.2], DP versus CSND: HR = 0.6[0.3-1.4], CSND versus NDP: HR = 0.8[0.4-1.7]); but DP and CSND were more likely to be newly institutionalized after 6 months compared to NDP (OR DP = 2.6[1.4-4.9], p = 0.003, OR CSND = 2.9[1.4-6.1], p = 0.004). 92% of population was walking after 6 months (63% with assistance): no difference was found between the three groups. CONCLUSION: In a dedicated geriatric care pathway, DP and CSND undergoing hip surgery have the same 6-month mortality and walking ability as NDP.

Association Between Later Life Lifestyle Factors and Alzheimer's Disease Biomarkers in Non-Demented Individuals: A Longitudinal Descriptive Cohort Study. - Reijs, Babette L R; Vos, Stephanie J B; Soininen, Hilkka; Lötjönen, Jyrki; Koikkalainen, Juha; Pikkarainen, Maria; Hall, Anette; Vanninen, Ritva; Liu, Yawu; Herukka, Sanna-Kaisa; Freund-Levi, Yvonne; Frisoni, Giovanni B; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Lifestyle factors have been associated with the risk of dementia, but the association with Alzheimer's disease (AD) remains unclear. OBJECTIVE: To examine the association between later life lifestyle factors and AD biomarkers (i.e., amyloid-β 1-42 (Aβ42) and tau in cerebrospinal fluid (CSF), and hippocampal volume) in individuals with subjective cognitive decline (SCD) and mild cognitive impairment (MCI). In addition, to examine the effect of later life lifestyle factors on developing AD-type dementia in individuals with MCI. METHODS: We selected individuals with SCD (n = 111) and MCI (n = 353) from the DESCRIPA and Kuopio Longitudinal MCI studies. CSF Aβ42 and tau concentrations were assessed with ELISA assay and hippocampal volume with multi-atlas segmentation. Lifestyle was assessed by clinical interview at baseline for: social activity, physical activity, cognitive activity, smoking, alcohol consumption, and sleep. We performed logistic and Cox regression analyses adjusted for study site, age, gender, education, and diagnosis. Prediction for AD-type dementia was performed in individuals with MCI only. RESULTS: Later life lifestyle factors were not associated with AD biomarkers or with conversion to AD-type dementia. AD biomarkers were strongly associated with conversion to AD-type dementia, but these relations were not modulated by lifestyle factors. Apolipoprotein E (APOE) genotype did not influence the results. CONCLUSIONS: Later life lifestyle factors had no impact on key AD biomarkers in individuals with SCD and MCI or on conversion to AD-type dementia in MCI.

Association between Mid-Regional Proadrenomedullin Levels and Progression of Deep White Matter Lesions in the Brain Accompanying Cognitive Decline. - Kuriyama, Nagato; Ihara, Masafumi; Mizuno, Toshiki; Ozaki, Etsuko; Matsui, Daisuke; Watanabe, Isao; Koyama, Teruhide; Kondo, Masaki; Tokuda, Takahiko; Tamura, Aiko; Yamada, Kei; Akazawa, Kentaro; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Adrenomedullin (ADM) is a vasoreactive physiological peptide with anti-inflammatory effects and vasodilative and immunomodulatory actions that is widely distributed throughout the vascular system of the brain. OBJECTIVE: To investigate mid-regional proADM (MR-proADM), a stable fragment of the ADM precursor, and cerebral deep white matter lesions (DWMLs) in association with cognitive decline. METHODS: The study participants were 288 patients (194 men, 94 women) who gave consent to participate in a 5-year longitudinal survey on arteriosclerosis from 2008 to 2013. The Fazekas classification system (Grade [G] 0 [normal] to G3 [severe]) was used for the evaluation of DWMLs on brain magnetic resonance imaging (MRI). In addition, all participants were asked to undergo cognitive function tests regarding word/letter fluency, the results of which were assessed for correlations with MR-proADM levels. RESULTS: MR-proADM levels significantly increased with DWML grade progression. The odds ratio for high MR-proADM levels was 3.08 (95% confidence interval: 1.49-5.17) in the groups graded G3 on brain MRI, suggesting that a high level of MR-proADM is an independent risk factor for DWMLs. A significant inverse correlation was observed between MR-proADM levels and cognitive test scores. MR-proADM levels were significantly increased in the G3 group in 2013 compared with 2008. CONCLUSION: MR-proADM levels were significantly different between the DWML groups and inversely correlated with cognitive function test scores, suggesting that high MR-proADM levels and DWMLs are associated with cognitive decline. Therefore, the MR-proADM level may be an effective candidate as a potential diagnostic surrogate marker of cognitive decline.

Association between Plasma Ceramides and Phosphatidylcholines and Hippocampal Brain Volume in Late Onset Alzheimer's Disease. - Kim, Min; Nevado-Holgado, Alejo; Whiley, Luke; Snowden, Stuart G; Soininen, Hilkka; Kloszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Thambisetty, Madhav; Dobson, Richard J B; Powell, John F; et al. (J Alzheimers Dis, 2017)
Lipids such as ceramides and phosphatidylcholines (PC) have been found altered in the plasma of Alzheimer's disease (AD) patients in a number of discovery studies. For this reason, the levels of 6 ceramides and 3 PCs, with different fatty acid length and saturation levels, were measured in the plasma from 412 participants (AD n = 205, Control n = 207) using mass spectrometry coupled with ultra-performance liquid chromatography. After this, associations with AD status, brain atrophy, and age-related effects were studied. In the plasma of AD participants, cross-sectional analysis revealed elevated levels of three ceramides (Cer16:0 p < 0.01, Cer18:0 p < 0.01, Cer24:1 p < 0.05). In addition, two PCs in AD plasma (PC36:5 p < 0.05, PC38:6 p < 0.05) were found to be depleted compared to the control group, with PC36:5 also associating with hippocampal atrophy (p < 0.01). Age-specific analysis further revealed that levels of Cer16:0, Cer18:0, and Cer20:0 were associated with hippocampal atrophy only in younger participants (age < 75, p < 0.05), while all 3 PCs did so in the older participants (age > 75, p < 0.05). PC36:5 was associated with AD status in the younger group (p < 0.01), while PC38:6 and 40:6 did so in the older group (p < 0.05). In this study, elevated ceramides and depleted PCs were found in the plasma from 205 AD volunteers. Our findings also suggest that dysregulation in PC and ceramide metabolism could be occurring in different stages of AD progression.

Associations of CAIDE Dementia Risk Score with MRI, PIB-PET measures, and cognition. - Stephen, Ruth; Liu, Yawu; Ngandu, Tiia; Rinne, Juha O; Kemppainen, Nina; Parkkola, Riitta; Laatikainen, Tiina; Paajanen, Teemu; Hänninen, Tuomo; Strandberg, Timo; Antikainen, Riitta; Tuomilehto, Jaakko; et al. (J Alzheimers Dis, 2017)
BACKGROUND: CAIDE Dementia Risk Score is the first validated tool for estimating dementia risk based on a midlife risk profile. OBJECTIVES: This observational study investigated longitudinal associations of CAIDE Dementia Risk Score with brain MRI, amyloid burden evaluated with PIB-PET, and detailed cognition measures. METHODS: FINGER participants were at-risk elderly without dementia. CAIDE Risk Score was calculated using data from previous national surveys (mean age 52.4 years). In connection to baseline FINGER visit (on average 17.6 years later, mean age 70.1 years), 132 participants underwent MRI scans, and 48 underwent PIB-PET scans. All 1,260 participants were cognitively assessed (Neuropsychological Test Battery, NTB). Neuroimaging assessments included brain cortical thickness and volumes (Freesurfer 5.0.3), visually rated medial temporal atrophy (MTA), white matter lesions (WML), and amyloid accumulation. RESULTS: Higher CAIDE Dementia Risk Score was related to more pronounced deep WML (OR 1.22, 95% CI 1.05-1.43), lower total gray matter (β-coefficient -0.29, p = 0.001) and hippocampal volume (β-coefficient -0.28, p = 0.003), lower cortical thickness (β-coefficient -0.19, p = 0.042), and poorer cognition (β-coefficients -0.31 for total NTB score, -0.25 for executive functioning, -0.33 for processing speed, and -0.20 for memory, all p < 0.001). Higher CAIDE Dementia Risk Score including APOE genotype was additionally related to more pronounced MTA (OR 1.15, 95% CI 1.00-1.30). No associations were found with periventricular WML or amyloid accumulation. CONCLUSIONS: The CAIDE Dementia Risk Score was related to indicators of cerebrovascular changes and neurodegeneration on MRI, and cognition. The lack of association with brain amyloid accumulation needs to be verified in studies with larger sample sizes.

Baseline Predictors of Antipsychotic Treatment Continuation and Response at Week 8 in Patients with Alzheimer's Disease with Psychosis or Aggressive Symptoms: An Analysis of the CATIE-AD Study. - Nagata, Tomoyuki; Nakajima, Shinichiro; Shinagawa, Shunichiro; Plitman, Eric; Nakayama, Kazuhiko; Graff-Guerrero, Ariel; Mimura, Masaru (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: The aim of the present study was to investigate predictors of atypical antipsychotic (AAP) treatment continuation and response by week 8 in patients with Alzheimer's disease (AD) who have psychotic/aggressive symptoms using the Clinical Antipsychotic Trials of Intervention Effectiveness-Alzheimer's Disease (CATIE-AD) dataset. METHODS: Clinical data was utilized from 421 AD outpatients with psychotic/aggressive symptoms who needed interventional treatment. Logistic regression analyses were performed to examine which baseline sociodemographic and clinical characteristics contributed to treatment 'continuation' and 'response', the latter of which was evaluated by the Clinical Global Impression of Change (CGI-C), Neuropsychiatric Inventory (NPI), and Brief Psychiatric Scale (BPRS). RESULTS: The treatment continuation rate was 48.7%, and CGI-C, NPI, and BPRS response rate by the last observation carried forward method were 42.7%, 48.6%, and 37.5%, respectively. No significant predictor was identified for treatment continuation in the Caucasian patients (n = 331), while better treatment response was predicted by a lower Mini-Mental State Examination score, treatment with risperidone (versus olanzapine and quetiapine), history of diabetes mellitus, healthier physical status, and more severe initial psychotic symptoms. CONCLUSIONS: Comparatively high intolerability from AAPs in the short term was confirmed. We found that baseline clinical predictors to treatment response in Caucasian AD patients with psychotic/aggressive symptoms include treatment with risperidone (versus quetiapine and olanzapine), diabetes mellitus, global physical status, cognitive impairment, and psychotic symptoms. Going forward, these findings may help to determine treatment strategies or care plans.

Baseline Telomere Length and Effects of a Multidomain Lifestyle Intervention on Cognition: The FINGER Randomized Controlled Trial. - Sindi, Shireen; Ngandu, Tiia; Hovatta, Iiris; Kåreholt, Ingemar; Antikainen, Riitta; Hänninen, Tuomo; Levälahti, Esko; Laatikainen, Tiina; Lindström, Jaana; Paajanen, Teemu; Peltonen, Markku; Khalsa, Dharma Singh; et al. (J Alzheimers Dis, 2017)
Leukocyte telomere length (LTL) is a biomarker of aging, and it is associated with lifestyle. It is currently unknown whether LTL is associated with the response to lifestyle interventions. The goal is to assess whether baseline LTL modified the cognitive benefits of a 2-year multidomain lifestyle intervention (exploratory analyses). The Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER) was a 2-year randomized controlled trial including 1,260 people at risk of cognitive decline, aged 60-77 years identified from the general population. Participants were randomly assigned to the lifestyle intervention (diet, exercise, cognitive training, and vascular risk management) and control (general health advice) groups. Primary outcome was change in cognition (comprehensive neuropsychological test battery). Secondary outcomes were changes in cognitive domains: memory, executive functioning, and processing speed. 775 participants (392 control, 383 intervention) had baseline LTL (peripheral blood DNA). Mixed effects regression models with maximum likelihood estimation were used to analyze change in cognition as a function of randomization group, time, baseline LTL, and their interaction. Intervention and control groups did not significantly differ at baseline. Shorter LTL was related to less healthy baseline lifestyle. Intervention benefits on executive functioning were more pronounced among those with shorter baseline LTL (p-value for interaction was 0.010 adjusted for age and sex, and 0.007 additionally adjusted for baseline lifestyle factors). The FINGER intervention cognitive benefits were more pronounced with shorter baseline LTL, particularly for executive functioning, indicating that the multidomain lifestyle intervention was especially beneficial among higher-risk individuals.

Bipolar Disorder and Frontotemporal Dementia: An Intriguing Association. - Papazacharias, Apostolos; Lozupone, Madia; Barulli, Maria Rosaria; Capozzo, Rosa; Imbimbo, Bruno P; Veneziani, Federica; De Blasi, Roberto; Nardini, Marcello; Seripa, Davide; Panza, Francesco; Logroscino, Giancarlo (J Alzheimers Dis, 2017)
Bipolar disorder (BD) could represent a prodromal state of frontotemporal dementia (FTD). Two patients affected by lifelong BD with a progressive decline of cognitive functions, behavioral, and neurological signs, reached the early diagnosis of FTD before the age of 60. They were diagnosed as affected by primary progressive aphasia and FTD with parkinsonism, respectively. A diagnosis of FTD should therefore be taken into account, in case of unexpected cognitive and behavioral decline in patients with a long history of BD. Follow-up studies with genetic, neuropsychological, and neuroimaging markers of these BD/FTD patients could further explore some of the underlying association, opening new viable therapeutic options.

Bryostatin Effects on Cognitive Function and PKCɛ in Alzheimer's Disease Phase IIa and Expanded Access Trials. - Nelson, Thomas J; Sun, Miao-Kun; Lim, Chol; Sen, Abhik; Khan, Tapan; Chirila, Florin V; Alkon, Daniel L (J Alzheimers Dis, 2017)
Bryostatin 1, a potent activator of protein kinase C epsilon (PKCɛ), has been shown to reverse synaptic loss and facilitate synaptic maturation in animal models of Alzheimer's disease (AD), Fragile X, stroke, and other neurological disorders. In a single-dose (25 μg/m2) randomized double-blind Phase IIa clinical trial, bryostatin levels reached a maximum at 1-2 h after the start of infusion. In close parallel with peak blood levels of bryostatin, an increase of PBMC PKCɛ was measured (p = 0.0185) within 1 h from the onset of infusion. Of 9 patients with a clinical diagnosis of AD, of which 6 received drug and 3 received vehicle within a double-blind protocol, bryostatin increased the Mini-Mental State Examination (MMSE) score by +1.83±0.70 unit at 3 h versus -1.00±1.53 unit for placebo. Bryostatin was well tolerated in these AD patients and no drug-related adverse events were reported. The 25 μg/m2 administered dose was based on prior clinical experience with three Expanded Access advanced AD patients treated with bryostatin, in which return of major functions such as swallowing, vocalization, and word recognition were noted. In one Expanded Access patient trial, elevated PKCɛ levels closely tracked cognitive benefits in the first 24 weeks as measured by MMSE and ADCS-ADL psychometrics. Pre-clinical mouse studies showed effective activation of PKCɛ and increased levels of BDNF and PSD-95. Together, these Phase IIa, Expanded Access, and pre-clinical results provide initial encouragement for bryostatin 1 as a potential treatment for AD.

Can Musical or Painting Interventions Improve Chronic Pain, Mood, Quality of Life, and Cognition in Patients with Mild Alzheimer's Disease? Evidence from a Randomized Controlled Trial. - Pongan, Elodie; Tillmann, Barbara; Leveque, Yohana; Trombert, Béatrice; Getenet, Jean Claude; Auguste, Nicolas; Dauphinot, Virginie; El Haouari, Hanane; Navez, Malou; Dorey, Jean-Michel; Krolak-Salmon, Pierre; Laurent, Bernard; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Among non-pharmacological therapies, musical intervention is often used for patients with Alzheimer's disease (AD) and patients presenting chronic pain. However, their efficacy is still under debate. OBJECTIVE: Our aim was to determine the efficacy of choral singing versus painting sessions on chronic pain, mood, quality of life, and cognition in AD patients. METHODS: In this multicenter randomized controlled trial, 59 mild AD patients were randomized to a 12-week singing (SG; n = 31) or painting group (PG; n = 28). Chronic pain, anxiety, depression, and quality of life were assessed before, after, and 1 month after the sessions. Cognitive abilities were assessed before and after interventions. The evolution of these different measures was assessed with mixed linear models. The primary data analysis was by intention-to-treat, and completed by a 'per protocol' approach. RESULTS: Both singing and painting interventions led to significant pain reduction (Time effect: F = 4.71; p = 0.01), reduced anxiety (Time effect: F = 10.74; p < 0.0001), improved Quality of Life (Time effect: F = 6.79; p = 0.002), improved digit span (F = 12.93; p = 0.001), and inhibitory processes (Time effect: F = 4.93; p = 0.03). Depression was reduced over time in PG only (Time x Group effect: F = 4.53; p = 0.01). Verbal Memory performance remained stable over time in SG, but decreased in PG (Time x group effect: F = 9.29; p = 0.004). CONCLUSION: Findings suggest that singing and painting interventions may reduce pain and improve mood, quality of life, and cognition in patients with mild AD, with differential effects of painting for depression and singing for memory performance.

CD44 Splice Variants as Potential Players in Alzheimer's Disease Pathology. - Pinner, Elhanan; Gruper, Yaron; Ben Zimra, Micha; Kristt, Don; Laudon, Moshe; Naor, David; Zisapel, Nava (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by cognitive deficits, deposition of amyloid-β (Aβ) plaques, intracellular neurofibrillary tangles, and neuronal cell death. Neuroinflammation is commonly believed to participate in AD pathogenesis. CD44 is an inflammation-related gene encoding a widely-distributed family of alternatively spliced cell surface glycoproteins that have been implicated in inflammation, metastases, and inflammation-linked neuronal injuries. Here we investigated the expression patterns of CD44S (which does not contain any alternative exon) and CD44 splice variants in postmortem hippocampal samples from AD patients and matched non-AD controls. The expression of CD44S and CD44 splice variants CD44V3, CD44V6, and CD44V10 was significantly higher in AD patients compared to non-AD controls. Immunohistochemistry of human hippocampal sections revealed that CD44S differentially localized to neuritic plaques and astrocytes, whereas CD44V3, CD44V6, and CD44V10 expression was mostly neuronal. Consistent with these findings, we found that the expression of CD44V6 and CD44V10 was induced by Aβ peptide in neuroblastoma cells and primary neurons. Furthermore, in loss of function studies we found that both CD44V10-specific siRNA and CD44V10 antibody protected neuronal cells from Aβ-induced toxicity, suggesting a causal relationship between CD44V10 and neuronal cell death. These data indicate that certain CD44 splice variants contribute to AD pathology and that CD44V10 inhibition may serve as a new neuroprotective treatment strategy for this disease.

Cerebral Amyloid Angiopathy-Related Microbleeds and Cerebrospinal Fluid Biomarkers in Alzheimer's Disease. - Noguchi-Shinohara, Moeko; Komatsu, Junji; Samuraki, Miharu; Matsunari, Ichiro; Ikeda, Tokuhei; Sakai, Kenji; Hamaguchi, Tsuyoshi; Ono, Kenjiro; Nakamura, Hiroyuki; Yamada, Masahito (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) commonly accompanies cerebral amyloid angiopathy (CAA). OBJECTIVE: We aimed to reveal associations between CAA-related brain microbleeds and cerebrospinal fluid (CSF) markers in AD patients. METHODS: Patients with probable AD (n = 88) from consecutive patients in our memory clinic were evaluated for patient demographics, vascular risk factors, neuropsychological tests, apolipoprotein E phenotype, MRI including T2*-weighted image and fluid attenuated inversion recovery sequence, and CSF amyloid and tau markers. RESULTS: The 88 patients with AD included 15 with microbleeds only in cortical/subcortical regions (cortical microbleeds) that could be CAA-related, 16 with microbleeds only in deep locations (deep microbleeds), 3 with microbleeds in both cortical and deep locations (mixed microbleeds), and 54 without microbleeds. The CSF levels of amyloid β-protein 1-40 (Aβ40) and amyloid β-protein 1-42 (Aβ42) were significantly lower in patients with cortical microbleeds than in those without microbleeds (p = 0.001 and p = 0.027, respectively). The result remained unchanged after adjustment for age, sex, apolipoprotein E E4 presence, and leukoaraiosis. CONCLUSIONS: CAA-related cortical microbleeds would be associated with lower CSF levels of Aβ40 and Aβ42 in AD, reflecting the deposition of both Aβ40 and Aβ42 in the cerebrovasculature.

The Cerebrospinal Fluid Aβ1-42/Aβ1-40 Ratio Improves Concordance with Amyloid-PET for Diagnosing Alzheimer's Disease in a Clinical Setting. - Niemantsverdriet, Ellis; Ottoy, Julie; Somers, Charisse; De Roeck, Ellen; Struyfs, Hanne; Soetewey, Femke; Verhaeghe, Jeroen; Van den Bossche, Tobi; Van Mossevelde, Sara; Goeman, Johan; De Deyn, Peter Paul; Mariën, Peter; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Evidence suggests that the concordance between amyloid-PET and cerebrospinal fluid (CSF) amyloid-β (Aβ) increases when the CSF Aβ1-42/Aβ1-40 ratio is used as compared to CSF Aβ1-42 levels alone. OBJECTIVE: In order to test this hypothesis, we set up a prospective longitudinal study comparing the concordance between different amyloid biomarkers for Alzheimer's disease (AD) in a clinical setting. METHODS: Seventy-eight subjects (AD dementia (n = 17), mild cognitive impairment (MCI, n = 48), and cognitively healthy controls (n = 13)) underwent a [18F]Florbetapir ([18F]AV45) PET scan, [18F]FDG PET scan, MRI scan, and an extensive neuropsychological examination. In a large subset (n = 67), a lumbar puncture was performed and AD biomarkers were analyzed (Aβ1-42, Aβ1-40, T-tau, P-tau181). RESULTS: We detected an increased concordance in the visual and quantitative (standardized uptake value ratio (SUVR) and total volume of distribution (VT)) [18F]AV45 PET measures when the CSF Aβ1-42/Aβ1-40 was applied compared to Aβ1-42 alone. CSF biomarkers were stronger associated to [18F]AV45 PET for SUVR values when considering the total brain white matter as reference region instead of cerebellar grey matterConclusions:The concordance between CSF Aβ and [18F]AV45 PET increases when the CSF Aβ1-42/Aβ1-40 ratio is applied. This finding is of most importance for the biomarker-based diagnosis of AD as well as for selection of subjects for clinical trials with potential disease-modifying therapies for AD.

Cerebrospinal Fluid Neurogranin as a Biomarker of Neurodegenerative Diseases: A Cross-Sectional Study. - Lista, Simone; Toschi, Nicola; Baldacci, Filippo; Zetterberg, Henrik; Blennow, Kaj; Kilimann, Ingo; Teipel, Stefan J; Cavedo, Enrica; Dos Santos, Antonio Melo; Epelbaum, Stéphane; Lamari, Foudil; Dubois, Bruno; et al. (J Alzheimers Dis, 2017)
We investigated cerebrospinal fluid (CSF) concentrations of the postsynaptic biomarker neurogranin at baseline in cognitively healthy controls (HC) compared to individuals with mild cognitive impairment (MCI), patients with Alzheimer's disease (AD) dementia, and patients with frontotemporal dementia (FTD). CSF neurogranin was quantified using an in-house immunoassay in a cross-sectional multicenter study of 108 participants [AD dementia (n = 35), FTD (n = 9), MCI (n = 41), cognitively HC (n = 23)]. CSF neurogranin concentrations were significantly higher in AD patients compared with both HC subjects and FTD patients, suggesting that increased CSF neurogranin concentrations may indicate AD-related pathophysiology. CSF neurogranin was independently associated with both total tau and hyperphosphorylated tau proteins, whereas a non-significant correlation with the 42-amino acid-long amyloid-β peptide was evident. CSF neurogranin, however, was not superior to core AD biomarkers in differentiating HC from the three diagnostic groups, and it did not improve their diagnostic accuracy. We conclude that further classification and longitudinal studies are required to shed more light into the potential role of neurogranin as a pathophysiological biomarker of neurodegenerative diseases.

Challenges and Considerations Related to Studying Dementia in Blacks/African Americans. - Ighodaro, Eseosa T; Nelson, Peter T; Kukull, Walter A; Schmitt, Frederick A; Abner, Erin L; Caban-Holt, Allison; Bardach, Shoshana H; Hord, Derrick C; Glover, Crystal M; Jicha, Gregory A; Van Eldik, Linda J; Byrd, Alexander X; et al. (J Alzheimers Dis, 2017)
Blacks/African Americans have been reported to be ∼2-4 times more likely to develop clinical Alzheimer's disease (AD) compared to Whites. Unfortunately, study design challenges (e.g., recruitment bias), racism, mistrust of healthcare providers and biomedical researchers, confounders related to socioeconomic status, and other sources of bias are often ignored when interpreting differences in human subjects categorized by race. Failure to account for these factors can lead to misinterpretation of results, reification of race as biology, discrimination, and missed or delayed diagnoses. Here we provide a selected historical background, discuss challenges, present opportunities, and suggest considerations for studying health outcomes among racial/ethnic groups. We encourage neuroscientists to consider shifting away from using biologic determination to interpret data, and work instead toward a paradigm of incorporating both biological and socio-environmental factors known to affect health outcomes with the goal of understanding and improving dementia treatments for Blacks/African Americans and other underserved populations.

Changes of Cerebrospinal Fluid Peptides due to Tauopathy. - Majerova, Petra; Barath, Peter; Michalicova, Alena; Katina, Stanislav; Novak, Michal; Kovac, Andrej (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) and progressive supranuclear palsy are two common neurodegenerative tauopathies, and the most common cause of progressive brain dementia in elderly affecting more than 35 million people. The tauopathies are characterized by abnormal deposition of microtubule associated protein tau into intracellular neurofibrillary tangles composed mainly of the hyperphosphorylated form of the protein. The diagnosis of tauopathies is based on the presence of clinical features and pathological changes. Over the last decade, there has been an intensive search for novel biochemical markers for clinical diagnosis of AD and other tauopathies. In the present study, we used transgenic rat model for tauopathy expressing human truncated tau protein (aa 151-391/4R) to analyze the cerebrospinal fluid (CSF) peptidome using liquid chromatography - matrix assisted laser desorption/ionization mass spectrometry (LC-MALDI TOF/TOF). From 345 peptides, we identified a total of 175 proteins. Among them, 17 proteins were significantly altered in the CSF of transgenic rats. The following proteins were elevated in the CSF of transgenic rats when compared to the control animals: neurofilament light and medium chain, apolipoprotein E, gamma-synuclein, chromogranin A, reticulon-4, secretogranin-2, calsyntein-1 and -3, endothelin-3, neuroendocrine protein B72A, alpha-1-macroglobulin, and augurin. Interestingly most of the identified proteins were previously linked to AD and other tauopathies, indicating the significance of transgenic animals in biomarker validation.

Chronic Lithium Treatment in a Rat Model of Basal Forebrain Cholinergic Depletion: Effects on Memory Impairment and Neurodegeneration. - Gelfo, Francesca; Cutuli, Debora; Nobili, Annalisa; De Bartolo, Paola; D'Amelio, Marcello; Petrosini, Laura; Caltagirone, Carlo (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is an age-related neurodegenerative disorder with multifactorial etiopathogenesis, characterized by progressive loss of memory and other cognitive functions. A fundamental neuropathological feature of AD is the early and severe brain cholinergic neurodegeneration. Lithium is a monovalent cation classically utilized in the treatment of mood disorders, but recent evidence also advances a beneficial potentiality of this compound in neurodegeneration. Interestingly, lithium acts on several processes whose alterations characterize the brain cholinergic impairment at short and long term. On this basis, the aim of the present research was to evaluate the potential beneficial effects of a chronic lithium treatment in preventing the damage that a basal forebrain cholinergic neurodegeneration provokes, by investigating memory functions and neurodegeneration correlates. Adult male rats were lesioned by bilateral injections of the immunotoxin 192 IgG-Saporin into the basal forebrain. Starting 7 days before the surgery, the animals were exposed to a 30-day lithium treatment, consisting of a 0.24% Li2CO3 diet. Memory functions were investigated by the open field test with objects, the sociability and preference for social novelty test, and the Morris water maze. Hippocampal and neocortical choline acetyltransferase (ChAT) levels and caspase-3 activity were determined. Cholinergic depletion significantly impaired spatial and social recognition memory, decreased hippocampal and neocortical ChAT levels and increased caspase-3 activity. The chronic lithium treatment significantly rescued memory performances but did not modulate ChAT availability and caspase-3 activity. The present findings support the lithium protective effects against the cognitive impairment that characterizes the brain cholinergic depletion.

Classification of Depression, Cognitive Disorders, and Co-Morbid Depression and Cognitive Disorders with Perfusion SPECT Neuroimaging. - Amen, Daniel G; Krishnamani, Pavitra; Meysami, Somayeh; Newberg, Andrew; Raji, Cyrus A (J Alzheimers Dis, 2017)
BACKGROUND: Depression and cognitive disorders (CDs) are two common co-morbid afflictions that commonly present with overlapping symptoms. OBJECTIVE: To evaluate if perfusion neuroimaging with brain SPECT can distinguish persons with depression from those with CDs or both conditions. METHODS: Inclusion criteria were DSM-IV defined depression or CDs (Alzheimer's disease, vascular dementia, dementia not otherwise specified, and amnestic disorders not otherwise specified) including persons with both (total n = 4,541; 847 CDs, 3,269 depression, 425 with both). Perfusion differences between the groups were calculated using two-sampled t-tests corrected for multiple comparisons. Diagnostic separation was determined with discriminant analysis. Feature selection revealed predictive regions in delineating depression from CDs and comorbid cases. RESULTS: Persons with CDs had lower cerebral perfusion compared to depression. In co-morbid persons, cerebral hypoperfusion was additive, with regions showing lower regional cerebral blood flow compared to either diagnosis alone. Both baseline and concentration SPECT regions yielded correct classification of 86% and leave one out cross-validation of 83%. AUC analysis for SPECT regions showed 86% accuracy, 80% sensitivity and 75% specificity. Discriminant analysis separated depression and CDs from comorbid cases with correct classification of 90.8% and cross validated accuracy of 88.6%. Area under the curve was 83% with sensitivity of 80% and specificity of 70%. Feature selection identified the most predictive regions in left hippocampus, right insula, cerebellar, and frontal lobe regions. CONCLUSION: Quantitative perfusion SPECT neuroimaging distinguishes depression from dementia and those with both co-morbidities. Perfusion brain SPECT can be utilized clinically to delineate between these two disorders.

Cognitive Status, Gray Matter Atrophy, and Lower Orthostatic Blood Pressure in Older Adults. - O'Hare, Celia; Kenny, Rose-Anne; Aizenstein, Howard; Boudreau, Robert; Newman, Anne; Launer, Lenore; Satterfield, Suzanne; Yaffe, Kristine; Rosano, Caterina (J Alzheimers Dis, 2017)
BACKGROUND: Associations between orthostatic blood pressure and cognitive status (CS) have been described with conflicting results. OBJECTIVE: We hypothesize that long-term exposure to lower orthostatic blood pressure is related to having worse CS later in life and that atrophy of regions involved in central regulation of autonomic function mediate these associations. METHODS: Three-to-four measures of orthostatic blood pressure were obtained from 1997-2003 in a longitudinal cohort of aging, and average systolic orthostatic blood pressure response (ASOBPR) was computed as % change in systolic blood pressure from sit-to-stand measured at one minute post stand. CS was determined in 2010-2012 by clinician-adjudication (n = 240; age = 87.1±2.6; 59% women; 37% black) with a subsample also undergoing concurrent structural neuroimaging (n = 129). Gray matter volume of regions related to autonomic function was measured. Multinomial regression was used to compare ASOBPR in those who were cognitively intact versus those with a diagnosis of mild cognitive impairment or dementia, controlling for demographics, trajectories of seated blood pressure, incident cardiovascular risk/events and medications measured from 1997 to 2012. Models were repeated in the subsample with neuroimaging, before and after adjustment for regional gray matter volume. RESULTS: There was an inverse association between ASOBPR and probability of dementia diagnosis (9% lower probability for each % point higher ASOBPR: OR 0.91, CI95%  = 0.85-0.98; p = 0.01). Associations were similar in the subgroup with neuroimaging before and after adjustment for regional gray matter volume. CONCLUSION: ASOBPR may be an early marker of risk of dementia in older adults living in the community.

Cognitive-Enhancing Effects of a Polyphenols-Rich Extract from Fruits without Changes in Neuropathology in an Animal Model of Alzheimer's Disease. - Dal-Pan, Alexandre; Dudonné, Stéphanie; Bourassa, Philippe; Bourdoulous, Morgane; Tremblay, Cyntia; Desjardins, Yves; Calon, Frederic (J Alzheimers Dis, 2017)
No effective preventive treatment is available for age-related cognitive decline and Alzheimer's disease (AD). Epidemiological studies indicate that a diet rich in fruit is associated with cognitive improvement. It was thus proposed that high polyphenol concentrations found in berries can prevent cognitive impairment associated with aging and AD. Therefore, the Neurophenols project aimed at investigating the effects of a polyphenolic extract from blueberries and grapes (PEBG) in the triple-transgenic (3xTg-AD) mouse model of AD, which develops AD neuropathological markers, including amyloid-β plaques and neurofibrillary tangles, leading to memory deficits. In this study, 12-month-old 3xTg-AD and NonTg mice were fed a diet supplemented with standardized PEBG (500 or 2500 mg/kg) for 4 months (n = 15-20/group). A cognitive evaluation with the novel object recognition test was performed at 15 months of age and mice were sacrificed at 16 months of age. We observed that PEBG supplementation with doses of 500 or 2500 mg/kg prevented the decrease in novel object recognition observed in both 15-month-old 3xTg-AD mice and NonTg mice fed a control diet. Although PEBG treatment did not reduce Aβ and tau pathologies, it prevented the decrease in mature BDNF observed in 16-month-old 3xTg-AD mice. Finally, plasma concentrations of phenolic metabolites, such as dihydroxyphenyl valerolactone, a microbial metabolite of epicatechin, positively correlated with memory performances in supplemented mice. The improvement in object recognition observed in 3xTg-AD mice after PEBG administration supports the consumption of polyphenols-rich extracts to prevent memory impairment associated with age-related disease, without significant effects on classical AD neuropathology.

Comparative Analysis of Cortical Microinfarcts and Microbleeds using 3.0-Tesla Postmortem Magnetic Resonance Images and Histopathology. - Niwa, Atsushi; Ii, Yuichiro; Shindo, Akihiro; Matsuo, Ko; Ishikawa, Hidehiro; Taniguchi, Akira; Takase, Shinichi; Maeda, Masayuki; Sakuma, Hajime; Akatsu, Hiroyasu; Hashizume, Yoshio; Tomimoto, Hidekazu (J Alzheimers Dis, 2017)
Microvascular lesions including cortical microinfarctions (CMIs) and cerebral lobar microbleeds (CMBs) are usually caused by cerebral amyloid angiopathy (CAA) in the elderly and are correlated with cognitive decline. However, their radiological-histopathological coincidence has not been revealed systematically with widely used 3-Tesla (3T) magnetic resonance imaging (MRI). The purpose of the present study is to delineate the histopathological background corresponding to MR images of these lesions. We examined formalin-fixed 10-mm thick coronal brain blocks from 10 CAA patients (five were also diagnosed with Alzheimer's disease, three with dementia with Lewy bodies, and two with CAA only) with dementia and six non CAA patients with neurodegenerative disease. Using 3T MRI, both 3D-fluid attenuated inversion recovery (FLAIR) and 3D-double inversion recovery (DIR) were examined to identify CMIs, and T2* and susceptibility-weighted images (SWI) were examined to identify CMBs. These blocks were subsequently examined histologically and immunohistochemically. In CAA patients, 48 CMIs and 6 lobar CMBs were invariably observed in close proximity to degenerated Aβ-positive blood vessels. Moreover, 16 CMIs (33%) of 48 were detected with postmortem MRI, but none were seen when the lesion size was smaller than 1 mm. In contrast, only 1 undeniable CMI was founded with MRI and histopathology in 6 non CAA patients. Small, cortical high-intensity lesions seen on 3D-FLAIR and 3D-DIR images likely represent CMIs, and low-intensity lesions in T2* and SWI correspond to CMBs with in vivo MRI. Furthermore, a close association between amyloid-laden vessels and these microvascular lesions indicated the contribution of CAA to their pathogenesis.

Comprehensive Screening for Disease Risk Variants in Early-Onset Alzheimer's Disease Genes in African Americans Identifies Novel PSEN Variants. - N'Songo, Aurelie; Carrasquillo, Minerva M; Wang, Xue; Nguyen, Thuy; Asmann, Yan; Younkin, Steven G; Allen, Mariet; Duara, Ranjan; Custo, Maria T Greig; Graff-Radford, Neill; Ertekin-Taner, Nilufer (J Alzheimers Dis, 2017)
We conducted a comprehensive screening of rare coding variants in an African American cohort to identify novel pathogenic mutations within the early-onset Alzheimer's disease (EOAD) genes (APP, PSEN1, and PSEN2) in this understudied population. Whole-exome sequencing of 238 African American subjects identified 6 rare missense variants within the EOAD genes, which were observed in AD cases but never among controls. These variants were analyzed in an independent cohort of 300 African American subjects in which PSEN2:NM_000447:exon5:c.T331C:p.Phe111Leu and PSEN1-minilin rs777923890 variants were again not observed, indicating that these novel rare variants, may contribute to AD risk in this population.

Consecutive Analysis of BACE1 Function on Developing and Developed Neuronal Cells. - Kamikubo, Yuji; Takasugi, Nobumasa; Niisato, Kazue; Hashimoto, Yoshie; Sakurai, Takashi (J Alzheimers Dis, 2017)
The amyloid-β protein precursor (AβPP) is cleaved by a transmembrane protease termed β-site AβPP cleavage enzyme (BACE1), which is being explored as a target for therapy and prevention of Alzheimer's disease (AD). Although genetic deletion of BACE1 results in abolished amyloid pathology in AD model mice, it also results in neurodevelopmental phenotypes such as hypomyelination and synaptic loss, observed in schizophrenia and autism-like phenotype. These lines of evidence indicate that the inhibition of BACE1 causes adverse side effects during the neurodevelopmental stage. However, the effects of the inhibition of BACE1 activity on already developed neurons remain unclear. Here, we utilized hippocampal slice cultures as an ex vivo model that enabled continuous and long-term analysis for the effect of BACE1 inhibition on neuronal circuits and synapses. Temporal changes in synaptic proteins in hippocampal slices indicated acute synaptic loss, followed by synapse formation and maintenance phases. Long-term BACE1 inhibition in the neurodevelopmental stage caused the loss of synaptic proteins but failed to alter synaptic proteins in the already developed maintenance stage. These data indicate that BACE1 function on synapses is dependent on synaptic developmental stages, and our study provides a useful model to observe the long-term effect of BACE1 activity in the brain, and to evaluate adverse effects of BACE inhibitors.

Cortical Iron Reflects Severity of Alzheimer's Disease. - van Duijn, Sara; Bulk, Marjolein; van Duinen, Sjoerd G; Nabuurs, Rob J A; van Buchem, Mark A; van der Weerd, Louise; Natté, Remco (J Alzheimers Dis, 2017)
Abnormal iron distribution in the isocortex is increasingly recognized as an in vivo marker for Alzheimer's disease (AD). However, the contribution of iron accumulation to the AD pathology is still poorly understood. In this study, we investigated: 1) frontal cortical iron distribution in AD and normal aging and 2) the relation between iron distribution and degree of AD pathology. We used formalin fixed paraffin embedded frontal cortex from 10 AD patients, 10 elder, 10 middle aged, and 10 young controls and visualized iron with a modified Perl's histochemical procedure. AD and elderly subjects were not different with respect to age and sex distribution. Iron distribution in the frontal cortex was not affected by normal aging but was clearly different between AD and controls. AD showed accumulation of iron in plaques, activated microglia, and, in the most severe cases, in the mid-cortical layers along myelinated fibers. The degree of altered iron accumulations was correlated to the amount of amyloid-β plaques and tau pathology in the same block, as well as to Braak stage (p < 0.001). AD and normal aging show different iron and myelin distribution in frontal cortex. These changes appear to occur after the development of the AD pathological hallmarks. These findings may help the interpretation of high resolution in vivo MRI and suggest the potential of using changes in iron-based MRI contrast to indirectly determine the degree of AD pathology in the frontal cortex.

A Cross-Validation of FDG- and Amyloid-PET Biomarkers in Mild Cognitive Impairment for the Risk Prediction to Dementia due to Alzheimer's Disease in a Clinical Setting. - Iaccarino, Leonardo; Chiotis, Konstantinos; Alongi, Pierpaolo; Almkvist, Ove; Wall, Anders; Cerami, Chiara; Bettinardi, Valentino; Gianolli, Luigi; Nordberg, Agneta; Perani, Daniela (J Alzheimers Dis, 2017)
Assessments of brain glucose metabolism (18F-FDG-PET) and cerebral amyloid burden (11C-PiB-PET) in mild cognitive impairment (MCI) have shown highly variable performances when adopted to predict progression to dementia due to Alzheimer's disease (ADD). This study investigates, in a clinical setting, the separate and combined values of 18F-FDG-PET and 11C-PiB-PET in ADD conversion prediction with optimized data analysis procedures. Respectively, we investigate the accuracy of an optimized SPM analysis for 18F-FDG-PET and of standardized uptake value ratio semiquantification for 11C-PiB-PET in predicting ADD conversion in 30 MCI subjects (age 63.57±7.78 years). Fourteen subjects converted to ADD during the follow-up (median 26.5 months, inter-quartile range 30 months). Receiver operating characteristic analyses showed an area under the curve (AUC) of 0.89 and of 0.81 for, respectively, 18F-FDG-PET and 11C-PiB-PET. 18F-FDG-PET, compared to 11C-PiB-PET, showed higher specificity (1.00 versus 0.62, respectively), but lower sensitivity (0.79 versus 1.00). Combining the biomarkers improved classification accuracy (AUC = 0.96). During the follow-up time, all the MCI subjects positive for both PET biomarkers converted to ADD, whereas all the subjects negative for both remained stable. The difference in survival distributions was confirmed by a log-rank test (p = 0.002). These results indicate a very high accuracy in predicting MCI to ADD conversion of both 18F-FDG-PET and 11C-PiB-PET imaging, the former showing optimal performance based on the SPM optimized parametric assessment. Measures of brain glucose metabolism and amyloid load represent extremely powerful diagnostic and prognostic biomarkers with complementary roles in prodromal dementia phase, particularly when tailored to individual cases in clinical settings.

Cyclic cis-Locked Phospho-Dipeptides Reduce Entry of AβPP into Amyloidogenic Processing Pathway. - Fisher, Carolyn L; Resnick, Ross J; De, Soumya; Acevedo, Lucila A; Lu, Kun Ping; Schroeder, Frank C; Nicholson, Linda K (J Alzheimers Dis, 2017)
The cis/trans isomerization of X-Pro peptide bonds in proteins in some instances acts as a molecular switch in biological pathways. Our prior work suggests that the cis isomer of the phospho-Thr668-Pro669 motif, located in the cytoplasmic domain of the amyloid-β protein precursor (AβPP), is correlated with an increase in amyloidogenic processing of AβPP and production of amyloid-beta (Aβ), the neurotoxic peptide fragment in Alzheimer's disease (AD). We designed a 100% cis-locked cyclic dipeptide composed of cyclized phospho-Thr-Pro (pCDP) as a mimic for this putative pathological conformation, and three phosphate-blocked derivatives (pCDP-diBzl, pCDP-Bzl, and pCDP-diPOM). Two H4 neuroglioma cell lines were established as AD cell models for use in testing these compounds: H4-AβPP695 for stable overexpression of wild-type AβPP695, and H4-BACE1 for stable overexpression of β-site AβPP cleaving enzyme-1 (BACE1). The level of the secreted AβPP fragment resulting from BACE1 activity, sAβPPβ, served as a key proxy for amyloidogenic processing, since cleavage of AβPP by BACE1 is a requisite first step in Aβ production. Of the compounds tested, pCDP-diBzl decreased sAβPPβ levels in both cell lines, while pCDP-diPOM decreased sAβPPβ levels in only H4-BACE1 cells, all with similar dose-dependences and patterns of proteolytic AβPP fragments. Enzymatic assays showed that none of the pCDP derivatives directly inhibit BACE1 catalytic activity. These results suggest a model in which pCDP-diBzl and pCDP-diPOM act at a common point to inhibit entry of AβPP into the amyloidogenic AβPP processing pathway but through different targets, and provide important insights for the development of novel AD therapeutics.

Death of Dementia Patients in Psychiatric Hospitals and Regional Supply of Psychiatric Services: Study of the National Data from 1996 to 2014 in Japan. - Nakanishi, Miharu; Niimura, Junko; Yamasaki, Syudo; Nishida, Atsushi (J Alzheimers Dis, 2017)
BACKGROUND: Japan designates psychiatric inpatient care for behavior management of individuals with dementia and for helping dementia patients discharge to home. However, there has been no examination of the effectiveness of this strategy. OBJECTIVE: The present study investigated the association between dementia and the discharge destination of patients in psychiatric hospitals. METHODS: Data from the National Patient Survey, which is a nationally representative cross-sectional survey of inpatient care, were used. The 96,420 patients with dementia or other mental illness who were discharged from psychiatric hospitals in September of every 3 years from 1996 to 2014 were included in analyses. RESULTS: Of the 96,420 discharged patients, 13,823 had dementia as the primary disease. Of the 13,823 dementia patients, 3,865 (28.0%) were discharged to home, 3,870 (28.0%) were admitted to a facility or other care settings, 3,574 (25.9%) were admitted to another hospital, and 2,514 (18.2%) died. Patients were more likely to die in psychiatric hospital if their primary disease was dementia, and they had resided in a region that provided fewer home visits for psychiatric nursing care or had available a larger number of psychiatric hospital beds per capita. CONCLUSION: Psychiatric inpatient care may be ineffective as a treatment for the challenging behaviors of dementia. A community mental health system for behavior management should be constructed in parallel with a reduction in the number of hospital beds allotted for psychiatric care.

Decrease of Amyloid-β Levels by Curcumin Derivative via Modulation of Amyloid-β Protein Precursor Trafficking. - Kotani, Rina; Urano, Yasuomi; Sugimoto, Hachiro; Noguchi, Noriko (J Alzheimers Dis, 2017)
The abnormal production and deposition of amyloid-β (Aβ) peptides is a pathologic hallmark of Alzheimer's disease. Aβ is generated from amyloid-β protein precursor (AβPP) by two sequential proteolytic cleavage steps involving β- and γ-secretases in the trans-Golgi network and endosomes. Since direct inhibition of secretase could induce undesirable side-effects due to inadvertent inhibition of unrelated secretase substrates, it is important to establish methods for inhibiting Aβ production that do not affect secretase activity. It has been suggested that curcumin may have potent anti-amyloidogenic effect. In the present study, we evaluate the effect of curcumin derivatives on Aβ production in human neuroblastoma SH-SY5Y cells and in CHO cells which stably express human AβPP (CHO-AβPP). We found that the curcumin derivative CU6 was more effective than curcumin itself in reducing Aβ secretion. We further found that in SH-SY5Y cells CU6 inhibited neither β- nor γ-secretase activity, and that increased amounts of immature forms of AβPP accumulated in the endoplasmic reticulum (ER). We also found that CU6 induced expression of the ER chaperone glucose-regulated protein 78 (GRP78), and enhanced formation of the AβPP/GRP78 complex. These results suggest that CU6 downregulates intracellular AβPP trafficking, resulting in suppression of Aβ production independently of secretase activity.

Decreased Expression of hsa-miR-4274 in Cerebrospinal Fluid of Normal Pressure Hydrocephalus Mimics with Parkinsonian Syndromes. - Jurjević, Ivana; Miyajima, Masakazu; Ogino, Ikuko; Akiba, Chihiro; Nakajima, Madoka; Kondo, Akihide; Kikkawa, Mika; Kanai, Mitsuyasu; Hattori, Nobutaka; Arai, Hajime (J Alzheimers Dis, 2017)
BACKGROUND: Patients presenting with the classical idiopathic normal pressure hydrocephalus (iNPH) triad often show additional parkinsonian spectrum signs. Accurate differential diagnosis strongly influences the long-term outcome of cerebrospinal fluid (CSF) shunting. OBJECTIVE: The aim of this study was to find potential CSF microRNA (miRNA) biomarkers for NPH mimics with parkinsonian syndromes that can reliably distinguish them from iNPH patients. METHODS: Two cohorts of 81 patients (cohort 1, n = 55; cohort 2, n = 26) with possible iNPH who were treated in two centers between January 2011 and May 2014 were studied. In both cohorts, CSF samples were obtained from patients clinically diagnosed with iNPH (n = 21 and n = 10, respectively), possible iNPH with parkinsonian spectrum (PS) (n = 18, n = 10, respectively), possible iNPH with Alzheimer's disease (AD) (n = 16), and non-affected elderly individuals (NC) (n = 6). A three-step qRT-PCR analysis of the CSF samples was performed to detect miRNAs that were differentially expressed in the groups. RESULTS: The expression of hsa-miR-4274 in CSF was decreased in both cohorts of PS group patients (cohort 1: p < 0.0001, cohort 2: p < 0.0001), and was able to distinguish PS from iNPH with high accuracy (area under the curve = 0.908). The CSF concentration of hsa-miR-4274 also correlated with the specific binding ratio of ioflupane (123I) dopamine transporter scan (r = -0.494, p = 0.044). By contrast, the level of hsa-miR-4274 was significantly increased in the PS group after CSF diversion. CONCLUSION: Levels of CSF hsa-miR-4274 can differentiate PS from patients with iNPH, AD, and NC. This may be clinically useful for diagnostic purposes and predicting shunt treatment responses.

Decreased Glucose Metabolism in Medial Prefrontal Areas is Associated with Nutritional Status in Patients with Prodromal and Early Alzheimer's Disease. - Sugimoto, Taiki; Nakamura, Akinori; Kato, Takashi; Iwata, Kaori; Saji, Naoki; Arahata, Yutaka; Hattori, Hideyuki; Bundo, Masahiko; Ito, Kengo; Niida, Shumpei; Sakurai, Takashi (J Alzheimers Dis, 2017)
BACKGROUND: Weight loss is frequently observed in patients with Alzheimer's disease (AD); however, the underlying mechanisms are not well understood. OBJECTS: To clarify the associations between nutritional status and AD-related brain changes using Pittsburgh Compound-B (PiB)-PET, fluorodeoxyglucose (FDG)-PET, and structural MRI. METHODS: The subjects were 34 amyloid-β (Aβ)-positive individuals with mild cognitive impairment or early AD (prodromal/early AD), and 55 Aβ-negative cognitively normal (CN) subjects who attended the Multimodal Neuroimaging for AD Diagnosis (MULNIAD) study. Nutritional status of the subjects was assessed by body mass index and waist to height ratio (waist circumference/height). The associations between nutritional status and brain changes were examined by multiple regression analysis using statistical parametric mapping. RESULTS: In the prodromal/early AD group, nutritional status was significantly positively correlated with regional cerebral glucose metabolism (rCGM) in the medial prefrontal cortices, while different topographical associations were seen in the CN group, suggesting these changes were AD-specific. Aβ deposition and gray matter volume were not significantly associated with nutritional status. Sub-analysis in the prodromal/early AD group demonstrated that fat mass index, but not fat-free mass index, was positively correlated with rCGM in the medial prefrontal areas. CONCLUSION: This present study provides preliminary results suggesting that hypometabolism in the medial prefrontal areas is specifically associated with AD-related weight loss, and decrease in fat mass may have a key role.

Decreased N-Acetyl Aspartate/Myo-Inositol Ratio in the Posterior Cingulate Cortex Shown by Magnetic Resonance Spectroscopy May Be One of the Risk Markers of Preclinical Alzheimer's Disease: A 7-Year Follow-Up Study. - Waragai, Masaaki; Moriya, Masaru; Nojo, Takeshi (J Alzheimers Dis, 2017)
Although molecular positron emission tomography imaging of amyloid and tau proteins can facilitate the detection of preclinical Alzheimer's disease (AD) pathology, it is not useful in clinical practice. More practical surrogate markers for preclinical AD would provide valuable tools. Thus, we sought to validate the utility of conventional magnetic resonance spectroscopy (MRS) as a screening method for preclinical AD. A total of 289 older participants who were cognitively normal at baseline were clinically followed up for analysis of MRS metabolites, including N-acetyl aspartate (NAA) and myo-inositol (MI) in the posterior cingulate cortex (PCC) for 7 years. The 289 participants were retrospectively divided into five groups 7 years after baseline: 200 (69%) remained cognitively normal; 53 (18%) developed mild cognitive impairment (MCI); 21 (7%) developed AD; eight (2%) developed Parkinson's disease with normal cognition, and seven (2%) developed dementia with Lewy bodies (DLB). The NAA/MI ratios of the PCC in the AD, MCI, and DLB groups were significantly decreased compared with participants who maintained normal cognition from baseline to 7 years after baseline. MMSE scores 7 years after baseline were significantly correlated with MI/Cr and NAA/MI ratios in the PCC. These results suggest that cognitively normal elderly subjects with low NAA/MI ratios in the PCC might be at risk of progression to clinical AD. Thus, the NAA/MI ratio in the PCC measured with conventional 1H MRS should be reconsidered as a possible adjunctive screening marker of preclinical AD in clinical practice.

Detecting At-Risk Alzheimer's Disease Cases. - Fladby, Tormod; Pålhaugen, Lene; Selnes, Per; Waterloo, Knut; Bråthen, Geir; Hessen, Erik; Almdahl, Ina Selseth; Arntzen, Kjell-Arne; Auning, Eirik; Eliassen, Carl Fredrik; Espenes, Ragna; Grambaite, Ramune; et al. (J Alzheimers Dis, 2017)
While APOEɛ4 is the major genetic risk factor for Alzheimer's disease (AD), amyloid dysmetabolism is an initial or early event predicting clinical disease and is an important focus for secondary intervention trials. To improve identification of cases with increased AD risk, we evaluated recruitment procedures using pathological CSF concentrations of Aβ42 (pAβ) and APOEɛ4 as risk markers in a multi-center study in Norway. In total, 490 subjects aged 40-80 y were included after response to advertisements and media coverage or memory clinics referrals. Controls (n = 164) were classified as normal controls without first-degree relatives with dementia (NC), normal controls with first-degree relatives with dementia (NCFD), or controls scoring below norms on cognitive screening. Patients (n = 301) were classified as subjective cognitive decline or mild cognitive impairment. Subjects underwent a clinical and cognitive examination and MRI according to standardized protocols. Core biomarkers in CSF from 411 and APOE genotype from 445 subjects were obtained. Cases (both self-referrals (n = 180) and memory clinics referrals (n = 87)) had increased fractions of pAβ and APOEɛ4 frequency compared to NC. Also, NCFD had higher APOEɛ4 frequencies without increased fraction of pAβ compared to NC, and cases recruited from memory clinics had higher fractions of pAβ and APOEɛ4 frequency than self-referred. This study shows that memory clinic referrals are pAβ enriched, whereas self-referred and NCFD cases more frequently are pAβ negative but at risk (APOEɛ4 positive), suitable for primary intervention.

Development of a Late-Life Dementia Prediction Index with Supervised Machine Learning in the Population-Based CAIDE Study. - Pekkala, Timo; Hall, Anette; Lötjönen, Jyrki; Mattila, Jussi; Soininen, Hilkka; Ngandu, Tiia; Laatikainen, Tiina; Kivipelto, Miia; Solomon, Alina (J Alzheimers Dis, 2017)
BACKGROUND AND OBJECTIVE: This study aimed to develop a late-life dementia prediction model using a novel validated supervised machine learning method, the Disease State Index (DSI), in the Finnish population-based CAIDE study. METHODS: The CAIDE study was based on previous population-based midlife surveys. CAIDE participants were re-examined twice in late-life, and the first late-life re-examination was used as baseline for the present study. The main study population included 709 cognitively normal subjects at first re-examination who returned to the second re-examination up to 10 years later (incident dementia n = 39). An extended population (n = 1009, incident dementia 151) included non-participants/non-survivors (national registers data). DSI was used to develop a dementia index based on first re-examination assessments. Performance in predicting dementia was assessed as area under the ROC curve (AUC). RESULTS: AUCs for DSI were 0.79 and 0.75 for main and extended populations. Included predictors were cognition, vascular factors, age, subjective memory complaints, and APOE genotype. CONCLUSION: The supervised machine learning method performed well in identifying comprehensive profiles for predicting dementia development up to 10 years later. DSI could thus be useful for identifying individuals who are most at risk and may benefit from dementia prevention interventions.

Diabetes is Not Associated with Alzheimer's Disease Neuropathology. - Dos Santos Matioli, Maria Niures Pimentel; Suemoto, Claudia Kimie; Rodriguez, Roberta Diehl; Farias, Daniela Souza; da Silva, Magnólia Moreira; Leite, Renata Elaine Paraizo; Ferretti-Rebustini, Renata Eloah Lucena; Farfel, José Marcelo; Pasqualucci, Carlos Augusto; Jacob Filho, Wilson; Arvanitakis, Zoe; Naslavsky, Michel Satya; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Previous evidence linking diabetes to Alzheimer's disease (AD) neuropathology is mixed and scant data are available from low- and middle-income countries. OBJECTIVE: To investigate the association between diabetes and AD neuropathology in a large autopsy study of older Brazilian adults. METHODS: In this cross-sectional study, diabetes was defined by diagnosis during life or use of antidiabetic medication. A standardized neuropathological examination was performed using immunohistochemistry. The associations of diabetes with Consortium to Establish and Registry for Alzheimer Disease (CERAD) scores for neuritic plaques and Braak-Braak (BB) scores for neurofibrillary tangles were investigated using multivariable ordinal logistic regression. We investigated effect modification of education, race, and APOE on these associations. RESULTS: Among 1,037 subjects (mean age = 74.4±11.5 y; mean education = 4.0±3.7 y; 48% male, 61% White), diabetes was present in 279 subjects. Diabetes was not associated with BB (OR = 1.12, 95% CI = 0.81-1.54, p = 0.48) or with CERAD (OR = 0.97, 95% CI = 0.68-1.38, p = 0.86) scores on analyses adjusted for sociodemographic and clinical variables. We observed effect modification by the APOE allele ɛ4 on the association between diabetes mellitus and BB scores. CONCLUSION: No evidence of an association between diabetes and AD neuropathology was found in a large sample of Brazilians; however, certain subgroups, such as APOE allele ɛ4 carriers, had higher odds of accumulation of neurofibrillary tangles.

Do Cancer Drugs Counteract Neurodegeneration? Repurposing for Alzheimer's Disease. - Monacelli, Fiammetta; Cea, Michele; Borghi, Roberta; Odetti, Patrizio; Nencioni, Alessio (J Alzheimers Dis, 2017)
In spite of in depth investigations in the field of the amyloid cascade hypothesis, so far, no disease modifying therapy has been developed for Alzheimer's disease (AD). The pathophysiology provides some evidence of the inverse correlation between cancer and AD. Both AD and cancer are characterized by abnormal cellular behaviors; trigger factors along with a meta synchronously action is expected to drive cancer or neurodegeneration, supporting, respectively, progressive neuronal loss or uncontrolled cell proliferation in cancer cells. So far, cancer and AD are seemingly two opposite ends of the same biological spectrum. Basic science increasingly indicates shared molecular mechanisms between cancer and AD and gives weight to key relevant biological theories; according to them, the inverse tuning of clustered gene expression, the sharing of mutual independent pathway or the deregulated unfolded proteins system (UPR) may count for this inverse association. Additionally, the common biological background gave credibility to the recent discovery of a repurposing role for cancer drugs in AD. It refers to the development of new uses for existing pharmaceuticals having the same role as the original mechanism or to the discovery of a new drug action with disease modifying effects. The present review summarizes the most important biological theories that link neurodegeneration and cancer and provides an up-to-date revision of the repurposing cancer agents for AD. The review also addresses the gap of knowledge, since drug cancer repositioning holds an important promise but further investigations are warranted to ascertain the clinical relevance of such attractive clinical candidate compounds for AD.

Do Hearing Aids Influence Behavioral and Psychological Symptoms of Dementia and Quality of Life in Hearing Impaired Alzheimer's Disease Patients and Their Caregivers? - Adrait, Arnaud; Perrot, Xavier; Nguyen, Marie-France; Gueugnon, Marine; Petitot, Charles; Collet, Lionel; Roux, Adeline; Bonnefoy, Marc (J Alzheimers Dis, 2017)
BACKGROUND: It has been suggested that age-related hearing loss (ARHL) and Alzheimer's disease (AD) are commonly associated. OBJECTIVE: The Alzheimer Disease, Presbycusis and Hearing Aids (ADPHA) clinical trial assessed the influence of hearing aids (HAs) on patients affected by ARHL and AD, as judged by behavioral symptoms and functional abilities, as well as patient and caregiver quality of life (QoL). METHODS: A multicenter double-blind randomized placebo-controlled trial, with a semi-crossover procedure over 12 months, was conducted from 2006 to 2012. For the first 6 months, the active group was treated with active HAs and the placebo group with inactive HAs. For the last 6 months, HAs in the placebo group were activated. Assessment was conducted at baseline, 6 months, and 12 months. We performed intergroup and intragroup comparisons. Behavioral symptoms were assessed by neuropsychiatric inventory (NPI), functional abilities by instrumental activities of daily living, and QoL by Zarit, Alzheimer's disease related quality of life, and simplified Duke scales. RESULTS: Fifty-one patients were included and randomized: 22 in active group (mean NPI 17.6; mean age 83±6.2) and 26 in placebo group (mean NPI 25.8; mean age 82.3±7.2) were fitted with HAs. At 6-month follow-up, all scores worsened without significant difference between the two groups. In placebo group, activation of HAs had no effect on the change of these scores. CONCLUSION: These findings do not provide evidence of improvement in behavioral symptoms, functional status, or QoL of hearing impaired AD patients and their caregivers after 6 months of HA use. However, we cannot exclude that HAs may have a positive effect in patients aged less than 75 years.

EEG Dominant Frequency Peak Differentiates Between Alzheimer's Disease and Frontotemporal Lobar Degeneration. - Goossens, Joery; Laton, Jorne; Van Schependom, Jeroen; Gielen, Jeroen; Struyfs, Hanne; Van Mossevelde, Sara; Van den Bossche, Tobi; Goeman, Johan; De Deyn, Peter Paul; Sieben, Anne; Martin, Jean-Jacques; Van Broeckhoven, Christine; et al. (J Alzheimers Dis, 2017)
We investigated the power of EEG as biomarker in differential diagnosis of Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD). EEG was recorded from 106 patients with AD or FTLD, of which 37 had a definite diagnosis, and 40 controls. Dominant frequency peaks were extracted for all 19 channels, for each subject. The average frequency of the largest dominant frequency peaks (maxpeak) was significantly lower in AD than FTLD patients and controls. Based on ROC analysis, classification could be made with diagnostic accuracy of 78.9%. Our findings show that quantitative analysis of EEG maxpeak frequency is an easy and useful measure for differential dementia diagnosis.

The Effects of Cortical Hypometabolism and Hippocampal Atrophy on Clinical Trajectories in Mild Cognitive Impairment with Suspected Non-Alzheimer's Pathology: A Brief Report. - Chung, Jun Ku; Plitman, Eric; Nakajima, Shinichiro; Caravaggio, Fernando; Shinagawa, Shunichiro; Iwata, Yusuke; Gerretsen, Philip; Kim, Julia; Takeuchi, Hiroyoshi; Patel, Raihaan; Chakravarty, M Mallar; Strafella, Antonio; et al. (J Alzheimers Dis, 2017)
The clinical and structural trajectories of suspected non-Alzheimer' pathology (SNAP) remain elusive due to its heterogeneous etiology. Baseline and longitudinal clinical (global cognition, daily functioning, symptoms of dementia, and learning memory) and hippocampal volume trajectories over two years were compared between patients with amnestic mild cognitive impairment (aMCI) with SNAP with reduced hippocampal volumes (SNAP+HIPPO) and aMCI patients with SNAP without reduced hippocampal volumes. SNAP+HIPPO showed overall worse baseline cognitive functions. Longitudinally, SNAP+HIPPO showed faster deterioration of clinical symptoms of dementia. Having both hippocampal atrophy and cortical hypometabolism without amyloid pathology may exacerbate symptoms of dementia in aMCI.

Effects of Exercise on Cognitive Function in Older People with Dementia: A Randomized Controlled Trial. - Toots, Annika; Littbrand, Håkan; Boström, Gustaf; Hörnsten, Carl; Holmberg, Henrik; Lundin-Olsson, Lillemor; Lindelöf, Nina; Nordström, Peter; Gustafson, Yngve; Rosendahl, Erik (J Alzheimers Dis, 2017)
BACKGROUND: Although physical exercise has been suggested to influence cognitive function, previous exercise studies show inconsistent results in people with dementia. OBJECTIVES: To investigate effects of exercise on cognitive function in people with dementia. METHOD: The Umeå Dementia and Exercise (UMDEX) study, a cluster-randomized controlled trial, was set in 16 nursing homes in Umeå, Sweden. One hundred-and-forty-one women and 45 men with dementia; mean age of 85 y and mean Mini-Mental State Examination (MMSE) score of 15, were randomized to a High-Intensity Functional Exercise program or a seated attention control activity. Blinded assessors measured global cognitive function using the MMSE and the Alzheimer's disease Assessment Scale - Cognitive subscale (ADAS-Cog), and executive function using Verbal fluency (VF) at baseline and 4 months (directly after intervention completion), and MMSE and VF at 7 months. RESULTS: Linear mixed models showed no between-group effects in mean difference from baseline (95% confidence intervals, CI) at 4 months in MMSE (-0.27; 95% CI -1.4 to 0.87, p = 0.644), ADAS-Cog (-1.04, 95% CI -4 to 1.92, p = 0.491), or VF (-0.53, 95% CI -1.42 to 0.35, p = 0.241) or at 7 months in MMSE (-1.15, 95% CI -2.32 to 0.03, p = 0.056) or VF (-0.18, 95% CI -1.09 to 0.74, p = 0.707). CONCLUSION: A 4-month, high-intensity functional exercise program had no superior effects on global cognition or executive function in people with dementia living in nursing homes when compared with an attention control activity.

Effects of Exercise on Type 2 Diabetes Mellitus-Related Cognitive Impairment and Dementia. - Callisaya, Michele; Nosaka, Kazunori (J Alzheimers Dis, 2017)
Cognitive impairment and dementia are common contributors to institutionalization and loss of quality of life in older people. Both type 2 diabetes mellitus (T2DM) and physical inactivity are prevalent and important modifiable risk factors for developing dementia. Physical activity is recommended in the management of T2DM, and there is growing evidence that exercise, a subgroup of physical activity, is also beneficial for maintaining and improving brain structure and function. This paper reviews the evidence for a benefit of exercise on T2DM related cognitive impairment and dementia. In addition, the type (e.g., aerobic, resistance), intensity, duration, and frequency of exercise are discussed. This review shows that although exercise has known benefits on the mechanisms linking T2DM to dementia, there are very few randomized controlled trials examining whether this is the case. It is concluded that the uptake of exercise for the brain has great potential to improve quality of life and provide significant cost savings, but further research is warranted to clarify the effects of exercise on T2DM and those on dementia.

The Effects of LW-AFC on the Hippocampal Transcriptome in Senescence-Accelerated Mouse Prone 8 Strain, a Mouse Model of Alzheimer's Disease. - Wang, Jianhui; Liu, Yang; Cheng, Xiaorui; Zhang, Xiaorui; Liu, Feng; Liu, Gang; Qiao, Shanyi; Ni, Ming; Zhou, Wenxia; Zhang, Yongxiang; Li, Fei (J Alzheimers Dis, 2017)
The senescence-accelerated mouse prone 8 (SAMP8) strain is considered a robust experimental model for developing preventative and therapeutic treatments for Alzheimer's disease (AD), a neurodegenerative disease which cannot be effectively prevented, halted, or cured. Our previous studies showed that LW-AFC, a new formula derived from the classical traditional Chinese medicinal prescription Liuwei Dihuang decoction, ameliorates cognitive deterioration in PrP-hAβPPswe/PS1ΔE9 transgenic mice and SAMP8 mice. This study aims to investigate the mechanism that mediates how LW-AFC improves cognitive deficit on the basis of the transcriptome. We conducted a genome-wide survey of gene expression in the hippocampus in mice from the senescence accelerated mouse resistant 1 (SAMR1) strain, from SAMP8 and from LW-AFC treated SAMP8. The results showed that LW-AFC reversed the transcriptome in the hippocampus of SAMP8 mice. The specific investigation of altered gene expression in subtypes defined by cognitive profiles indicated that the systemic lupus erythematosus pathway, spliceosomes, amyotrophic lateral sclerosis, and the insulin signaling were involved in the improvement of cognitive ability by LW-AFC. The expression of genes Enpp2, Etnk1, Epdr1, and Gm5900 in the hippocampus were correlated with that of LW-AFC's ameliorating cognitive impairment in SAMP8 mice. Because LW-AFC is composed of polysaccharides, glycosides, and oligosaccharides, we infer that LW-AFC has direct or indirect effects on altering gene expressions and regulating pathways in the hippocampus of SAMP8 mice. These data are helpful for the enhanced identification of LW-AFC as new therapeutic modalities to AD.

Effects of Multiple Genetic Loci on Age at Onset in Frontotemporal Dementia. - Ferrari, Raffaele; Grassi, Mario; Graziano, Francesca; Palluzzi, Fernando; Archetti, Silvana; Bonomi, Elisa; Bruni, Amalia C; Maletta, Raffaele G; Bernardi, Livia; Cupidi, Chiara; Colao, Rosanna; Rainero, Innocenzo; et al. (J Alzheimers Dis, 2017)
In frontotemporal dementia (FTD), age at disease onset (AAO) is unpredictable in both early and late-onset cases; AAO variability is found even in autosomal dominant FTD. The present study was aimed at identifying genetic modifiers modulating AAO in a large cohort of Italian FTD patients. We conducted an association analysis on 411 FTD patients, belonging to 7 Italian Centers, and for whom AAO was available. Population structure was evaluated by principal component analysis to infer continuous axes of genetic variation, and single linear regression models were applied. A genetic score (GS) was calculated on the basis of suggestive single nucleotide polymorphisms (SNPs) found by association analyses. GS showed genome-wide significant slope decrease by -3.86 (95% CI: -4.64 to -3.07, p < 2×10-16) per standard deviation of the GS for 6 SNPs mapping to genes involved in neuronal development and signaling, axonal myelinization, and glutamatergic/GABA neurotransmission. An increase of the GS was associated with a decrease of the AAO. Our data indicate that there is indeed a genetic component that underpins and modulates up to 14.5% of variability of AAO in Italian FTD. Future studies on genetic modifiers in FTD are warranted.

Effects of Regular and Long-Acting Insulin on Cognition and Alzheimer's Disease Biomarkers: A Pilot Clinical Trial. - Craft, Suzanne; Claxton, Amy; Baker, Laura D; Hanson, Angela J; Cholerton, Brenna; Trittschuh, Emily H; Dahl, Deborah; Caulder, Erin; Neth, Bryan; Montine, Thomas J; Jung, Youngkyoo; Maldjian, Joseph; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Long acting insulin detemir administered intranasally for three weeks enhanced memory for adults with Alzheimer's disease dementia (AD) or amnestic mild cognitive impairment (MCI). The investigation of longer-term administration is necessary to determine whether benefits persist, whether they are similar to benefits provided by regular insulin, and whether either form of insulin therapy affects AD biomarkers. OBJECTIVE: The present study aimed to determine whether four months of treatment with intranasal insulin detemir or regular insulin improves cognition, daily functioning, and AD biomarkers for adults with MCI or AD. METHODS: This randomized, double-blind, placebo-controlled trial included an intent-to-treat sample consisting of 36 adults diagnosed with MCI or mild to moderate AD. Participants received placebo (n = 12), 40 IU of insulin detemir (n = 12), or 40 IU of regular insulin (n = 12) daily for four months, administered with a nasal delivery device. A cognitive battery was administered at baseline and after two and four months of treatment. MRI was administered for all participants and lumbar puncture for a subset (n = 20) at baseline and four months. The primary outcome was change from baseline to four months on a memory composite (sum of Z scores for delayed list and story recall). Secondary outcomes included: global cognition (Alzheimer's Disease Assessment Scale-Cognition), daily functioning (Dementia Severity Rating Scale), MRI volume changes in AD-related regions of interest, and cerebrospinal fluid AD markers. RESULTS: The regular insulin treated group had better memory after two and four months compared with placebo (p < 0.03). No significant effects were observed for the detemir-assigned group compared with the placebo group, or for daily functioning for either group. Regular insulin treatment was associated with preserved volume on MRI. Regular insulin treatment was also associated with reduction in the tau-P181/Aβ42 ratio. CONCLUSION: Future research is warranted to examine the mechanistic basis of treatment differences, and to further assess the efficacy and safety of intranasal insulin.

Efficacy and Safety of Plasma Exchange with 5% Albumin to Modify Cerebrospinal Fluid and Plasma Amyloid-β Concentrations and Cognition Outcomes in Alzheimer's Disease Patients: A Multicenter, Randomized, Controlled Clinical Trial. - Boada, Merce; Anaya, Fernando; Ortiz, Pilar; Olazarán, Javier; Shua-Haim, Joshua R; Obisesan, Thomas O; Hernandez, Isabel; Muñoz, Joan; Buendia, Mar; Alegret, Montserrat; Lafuente, Asunción; Tárraga, Lluís; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Studies conducted in animal models and humans suggest the presence of a dynamic equilibrium of amyloid-β (Aβ) peptide between cerebrospinal fluid (CSF) and plasma compartments. OBJECTIVE: To determine whether plasma exchange (PE) with albumin replacement was able to modify Aβ concentrations in CSF and plasma as well as to improve cognition in patients with mild-moderate Alzheimer's disease (AD). METHODS: In a multicenter, randomized, patient- and rater-blind, controlled, parallel-group, phase II study, 42 AD patients were assigned (1 : 1) to PE treatment or control (sham) groups. Treated patients received a maximum of 18 PE with 5% albumin (Albutein®, Grifols) with three different schedules: two PE/weekly (three weeks), one PE/weekly (six weeks), and one PE/bi- weekly (12 weeks), plus a six-month follow-up period. Plasma and CSF Aβ1-40 and Aβ1-42 levels, as well as cognitive, functional, and behavioral measures were determined. RESULTS: CSF Aβ1-42 levels after the last PE compared to baseline were marginally higher in PE-treated group versus controls (adjusted means of variation: 75.3 versus -45.5 pg/mL; 95% CI: -19.8, 170.5 versus 135.1, 44.2; p = 0.072). Plasma Aβ1-42 levels were lower in the PE-treated group after each treatment period (p < 0.05). Plasma Aβ1-40 levels showed a saw-tooth pattern variation associated with PE. PE-treated patients scored better in the Boston Naming Test and Semantic Verbal Fluency (p < 0.05) throughout the study. Neuropsychiatric Inventory scores were higher in controls during the PE phase (p < 0.05). CONCLUSION: PE with human albumin modified CSF and plasma Aβ1-42 levels. Patients treated with PE showed improvement in memory and language functions, which persisted after PE was discontinued.

Efficacy of Antidepressants for Depression in Alzheimer's Disease: Systematic Review and Meta-Analysis. - Orgeta, Vasiliki; Tabet, Naji; Nilforooshan, Ramin; Howard, Robert (J Alzheimers Dis, 2017)
BACKGROUND: Depression is common in people with Alzheimer's disease (AD) affecting overall outcomes and decreasing quality of life. Although depression in AD is primarily treated with antidepressants, there are few randomized controlled trials (RCTs) assessing efficacy and results have been conflicting. OBJECTIVES: To systematically review evidence on efficacy of antidepressant treatments for depression in AD. METHODS: Systematic review and meta-analysis of double blind RCTs comparing antidepressants versus placebo for depression in AD. We searched MEDLINE, CINAHL, EMBASE, PsycINFO, the Cochrane Controlled Trials Register and on line national and international registers. Primary outcomes were treatment response and depressive symptoms. Secondary outcomes were cognition, acceptability, and tolerability. Risk of bias was also assessed. RESULTS: Seven studies met inclusion criteria. Three compared sertraline with placebo; one compared both sertraline and mirtazapine to placebo; imipramine, fluoxetine, and clomipramine were evaluated in one study each. In terms of response to treatment (6 studies, 297 patients treated with antidepressants and 223 with placebo), no statistically significant difference between antidepressants and placebo was found (odds ratio (OR) 1.95, 95% CI 0.97-3.92). We found no significant drug-placebo difference for depressive symptoms (5 studies, 311 patients, SMD -0.13; 95% CI -0.49 to 0.24). Overall quality of the evidence was moderate because of methodological limitations in studies and the small number of trials. CONCLUSION: Despite the importance of depression in people with AD, few RCTs are available on efficacy of antidepressants, limiting clear conclusions of their potential role. There is a need for further high quality RCTs.

Efficacy of Hearing Aids on the Cognitive Status of Patients with Alzheimer's Disease and Hearing Loss: A Multicenter Controlled Randomized Trial. - Nguyen, Marie-France; Bonnefoy, Marc; Adrait, Arnaud; Gueugnon, Marine; Petitot, Charles; Collet, Lionel; Roux, Adeline; Perrot, Xavier (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: This study evaluated the cognitive benefit of hearing aids (HA) in older patients with Alzheimer's disease (AD) and hearing loss (HL) after a 6- and 12-month period of utilization. METHODS: A multicenter double-blind randomized placebo-controlled trial was conducted in patients aged more than 65 years. A group was equipped with active HA for 6 months (active group) and a second group had placebo HA for 6 months (placebo group) followed by a secondary activation phase for a further 6 months (semi crossover procedure). Both groups were retested after a 12-month period. The primary endpoint was the change from baseline of the Alzheimer's Disease Assessment Scale-Cognitive subscale (ADAS Cog) after a 6-month period in both groups and after 6 months of secondary HA activation in the placebo group. A smaller cognitive decline should be obtained with HA use; an increase in ADAS Cog score of less than 6 points was defined a success. RESULTS: Fifty-one patients aged 68 to 99 years were included; 38 attended the 6-month visit: 18 in the active group and 20 in the placebo group. At 6 months, 14 (82.4%) successes were noticed in the active group, and 15 (88.2%) in the placebo group (p = 1.0); delta ADAS Cog in the active group was 1.8±5.3 and 1.3±5.3 in the placebo group (p = 0.8). In the placebo group, after the secondary HA activation, no significant improvement was observed. CONCLUSION: No significant effect of HA use was observed after 6 months of follow-up in patients with AD and HL.

Ethnic Variations in Prognosis of Patients with Dementia: A Prospective Nationwide Registry Linkage Study in The Netherlands. - Agyemang, Charles; van de Vorst, Irene E; Koek, Huiberdina L; Bots, Michiel L; Seixas, Azizi; Norredam, Marie; Ikram, Umar; Stronks, Karien; Vaartjes, Ilonca (J Alzheimers Dis, 2017)
BACKGROUND: Data on dementia prognosis among ethnic minority groups are limited in Europe. OBJECTIVE: We assessed differences in short-term (1-year) and long-term (3-year) mortality and readmission risk after a first hospitalization or first ever referral to a day clinic for dementia between ethnic minority groups and the ethnic Dutch population in the NetherlandsMethods: Nationwide prospective cohorts of first hospitalized dementia patients (N = 55,827) from January 1, 2000 to December 31, 2010 were constructed. Differences in short-term and long-term mortality and readmission risk following hospitalization or referral to the day clinic between ethnic minority groups (Surinamese, Turkish, Antilleans, Indonesians) and the ethnic Dutch population were investigated using Cox proportional hazard regression models with adjustment for age, sex, and comorbidities. RESULTS: Age-sex-adjusted short-term and long-term risks of death following a first hospitalization with dementia were comparable between the ethnic minority groups and the ethnic Dutch. Age- and sex-adjusted risk of admission was higher only in Turkish compared with ethnic Dutch (HR 1.57, 95% CI,1.08-2.29). The difference between Turkish and the Dutch attenuated and was no longer statistically significant after further adjustment for comorbidities. There were no ethnic differences in short-term and long-term risk of death, and risk of readmission among day clinic patients. CONCLUSION: Compared with Dutch patients with a comparable comorbidity rate, ethnic minority patients with dementia did not have a worse prognosis. Given the poor prognosis of dementia, timely and targeted advance care planning is essential, particularly in ethnic minority groups who are mired by cultural barriers and where uptake of advance care planning is known to be low.

Exercise Training and Functional Connectivity Changes in Mild Cognitive Impairment and Healthy Elders. - Chirles, Theresa J; Reiter, Katherine; Weiss, Lauren R; Alfini, Alfonso J; Nielson, Kristy A; Smith, J Carson (J Alzheimers Dis, 2017)
BACKGROUND: Effective interventions are needed to improve brain function in mild cognitive impairment (MCI), an early stage of Alzheimer's disease (AD). The posterior cingulate cortex (PCC)/precuneus is a hub of the default mode network (DMN) and is preferentially vulnerable to disruption of functional connectivity in MCI and AD. OBJECTIVE: We investigated whether 12 weeks of aerobic exercise could enhance functional connectivity of the PCC/precuneus in MCI and healthy elders. METHODS: Sixteen MCI and 16 healthy elders (age range = 60-88) engaged in a supervised 12-week walking exercise intervention. Functional MRI was acquired at rest; the PCC/precuneus was used as a seed for correlated brain activity maps. RESULTS: A linear mixed effects model revealed a significant interaction in the right parietal lobe: the MCI group showed increased connectivity while the healthy elders showed decreased connectivity. In addition, both groups showed increased connectivity with the left postcentral gyrus. Comparing pre to post intervention changes within each group, the MCI group showed increased connectivity in 10 regions spanning frontal, parietal, temporal and insular lobes, and the cerebellum. Healthy elders did not demonstrate any significant connectivity changes. CONCLUSION: The observed results show increased functional connectivity of the PCC/precuneus in individuals with MCI after 12 weeks of moderate intensity walking exercise training. The protective effects of exercise training on cognition may be realized through the enhancement of neural recruitment mechanisms, which may possibly increase cognitive reserve. Whether these effects of exercise training may delay further cognitive decline in patients diagnosed with MCI remains to be demonstrated.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Exercise; Exercise Test; Female; Gyrus Cinguli; Humans; Image Processing, Computer-Assisted; Linear Models; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Oxygen; Psychiatric Status Rating Scales

Failure to Recover from Proactive Semantic Interference and Abnormal Limbic Connectivity in Asymptomatic, Middle-Aged Offspring of Patients with Late-Onset Alzheimer's Disease. - Sánchez, Stella M; Abulafia, Carolina; Duarte-Abritta, Barbara; de Guevara, M Soledad Ladrón; Castro, Mariana N; Drucaroff, Lucas; Sevlever, Gustavo; Nemeroff, Charles B; Vigo, Daniel E; Loewenstein, David A; Villarreal, Mirta F; Guinjoan, Salvador M (J Alzheimers Dis, 2017)
BACKGROUND: We have obtained previous evidence of limbic dysfunction in middle-aged, asymptomatic offspring of late-onset Alzheimer's disease (LOAD) patients, and failure to recover from proactive semantic interference has been shown to be a sensitive cognitive test in other groups at risk for LOAD. OBJECTIVE: To assess the effects of specific proactive semantic interference deficits as they relate to functional magnetic resonance imaging (fMRI) neocortical and limbic functional connectivity in middle aged offspring of individuals with LOAD (O-LOAD) and age-equivalent controls. METHODS: We examined 21 O-LOAD and 20 controls without family history of neurodegenerative disorders (CS) on traditional measures of cognitive functioning and the LASSI-L, a novel semantic interference test uniquely sensitive to the failure to recover from proactive interference (frPSI). Cognitive tests then were correlated to fMRI connectivity of seeds located in entorhinal cortex and anterodorsal thalamic nuclei among O-LOAD and CS participants. RESULTS: Relative to CS, O-LOAD participants evidenced lower connectivity between entorhinal cortex and orbitofrontal, anterior cingulate, and anterior temporal cortex. In the offspring of LOAD patients, LASSI-L measures of frPSI were inversely associated with connectivity between anterodorsal thalamus and contralateral posterior cingulate. Intrusions on the task related to frPSI were inversely correlated with a widespread connectivity network involving hippocampal, insular, posterior cingulate, and dorsolateral prefrontal cortices, along with precunei and anterior thalamus in this group. Different patterns of connectivity associated with frPSI were observed among controls. CONCLUSION: The present results suggest that both semantic interference deficits and connectivity abnormalities might reflect limbic circuit dysfunction as a very early clinical signature of LOAD pathology, as previously demonstrated for other limbic phenotypes, such as sleep and circadian alterations.

Five-Year Longitudinal Brain Volume Change in Healthy Elders at Genetic Risk for Alzheimer's Disease. - Reiter, Katherine; Nielson, Kristy A; Durgerian, Sally; Woodard, John L; Smith, J Carson; Seidenberg, Michael; Kelly, Dana A; Rao, Stephen M (J Alzheimers Dis, 2017)
Neuropathological changes associated with Alzheimer's disease (AD) precede symptom onset by more than a decade. Possession of an apolipoprotein E (APOE) ɛ4 allele is the strongest genetic risk factor for late onset AD. Cross-sectional studies of cognitively intact elders have noted smaller hippocampal/medial temporal volumes in ɛ4 carriers (ɛ4+) compared to ɛ4 non-carriers (ɛ4-). Few studies, however, have examined long-term, longitudinal, anatomical brain changes comparing healthy ɛ4+ and ɛ4- individuals. The current five-year study examined global and regional volumes of cortical and subcortical grey and white matter and ventricular size in 42 ɛ4+ and 30 ɛ4- individuals. Cognitively intact participants, ages 65-85 at study entry, underwent repeat anatomical MRI scans on three occasions: baseline, 1.5, and 4.75 years. Results indicated no between-group volumetric differences at baseline. Over the follow-up interval, the ɛ4+ group experienced a greater rate of volume loss in total grey matter, bilateral hippocampi, right hippocampal subfields, bilateral lingual gyri, bilateral parahippocampal gyri, and right lateral orbitofrontal cortex compared to the ɛ4- group. Greater loss in grey matter volumes in ɛ4+ participants were accompanied by greater increases in lateral, third, and fourth ventricular volumes. Rate of change in white matter volumes did not differentiate the groups. The current results indicate that longitudinal measurements of brain atrophy can serve as a sensitive biomarker for identifying neuropathological changes in persons at genetic risk for AD and potentially, for assessing the efficacy of treatments designed to slow or prevent disease progression during the preclinical stage of AD.

Frontal Lobe Function Correlates with One-Year Incidence of Urinary Incontinence in Elderly with Alzheimer Disease. - Sugimoto, Taiki; Yoshida, Masaki; Ono, Rei; Murata, Shunsuke; Saji, Naoki; Niida, Shumpei; Toba, Kenji; Sakurai, Takashi (J Alzheimers Dis, 2017)
BACKGROUND: Urinary incontinence (UI) is frequently observed in patients with Alzheimer's disease (AD). Although previous works highlight the association between frontal lobe-related function and UI, causal relationship is unclear. OBJECTS: To clarify the longitudinal association between frontal lobe function and the incidence of UI at 1 year in patients with AD. METHODS: The subjects were 215 continent AD patients who attended the Memory Clinic of the National Center for Geriatrics and Gerontology of Japan during the period from March 2011 to December 2014. The absence or presence of UI was operationally assigned by the dementia behavior disturbance scale subscale, which was completed by the patients' caregivers. Frontal lobe function was assessed using the Frontal Assessment Battery (FAB). Other confounding factors including demographic data, cognitive status, vitality, mood, physical performance, and use of medication (cholinesterase inhibitors, calcium channel blockers [CCBs], diuretics, alpha blockers and anticholinergic drugs) were assessed. RESULTS: During 1-year follow up (mean: 377.4±83.7 days), the incidence of UI was 12.1% (n = 26). Patients with UI had significantly lower FAB performance at baseline (no UI versus UI = 9.3±2.8 versus 7.8±2.7). In multivariate analysis, stepwise logistic regression analysis demonstrated that FAB (odds ratio [OR] = 0.79, 95% confidence interval [CI] = 0.66-0.94) and the use of CCB (OR = 2.72, 95% CI = 1.09-6.77) were significantly associated with UI at 1 year. CONCLUSION: The results of study indicate that frontal lobe dysfunction is predictor for UI in patients with AD.

Functional Connectivity in the Default Mode Network is Reduced in Association with Nocturnal Awakening in Mild Cognitive Impairment. - McKinnon, Andrew C; Duffy, Shantel L; Cross, Nathan E; Terpening, Zoe; Grunstein, Ron R; Lagopoulos, Jim; Batchelor, Jennifer; Hickie, Ian B; Lewis, Simon J G; Shine, James M; Naismith, Sharon L (J Alzheimers Dis, 2017)
BACKGROUND: Sleep disturbance is prevalent in MCI, and is a risk factor for cognitive deterioration. OBJECTIVE: To identify functional connectivity deficits in the default mode network (DMN) in patients with mild cognitive impairment (MCI) and sleep disturbance, relative to MCIs with intact sleep. METHODS: Participants comprised 47 adults aged 55 years and over, recruited from the Healthy Brain Ageing Clinic at the Brain and Mind Centre, Sydney, Australia. This sample contained 15 controls and 32 participants meeting criteria for MCI. Participants underwent resting-state fMRI and actigraphy, along with comprehensive neuropsychological, medical and psychiatric assessment. MCIs were split into two groups according to average wake after sleep onset (WASO) per night. WASO equal to or greater than 1 standard deviation (SD) above the control mean was deemed to reflect disturbed sleep. There were 11 patients in the MCI sleep-disturbed group, and 21 in the MCI sleep-intact group. RESULTS: Relative to controls, MCIs demonstrated significant connectivity reductions between parietal and temporoparietal regions, and between temporal regions. Relative to MCIs with intact sleep, MCIs with sleep disturbance demonstrated reductions in functional connectivity between temporal and parietal regions, and between temporal and temporoparietal regions. CONCLUSIONS: MCIs with nocturnal awakenings demonstrate reductions in DMN connectivity. These reductions comprise brain regions that are crucially involved in sleep and memory processes. These results strengthen our previous findings, which found reduced connectivity in MCIs with self-reported sleep disturbances. Future studies may build on these findings through incorporating complementary neuroimaging techniques and experimental manipulations of sleep.

Galantamine Response Associates with Agitation and the Prefrontal Cortex in Patients with Alzheimer's Disease. - Nakayama, Sachiko; Suda, Akimitsu; Nakanishi, Atsushi; Motoi, Yumiko; Hattori, Nobutaka (J Alzheimers Dis, 2017)
Behavioral and psychological symptoms of dementia (BPSD) occur in up to 80% of AD patients and represent one of the largest factors contributing to caregiver burden. To analyze the effect of galantamine on BPSD and caregiver burden, we treated a total of 50 patients with mild AD for 12 weeks and evaluated them using the Neuropsychiatric Inventory (NPI) and Japanese version of the Zarit Caregiver Burden Interview (ZBI). We also performed regional cerebral blood flow single photon emission computed tomography (rCBF SPECT) at baseline using three-dimensional sterotatic surface projections. Total NPI and ZBI scores did not significantly change after 12-week galantamine treatment. To identify the characteristics of patients who showed improvement after galantamine treatment, we divided patients into two groups, those with and those without sub-items on the NPI. Patients with aggression showed improvement in ZBI scores (p < 0.05). A comparison of rCBF SPECT between these two groups indicated that patients with aggression exhibited increased rCBF in the right prefrontal cortex compared with those without aggression. In a patient with aggression, 20-month treatment with galantamine inhibited increases in the rCBF area in the right prefrontal lobe. These results suggest that galantamine response may be related to aggression and dysfunction of the prefrontal cortex.

Gender-Specific Degeneration of Dementia-Related Subcortical Structures Throughout the Lifespan. - Nemeth, Viola Luca; Must, Anita; Horvath, Szatmar; Király, Andras; Kincses, Zsigmond Tamas; Vecsei, Laszlo (J Alzheimers Dis, 2017)
Age-related changes in brain structure are a question of interest to a broad field of research. Structural decline has been consistently, but not unambiguously, linked to functional consequences, including cognitive impairment and dementia. One of the areas considered of crucial importance throughout this process is the medial temporal lobe, and primarily the hippocampal region. Gender also has a considerable effect on volume deterioration of subcortical grey matter (GM) structures, such as the hippocampus. The influence of age×gender interaction on disproportionate GM volume changes might be mediated by hormonal effects on the brain. Hippocampal volume loss appears to become accelerated in the postmenopausal period. This decline might have significant influences on neuroplasticity in the CA1 region of the hippocampus highly vulnerable to pathological influences. Additionally, menopause has been associated with critical pathobiochemical changes involved in neurodegeneration. The micro- and macrostructural alterations and consequent functional deterioration of critical hippocampal regions might result in clinical cognitive impairment-especially if there already is a decline in the cognitive reserve capacity. Several lines of potential vulnerability factors appear to interact in the menopausal period eventually leading to cognitive decline, mild cognitive impairment, or Alzheimer's disease. This focused review aims to delineate the influence of unmodifiable risk factors of neurodegenerative processes, i.e., age and gender, on critical subcortical GM structures in the light of brain derived estrogen effects. The menopausal period appears to be of key importance for the risk of cognitive decline representing a time of special vulnerability for molecular, structural, and functional influences and offering only a narrow window for potential protective effects.

Genetic Risk as a Marker of Amyloid-β and Tau Burden in Cerebrospinal Fluid. - Voyle, Nicola; Patel, Hamel; Folarin, Amos; Newhouse, Stephen; Johnston, Caroline; Visser, Pieter Jelle; Dobson, Richard J B; Kiddle, Steven J (J Alzheimers Dis, 2017)
BACKGROUND: The search for a biomarker of Alzheimer's disease (AD) pathology (amyloid-β (Aβ) and tau) is ongoing, with the best markers currently being measurements of Aβ and tau in cerebrospinal fluid (CSF) and via positron emission tomography (PET) scanning. These methods are relatively invasive, costly, and often have high screening failure rates. Consequently, research is aiming to elucidate blood biomarkers of Aβ and tau. OBJECTIVE: This study aims to investigate a case/control polygenic risk score (PGRS) as a marker of tau and investigate blood markers of a combined Aβ and tau outcome for the first time. A sub-study also considers plasma tau as markers of Aβ and tau pathology in CSF. METHODS: We used data from the EDAR*, DESCRIPA**, and Alzheimer's Disease Neuroimaging Initiative (ADNI) cohorts in a logistic regression analysis to investigate blood markers of Aβ and tau in CSF. In particular, we investigated the extent to which a case/control PGRS is predictive of CSF tau, CSF amyloid, and a combined amyloid and tau outcome. The predictive ability of models was compared to that of age, gender, and APOE genotype ('basic model'). RESULTS: In EDAR and DESCRIPA test data, inclusion of a case/control PGRS was no more predictive of Aβ, and a combined Aβ and tau endpoint than the basic models (accuracies of 66.0%, and 73.3% respectively). The tau model saw a small increase in accuracy compared to basic models (59.6%). ADNI 2 test data also showed a slight increase in accuracy for the Aβ model when compared to the basic models (61.4%). CONCLUSION: We see some evidence that a case/control PGRS is marginally more predictive of Aβ and tau pathology than the basic models. The search for predictive factors of Aβ and tau pathologies, above and beyond demographic information, is still ongoing. Better understanding of AD risk alleles, development of more sensitive assays, and studies of larger sample size are three avenues that may provide such factors. However, the clinical utility of possible predictors of brain Aβ and tau pathologies must also be investigated.*'Beta amyloid oligomers in the early diagnosis of AD and as marker for treatment response'**'Development of screening guidelines and criteria for pre-dementia Alzheimer's disease'.

Genetic Stratification to Identify Risk Groups for Alzheimer's Disease. - Marioni, Riccardo E; Campbell, Archie; Hagenaars, Saskia P; Nagy, Reka; Amador, Carmen; Hayward, Caroline; Porteous, David J; Visscher, Peter M; Deary, Ian J (J Alzheimers Dis, 2017)
Stratification by genetic risk factors for Alzheimer's disease (AD) may help identify groups with the greatest disease risk. Biological changes that cause late-onset AD are likely to occur years, if not decades prior to diagnosis. Here, we select a subset of the Generation Scotland: Scottish Family Health Study cohort in a likely preclinical age-range of 60-70 years (subset n = 3,495 with cognitive and genetic data). We test for cognitive differences by polygenic risk scores for AD. The polygenic scores are constructed using all available SNPs, excluding those within a 500 kb distance of the APOE locus. Additive and multiplicative effects of APOE status on these associations are investigated. Small memory decrements were observed in those with high polygenic risk scores for AD (standardized beta -0.04, p = 0.020). These associations were independent of APOE status. There was no difference in AD polygenic scores across APOE haplotypes (p = 0.72). Individuals with high compared to low polygenic risk scores for AD (top and bottom 5% of the distribution) show cognitive decrements, albeit much smaller than for APOE ɛ4ɛ4 compared to ɛ3ɛ3 individuals (2.3 versus 3.5 fewer points on the processing speed test, and 1.8 versus 2.8 fewer points on the memory test). Polygenic risk scores for AD may help identify older individuals at greatest risk of cognitive decline and preclinical AD.

Higher Peripheral TREM2 mRNA Levels Relate to Cognitive Deficits and Hippocampal Atrophy in Alzheimer's Disease and Amnestic Mild Cognitive Impairment. - Tan, Yi Jayne; Ng, Adeline S L; Vipin, Ashwati; Lim, Joseph K W; Chander, Russell J; Ji, Fang; Qiu, Yingwei; Ting, Simon K S; Hameed, Shahul; Lee, Tih-Shih; Zeng, Li; Kandiah, Nagaendran; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Variants in triggering receptor expressed on myeloid cells 2 (TREM2) are associated with increased Alzheimer's disease (AD) risk. Recent studies have reported inconsistent peripheral TREM2 mRNA expression levels and relationship with cognitive scores in AD and mild cognitive impairment (MCI). Additionally, no study has examined the association of peripheral TREM2 levels with neuroimaging measures in AD and MCI. OBJECTIVE: To determine peripheral TREM2 mRNA levels in AD, amnestic MCI (aMCI) and healthy controls, and the association with cognitive performance and brain structural changes. METHODS: We measured peripheral TREM2 mRNA levels in 80 AD, 30 aMCI, and 86 healthy controls using real time polymerase chain reaction. TREM2 levels were correlated with various cognitive performance and brain volumes, correcting for APOE4 status. RESULTS: TREM2 mRNA levels were significantly higher in AD compared to controls and aMCI. Levels did not differ between aMCI and controls. Corrected for APOE4, higher TREM2 levels correlated with lower Mini-Mental State Examination, Montreal Cognitive Assessment (MoCA) and episodic memory scores, and lower total grey matter and right hippocampal volumes. Whole-brain voxel-based morphometry analysis found negative association between TREM2 mRNA levels and grey matter volumes in temporal, parietal and frontal regions. AD subjects with MoCA scores ≤20 had higher TREM2 levels correlating with smaller total grey matter, left hippocampal and right hippocampal volumes. CONCLUSION: Peripheral TREM2 mRNA levels are higher in AD and are associated with AD-related cognitive deficits and hippocampal atrophy. Our findings suggest that TREM2 may be a potential non-invasive peripheral biomarker for AD diagnosis.

Hippocampal and Clinical Trajectories of Mild Cognitive Impairment with Suspected Non-Alzheimer's Disease Pathology. - Chung, Jun Ku; Plitman, Eric; Nakajima, Shinichiro; Caravaggio, Fernando; Iwata, Yusuke; Gerretsen, Philip; Kim, Julia; Takeuchi, Hiroyoshi; Shinagawa, Shunichiro; Patel, Raihaan; Chakravarty, M Mallar; Graff-Guerrero, Ariel (J Alzheimers Dis, 2017)
Suspected non-Alzheimer's disease pathology (SNAP) characterizes individuals showing neurodegeneration (e.g., hypometabolism) without amyloid-β (Aβ). Findings from previous studies regarding clinical and structural trajectories of SNAP are inconsistent. Using data from the Alzheimer's Disease Neuroimaging Initiative, patients with amnestic mild cognitive impairment (MCI) were categorized into four groups: amyloid positive with hypometabolism (Aβ+ND+), amyloid only (Aβ+ND-), neither amyloid nor hypometabolism (Aβ-ND-), and SNAP (Aβ-ND+). Aβ+ND+(n = 33), Aβ+ND-(n = 32), and Aβ-ND-(n = 36) were matched to SNAP for age, gender, apolipoprotein E4 (apoE4) genotype, and scores on the Montreal Cognitive Assessment. Elderly controls (n = 40) were also matched to SNAP for age, gender, and apoE4 genotype. Longitudinal changes were compared across groups in terms of hippocampal volume, clinical symptoms, daily functioning, and cognitive functioning over a 2-year period. At baseline, no difference in cognition and functioning was observed between SNAP and Aβ+groups. SNAP showed worse clinical symptoms and impaired functioning at baseline compared to Aβ-ND-and controls. Two years of follow-up showed no differences in hippocampal volume changes between SNAP and any of the comparison groups. SNAP showed worse functional deterioration in comparison to Aβ-ND-and controls. However, Aβ+ND+ showed more severe changes in clinical symptoms in comparison to SNAP. Thus, patients with MCI and SNAP showed 1) more severe functional deterioration compared to Aβ-ND-and controls, 2) no differences with Aβ+ND-, and 3) less cognitive deterioration than Aβ+ND+. Future studies should investigate what causes SNAP, which is different from typical AD pathology and biomarker cascades.

Implication of the APP Gene in Intellectual Abilities. - Myrum, Craig; Nikolaienko, Oleksii; Bramham, Clive R; Haavik, Jan; Zayats, Tetyana (J Alzheimers Dis, 2017)
BACKGROUND: Cognitive functions are highly heritable and polygenic, though the source of this genetic influence is unclear. On the neurobiological level, these functions rely on effective neuroplasticity, in which the activity-regulated cytoskeleton associated protein (ARC) plays an essential role. OBJECTIVES: To examine whether the ARC gene complex may contribute to the genetic components of intellectual function given the crucial role of ARC in brain plasticity and memory formation. METHODS: The ARC complex was tested for association with intelligence (IQ) in children from the Avon Longitudinal Study of Parents and Children (ALSPAC, N = 5,165). As Alzheimer's disease (AD) shares genetics with cognitive functioning, the association was followed up in an AD sample (17,008 cases, 37,154 controls). RESULTS: The ARC complex revealed association with verbal and total IQ (empirical p = 0.027 and 0.041, respectively) in the ALSPAC. The strongest single variant signal (rs2830077; empirical p = 0.018), within the APP gene, was confirmed in the AD sample (p = 2.76E-03). Functional analyses of this variant showed its preferential binding to the transcription factor CP2. DISCUSSION: This study implicates APP in childhood IQ. While follow-up studies are needed, this observation could help elucidate the etiology of disorders associated with cognitive dysfunction, such as AD.

Improved Cerebrospinal Fluid-Based Discrimination between Alzheimer's Disease Patients and Controls after Correction for Ventricular Volumes. - van Waalwijk van Doorn, Linda J C; Gispert, Juan D; Kuiperij, H Bea; Claassen, Jurgen A H R; Arighi, Andrea; Baldeiras, Ines; Blennow, Kaj; Bozzali, Marco; Castelo-Branco, Miguel; Cavedo, Enrica; Emek-Savaş, Derya D; Eren, Erden; et al. (J Alzheimers Dis, 2017)
Cerebrospinal fluid (CSF) biomarkers may support the diagnosis of Alzheimer's disease (AD). We studied if the diagnostic power of AD CSF biomarker concentrations, i.e., Aβ42, total tau (t-tau), and phosphorylated tau (p-tau), is affected by differences in lateral ventricular volume (VV), using CSF biomarker data and magnetic resonance imaging (MRI) scans of 730 subjects, from 13 European Memory Clinics. We developed a Matlab-algorithm for standardized automated segmentation analysis of T1 weighted MRI scans in SPM8 for determining VV, and computed its ratio with total intracranial volume (TIV) as proxy for total CSF volume. The diagnostic power of CSF biomarkers (and their combination), either corrected for VV/TIV ratio or not, was determined by ROC analysis. CSF Aβ42 levels inversely correlated to VV/TIV in the whole study population (Aβ42: r = -0.28; p < 0.0001). For CSF t-tau and p-tau, this association only reached statistical significance in the combined MCI and AD group (t-tau: r = -0.15; p-tau: r = -0.13; both p < 0.01). Correction for differences in VV/TIV improved the differentiation of AD versus controls based on CSF Aβ42 alone (AUC: 0.75 versus 0.81) or in combination with t-tau (AUC: 0.81 versus 0.91). In conclusion, differences in VV may be an important confounder in interpreting CSF Aβ42 levels.

In vivo Patterns of Tau Pathology, Amyloid-β Burden, and Neuronal Dysfunction in Clinical Variants of Alzheimer's Disease. - Dronse, Julian; Fliessbach, Klaus; Bischof, Gérard N; von Reutern, Boris; Faber, Jennifer; Hammes, Jochen; Kuhnert, Georg; Neumaier, Bernd; Onur, Oezguer A; Kukolja, Juraj; van Eimeren, Thilo; Jessen, Frank; et al. (J Alzheimers Dis, 2017)
The clinical heterogeneity of Alzheimer's disease is not reflected in the rather diffuse cortical deposition of amyloid-β. We assessed the relationship between clinical symptoms, in vivo tau pathology, amyloid distribution, and hypometabolism in variants of Alzheimer's disease using novel multimodal PET imaging techniques. Tau pathology was primarily observed in brain regions related to clinical symptoms and overlapped with areas of hypometabolism. In contrast, amyloid-β deposition was diffusely distributed over the entire cortex. Tau PET imaging may thus serve as a valuable biomarker for the localization of neuronal injury in vivo and may help to validate atypical subtypes of Alzheimer's disease.

Increased Release of Apolipoprotein E in Extracellular Vesicles Following Amyloid-β Protofibril Exposure of Neuroglial Co-Cultures. - Nikitidou, Elisabeth; Khoonsari, Payam Emami; Shevchenko, Ganna; Ingelsson, Martin; Kultima, Kim; Erlandsson, Anna (J Alzheimers Dis, 2017)
Extracellular vesicles (EVs), including exosomes and larger microvesicles, have been implicated to play a role in several conditions, including Alzheimer's disease (AD). Since the EV content mirrors the intracellular environment, it could contribute with important information about ongoing pathological processes and may be a useful source for biomarkers, reflecting the disease progression. The aim of the present study was to analyze the protein content of EVs specifically released from a mixed co-culture of primary astrocytes, neurons, and oligodendrocytes treated with synthetic amyloid-β (Aβ42) protofibrils. The EV isolation was performed by ultracentrifugation and validated by transmission electron microscopy. Mass spectrometry analysis of the EV content revealed a total of 807 unique proteins, of which five displayed altered levels in Aβ42 protofibril exposed cultures. The most prominent protein was apolipoprotein E (apoE), and by western blot analysis we could confirm a threefold increase of apoE in EVs from Aβ42 protofibril exposed cells, compared to unexposed cells. Moreover, immunoprecipitation studies demonstrated that apoE was primarily situated inside the EVs, whereas immunocytochemistry indicated that the EVs most likely derived from the astrocytes and the neurons in the culture. The identified Aβ-induced sorting of apoE into EVs from cultured neuroglial cells suggests a possible role for intercellular transfer of apoE in AD pathology and encourage future studies to fully elucidate the clinical relevance of this event.

Intracranial Arterial 4D Flow in Individuals with Mild Cognitive Impairment is Associated with Cognitive Performance and Amyloid Positivity. - Berman, Sara E; Clark, Lindsay R; Rivera-Rivera, Leonardo A; Norton, Derek; Racine, Annie M; Rowley, Howard A; Bendlin, Barbara B; Blennow, Kaj; Zetterberg, Henrik; Carlsson, Cynthia M; Asthana, Sanjay; Turski, Patrick; et al. (J Alzheimers Dis, 2017)
It is becoming increasingly recognized that cerebrovascular disease is a contributing factor in the pathogenesis of Alzheimer's disease (AD). A unique 4D-Flow magnetic resonance imaging (MRI) technique, phase contrast vastly undersampled isotropic projection imaging (PC VIPR), enables examination of angiographic and quantitative metrics of blood flow in the arteries of the Circle of Willis within a single MRI acquisition. Thirty-eight participants with mild cognitive impairment (MCI) underwent a comprehensive neuroimaging protocol (including 4D-Flow imaging) and a standard neuropsychological battery. A subset of participants (n = 22) also underwent lumbar puncture and had cerebrospinal fluid (CSF) assayed for AD biomarkers. Cut-offs for biomarker positivity in CSF resulting from a receiver operating characteristic curve analysis of AD cases and controls from the larger Wisconsin Alzheimer's Disease Research Center cohort were used to classify MCI participants as biomarker positive or negative on amyloid-β (Aβ42), total-tau and total-tau/Aβ42 ratio. Internal carotid artery (ICA) and middle cerebral artery (MCA) mean flow were associated with executive functioning performance, with lower mean flow corresponding to worse performance. MCI participants who were biomarker positive for Aβ42 had lower ICA mean flow than did those who were Aβ42 negative. In sum, mean ICA and MCA arterial flow was associated with cognitive performance in participants with MCI and lower flow in the ICA was associated with amyloid positivity. This provides further evidence for vascular health as a contributing factor in the etiopathogenesis of AD, and could represent a point to intervene in the disease process.

Intranasal Insulin Transport is Preserved in Aged SAMP8 Mice and is Altered by Albumin and Insulin Receptor Inhibition. - Rhea, Elizabeth M; Humann, Samantha R; Nirkhe, Surabhi; Farr, Susan A; Morley, John E; Banks, William A (J Alzheimers Dis, 2017)
Insulin delivered to the level of the cribriform plate (intranasal insulin) is being investigated for its ability to enhance memory in people with Alzheimer's disease (AD). Recent work has shown intranasal insulin can be detected in young CD-1 mice within 5 min and is still present 60 min after injection. The current study determined whether intranasal insulin transport and the subsequent brain distribution of insulin varies in young, healthy mice (CD-1) compared to those with an AD-like phenotype (aged SAMP8) or those pre-disposed to develop such a phenotype (young SAMP8). We showed transport does not vary among these three mouse cohorts, suggesting that intranasal uptake and brain pharmacokinetics do not differ with AD-like signs or the genetic predisposition to developing them. We found that co-administration with bovine serum albumin increased levels of insulin in most brain regions. In addition, the insulin receptor inhibitor, S961, decreases the amount of insulin transported throughout the brain after intranasal injection. These results show insulin delivery to the brain by intranasal administration can be modified with agents such as albumin, may be dependent on the insulin receptor, and is not affected by an AD-like phenotype as presented by the SAMP8 mouse.

Investigating Simulated Driving Errors in Amnestic Single- and Multiple-Domain Mild Cognitive Impairment. - Hird, Megan A; Vesely, Kristin A; Fischer, Corinne E; Graham, Simon J; Naglie, Gary; Schweizer, Tom A (J Alzheimers Dis, 2017)
The areas of driving impairment characteristic of mild cognitive impairment (MCI) remain unclear. This study compared the simulated driving performance of 24 individuals with MCI, including amnestic single-domain (sd-MCI, n = 11) and amnestic multiple-domain MCI (md-MCI, n = 13), and 20 age-matched controls. Individuals with MCI committed over twice as many driving errors (20.0 versus 9.9), demonstrated difficulty with lane maintenance, and committed more errors during left turns with traffic compared to healthy controls. Specifically, individuals with md-MCI demonstrated greater driving difficulty compared to healthy controls, relative to those with sd-MCI. Differentiating between different subtypes of MCI may be important when evaluating driving safety.

Iron Concentration in Deep Gray Matter Structures is Associated with Worse Visual Memory Performance in Healthy Young Adults. - Darnai, Gergely; Nagy, Szilvia Anett; Horváth, Réka; Ács, Péter; Perlaki, Gábor; Orsi, Gergely; Kovács, Norbert; Altbäcker, Anna; Plózer, Enikő; Tényi, Dalma; Weintraut, Rita; Schwarcz, Attila; et al. (J Alzheimers Dis, 2017)
Abnormally high deposition of iron can contribute to neurodegenerative disorders with cognitive impairment. Since previous studies investigating cognition-brain iron accumulation relationships focused on elderly people, our aim was to explore the association between iron concentration in subcortical nuclei and two types of memory performances in a healthy young population. Gender difference was found only in the globus pallidus. Our results showed that iron load characterized by R2* value on the MRI in the caudate and putamen was related to visual memory, while verbal memory was unrelated to iron concentration.

The Link between Type 2 Diabetes and Neurodegeneration: Roles for Amyloid-β, Amylin, and Tau Proteins. - Bharadwaj, Prashant; Wijesekara, Nadeeja; Liyanapathirana, Milindu; Newsholme, Philip; Ittner, Lars; Fraser, Paul; Verdile, Giuseppe (J Alzheimers Dis, 2017)
A wealth of evidence indicates a strong link between type 2 diabetes (T2D) and neurodegenerative diseases such as Alzheimer's disease (AD). Although the precise mechanism remains unclear, T2D can exacerbate neurodegenerative processes. Brain atrophy, reduced cerebral glucose metabolism, and central nervous system insulin resistance are features of both AD and T2D. The T2D phenotype (glucose dyshomeostasis, insulin resistance, impaired insulin signaling) also promotes AD pathology, namely accumulation of amyloid-β (Aβ) and hyperphosphorylated tau and can induce other aspects of neuronal degeneration including inflammatory and oxidative processes. Aβ and hyperphosphorylated tau may also have roles in pancreatic β-cell dysfunction and in reducing insulin sensitivity and glucose uptake by peripheral tissues such as liver, skeletal muscle, and adipose tissue. This suggests a role for these AD-related proteins in promoting T2D. The accumulation of the islet amyloid polypeptide (IAPP, or amylin) within islet β-cells is a major pathological feature of the pancreas in patients with chronic T2D. Co-secreted with insulin, amylin accumulates over time and contributes to β-cell toxicity, ultimately leading to reduced insulin secretion and onset of overt (insulin dependent) diabetes. Recent evidence also suggests that this protein accumulates in the brain of AD patients and may interact with Aβ to exacerbate the neurodegenerative process. In this review, we highlight evidence indicating T2D in promoting Aβ and tau mediated neurodegeneration and the potential contributions of Aβ and tau in promoting a diabetic phenotype that could further exacerbate neurodegeneration. We also discuss underlying mechanisms by which amylin can contribute to the neurodegenerative processes.

Living Alone with Alzheimer's Disease: Data from SveDem, the Swedish Dementia Registry. - Cermakova, Pavla; Nelson, Maja; Secnik, Juraj; Garcia-Ptacek, Sara; Johnell, Kristina; Fastbom, Johan; Kilander, Lena; Winblad, Bengt; Eriksdotter, Maria; Religa, Dorota (J Alzheimers Dis, 2017)
BACKGROUND: Many people with Alzheimer's disease (AD) live alone in their own homes. There is a lack of knowledge about whether these individuals receive the same quality of diagnostics and treatment for AD as patients who are cohabiting. OBJECTIVES: To investigate the diagnostic work-up and treatment of community-dwelling AD patients who live alone. METHODS: We performed a cross-sectional cohort study based on data from the Swedish Dementia Registry (SveDem). We studied patients diagnosed with AD between 2007 and 2015 (n = 26,163). Information about drugs and comorbidities was acquired from the Swedish Prescribed Drug Register and the Swedish Patient Register. RESULTS: 11,878 (46%) patients lived alone, primarily older women. After adjusting for confounders, living alone was inversely associated with receiving computed tomography (OR 0.90; 95% CI 0.82-0.99), magnetic resonance imaging (OR 0.91; 95% CI 0.83-0.99), and lumbar puncture (OR 0.86; 95% CI 0.80-0.92). Living alone was also negatively associated with the use of cholinesterase inhibitors (OR 0.81; 95% CI 0.76; 0.87), memantine (OR 0.77; 95% CI 0.72; 0.83), and cardiovascular medication (OR 0.92; 0.86; 0.99). On the other hand, living alone was positively associated with the use of antidepressants (OR 1.15; 95% CI 1.08; 1.22), antipsychotics (OR 1.41; 95% CI 1.25; 1.58), and hypnotics and sedatives (OR 1.09; 95% CI 1.02; 1.17). CONCLUSIONS: Solitary living AD patients do not receive the same extent of care as those who are cohabiting.

Long-Term Cognitive Decline in Dementia with Lewy Bodies in a Large Multicenter, International Cohort. - Kramberger, Milica G; Auestad, Bjørn; Garcia-Ptacek, Sara; Abdelnour, Carla; Olmo, Josep Garre; Walker, Zuzana; Lemstra, Afina W; Londos, Elisabet; Blanc, Frédéric; Bonanni, Laura; McKeith, Ian; Winblad, Bengt; et al. (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: The aim of this study was to describe the rate and clinical predictors of cognitive decline in dementia with Lewy bodies (DLB), and compare the findings with Alzheimer's disease (AD) and Parkinson's disease dementia (PDD) patients. METHODS: Longitudinal scores for the Mini-Mental State Examination (MMSE) in 1,290 patients (835 DLB, 198 PDD, and 257 AD) were available from 18 centers with up to three years longitudinal data. Linear mixed effects analyses with appropriate covariates were used to model MMSE decline over time. Several subgroup analyses were performed, defined by anti-dementia medication use, baseline MMSE score, and DLB core features. RESULTS: The mean annual decline in MMSE score was 2.1 points in DLB, compared to 1.6 in AD (p = 0.07 compared to DLB) and 1.8 in PDD (p = 0.19). Rates of decline were significantly higher in DLB compared to AD and PDD when baseline MMSE score was included as a covariate, and when only those DLB patients with an abnormal dopamine transporter SPECT scan were included. Decline was not predicted by sex, baseline MMSE score, or presence of specific DLB core features. CONCLUSIONS: The average annual decline in MMSE score in DLB is approximately two points. Although in the overall analyses there were no differences in the rate of decline between the three neurodegenerative disorders, there were indications of a more rapid decline in DLB than in AD and PDD. Further studies are needed to understand the predictors and mechanisms of cognitive decline in DLB.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Cognition Disorders; Cohort Studies; Female; Humans; International Cooperation; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged

Low Florbetapir PET Uptake and Normal Aβ1-42 Cerebrospinal Fluid in an APP Ala713Thr Mutation Carrier. - Lombardi, Gemma; Berti, Valentina; Tedde, Andrea; Bagnoli, Silvia; Piaceri, Irene; Polito, Cristina; Lucidi, Giulia; Ferrari, Camilla; Ginestroni, Andrea; Moretti, Marco; Pupi, Alberto; Nacmias, Benedetta; et al. (J Alzheimers Dis, 2017)
According to the literature, the APP Ala713Thr mutation is associated with Alzheimer's disease and cerebral amyloid angiopathy. We describe a case of dementia clinically compatible with frontotemporal dementia in an APP Ala713Thr mutation carrier in which both [18F]Florbetapir PET uptake and Aβ1-42 cerebrospinal fluid levels were normal. Further evidences are required to establish if this association is only incidental.
Keywords: Alanine; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Aniline Compounds; Brain; Ethylene Glycols; Humans; Male; Middle Aged; Mutation; Peptide Fragments; Positron-Emission Tomography; Threonine

Memantine for Alzheimer's Disease: An Updated Systematic Review and Meta-analysis. - Kishi, Taro; Matsunaga, Shinji; Oya, Kazuto; Nomura, Ikuo; Ikuta, Toshikazu; Iwata, Nakao (J Alzheimers Dis, 2017)
BACKGROUND: The clinical benefit of memantine for Alzheimer's disease (AD) remains inconclusive. OBJECTIVE: We performed an updated systematic review and meta-analysis of the efficacy/safety of memantine in AD. METHODS: We included randomized trials of memantine for AD patients. Cognitive function scores (CF), behavioral disturbances scores (BD), and all-cause discontinuation were used as primary measures. Effect size based on a random-effects model was evaluated in the meta-analyses. RESULTS: Thirty studies (n = 7,567; memantine versus placebo: N = 11, n = 3,298; memantine + cholinesterase inhibitors (M+ChEIs) versus ChEIs: N = 17, n = 4,175) were identified. Memantine showed a significant improvement in CF [standardized mean difference (SMD) = -0.24, 95% confidence intervals (95% CIs) = -0.34, -0.15, p < 0.00001, I2 = 35% ] and BD (SMD = -0.16, 95% CIs = -0.29, -0.04, p = 0.01, I2 = 52%) compared with placebo. In the sensitivity analysis including only patients with moderate-severe AD, memantine was superior to the placebo in reducing BD without considerable heterogeneity (SMD = -0.20, 95% CIs = -0.34, -0.07, p = 0.003, I2 = 36%). Compared with ChEIs, M+ChEIs showed a greater reduction in BD (SMD = -0.20, 95% CIs = -0.36, -0.03, p = 0.02, I2 = 77%) and a trend of CF improvement (SMD = -0.11, 95% CIs = -0.22, 0.01, p = 0.06, I2 = 56%). However, in the sensitivity analysis of double-blind, placebo-controlled studies only, M+ChEIs showed a significant reduction in BD compared with ChEIs without considerable heterogeneity (SMD = -0.11, 95% CIs = -0.21, -0.01, p = 0.04, I2 = 40%). When performing the sensitivity analysis of donepezil studies only, M+ChEIs was superior to ChEIs in improving CF without considerable heterogeneity (SMD = -0.18, 95% CIs = -0.31, -0.05, p = 0.006, I2 = 49%). No differences were detected in all-cause discontinuation between the groups. CONCLUSIONS: The meta-analyses suggest the credible efficacy and safety of memantine in treating AD when used alone or in combination with ChEIs.

Memory Correlates of Alzheimer's Disease Cerebrospinal Fluid Markers: A Longitudinal Cohort Study. - Reijs, Babette L R; Ramakers, Inez H G B; Köhler, Sebastian; Teunissen, Charlotte E; Koel-Simmelink, Marleen; Nathan, Pradeep J; Tsolaki, Magda; Wahlund, Lars-Olof; Waldemar, Gunhild; Hausner, Lucrezia; Vandenberghe, Rik; Johannsen, Peter; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Performance on episodic, semantic, and working memory tests is impaired in Alzheimer's disease (AD)-type dementia, but it is unclear which type of memory test is most strongly associated with early AD biomarkers in cerebrospinal fluid (CSF), and most useful for monitoring disease progression. OBJECTIVE: To examine the association between amyloid-β 1-42 (Aβ42) and tau in CSF with performance on different memory domains at baseline, and how these CSF markers are related with memory decline. METHODS: We included 263 individuals with normal cognition, mild cognitive impairment, AD-type dementia, and non-AD dementia from the European EDAR study. Assessment included CSF Aβ42 and t-tau analyses with INNO-BIA AlzBio3 Luminex assay, the CERAD wordlist learning and delayed recall, animal fluency test, and the CANTAB Paired Associates Learning (PAL) and Spatial Working Memory tasks. Follow-up assessments were performed within 3 years after baseline. RESULTS: At baseline, decreased CSF Aβ42 correlated most strongly with the PAL total errors adjusted and the wordlist delayed recall and increased CSF t-tau with the wordlist delayed recall. Over time, decreased CSF Aβ42 was associated with decline on the wordlist learning, whereas increased CSF t-tau were associated with decline in scores on the wordlist learning, wordlist delayed recall, and animal fluency. Associations were independent of baseline diagnosis. CONCLUSION: Tests assessing episodic verbal and visuospatial memory are most useful for detection of AD pathology. Tests for episodic verbal memory and semantic memory are most useful for tracking memory decline.

Metabolic and Growth Rate Alterations in Lymphoblastic Cell Lines Discriminate Between Down Syndrome and Alzheimer's Disease. - Coskun, Pinar; Helguera, Pablo; Nemati, Zahra; Bohannan, Ryan C; Thomas, Jean; Samuel, Schriner E; Argueta, Jocelyn; Doran, Eric; Wallace, Douglas C; Lott, Ira T; Busciglio, Jorge (J Alzheimers Dis, 2017)
BACKGROUND: Deficits in mitochondrial function and oxidative stress play pivotal roles in Down syndrome (DS) and Alzheimer's disease (AD) and these alterations in mitochondria occur systemically in both conditions. OBJECTIVE: We hypothesized that peripheral cells of elder subjects with DS exhibit disease-specific and dementia-specific metabolic features. To test this, we performed a comprehensive analysis of energy metabolism in lymphoblastic-cell-lines (LCLs) derived from subjects belonging to four groups: DS-with-dementia (DSAD), DS-without-dementia (DS), sporadic AD, and age-matched controls. METHODS: LCLs were studied under regular or minimal feeding regimes with galactose or glucose as primary carbohydrate sources. We assessed metabolism under glycolysis or oxidative phosphorylation by quantifying cell viability, oxidative stress, ATP levels, mitochondrial membrane potential (MMP), mitochondrial calcium uptake, and autophagy. RESULTS: DS and DSAD LCLs showed slower growth rates under minimal feeding. DS LCLs mainly dependent on mitochondrial respiration exhibited significantly slower growth and higher levels of oxidative stress compared to other groups. While ATP levels (under mitochondrial inhibitors) and mitochondrial calcium uptake were significantly reduced in DSAD and AD cells, MMP was decreased in DS, DSAD, and AD LCLs. Finally, DS LCLs showed markedly reduced levels of the autophagy marker LC3-II, underscoring the close association between metabolic dysfunction and impaired autophagy in DS. CONCLUSION: There are significant mitochondrial functional changes in LCLs derived from DS, DSAD, and AD patients. Several parameters analyzed were consistently different between DS, DSAD, and AD lines suggesting that metabolic indicators between LCL groups may be utilized as biomarkers of disease progression and/or treatment outcomes.

The Methylenetetrahydrofolate Reductase C677T Polymorphism and Risk for Late-Onset Alzheimer's disease: Further Evidence in an Italian Multicenter Study. - Stoccoro, Andrea; Tannorella, Pierpaola; Salluzzo, Maria Grazia; Ferri, Raffaele; Romano, Corrado; Nacmias, Benedetta; Siciliano, Gabriele; Migliore, Lucia; Coppedè, Fabio (J Alzheimers Dis, 2017)
BACKGROUND: A functional polymorphism in the methylenetetrahydrofolate reductase (MTHFR) gene, namely C677T (rs1801133), results in increased Hcy levels and has been associated with risk of late-onset Alzheimer's disease (LOAD). Many investigators reported association between rs1801133 and LOAD risk in Asian populations and in carriers of the apolipoprotein E (APOE) ɛ4 allele, but recent meta-analyses suggest a contribution also in other populations, including Caucasians and/or northern Africans. OBJECTIVE: To further address this issue, we performed a relatively large case-control study, including 581 LOAD patients and 468 matched controls of Italian origin. APOE data were available for a subgroup of almost 600 subjects. METHODS: Genotyping for rs1801133 was performed with PCR-RFLP techniques. RESULTS: In the total population, the MTHFR 677T allele (OR = 1.20; 95% CI = 1.01-1.43) and carriers of the MTHFR 677T allele (CT+TT versus CC: OR = 1.34; 95% CI = 1.03-1.73) resulted in increased LOAD risk. Similarly, in APOEɛ4 carriers, we observed an increased frequency of MTHFR 677CT carriers (CT versus CC: OR = 2.82; 95% CI = 1.25-6.32). Very interestingly, also in non-APOEɛ4 carriers, both MTHFR 677T allele (OR = 1.38; 95% CI = 1.03-1.85) and MTHFR 677TT genotype (OR = 2.08; 95% CI = 1.11-3.90) were associated with LOAD. All these associations survived after corrections for age, gender, and multiple testing. CONCLUSIONS: The present results suggest that the MTHFR C677T polymorphism is likely a LOAD risk factor in our cohort, either in APOEɛ4 or in non-APOEɛ4 carriers.

The Mild Behavioral Impairment Checklist (MBI-C): A Rating Scale for Neuropsychiatric Symptoms in Pre-Dementia Populations. - Ismail, Zahinoor; Agüera-Ortiz, Luis; Brodaty, Henry; Cieslak, Alicja; Cummings, Jeffrey; Fischer, Corinne E; Gauthier, Serge; Geda, Yonas E; Herrmann, Nathan; Kanji, Jamila; Lanctôt, Krista L; Miller, David S; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Mild behavioral impairment (MBI) is a construct that describes the emergence at ≥50 years of age of sustained and impactful neuropsychiatric symptoms (NPS), as a precursor to cognitive decline and dementia. MBI describes NPS of any severity, which are not captured by traditional psychiatric nosology, persist for at least 6 months, and occur in advance of or in concert with mild cognitive impairment. While the detection and description of MBI has been operationalized in the International Society to Advance Alzheimer's Research and Treatment - Alzheimer's Association (ISTAART-AA) research diagnostic criteria, there is no instrument that accurately reflects MBI as described. OBJECTIVE: To develop an instrument based on ISTAART-AA MBI criteria. METHODS: Eighteen subject matter experts participated in development using a modified Delphi process. An iterative process ensured items reflected the five MBI domains of 1) decreased motivation; 2) emotional dysregulation; 3) impulse dyscontrol; 4) social inappropriateness; and 5) abnormal perception or thought content. Instrument language was developed a priori to pertain to non-demented functionally independent older adults. RESULTS: We present the Mild Behavioral Impairment Checklist (MBI-C), a 34-item instrument, which can easily be completed by a patient, close informant, or clinician. CONCLUSION: The MBI-C provides the first measure specifically developed to assess the MBI construct as explicitly described in the criteria. Its utility lies in MBI case detection, and monitoring the emergence of MBI symptoms and domains over time. Studies are required to determine the prognostic value of MBI for dementia development, and for predicting different dementia subtypes.

Modulation of Immune Responses to Herpes Simplex Virus Type 1 by IFNL3 and IRF7 Polymorphisms: A Study in Alzheimer's Disease. - Costa, Andrea Saul; Agostini, Simone; Guerini, Franca Rosa; Mancuso, Roberta; Zanzottera, Milena; Ripamonti, Enrico; Racca, Vittorio; Nemni, Raffaello; Clerici, Mario (J Alzheimers Dis, 2017)
Herpes simplex virus type 1 (HSV-1) has long been suspected to play a role in Alzheimer's disease (AD), the most common form of dementia. IFN-lambda (IFN-λ) is one of the key cytokine in innate antiviral defenses and, in particular, has an appreciable antiviral activity against HSV-1 infection. IFN-λ expression is regulated by the interaction between two different proteins: Mediator Complex 23 (MED23) and Interferon-Responsive Transcription Factor 7 (IRF7); single nucleotide polymorphisms (SNPs) in these genes as well as in IFNL3 were shown to be differently distributed in AD patients. In this study, allelic discrimination analysis for IFNL3 rs12979860, MED23 rs3756784, and IRF7 rs6598008, as well as IFN-λ serum concentration and anti-HSV-1 antibody (Ab) titers were performed in 79 AD patients, 57 mild cognitive impairment (MCI) individuals, and 81 healthy controls (HC) who were HSV-1-seropositive. Results showed that INF-λ serum concentration was increased in AD and MCI carrying the IFNL3 T allele compared to HC (AD versus HC: p = 0.014; MCI versus HC: p = 0.029), with the highest anti-HSV-1 Ab titers seen in AD patients carrying the IFNL3 CC genotype (p = 0.012 versus HC). Notably, anti-HSV-1 Ab titers were higher in AD and MCI individuals carrying the IRF7 AA genotype compared to HC (p = 0.018 for both). MED23 polymorphisms did not show any statistical association either with serum IFN-λ or with anti-HSV-1 Ab. Data herein suggest that the IFNL3 rs12979860 and IRF7 rs6598008 polymorphisms modulate immune responses against HSV-1 via their effect on the IFN-λ pathway. These results help to clarify the possible role of HSV-1 infection in AD pathogenesis.

Molecular Mechanisms Underlying Neuroprotective Effect of Intranasal Administration of Human Hsp70 in Mouse Model of Alzheimer's Disease. - Evgen'ev, Michail B; Krasnov, George S; Nesterova, Inna V; Garbuz, David G; Karpov, Vadim L; Morozov, Alexey V; Snezhkina, Anastasiya V; Samokhin, Alexander N; Sergeev, Alexander; Kulikov, Alexei M; Bobkova, Natalia V (J Alzheimers Dis, 2017)
Heat shock protein 70, encoded by the HSPA1A gene in humans, is a key component of the machinery that protects neuronal cells from various stress conditions and whose production significantly declines during the course of aging and as a result of several neurodegenerative diseases. Herein, we investigated whether sub-chronic intranasal administration of exogenous Hsp70 (eHsp70) exerts a neuroprotective effect on the temporal cortex and areas of the hippocampus in transgenic 5XFAD mice, a model of Alzheimer's disease. The quantitative analysis of neuronal pathologies in the compared groups, transgenic (Tg) versus non-transgenic (nTg), revealed high level of abnormalities in the brains of transgenic mice. Treatment with human recombinant Hsp70 had profound rejuvenation effect on both neuronal morphology and functional state in the temporal cortex and hippocampal regions in transgenic mice. Hsp70 administration had a smaller, but still significant, effect on the functional state of neurons in non-transgenic mice as well. Using deep sequencing, we identified multiple differentially expressed genes (DEGs) in the hippocampus of transgenic and non-transgenic mice. Furthermore, this analysis demonstrated that eHsp70 administration strongly modulates the spectrum of DEGs in transgenic animals, reverting to a pattern similar to that observed in non-transgenic age-matched mice, which included upregulation of genes responsible for amine transport, transmission of nerve impulses and other pathways that are impaired in 5XFAD mice. Overall, our data indicate that Hsp70 treatment may be an effective therapeutic against old age diseases of the Alzheimer's type.

The Montreal Cognitive Assessment: Normative Data from a Large Swedish Population-Based Cohort. - Borland, Emma; Nägga, Katarina; Nilsson, Peter M; Minthon, Lennart; Nilsson, Erik D; Palmqvist, Sebastian (J Alzheimers Dis, 2017)
BACKGROUND: The Montreal Cognitive Assessment (MoCA) has a high sensitivity for detecting cognitive dysfunction. Swedish normative data does not exist and international norms are often derived from populations where cognitive impairment has not been screened for and not been thoroughly assessed to exclude subjects with dementia or mild cognitive impairment. OBJECTIVE: To establish norms for MoCA and develop a regression-based norm calculator based on a large, well-examined cohort. METHODS: MoCA was administered on 860 randomly selected elderly people from a population-based cohort from the EPIC study. Cognitive dysfunction was screened for and further assessed at a memory clinic. After excluding cognitively impaired participants, normative data was derived from 758 people, aged 65-85. RESULTS: MoCA cut-offs (-1 to -2 standard deviations) for cognitive impairment ranged from <25 to <21 for the lowest educated and <26 to <24 for the highest educated, depending on age group. Significant predictors for MoCA score were age, sex and level of education. CONCLUSION: We present detailed normative MoCA data and cut-offs according to the DSM-5 criteria for cognitive impairment based on a large population-based cohort of elderly individuals, screened and thoroughly investigated to rule out cognitive impairment. Level of education, sex, and age should be taken in account when evaluating MoCA score, which is facilitated by our online regression-based calculator that provide percentile and z-score for a subject's MoCA score.

Mortality Risk after Diagnosis of Early-Onset Alzheimer's Disease versus Late-Onset Alzheimer's Disease: A Propensity Score Matching Analysis. - Chang, Ki Jung; Hong, Chang Hyung; Lee, Kang Soo; Kang, Dae Ryong; Lee, Jeong Dong; Choi, Seong Hye; Kim, Seong Yoon; Na, Duk L; Seo, Sang Won; Kim, Do-Kwan; Lee, Yunhwan; Chung, Young Ki; et al. (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: We aimed to compare the risk of mortality in patients with early-onset Alzheimer's disease (EOAD) versus those with late-onset AD (LOAD) using a large number of study subjects. We applied propensity score matching (PSM) to minimize confounding biases in the comparison between EOAD and LOAD. METHODS: We obtained data from elderly Korean subjects with AD (n = 3,611) at baseline from the CREDOS cohort study, which was conducted from November 2005 to July 2013. We conducted PSM to reduce the bias due to confounding variables related to survival in patients with AD. The risks of mortality associated with EOAD and LOAD were evaluated by Cox proportional hazard analyses, controlling for relevant covariates. RESULTS: After propensity score matching, 312 subjects with EOAD and 624 subjects with LOAD were selected for further analysis. The Cox proportional hazard analysis showed that patients with EOAD are at a greater risk for mortality compared to those with LOAD (Hazard Ratio: 2.01, 95% CI: 1.01-4.00, p-value: 0.04) when controlling for the direct effect of aging on mortality. The results did not change after adjusting for age at diagnosis, general cognitive function, nutritional factor related to body mass index, and physical disability using activities of daily living. The results support the assumption that EOAD takes a more malignant course than LOAD. CONCLUSIONS: Our results provide support for the idea that EOAD takes a clinical course that is distinct from that of LOAD, especially as pertains to the risk of mortality.

A Multi-Cohort Study of ApoE ɛ4 and Amyloid-β Effects on the Hippocampus in Alzheimer's Disease. - Khan, Wasim; Giampietro, Vincent; Banaschewski, Tobias; Barker, Gareth J; Bokde, Arun L W; Büchel, Christian; Conrod, Patricia; Flor, Herta; Frouin, Vincent; Garavan, Hugh; Gowland, Penny; Heinz, Anreas; et al. (J Alzheimers Dis, 2017)
The apolipoprotein E (APOE) gene has been consistently shown to modulate the risk of Alzheimer's disease (AD). Here, using an AD and normal aging dataset primarily consisting of three AD multi-center studies (n = 1,781), we compared the effect of APOE and amyloid-β (Aβ) on baseline hippocampal volumes in AD patients, mild cognitive impairment (MCI) subjects, and healthy controls. A large sample of healthy adolescents (n = 1,387) was also used to compared hippocampal volumes between APOE groups. Subjects had undergone a magnetic resonance imaging (MRI) scan and APOE genotyping. Hippocampal volumes were processed using FreeSurfer. In the AD and normal aging dataset, hippocampal comparisons were performed in each APOE group and in ɛ4 carriers with positron emission tomography Aβ who were dichotomized (Aβ+/Aβ-) using previous cut-offs. We found a linear reduction in hippocampal volumes with ɛ4 carriers possessing the smallest volumes, ɛ3 carriers possessing intermediate volumes, and ɛ2 carriers possessing the largest volumes. Moreover, AD and MCI ɛ4 carriers possessed the smallest hippocampal volumes and control ɛ2 carriers possessed the largest hippocampal volumes. Subjects with both APOE ɛ4 and Aβ+ had the lowest hippocampal volumes when compared to Aβ- ɛ4 carriers, suggesting a synergistic relationship between APOE ɛ4 and Aβ. However, we found no hippocampal volume differences between APOE groups in healthy 14-year-old adolescents. Our findings suggest that the strongest neuroanatomic effect of APOE ɛ4 on the hippocampus is observed in AD and groups most at risk of developing the disease, whereas hippocampi of old and young healthy individuals remain unaffected.

Music Perception in Dementia. - Golden, Hannah L; Clark, Camilla N; Nicholas, Jennifer M; Cohen, Miriam H; Slattery, Catherine F; Paterson, Ross W; Foulkes, Alexander J M; Schott, Jonathan M; Mummery, Catherine J; Crutch, Sebastian J; Warren, Jason D (J Alzheimers Dis, 2017)
Despite much recent interest in music and dementia, music perception has not been widely studied across dementia syndromes using an information processing approach. Here we addressed this issue in a cohort of 30 patients representing major dementia syndromes of typical Alzheimer's disease (AD, n = 16), logopenic aphasia (LPA, an Alzheimer variant syndrome; n = 5), and progressive nonfluent aphasia (PNFA; n = 9) in relation to 19 healthy age-matched individuals. We designed a novel neuropsychological battery to assess perception of musical patterns in the dimensions of pitch and temporal information (requiring detection of notes that deviated from the established pattern based on local or global sequence features) and musical scene analysis (requiring detection of a familiar tune within polyphonic harmony). Performance on these tests was referenced to generic auditory (timbral) deviance detection and recognition of familiar tunes and adjusted for general auditory working memory performance. Relative to healthy controls, patients with AD and LPA had group-level deficits of global pitch (melody contour) processing while patients with PNFA as a group had deficits of local (interval) as well as global pitch processing. There was substantial individual variation within syndromic groups. Taking working memory performance into account, no specific deficits of musical temporal processing, timbre processing, musical scene analysis, or tune recognition were identified. The findings suggest that particular aspects of music perception such as pitch pattern analysis may open a window on the processing of information streams in major dementia syndromes. The potential selectivity of musical deficits for particular dementia syndromes and particular dimensions of processing warrants further systematic investigation.

Neuronal Expression of Truncated Tau Efficiently Promotes Neurodegeneration in Animal Models: Pitfalls of Toxic Oligomer Analysis. - Skrabana, Rostislav; Kovacech, Branislav; Filipcik, Peter; Zilka, Norbert; Jadhav, Santosh; Smolek, Tomas; Kontsekova, Eva; Novak, Michal (J Alzheimers Dis, 2017)
Animal models of neurodegeneration induced by neuronal expression of truncated tau protein emerge as an important tool for understanding the pathogenesis of human tauopathies and for therapy development. Here we highlight common features of truncated tau models and make a critical assessment of possible pitfalls in their analysis. Particularly, the amount of soluble tau oligomers, which are suspected to be neurotoxic agents participating on the spreading of pathology inside the brain, may be overestimated due to a post-lysis oxidative tau oligomerization. Using a mouse brain lysate spiked with recombinant truncated and full length tau forms, we show that tau oligomers might inadvertently be produced during the isolation procedure. This finding is further corroborated by the analysis of brain lysates originated from a mouse model expressing truncated tau variant. Our results underline the necessity of thiol-protecting conditions during the analysis of tau oligomers involved in the etiopathogenesis of various tauopathies including Alzheimer's disease.

Neutrophil Gelatinase-Associated Lipocalin and its Receptors in Alzheimer's Disease (AD) Brain Regions: Differential Findings in AD with and without Depression. - Dekens, Doortje W; Naudé, Petrus J W; Engelborghs, Sebastiaan; Vermeiren, Yannick; Van Dam, Debby; Oude Voshaar, Richard C; Eisel, Ulrich L M; De Deyn, Peter P (J Alzheimers Dis, 2017)
Co-existing depression worsens Alzheimer's disease (AD) pathology. Neutrophil gelatinase-associated lipocalin (NGAL) is a newly identified (neuro)inflammatory mediator in the pathophysiologies of both AD and depression. This study aimed to compare NGAL levels in healthy controls, AD without depression (AD-D), and AD with co-existing depression (AD+D) patients. Protein levels of NGAL and its receptors, 24p3R and megalin, were assessed in nine brain regions from healthy controls (n = 19), AD-D (n = 19), and AD+D (n = 21) patients. NGAL levels in AD-D patients were significantly increased in brain regions commonly associated with AD. In the hippocampus, NGAL levels were even further increased in AD+D subjects. Unexpectedly, NGAL levels in the prefrontal cortex of AD+D patients were comparable to those in controls. Megalin levels were increased in BA11 and amygdala of AD+D patients, while no changes in 24p3R were detected. These findings indicate significant differences in neuroimmunological regulation between AD patients with and without co-existing depression. Considering its known effects, elevated NGAL levels might actively promote neuropathological processes in AD with and without depression.

NFATc2 Modulates Microglial Activation in the AβPP/PS1 Mouse Model of Alzheimer's Disease. - Manocha, Gunjan D; Ghatak, Atreyi; Puig, Kendra L; Kraner, Susan D; Norris, Christopher M; Combs, Colin K (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) brains are characterized by fibrillar amyloid-β (Aβ) peptide containing plaques and associated reactive microglia. The proinflammatory phenotype of the microglia suggests that they may negatively affect disease course and contribute to behavioral decline. This hypothesis predicts that attenuating microglial activation may provide benefit against disease. Prior work from our laboratory and others has characterized a role for the transcription factor, nuclear factor of activated T cells (NFAT), in regulating microglial phenotype in response to different stimuli, including Aβ peptide. We observed that the NFATc2 isoform was the most highly expressed in murine microglia cultures, and inhibition or deletion of NFATc2 was sufficient to attenuate the ability of the microglia to secrete cytokines. In order to determine whether the NFATc2 isoform, in particular, was a valid immunomodulatory target in vivo, we crossed an NFATc2-/- line to a well-known AD mouse model, an AβPP/PS1 mouse line. As expected, the AβPP/PS1 x NFATc2-/- mice had attenuated cytokine levels compared to AβPP/PS1 mice as well as reduced microgliosis and astrogliosis with no effect on plaque load. Although some species differences in relative isoform expression may exist between murine and human microglia, it appears that microglial NFAT activity is a viable target for modulating the proinflammatory changes that occur during AD.

No Genetic Overlap Between Circulating Iron Levels and Alzheimer's Disease. - Lupton, Michelle K; Benyamin, Beben; Proitsi, Petroula; Nyholt, Dale R; Ferreira, Manuel A; Montgomery, Grant W; Heath, Andrew C; Madden, Pamela A; Medland, Sarah E; Gordon, Scott D; Lovestone, Simon; Tsolaki, Magda; et al. (J Alzheimers Dis, 2017)
Iron deposition in the brain is a prominent feature of Alzheimer's disease (AD). Recently, peripheral iron measures have also been shown to be associated with AD status. However, it is not known whether these associations are causal: do elevated or depleted iron levels throughout life have an effect on AD risk? We evaluate the effects of peripheral iron on AD risk using a genetic profile score approach by testing whether variants affecting iron, transferrin, or ferritin levels selected from GWAS meta-analysis of approximately 24,000 individuals are also associated with AD risk in an independent case-control cohort (n∼10,000). Conversely, we test whether AD risk variants from a GWAS meta-analysis of approximately 54,000 account for any variance in iron measures (n∼9,000). We do not identify a genetic relationship, suggesting that peripheral iron is not causal in the initiation of AD pathology.

Novel Blood-Based Biomarkers of Cognition, Stress, and Physical or Cognitive Training in Older Adults at Risk of Dementia: Preliminary Evidence for a Role of BDNF, Irisin, and the Kynurenine Pathway. - Küster, Olivia C; Laptinskaya, Daria; Fissler, Patrick; Schnack, Cathrin; Zügel, Martina; Nold, Verena; Thurm, Franka; Pleiner, Sina; Karabatsiakis, Alexander; von Einem, Björn; Weydt, Patrick; Liesener, André; et al. (J Alzheimers Dis, 2017)
Psychosocial stress and physical, cognitive, and social activity predict the risk of cognitive decline and dementia. The aim of this study was to elucidate brain-derived neurotrophic factor (BDNF), irisin, and the kynurenine pathway (KP) as potential underlying biological correlates. We evaluated associations of irisin and the KP with BDNF in serum and with cognition, stress, and activities. Furthermore, changes in serum concentrations of BDNF, irisin, and KP metabolites were investigated after physical or cognitive training. Forty-seven older adults at risk of dementia were assigned to 10 weeks of physical training, cognitive training, or a wait-list control condition. Previous physical, cognitive, and social activities and stressful life events were recorded; global cognition, episodic memory, and executive functions were assessed. Serum levels of L-kynurenine, kynurenic acid, 3-hydroxykynurenine (3-HK), and quinolinic acid (QUIN) were determined by validated assays based on liquid chromatography coupled to tandem mass spectrometry. BDNF and irisin serum levels were determined with enzyme-linked immunosorbent assays. BDNF and irisin correlated positively with global cognition and episodic memory, while the neurotoxic metabolite QUIN correlated negatively with executive functions. Stressful life events were associated with reduced BDNF and increased 3-HK. 3-HK decreased after cognitive training, while BDNF tended to increase after physical training. This suggests that psychosocial stress as well as cognitive and physical training may impact BDNF serum levels and the KP. Irisin and QUIN may constitute novel serum biomarkers of cognitive impairment, in addition to BDNF. Larger scale trials are needed to replicate and extend these novel findings.

N-Terminal Pro-B Type Natriuretic Peptide is Associated with Mild Cognitive Impairment in the General Population. - Kara, Kaffer; Mahabadi, Amir Abbas; Weimar, Christian; Winkler, Angela; Neumann, Till; Kälsch, Hagen; Dragano, Nico; Moebus, Susanne; Erbel, Raimund; Jöckel, Karl-Heinz; Jokisch, Martha (J Alzheimers Dis, 2017)
BACKGROUND: N-terminal pro-B type natriuretic peptide (NT-proBNP) is a marker of cardiac stress and is linked with silent cardiac diseases. While associations of cognitive impairment with manifest cardiovascular diseases are established, data on whether subclinical elevation of NT-proBNP levels below clinically established threshold of heart failure is related with cognitive functioning, especially mild cognitive impairment (MCI), is rare. OBJECTIVE: Aim of the present study was to investigate the cross-sectional association of NT-proBNP levels and MCI in a population-based study sample without heart failure. METHODS: We used data from the second examination of the population based Heinz-Nixdorf-Recall-Study. Subjects with overt coronary heart disease and subjects with NT-proBNP levels indicating potential heart failure (NT-proBNP≥300 pg/ml) were excluded from this analysis. Participants performed a validated brief cognitive assessment and were classified either as MCI [subtypes: amnestic-MCI (aMCI), non-amnestic-MCI (naMCI)], or cognitively-normal. RESULTS: We included 419 participants with MCI (63.1±7.4 y; 47% men; aMCI n = 209; naMCI n = 210) and 1,206 cognitively normal participants (62.42±7.1 y; 48% men). NT-proBNP-levels≥125 pg/ml compared to <125 pg/ml were associated with MCI in fully adjusted models (OR 1.65 (1.23;2.23) in the total sample, 1.73 (1.09;2.74) in men and 1.63(1.10;2.41) in women). For aMCI, the fully adjusted OR was 1.53 (1.04;2.25) and for naMCI, the fully adjusted OR was 1.34 (1.09; 166) in the total sample. CONCLUSION: Within normal ranges and without manifest heart failure, higher NT-proBNPlevels are associated with MCI and both MCI subtypes independent of traditional cardiovascular risk factors and sociodemographic parameters.

Occupational Attainment as Risk Factor for Progression from Mild Cognitive Impairment to Alzheimer's Disease: A CREDOS Study. - Myung, Woojae; Lee, Chunsoo; Park, Jin Hong; Woo, Sook-Young; Kim, Seonwoo; Kim, Sangha; Chung, Jae Won; Kang, Hyo Shin; Lim, Shinn-Won; Choi, Junbae; Na, Duk L; Kim, Seong Yoon; et al. (J Alzheimers Dis, 2017)
High occupational attainment has been known as a marker of cognitive reserve. Previous studies in the general population have shown that high occupational attainment is associated with reduced risk of Alzheimer's disease (AD). However, few studies have assessed the effect of occupational attainment on the clinical course of mild cognitive impairment (MCI). In this study, we evaluated whether individuals with high occupational attainment show more frequent progression from MCI to AD. Participants (n = 961) with MCI were recruited from a nationwide, hospital-based multi-center cohort, and were followed for up to 60 months (median: 17.64, interquartile range [12.36, 29.28]). We used Cox regression for competing risks to analyze the effect of occupational attainment on development of AD, treating dementia other than AD as a competing risk. Among the 961 individuals with MCI, a total of 280 (29.1%) converted to dementia during the follow-up period. The risk of progression to AD was higher in the individuals with high occupational attainment after controlling for potential confounders (hazard ratio = 1.83, 95% confidence interval = 1.25-2.69, p = 0.002). High occupational attainment in individuals with MCI is an independent risk factor for higher progression rate of MCI to AD. This result suggests that the protective effect of high occupational attainment against cognitive decline disappears in the MCI stage, and that careful assessment of occupational history can yield important clinical information for prognosis in individuals with MCI.

PE859, A Novel Curcumin Derivative, Inhibits Amyloid-β and Tau Aggregation, and Ameliorates Cognitive Dysfunction in Senescence-Accelerated Mouse Prone 8. - Okuda, Michiaki; Fujita, Yuki; Hijikuro, Ichiro; Wada, Mei; Uemura, Takuya; Kobayashi, Yukako; Waku, Tomonori; Tanaka, Naoki; Nishimoto, Takaaki; Izumi, Yasuhiko; Kume, Toshiaki; Akaike, Akinori; et al. (J Alzheimers Dis, 2017)
Aggregation of amyloid-β (Aβ) and tau plays a crucial role in the onset and progression of Alzheimer's disease (AD). Therefore, the inhibition of Aβ and tau aggregation may represent a potential therapeutic target for AD. Herein, we designed and synthesized both Aβ and tau dual aggregation inhibitors based on the structure of curcumin and developed the novel curcumin derivative PE859. In this study, we investigated the inhibitory activity of PE859 on Aβ aggregationin vitro and the therapeutic effects of PE859 on cognitive dysfunction via dual inhibition of Aβ and tau aggregation in vivo. PE859 inhibited Aβ aggregation in vitro and protected cultured cells from Aβ-induced cytotoxicity. Furthermore, PE859 ameliorated cognitive dysfunction and reduced the amount of aggregated Aβ and tau in brains of senescence-accelerated mouse prone 8 (SAMP8). These results warrant consideration of PE859 as a candidate drug for AD.

PET Imaging of Tau Pathology and Relationship to Amyloid, Longitudinal MRI, and Cognitive Change in Down Syndrome: Results from the Down Syndrome Biomarker Initiative (DSBI). - Rafii, Michael S; Lukic, Ana S; Andrews, Randolph D; Brewer, James; Rissman, Robert A; Strother, Stephen C; Wernick, Miles N; Pennington, Craig; Mobley, William C; Ness, Seth; Matthews, Dawn C (J Alzheimers Dis, 2017)
BACKGROUND: Adults with Down syndrome (DS) represent an enriched population for the development of Alzheimer's disease (AD), which could aid the study of therapeutic interventions, and in turn, could benefit from discoveries made in other AD populations. OBJECTIVES: 1) Understand the relationship between tau pathology and age, amyloid deposition, neurodegeneration (MRI and FDG PET), and cognitive and functional performance; 2) detect and differentiate AD-specific changes from DS-specific brain changes in longitudinal MRI. METHODS: Twelve non-demented adults, ages 30 to 60, with DS were enrolled in the Down Syndrome Biomarker Initiative (DSBI), a 3-year, observational, cohort study to demonstrate the feasibility of conducting AD intervention/prevention trials in adults with DS. We collected imaging data with 18F-AV-1451 tau PET, AV-45 amyloid PET, FDG PET, and volumetric MRI, as well as cognitive and functional measures and additional laboratory measures. RESULTS: All amyloid negative subjects imaged were tau-negative. Among the amyloid positive subjects, three had tau in regions associated with Braak stage VI, two at stage V, and one at stage II. Amyloid and tau burden correlated with age. The MRI analysis produced two distinct volumetric patterns. The first differentiated DS from normal (NL) and AD, did not correlate with age or amyloid, and was longitudinally stable. The second pattern reflected AD-like atrophy and differentiated NL from AD. Tau PET and MRI atrophy correlated with several cognitive and functional measures. CONCLUSIONS: Tau accumulation is associated with amyloid positivity and age, as well as with progressive neurodegeneration measurable using FDG and MRI. Tau correlates with cognitive decline, as do AD-specific hypometabolism and atrophy.

Physical Exercise with Music Maintains Activities of Daily Living in Patients with Dementia: Mihama-Kiho Project Part 21. - Satoh, Masayuki; Ogawa, Jun-Ichi; Tokita, Tomoko; Nakaguchi, Noriko; Nakao, Koji; Kida, Hirotaka; Tomimoto, Hidekazu (J Alzheimers Dis, 2017)
BACKGROUND: Recent studies suggest that combined non-pharmacological interventions are more beneficial than single interventions for primary and secondary prevention of dementia. We previously reported enhanced effects of physical exercise with music (ExM) on cognitive function in normal elderly people compared to exercise alone. OBJECTIVE: To identify if ExM improves cognitive function and activities of daily livings (ADLs) in dementia patients over cognitive stimulation (CS). METHODS: We enrolled 85 patients with mild to moderate dementia. Forty-three subjects performed ExM developed by the Yamaha Music Foundation, and 42 subjects performed cognitive stimulation using portable game consoles and drills involving easy calculations, mazes, and mistake-searching in pictures. Interventions were performed once a week for 40 minutes. Before and after the six-month intervention, patients were assessed using neuropsychological batteries, and ADLs were assessed by patients' caregivers using the functional independence measure (FIM). Voxel-based specific regional analysis system for Alzheimer's disease (VSRAD) was used to assess medial temporal lobe atrophy. RESULTS: Twenty-three subjects dropped out during the intervention. Thirty-one patients from each group were analyzed. Post-intervention, both groups showed significantly improved visuospatial function. Significant benefits were observed in psychomotor speed or memory in the ExM or CS groups, respectively. FIM scores, reflecting ADLs, and VSRAD scores were significantly preserved in the ExM group, but significantly worsened in the CS group. CONCLUSIONS: ExM produced greater positive effects on cognitive function and ADLs in patients with mild to moderate dementia than CS, excluding memory. Optimal interventions for dementia will likely be achieved by combining ExMand CS.

Plasma Amyloid-β and Alzheimer's Disease-Related Changes in Late-Life Depression. - Yamazaki, Chiemi; Tamaoki, Toshio; Nunomura, Akihiko; Tamai, Kenichi; Yasuda, Kazuyuki; Motohashi, Nobutaka (J Alzheimers Dis, 2017)
To elucidate an involvement of amyloid dysmetabolism in the pathophysiology of depression, we investigated associations of plasma amyloid-β (Aβ) levels with Alzheimer's disease-related changes in neuroimaging and cognitive dysfunction in patients with late-life depression. Higher plasma Aβ40, but not Aβ42 nor Aβ40/Aβ42 ratio, was associated with higher degree of parahippocampal atrophy and lower verbal fluency performance. Indeed, high plasma Aβ40 predicted poor cognitive prognosis of depressed patients with mild cognitive impairment. As an anti-depressive treatment, electroconvulsive therapy (ECT) resulted in a marginally significant reduction of plasma Aβ40 compared to pharmacotherapy alone, suggesting protective effects of ECT against amyloid dysmetabolism.

Plasma Amyloid-β Levels, Cerebral Small Vessel Disease, and Cognition: The Rotterdam Study. - Hilal, Saima; Akoudad, Saloua; van Duijn, Cornelia M; Niessen, Wiro J; Verbeek, Marcel M; Vanderstichele, Hugo; Stoops, Erik; Ikram, M Arfan; Vernooij, Meike W (J Alzheimers Dis, 2017)
BACKGROUND: Plasma amyloid-β (Aβ) levels are increasingly studied as a potential, accessible marker of cognitive impairment and dementia. The most common plasma Aβ isoforms, i.e., Aβ1-40 and Aβ1-42 have been linked with risk of Alzheimer's disease. However, it remains under-explored whether plasma Aβ levels including novel Aβ1-38 relate to vascular brain disease and cognition in a preclinical-phase of dementiaObjective:To examine the association of plasma Aβ levels (i.e., Aβ1-38, Aβ1-40, and Aβ1-42) with markers of cerebral small vessel disease (SVD) and cognition in a large population-based setting. METHODS: We analyzed plasma Aβ1 levels in 1201 subjects from two independent cohorts of the Rotterdam Study. Markers of SVD [lacunes, white matter hyperintensity (WMH) volume] were assessed on brain MRI (1.5T). Cognition was assessed by a detailed neuropsychological battery. In each cohort, the association of Aβ levels with SVD and cognition was performed using regression models. Estimates were then pooled across cohorts using inverse variance meta-analysis with fixed effects. RESULTS: Higher levels of plasma Aβ1-38, Aβ1-40, Aβ1-42, and Aβ1-40/ Aβ1-42 ratio were associated with increasing lacunar and microbleeds counts. Moreover, higher levels of Aβ1-40 and Aβ1-40/ Aβ1-42 were significantly associated with larger WMH volumes. With regard to cognition, a higher level of Aβ1-38 Aβ1-40 and Aβ1-40/ Aβ1-42 was related to worse performance on cognitive test specifically in memory domain. CONCLUSION: Higher plasma levels of Aβ levels are associated with subclinical markers of vascular disease and poorer memory. Plasma Aβ levels thus mark the presence of vascular brain pathology.

Plasma Tau Association with Brain Atrophy in Mild Cognitive Impairment and Alzheimer's Disease. - Deters, Kacie D; Risacher, Shannon L; Kim, Sungeun; Nho, Kwangsik; West, John D; Blennow, Kaj; Zetterberg, Henrik; Shaw, Leslie M; Trojanowski, John Q; Weiner, Michael W; Saykin, Andrew J (J Alzheimers Dis, 2017)
BACKGROUND: Peripheral (plasma) and central (cerebrospinal fluid, CSF) measures of tau are higher in Alzheimer's disease (AD) relative to prodromal stages and controls. While elevated CSF tau concentrations have been shown to be associated with lower grey matter density (GMD) in AD-specific regions, this correlation has yet to be examined for plasma in a large study. OBJECTIVE: Determine the neuroanatomical correlates of plasma tau using voxel-based analysis. METHODS: Cross-sectional data for 508 ADNI participants were collected for clinical, plasma total-tau (t-tau), CSF amyloid (Aβ42) and tau, and MRI variables. The relationship between plasma tau and GMD and between CSF t-tau and GMD were assessed on a voxel-by-voxel basis using regression models. Age, sex, APOEɛ4 status, diagnosis, and total intracranial volume were used as covariates where appropriate. Participants were defined as amyloid positive (Aβ+) if CSF Aβ42 was <192 pg/mL. RESULTS: Plasma tau was negatively correlated with GMD in the medial temporal lobe (MTL), precuneus, thalamus, and striatum. The associations with thalamus and striatum were independent of diagnosis. A negative correlation also existed between plasma tau and GMD in Aβ+ participants in the MTL, precuneus, and frontal lobe. When compared to CSF t-tau, plasma tau showed a notably different associated brain atrophy pattern, with only small overlapping regions in the fusiform gyrus. CONCLUSION: Plasma tau may serve as a non-specific marker for neurodegeneration but is still relevant to AD considering low GMD was associated with plasma tau in Aβ+ participants and not Aβ-participants.

Prediction Model of Conversion to Dementia Risk in Subjects with Amnestic Mild Cognitive Impairment: A Longitudinal, Multi-Center Clinic-Based Study. - Jang, Hyemin; Ye, Byoung Seok; Woo, Sookyoung; Kim, Sun Woo; Chin, Juhee; Choi, Seong Hye; Jeong, Jee Hyang; Yoon, Soo Jin; Yoon, Bora; Park, Kyung Won; Hong, Yun Jeong; Kim, Hee Jin; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Patients with amnestic mild cognitive impairment (aMCI) have an increased risk of dementia. However, conversion rate varies. Therefore, predicting the dementia conversion in these patients is important. OBJECTIVE: We aimed to develop a nomogram to predict dementia conversion in aMCI subjects using neuropsychological profiles. METHODS: A total of 338 aMCI patients from two hospital-based cohorts were used in analysis. All patients were classified into 1) verbal, visual, or both, 2) early or late, and 3) single or multiple-domain aMCI according to the modality, severity of memory dysfunction, and multiplicity of involved cognitive domains, respectively. Patients were followed up, and conversion to dementia within 3 years was defined as the primary outcome. Our patients were divided into a training data set and a validation data set. The associations of potential covariates with outcome were tested, and nomogram was constructed by logistic regression model. We also developed another model with APOE data, which included 242 patients. RESULTS: In logistic regression models, both modalities compared with visual only (OR 4.44, 95% CI 1.83-10.75, p = 0.001), late compared to early (OR 2.59, 95% CI 1.17-5.72, p = 0.019), and multiple compared to single domain (OR 3.51, 95% CI 1.62-7.60, p = 0.002) aMCI were significantly associated with dementia conversion within 3 years. A nomogram incorporating these clinical variables was constructed on the training data set and validated on the validation data set. Both nomograms with and without APOE data showed good prediction performance (c-statistics ≥ 0.75). CONCLUSIONS: This study showed that several neuropsychological profiles of aMCI are significantly associated with imminent dementia conversion, and a nomogram incorporating these clinical subtypes is simple and useful to help to predict disease progression.

A Preliminary Study on the Feasibility of Using a Virtual Reality Cognitive Training Application for Remote Detection of Mild Cognitive Impairment. - Zygouris, Stelios; Ntovas, Konstantinos; Giakoumis, Dimitrios; Votis, Konstantinos; Doumpoulakis, Stefanos; Segkouli, Sofia; Karagiannidis, Charalampos; Tzovaras, Dimitrios; Tsolaki, Magda (J Alzheimers Dis, 2017)
BACKGROUND: It has been demonstrated that virtual reality (VR) applications can be used for the detection of mild cognitive impairment (MCI). OBJECTIVE: The aim of this study is to provide a preliminary investigation on whether a VR cognitive training application can be used to detect MCI in persons using the application at home without the help of an examiner. METHODS: Two groups, one of healthy older adults (n = 6) and one of MCI patients (n = 6) were recruited from Thessaloniki day centers for cognitive disorders and provided with a tablet PC with custom software enabling the self-administration of the Virtual Super Market (VSM) cognitive training exercise. The average performance (from 20 administrations of the exercise) of the two groups was compared and was also correlated with performance in established neuropsychological tests. RESULTS: Average performance in terms of duration to complete the given exercise differed significantly between healthy(μ  = 247.41 s/ sd = 89.006) and MCI (μ= 454.52 s/ sd = 177.604) groups, yielding a correct classification rate of 91.8% with a sensitivity and specificity of 94% and 89% respectively for MCI detection. Average performance also correlated significantly with performance in Functional Cognitive Assessment Scale (FUCAS), Test of Everyday Attention (TEA), and Rey Osterrieth Complex Figure test (ROCFT). DISCUSSION: The VR application exhibited very high accuracy in detecting MCI while all participants were able to operate the tablet and application on their own. Diagnostic accuracy was improved compared to a previous study using data from only one administration of the exercise. The results of the present study suggest that remote MCI detection through VR applications can be feasible.

Proteomics Analysis of Blood Serums from Alzheimer's Disease Patients Using iTRAQ Labeling Technology. - Shen, Liming; Liao, Liping; Chen, Cheng; Guo, Yi; Song, Dalin; Wang, Yong; Chen, Youjiao; Zhang, Kaoyuan; Ying, Ming; Li, Shuiming; Liu, Qiong; Ni, Jiazuan (J Alzheimers Dis, 2017)
Alzheimer' disease (AD) is the most common form of dementia affecting up to 6% of the population over the age of 65. In order to discover differentially expressed proteins that might serve as potential biomarkers, the serums from AD patients and healthy controls were compared and analyzed using the proteomics approach of isobaric tagging for relative and absolute quantitation (iTRAQ). For the first time, AD biomarkers in serums are investigated in the Han Chinese population using iTRAQ labeled proteomics strategy. Twenty-two differentially expressed proteins were identified and out of which nine proteins were further validated with more sample test. Another three proteins that have been reported in the literature to be potentially associated with AD were also investigated for alteration in expression level. Functions of those proteins were mainly related to the following processes: amyloid-β (Aβ) metabolism, cholesterol transport, complement and coagulation cascades, immune response, inflammation, hemostasis, hyaluronan metabolism, and oxidative stress. These results support current views on the molecular mechanism of AD. For the first time, differential expression of zinc-alpha-2-glycoprotein (AZGP1), fibulin-1 (FBLN1), platelet basic protein (PPBP), thrombospondin-1 (THBS1), S100 calcium-binding protein A8 (S100A8), and S100 calcium-binding protein A9 (S100A9) were detected in the serums of AD patients compared with healthy controls. These proteins might play a role in AD pathophysiology and serve as potential biomarkers for AD diagnosis. Specifically, our results strengthened the crucial role of Aβ metabolism and blood coagulation in AD pathogenesis and proteins related to these two processes may be used as peripheral blood biomarkers for AD.

Psychosocial Risk and Protective Factors and Incident Mild Cognitive Impairment and Dementia in Community Dwelling Elderly: Findings from the Singapore Longitudinal Ageing Study. - Rawtaer, Iris; Gao, Qi; Nyunt, Ma Shwe Zin; Feng, Lei; Chong, Mei Sian; Lim, Wee Shiong; Lee, Tih-Shih; Yap, Philip; Yap, Keng Bee; Ng, Tze Pin (J Alzheimers Dis, 2017)
BACKGROUND: Indicators of social isolation or support such as living alone, loneliness, being married, and life satisfaction are possible psychosocial risk and protective factors for dementia. OBJECTIVE: We investigate the associations of these overlapping psychosocial factors with incident MCI-dementia (neurocognitive disorder) in a population cohort. METHODS: Using data from 1601 participants of the Singapore Longitudinal Ageing Study (SLAS) who were free of MCI or dementia at baseline and followed up to 8 years, we estimated hazards ratio (HR) of association of living alone, loneliness, being married, and high life satisfaction with incident MCI-dementia. RESULTS: In univariate analyses, individual HRs of association with incident MCI-dementia for living alone was 1.86 [1.18 - 2.95], (p = 0.008), loneliness was 1.26 [0.86 - 1.84], (p = 0.23), being married was 0.54 [0.39 - 0.75] (p < 0.0001), and being very satisfied with life was 0.59 [0.38-0.91]), (p = 0.017). Adjusted mutually for other psychosocial variables, and for age, sex, education, ethnicity, smoking, alcohol, dyslipidemia, hypertension, diabetes, central obesity, history of stroke or heart disease, APOE-ɛ4, depression, physical, social, and productive activities, only being married (0.68 [0.47-0.99], p = 0.044), and being very satisfied with life (0.61 [0.39 - 0.96], p = 0.034) remained significant variables associated with lower risks of developing MCI-dementia. CONCLUSION: Individuals who were married and those who were very satisfied with life are protected against the risk of developing MCI and dementia. Controlling for the adverse effects of being without spousal support and low life satisfaction, living alone or a feeling of loneliness were not associated with increased risk of MCI-dementia.

Psychotropic Polypharmacy in Patients with Dementia: Prevalence and Predictors. - Nørgaard, Ane; Jensen-Dahm, Christina; Gasse, Christiane; Hansen, Elsebet Steno; Waldemar, Gunhild (J Alzheimers Dis, 2017)
BACKGROUND: Antipsychotics and other psychotropics are frequently used to treat neuropsychiatric symptoms in patients with dementia, even though the evidence for effect is limited. Concerns have been raised about the safety of antipsychotics, but concomitant use of multiple psychotropic drug classes (psychotropic polypharmacy) may also pose a risk for patients. OBJECTIVE: To investigate the prevalence and predictors associated with use of psychotropic polypharmacy in patients with dementia. METHODS: A population-based study using nationwide registers. Patients with dementia were identified among all Danish residents ≥65 years on January 1, 2012. Data on prescriptions and comorbidity was included in the analysis. Overlapping prescriptions for different psychotropic drug classes were used to determine psychotropic polypharmacy. A multivariable logistic regression analysis was conducted to evaluate factors independently associated with the prescription of other psychotropic drug classes among patients already using antipsychotics. RESULTS: Among all patients registered with dementia (34,553), 25.3% (8,728) used ≥2 psychotropic drugs. Among patients treated with antipsychotics 75.8% (5,403) used at least one other psychotropic drug during the antipsychotic treatment period. Nursing home residency, number of non-psychotropic medications used in 2011, and prior psychiatric diagnosis were associated with psychotropic polypharmacy among antipsychotic drug users. The most frequent combination of psychotropic drugs was antipsychotics and antidepressants. CONCLUSION: Concomitant use of psychotropic drugs was frequent in dementia patients. Patients living in nursing homes had the highest risk of receiving a combination of antipsychotics and other psychotropic drugs. Concomitant use of psychotropics may cause adverse events, and potential consequences for patients' safety call for further investigation.

Quantitative Magnetic Resonance Abnormalities in Creutzfeldt-Jakob Disease and Fatal Insomnia. - Grau-Rivera, Oriol; Calvo, Anna; Bargalló, Nuria; Monté, Gemma C; Nos, Carlos; Lladó, Albert; Molinuevo, José Luis; Gelpi, Ellen; Sánchez-Valle, Raquel (J Alzheimers Dis, 2017)
BACKGROUND: Quantitative neuroimaging might unveil abnormalities in prion diseases that are not perceivable at visual inspection. On the other hand, scarce studies have quantified volumetric changes in prion diseases. OBJECTIVES: We aim to characterize volumetric and diffusion tensor imaging (DTI) changes in patients with prion diseases who presented with either Creutzfeldt-Jakob disease (CJD) or fatal insomnia (FI) phenotype. METHODS: Twenty patients with prion diseases- 15 with CJD and 5 with fatal insomnia (FI)- and 40 healthy controls were examined with a 3-Tesla magnetic resonance imaging scanner. Images were segmented and normalized with SPM12. DTI maps were obtained with FMRIB Software Library. Whole-brain voxel-wise and region-of-interest analyses of volumetric and DTI changes were performed with SPM12. White matter (WM) changes were also analyzed with tract-based spatial statistics. Semiquantitive assessment of neuropathological parameters was compared with DTI metrics in thalamus from 11 patients. RESULTS: Patients with CJD and FI presented significant atrophy in thalamus and cerebellum. In CJD, mean diffusivity (MD) was decreased in striatum and increased in subcortical WM, while both increased and decreased values were observed across different thalamic nuclei. In FI, MD was increased in thalamus and cerebellum. Spongiform change and PrPSc deposition were more intense in thalamus in CJD than in FI, although no significant correlations arose with MD values in the nuclei studied. CONCLUSION: Volumetric and DTI abnormalities suggest a central common role of the thalamus in prion diseases. We report, for the first time, quantitative MRI changes in FI, and provide further evidence of WM involvement in prion diseases.

Recent Increases in Hippocampal Tau Pathology in the Aging Japanese Population: The Hisayama Study. - Hamasaki, Hideomi; Honda, Hiroyuki; Okamoto, Tsuyoshi; Koyama, Sachiko; Suzuki, Satoshi O; Ohara, Tomoyuki; Ninomiya, Toshiharu; Kiyohara, Yutaka; Iwaki, Toru (J Alzheimers Dis, 2017)
BACKGROUND: The Hisayama study is a prospective cohort study of lifestyle-related diseases that commenced in 1961. Through it, a significant increasing trend in the prevalence of Alzheimer's disease has been observed over the past 18 years. OBJECTIVES: We sought to investigate the increases in brain pathology related to Alzheimer's disease using automated MATLAB morphometric analyses for quantifying tau pathology. METHODS: We examined a series of autopsied cases from Hisayama residents obtained between 1998 and 2003 (group A: 203 cases), and between 2009 and 2014 (group B: 232 cases). We developed custom software in MATLAB to analyze abnormal tau deposits quantitatively. Specimens were immunostained with both anti-amyloid-β-protein and anti-phosphorylated tau antibodies. RESULTS: Both the Consortium to Establish a Registry for Alzheimer's Disease (CERAD) criteria for senile plaques and Braak stage for NFT were higher in group B. Morphometric analyses of the hippocampi also revealed a trend toward increased tau pathology in both men and women over 80 years of age in group B. The increases were also significant when the subjects were examined independently according to high or low CERAD scores and in all levels of AD neuropathologic change according to the National Institute on Aging-Alzheimer's Association guidelines (2012). CONCLUSION: We revealed a recent trend of increased tauopathy in the older people, which is partly independent of amyloid-β pathology.

The Relationships Between Components of Metabolic Syndrome and Mild Cognitive Impairment Subtypes: A Cross-Sectional Study of Japanese Older Adults. - Bae, Seongryu; Shimada, Hiroyuki; Lee, Sangyoon; Makizako, Hyuma; Lee, Sungchul; Harada, Kazuhiro; Doi, Takehiko; Tsutsumimoto, Kota; Hotta, Ryo; Nakakubo, Sho; Park, Hyuntae; Suzuki, Takao (J Alzheimers Dis, 2017)
BACKGROUND: The associations between components of metabolic syndrome (MetS) and mild cognitive impairment (MCI) subtypes remain unclear. OBJECTIVE: The study aim was to identify the prevalence of MetS for MCI subtypes and to investigate sex differences in the association between MetS and MCI subtypes in older Japanese adults. METHODS: The study analyzed data from 3,312 men and women aged 70 years or more. MetS was diagnosed according to International Diabetes Federation criteria. Participants completed cognitive tests and were categorized into normal cognition, amnestic MCI (aMCI), and non-amnestic MCI (naMCI). The associations between MetS and its components and MCI subtypes were analyzed using multiple logistic regression. RESULTS: MetS prevalence was greater in participants with naMCI (men: p = 0.030; women: p = 0.040). Participants with naMCI showed higher odds ratios (OR) of MetS (men: 2.45, 95% confidence intervals (CI): 1.13-5.32; women: OR: 1.94, 95% CI: 1.12-3.39) compared with participants with normal cognition. MetS was not associated with aMCI. Analysis of MetS components showed that raised glucose (OR: 1.62, 95% CI: 1.19-2.22) and reduced high-density lipoprotein cholesterol (OR: 1.97, 95% CI: 1.25-3.12) were associated with naMCI in men. In women, raised blood pressure (OR: 1.42, 95% CI: 1.03-1.94) and raised glucose (OR: 1.32, 95% CI: 1.02-1.71) were associated with naMCI. CONCLUSION: MetS was associated only with naMCI regardless of sex, which suggests etiologic differences in MCI subtypes. We also found sex differences in the relationship between naMCI risk and MetS and its components.

Secular Trends in the Incidence of Dementia in a Multi-Ethnic Community. - Noble, James M; Schupf, Nicole; Manly, Jennifer J; Andrews, Howard; Tang, Ming-Xin; Mayeux, Richard (J Alzheimers Dis, 2017)
BACKGROUND: Determination of secular trends in cognitive aging is important for prioritization of resources, services, and research in aging populations. Prior studies have identified declining dementia incidence associated with changes in cardiovascular risk factors and increased educational attainment. However, few studies have examined these factors in multi-ethnic cohorts. OBJECTIVE: To identify secular trends in the incidence rate of dementia in an elderly population. METHODS: Participants in this study were drawn from the Washington Heights-Inwood Columbia Aging Project, a multi-ethnic cohort study of northern Manhattan residents aged 65 years and older. Cox proportional hazards models were used to examine differences in the incidence of dementia in cohorts recruited in 1992 and 1999, with age at dementia or age at last follow-up visit as the "time-to-event" variable. RESULTS: Overall, there was a 41% reduction in the hazard ratio for dementia among participants in the 1999 cohort compared with those in the 1992 cohort, adjusting for age, sex, race, and baseline memory complaints (HR = 0.59). The reduction in incidence was greatest among non-Hispanic Whites and African-Americans and lowest among Hispanic participants (HRs = 0.60, 0.52 and 0.64, respectively), and was associated with increases in level of educational attainment, especially among African-Americans. Reduction in incidence of dementia was also greater among persons 75 years or older than among younger participants (HR = 0.52 versus HR = 0.69). CONCLUSIONS: Our results support previous findings that secular trends in dementia incidence are changing, including in aging minority populations.

Selenomethionine Attenuates the Amyloid-β Level by Both Inhibiting Amyloid-β Production and Modulating Autophagy in Neuron-2a/AβPPswe Cells. - Zhang, Zhong-Hao; Wu, Qiu-Yan; Chen, Chen; Zheng, Rui; Chen, Yao; Liu, Qiong; Ni, Jia-Zuan; Song, Guo-Li (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a complex and progressive neurological disorder, and amyloid-β (Aβ) has been recognized as the major cause of AD. Inhibiting Aβ production and/or enhancing the clearance of Aβ to reduce its levels are still the effective therapeutic strategies pursued in anti-AD research. In previous studies, we have reported that selenomethionine (Se-Met), a major form of selenium in animals and humans with significant antioxidant capacity, can reduce both amyloid-β (Aβ) deposition and tau hyperphosphorylation in a triple transgenic mouse model of AD. In this study, a Se-Met treatment significantly decreased the Aβ levels in Neuron-2a/AβPPswe (N2asw) cells, and the anti-amyloid effect of Se-Met was attributed to its ability to inhibit Aβ generation by suppressing the activity of BACE1. Furthermore, both the LC3-II/LC3-I ratio and the number of LC3-positive puncta were significantly decreased in Se-Met-treated cells, suggesting that Se-Met also promoted Aβ clearance by modulating the autophagy pathway. Subsequently, Se-Met inhibited the initiation of autophagy through the AKT-mTOR-p70S6K signaling pathway and enhanced autophagic turnover by promoting autophagosome-lysosome fusion and autophagic clearance. Our results further highlight the potential therapeutic effects of Se-Met on AD.

Sembragiline in Moderate Alzheimer's Disease: Results of a Randomized, Double-Blind, Placebo-Controlled Phase II Trial (MAyflOwer RoAD). - Nave, Stephane; Doody, Rachelle S; Boada, Merce; Grimmer, Timo; Savola, Juha-Matti; Delmar, Paul; Pauly-Evers, Meike; Nikolcheva, Tania; Czech, Christian; Borroni, Edilio; Ricci, Benedicte; Dukart, Juergen; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Sembragiline is a potent, selective, long-acting, and reversible MAO-B inhibitor developed as a potential treatment for Alzheimer's disease (AD). OBJECTIVE: To evaluate the safety, tolerability, and efficacy of sembragiline in patients with moderate AD. METHODS: In this Phase II study (NCT01677754), 542 patients with moderate dementia (MMSE 13-20) on background acetylcholinesterase inhibitors with/without memantine were randomized (1:1:1) to sembragiline 1 mg, 5 mg, or placebo once daily orally for 52 weeks. RESULTS: No differences between treated groups and placebo in adverse events or in study completion. The primary endpoint, change from baseline in ADAS-Cog11, was not met. At Week 52, the difference between sembragiline and placebo in ADAS-Cog11 change from baseline was - 0.15 (p = 0.865) and 0.90 (p = 0.312) for 1 and 5 mg groups, respectively. Relative to placebo at Week 52 (but not at prior assessment times), the 1 mg and 5 mg sembragiline groups showed differences in ADCS-ADL of 2.64 (p = 0.051) and 1.89 (p = 0.160), respectively. A treatment effect in neuropsychiatric symptoms (as assessed by the difference between sembragiline and placebo on BEHAVE-AD-FW) was also seen at Week 52 only: - 2.80 (p = 0.014; 1 mg) and - 2.64 (p = 0.019; 5 mg), respectively. A post hoc subgroup analysis revealed greater treatment effects on behavior and functioning in patients with more severe baseline behavioral symptoms (above the median). CONCLUSIONS: This study showed that sembragiline was well-tolerated in patients with moderate AD. The study missed its primary and secondary endpoints. Post hoc analyses suggested potential effect on neuropsychiatric symptoms and functioning in more behaviorally impaired study population at baseline.

Sensing of Alzheimer's Disease and Multiple Sclerosis Using Nano-Bio Interfaces. - Hajipour, Mohammad Javad; Ghasemi, Forough; Aghaverdi, Haniyeh; Raoufi, Mohammad; Linne, Uwe; Atyabi, Fatemeh; Nabipour, Iraj; Azhdarzadeh, Morteza; Derakhshankhah, Hossein; Lotfabadi, Alireza; Bargahi, Afshar; Alekhamis, Zahra; et al. (J Alzheimers Dis, 2017)
It is well understood that patients with different diseases may have a variety of specific proteins (e.g., type, amount, and configuration) in their plasmas. When nanoparticles (NPs) are exposed to these plasmas, the resulting coronas may incorporate some of the disease-specific proteins. Using gold (Au) NPs with different surface properties and corona composition, we have developed a colorimetric sensor array for the discrimination and detection of two neurodegenerative diseases, Alzheimer's disease (AD) and multiple sclerosis (MS). Applying a variety of techniques, including UV-visible spectra, array response analyses and liquid chromatography-tandem mass spectrometry, we found the corona-NP complexes, obtained from different human serums, had distinct protein composition, including some specific proteins that are known as AD and MS biomarkers. The array responses, analyzed by chemometrics and statistical methods, demonstrate promising capabilities of the sensor to unambiguously identify and discriminate AD and MS. The developed sensor array might enable a simple, inexpensive and rapid detection/discrimination of neurodegenerative diseases.

Sex Differences in the Psychophysical Response to Contact Heat in Moderate Cognitive Impairment Alzheimer's Disease: A Cross-Sectional Brief Report. - Cowan, Ronald L; Beach, Paul A; Atalla, Sebastian W; Dietrich, Mary S; Bruehl, Stephen P; Deng, Jie; Wang, Jinjiao; Newhouse, Paul A; Gore, John C; Monroe, Todd B (J Alzheimers Dis, 2017)
BACKGROUND: People with Alzheimer's disease (AD) report pain less frequently and receive less pain medication than people without AD. Recent studies have begun to elucidate how pain may be altered in those with AD. However, potential sex differences in pain responsiveness have never been explored in these patients. It is unclear whether sex differences found in prior studies of healthy young and older individuals extend to people with AD. OBJECTIVE: The purpose of this study was to examine sex differences in the psychophysical response to experimental thermal pain in people with AD. METHODS: Cross-sectional analysis of 14 male and 14 female age-matched (≥65 years of age, median = 74) and AD severity-matched (Mini-Mental State Exam score <24, median = 16) communicative people who completed thermal psychophysics. RESULTS: There was a statistically significant main effect of sex for both temperature and unpleasantness ratings that persisted after controlling for average and current pain (mixed-effects general liner model: temperature: p = 0.004, unpleasantness: p < 0.001). Females reported sensing mild pain and moderate pain percepts at markedly lower temperatures than did males (mild: Cohen's d = 0.72, p = 0.051, moderate: Cohen's d = 0.80, p = 0.036). By contrast, males rated mild and moderate thermal pain stimuli as more unpleasant than did females (mild: Cohen's d = 0.80, p = 0.072, moderate: Cohen's d = 1.32, p = 0.006). There were no statistically significant correlations of temperature with perceived unpleasantness for mild or moderate pain (rs = 0.29 and rs = 0.20 respectively, p > 0.05). CONCLUSIONS: Results suggest experimental pain-related sex differences persist in older adults with AD in a different manner than those previously demonstrated in cognitively intact older adults. These findings could potentially aid in developing targeted pain management approaches in this vulnerable population. Further studies are warranted to replicate the findings from this pilot work.

Subjective Cognitive Complaints in Cognitively Healthy Older Adults and Their Relationship to Cognitive Performance and Depressive Symptoms. - Marková, Hana; Andel, Ross; Stepankova, Hana; Kopecek, Miloslav; Nikolai, Tomas; Hort, Jakub; Thomas-Antérion, Catherine; Vyhnálek, Martin (J Alzheimers Dis, 2017)
BACKGROUND: Subjective cognitive complaints (SCCs) may be an early marker of prodromal Alzheimer's disease. OBJECTIVES: Using a 10-item yes/no SCCs questionnaire (Le Questionnaire de Plainte Cognitive [QPC]), we evaluated the prevalence and distribution of SCCs in cognitively healthy Czech older adults and examined total score and specific QPC items in relation to depressive symptomology and cognitive performance. METHODS: A sample of 340 cognitively healthy older community-dwelling volunteers aged 60 or older from the third wave of the longitudinal project National Normative Study of Cognitive Determinants of Healthy Aging, who underwent a comprehensive neuropsychological assessment and completed the QPC and the 15-item Geriatric Depression Scale (GDS-15). Regression analysis was controlled for age when GDS-15 was the outcome and for age and GDS-15 with cognitive domains as the outcome. RESULTS: 71% reported 1 + SCCs, with prevalence of individual complaints ranging from 4% to 40%. The number of SCCs was associated with GDS-15 (p < 0.001). Personality change (p < 0.001) and Limitation in daily activities (p = 0.002) were significantly associated with higher GDS-15 score and Spatial orientation difficulties (p = 0.019) and Impression of worse memory in comparison to peers (p = 0.012) were significantly associated with lower memory performance. CONCLUSIONS: We identified some cognitive complaints that were very common in our sample. Overall, a higher number of SCCs in well cognitively functioning individuals was most closely related to depressive symptomatology, while some specific complaints reflected lower memory performance and should be considered when screening for people at risk of cognitive decline.

Tau Oligomers Associate with Inflammation in the Brain and Retina of Tauopathy Mice and in Neurodegenerative Diseases. - Nilson, Ashley N; English, Kelsey C; Gerson, Julia E; Whittle, T Barton; Crain, C Nicolas; Xue, Judy; Sengupta, Urmi; Castillo-Carranza, Diana L; Zhang, Wenbo; Gupta, Praveena; Kayed, Rakez (J Alzheimers Dis, 2017)
It is well-established that inflammation plays an important role in Alzheimer's disease (AD) and frontotemporal lobar dementia (FTLD). Inflammation and synapse loss occur in disease prior to the formation of larger aggregates, but the contribution of tau to inflammation has not yet been thoroughly investigated. Tau pathologically aggregates to form large fibrillar structures known as tangles. However, evidence suggests that smaller soluble aggregates, called oligomers, are the most toxic species and form prior to tangles. Furthermore, tau oligomers can spread to neighboring cells and between anatomically connected brain regions. In addition, recent evidence suggests that inspecting the retina may be a window to brain pathology. We hypothesized that there is a relationship between tau oligomers and inflammation, which are hallmarks of early disease. We conducted immunofluorescence and biochemical analyses on tauopathy mice, FTLD, and AD subjects. We showed that oligomers co-localize with astrocytes, microglia, and HMGB1, a pro-inflammatory cytokine. Additionally, we show that tau oligomers are present in the retina and are associated with inflammatory cells suggesting that the retina may be a valid non-invasive biomarker for brain pathology. These results suggest that there may be a toxic relationship between tau oligomers and inflammation. Therefore, the ability of tau oligomers to spread may initiate a feed-forward cycle in which tau oligomers induce inflammation, leading to neuronal damage, and thus more inflammation. Further mechanistic studies are warranted in order to understand this relationship, which may have critical implications for improving the treatment of tauopathies.

Tocotrienol-Rich Fraction Modulates Amyloid Pathology and Improves Cognitive Function in AβPP/PS1 Mice. - Ibrahim, Nor Faeizah; Yanagisawa, Daijiro; Durani, Lina Wati; Hamezah, Hamizah Shahirah; Damanhuri, Hanafi Ahmad; Wan Ngah, Wan Zurinah; Tsuji, Mayumi; Kiuchi, Yuji; Ono, Kenjiro; Tooyama, Ikuo (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is the most common cause of dementia. The cardinal neuropathological characteristic of AD is the accumulation of amyloid-β (Aβ) into extracellular plaques that ultimately disrupt neuronal function and lead to neurodegeneration. One possible therapeutic strategy therefore is to prevent Aβ aggregation. Previous studies have suggested that vitamin E analogs slow AD progression in humans. In the present study, we investigated the effects of the tocotrienol-rich fraction (TRF), a mixture of vitamin E analogs from palm oil, on amyloid pathology in vitro and in vivo. TRF treatment dose-dependently inhibited the formation of Aβ fibrils and Aβ oligomers in vitro. Moreover, daily TRF supplementation to AβPPswe/PS1dE9 double transgenic mice for 10 months attenuated Aβ immunoreactive depositions and thioflavin-S-positive fibrillar type plaques in the brain, and eventually improved cognitive function in the novel object recognition test compared with control AβPPswe/PS1dE9 mice. The present result indicates that TRF reduced amyloid pathology and improved cognitive functions, and suggests that TRF is a potential therapeutic agent for AD.

The Utility of the Cognitive Function Instrument (CFI) to Detect Cognitive Decline in Non-Demented Older Adults. - Li, Clara; Neugroschl, Judith; Luo, Xiaodong; Zhu, Carolyn; Aisen, Paul; Ferris, Steven; Sano, Mary (J Alzheimers Dis, 2017)
BACKGROUND: Subjective cognitive complaint is a sensitive marker of decline. OBJECTIVE: This study aimed to (1) examine reliability of subjective cognitive complaint using the Cognitive Function Instrument (CFI), and (2) assess the utility of the CFI to detect cognitive decline in non-demented elders. METHODS: Data from a four-year longitudinal study at multiple Alzheimer's Disease Cooperative Study (ADCS) sites were extracted (n = 644). Of these, 497 had Clinical Dementia Rating (CDR) global scores of 0 and 147 had a CDR of 0.5. Mean age and education were 79.5±3.6 and 15.0±3.1 years, respectively. All participants and their study partners completed the subject and study partner CFI yearly. Modified Mini-Mental State Exam (mMMSE) and Free and Cued Selective Reminding Test (FCSRT) were administered. Scores below the predetermined cut-off scores on either measure at annual visit were triggers for a full diagnostic evaluation. Cognitive decline was defined by the absence/presence of the trigger. RESULTS: Three-month test retest reliability showed that inter-class coefficients for subject and study partner CFI were 0.76 and 0.78, respectively. Generalized estimating equation method revealed that both subject and study partner CFI change scores and scores from previous year were sensitive to cognitive decline in the CDR 0 group (p < 0.05). In the CDR 0.5 group, only the study partner CFI change score predicted cognitive decline (p < 0.05). CONCLUSION: Cognitive decline was predicted differentially by CDR level with subject CFI scores providing the best prediction for those with CDR 0 while study partner CFI predicted best for those at CDR 0.5.

Validation by Magnetic Resonance Imaging of the Diagnostic Potential of a Heptapeptide-Functionalized Imaging Probe Targeted to Amyloid-β and Able to Cross the Blood-Brain Barrier. - André, Séverine; Ansciaux, Emilie; Saidi, Elamine; Larbanoix, Lionel; Stanicki, Dimitri; Nonclercq, Denis; Vander Elst, Luce; Laurent, Sophie; Muller, Robert N; Burtea, Carmen (J Alzheimers Dis, 2017)
The diagnosis of Alzheimer's disease (AD) is a critical step in the management of patients. We have developed a non-invasive diagnosis tool based on magnetic resonance molecular imaging (MRMI) of amyloid-β peptide using ultra-small particles of iron oxide (USPIO) functionalized with a disulfide constrained cyclic heptapeptide (PHO) identified by phage display (USPIO-PHO). After previously demonstrating the optimal pharmacologic properties of USPIO-PHO and its capacity to cross the blood-brain barrier (BBB), the ability of USPIO-PHO to target amyloid plaques (AP) by MRMI has been validated in the present work on AD transgenic mice. The immunohistochemistry and immunofluorescent detection of USPIO-PHO on brain sections collected after in vivo MRMI studies enabled its colocalization with AP, confirming the BBB passage and specific targeting. The AP targeting by USPIO-PHO has been moreover corroborated by the good correlation between the number of AP detected with anti-amyloid β antibody and Perls'-DAB staining. Finally, the crossing mechanism of USPIO-PHO through the BBB was elucidated, revealing the involvement of non-degradation pathway of caveolae, while the control contrast agent USPIO-PEG was not endocytosed by the human brain endothelial cells.

Validation of a Latent Construct for Dementia in a Population-Wide Dataset from Singapore. - Peh, Chao Xu; Abdin, Edimansyah; Vaingankar, Janhavi A; Verma, Swapna; Chua, Boon Yiang; Sagayadevan, Vathsala; Seow, Esmond; Zhang, YunJue; Shahwan, Shazana; Ng, Li Ling; Prince, Martin; Chong, Siow Ann; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The latent variable δ has been proposed as a proxy for dementia. Previous validation studies have been conducted using convenience samples. It is currently unknown how δ performs in population-wide data. OBJECTIVE: To validate δ in Singapore using population-wide epidemiological study data on persons aged 60 and above. METHODS: δ was constructed using items from the Community Screening Instrument for Dementia (CSI'D) and World Health Organization Disability Assessment Schedule (WHODAS II). Confirmatory factor analysis (CFA) was conducted to examine δ model fit. Convergent validity was examined with the Clinical Dementia Rating scale (CDR) and GMS-AGECAT dementia. Divergent validity was examined with GMS-AGECAT depression. RESULTS: The δ model demonstrated fit to the data, χ2(df) = 249.71(55), p < 0.001, CFI = 0.990, TLI = 0.997, RMSEA = 0.037. Latent variable δ was significantly associated with CDR and GMS-AGECAT dementia (range: β= 0.32 to 0.63), and was not associated with GMS-AGECAT depression. Compared to unadjusted models, δ model fit was poor when adjusted for age, gender, ethnicity, and education. CONCLUSION: The study found some support for δ as a proxy for dementia in Singapore based on population data. Both convergent and divergent validity were established. In addition, the δ model structure appeared to be influenced by age, gender, ethnicity, and education covariates.

Violation of Laws in Frontotemporal Dementia: A Multicenter Study in Japan. - Shinagawa, Shunichiro; Shigenobu, Kazue; Tagai, Kenji; Fukuhara, Ryuji; Kamimura, Naoto; Mori, Takaaki; Yoshiyama, Kenji; Kazui, Hiroaki; Nakayama, Kazuhiko; Ikeda, Manabu (J Alzheimers Dis, 2017)
Although violations of laws, such as shoplifting, are considered to be common in frontotemporal dementia (FTD) patients, there have been few studies on this subject and the frequencies and types of such violations have not been clarified. The objective of this study was to conduct a retrospective investigation of FTD patients in the psychiatry departments of multiple institutions to determine the types and frequencies of any law violations and compare them with those of AD patients. All patients were examined between January 2011 and December 2015 at the specialized dementia outpatient clinics of 10 facilities (5 psychiatry departments of university hospitals, 5 psychiatric hospitals). According to diagnostic criteria, 73 behavior variant FTD (bvFTD) patients, 84 semantic variant of primary progressive aphasia (svPPA) patients, and 255 age- and sex-matched AD subjects as the control group were selected. The findings revealed a higher rate of law violations in the bvFTD and svPPA patients before the initial consultation as compared to the AD group (bvFTD: 33%, svPPA: 21%, AD: 6%) and that many patients had been referred due to such violations. Laws had been broken 4 times or 5 or more times in several cases in the FTD group before the initial consultation. Regarding rates for different types of violation, in bvFTD subjects, the highest rate was for theft, followed by nuisance acts and hit and run. In svPPA, theft had the highest rate, followed by ignoring road signs. There was no gender difference in law violations but they were more frequent when the disease was severe at the initial consultation in the FTD group. As the rates of law violations after the initial consultation were lower than before it, interventions were considered to have been effective. These findings may be useful for future prevention as well as to the legal system.

Visit-to-Visit Blood Pressure Variability and Alzheimer's Disease: Links and Risks. - Nagai, Michiaki; Dote, Keigo; Kato, Masaya; Sasaki, Shota; Oda, Noboru; Kagawa, Eisuke; Nakano, Yoshinori; Yamane, Aya; Higashihara, Tasuku; Miyauchi, Shunsuke; Tsuchiya, Akane (J Alzheimers Dis, 2017)
While hypertension has been shown to be a risk factor for vascular dementia, several studies have also demonstrated that hypertension also increases the risk of Alzheimer's disease (AD). Although the relationship between visit-to-visit blood pressure variability (VVV) and cognitive impairment, including AD, have been provided, the mechanisms remain poorly understood. This review paper focuses on the relationship of VVV with AD and summarizes the pathophysiology underlying that relationship, which appears to be mediated by arterial stiffness.

An 18-mer Peptide Derived from Prosaposin Ameliorates the Effects of Aβ1-42 Neurotoxicity on Hippocampal Neurogenesis and Memory Deficit in Mice. - Gao, Hui-Ling; Li, Cheng; Nabeka, Hiroaki; Shimokawa, Tetsuya; Wang, Zhan-You; Cao, Ya-Ming; Matsuda, Seiji (J Alzheimers Dis, 2016)
The pathological hallmarks of Alzheimer's disease (AD) include amyloid-β (Aβ) accumulation, neurofibrillary tangle formation, synaptic dysfunction, and neuronal loss. The present study was performed to investigate the protective effects and mechanism of action of a prosaposin-derived 18-mer peptide (PS18: LSELIINNATEELLIKGL) on mice hippocampal progenitor cell proliferation, neurogenesis, and memory tasks after intracerebroventricular injection of Aβ1-42 peptide. Seven days after Aβ1-42 injection, significant proliferation of hippocampal progenitor cells and memory impairment were evident. Two weeks after Aβ1-42 peptide injection, elevated numbers of surviving 5-bromo-2-deoxyuridine cells and newly formed neurons were detected. Treatment with PS18 attenuated these effects evoked by Aβ1-42. Our data indicate that treatment with PS18 partially attenuated the increase in hippocampal neurogenesis caused by Aβ1-42-induced neuroinflammation and prevented memory deficits associated with increased numbers of activated glial cells. We observed an increase in ADAM10 and decreases in BACE1, PS1/2, and AβPP protein levels, suggesting that PS18 enhances the nonamyloidogenic AβPP cleavage pathway. Importantly, our results further showed that PS18 activated the PI3K/Akt pathway, phosphorylated GSK-3α/β, and, as a consequence, exerted a neuroprotective effect. In addition, PS18 showed a protective effect against Aβ1-42-induced neurotoxicity via suppression of the caspase pathway; upregulation of Bcl-2; downregulation of BAX, attenuating mitochondrial damage; and inhibition of caspase-3. These findings suggest that PS18 may provide a valuable therapeutic strategy for the treatment of progressive neurodegenerative diseases, such as AD.

Aberrant Spontaneous Brain Activity in Patients with Mild Cognitive Impairment and concomitant Lacunar Infarction: A Resting-State Functional MRI Study. - Ni, Ling; Liu, Renyuan; Yin, Zhenyu; Zhao, Hui; Nedelska, Zuzana; Hort, Jakub; Zhou, Fei; Wu, Wenbo; Zhang, Xin; Li, Ming; Yu, Haiping; Zhu, Bin; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Lacunar infarctions (LI) have been associated with a cognitive decline and an increased risk of dementia. Whether and how the pattern of spontaneous brain activity in patients with mild cognitive impairment (MCI) differs in subjects with and without concomitant LI remains unclear. OBJECTIVE: To compare the pattern of spontaneous brain activity in MCI patients with versus those without LI using resting-state functional magnetic resonance imaging (rs-fMRI). METHODS: Forty-eight MCI patients, including 22 with LI [MCI-LI] and 26 without LI [MCI-no LI], and 28 cognitive normal subjects underwent rs-fMRI post-processed using regional homogeneity (ReHo) and the amplitude of low-frequency fluctuation (ALFF) methods. RESULTS: Compared with cognitively normal subjects, the MCI-LI patients had decreased ReHo in the precuneus/cuneus (Pcu/CU) and insula; decreased ALFF in the Pcu/CU and frontal lobe; and increased ALFF and ReHo in the temporal lobe. While the MCI-no LI group had increased ReHo and ALFF in the bilateral hippocampus and parahippocampal gyrus, frontal lobe, and decreased ALFF and ReHo in the temporal lobe. Compared with the MCI-no LI patients, those with MCI-LI had decreased ALFF in the frontal lobe; decreased ReHo in the Pcu/CU and insula; and increased ALFF and ReHo in the temporal lobe (p <  0.05, AlphaSim corrected). In MCI-LI patients, the MOCA scores showed a relatively weak correlation with ALFF values in the medial frontal gyrus (r = 0.432, p = 0.045) (of borderline significance after Bonferroni correction). CONCLUSIONS: The spontaneous brain activities in MCI-LI were distinct from MCI-no LI. The probable compensatory mechanism observed in MCI-no LI might be disrupted in MCI with LI due to vascular damage.
Keywords: Aged; Aged, 80 and over; Brain; Brain Mapping; Cognitive Dysfunction; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Rest; Stroke, Lacunar

Age-Dependent Regulation of the Blood-Brain Barrier Influx/Efflux Equilibrium of Amyloid-β Peptide in a Mouse Model of Alzheimer's Disease (3xTg-AD). - Do, Tuan Minh; Dodacki, Agnès; Alata, Wael; Calon, Frederic; Nicolic, Sophie; Scherrmann, Jean-Michel; Farinotti, Robert; Bourasset, Fanchon (J Alzheimers Dis, 2016)
The involvement of transporters located at the blood-brain barrier (BBB) has been suggested in the control of cerebral Aβ levels, and thereby in Alzheimer's disease (AD). However, little is known about the regulation of these transporters at the BBB in animal models of AD. In this study, we investigated the BBB expression of Aβ influx (Rage) and efflux (Abcb1-Abcg2-Abcg4-Lrp-1) transporters and cholesterol transporter (Abca1) in 3-18-month-old 3xTg-AD and control mice. The age-dependent effect of BBB transporters regulation on the brain uptake clearance (Clup) of [3H]cholesterol and [3H]Aβ1 - 40 was then evaluated in these mice, using the in situ brain perfusion technique. Our data suggest that transgenes expression led to the BBB increase in Aβ influx receptor (Rage) and decrease in efflux receptor (Lrp-1). Our data also indicate that mice have mechanisms counteracting this increased net influx. Indeed, Abcg4 and Abca1 are up regulated in 3- and 3/6-month-old 3xTg-AD mice, respectively. Our data show that the balance between the BBB influx and efflux of Aβ is maintained in 3 and 6-month-old 3xTg-AD mice, suggesting that Abcg4 and Abca1 control the efflux of Aβ through the BBB by a direct (Abcg4) or indirect (Abca1) mechanism. At 18 months, the BBB Aβ efflux is significantly increased in 3xTg-AD mice compared to controls. This could result from the significant up-regulation of both Abcg2 and Abcb1 in 3xTg-AD mice compared to control mice. Thus, age-dependent regulation of several Aβ and cholesterol transporters at the BBB could ultimately limit the brain accumulation of Aβ.
Keywords: Aging; Alzheimer Disease; Amyloid beta-Peptides; Animals; ATP Binding Cassette Transporter, Sub-Family G, Member 1; ATP Binding Cassette Transporter, Sub-Family G, Member 2; ATP-Binding Cassette Transporters; Biological Transport; Blood-Brain Barrier; Brain; Carbon Isotopes; Cholesterol; Disease Models, Animal; Humans; Lipoproteins; Mice; Mice, Transgenic; P-Glycoproteins; Peptide Fragments; Receptors, LDL; Sucrose; Tritium; Tumor Suppressor Proteins

Aging Enables Ca2+ Overload and Apoptosis Induced by Amyloid-β Oligomers in Rat Hippocampal Neurons: Neuroprotection by Non-Steroidal Anti-Inflammatory Drugs and R-Flurbiprofen in Aging Neurons. - Calvo-Rodríguez, María; García-Durillo, Mónica; Villalobos, Carlos; Núñez, Lucía (J Alzheimers Dis, 2016)
The most important risk factor for Alzheimer's disease (AD) is aging. Neurotoxicity in AD has been linked to dyshomeostasis of intracellular Ca2+ induced by small aggregates of the amyloid-β peptide 1-42 (Aβ42 oligomers). However, how aging influences susceptibility to neurotoxicity induced by Aβ42 oligomers is unknown. In this study, we used long-term cultures of rat hippocampal neurons, a model of neuronal in vitro aging, to investigate the contribution of aging to Ca2+ dishomeostasis and neuron cell death induced by Aβ42 oligomers. In addition, we tested whether non-steroidal anti-inflammatory drugs (NSAIDs) and R-flurbiprofen prevent apoptosis acting on subcellular Ca2+ in aged neurons. We found that Aβ42 oligomers have no effect on young hippocampal neurons cultured for 2 days in vitro (2 DIV). However, they promoted apoptosis modestly in mature neurons (8 DIV) and these effects increased dramatically after 13 DIV, when neurons display many hallmarks of in vivo aging. Consistently, cytosolic and mitochondrial Ca2+ responses induced by Aβ42 oligomers increased dramatically with culture age. At low concentrations, NSAIDs and the enantiomer R-flurbiprofen lacking anti-inflammatory activity prevent Ca2+ overload and neuron cell death induced by Aβ42 oligomers in aged neurons. However, at high concentrations R-flurbiprofen induces apoptosis. Thus, Aβ42 oligomers promote Ca2+ overload and neuron cell death only in aged rat hippocampal neurons. These effects are prevented by low concentrations of NSAIDs and R-flurbiprofen acting on mitochondrial Ca2+ overload.

Alterations in the Levels of Amyloid-β, Phospholipid Hydroperoxide, and Plasmalogen in the Blood of Patients with Alzheimer's Disease: Possible Interactions between Amyloid-β and These Lipids. - Yamashita, Shinji; Kiko, Takehiro; Fujiwara, Hironori; Hashimoto, Michio; Nakagawa, Kiyotaka; Kinoshita, Mikio; Furukawa, Katsutoshi; Arai, Hiroyuki; Miyazawa, Teruo (J Alzheimers Dis, 2016)
Aside from accumulation of amyloid-β (Aβ) peptide in the brain, Alzheimer's disease (AD) has been reported as being associated with peroxidation of major phospholipids (e.g., phosphatidylcholine (PtdCho)) and degradation of antioxidative phospholipids (e.g., ethanolamine plasmalogen (PlsEtn)). In addition to its presence in the brain, Aβ is also found in blood; however, there is still little information about the levels of PtdCho hydroperoxide (PCOOH) and PlsEtn in the blood of patients with AD. In this study, by assuming a possible interaction among Aβ, PCOOH, and PlsEtn in blood circulation, we evaluated the levels of these molecules and correlations in blood samples that had been obtained from our former AD study for PCOOH measurement (Kiko et al., J Alzheimers Dis28, 593-600, 2012). We found that when compared to controls, plasma from patients with AD showed lower concentrations of PlsEtn species, especially PlsEtn bearing the docosahexaenoic acid (DHA) moiety. In addition, lower PlsEtn and higher PCOOH levels were observed in red blood cells (RBCs) of patients with AD. In both AD and control blood samples, RBC PCOOH levels tended to correlate with plasma levels of Aβ40, and each PlsEtn species showed different correlations with plasma Aβ. These results, together with in vitro data suggesting Aβ aggregation due to a decrease in levels of PlsEtn having DHA, led us to deduce that Aβ is involved in alterations in levels of PCOOH and PlsEtn species observed in the blood of patients with AD.
Keywords: Aged; Amyloid beta-Peptides; Female; Humans; Hydrogen Peroxide; Male; Phosphatidylcholines; Plasmalogens

Altered sense of humor in dementia. - Clark, Camilla N; Nicholas, Jennifer M; Gordon, Elizabeth; Golden, Hannah L; Cohen, Miriam H; Woodward, Felix J; Macpherson, Kirsty; Slattery, Catherine F; Mummery, Catherine J; Schott, Jonathan M; Rohrer, Jonathan D; Warren, Jason D (J Alzheimers Dis, 2016)
Sense of humor is potentially relevant to social functioning in dementias, but has been little studied in these diseases. We designed a semi-structured informant questionnaire to assess humor behavior and preferences in patients with behavioral variant frontotemporal dementia (bvFTD; n = 15), semantic dementia (SD; n = 7), progressive nonfluent aphasia (PNFA; n = 10), and Alzheimer's disease (AD; n = 16) versus healthy age-matched individuals (n = 21). Altered (including frankly inappropriate) humor responses were significantly more frequent in bvFTD and SD (all patients) than PNFA or AD (around 40% of patients). All patient groups liked satirical and absurdist comedy significantly less than did healthy controls. This pattern was reported premorbidly for satirical comedy in bvFTD, PNFA, and AD. Liking for slapstick comedy did not differ between groups. Altered sense of humor is particularly salient in bvFTD and SD, but also frequent in AD and PNFA. Humor may be a sensitive probe of social cognitive impairment in dementia, with diagnostic, biomarker and social implications.
Keywords: Aged; Alzheimer Disease; Case-Control Studies; Cognition Disorders; Emotions; Female; Frontotemporal Dementia; Humans; Male; Middle Aged; Neuropsychological Tests; Primary Progressive Nonfluent Aphasia; Psychiatric Status Rating Scales; Surveys and Questionnaires

Alzheimer's and Parkinson's Diseases: Expected Economic Impact on Europe-A Call for a Uniform European Strategy. - Maresova, Petra; Klimova, Blanka; Novotny, Michal; Kuca, Kamil (J Alzheimers Dis, 2016)
The purpose of this study is to analyze the economic burden of persons with Alzheimer's disease (AD) and Parkinson's disease (PD) in Europe. On the basis of available data about the number of persons with dementia, their prevalence, and treatment and care costs, a mean cost burden is estimated for the year of 2030 and for the year of 2050 in Europe. The method of retrospective analysis of available sources was used; furthermore, analysis of database data such as WHO and Eurostat, which provide information about the number of older people and people with dementia; and specification of direct and indirect medical and nonmedical costs of patients with AD and PD from current studies was also used. The findings of this study confirm that the number of patients affected with AD and PD, as well as annual costs of the treatment and care of these patients, in the selected European countries are rapidly growing. The cost burden of both AD and PD in the selected European countries rises year by year, and by 2050, the cost burden of both diseases in fact will be almost two times higher in comparison with the year of 2010. In 2050, the overall mean cost burden is estimated to reach 357 billion Euros. The European Union calls for a joint initiative in the development of a uniformed strategic plan in the fight against dementia.

Amyloid-β Reduces Exosome Release from Astrocytes by Enhancing JNK Phosphorylation. - Abdullah, Mohammad; Takase, Hiroshi; Nunome, Mari; Enomoto, Hiroyuki; Ito, Jin-Ichi; Gong, Jian-Sheng; Michikawa, Makoto (J Alzheimers Dis, 2016)
Exosomes are small extracellular vesicles secreted by variety of cell types such as neurons, astrocytes, and oligodendrocytes. It is suggested that exosomes play essential role in the maintenance of the neuronal functions and also in the clearance of amyloid-β (Aβ) from the brain. Aβ is well known to cause neuronal cell death, whereas little is known about its effect on astrocytes. In this study, we examined the effect of Aβ on release of exosomes from astrocytes in culture. We analyzed release of exosomes and apoE, both of which are known to remove/clear Aβ from the brain, in the culture medium of astrocytes. We found that exosome and apoE-HDL were successfully separated by density gradient ultracentrifugation demonstrated by distribution of their specific markers, flotillin and HSP90, and cholesterol, and morphological analysis using electron microscopy. Exosome release was significantly reduced by Aβ1-42 treatment in cultured astrocytes accompanied by an increased JNK phosphorylation. Whereas, apoE-HDL release remained unchanged. A JNK inhibitor restored the decreased levels of exosome release induced by Aβ treatment to levels similar to those of control, suggesting that Aβ1-42 inhibits exosome release via stimulation of JNK signal pathway. Because exosomes are shown to remove Aβ in the brain, our findings suggest that increased Aβ levels in the brain may impair the exosome-mediated Aβ clearance pathway.

Apo J and Apo D: Complementary or Antagonistic Roles in Alzheimer's Disease? - Del Valle, Eva; Navarro, Ana; Martínez-Pinilla, Eva; Torices, Silvia; Tolivia, Jorge (J Alzheimers Dis, 2016)
Apolipoprotein D (Apo D) and Apolipoprotein J (Apo J) are among the only nine apolipoproteins synthesized in the nervous system. Apart from development, these apolipoproteins are implicated in the normal aging process as well as in different neuropathologies as Alzheimer's disease (AD), where a neuroprotective role has been postulated. Different authors have proposed that Apo D and Apo J could be biomarkers for AD but as far as we know, there are no studies about the relationship between them as well as their expression pattern along the progression of the disease. In this paper, using double immunohistochemistry techniques, we have demonstrated that Apo D is mainly located in glial cells while Apo J expression preferentially occurs in neurons; both proteins are also present in AD diffuse and mature senile plaques but without signal overlap. In addition, we have observed that Apo J and Apo D immunostaining shows a positive correlation with the progression of the disease and the Braak's stages. These results suggest complementary and cell-dependent neuroprotective roles for each apolipoprotein during AD progress.

Association between Cerebrospinal Fluid Biomarkers for Alzheimer's Disease, APOE Genotypes and Auditory Verbal Learning Task in Subjective Cognitive Decline, Mild Cognitive Impairment, and Alzheimer's Disease. - Mandecka, Monika; Budziszewska, Magdalena; Barczak, Anna; Pepłońska, Beata; Chodakowska-Żebrowska, Małgorzata; Filipek-Gliszczyńska, Anna; Nesteruk, Marta; Styczyńska, Maria; Barcikowska, Maria; Gabryelewicz, Tomasz (J Alzheimers Dis, 2016)
In the course of Alzheimer's disease (AD), early pathological changes in the brain start decades before any clinical manifestation. The concentration levels of AD cerebrospinal fluid (CSF) biomarkers, such as amyloid-β1-42 (Aβ1-42), total tau (T-tau), and phosphorylated tau (P-tau), may reflect a cerebral pathology facilitating an early diagnosis of the disease and predicting a cognitive deterioration. The aim of this study was to estimate the prevalence of AD CSF biomarkers in those individuals with a subjective cognitive decline (SCD), a mild cognitive impairment (MCI), and Alzheimer's dementia (AD-D), together with the relationships between the biomarkers, an APOE ɛ4 presence, and a verbal episodic memory performance. We included 252 patients from the memory clinic with a diagnosis of SCD (n = 85), MCI (n = 87), and AD-D (n = 80). A verbal episodic memory performance level was assessed and was based on a delayed recall trial from the 10-word list of an auditory verbal learning task (AVLT). We found that the patients with more severe cognitive impairments had significantly lower levels of Aβ1-42 and higher levels of T-tau and P-tau. This pattern was also typical for the APOE ɛ4 carriers, who had lower levels of Aβ1-42 than the noncarriers in the AD-D and MCI groups. The levels of T-tau and P-tau were significantly higher in the APOE ɛ4 carriers than in the noncarriers, but only in the MCI patients. The AVLT performance in the whole study samples was predicted by age, Aβ1-42, and the T-tau CSF biomarkers, but not by the APOE genotyping.

Association of Coffee Consumption with MRI Markers and Cognitive Function: A Population-Based Study. - Araújo, Larissa Fortunato; Mirza, Saira Saeed; Bos, Daniel; Niessen, Wiro J; Barreto, Sandhi Maria; van der Lugt, Aad; Vernooij, Meike W; Hofman, Albert; Tiemeier, Henning; Ikram, M Arfan (J Alzheimers Dis, 2016)
BACKGROUND: Coffee is one of the most widely consumed beverages worldwide and has been of considerable interest in research on cognition and dementia. OBJECTIVE: To investigate the effect of coffee on preclinical brain MRI markers of dementia and cognitive performance. METHODS: In 2,914 participants from the population-based Rotterdam Study (mean age: 59.3±7.2 years, 55% females), we assessed coffee consumption, performed brain MRI, and assessed cognition at baseline. To study cognitive change, cognitive assessment was repeated after 5 years of follow-up. Coffee consumption was analyzed continuously (per cup increase) and in categories (0-1, >1-3, >3 cups/day). Using logistic and linear regression, associations of coffee consumption with lacunar infarcts and brain tissue volumes on MRI, and cognitive performance (cross-sectional and longitudinal) were investigated, adjusting for relevant confounders. RESULTS: We found that higher coffee consumption was associated with a lower prevalence of lacunar infarcts [odds ratio per cup increase: 0.88 (95% CI:0.79;0.98)], and smaller hippocampal volume [difference: -0.01 (95% CI:-0.02;0.00)]. Also, we found that the highest category of coffee consumption was associated with better performance on the Letter Digit Substitution Task [difference: 1.13(95% CI:0.39;1.88)], Word Fluency test [0.74(95% CI:0.04,1.45)], Stroop interference task [1.82(95% CI:0.23;3.41)], and worse performance on the 15-Word Learning test delayed recall [-0.38(95% CI:-0.74;-0.02)]. These associations were not found when cognition was analyzed longitudinally. CONCLUSION: We found complex associations between coffee consumption, brain structure, and cognition. Higher coffee consumption was cross-sectionally associated with a lower occurrence of lacunar infarcts and better executive function, but also with smaller hippocampal volume and worse memory function.

Association of Plasma Aβ40 Peptides, But Not Aβ42, with Coronary Artery Disease and Diabetes Mellitus. - Roeben, Benjamin; Maetzler, Walter; Vanmechelen, Eugeen; Schulte, Claudia; Heinzel, Sebastian; Stellos, Konstantinos; Godau, Jana; Huber, Heiko; Brockmann, Kathrin; Wurster, Isabel; Gaenslen, Alexandra; Grüner, Eva; et al. (J Alzheimers Dis, 2016)
BACKGROUND/OBJECTIVE: Plasma levels of amyloid-beta (Aβ) 1-40 peptide have been proposed to be associated with cardiovascular mortality in patients with coronary artery disease (CAD). Therefore, we aimed to investigate the association of plasma Aβ levels with CAD, cardiovascular risk factors (CVRF), and APOE genotype in non-demented elderly individuals. METHODS: Plasma Aβ1 - 40 and Aβ1 - 42 levels of 526 individuals (mean age of 63.0±7.3 years) were quantified with the INNO-BIA plasma Aβ forms assay based on multiplextrademark technique. APOE genotype was determined with an established protocol. Presence of CAD and CVRFs were ascertained using a questionnaire and/or medical records. RESULTS: Plasma Aβ1 - 40 levels were significantly higher in individuals with CAD (p = 0.043) and, independently, in individuals with diabetes mellitus (DM) type 2 (p = 0.001) while accounting for age- and gender-effects. Plasma Aβ1 - 42 levels were higher in APOEɛ4 carriers (p = 0.004), but were neither relevantly associated with CAD nor with any CVRF. Plasma Aβ1 - 40 showed no association with APOE genotype. DISCUSSION: Our findings argue for an association of circulating plasma Aβ1 - 40 peptides with incident CAD and DM. Further investigations are needed to entangle the role of Aβ1 - 40 role in the pathophysiology of cardiovascular disease independent of its known role in Alzheimer's disease.

Associations between Performance on an Abbreviated CogState Battery, Other Measures of Cognitive Function, and Biomarkers in People at Risk for Alzheimer's Disease. - Racine, Annie M; Clark, Lindsay R; Berman, Sara E; Koscik, Rebecca L; Mueller, Kimberly D; Norton, Derek; Nicholas, Christopher R; Blennow, Kaj; Zetterberg, Henrik; Jedynak, Bruno; Bilgel, Murat; Carlsson, Cynthia M; et al. (J Alzheimers Dis, 2016)
It is not known whether computerized cognitive assessments, like the CogState battery, are sensitive to preclinical cognitive changes or pathology in people at risk for Alzheimer's disease(AD). In 469 late middle-aged participants from the Wisconsin Registry for Alzheimer's Prevention(mean age 63.8±7 years at testing; 67% female; 39% APOE4+), we examined relationships between a CogState abbreviated battery(CAB) of seven tests and demographic characteristics, traditional paper-based neuropsychological tests as well as a composite cognitive impairment index, cognitive impairment status(determined by consensus review), and biomarkers for amyloid and tau(CSF phosphorylated-tau/Aβ42 and global PET-PiB burden) and neural injury(CSF neurofilament light protein). CSF and PET-PiB were collected in n = 71 and n = 91 participants, respectively, approximately four years prior to CAB testing. For comparison, we examined three traditional tests of delayed memory in parallel. Similar to studies in older samples, the CAB was less influenced by demographic factors than traditional tests. CAB tests were generally correlated with most paper-based cognitive tests examined and mapped onto the same cognitive domains. Greater composite cognitive impairment index was associated with worse performance on all CAB tests. Cognitively impaired participants performed significantly worse compared to normal controls on all but one CAB test. Poorer One Card Learning test performance was associated with higher levels of CSF phosphorylated-tau/Aβ42. These results support the use of the CogState battery as measures of early cognitive impairment in studies of people at risk for AD.

Associations between Serum Omega-3 Fatty Acid Levels and Cognitive Functions among Community-Dwelling Octogenarians in Okinawa, Japan: The KOCOA Study. - Nishihira, Junko; Tokashiki, Takashi; Higashiuesato, Yasushi; Willcox, Donald Craig; Mattek, Nora; Shinto, Lynne; Ohya, Yusuke; Dodge, Hiroko H (J Alzheimers Dis, 2016)
BACKGROUND: Epidemiological studies have found frequent consumption of fatty fish is protective against cognitive decline. However, the association between circulating omega-3 polyunsaturated fatty acid (PUFA) levels and cognitive functions among the oldest old is not well known. OBJECTIVE: To examine the association between serum PUFA levels and cognitive function among community-dwelling, non-demented elderly aged over 80 years old. METHODS: The data came from the Keys to Optimal Cognitive Aging (KOCOA) study; an ongoing cohort of relatively healthy volunteers aged over 80 years old, living in Okinawa, Japan. One hundred eighty five participants (mean age 84.1±3.4 years) assessed in 2011 who were free from frank dementia (defined as Clinical Dementia Rating <1.0) were used for the current cross-sectional study. We examined whether serum omega-3 PUFAs (docosahexaenoic acid [DHA] and eicosapentaenoic acid [EPA]), arachidonic acid (AA), EPA/AA ratio, DHA/AA ratio, and DHA+EPA are associated with (1) age and (2) global cognitive function (Japanese MMSE) and executive function (Verbal Fluency Letter). Data was analyzed univariately by t-test and multivariately by cumulative logistic regression models controlling for age, gender, years of education, obesity, hypertension, diabetes, and dyslipidemia. RESULTS: Serum DHA levels decreased with increasing age (p = 0.04). Higher global cognitive function was associated with higher levels of serum EPA (p = 0.03) and DHA + EPA (p = 0.03) after controlling for confounders. CONCLUSIONS: Higher serum EPA and DHA + EPA levels were independently associated with better scores on global cognitive function among the oldest old, free from dementia. Longitudinal follow-up studies are warranted.
Keywords: Age Factors; Aged, 80 and over; Arachidonic Acid; Blood Chemical Analysis; Cognition; Cross-Sectional Studies; Educational Status; Fatty Acids, Omega-3; Female; Humans; Japan; Logistic Models; Male; Mental Status Schedule; Obesity; Prospective Studies; Sex Factors

Astrocytes release HspB1 in response to amyloid-β exposure in vitro. - Nafar, Firoozeh; Williams, J Bradley; Mearow, Karen M (J Alzheimers Dis, 2016)
Although heat shock proteins are thought to function primarily as intracellular chaperones, the release and potential extracellular functions of heat shock proteins have been the focus of an increasing number of studies. Our particular interest is HspB1 (Hsp25/27) and as astrocytes are an in vivo source of HspB1 it is a reasonable possibility they could release HspB1 in response to local stresses. Using primary cultures of rat cortical astrocytes, we investigated the extracellular release of HspB1 with exposure to amyloid-β (Aβ). In order to assess potential mechanisms of release, we cotreated the cells with compounds that can modulate protein secretion including Brefeldin A, Methyl β-cyclodextrin, and MAP kinase inhibitors. Exposure to Aβ (0.1, 1.0, 2.0 μM) for 24-48 h resulted in a selective release of HspB1 that was insensitive to BFA treatment; none of the other inhibitors had any detectable influence. Protease protection assays indicated that some of the released HspB1 was associated with a membrane bound fraction, and analysis of exosomal preparations indicated the presence of HspB1 in exosomes. Finally, immunoprecipitation experiments demonstrated that the extracellular HspB1 was able to interact with extracellular Aβ. In summary, Aβ can stimulate release of HspB1 from astrocytes, this release is insensitive to Golgi or lipid raft disruption, and HspB1 can be found either free in the medium or associated with exosomes. This release suggests that there is a potential for extracellular HspB1 to be able to bind and sequester extracellular Aβ.
Keywords: Amyloid beta-Peptides; Animals; Astrocytes; Cells, Cultured; HSP27 Heat-Shock Proteins; Protein Transport; Rats

Attitudes and Perceptions of Research in Aging and Dementia in an Urban Minority Population. - Neugroschl, Judith; Sewell, Margaret; De La Fuente, Angelica; Umpierre, Mari; Luo, Xiaodong; Sano, Mary (J Alzheimers Dis, 2016)
In dementia trials, minority participation is low. We assessed attitudes toward research in a community based urban poor minority sample of elderly adults attending senior center talks using the 7-item Research Attitudes Questionnaire (RAQ). Presentations on cognitive aging were given at senior centers, and 123 attendees completed the RAQ-7. On trust and safety questions, a significant minority (42-48%) responded neutrally or negatively. Encouragingly, on questions concerning the importance of research, 72-81% answered positively. More work can be done to capitalize on these findings to engage and foster trust, and this can be a focus of outreach.

Better Objective Sleep Quality in Older Adults with High Subjective Memory Decline. - Cavuoto, Marina G; Ong, Ben; Pike, Kerryn E; Nicholas, Christian L; Bei, Bei; Kinsella, Glynda J (J Alzheimers Dis, 2016)
BACKGROUND: Sleep disturbance is implicated in memory function across normal aging and neurodegenerative disease. Furthermore, there is mounting evidence to suggest that high levels of subjective memory decline (SMD) may signal very early neurodegenerative changes associated with Alzheimer's disease (AD). This view prompts research examining the relationship between SMD and other risk factors for cognitive decline, including sleep disturbance. OBJECTIVE: To determine whether objective and subjective indices of sleep predict SMD in older adults. METHODS: 181 community-based older adults were divided into groups of high and low SMD based on their responses to the Memory Assessment Complaint Questionnaire (MAC-Q). They undertook two weeks of objective sleep monitoring (actigraphy), and completed a subjective sleep quality assessment using the Pittsburgh Sleep Quality Index. RESULTS: Hierarchical logistic regression indicated that after controlling for demographics and mood, objective sleep quality predicted high SMD group status (ΔNagelkerke R2 = 0.07, χ2 = 9.80 (3), p = 0.020), while subjective sleep quality did not. Contrary to expectation, however, less sleep disruption predicted high SMD. CONCLUSION: These unexpected results may suggest a non-linear trajectory between sleep and memory decline in aging. The findings are discussed in relation to previous research, which taken together, may indicate compensatory sleep patterns of reduced sleep disruption in people with high levels of SMD. These preliminary findings suggest the utility of including analysis of sleep behavior in further longitudinal research of this at-risk group of older people.

Biomarkers Differentiating Dementia with Lewy Bodies from Other Dementias: A Meta-Analysis. - Mishima, Aki; Nihashi, Takashi; Ando, Yoshio; Kawai, Hisashi; Kato, Takashi; Ito, Kengo; Terasawa, Teruhiko (J Alzheimers Dis, 2016)
BACKGROUND: Several nuclear imaging and cerebrospinal fluid (CSF) biomarkers are under investigation, aimed at facilitating the differential diagnosis of dementias. OBJECTIVE: To quantitatively synthesize data on test performance in differentiating dementia with Lewy bodies (DLB) from other dementias. METHODS: We searched PubMed (January 2000- March 2015) for English-language publications that assessed a selected set of five imaging and three CSF biomarkers for this purpose. We meta-analyzed measures of agreement between biomarker results and clinical diagnosis. RESULTS: Forty-five publications were eligible. The majority of evidence was based on studies that enrolled representative disease populations. For differentiating between DLB and Alzheimer's disease (AD) or other dementias, metaiodobenzylguanidine scintigraphy and dopamine transporter (DAT) single photon emission computed tomography (SPECT) showed, respectively, excellent (summary kappa = 0.85; 95% confidence interval [95% CI], 0.74-0.96) and good (summary kappa = 0.71; 95% CI, 0.43-0.99) agreement. Metaiodobenzylguanidine scintigraphy appeared superior to fluorodeoxyglucose- positron emission tomography (summary kappa = 0.53; 95% CI, 0.36-0.69) and cerebral blood flow SPECT (summary kappa = 0.40; 95% CI, 0.33-0.47). For differentiating DLB from AD, CSF t-tau levels (summary kappa = 0.68; 95% CI, 0.55-0.82) performed comparably to metaiodobenzylguanidine scintigraphy and DAT SPECT. Sparse direct comparative evidence failed to corroborate these indirect comparisons. CONCLUSION: Metaiodobenzylguanidine scintigraphy and DAT SPECT are highly concordant with clinical diagnosis in differentiating DLB from other dementias. However, given the limitations in the study design, the applicability of these results to real-world differential diagnosis remains unclear. Prospective studies targeting patients with atypical presentations that adopt gold standard tests would reliably estimate the true test performance of these promising biomarkers.
Keywords: Biomarkers; Dementia; Diagnosis, Differential; Humans; Lewy Bodies; PubMed; Radionuclide Imaging; Retrospective Studies

Breakdown of the Cerebrovasculature and Blood-Brain Barrier: A Mechanistic Link Between Diabetes Mellitus and Alzheimer's Disease. - Goldwaser, Eric L; Acharya, Nimish K; Sarkar, Abhirup; Godsey, George; Nagele, Robert G (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) and diabetes mellitus (DM) are among the most pervasive and devastating disorders that afflict people throughout the world. Although typically associated with older demographics, recent epidemiologic studies have reported parallel trends in decreasing age of onset and increasing incidence of these conditions. Promising research continues to implicate the cerebrovasculature and blood-brain barrier (BBB) as playing key roles in AD pathoetiology. Similarly, complications accompanying DM, such as diabetic nephropathy/retinopathy, cardiovascular disease, and stroke, have been rooted in vascular compromise. Not surprisingly, DM is now considered a major risk factor for AD. The purpose of this review is to highlight investigations into the role of the cerebrovasculature in the development and progression of AD. We give particular attention to studies on humans and a variety of animal model systems that have demonstrated a link between BBB dysfunction and pathological changes in the brain consistent with aging and AD. Together, these studies suggest that the vascular complications associated with chronic, poorly managed DM can lead to subclinical BBB breakdown that precedes and drives the pathological changes progressing to symptomatic AD, providing a common mechanistic thread connecting these two disorders. Furthermore, this emphasizes the need to focus on the vasculature as a potential therapeutic target with the intent of limiting BBB breakdown involved in disease initiation and progression. In conclusion, AD may be more than just an associated comorbidity of DM, and instead another manifestation of the underlying vascular pathology that is common to both.

Cerebral Small Vessel Disease and Motoric Cognitive Risk Syndrome: Results from the Kerala-Einstein Study. - Wang, Nan; Allali, Gilles; Kesavadas, Chandrasekharan; Noone, Mohan L; Pradeep, Vayyattu G; Blumen, Helena M; Verghese, Joe (J Alzheimers Dis, 2016)
BACKGROUND: The contribution of cerebral small vessel disease to cognitive decline, especially in non-Caucasian populations, is not well established. OBJECTIVE: We examined the relationship between cerebral small vessel disease and motoric cognitive risk syndrome (MCR), a recently described pre-dementia syndrome, in Indian seniors. METHODS: 139 participants (mean age 66.6 ± 5.4 y, 33.1% female) participating in the Kerala-Einstein study in Southern India were examined in a cross-sectional study. The presence of cerebral small vessel disease (lacunar infarcts and cerebral microbleeds (CMB)) and white matter hyperintensities on MRI was ascertained by raters blinded to clinical information. MCR was defined by the presence of cognitive complaints and slow gait in older adults without dementia or mobility disability. RESULTS: Thirty-eight (27.3%) participants met MCR criteria. The overall prevalence of lacunar infarcts and CMB was 49.6% and 9.4% , respectively. Lacunar infarcts in the frontal lobe, but no other brain regions, were associated with MCR even after adjusting for vascular risk factors and presence of white matter hyperintensities (adjusted Odds Ratio (aOR): 4.67, 95% CI: 1.69-12.94). Frontal lacunar infarcts were associated with slow gait (aOR: 3.98, 95% CI: 1.46-10.79) and poor performance on memory test (β: -1.24, 95% CI: -2.42 to -0.05), but not with cognitive complaints or non-memory tests. No association of CMB was found with MCR, individual MCR criterion or cognitive tests. CONCLUSIONS: Frontal lacunar infarcts are associated with MCR in Indian seniors, perhaps, by contributing to slow gait and poor memory function.
Keywords: Aged; Brain; Cerebral Small Vessel Diseases; Cognition Disorders; Female; Humans; Image Processing, Computer-Assisted; India; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Risk Factors; Stroke, Lacunar; White Matter

Cerebrospinal Fluid Anti-Amyloid-β Autoantibodies and Amyloid PET in Cerebral Amyloid Angiopathy-Related Inflammation. - Carmona-Iragui, María; Fernández-Arcos, Ana; Alcolea, Daniel; Piazza, Fabrizio; Morenas-Rodriguez, Estrella; Antón-Aguirre, Sofía; Sala, Isabel; Clarimón, Jordi; Dols-Icardo, Oriol; Camacho, Valle; Sampedro, Frederic; Munuera, Josep; et al. (J Alzheimers Dis, 2016)
We report a biomarker and genetic evaluation of four patients with cerebral amyloid angiopathy-related inflammation (CAA-ri) treated with corticosteroids. Patients presented with focal symptomatology and cognitive impairment. MRI revealed cortical microbleeds and asymmetrical hyperintense white matter lesions (WML). Cerebrospinal fluid (CSF) biomarker analyses showed increased anti-Aβ autoantibodies, t-Tau, and p-Tau and decreased Aβ40 and Aβ42. After treatment, focal symptomatology disappeared, and WML and anti-Aβ autoantibodies decreased. The APOEɛ4 allele was overrepresented. Florbetapir-PET showed cortical deposition with lower retention in swollen areas. In the case of suspected CAA-ri, both CSF anti-Aβ autoantibodies levels and Florbetapir-PET could provide highly useful data to guide the correct diagnosis.
Keywords: Aged; Amyloid beta-Peptides; Aniline Compounds; Apolipoproteins E; Autoantibodies; Cerebral Amyloid Angiopathy; Ethylene Glycols; Female; Humans; Magnetic Resonance Imaging; Male; Meningoencephalitis; Peptide Fragments; Positron-Emission Tomography; Statistics, Nonparametric; tau Proteins

Changes in Brain Volume with Bapineuzumab in Mild to Moderate Alzheimer's Disease. - Novak, Gerald; Fox, Nick; Clegg, Shona; Nielsen, Casper; Einstein, Steven; Lu, Yuan; Tudor, Iulia Cristina; Gregg, Keith; Di, Jianing; Collins, Peter; Wyman, Bradley T; Yuen, Eric; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Bapineuzumab, an anti-amyloid-β monoclonal antibody, was evaluated in two placebo-controlled trials in APOE*ɛ4 carriers and noncarriers, respectively, with Alzheimer's disease. OBJECTIVES: A volumetric magnetic resonance imaging substudy was performed to determine if bapineuzumab altered brain volume rate of change. METHODS: Bapineuzumab dosages included 0.5 mg/kg in carriers and 0.5 or 1.0 mg/kg in noncarriers, every 13 weeks for 78 weeks. Volumetric outcomes included annualized brain, ventricular, and mean hippocampal boundary shift integrals (BBSI; VBSI; HBSI) up to Week 71. Treatment differences were estimated using mixed models for repeated measures. RESULTS: For BBSI and HBSI, there were no significant treatment-related differences within either study, but, compared to pooled carriers and noncarriers receiving placebo, noncarriers receiving1.0 mg/kg bapineuzumab had greater increases in these measures. Bapineuzumab-treated patients showed significantly greater VBSI rates compared with placebo for 0.5 mg/kg in carriers and 1.0 mg/kg (but not 0.5 mg/kg) in noncarriers. CONCLUSIONS: Bapineuzumab produced an increase in ventricular volume compared with placebo. Etiology for this increase is unclear but may be related to amyloid-β clearance or its consequences.
Keywords: Aged; Alzheimer Disease; Antibodies, Monoclonal, Humanized; Apolipoprotein E4; Brain; Double-Blind Method; Female; Heterozygote; Humans; Least-Squares Analysis; Magnetic Resonance Imaging; Male; Nootropic Agents; Organ Size; Severity of Illness Index; Treatment Outcome

Changes in Neural Connectivity and Memory Following a Yoga Intervention for Older Adults: A Pilot Study. - Eyre, Harris A; Acevedo, Bianca; Yang, Hongyu; Siddarth, Prabha; Van Dyk, Kathleen; Ercoli, Linda; Leaver, Amber M; Cyr, Natalie St; Narr, Katherine; Baune, Bernhard T; Khalsa, Dharma S; Lavretsky, Helen (J Alzheimers Dis, 2016)
BACKGROUND: No study has explored the effect of yoga on cognitive decline and resting-state functional connectivity. OBJECTIVES: This study explored the relationship between performance on memory tests and resting-state functional connectivity before and after a yoga intervention versus active control for subjects with mild cognitive impairment (MCI). METHODS: Participants ( ≥ 55 y) with MCI were randomized to receive a yoga intervention or active "gold-standard" control (i.e., memory enhancement training (MET)) for 12 weeks. Resting-state functional magnetic resonance imaging was used to map correlations between brain networks and memory performance changes over time. Default mode networks (DMN), language and superior parietal networks were chosen as networks of interest to analyze the association with changes in verbal and visuospatial memory performance. RESULTS: Fourteen yoga and 11 MET participants completed the study. The yoga group demonstrated a statistically significant improvement in depression and visuospatial memory. We observed improved verbal memory performance correlated with increased connectivity between the DMN and frontal medial cortex, pregenual anterior cingulate cortex, right middle frontal cortex, posterior cingulate cortex, and left lateral occipital cortex. Improved verbal memory performance positively correlated with increased connectivity between the language processing network and the left inferior frontal gyrus. Improved visuospatial memory performance correlated inversely with connectivity between the superior parietal network and the medial parietal cortex. CONCLUSION: Yoga may be as effective as MET in improving functional connectivity in relation to verbal memory performance. These findings should be confirmed in larger prospective studies.

Chronic Cerebral Hypoperfusion Accelerates Alzheimer's Disease Pathology with Cerebrovascular Remodeling in a Novel Mouse Model. - Zhai, Yun; Yamashita, Toru; Nakano, Yumiko; Sun, Zhuoran; Shang, Jingwei; Feng, Tian; Morihara, Ryuta; Fukui, Yusuke; Ohta, Yasuyuki; Hishikawa, Nozomi; Abe, Koji (J Alzheimers Dis, 2016)
Recently, aging societies have been showing an increasingly strong relationship between Alzheimer's disease (AD) and chronic cerebral hypoperfusion (HP). In the present study, we created a new mouse model for AD with HP, and investigated its clinical and pathological characteristics. Alzheimer's disease transgenic mice (APP23) were subjected to bilateral common carotid arteries stenosis with ameroid constrictors for slowly progressive cerebral HP. In contrast to simple APP23 mice, cerebral HP exacerbated motor and cognitive dysfunctions with white matter lesions and meningo-parenchymal amyloid-β (Aβ) burdens. Strong cerebrovascular inflammation and severe amyloid angiopathy with cerebrovascular remodeling were also observed in APP23 + HP mouse brains. An acetylcholinesterase inhibitor galantamine improved such clinical dysfunctions, retrieved above neuropathological characteristics, and enhanced nicotinic acetylcholine receptor (nAChR)-binding activity. The present study demonstrates that chronic cerebral HP enhanced cognitive/motor dysfunctions with parenchymal/cerebrovascular Aβ accumulation and cerebrovascular remodeling. These neuropathological abnormalities were greatly ameliorated by galantamine treatment associated with nAChR-mediated neuroprotection by allosterically potentiating ligand action.

Chronic Traumatic Encephalopathy Presenting as Alzheimer's Disease in a Retired Soccer Player. - Grinberg, Lea T; Anghinah, Renato; Nascimento, Camila Fernandes; Amaro, Edson; Leite, Renata P; Martin, Maria da Graça M; Naslavsky, Michel S; Takada, Leonel T; Filho, Wilson Jacob; Pasqualucci, Carlos A; Nitrini, Ricardo (J Alzheimers Dis, 2016)
The relationship between soccer and chronic traumatic encephalopathy (CTE) is not well established. We report clinicopathological correlations in an 83-year-old retired center-back soccer player, with no history of concussion, manifesting typical Alzheimer-type dementia. Examination revealed mixed pathology including widespread CTE, moderate Alzheimer's disease, hippocampal sclerosis, and TDP-43 proteinopathy. This case adds to a few CTE cases described in soccer players. Furthermore, it corroborates that CTE may present clinically as typical Alzheimer-type dementia. Further studies investigating the extent to which soccer is a risk for CTE are needed.

Cigarette Smoke-Induced Alterations in Frontal White Matter Lipid Profiles Demonstrated by MALDI-Imaging Mass Spectrometry: Relevance to Alzheimer's Disease. - Nunez, Kavin; Kay, Jared; Krotow, Alexander; Tong, Ming; Agarwal, Amit R; Cadenas, Enrique; de la Monte, Suzanne M (J Alzheimers Dis, 2016)
BACKGROUND: Meta-analysis has shown that smokers have significantly increased risks for Alzheimer's disease (AD), and neuroimaging studies showed that smoking alters white matter (WM) structural integrity. OBJECTIVE: Herein, we characterize the effects of cigarette smoke (CS) exposures and withdrawal on WM myelin lipid composition using matrix assisted laser desorption and ionization-imaging mass spectrometry (MALDI-IMS). METHODS: Young adult male A/J mice were exposed to air (8 weeks; A8), CS (4 or 8 weeks; CS4, CS8), or CS8 followed by 2 weeks recovery (CS8 + R). Frontal lobe WM was examined for indices of lipid and protein oxidation and lipid profile alterations by MALDI-IMS. Lipid ions were identified by MS/MS with the LIPID MAPS prediction tools database. Inter-group comparisons were made using principal component analysis and R-generated heatmap. RESULTS: CS increased lipid and protein adducts such that higher levels were present in CS8 compared with CS4 samples. CS8 + R reversed CS8 effects and normalized the levels of oxidative stress. MALDI-IMS demonstrated striking CS-associated alterations in WM lipid profiles characterized by either reductions or increases in phospholipids (phosphatidylinositol, phosphatidylserine, phosphatidylcholine, or phosphatidylethanolamine) and sphingolipids (sulfatides), and partial reversal of CS's inhibitory effects with recovery. The heatmap hierarchical dendrogram and PCA distinguished CS exposure, duration, and withdrawal effects on WM lipid profiles. CONCLUSION: CS-mediated WM degeneration is associated with lipid peroxidation, protein oxidative injury, and alterations in myelin lipid composition, including shifts in phospholipids and sphingolipids needed for membrane integrity, plasticity, and intracellular signaling. Future goals are to delineate WM abnormalities in AD using MALDI-IMS, and couple the findings with MRI-mass spectroscopy to improve in vivo diagnostics and early detection of brain biochemical responses to treatment.
Keywords: Aldehydes; Analysis of Variance; Animals; Dinoprost; Disease Models, Animal; Enzyme-Linked Immunosorbent Assay; Frontal Lobe; Lipid Metabolism; Male; Mice; Phospholipids; Principal Component Analysis; Protein Carbonylation; Smoking; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Substance Withdrawal Syndrome; White Matter

Classification of Neuropsychiatric Symptoms Requiring Antipsychotic Treatment in Patients with Alzheimer's Disease: Analysis of the CATIE-AD Study. - Nagata, Tomoyuki; Shinagawa, Shunichiro; Nakajima, Shinichiro; Plitman, Eric; Mihashi, Yukiko; Hayashi, Shogo; Mimura, Masaru; Nakayama, Kazuhiko (J Alzheimers Dis, 2016)
BACKGROUND: The Neuropsychiatric Inventory (NPI) comprises 12 items, which were conventionally determined by psychopathological symptoms of patients with dementia. The clinical rating scales with structured questionnaires have been useful to evaluate neuropsychiatric symptoms (NPSs) of patients with dementia over the past twenty year. OBJECTIVE: The aim of this study was to classify the conventional NPSs in patients with Alzheimer's disease (AD) requiring antipsychotic treatment for their NPSs into distinct clusters to simplify assessment of these numerous symptoms. METHODS: Twelve items scores (product of severity and frequency of each symptom) in the NPI taken from the baseline visit were classified into subgroups by principle component analysis using data from 421 outpatients with AD enrolled in the Clinical Antipsychotic Trials of Intervention Effectiveness-Alzheimer's Disease (CATIE-AD) Phase 1. Chi square tests were conducted to examine the co-occurrence of the subgroups. RESULTS: We found four distinct clusters: aggressiveness (agitation and irritabilities), apathy and eating problems (apathy and appetite/eating disturbance), psychosis (delusions and hallucinations), and emotion and disinhibition (depression, euphoria, and disinhibition). Anxiety, aberrant motor behavior, and sleep disturbance were not included by these clusters. Apathy and eating problems, and emotion and disinhibition co-occurred (p = 0.002), whereas aggressiveness and psychosis occurred independent of the other clusters. CONCLUSIONS: Four distinct category clusters were identified from NPSs in patients with AD requiring antipsychotic treatment. Future studies should investigate psychosocial backgrounds or risk factors of each distinct cluster, in addition to their longitudinal course over treatment intervention.
Keywords: Aged; Aged, 80 and over; Aggression; Alzheimer Disease; Antipsychotic Agents; Apathy; Cluster Analysis; Female; Humans; Male; Psychiatric Status Rating Scales; Psychomotor Agitation; Psychotic Disorders; Retrospective Studies; Severity of Illness Index

Clinical and Demographic Factors Associated with the Cognitive and Emotional Efficacy of Regular Musical Activities in Dementia. - Särkämö, Teppo; Laitinen, Sari; Numminen, Ava; Kurki, Merja; Johnson, Julene K; Rantanen, Pekka (J Alzheimers Dis, 2016)
Recent evidence suggests that music-based interventions can be beneficial in maintaining cognitive, emotional, and social functioning in persons with dementia (PWDs). Our aim was to determine how clinical, demographic, and musical background factors influence the cognitive and emotional efficacy of caregiver-implemented musical activities in PWDs. In a randomized controlled trial, 89 PWD-caregiver dyads received a 10-week music coaching intervention involving either singing or music listening or standard care. Extensive neuropsychological testing and mood and quality of life (QoL) measures were performed before and after the intervention (n = 84) and six months later (n = 74). The potential effects of six key background variables (dementia etiology and severity, age, care situation, singing/instrument playing background) on the outcome of the intervention were assessed. Singing was beneficial especially in improving working memory in PWDs with mild dementia and in maintaining executive function and orientation in younger PWDs. Music listening was beneficial in supporting general cognition, working memory, and QoL especially in PWDs with moderate dementia not caused by Alzheimer's disease (AD) who were in institutional care. Both music interventions alleviated depression especially in PWDs with mild dementia and AD. The musical background of the PWD did not influence the efficacy of the music interventions. Our findings suggest that clinical and demographic factors can influence the cognitive and emotional efficacy of caregiver-implemented musical activities and are, therefore, recommended to take into account when applying and developing the intervention to achieve the greatest benefit.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Caregivers; Case-Control Studies; Cognition Disorders; Dementia; Executive Function; Female; Follow-Up Studies; Humans; Male; Memory, Short-Term; Middle Aged; Mood Disorders; Music Therapy; Neuropsychological Tests; Orientation; Outcome Assessment (Health Care); Psychiatric Status Rating Scales; Quality of Life

Clinical Conversion or Reversion of Mild Cognitive Impairment in Community versus Hospital Based Studies: GDEMCIS (Gwangju Dementia and Mild Cognitive Impairment Study) and CREDOS (Clinical Research Center for Dementia of South Korea). - Roh, Hyun Woong; Hong, Chang Hyung; Lee, Yunhwan; Lee, Kang Soo; Chang, Ki Jung; Kang, Dae Ryong; Lee, Jung-Dong; Choi, Seong Hye; Kim, Seong Yoon; Na, Duk L; Seo, Sang Won; Kim, Doh Kwan; et al. (J Alzheimers Dis, 2016)
BACKGROUND: In keeping with increasing interest in dementia, few recent studies suggest that clinical course of mild cognitive impairment vary across different studies with hospital-based subjects showing higher rates of conversion than community-based subjects. OBJECTIVE: The main objective of the present study was to assess whether the clinical conversion or reversion rates differ according to recruitment source. METHODS: The baseline study subjects comprised of patients who were diagnosed with mild cognitive impairment in community-based GDEMCIS or hospital-based CREDOS. The two studies had nearly the same protocol and were performed over a similar period. We used propensity score matching for baseline comparability. After that, Cox proportional hazards regression analyses were conducted to estimate the hazard ratios and 95% confidence intervals of clinical conversion or reversion. RESULTS: Based on 89 GDEMCIS subjects, 1 : 4 propensity score matching was conducted and 356 CREDOS subjects were selected. After adjusting for covariates including baseline demographics, comorbidity, depression, disability, and neuropsychological result, Cox proportional hazard regression analysis for time to clinical conversion indicated that recruitment from hospital-based CREDOS exhibited hazard ratio of 2.13 (95% CI, 1.08-4.21), as compared to recruitment from community-based GDEMCIS. Similarly, Cox proportional hazard regression analysis for time to reversion indicated that recruitment from hospital-based CREDOS exhibited hazard ratio of 0.34 (95% CI, 0.20-0.59), as compared to recruitment from community-based GDEMCIS. CONCLUSION: The present study demonstrated that even after the matching process and adjustments for baseline covariates, recruitment source greatly affected the course of mild cognitive impairment.

Cognitive Impairment after Mild Stroke: Development and Validation of the SIGNAL2 Risk Score. - Kandiah, Nagaendran; Chander, Russell Jude; Lin, Xuling; Ng, Aloysius; Poh, Yen Yeong; Cheong, Chin Yee; Cenina, Alvin Rae; Assam, Pryseley Nkouibert (J Alzheimers Dis, 2016)
BACKGROUND: Post stroke cognitive impairment (PSCI), an important complication of strokes, has numerous risk factors. A scale adequately classifying risk of cognitive impairment 3-6 months after mild stroke will be useful for clinicians. OBJECTIVE: To develop a risk score based on clinical and neuroimaging variables that will be useful in identifying mild ischemic stroke patients at high risk for PSCI. METHODS: The risk score development cohort comprised of a retrospective dataset of 209 mild stroke patients with MRI confirmed infarcts, without pre-stroke cognitive impairment, and evaluated within 6 months post-stroke for PSCI. Logistic regression identified factors predictive of PSCI and a risk score was developed based on regression coefficients. The risk score was checked for stability using 10-fold cross-validation and validated in an independent prospective cohort of 185 ischemic mild stroke patients. RESULTS: Within 6 months post-stroke, 37.32% developed PSCI in the retrospective dataset. A 15-point risk score based on age, education, acute cortical infarcts, white matter hyperintensity, chronic lacunes, global cortical atrophy, and intracranial large vessel stenosis was highly predictive of PSCI with an AUC of 0.829. 10.11% with low scores, 52.69% with moderate scores, and 74.07% with high scores developed PSCI. In the prospective validation cohort, the model had an AUC of 0.776, and exhibited similar accuracy and stability statistics at both 6 and 12 months. CONCLUSION: The seven item risk score adequately identified mild stroke patients who are at an increased risk of developing PSCI.
Keywords: Aged; Aging; Area Under Curve; Brain; Brain Ischemia; Cognition Disorders; Constriction, Pathologic; Educational Status; Female; Follow-Up Studies; Humans; Logistic Models; Male; Middle Aged; Prospective Studies; Retrospective Studies; Risk; Severity of Illness Index; Stroke; White Matter

Cohort Effects in the Prevalence and Survival of People with Dementia in a Rural Area in Northern Sweden. - Wimo, Anders; Sjölund, Britt-Marie; Sköldunger, Anders; Qiu, Chengxuan; Klarin, Inga; Nordberg, Gunilla; von Strauss, Eva (J Alzheimers Dis, 2016)
BACKGROUND: Recent studies suggest that trends in cardiovascular risk may result in a decrease in age-specific prevalence of dementia. Studies in rural areas are rare. OBJECTIVES: To study cohort effects in dementia prevalence and survival of people with dementia in a Swedish rural area. METHODS: Participants were from the 1995-1998 Nordanstig Project (NP) (n = 303) and the 2001-2003 Swedish National study on Aging and Care in Nordanstig (SNAC-N) (n = 384). Overall 6-year dementia prevalence and mortality in NP and SNAC-N were compared for people 78 years and older. Logistic regression analyses were used to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for dementia occurrence using the NP study population as the reference group. Cox regression models were used to analyze time to death. RESULTS: The crude prevalence of dementia was 21.8% in NP and 17.4% in SNAC-N. When the NP cohort was used as the reference group, the age- and gender-adjusted OR of dementia was 0.71 (95% CI 0.48-1.04) in SNAC-N; the OR was 0.47 (0.24-0.90) for men and 0.88 (0.54-1.44) for women. In the extended model, the OR of dementia was significantly lower in SNAC-N than in the NP cohort as a whole (0.63; 0.39-0.99) and in men (0.34; 0.15-0.79), but not in women (0.81; 0.46-1.44). The Cox regression models indicated that the hazard ratio of dying was lower in the SNAC-N than NP population. CONCLUSIONS: Trends toward a lower prevalence of dementia in high-income countries seem to be evident in this Swedish rural area, at least in men.
Keywords: Aged; Aged, 80 and over; Aging; Cohort Effect; Dementia; Female; Humans; Male; Prevalence; Risk Factors; Rural Population; Sex Factors; Survival Rate; Sweden

Comorbid Mild Cognitive Impairment and Depressive Symptoms Predict Future Dementia in Community Older Adults: A 24-Month Follow-Up Longitudinal Study. - Makizako, Hyuma; Shimada, Hiroyuki; Doi, Takehiko; Tsutsumimoto, Kota; Hotta, Ryo; Nakakubo, Sho; Makino, Keitaro; Suzuki, Takao (J Alzheimers Dis, 2016)
BACKGROUND: Older adults with mild cognitive impairment (MCI) are non-demented, but demonstrate cognitive dysfunction, and have significantly higher risk of progressing to dementia. A better understanding of more sensitive risk factors, such as combination of cognitive and psychological status, for progression of MCI to dementia may be crucial for prevention of development of dementia. OBJECTIVE: To examine MCI, depressive symptoms, and comorbid MCI and depressive symptoms as risk factors for development of dementia. METHODS: A total of 3,663 community-dwelling older people were included in this prospective longitudinal study. MCI was determined by age- and education-adjusted objective cognitive impairment using computerized comprehensive cognitive measures including memory, attention/executive function, and processing speed. Depressive symptoms were measured using the 15-item Geriatric Depression Scale (GDS) and defined by a GDS score of 6 or more. RESULTS: During the 24-month follow-up period, 72 participants (2.0%) developed dementia. Baseline MCI was significantly associated with an increased risk of incident dementia (hazard ratio [HR], 3.2; 95% confidence interval [CI], 1.8-5.5) but depressive symptoms were not (2.0; 1.0-4.2) after adjusting for age, sex, education, prescribed medications, and walking speed. Participants with comorbid MCI and depressive symptoms at baseline had a higher risk of developing dementia (HR, 4.8; 2.3-10.5). CONCLUSION: Although MCI and depressive symptoms may be associated with increased risk for incident dementia independently, comorbid MCI and depressive symptoms have a significantly greater impact on dementia development among community-dwelling older adults.

Contribution of the Cholinergic System to Verbal Memory Performance in Mild Cognitive Impairment. - Peter, Jessica; Lahr, Jacob; Minkova, Lora; Lauer, Eliza; Grothe, Michel J; Teipel, Stefan; Köstering, Lena; Kaller, Christoph P; Heimbach, Bernhard; Hüll, Michael; Normann, Claus; Nissen, Christoph; et al. (J Alzheimers Dis, 2016)
Acetylcholine is critically involved in modulating learning and memory function, which both decline in neurodegeneration. It remains unclear to what extent structural and functional changes in the cholinergic system contribute to episodic memory dysfunction in mild cognitive impairment (MCI), in addition to hippocampal degeneration. A better understanding is critical, given that the cholinergic system is the main target of current symptomatic treatment in mild to moderate Alzheimer's disease. We simultaneously assessed the structural and functional integrity of the cholinergic system in 20 patients with MCI and 20 matched healthy controls and examined their effect on verbal episodic memory via multivariate regression analyses. Mediating effects of either cholinergic function or hippocampal volume on the relationship between cholinergic structure and episodic memory were computed. In MCI, a less intact structure and function of the cholinergic system was found. A smaller cholinergic structure was significantly correlated with a functionally more active cholinergic system in patients, but not in controls. This association was not modulated by age or disease severity, arguing against compensational processes. Further analyses indicated that neither functional nor structural changes in the cholinergic system influence verbal episodic memory at the MCI stage. In fact, those associations were fully mediated by hippocampal volume. Although the cholinergic system is structurally and functionally altered in MCI, episodic memory dysfunction results primarily from hippocampal neurodegeneration, which may explain the inefficiency of cholinergic treatment at this disease stage.

Copeptin, a Marker of Vasopressin, Predicts Vascular Dementia but not Alzheimer's Disease. - Nilsson, Erik D; Melander, Olle; Elmståhl, Sölve; Lethagen, Eva; Minthon, Lennart; Pihlsgård, Mats; Nägga, Katarina (J Alzheimers Dis, 2016)
BACKGROUND: Copeptin is a reliable surrogate marker for the neurohypophyseal hormone vasopressin. Elevated plasma level of copeptin has been associated with cardiovascular and metabolic disease risk. OBJECTIVE: To investigate the association between copeptin and risk of dementia. METHODS: In all, 18,240 individuals from Malmö, Sweden, were examined between 2002 and 2006 (mean age 69.3 years, 69.8% men). Incident cases of dementia until 31 December 2009 were identified by linkage with the Swedish National Patient Register. To validate the dementia diagnoses, medical records as well as laboratory and neuroimaging data were carefully reviewed. Baseline level of copeptin was measured in frozen plasma in: (1) all participants who were diagnosed with dementia during follow-up, (2) a random sample of 5100 individuals of the cohort. RESULTS: During a median follow-up of 4.2 years, there were 374 incident dementia cases (age range 60-83 years at baseline): 120 were classified as Alzheimer's disease (AD), 84 as vascular dementia (VaD), and 102 as mixed dementia. In logistic regressions adjusted for cardiovascular risk factors, baseline level of copeptin predicted incident VaD (Odds ratio (OR) 1.30 per 1 SD increase in log copeptin, 95% CI 1.03-1.64). Copeptin did not predict incidence of all-cause dementia (OR 1.05, 95% CI 0.94-1.18), AD (OR 0.97, 95% CI 0.79-1.18), or mixed dementia (OR 0.85, 95% CI 0.68-1.05). CONCLUSION: Elevated plasma level of copeptin is a risk marker for incident VaD, but not for incident AD. This suggests that the vasopressin hormonal system might be involved in the development of VaD.

Cortical Amyloid Burden Differences Across Empirically-Derived Mild Cognitive Impairment Subtypes and Interaction with APOE ɛ4 Genotype. - Bangen, Katherine J; Clark, Alexandra L; Werhane, Madeline; Edmonds, Emily C; Nation, Daniel A; Evangelista, Nicole; Libon, David J; Bondi, Mark W; Delano-Wood, Lisa (J Alzheimers Dis, 2016)
We examined cortical amyloid-β (Aβ) levels and interactions with apolipoprotein (APOE) ɛ4 genotype status across empirically-derived mild cognitive impairment (MCI) subgroups and cognitively normal older adults. Participants were 583 ADNI participants (444 MCI, 139 normal controls [NC]) with baseline florbetapir positron emission tomography (PET) amyloid imaging and neuropsychological testing. Of those with ADNI-defined MCI, a previous cluster analysis [1] classified 51% (n = 227) of the current sample as amnestic MCI, 8% (n = 37) as dysexecutive/mixed MCI, and 41% (n = 180) as cluster-derived normal (cognitively normal). Results demonstrated that the dysexecutive/mixed and amnestic MCI groups showed significantly greater levels of amyloid relative to the cluster-derived normal and NC groups who did not differ from each other. Additionally, 78% of the dysexecutive/mixed, 63% of the amnestic MCI, 42% of the cluster-derived normal, and 34% of the NC group exceeded the amyloid positivity threshold. Finally, a group by APOE genotype interaction demonstrated that APOE ɛ4 carriers within the amnestic MCI, cluster-derived normal, and NC groups showed significantly greater amyloid accumulation compared to non-carriers of their respective group. Such an interaction was not revealed within the dysexecutive/mixed MCI group which was characterized by both greater cognitive impairment and amyloid accumulation compared to the other participant groups. Our results from the ADNI cohort show considerable heterogeneity in Aβ across all groups studied, even within a group of robust NC participants. Findings suggest that conventional criteria for MCI may be susceptible to false positive diagnostic errors, and that onset of Aβ accumulation may occur earlier in APOE ɛ4 carriers compared to non-carriers.

Cost Related to Dementia in the Young and the Impact of Etiological Subtype on Cost. - Kandiah, Nagaendran; Wang, Vivian; Lin, Xuling; Nyu, Mei Mei; Lim, Linda; Ng, Adeline; Hameed, Shahul; Wee, Hwee Lin (J Alzheimers Dis, 2016)
BACKGROUND: Young onset dementia (YOD) presents in individuals who are economically productive and socially active. While the cost related to dementia in the elderly has been widely studied, the cost related to YOD is largely unknown. OBJECTIVE: To study the economic burden of community dwelling YOD in relation to late onset dementia (LOD) and cost of YOD based on etiology. METHODS: In this prospective cross-sectional study of 255 patients attending a tertiary neurology center, data on economic burden, clinical features, and caregiver burden were collected using structured financial questionnaire, standard cognitive and neuropsychiatric measures, and Zarit caregiver burden scale. Cost components were grouped into those relating to direct medical costs, direct non-medical costs, and those related to indirect costs. Cost was also categorized based on etiology of YOD. RESULTS: The mean age at symptom onset in the YOD and LOD cohort was 57.0 (SD 5.1) and 75.0 (SD 5.9) years, respectively. The median annual cost for patients with YOD was almost twice that of LOD (USD 15,815 versus USD 8,396). Indirect cost contributed heavily to cost related to YOD. Even when grouped by dementia etiology, YOD patients with Alzheimer's disease, frontotemporal dementia (FTD), and vascular dementia had higher cost compared to their elderly counterparts. Young onset FTD had the highest cost. 43.2% of YOD reported loss of employment due to dementia, which was significantly higher than that in LOD (2.4%). CONCLUSION: Patients with YOD have a high economic burden. Young patients with FTD have the highest cost followed by vascular dementia and Alzheimer's disease.
Keywords: Age of Onset; Aged; Cohort Studies; Costs and Cost Analysis; Cross-Sectional Studies; Dementia; Female; Humans; Independent Living; Male; Mental Disorders; Middle Aged; Perceptual Disorders; Prospective Studies; Psychiatric Status Rating Scales; Severity of Illness Index; Surveys and Questionnaires; Young Adult

A Decade of Cerebrospinal Fluid Biomarkers for Alzheimer's Disease in Belgium. - Somers, Charisse; Struyfs, Hanne; Goossens, Joery; Niemantsverdriet, Ellis; Luyckx, Jill; De Roeck, Naomi; De Roeck, Ellen; De Vil, Bart; Cras, Patrick; Martin, Jean-Jacques; De Deyn, Peter-Paul; Bjerke, Maria; et al. (J Alzheimers Dis, 2016)
During the past ten years, over 5,000 cerebrospinal fluid (CSF) samples were analyzed at the Reference Center for Biological Markers of Dementia (BIODEM), UAntwerp, for core Alzheimer's disease (AD) CSF biomarkers: amyloid-β peptide of 42 amino acids (Aβ1-42), total tau protein (T-tau), and tau phosphorylated at threonine 181 (P-tau181P). CSF biomarker analyses were performed using single-analyte ELISA kits. In-house validated cutoff values were applied: Aβ1-42 <638.5 pg/mL, T-tau >296.5 pg/mL, P-tau181P >56.5 pg/mL. A CSF biomarker profile was considered to be suggestive for AD if the CSF Aβ1-42 concentration was below the cutoff, in combination with T-tau and/or P-tau181P values above the cutoff (IWG2 criteria for AD). Biomarker analyses were requested for following clinical indications: 1) neurochemical confirmation of AD in case of clinical AD, 2) neurochemical confirmation of AD in case of doubt between AD and a non-AD dementia, 3) neurochemical diagnosis of prodromal AD in case of mild cognitive impairment, 4) neurochemical confirmation of AD in case of psychiatric symptoms (like depression, psychosis), or 5) other clinical indications. During these ten years, the number of yearly referred samples increased by 238% and clinical indications for referral showed a shift from neurochemical confirmation of AD in case of clinical AD to differential dementia diagnosis in case of doubt between AD and a non-AD dementia. Four percent of the patients also had a postmortem neuropathological examination. Together, these biomarker data were the basis for several research papers, and significantly contributed to the validation of these biomarkers in autopsy-confirmed subjects.

Depressive Symptoms and Small Hippocampal Volume Accelerate the Progression to Dementia from Mild Cognitive Impairment. - Chung, Jun Ku; Plitman, Eric; Nakajima, Shinichiro; Chakravarty, M Mallar; Caravaggio, Fernando; Takeuchi, Hiroyoshi; Gerretsen, Philip; Iwata, Yusuke; Patel, Raihaan; Mulsant, Benoit H; Graff-Guerrero, Ariel (J Alzheimers Dis, 2016)
Previous studies have highlighted that decreased hippocampal volume, an early neural correlate of dementia, is commonly observed in patients with mild cognitive impairment (MCI). However, it is unclear whether neurodegenerative and resultant clinical trajectories are accelerated in MCI patients with concomitant depressive symptoms, leading to a faster conversion to dementia stages than those who are not depressed. No longitudinal study has investigated whether depressed amnestic MCI (DEP+aMCI) patients show an earlier onset of progression to dementia than non-depressed amnestic MCI (DEP-aMCI) patients and whether progressive hippocampal volume reductions are related in the conversion process. Using data from Alzheimer's Disease Neuroimaging Initiative, we examined 2-year follow-up data from 38 DEP+aMCI patients and 38 matched DEP-aMCI patients and compared their ages of conversion from aMCI to AD and trajectories of progressive hippocampal volume changes. DEP+ and DEP- patients were defined as having baseline Geriatric Depression Scale scores of 5 or above and 0, respectively. DEP+ converters showed earlier ages of conversion to dementia (p = 0.009) and greater left hippocampal volume loss than both DEP- converters and DEP+ non-converters over the 2-year period (p = 0.003, p = 0.001, respectively). These findings could not be explained by changes in total brain volume, differences in their clinical symptoms of dementia, daily functioning, or apolipoprotein E4 genotypes. No difference in conversion rate to dementia or progressive hippocampal volume change was found between DEP+ patients and DEP-patients, which suggested depressive symptoms themselves may not lead to progression of dementia from MCI. In conclusion, there is a synergistic effect of depressive symptoms and smaller left hippocampal volume in MCI patients that accelerates conversion to dementia.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Dementia; Depression; Disease Progression; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Psychiatric Status Rating Scales

Diagnostic Impact of Cerebrospinal Fluid Biomarker (Pre-)Analytical Variability in Alzheimer's Disease. - Niemantsverdriet, Ellis; Goossens, Joery; Struyfs, Hanne; Martin, Jean-Jacques; Goeman, Johan; De Deyn, Peter Paul; Vanderstichele, Hugo; Engelborghs, Sebastiaan (J Alzheimers Dis, 2016)
Intra- and inter-laboratory variability of cerebrospinal fluid (CSF) biomarker analyses remains an important issue. We investigated the clinical-diagnostic impact of CSF biomarker concentration shifts in mild cognitive impairment (MCI) and autopsy-confirmed Alzheimer's disease (AD) dementia patients. MCI patients (n = 85), autopsy-confirmed AD dementia patients (n = 72), and cognitively healthy controls (n = 100) were included in this prospective, longitudinal study. AD dementia patients were followed up until death, and controls were included from 1992 until 2003. In-house validated cutoff values of biomarkers were applied: Aβ1-42 <638.5 pg/mL, T-tau>296.5 pg/mL, P-tau(181P) >56.5 pg/mL. Both increments and decrements (from ± 5% to ± 40% ) were added to the true (=observed) CSF biomarker values, imitating the anticipated differences in biomarker concentrations. Within certain limits, the clinical diagnostic performance of AD CSF biomarkers remains largely unchanged and clinical diagnostic accuracy deviated less than 8.2% from the reference when concentration shifts ranging between -20% and +20% were added to one of the three CSF biomarkers in MCI and autopsy-confirmed AD patients. Notwithstanding the fact that (pre- and post-)analytical parameters can affect the clinical classification, the present exploratory study provides evidence that for a specific context of use, the impact on clinical accuracy of biomarker concentration shifts might be lower than originally expected. In conclusion, induced shifts of ±20% in only one of the three biomarkers has limited impact on the clinical accuracy of AD CSF biomarkers in MCI and autopsy-confirmed AD patients when using the IWG-2 criteria.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Autopsy; Cognitive Dysfunction; Enzyme-Linked Immunosorbent Assay; Exercise; Female; Follow-Up Studies; Humans; Male; Middle Aged; Peptide Fragments; Psychiatric Status Rating Scales; Retrospective Studies; Statistics, Nonparametric; tau Proteins

Differential Diagnosis of Dementia with High Levels of Cerebrospinal Fluid Tau Protein. - Grangeon, Lou; Paquet, Claire; Bombois, Stephanie; Quillard-Muraine, Muriel; Martinaud, Olivier; Bourre, Bertrand; Lefaucheur, Romain; Nicolas, Gaël; Dumurgier, Julien; Gerardin, Emmanuel; Jan, Mary; Laplanche, Jean-Louis; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Total Tau concentration in cerebrospinal fluid (CSF) is widely used as a biomarker in the diagnosis of neurodegenerative process primarily in Alzheimer's disease (AD). A particularly high Tau level may indicate AD but may also be associated with Creutzfeldt-Jakob disease (CJD). In such situations little is known about the distribution of differential diagnoses. OBJECTIVE: Our study aimed to describe the different diagnoses encountered in clinical practice for patients with dementia and CSF Tau levels over 1000 pg/ml. We studied the p-Tau/Tau ratio to specify its ability to distinguish AD from CJD. METHODS: Patients (n = 202) with CSF Tau levels over 1000 pg/ml were recruited in three memory clinics in France. All diagnoses were made using the same diagnostic procedure and criteria. RESULTS: Patients were diagnosed with AD (n = 148, 73.2%), mixed dementia (n = 38, 18.8%), CJD, vascular dementia (n = 4, 2.0% for each), Lewy body dementia, and frontotemporal dementia (n = 3, 1.5% for each). Dispersion of CSF Tau levels clearly showed an overlap between all diagnoses. Using the p-Tau/Tau ratio suggestive of CJD (<0.075), all CJD patients were correctly categorized and only two AD patients were miscategorized. This ratio was highly associated with CJD compared to AD (p < 0.0001). CONCLUSION: Our study showed that in clinical practice, extremely high CSF Tau levels are mainly related to diagnosis of AD. CJD patients represent a minority. Our results support a sequential interpretation algorithm for CSF biomarkers in dementia. High CSF Tau levels should alert clinicians to check the p-Tau/Tau ratio to consider a probable diagnosis of CJD.
Keywords: Adult; Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Creutzfeldt-Jakob Syndrome; Dementia, Vascular; Diagnosis, Differential; Female; France; Frontotemporal Dementia; Humans; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged; Phosphorylation; Retrospective Studies; Sex Factors; tau Proteins

The Disconnection Hypothesis in Alzheimer's Disease Studied Through Multimodal Magnetic Resonance Imaging: Structural, Perfusion, and Diffusion Tensor Imaging. - Lacalle-Aurioles, María; Navas-Sánchez, Francisco Javier; Alemán-Gómez, Yasser; Olazarán, Javier; Guzmán-De-Villoria, Juan Adán; Cruz-Orduña, Isabel; Mateos-Pérez, José María; Desco, Manuel (J Alzheimers Dis, 2016)
According to the so-called disconnection hypothesis, the loss of synaptic inputs from the medial temporal lobes (MTL) in Alzheimer's disease (AD) may lead to reduced activity of target neurons in cortical areas and, consequently, to decreased cerebral blood flow (CBF) in those areas. The aim of this study was to assess whether hypoperfusion in parietotemporal and frontal cortices of patients with mild cognitive impairment who converted to AD (MCI-c) and patients with mild AD is associated with atrophy in the MTL and/or microstructural changes in the white matter (WM) tracts connecting these areas. We assessed these relationships by investigating correlations between CBF in hypoperfused areas, mean cortical thickness in atrophied regions of the MTL, and fractional anisotropy (FA) in WM tracts. In the MCI-c group, a strong correlation was observed between CBF of the superior parietal gyri and FA in the parahippocampal tracts (left: r = 0.90, p <  0.0001; right: r = 0.597, p = 0.024), and between FA in the right parahippocampal tract and the right precuneus (r = 0.551, p = 0.041). No significant correlations between CBF in hypoperfused regions and FA in the WM tract were observed in the AD group. These results suggest an association between perfusion deficits and altered WM tracts in prodromal AD, while microvasculature impairments may have a greater influence in more advanced stages. We did not find correlations between cortical thinning in the medial temporal lobes and decreased FA in the WM tracts of the limbic system in either group.
Keywords: Aged; Alzheimer Disease; Brain; Brain Mapping; Cerebral Angiography; Cerebrovascular Circulation; Cognitive Dysfunction; Diffusion Tensor Imaging; Female; Functional Laterality; Humans; Magnetic Resonance Imaging; Male; Mental Status Schedule; Models, Neurological; Multimodal Imaging; Organ Size; Prospective Studies

Disruption of White Matter Integrity by Chronic Cerebral Hypoperfusion in Alzheimer's Disease Mouse Model. - Zhai, Yun; Yamashita, Toru; Nakano, Yumiko; Sun, Zhuoran; Morihara, Ryuta; Fukui, Yusuke; Ohta, Yasuyuki; Hishikawa, Nozomi; Abe, Koji (J Alzheimers Dis, 2016)
A rapidly progressing aging society has raised attention to white matter lesions in Alzheimer's disease. In the present study, we applied an AD plus cerebral hypoperfusion (HP) mouse model and investigated the alternation of key protein molecules in the nodal, paranodal, and intermodal sites in the white matter as well as the efficacy of galantamine. Cerebral HP was induced in APP23 mice by bilateral common carotid arteries stenosis with ameroid constrictors. Compared with the wild type and simple APP23 mice, APP23 + HP mice showed a progressive loss of MAG and NF186 from 6 to 12 months, broken misdistribution of MBP, and extended relocation of Nav1.6 and AnkG beyond the primary nodal region in the corpus callosum. Such abnormal neuropathological processes were retrieved with galantamine treatment. The present study demonstrated that cerebral HP strongly disrupted white matter integrity (WMI) at intermodal, paranodal, and Ranvier's nodal sites which may be associated with cognitive decline. Galantamine treatment significantly protected such WMI probably by allosterically potentiating ligand action.

Distinctive Resting State Network Disruptions Among Alzheimer's Disease, Subcortical Vascular Dementia, and Mixed Dementia Patients. - Kim, Hee Jin; Cha, Jungho; Lee, Jong-Min; Shin, Ji Soo; Jung, Na-Yeon; Kim, Yeo Jin; Choe, Yearn Seong; Lee, Kyung Han; Kim, Sung Tae; Kim, Jae Seung; Lee, Jae Hong; Na, Duk L; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Recent advances in resting-state functional MRI have revealed altered functional networks in Alzheimer's disease (AD), especially those of the default mode network (DMN) and central executive network (CEN). However, few studies have evaluated whether small vessel disease (SVD) or combined amyloid and SVD burdens affect the DMN or CEN. OBJECTIVE: The aim of this study was to evaluate whether SVD or combined amyloid and SVD burdens affect the DMN or CEN. METHODS: In this cross-sectional study, we investigated the resting-state functional connectivity within DMN and CEN in 37 Pittsburgh compound-B (PiB)(+) AD, 37 PiB(-) subcortical vascular dementia (SVaD), 13 mixed dementia patients, and 65 normal controls. RESULTS: When the resting-state DMN of PiB(+) AD and PiB(-) SVaD patients were compared, the PiB(+) AD patients displayed lower functional connectivity in the inferior parietal lobule while the PiB(-) SVaD patients displayed lower functional connectivity in the medial frontal and superior frontal gyri. Compared to the PiB(-) SVaD or PiB(+) AD, the mixed dementia patients displayed lower functional connectivity within the DMN in the posterior cingulate gyrus. When the resting-state CEN connectivity of PiB(+) AD and PiB(-) SVaD patients were compared, the PiB(-) SVaD patients displayed lower functional connectivity in the anterior insular region. Compared to the PiB(-) SVaD or PiB(+) AD, the mixed dementia patients displayed lower functional connectivity within the CEN in the inferior frontal gyrus. CONCLUSIONS: Our findings suggest that in PiB(+) AD and PiB(-) SVaD, there is divergent disruptions in resting-state DMN and CEN. Furthermore, patients with combined amyloid and SVD burdens exhibited more disrupted resting-state DMN and CEN than patients with only amyloid or SVD burden.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Cerebral Cortex; Cross-Sectional Studies; Dementia; Dementia, Vascular; Female; Humans; Image Processing, Computer-Assisted; Male; Middle Aged; Models, Neurological; Neural Pathways; Neuropsychological Tests; Oxygen; Psychiatric Status Rating Scales; Radionuclide Imaging; Rest; Thiazoles

Does Microglial Activation Influence Hippocampal Volume and Neuronal Function in Alzheimer's Disease and Parkinson's Disease Dementia? - Femminella, Grazia D; Ninan, Siddharth; Atkinson, Rebecca; Fan, Zhen; Brooks, David J; Edison, Paul (J Alzheimers Dis, 2016)
BACKGROUND: The influence of neuroinflammation on neuronal function and hippocampal atrophy in Alzheimer's disease (AD) and Parkinson's disease dementia (PDD) is still unclear. OBJECTIVES: Here we investigated whether microglial activation measured by [11C]PK11195 PET is associated with neuronal function measured by cerebral glucose metabolic rate (rCMRGlc) using FDG-PET and hippocampal volume measurements. METHODS: We enrolled 25 subjects (9 PDD, 8 AD, and 8 controls) who underwent PET scans with [11C](R)PK11195, [18F]FDG, and volumetric MRI scanning. RESULTS: SPM correlation analysis in AD and PDD showed a negative correlation between hippocampal volume and microglial activation within hippocampus or parahippocampus and with cortical and subcortical areas of projections from hippocampus, while there was a positive correlation between rCMRGlc in cortical and subcortical areas of projections from hippocampus and hippocampal volume. Hippocampal volume was significantly reduced in AD compared to controls but not in PDD. CONCLUSIONS: These findings indicate that microglial activation inversely correlated with hippocampal volume and hippocampal rCMRGlc in neurodegenerative diseases with dementia, providing further evidence for the central role of microglial activation in neurodegenerative diseases.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antineoplastic Agents; Brain Mapping; Cognition; Female; Fluorodeoxyglucose F18; Hippocampus; Humans; Isoquinolines; Magnetic Resonance Imaging; Male; Microglia; Middle Aged; Neurons; Neuropsychological Tests; Parkinson Disease; Positron-Emission Tomography; Psychiatric Status Rating Scales; Supranuclear Palsy, Progressive

EEG Markers of Dementia with Lewy Bodies: A Multicenter Cohort Study. - Bonanni, Laura; Franciotti, Raffaella; Nobili, Flavio; Kramberger, Milica G; Taylor, John-Paul; Garcia-Ptacek, Sara; Falasca, N Walter; Famá, Francesco; Cromarty, Ruth; Onofrj, Marco; Aarsland, Dag (J Alzheimers Dis, 2016)
Quantitative EEG (QEEG) has demonstrated good discriminative capacity for dementia with Lewy bodies (DLB) diagnosis as compared to Alzheimer's disease (AD) with a predictive value of 100% in a single cohort study. EEG in DLB was characterized by a dominant frequency (DF) in pre-alpha (5.5-7.5 Hz), theta, or delta bands and DF variability (DFV) >1.2 Hz, frequency prevalence (FP) pre-alpha in >40% and FP alpha in <32% of the epochs. To validate the aforementioned QEEG findings in independent cohorts of clinically diagnosed DLB versus AD patients, we analyzed EEG traces of 79 DLB and 133 AD patients (MMSE >20) collected from four European Centers. EEG traces from 19 scalp derivations were acquired as at least 10 min continuous signals and epoched in off-setting as series of 2-second-long epochs, subsequently processed by Fast Fourier Transform (frequency resolution 0.5 Hz). DLB patients showed EEG specific abnormalities in posterior derivations characterized by DF <8 Hz FP pre-alpha >50%, FP alpha <25%. DFV was >0.5 Hz. AD patients displayed stable alpha DF, DFV <0.5 Hz, FP pre-alpha <30%, and FP alpha >55%. DLB and AD differed for DF (p < 10-6), DFV (p < 0.05), FP pre-alpha (p < 10-12) and FP alpha (p < 10-12). Discriminant analysis detected specific cut-offs for every EEG mathematical descriptor; DF = 8, DFV = 2.2 Hz, FP pre-alpha=33%, FP alpha = 41% for posterior derivations. If at least one of the cut-off values was met, the percentage of DLB and AD patients correctly classified was 90% and 64%, respectively. The findings in this multicenter study support the validity of QEEG analysis as a tool for diagnosis in DLB patients.

Effect of Continuous Propofol Infusion in Rat on Tau Phosphorylation with or without Temperature Control. - Huang, Chunxia; Ng, Olivia Tsz-Wa; Ho, Yuen-Shan; Irwin, Michael Garnet; Chang, Raymond Chuen-Chung; Wong, Gordon Tin-Chun (J Alzheimers Dis, 2016)
Several studies suggest a relationship between anesthesia-induced tau hyperphosphorylation and the development of postoperative cognitive dysfunction. This study further characterized the effects of continuous propofol infusion on tau protein phosphorylation in rats, with or without temperature control. Propofol was administered intravenously to 8-10-week-old male Sprague-Dawley rats and infused to the loss of the righting reflex for 2 h continuously. Proteins from cortex and hippocampus were examined by western blot and immunohistochemistry. Rectal temperature was significantly decreased during propofol infusion. Propofol with hypothermia significantly increased phosphorylation of tau at AT8, AT180, Thr205, and Ser199 in cortex and hippocampus except Ser396. With temperature maintenance, propofol still induced significant elevation of AT8, Thr205, and Ser199 in cortex and hippocampus; however, increase of AT180 and Ser396 was only found in hippocampus and cortex, respectively. Differential effects of propofol with or without hypothermia on multiple tau related kinases, such as Akt/GSK3β, MAPK pathways, or phosphatase (PP2A), were demonstrated in region-specific manner. These findings indicated that propofol increased tau phosphorylation under both normothermic and hypothermic conditions, and temperature control could partially attenuate the hyperphosphorylation of tau. Further studies are warranted to determine the long-term impact of propofol on the tau pathology and cognitive functions.
Keywords: Amyloid beta-Peptides; Analysis of Variance; Anesthetics, Intravenous; Animals; Body Temperature; Brain; Gene Expression Regulation; Glycogen Synthase Kinase 3 beta; Hypothermia, Induced; Male; Peptide Fragments; Phosphorylation; Propofol; Rats; Rats, Sprague-Dawley; Signal Transduction; tau Proteins

The Effect of Propofol Versus Isoflurane Anesthesia on Human Cerebrospinal Fluid Markers of Alzheimer's Disease: Results of a Randomized Trial. - Berger, Miles; Nadler, Jacob W; Friedman, Allan; McDonagh, David L; Bennett, Ellen R; Cooter, Mary; Qi, Wenjing; Laskowitz, Daniel T; Ponnusamy, Vikram; Newman, Mark F; Shaw, Leslie M; Warner, David S; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Preclinical studies have found differential effects of isoflurane and propofol on the Alzheimer's disease (AD)-associated markers tau, phosphorylated tau (p-tau) and amyloid-β (Aβ). OBJECTIVE: We asked whether isoflurane and propofol have differential effects on the tau/Aβ ratio (the primary outcome), and individual AD biomarkers. We also examined whether genetic/intraoperative factors influenced perioperative changes in AD biomarkers. METHODS: Patients undergoing neurosurgical/otolaryngology procedures requiring lumbar cerebrospinal fluid (CSF) drain placement were prospectively randomized to receive isoflurane (n = 21) or propofol (n = 18) for anesthetic maintenance. We measured perioperative CSF sample AD markers, performed genotyping assays, and examined intraoperative data from the electronic anesthesia record. A repeated measures ANOVA was used to examine changes in AD markers by anesthetic type over time. RESULTS: The CSF tau/Aβ ratio did not differ between isoflurane- versus propofol-treated patients (p = 1.000). CSF tau/Aβ ratio and tau levels increased 10 and 24 h after drain placement (p = 2.002×10-6 and p = 1.985×10-6, respectively), mean CSF p-tau levels decreased (p = 0.005), and Aβ levels did not change (p = 0.152). There was no interaction between anesthetic treatment and time for any of these biomarkers. None of the examined genetic polymorphisms, including ApoE4, were associated with tau increase (n = 9 polymorphisms, p > 0.05 for all associations). CONCLUSION: Neurosurgery/otolaryngology procedures are associated with an increase in the CSF tau/Aβ ratio, and this increase was not influenced by anesthetic type. The increased CSF tau/Aβ ratio was largely driven by increases in tau levels. Future work should determine the functional/prognostic significance of these perioperative CSF tau elevations.

The Effects of Amnestic Mild Cognitive Impairment on Go/NoGo Semantic Categorization Task Performance and Event-Related Potentials. - Mudar, Raksha A; Chiang, Hsueh-Sheng; Eroh, Justin; Nguyen, Lydia T; Maguire, Mandy J; Spence, Jeffrey S; Kung, Fanting; Kraut, Michael A; Hart, John (J Alzheimers Dis, 2016)
We examined the effects of amnestic mild cognitive impairment (aMCI) on behavioral (response times and error rates) and scalp-recorded event-related potential (ERP) measures of response execution and inhibition, using Go/NoGo tasks involving basic and superordinate semantic categorization. Twenty-five aMCI (16 F; 68.5±8 years) and 25 age- and gender-matched normal control subjects (16 F; 65.4±7.1 years) completed two visual Go/NoGo tasks. In the single car task, responses were made based on single exemplars of a car (Go) and a dog (NoGo) (basic). In the object animal task, responses were based on multiple exemplars of objects (Go) and animals (NoGo) (superordinate). The aMCI subjects had higher commission errors on the NoGo trials compared to the control subjects, whereas both groups had comparable omission errors and reaction times during the Go trials. The aMCI subjects had significantly prolonged N2 ERP latency during Go and NoGo trials across tasks compared to the controls. Both groups showed similar categorization effects and response type effects in N2/P3 ERP latencies and P3 amplitude. Our findings indicate that altered early neural processing indexed by N2 latency distinguishes subjects with aMCI from controls during the Go/NoGo task. Prolonged Go-N2 latency in aMCI appears to precede behavioral changes in response execution, whereas prolonged NoGo-N2 latency underlies behavioral deterioration in response inhibition.
Keywords: Aged; Aged, 80 and over; Amnesia; Brain; Brain Mapping; Cognitive Dysfunction; Electroencephalography; Evoked Potentials; Female; Humans; Inhibition (Psychology); Male; Middle Aged; Neuropsychological Tests; Reaction Time

The Effects of LW-AFC on Intestinal Microbiome in Senescence-Accelerated Mouse Prone 8 Strain, a Mouse Model of Alzheimer's Disease. - Wang, Jianhui; Ye, Fuqiang; Cheng, Xiaorui; Zhang, Xiaorui; Liu, Feng; Liu, Gang; Ni, Ming; Qiao, Shanyi; Zhou, Wenxia; Zhang, Yongxiang (J Alzheimers Dis, 2016)
Microbes have deserved broader attention as causal factors in Alzheimer's disease (AD), a neurodegenerative disorder. The senescence-accelerated mouse prone 8 (SAMP8) strain, a spontaneous mice of accelerated aging, are considered a robust model for sporadic AD. LW-AFC, an herbal medicine, was prepared from LiuweiDihuang decoction, which is a classical traditional Chinese medicine prescription. Here, we showed that the treatment of LW-AFC improved cognitive impairments of SAMP8 mice, including spatial learning and memory ability, active avoidance response, and object recognition memory capability. Our data indicated that there were significantly 8 increased and 12 decreased operational taxonomic units (OTUs) in the gut microbiota of SAMP8 mice compared with senescence accelerated mouse resistant 1 (SAMR1) strains, the control of SAMP8 mice. The treatment of LW-AFC altered 22 (16 increased and 6 decreased) OTUs in SAMP8 mice and among them, 15 OTUs could be reversed by LW-AFC treatment resulting in a microbial composition similar to that of SAMR1 mice. We further showed that there were 7 (3 negative and 4 positive correlation) OTUs significantly correlated with all the three types of cognitive abilities, at the order level, including Bacteroidales, Clostridiales, Desulfovibrionales, CW040, and two unclassified orders. LW-AFC had influences on bacterial taxa correlated with the abilities of learning and memory in SAMP8 mice and restored them to SAMR1 mice. Our results indicate that the effects of LW-AFC on improving cognitive impairments of SAMP8 mice might be via modulating intestinal microbiome and LW-AFC could be used as a potential anti-AD agent.

Efficacy and Safety of Sustained Release Donepezil High Dose versus Immediate Release Donepezil Standard Dose in Japanese Patients with Severe Alzheimer's Disease: A Randomized, Double-Blind Trial. - Homma, Akira; Atarashi, Hirotsugu; Kubota, Naoki; Nakai, Kenya; Takase, Takao (J Alzheimers Dis, 2016)
BACKGROUND: Donepezil is an established treatment for mild, moderate, and severe Alzheimer's disease (AD). An international study demonstrated superior efficacy of sustained release (SR) 23 mg/day donepezil over immediate release (IR) 10 mg/day donepezil for cognitive function, but not global function in moderate-to-severe AD. OBJECTIVE: To demonstrate the superiority of SR 23 mg/day donepezil over IR 10 mg/day donepezil in Japanese patients with severe AD (SAD). METHODS: In this multicenter, randomized, double-blind, parallel-group study, Japanese outpatients with SAD were randomly assigned to continue IR 10 mg/day or switch to SR 23 mg/day for 24 weeks. Endpoints included the Severe Impairment Battery (SIB), Clinician's Interview-Based Impression of Change Plus Caregiver Input (CIBIC-plus), and safety. RESULTS: Overall, 166 and 185 patients were randomized to receive IR 10 mg/day and SR 23 mg/day, respectively. SR 23 mg/day was not statistically superior to IR 10 mg/day by SIB (least squares mean difference [LSMD]: 0.0; 95% confidence interval [CI]: -1.7, 1.8; p = 0.981) or CIBIC-plus (LSMD: 0.2; 95% CI: 0.0, 0.4; p = 0.080). Common adverse events in the SR 23 mg group were decreased appetite, vomiting, diarrhea, and contusion. Safety findings were consistent with known safety profiles of donepezil. CONCLUSION: SR 23 mg/day donepezil was not superior to IR 10 mg/day donepezil regarding the efficacy endpoints for Japanese SAD. Considering that a 10 mg/day dose is approved for SAD in Japan, the present findings suggest that IR 10 mg/day donepezil is the optimal dosage for Japanese patients with SAD.
Keywords: Aged; Alzheimer Disease; Cholinesterase Inhibitors; Delayed-Action Preparations; Double-Blind Method; Female; Humans; Indans; Japan; Male; Mental Status Schedule; Nootropic Agents; Outpatients; Piperidines; Psychiatric Status Rating Scales; Severity of Illness Index; Treatment Outcome

Enalapril Alone or Co-Administered with Losartan Rescues Cerebrovascular Dysfunction, but not Mnemonic Deficits or Amyloidosis in a Mouse Model of Alzheimer's Disease. - Ongali, Brice; Nicolakakis, Nektaria; Tong, Xing-Kang; Aboulkassim, Tahar; Imboden, Hans; Hamel, Edith (J Alzheimers Dis, 2016)
The co-administration of angiotensin converting enzyme inhibitors (ACEi) and angiotensin II (AngII) receptor blockers (ARB) that bind angiotensin type 1 receptors (AT1R) may protect from Alzheimer's disease (AD) better than each treatment taken alone. We tested the curative potential of the non brain-penetrant ACEi enalapril (3 mg/kg/day) administered for 3 months either alone or in combination with the brain penetrant ARB losartan (10 mg/kg/day) in aged (∼15 months) transgenic mice overexpressing a mutated form of the human amyloid-β protein precursor (AβPP, thereafter APP mice). We studied cerebrovascular function, protein levels of oxidative stress markers (superoxide dismutases SOD1, SOD2 and the NADPH oxidase subunit p67phox), amyloid-β (Aβ) pathology, astrogliosis, cholinergic innervation, AT1R and angiotensin IV receptor (AT4R) levels, together with cognitive performance. Both treatments normalized cerebrovascular reactivity and p67phox protein levels, but they did not reduce the cerebrovascular levels of SOD1. Combined treatment normalized cerebrovascular SOD2 levels, significantly attenuated astrogliosis, but did not reduce the increased levels of cerebrovascular AT1R. Yet, combined therapy enhanced thioflavin-S labeled Aβ plaque burden, a tendency not significant when Aβ1 - 42 plaque load was considered. None of the treatments rescued cognitive deficits, cortical AT4R or cholinergic innervation. We conclude that both treatments normalized cerebrovascular function by inhibiting the AngII-induced oxidative stress cascade, and that the positive effects of the combined therapy on astrogliosis were likely due to the ability of losartan to enter brain parenchyma. However, enalapril did not potentiate, and may even dampen, the reported cognitive benefits of losartan, raising caution when selecting the most appropriate antihypertensive therapy in AD patients.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloidosis; Analysis of Variance; Animals; Antihypertensive Agents; Cerebrovascular Disorders; Cholinesterases; Disease Models, Animal; Drug Combinations; Enalapril; Female; Glial Fibrillary Acidic Protein; Humans; Losartan; Male; Maze Learning; Memory Disorders; Mice; Mice, Transgenic; Mutation

Evaluation of Cerebrospinal Fluid Assay Variability in Alzheimer's Disease. - White, Matthew T; Shaw, Leslie M; Xie, Sharon X (J Alzheimers Dis, 2016)
Studies of cerebrospinal fluid (CSF) biomarkers in Alzheimer's disease (AD) have indicated that much of the variability observed in the biomarkers may be due to measurement error. Biomarkers are often obtained with measurement error, which may make the diagnostic biomarker appear less effective than it truly is. In the Alzheimer's Disease Neuroimaging Initiative (ADNI) database, technical replicates of CSF biomarkers are available; the National Alzheimer's Coordinating Center database contains longitudinal replicates of CSF biomarkers. We focus on the area under the receiver operating characteristic curve (AUC) as the measure of diagnostic effectiveness for differentiating AD from normal cognition using CSF biomarkers and compare AUC estimates obtained by a more standard, naïve method (which uses a single observation per subject and ignores measurement error) to a maximum likelihood (ML) based method (which uses all replicates per subject and adjusts for measurement error). The choice of analysis method depends upon the noise to signal ratio (i.e., the magnitude of the measurement error variability relative to the true biomarker variability); moderate to high ratios may significantly bias the naïve AUC estimate, and the ML-based method would be preferred. The noise to signal ratios were low for the ADNI biomarkers but high for the tTau and pTau biomarkers in NACC. Correspondingly, the naïve and ML-based AUC estimates were nearly identical in the ADNI data but dissimilar for the tTau and pTau biomarkers in the NACC data. Therefore, using the naïve method is adequate for analysis of CSF biomarkers in the ADNI study, but the ML method is recommended for the NACC data.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Area Under Curve; Biomarkers; Databases, Factual; Female; Humans; Likelihood Functions; Male; Peptide Fragments; Phosphorylation; ROC Curve; tau Proteins

Evidence For and Against a Pathogenic Role of Reduced γ-Secretase Activity in Familial Alzheimer's Disease. - Jayne, Tanya; Newman, Morgan; Verdile, Giuseppe; Sutherland, Greg; Münch, Gerald; Musgrave, Ian; Moussavi Nik, Seyyed Hani; Lardelli, Michael (J Alzheimers Dis, 2016)
The majority of mutations causing familial Alzheimer's disease (fAD) have been found in the gene PRESENILIN1 (PSEN1) with additional mutations in the related gene PRESENILIN2 (PSEN2). The best characterized function of PRESENILIN (PSEN) proteins is in γ-secretase enzyme activity. One substrate of γ-secretase is encoded by the gene AMYLOID BETA A4 PRECURSOR PROTEIN (AβPP/APP) that is a fAD mutation locus. AβPP is the source of the amyloid-β (Aβ) peptide enriched in the brains of people with fAD or the more common, late onset, sporadic form of AD, sAD. These observations have resulted in a focus on γ-secretase activity and Aβ as we attempt to understand the molecular basis of AD pathology. In this paper we briefly review some of the history of research on γ-secretase in AD. We then discuss the main ideas regarding the role of γ-secretase and the PSEN genes in this disease. We examine the significance of the "fAD mutation reading frame preservation rule" that applies to PSEN1 and PSEN2 (and AβPP) and look at alternative roles for AβPP and Aβ in fAD. We present a case for an alternative interpretation of published data on the role of γ-secretase activity and fAD-associated mutations in AD pathology. Evidence supports a "PSEN holoprotein multimer hypothesis" where PSEN fAD mutations generate mutant PSEN holoproteins that multimerize with wild type holoprotein and dominantly interfere with an AD-critical function(s) such as autophagy or secretion of Aβ. Holoprotein multimerization may be required for the endoproteolysis that activates PSENs' γ-secretase activity.

Expression of the Alzheimer's Disease Mutations AβPP695sw and PSEN1M146I in Double-Transgenic Göttingen Minipigs. - Jakobsen, Jannik E; Johansen, Marianne G; Schmidt, Mette; Liu, Ying; Li, Rong; Callesen, Henrik; Melnikova, Margarita; Habekost, Mette; Matrone, Carmela; Bouter, Yvonne; Bayer, Thomas A; Nielsen, Anders Lade; et al. (J Alzheimers Dis, 2016)
Mutations in the amyloid-β protein precursor gene (AβPP), the presenilin 1 gene (PSEN1) or the presenilin 2 gene (PSEN2) that increase production of the AβPP-derived peptide Aβ42 cause early-onset Alzheimer's disease. Rodent models of the disease show that further increase in Aβ42 production and earlier brain pathology can be obtained by coexpressing AβPP and PSEN1 mutations. To generate such elevated Aβ42 level in a large animal model, we produced Göttingen minipigs carrying in their genome one copy of a human PSEN1 cDNA with the Met146Ile (PSEN1M146I) mutation and three copies of a human AβPP695 cDNA with the Lys670Asn/Met671Leu (AβPPsw) double-mutation. Both transgenes were expressed in fibroblasts and in the brain, and their respective proteins were processed normally. Immunohistochemical staining with Aβ42-specific antibodies detected intraneuronal accumulation of Aβ42 in brains from a 10- and an 18-month-old pig. Such accumulation may represent an early event in the pathogenesis of Alzheimer's disease.

Feasibility of a Memory Clinic-Based Physical Activity Prescription Program. - Vidoni, Eric D; Watts, Amber S; Burns, Jeffrey M; Greer, Colby S; Graves, Rasinio S; Van Sciver, Angela; Black, Jessica R; Cooper, Sarah K; Nagely, Allison C; Uphoff, Elaine; Volmer, Jennifer M; Bieberle, Natalie A (J Alzheimers Dis, 2016)
BACKGROUND: Effective programs for promoting physical activity are needed for those with cognitive impairment. OBJECTIVE: To test the feasibility of mobile Health (mHealth) technology-supported physical activity prescription from a tertiary care memory clinic. METHODS: This feasibility study was designed as a 16-week randomized, crossover trial of a physical activity prescription: 8 weeks of intervention, 8 weeks of baseline or maintenance phase data collection. We recruited 2 cohorts: 21 individuals with Alzheimer-related cognitive impairment (mean age 72.3 (5.2), 9 females), and 9 individuals with normal cognition (mean age 69.6 (5.8), 8 females). We gave each cohort an mHealth accelerometer-based physical activity prescription to double number of steps taken. Our primary outcomes were feasibility and safety. Our secondary outcomes were change in weekly steps taken, Dementia Quality of Life Scale, Self-efficacy Scale, 6-minute Walk, and mini-Physical Performance Test. RESULTS: Set-up and use of the device was not a barrier to participation. However, only 62% of participants with cognitive impairment completed the intervention. The cohort with cognitive impairment did not change their weekly step count above Week 1. All participants in the cohort with normal cognition were able to set up and use their device and increased their weekly step count above Week 1. There were no differences between Week 1 and Week 8 for any secondary measures in either cohort. CONCLUSIONS: Setup and daily use of mHealth technology appears to be feasible for a person with cognitive impairment with the help of a partner, but increasing daily step counts over 8 weeks was not achieved. Future work needs to assess alternative activity prescription goals or additional support for patients and their partners.

FTIR and Raman Spectroscopy Applied to Dementia Diagnosis Through Analysis of Biological Fluids. - Lopes, Jéssica; Correia, Marta; Martins, Ilka; Henriques, Ana Gabriela; Delgadillo, Ivonne; da Cruz E Silva, Odete; Nunes, Alexandra (J Alzheimers Dis, 2016)
To date, it is still difficult to perform an early and accurate diagnosis of dementia, therefore significant research has focused on finding new dementia biomarkers that can aid in this respect. There is an urgent need for non-invasive, rapid, and relatively inexpensive procedures for early diagnostics. Studies have demonstrated that of spectroscopic techniques, such as Fourier Transform Infrared Spectroscopy (FTIR) and Raman Spectroscopy could be a useful and accurate procedure to diagnose dementia. Given that several biochemical mechanisms related to neurodegeneration and dementia can lead to changes in plasma components and others peripheral body fluids; blood-based samples coupled to spectroscopic analyses can be used as a simple and less invasive approach.

Genetic Counseling and Testing for Alzheimer's Disease and Frontotemporal Lobar Degeneration: An Italian Consensus Protocol. - Bocchetta, Martina; Mega, Anna; Bernardi, Livia; Di Maria, Emilio; Benussi, Luisa; Binetti, Giuliano; Borroni, Barbara; Colao, Rosanna; Di Fede, Giuseppe; Fostinelli, Silvia; Galimberti, Daniela; Gennarelli, Massimo; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Genetic testing of familial Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD) is attracting interest thanks to innovative primary prevention clinical trials and increased request for information by at-risk individuals. However, ethical, social, and psychological implications are paramount and genetic testing must be supported by structured genetic counseling. In Italy, practice parameters and guidelines for genetic counseling in dementia are not available. OBJECTIVE: To develop a nationally harmonized protocol for genetic counseling and testing of familial AD and FTLD. METHODS: Activities were carried out in the context of the Italian Dominantly Inherited Alzheimer's and Frontotemporal Network (IT-DIAfN) project, a national network of centers of excellence with expertise in managing patients with familial AD and FTLD. A survey of the literature on genetic counseling protocols and guidelines was conducted. Local protocols for genetic counseling were surveyed. Differences and commonalities among protocols were identified and discussed among project partners. Consensus was reached following implicit aggregation methods. RESULTS: Consensus was reached on a protocol for patients with clinically diagnosed familial AD or FTLD and a distinct protocol for their at-risk relatives. Genetic counseling should be provided by a multidisciplinary team including a geneticist, a neurologist/geriatrician, and a psychologist/psychiatrist, according to the following schedule: (i) initial consultation with tailored information on the genetics of the dementias; (ii) clinical, psychological, and cognitive assessment; if deemed appropriate (iii) genetic testing following a structured decision tree for gene mutation search; (iv) genetic testing result disclosure; (v) psychological support follow-up. CONCLUSION: This genetic counseling protocol provides Italian centers with a line of shared practice for dealing with the requests for genetic testing for familial AD and FTLD from patients and at-risk relatives, who may also be eligible participants for novel prevention clinical trials.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Consensus; Female; Follow-Up Studies; Frontotemporal Lobar Degeneration; Genetic Counseling; Genetic Testing; Humans; Italy; Male; Peptide Fragments; Psychiatric Status Rating Scales

Genetic Influences on Plasma Homocysteine Levels in African Americans and Yoruba Nigerians. - Kim, Sungeun; Nho, Kwangsik; Ramanan, Vijay K; Lai, Dongbing; Foroud, Tatiana M; Lane, Katie; Murrell, Jill R; Gao, Sujuan; Hall, Kathleen S; Unverzagt, Frederick W; Baiyewu, Olusegun; Ogunniyi, Adesola; et al. (J Alzheimers Dis, 2016)
Plasma homocysteine, a metabolite involved in key cellular methylation processes seems to be implicated in cognitive functions and cardiovascular health with its high levels representing a potential modifiable risk factor for Alzheimer's disease (AD) and other dementias. A better understanding of the genetic factors regulating homocysteine levels, particularly in non-white populations, may help in risk stratification analyses of existing clinical trials and may point to novel targets for homocysteine-lowering therapy. To identify genetic influences on plasma homocysteine levels in individuals with African ancestry, we performed a targeted gene and pathway-based analysis using a priori biological information and then to identify new association performed a genome-wide association study. All analyses used combined data from the African American and Yoruba cohorts from the Indianapolis-Ibadan Dementia Project. Targeted analyses demonstrated significant associations of homocysteine and variants within the CBS (Cystathionine beta-Synthase) gene. We identified a novel genome-wide significant association of the AD risk gene CD2AP (CD2-associated protein) with plasma homocysteine levels in both cohorts. Minor allele (T) carriers of identified CD2AP variant (rs6940729) exhibited decreased homocysteine level. Pathway enrichment analysis identified several interesting pathways including the GABA receptor activation pathway. This is noteworthy given the known antagonistic effect of homocysteine on GABA receptors. These findings identify several new targets warranting further investigation in relation to the role of homocysteine in neurodegeneration.
Keywords: Adaptor Proteins, Signal Transducing; African Americans; African Continental Ancestry Group; Aged; Aged, 80 and over; Cohort Studies; Cystathionine beta-Synthase; Cytoskeletal Proteins; Female; Genetic Variation; Genome-Wide Association Study; Heterozygote; Homocysteine; Humans; Indiana; Longitudinal Studies; Male; Nigeria; Prospective Studies

A Genetic Variant of the Sortilin 1 Gene is Associated with Reduced Risk of Alzheimer's Disease. - Andersson, Carl-Henrik; Hansson, Oskar; Minthon, Lennart; Andreasen, Niels; Blennow, Kaj; Zetterberg, Henrik; Skoog, Ingmar; Wallin, Anders; Nilsson, Staffan; Kettunen, Petronella (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a neurodegenerative disorder represented by the accumulation of intracellular tau protein and extracellular deposits of amyloid-β (Aβ) in the brain. The gene sortilin 1 (SORT1) has previously been associated with cardiovascular disease in gene association studies. It has also been proposed to be involved in AD pathogenesis through facilitating Aβ clearance by binding apoE/Aβ complexes prior to cellular uptake. However, the neuropathological role of SORT1 in AD is not fully understood. To evaluate the associations between gene variants of SORT1 and risk of AD, we performed genetic analyses in a Swedish case-control cohort. Ten single nucleotide polymorphisms (SNPs), covering the whole SORT1 gene, were selected and genotyped in 620 AD patients and 1107 controls. The SNP rs17646665, located in a non-coding region of the SORT1 gene, remained significantly associated with decreased risk of AD after multiple testing (pc = 0.0061). In addition, other SNPs were found to be nominally associated with risk of AD, as well as altered cognitive function and the CSF biomarker Aβ42, but these associations did not survive correction for multiple testing. The fact that SORT1 has been strongly associated with risk of cardiovascular disease is intriguing as cardiovascular disease is also regarded as a risk factor for AD. Finally, increased knowledge about SORT1 function has a potential to increase our understanding of APOE, the strongest risk factor for AD.

Genetic Variations in ABCA7 Can Increase Secreted Levels of Amyloid-β40 and Amyloid-β42 Peptides and ABCA7 Transcription in Cell Culture Models. - Bamji-Mirza, Michelle; Li, Yan; Najem, Dema; Liu, Qing Yan; Walker, Douglas; Lue, Lih-Fen; Stupak, Jacek; Chan, Kenneth; Li, Jianjun; Ghani, Mahdi; Yang, Ze; Rogaeva, Ekaterina; et al. (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by extracellular deposits of amyloid-β (Aβ) in the brain. ABCA7 is highly expressed in the brain and a susceptibility gene for late-onset AD (LOAD). The minor alleles at two ABCA7 single-nucleotide polymorphisms (SNPs), rs3764650 (T>G; intron13) and rs3752246 at a predicted myristoylation site (C>G; exon33; p.Gly1527Ala), are significantly associated with LOAD risk; however, the mechanism of this association is unknown. Functional consequences of both SNPs were examined in HEK293 and CHO cells stably expressing AβPPSwe. Luciferase reporter assays in HEK293 cells suggested that intron13 carrying rs3764650 major T-allele (int13-T) possessed promoter-enhancing capabilities. Co-transfection experiments with hABCA7 and int13-T resulted in significantly increased ABCA7 protein level relative to that with int13-G. Expression of hABCA7 carrying rs3752246 risk allele led to increases in secreted Aβ40 and Aβ42 and β-secretase activity in CHO- and HEK-AβPPSwe cells. Hydroxymyristic acid treatment of cells expressing hABCA7 carrying the rs3752246 major G allele resulted in increased β-secretase activity and levels of Aβ, suggesting that lack of myristoylation contributes to the observed cell-phenotypes. Molecular weight determination, by gel-electrophoresis and mass spectrometry, of hABCA7 peptides spanning position 1527 showed loss of post-translational modification in the risk-allele peptide. These results suggest that decreased expression, or impaired function, of ABCA7 may contribute to AD pathology.

Geographical Variation in Antipsychotic Drug Use in Elderly Patients with Dementia: A Nationwide Study. - Zakarias, Johanne Købstrup; Jensen-Dahm, Christina; Nørgaard, Ane; Stevnsborg, Lea; Gasse, Christiane; Andersen, Bodil Gramkow; Søren, Jakobsen; Waldorff, Frans Boch; Moos, Torben; Waldemar, Gunhild (J Alzheimers Dis, 2016)
BACKGROUND: Use of antipsychotics in elderly patients with dementia has decreased in the past decade due to safety regulations; however use is still high. Geographical variation may indicate discrepancies in clinical practice and lack of adherence to evidence-based guidelines for the management of behavioral symptoms. OBJECTIVE: To investigate potential geographical variances in use of antipsychotic drugs in dementia care. METHODS: A registry-based cross-sectional study in the entire elderly population of Denmark (≥65 years) conducted in 2012. Data included place of residence, prescriptions filled, and hospital discharge diagnoses. Antipsychotic drug use among elderly with (n = 34,536) and without (n = 931,203) a dementia diagnosis was compared across the five regions and 98 municipalities in Denmark, adjusted for age and sex. RESULTS: In 2012, the national prevalence of antipsychotic drug use was 20.7% for elderly patients with dementia, with a national incidence of 3.9%. The prevalence ranged from 17.0% to 23.3% in the five regions and from 7.5% to 33.1% in the 98 municipalities, demonstrating an over four-fold difference. CONCLUSION: The observed geographical variation was more pronounced at municipal level as compared to regional level, suggesting that the variation may be related to variances in clinical practice in primary care. This study highlights an urgent need for further educating professional carers and physicians to guide non-pharmacological as well as pharmacological management of neuropsychiatric symptoms in elderly patients with dementia.

Greater than the Sum of Its Parts: δ can be Constructed from Item Level Data. - Royall, Donald R; Palmer, Raymond F; Matsuoka, Teruyuki; Kato, Yuka; Taniguchi, Shogo; Ogawa, Mayu; Fujimoto, Hiroshi; Okamura, Aiko; Shibata, Keisuke; Nakamura, Kaeko; Nakaaki, Shutaro; Koumi, Hiroyuki; et al. (J Alzheimers Dis, 2016)
"δ", a latent variable constructed from cognitive performance and functional status measures, can accurately diagnose dementia. The minimal assessment needed is unknown. We have constructed a δ homolog, "dTEXAS", from Telephone Executive Assessment Scale (TEXAS) items, and validated it in a convenience sample of Japanese persons (n = 176). dTEXAS scores correlated strongly with both Instrumental Activities of Daily Living (IADL) (r = -0.86, p <  0.001) and Clinical Dementia Rating Scale (CDR) (r = 0.71, p <  0.001). Constructed independently of their diagnoses, dTEXAS scores accurately distinguished dementia versus controls (area under the receiver operating curve [(AUC; ROC) = 0.92], dementia versus mild cognitive impairment (MCI) (AUC = 0.80) and controls versus MCI (AUC = 0.74). These AUCs are higher than those of multiple observed executive measures, as reported recently by Matsuoka et al., 2014. A dTEXAS score of -0.58 best discriminated between dementia versus controls with 90.1% sensitivity and 80.0% specificity.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Executive Function; Female; Humans; Japan; Male; Neuropsychological Tests; Psychiatric Status Rating Scales; ROC Curve; United States

Hippocampal Sclerosis of Aging, a Common Alzheimer's Disease 'Mimic': Risk Genotypes are Associated with Brain Atrophy Outside the Temporal Lobe. - Nho, Kwangsik; Saykin, Andrew J; Nelson, Peter T (J Alzheimers Dis, 2016)
Hippocampal sclerosis of aging (HS-Aging) is a common brain disease in older adults with a clinical course that is similar to Alzheimer's disease. Four single-nucleotide polymorphisms (SNPs) have previously shown association with HS-Aging. The present study investigated structural brain changes associated with these SNPs using surface-based analysis. Participants from the Alzheimer's Disease Neuroimaging Initiative cohort (ADNI; n = 1,239), with both MRI scans and genotype data, were used to assess the association between brain atrophy and previously identified HS-Aging risk SNPs in the following genes: GRN, TMEM106B, ABCC9, and KCNMB2 (minor allele frequency for each is >30%). A fifth SNP (near the ABCC9 gene) was evaluated in post-hoc analysis. The GRN risk SNP (rs5848_T) was associated with a pattern of atrophy in the dorsomedial frontal lobes bilaterally, remarkable since GRN is a risk factor for frontotemporal dementia. The ABCC9 risk SNP (rs704180_A) was associated with multifocal atrophy whereas a SNP (rs7488080_A) nearby (∼50 kb upstream) ABCC9 was associated with atrophy in the right entorhinal cortex. Neither TMEM106B (rs1990622_T), KCNMB2 (rs9637454_A), nor any of the non-risk alleles were associated with brain atrophy. When all four previously identified HS-Aging risk SNPs were summed into a polygenic risk score, there was a pattern of associated multifocal brain atrophy in a predominately frontal pattern. We conclude that common SNPs previously linked to HS-Aging pathology were associated with a distinct pattern of anterior cortical atrophy. Genetic variation associated with HS-Aging pathology may represent a non-Alzheimer's disease contribution to atrophy outside of the hippocampus in older adults.

Human Truncated Tau Induces Mature Neurofibrillary Pathology in a Mouse Model of Human Tauopathy. - Zimova, Ivana; Brezovakova, Veronika; Hromadka, Tomas; Weisova, Petronela; Cubinkova, Veronika; Valachova, Bernadeta; Filipcik, Peter; Jadhav, Santosh; Smolek, Tomas; Novak, Michal; Zilka, Norbert (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) represents the most common neurodegenerative disorder. Several animal models have been developed in order to test pathophysiological mechanisms of the disease and to predict effects of pharmacological interventions. Here we examine the molecular and behavioral features of R3m/4 transgenic mice expressing human non-mutated truncated tau protein (3R tau, aa151-391) that were previously used for efficacy testing of passive tau vaccine. The mouse model reliably recapitulated crucial histopathological features of human AD, such as pre-tangles, neurofibrillary tangles, and neuropil threads. The pathology was predominantly located in the brain stem. Transgenic mice developed mature sarkosyl insoluble tau complexes consisting of mouse endogenous and human truncated and hyperphosphorylated forms of tau protein. The histopathological and biochemical features were accompanied by significant sensorimotor impairment and reduced lifespan. The sensorimotor impairment was monitored by a highly sensitive, fully-automated tool that allowed us to assess early deficit in gait and locomotion. We suggest that the novel transgenic mouse model can serve as a valuable tool for analysis of the therapeutic efficacy of tau vaccines for AD therapy.

Immunization Against Specific Fragments of Neurotrophin p75 Receptor Protects Forebrain Cholinergic Neurons in the Olfactory Bulbectomized Mice. - Bobkova, Natalia; Vorobyov, Vasily; Medvinskaya, Natalia; Nesterova, Inna; Tatarnikova, Olga; Nekrasov, Pavel; Samokhin, Alexander; Deev, Alexander; Sengpiel, Frank; Koroev, Dmitry; Volpina, Olga (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by progressive cognitive impairment associated with marked cholinergic neuron loss and amyloid-β (Aβ) peptide accumulation in the brain. The cytotoxicity in AD is mediated, at least in part, by Aβ binding with the extracellular domain of the p75 neurotrophin receptor (p75NTR), localized predominantly in the membranes of acetylcholine-producing neurons in the basal forebrain. Hypothesizing that an open unstructured loop of p75NTR might be the effective site for Aβ binding, we have immunized both olfactory bulbectomized (OBX) and sham-operated (SO) mice (n = 82 and 49, respectively) with synthetic peptides, structurally similar to different parts of the loops, aiming to block them by specific antibodies. OBX-mice have been shown in previous studies, and confirmed in the present one, to be characterized by typical behavioral, morphological, and biochemical AD hallmarks, including cholinergic deficits in forebrain neurons. Immunization of OBX- or SO-mice with KLH conjugated fragments of p75NTR induced high titers of specific serum antibodies for each of nine chosen fragments. However, maximal protective effects on spatial memory, evaluated in a Morris water maze, and on activity of choline acetyltransferase in forebrain neurons, detected by immunoreactivity to specific antibodies, were revealed only for peptides with amino acid residue sequences of 155-164 and 167-176. We conclude that the approach based on immunological blockade of specific p75NTR sites, linked with the cytotoxicity, is a useful and effective tool for study of AD-associated mechanisms and for development of highly selective therapy of cholinergic malfunctioning in AD patients.

Impact of Depressive Symptoms on Conversion from Mild Cognitive Impairment Subtypes to Alzheimer's Disease: A Community-Based Longitudinal Study. - Kida, Jiro; Nemoto, Kiyotaka; Ikejima, Chiaki; Bun, Shogyoku; Kakuma, Tatsuyuki; Mizukami, Katsuyoshi; Asada, Takashi (J Alzheimers Dis, 2016)
BACKGROUND: While longitudinal studies have investigated the relationships between mild cognitive impairment (MCI) subtypes and dementia subtypes, the results have been contradictory. In addition, some research shows that depression accompanied by MCI might increase the risk of Alzheimer's disease (AD). OBJECTIVE: The aim of this study is to longitudinally investigate the relationships between MCI subtypes and dementia subtypes, with special attention to the effect of comorbid depressive symptoms in a Japanese rural community. METHODS: Non-demented participants (n = 802) completed a baseline and follow-up study. Outcomes were conversion to dementia especially AD, MCI, or no conversion. A complementary log-log analysis was conducted to investigate the risk of dementia and AD in amnestic MCI (aMCI) compared to nonamnestic MCI (naMCI) groups. The impact of depressive symptoms on the transition from MCI to AD and from cognitively normal to MCI or AD was also analyzed. RESULTS: The risk of developing dementia, in particular AD, for the aMCI group was significantly higher than that for the naMCI group. In the aMCI group, the presence of depressive symptoms increased the risk of developing AD, but depressive symptoms in the naMCI group did not. In the cognitively normal group, the presence of depressive symptoms increased the risk of aMCI but not naMCI or AD. CONCLUSION: MCI subtyping could be useful in finding a prodrome for dementia and in particular for AD. The differing impacts of depressive symptoms on the development of AD suggest that the relationship between depressive symptoms and cognitive impairment could differ in aMCI and naMCI patients.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Cognitive Dysfunction; Depression; Disease Progression; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Prodromal Symptoms; Prognosis; Risk

Increased Expression of Readthrough Acetylcholinesterase Variants in the Brains of Alzheimer's Disease Patients. - Campanari, Maria-Letizia; Navarrete, Francisco; Ginsberg, Stephen D; Manzanares, Jorge; Sáez-Valero, Javier; García-Ayllón, María-Salud (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by a decrease in the enzymatic activity of the enzyme acetylcholinesterase (AChE). AChE is expressed as multiple splice variants, which may serve both cholinergic degradative functions and non-cholinergic functions unrelated with their capacity to hydrolyze acetylcholine. We have recently demonstrated that a prominent pool of enzymatically inactive AChE protein exists in the AD brain. In this study, we analyzed protein and transcript levels of individual AChE variants in human frontal cortex from AD patients by western blot analysis using specific anti-AChE antibodies and by quantitative real-time PCR (qRT-PCR). We found similar protein and mRNA levels of the major cholinergic "tailed"-variant (AChE-T) and the anchoring subunit, proline-rich membrane anchor (PRiMA-1) in frontal cortex obtained from AD patients and non-demented controls. Interestingly, we found an increase in the protein and transcript levels of the non-cholinergic "readthrough" AChE (AChE-R) variants in AD patients compared to controls. Similar increases were detected by western blot using an antibody raised against the specific N-terminal domain, exclusive of alternative N-extended variants of AChE (N-AChE). In accordance with a subset of AChE-R monomers that display amphiphilic properties that are upregulated in the AD brain, we demonstrate that the increase of N-AChE species is due, at least in part, to N-AChE-R variants. In conclusion, we demonstrate selective alterations in specific AChE variants in AD cortex, with no correlation in enzymatic activity. Therefore, differential expression of AChE variants in AD may reflect changes in the pathophysiological role of AChE, independent of cholinergic impairment or its role in degrading acetylcholine.

Increased Levels of Extracellular Microvesicle Markers and Decreased Levels of Endocytic/Exocytic Proteins in the Alzheimer's Disease Brain. - Musunuri, Sravani; Khoonsari, Payam Emami; Mikus, Maria; Wetterhall, Magnus; Häggmark-Mänberg, Anna; Lannfelt, Lars; Erlandsson, Anna; Bergquist, Jonas; Ingelsson, Martin; Shevchenko, Ganna; Nilsson, Peter; Kultima, Kim (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) is a chronic neurodegenerative disorder accounting for more than 50% of all dementia cases. AD neuropathology is characterized by the formation of extracellular plaques and intracellular neurofibrillary tangles consisting of aggregated amyloid-β and tau, respectively. The disease mechanism has only been partially elucidated and is believed to also involve many other proteins. OBJECTIVE: This study intended to perform a proteomic profiling of post mortem AD brains and compare it with control brains as well as brains from other neurological diseases to gain insight into the disease pathology. METHODS: Here we used label-free shotgun mass spectrometry to analyze temporal neocortex samples from AD, other neurological disorders, and non-demented controls, in order to identify additional proteins that are altered in AD. The mass spectrometry results were verified by antibody suspension bead arrays. RESULTS: We found 50 proteins with altered levels between AD and control brains. The majority of these proteins were found at lower levels in AD. Pathway analyses revealed that several of the decreased proteins play a role in exocytic and endocytic pathways, whereas several of the increased proteins are related to extracellular vesicles. Using antibody-based analysis, we verified the mass spectrometry results for five representative proteins from this group of proteins (CD9, HSP72, PI42A, TALDO, and VAMP2) and GFAP, a marker for neuroinflammation. CONCLUSIONS: Several proteins involved in exo-endocytic pathways and extracellular vesicle functions display altered levels in the AD brain. We hypothesize that such changes may result in disturbed cellular clearance and a perturbed cell-to-cell communication that may contribute to neuronal dysfunction and cell death in AD.

Inequalities in Access to Treatment and Care for Patients with Dementia and Immigrant Background: A Danish Nationwide Study. - Stevnsborg, Lea; Jensen-Dahm, Christina; Nielsen, Thomas R; Gasse, Christiane; Waldemar, Gunhild (J Alzheimers Dis, 2016)
BACKGROUND: Previous studies demonstrated lower quality diagnostic assessment of dementia in immigrant populations, but knowledge about the quality of treatment and care for dementia is still lacking. OBJECTIVE: To conduct a nationwide registry-based study to determine whether inequality exists regarding access to anti-dementia treatment and care between immigrant and Danish-born patients with dementia. METHODS: A cross-sectional register-based study was conducted in the entire elderly (60≥years) population with dementia in Denmark in 2012 (n = 34,877). The use of anti-dementia drugs and residency in a nursing home were compared among Danish-born and Western and non-Western immigrants with dementia. Logistic regression analysis was done with adjustment for age, sex, comorbidity, marital status, basis of inclusion, and time since dementia diagnosis. RESULTS: Immigrant background was associated with a significantly lower likelihood of receiving anti-dementia drug therapy (odds ratio (OR) [95% confidence interval (CI)]): non-Western = 0.70 [0.56-0.87]; Western = 0.74 [0.63-0.87]). No significant differences were found in type or amount of anti-dementia medication dispensed between the population groups (proxy measure for adherence). Non-Western immigrants were significantly less likely to live in a nursing home (0.52 [0.41-0.65]). CONCLUSION: This nationwide registry-based study indicated a worrisome difference in access to anti-dementia treatment and care for dementia patients with an immigrant background, but similar levels of adherence compared with the Danish-born population. Further research is necessary to pinpoint barriers to access to suitable healthcare among elderly immigrants with dementia but also to identify and develop culturally sensitive methods for their treatment and care.

Influence of Low-Dose Aspirin on Cerebral Amyloid Angiopathy in Mice. - Hattori, Yorito; Maki, Takakuni; Saito, Satoshi; Yamamoto, Yumi; Nagatsuka, Kazuyuki; Ihara, Masafumi (J Alzheimers Dis, 2016)
Accumulation of amyloid-β peptide (Aβ) in the brain is one of the most important features of Alzheimer's dementia (AD). Cerebral amyloid angiopathy (CAA) is characterized by Aβ accumulation in the walls of cerebral arteries and capillaries, and is present in over 90% of patients with AD. Several novel agents for AD/CAA developed around the amyloid hypothesis have shown positive signs in animal studies but have failed in clinical trials due to adverse events and/or lack of efficiency. As CAA is presumably caused by a failure in Aβ clearance, drugs that promote Aβ clearance may hold promise in the treatment of CAA and possibly AD. With this in mind, cilostazol, an anti-platelet drug with vasodilating action, has been found to promote Aβ clearance along perivascular drainage pathway, reduce Aβ accumulation in the brain, and restore memory impairment in Tg-SwDI mice, an animal model of CAA. We therefore tested whether the most common anti-platelet agent, aspirin, also reduced Aβ and rescued cognitive impairment in Tg-SwDI mice, and also whether aspirin affected hemorrhagic complications that can occur in Tg-SwDI mice. Mice aged 4 months were assigned into vehicle-treated and low-dose aspirin-treated groups. Low-dose aspirin for 8 months did not increase hemorrhagic lesions, nor increase resting cerebral blood flow or cerebral vascular reserve in response to hypercapnia or acetylcholine. Subsequently, aspirin did not restore cognitive dysfunction. These results suggest that low-dose aspirin does not have a direct influence on cerebrovascular Aβ metabolism nor aggravate hemorrhagic complications in CAA.

Interaction Between Midlife Blood Glucose and APOE Genotype Predicts Later Alzheimer's Disease Pathology. - Bangen, Katherine J; Himali, Jayandra J; Beiser, Alexa S; Nation, Daniel A; Libon, David J; Fox, Caroline S; Seshadri, Sudha; Wolf, Philip A; McKee, Ann C; Au, Rhoda; Delano-Wood, Lisa (J Alzheimers Dis, 2016)
Elevated blood glucose and the apolipoprotein (APOE) ɛ4 allele have both been associated with increased dementia risk; however, the neuropathological mechanisms underlying these associations remain unclear. We examined the impact of APOE genotype and midlife blood glucose on post-mortem vascular and Alzheimer's disease (AD) neuropathology. Ninety-four participants from the Framingham Heart Study without diagnosed diabetes underwent health examination at midlife and brain autopsy at death. Histopathological measures of vascular and AD neuropathology were obtained and analyzed. Results demonstrated that, among APOE ɛ4 carriers, elevated blood glucose was associated with more severe AD pathology. There was no such relationship with vascular pathology. In a relatively healthy sample with low vascular risk burden, midlife elevated blood glucose was associated with greater AD pathology among APOE ɛ4 carriers. A better understanding of interactive effects of APOE genotype and vascular risk on neuropathology has implications for identification of individuals at risk for decline and long-term preventive treatment.

Intracerebroventricular Infusion of Angiotensin-(1-7) Ameliorates Cognitive Impairment and Memory Dysfunction in a Mouse Model of Alzheimer's Disease. - Uekawa, Ken; Hasegawa, Yu; Senju, Satoru; Nakagata, Naomi; Ma, Mingjie; Nakagawa, Takashi; Koibuchi, Nobutaka; Kim-Mitsuyama, Shokei (J Alzheimers Dis, 2016)
This work was performed to test our hypothesis that angiotensin-(1-7) can ameliorate cognitive impairment and cerebrovascular reactivity in 5XFAD mice, a useful model of Alzheimer's disease. 5XFAD mice received intracerebroventricular infusion of (1) vehicle, (2) angiotensin-(1-7), or (3) angiotensin-(1-7)+A779, a specific Mas receptor antagonist, for 4 weeks. Angiotensin-(1-7), through Mas receptor, significantly ameliorated cognitive impairment in 5XFAD mice. As estimated by acetazolamide-induced increase in cerebral blood flow, angiotensin-(1-7), through Mas receptor, enhanced cerebrovascular reactivity in 5XFAD mice. In conclusion, angiotensin-(1-7)/Mas receptor axis improves cognitive function and cerebrovascular function in a mouse model of Alzheimer's disease.

Japanese Care Location and Medical Procedures for People with Dementia in the Last Month of Life. - Nakanishi, Miharu; Nakashima, Taeko; Shindo, Yumi; Niimura, Junko; Nishida, Atsushi (J Alzheimers Dis, 2016)
BACKGROUND: Dementia-related societies worldwide have called for palliative end-of-life care for those suffering dementia; meanwhile, the Japanese dementia plan was revised on January 2015 to introduce into its objectives the support for end-of-life care via increased social and health care collaboration. OBJECTIVE: The study focus was the use of medical procedures in the last month of life among dementia patients in different care locations in Japan. METHODS: This study was conducted using a retrospective study design. Data from the Survey of Institutions and Establishments for Long-Term Care, which is a nationally representative cross-sectional survey of the public long-term care insurance services, were used. The 6,148 patients who received end-of-life care in their own home, nursing homes, or hospitals in September 2007, 2010, and 2013 were included for analysis. The primary disease of each patient was based on the ICD-10 code; a diagnosis of dementia included F00 (Alzheimer's), F01 (vascular), F02 (other), and F03 (unspecified). RESULTS: Of 6,148 patients, 886 (14.4%) had dementia as a primary disease; most received care in the last month of life in nursing homes (48.0%) or hospitals (44.8%) rather than in their own home (7.2%). Patients were less likely to undergo pain management when their primary disease was dementia (adjusted odds ratio, 0.44; 95% confidence interval, 0.21-0.91). CONCLUSION: Education and policy efforts are required to provide palliative end-of-life care to people with dementia at home. The national dementia plan should also explore possible approaches regarding pain management for dying people who have dementia.
Keywords: Aged, 80 and over; Cross-Sectional Studies; Dementia; Female; Hospitals; Housing; Humans; Japan; Male; Nursing Homes; Pain Management; Retrospective Studies; Terminal Care; Time Factors

Lack of evidence for a role of HHV-6 in the pathogenesis of Alzheimer's disease. - Agostini, Simone; Mancuso, Roberta; Baglio, Francesca; Cabinio, Monia; Hernis, Ambra; Guerini, Franca Rosa; Calabrese, Elena; Nemni, Raffaello; Clerici, Mario (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD), the most common form of dementia worldwide, is associated with impairment in the mechanisms of the clearing of amyloid-β within a scenario of neuroinflammation. The etiopathogenesis of the AD is unclear, but a role for viral infection is suspected to play a role in initiating the disease. We recently described a positive correlation between high titers of HSV-1-specific antibodies (Ab) and the volumes of brain regions typically affected in disease. OBJECTIVE: The exploration of a possible role for Herpesviridae in AD was extended by analyzing HHV-6-specific humoral immunity in individuals with AD or a diagnosis of amnestic mild cognitive impairment (aMCI), a condition that is often prodromic of the development of AD. METHODS: 59 AD, 60 aMCI, and 61 age-matched healthy controls were enrolled in the study. Serum HHV-6 IgG antibody titers and avidity index were tested by ELISA. Two randomly selected subgroups of AD and aMCI in whom HHV-6 serum antibodies were detected underwent brain magnetic resonance imaging (MRI) by 1.5 T scanner. RESULTS: HHV-6 seroprevalence, antibody titers, and avidity were similar in the three groups. No correlation was found between Ab titers or avidity and brain volumes, either overall or in the regions typically affected by disease. CONCLUSIONS: The lack of any relation between humoral immune response against HHV-6 and AD and aMCI seems to rule out a role for this virus in the pathogenesis of AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antibodies; Case-Control Studies; Cognitive Dysfunction; Female; Herpesvirus 1, Human; Herpesvirus 6, Human; Humans; Immunity, Humoral; Magnetic Resonance Imaging; Male; Seroepidemiologic Studies; Temporal Lobe

Measuring Information Processing Speed in Mild Cognitive Impairment: Clinical Versus Research Dichotomy. - Haworth, Judy; Phillips, Michelle; Newson, Margaret; Rogers, Peter J; Torrens-Burton, Anna; Tales, Andrea (J Alzheimers Dis, 2016)
A substantial body of research evidence is indicative of disproportionately slowed information processing speed in a wide range of multi-trial, computer-based, neuroimaging- and electroencephalography-based reaction time (RT) tests in Alzheimer's disease and mild cognitive impairment (MCI). However, in what is arguably a dichotomy between research evidence and clinical practice, RT associated with different brain functions is rarely assessed as part of their diagnosis. Indeed, often only the time taken to perform a single, specific task, commonly the Trail making test (TMT), is measured. In clinical practice therefore, there can be a failure to assess adequately the integrity of the rapid, serial information processing and response, necessary for efficient, appropriate, and safe interaction with the environment. We examined whether a typical research-based RT task could at least match the TMT in differentiating amnestic MCI (aMCI) from cognitively healthy aging at group level. As aMCI is a heterogeneous group, typically containing only a proportion of individuals for whom aMCI represents the early stages of dementia, we examined the ability of each test to provide intra-group performance variation. The results indicate that as well as significant slowing in performance of the operations involved in TMT part B (but not part A), individuals with aMCI also experience significant slowing in RT compared to controls. The results also suggest that research-typical RT tests may be superior to the TMT in differentiating between cognitively healthy aging and aMCI at group level and in revealing the performance variability one would expect from an etiologically heterogeneous disorder such as aMCI.
Keywords: Aged; Aged, 80 and over; Attention; Cognitive Dysfunction; Electroencephalography; Female; Humans; Male; Mental Processes; Mental Status Schedule; Middle Aged; Neuroimaging; Neuropsychological Tests; Photic Stimulation; Reaction Time; Residence Characteristics

A Mercaptoacetamide-Based Class II Histone Deacetylase Inhibitor Increases Dendritic Spine Density via RasGRF1/ERK Pathway. - Song, Jung Min; Sung, You Me; Nam, Jin Han; Yoon, Hyejin; Chung, Andrew; Moffat, Emily; Jung, Mira; Pak, Daniel T S; Kim, Jungsu; Hoe, Hyang-Sook (J Alzheimers Dis, 2016)
BACKGROUND: The accumulation of amyloid-β (Aβ) leads to the loss of dendritic spines and synapses, which is hypothesized to cause cognitive impairments in Alzheimer's disease (AD) patients. In our previous study, we demonstrated that a novel mercaptoacetamide-based class II histone deacetylase inhibitor (HDACI), known as W2, decreased Aβ levels and improved learning and memory in mice. However, the underlying mechanism of this effect is unknown. OBJECTIVE: Because dendritic spine formation is associated with cognitive performance, here we investigated whether HDACI W2 regulates dendritic spine density and its molecular mechanism of action. METHODS: To examine the effect of HDACI W2 on dendritic spine density, we conducted morphological analysis of dendritic spines using GFP transfection and Golgi staining. In addition, to determine the molecular mechanism of W2 effects on spines, we measured the levels of mRNAs and proteins involved in the Ras signaling pathway using quantitative real-time PCR, immunocytochemistry, and western analysis. RESULTS: We found that HDACI W2 altered dendritic spine density and morphology in vitro and in vivo. Additionally, W2 increased the mRNA or protein levels of Ras GRF1 and phospho-ERK. Moreover, knockdown of RasGRF1 and inhibition of ERK activity prevented the W2-mediated spinogenesis in primary hippocampal neurons. CONCLUSION: Our Class II-selective HDACI W2 promotes the formation and growth of dendritic spines in a RasGRF1 and ERK dependent manner in primary hippocampal neurons.
Keywords: Acetamides; Animals; Blotting, Western; Cells, Cultured; Cerebral Cortex; Dendritic Spines; Gene Knockdown Techniques; Green Fluorescent Proteins; Hippocampus; Histone Deacetylase Inhibitors; Immunohistochemistry; MAP Kinase Signaling System; Mice, Inbred C57BL; ras-GRF1; Rats, Sprague-Dawley; Real-Time Polymerase Chain Reaction; Receptors, AMPA; Receptors, N-Methyl-D-Aspartate; RNA, Messenger; Thioglycolates; Transfection

Multimodal Magnetic Resonance Imaging in Alzheimer's Disease Patients at Prodromal Stage. - Eustache, Pierre; Nemmi, Federico; Saint-Aubert, Laure; Pariente, Jérémie; Péran, Patrice (J Alzheimers Dis, 2016)
One objective of modern neuroimaging is to identify markers that can aid in diagnosis, monitor disease progression, and impact long-term drug analysis. In this study, physiopathological modifications in seven subcortical structures of patients with mild cognitive impairment (MCI) due to Alzheimer's disease (AD) were characterized by simultaneously measuring quantitative magnetic resonance parameters that are sensitive to complementary tissue characteristics (e.g., volume atrophy, shape changes, microstructural damage, and iron deposition). Fourteen MCI patients and fourteen matched, healthy subjects underwent 3T-magnetic resonance imaging with whole-brain, T1-weighted, T2*-weighted, and diffusion-tensor imaging scans. Volume, shape, mean R2*, mean diffusivity (MD), and mean fractional anisotropy (FA) in the thalamus, hippocampus, putamen, amygdala, caudate nucleus, pallidum, and accumbens were compared between MCI patients and healthy subjects. Comparisons were then performed using voxel-based analyses of R2*, MD, FA maps, and voxel-based morphometry to determine which subregions showed the greatest difference for each parameter. With respect to the micro- and macro-structural patterns of damage, our results suggest that different and distinct physiopathological processes are present in the prodromal phase of AD. MCI patients had significant atrophy and microstructural changes within their hippocampi and amygdalae, which are known to be affected in the prodromal stage of AD. This suggests that the amygdala is affected in the same, direct physiopathological process as the hippocampus. Conversely, atrophy alone was observed within the thalamus and putamen, which are not directly involved in AD pathogenesis. This latter result may reflect another mechanism, whereby atrophy is linked to indirect physiopathological processes.
Keywords: Aged; Alzheimer Disease; Biomarkers; Brain; Cognitive Dysfunction; Diffusion Tensor Imaging; Female; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Mental Status Schedule; Multimodal Imaging; Neuropsychological Tests; Organ Size; Positron-Emission Tomography; Prodromal Symptoms; Radiopharmaceuticals

Neurophysiological assessment of Alzheimer's disease individuals by a single electroencephalographic marker. - Lizio, Roberta; Del Percio, Claudio; Marzano, Nicola; Soricelli, Andrea; Yener, Görsev G; Başar, Erol; Mundi, Ciro; De Rosa, Salvatore; Triggiani, Antonio Ivano; Ferri, Raffaele; Arnaldi, Dario; Nobili, Flavio Mariano; et al. (J Alzheimers Dis, 2016)
Here we presented a single electroencephalographic (EEG) marker for a neurophysiological assessment of Alzheimer's disease (AD) patients already diagnosed by current guidelines. The ability of the EEG marker to classify 127 AD individuals and 121 matched cognitively intact normal elderly (Nold) individuals was tested. Furthermore, its relationship to AD patients' cognitive status and structural brain integrity was examined. Low-resolution brain electromagnetic tomography (LORETA) freeware estimated cortical sources of resting state eyes-closed EEG rhythms. The EEG marker was defined as the ratio between the activity of parieto-occipital cortical sources of delta (2-4 Hz) and low-frequency alpha (8-10.5 Hz) rhythms. Results showed 77.2% of sensitivity in the recognition of the AD individuals; 65% of specificity in the recognition of the Nold individuals; and 0.75 of area under the receiver-operating characteristic curve. Compared to the AD subgroup with the EEG maker within one standard deviation of the Nold mean (EEG-), the AD subgroup with EEG+ showed lower global cognitive status, as revealed by Mini-Mental State Evaluation score, and more abnormal values of white-matter and cerebrospinal fluid normalized volumes, as revealed by structural magnetic resonance imaging. We posit that cognitive and functional status being equal, AD patients with EEG+ should receive special clinical attention due to a neurophysiological "frailty". EEG+ label can be also used in clinical trials (i) to form homogeneous groups of AD patients diagnosed by current guidelines and (ii) as end-point to evaluate intervention effects.
Keywords: Aged; Alzheimer Disease; Biomarkers; Brain Mapping; Case-Control Studies; Cognition Disorders; Electroencephalography; Female; Humans; Italy; Magnetic Resonance Imaging; Male; Middle Aged; Occipital Lobe; Rest; ROC Curve; Turkey

Novel Mutation (Gly212Val) in the PS2 Gene Associated with Early-Onset Familial Alzheimer's Disease. - Marín-Muñoz, Juan; Noguera-Perea, Ma Fuensanta; Gómez-Tortosa, Estrella; López-Motos, David; Antequera-Torres, Martirio; Martínez-Herrada, Begoña; Manzanares-Sánchez, Salvadora; Vivancos-Moreau, Laura; Legaz-García, Agustina; Rábano-Gutiérrez Del Arroyo, Alberto; Antúnez-Almagro, Carmen (J Alzheimers Dis, 2016)
Mutations in the presenilin 2 gene (PS2) are an extremely rare cause of early-onset autosomal dominant Alzheimer's disease (AD), accounting for only 5% of these families. These cases represent a particular model of AD, and the scarcity of reports on their clinical phenotypes makes them of great interest. We report a family with early-onset autosomal dominant AD in four members, where the two living siblings were found to carry the novel PS2 mutation Gly212Val (exon 7, transmembrane domain IV) with highly predicted pathogenicity. Age at onset ranged from 60 to 65 years and three of the cases died between ages 74 and 76 years. Clinical phenotype was quite homogeneous among affected members of the family, and overall features, including cognitive decline, tau/p-tau and amyloid-β cerebrospinal fluid markers, neuroimaging, and neuropathology were consistent with typical AD. Lewy bodies were present but restricted to the amygdala.

A Novel Small Molecule Modulator of Amyloid Pathology. - Lovell, Mark A; Lynn, Bert C; Fister, Shuling; Bradley-Whitman, Melissa; Murphy, M Paul; Beckett, Tina L; Norris, Christopher M (J Alzheimers Dis, 2016)
Because traditional approaches to drug development for Alzheimer's disease are becoming increasingly expensive and in many cases disappointingly unsuccessful, alternative approaches are required to shift the paradigm. Following leads from investigations of dihydropyridine calcium channel blockers, we observed unique properties from a class of functionalized naphthyridines and sought to develop these as novel therapeutics that minimize amyloid pathology without the adverse effects associated with current therapeutics. Our data show methyl 2,4-dimethyl-5-oxo-5,6-dihydrobenzo[c][2,7]naphthyridine-1-carboxylate (BNC-1) significantly decreases amyloid burden in a well-established mouse model of amyloid pathology through a unique mechanism mediated by Elk-1, a transcriptional repressor of presenilin-1. Additionally, BNC-1 treatment leads to increased levels of synaptophysin and synapsin, markers of synaptic integrity, but does not adversely impact presenilin-2 or processing of Notch-1, thus avoiding negative off target effects associated with pan-gamma secretase inhibition. Overall, our data show BNC-1 significantly decreases amyloid burden and improves markers of synaptic integrity in a well-established mouse model of amyloid deposition by promoting phosphorylation and activation of Elk-1, a transcriptional repressor of presenilin-1 but not presenilin-2. These data suggest BNC-1 might be a novel, disease-modifying therapeutic that will alter the pathogenesis of Alzheimer's disease.

Older Adults Taking AT1-Receptor Blockers Exhibit Reduced Cerebral Amyloid Retention. - Nation, Daniel A; Ho, Jean; Yew, Belinda (J Alzheimers Dis, 2016)
BACKGROUND: Evidence suggests that angiotensin II AT1-receptor blockers (ARBs) may be protective against dementia, and studies in transgenic animals indicate that this may be due to improved amyloid-β (Aβ) clearance. OBJECTIVE: We investigated whether taking ARBs was associated with an attenuation of age-related increases in cerebral Aβ retention, and reduced progression to dementia. METHODS: Eight hundred seventy-one stroke-free and dementia-free older adults from the Alzheimer's Disease Neuroimaging Initiative (ADNI) study underwent baseline lumbar puncture, and a subgroup (n = 124) underwent 12 and 24 month follow-up lumbar puncture. Participants were followed at variable intervals for clinical progression to dementia. Linear mixed models and ANCOVA compared ARBs users with those taking other antihypertensives (O-antiHTN) or no antihypertensives (No-antiHTN) on cerebrospinal fluid (CSF) Aβ and phosphorylated tau (P-tau) levels. Cox regression and chi-square analyses compared groups on progression to dementia. RESULTS: ARBs users exhibited greater vascular risk and lower educational attainment than the No-antiHTN group. Longitudinal analyses indicated higher CSF Aβ and lower P-tau in ARBs users versus other groups. Cross-sectional analyses revealed age-related decreases in CSF Aβ in other groups but not ARBs users. ARBs users were less likely to progress to dementia and showed reduced rate of progression relative to the No-antiHTN group. DISCUSSION: Patients taking ARBs showed an attenuation of age-related decreases in CSF Aβ, a finding that is consistent with studies done in transgenic animals. These findings may partly explain why ARBs users show reduced progression to dementia despite their lower educational attainment and greater vascular risk burden.
Keywords: Aged; Aged, 80 and over; Aging; Amyloid beta-Peptides; Angiotensin Receptor Antagonists; Antihypertensive Agents; Chi-Square Distribution; Cross-Sectional Studies; Dementia; Female; Humans; Longitudinal Studies; Male; Middle Aged; Peptide Fragments; Psychiatric Status Rating Scales; Regression Analysis; tau Proteins; Time Factors

An Oral Aβ Vaccine Using a Recombinant Adeno-Associated Virus Vector in Aged Monkeys: Reduction in Plaque Amyloid and Increase in Aβ Oligomers. - Hara, Hideo; Ono, Fumiko; Nakamura, Shinichiro; Matsumoto, Shin-Ei; Jin, Haifeng; Hattori, Nobutaka; Tabira, Takeshi (J Alzheimers Dis, 2016)
With the objective to improve the amyloid-β (Aβ) targeting immunotherapy, we investigated the safety and efficacy of an oral vaccine with recombinant adeno-associated virus vector carrying a signal sequence and Aβ1-43 cDNA (rAAV/Aβ) in old non-human primates, 12 African green and 10 cynomolgus monkeys. The enteric-dissolving coated capsules containing rAAV/Aβ were orally administered once or twice, then monkeys' conditions were carefully observed with complete blood count and laboratory examinations of the sera. General conditions, food intake, water intake, stool conditions, body weight changes, and menstruation cycles were not significantly altered, and laboratory tests and pathological examinations of the systemic organs were unremarkable. Pathological examinations of the brain showed significant reduction of the amyloid plaque burden and intracellular Aβ without inflammatory or hemorrhagic changes in the brain. However, soluble Aβ and some Aβ oligomers were increased in rAAV-treated monkey brains without changes of the neuronal density and vascular amyloidosis. Thus, this vaccine seems to be safe in general, but we must be cautious about the increase of Aβ oligomers after vaccination. This vaccine may be recommended at a very early stage of Alzheimer's disease when little amyloid is deposited.

Oral Infections and Cytokine Levels in Patients with Alzheimer's Disease and Mild Cognitive Impairment Compared with Controls. - Cestari, José Augusto Ferrari; Fabri, Gisele Maria Campos; Kalil, Jorge; Nitrini, Ricardo; Jacob-Filho, Wilson; de Siqueira, José Tadeu Tesseroli; Siqueira, Silvia Regina D T (J Alzheimers Dis, 2016)
BACKGROUND: Oral infections are prevalent in the adult population. Their impact includes the implication as a risk factor for Alzheimer's disease (AD), altering its progression. One of the potential mechanisms involves immune mediators such as circulating cytokines. OBJECTIVE: The goal of the present study was to investigate the prevalence of oral infections and blood levels of IL-1β, TNF-α, and IL-6 in patients with AD, mild cognitive impairment (MCI), and controls. METHODS: Sixty-five elderly were evaluated (25 AD, 19 MCI, and 21 controls) by the following methods: Mini Mental State Exam, Questionnaire of Functional Activities, periodontal and oral evaluation, and blood concentrations of IL-1β, TNF-α and IL-6. RESULTS: Patients with AD had high serum IL-6 levels (p = 0.029), and patients with periodontitis had high serum TNF-α levels (p = 0.005). There was an association between IL-6 and TNF-α in patients with AD/MCI and periodontitis (p = 0.023). CONCLUSION: The increased levels of TNF-α and IL-6 in this study suggests their implication in the overlapping mechanisms between oral infections and AD. Longitudinal studies are necessary for further investigation.

Paired Studies Comparing Clinical Profiles of Lewy Body Dementia with Alzheimer's and Parkinson's Diseases. - Scharre, Douglas W; Chang, Shu-Ing; Nagaraja, Haikady N; Park, Ariane; Adeli, Anahita; Agrawal, Punit; Kloos, Anne; Kegelmeyer, Deb; Linder, Shannon; Fritz, Nora; Kostyk, Sandra K; Kataki, Maria (J Alzheimers Dis, 2016)
Limited data compares clinical profiles of Lewy Body Dementia (LBD) with Alzheimer's disease (AD) and Parkinson's disease (PD). Twenty-one mildly demented ambulatory LBD subjects were individually matched by MMSE score with 21 AD subjects and by UPDRS motor score with 21 PD subjects. Matched by age, gender, education, and race, pairs were compared using cognitive, functional, behavioral, and motor measures. LBD group performed worse than PD on axial motor, gait, and balance measures. AD had more amnesia and orientation impairments, but less executive and visuospatial deficits than LBD subjects. LBD group had more sleepiness, cognitive/behavioral fluctuations, hallucinations, and sleep apnea than AD or PD. Axial motor, gait, and balance disturbances correlated with executive, visuospatial, and global cognition deficits. LBD is differentiated from AD and PD by retrieval memory, visuospatial, and executive deficits; axial motor, gait and balance impairments; sleepiness, cognitive/behavioral fluctuations, hallucinations, and sleep apnea.

A Pathway Based Classification Method for Analyzing Gene Expression for Alzheimer's Disease Diagnosis. - Voyle, Nicola; Keohane, Aoife; Newhouse, Stephen; Lunnon, Katie; Johnston, Caroline; Soininen, Hilkka; Kloszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Lovestone, Simon; Hodges, Angela; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Recent studies indicate that gene expression levels in blood may be able to differentiate subjects with Alzheimer's disease (AD) from normal elderly controls and mild cognitively impaired (MCI) subjects. However, there is limited replicability at the single marker level. A pathway-based interpretation of gene expression may prove more robust. OBJECTIVES: This study aimed to investigate whether a case/control classification model built on pathway level data was more robust than a gene level model and may consequently perform better in test data. The study used two batches of gene expression data from the AddNeuroMed (ANM) and Dementia Case Registry (DCR) cohorts. METHODS: Our study used Illumina Human HT-12 Expression BeadChips to collect gene expression from blood samples. Random forest modeling with recursive feature elimination was used to predict case/control status. Age and APOE ɛ4 status were used as covariates for all analysis. RESULTS: Gene and pathway level models performed similarly to each other and to a model based on demographic information only. CONCLUSIONS: Any potential increase in concordance from the novel pathway level approach used here has not lead to a greater predictive ability in these datasets. However, we have only tested one method for creating pathway level scores. Further, we have been able to benchmark pathways against genes in datasets that had been extensively harmonized. Further work should focus on the use of alternative methods for creating pathway level scores, in particular those that incorporate pathway topology, and the use of an endophenotype based approach.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Cohort Studies; Datasets as Topic; Female; Gene Expression; Gene Expression Profiling; Humans; Male; Models, Genetic; Oligonucleotide Array Sequence Analysis; Signal Transduction

Patients that have Undergone Hemodialysis Exhibit Lower Amyloid Deposition in the Brain: Evidence Supporting a Therapeutic Strategy for Alzheimer's Disease by Removal of Blood Amyloid. - Sakai, Kazuyoshi; Senda, Takao; Hata, Ryuji; Kuroda, Makoto; Hasegawa, Midori; Kato, Masao; Abe, Masato; Kawaguchi, Kazunori; Nakai, Shigeru; Hiki, Yoshiyuki; Yuzawa, Yukio; Kitaguchi, Nobuya (J Alzheimers Dis, 2016)
As a proof of concept that removal of blood amyloid-β (Aβ) can reduce Aβ deposition in the brains of patients with Alzheimer's disease, cortices of patients who had undergone hemodialysis (HD), which removes Aβ from the blood, were histochemically analyzed; postmortem brain sections were stained with anti-Aβ antibodies. Brains from patients who had undergone HD had significantly fewer senile plaques than those of patient who had not undergone HD. This significant difference was also confirmed by silver staining. Our findings suggest that removal of blood Aβ by hemodialysis results in lower accumulation of Aβ in the brain.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Autopsy; Brain; Case-Control Studies; Humans; Kidney Diseases; Plaque, Amyloid; Renal Dialysis; Silver Staining; Statistics, Nonparametric

Perfusion Neuroimaging Abnormalities Alone Distinguish National Football League Players from a Healthy Population. - Amen, Daniel G; Willeumier, Kristen; Omalu, Bennet; Newberg, Andrew; Raghavendra, Cauligi; Raji, Cyrus A (J Alzheimers Dis, 2016)
BACKGROUND: National Football League (NFL) players are exposed to multiple head collisions during their careers. Increasing awareness of the adverse long-term effects of repetitive head trauma has raised substantial concern among players, medical professionals, and the general public. OBJECTIVE: To determine whether low perfusion in specific brain regions on neuroimaging can accurately separate professional football players from healthy controls. METHOD: A cohort of retired and current NFL players (n = 161) were recruited in a longitudinal study starting in 2009 with ongoing interval follow up. A healthy control group (n = 124) was separately recruited for comparison. Assessments included medical examinations, neuropsychological tests, and perfusion neuroimaging with single photon emission computed tomography (SPECT). Perfusion estimates of each scan were quantified using a standard atlas. We hypothesized that hypoperfusion particularly in the orbital frontal, anterior cingulate, anterior temporal, hippocampal, amygdala, insular, caudate, superior/mid occipital, and cerebellar sub-regions alone would reliably separate controls from NFL players. Cerebral perfusion differences were calculated using a one-way ANOVA and diagnostic separation was determined with discriminant and automatic linear regression predictive models. RESULTS: NFL players showed lower cerebral perfusion on average (p < 0.01) in 36 brain regions. The discriminant analysis subsequently distinguished NFL players from controls with 90% sensitivity, 86% specificity, and 94% accuracy (95% CI 95-99). Automatic linear modeling achieved similar results. Inclusion of age and clinical co-morbidities did not improve diagnostic classification. CONCLUSION: Specific brain regions commonly damaged in traumatic brain injury show abnormally low perfusion on SPECT in professional NFL players. These same regions alone can distinguish this group from healthy subjects with high diagnostic accuracy. This study carries implications for the neurological safety of NFL players.

Peripheral Administration of GSK-3β Antisense Oligonucleotide Improves Learning and Memory in SAMP8 and Tg2576 Mouse Models of Alzheimer's Disease. - Farr, Susan A; Sandoval, Karin E; Niehoff, Michael L; Witt, Ken A; Kumar, Vijaya B; Morley, John E (J Alzheimers Dis, 2016)
Glycogen synthase kinase (GSK)-3β is a multifunctional protein that has been implicated in the pathological characteristics of Alzheimer's disease (AD), including the heightened levels of neurofibrillary tangles, amyloid-beta (Aβ), and neurodegeneration. We have previously shown that an antisense oligonucleotide directed at the Tyr 216 site on GSK-3β (GAO) when injected centrally can decrease GSK-3β levels, improve learning and memory, and decrease oxidative stress. In addition, we showed that GAO can cross the blood-brain barrier. Herein the impact of peripherally administered GAO in both the non-transgenic SAMP8 and transgenic Tg2576 (APPswe) models of AD were examined respective to learning and memory. Brain tissues were then evaluated for expression changes in the phosphorylated-Tyr 216 residue, which leads to GSK-3β activation, and the phosphorylated-Ser9 residue, which reduces GSK-3β activity. SAMP8 GAO-treated mice showed improved acquisition and retention using aversive T-maze, and improved declarative memory as measured by the novel object recognition (NOR) test. Expression of the phosphorylated-Tyr 216 was decreased and the phosphorylated-Ser9 was increased in GAO-treated SAMP8 mice. Tg2576 GAO-treated mice improved acquisition and retention in both the T-maze and NOR tests, with an increased phosphorylated-Ser9 GSK-3β expression. Results demonstrate that peripheral administration of GAO improves learning and memory, corresponding with alterations in GSK-3β phosphorylation state. This study supports peripherally administered GAO as a viable means to mediate GSK-3β activity within the brain and a possible treatment for AD.

A Phase II, Randomized, Double-Blind, Placebo-Controlled Study of Safety, Pharmacokinetics, and Biomarker Results of Subcutaneous Bapineuzumab in Patients with mild to moderate Alzheimer's disease. - Brody, Mark; Liu, Enchi; Di, Jianing; Lu, Ming; Margolin, Richard A; Werth, John L; Booth, Kevin; Shadman, Anna; Brashear, H Robert; Novak, Gerald (J Alzheimers Dis, 2016)
BACKGROUND: Bapineuzumab, a humanized monoclonal antibody, targets amyloid-β (Aβ1-40/1 -42) that is believed to play a key role in the pathogenesis of Alzheimer disease (AD). OBJECTIVES: To assess the effects of monthly subcutaneous (SC) bapineuzumab versus placebo on cerebral amyloid signal in amyloid-positive patients with mild to moderate AD. The incidence of amyloid-related imaging abnormalities-edema/effusion (ARIA-E), pharmacokinetics, pharmacodynamics, immunogenicity, and other safety aspects of bapineuzumab were also evaluated. METHODS: In this multicenter, double-blind study, 146 patients were randomized (1 : 1:1 : 1) to SC bapineuzumab 2, 7, or 20 mg/month or placebo. Lack of efficacy of intravenous (IV) bapineuzumab in Phase III studies led to truncation of the treatment duration from 24 months to 12 months. Primary endpoint: change from baseline to month 12 in brain amyloid signal as measured by standardized uptake value ratio (SUVR) using florbetapir positron emission tomography (PET). RESULTS: Florbetapir PET SUVR decreased significantly (p = 0.038) from baseline to month 12 for the bapineuzumab 7 mg/month group only; reductions versus placebo were not significant for any dosage. One patient each in bapineuzumab 2 mg/month and 20 mg/month groups had ARIA-E. The percentages of patients with treatment-emergent adverse events were similar in placebo (77.8%) and bapineuzumab 2 mg/month (78.4%) group, but higher in 7 mg/month (94.4%) and 20 mg/month (89.2%) groups. CONCLUSION: Bapineuzumab SC once-monthly did not demonstrate significant treatment difference over placebo on cerebral amyloid signal at one year but was well-tolerated. There was less ARIA-E than had been expected based on prior experience with comparable exposure on IV bapineuzumab.

PiB-PET Imaging-Based Serum Proteome Profiles Predict Mild Cognitive Impairment and Alzheimer's Disease. - Kang, Seokjo; Jeong, Hyobin; Baek, Je-Hyun; Lee, Seung-Jin; Han, Sun-Ho; Cho, Hyun Jin; Kim, Hee; Hong, Hyun Seok; Kim, Young Ho; Yi, Eugene C; Seo, Sang Won; Na, Duk L; et al. (J Alzheimers Dis, 2016)
Development of a simple, non-invasive early diagnosis platform of Alzheimer's disease (AD) using blood is urgently required. Recently, PiB-PET imaging has been shown to be powerful to quantify amyloid-β plaque loads leading to pathophysiological alterations in AD brains. Thus, there has been a need for serum biomarkers reflecting PiB-PET imaging data as an early diagnosis platform of AD. Here, using LC-MS/MS analysis coupled with isobaric tagging, we performed comprehensive proteome profiling of serum samples from cognitively normal controls, mild cognitive impairment (MCI), and AD patients, who were selected using PiB-PET imaging. Comparative analysis of the proteomes revealed 79 and 72 differentially expressed proteins in MCI and AD, respectively, compared to controls. Integrated analysis of these proteins with genomic and proteomic data of AD brain tissues, together with network analysis, identified three biomarker candidates representing the altered proteolysis-related process in MCI or AD: proprotein convertase subtilisin/kexin type 9 (PCSK9), coagulation factor XIII, A1 polypeptide (F13A1), and dermcidin (DCD). In independent serum samples of MCI and AD, we confirmed the elevation of the candidates using western blotting and ELISA. Our results suggest that these biomarker candidates can serve as a potential non-invasive early diagnosis platform reflecting PiB-PET imaging for MCI and AD.

The Polyphenol Oleuropein Aglycone Modulates the PARP1-SIRT1 Interplay: An In Vitro and In Vivo Study. - Luccarini, Ilaria; Pantano, Daniela; Nardiello, Pamela; Cavone, Leonardo; Lapucci, Andrea; Miceli, Caterina; Nediani, Chiara; Berti, Andrea; Stefani, Massimo; Casamenti, Fiorella (J Alzheimers Dis, 2016)
Poly(ADP-ribose) polymerase-1 (PARP1) activation contributes to the cascade of events initiated by amyloid-β (Aβ) peptide eventually leading to cell death in Alzheimer's disease brain. A significant accumulation of PAR polymers and increase of PARP1 expression were detected in the cortex at the early (3.5 months) and intermediate (6 months) stage of Aβ deposition in the TgCRND8 mouse model. Our previous data highlighted the beneficial effects of oleuropein aglycone (OLE), the main polyphenol found in the olive oil, against neurodegeneration both in cultured cells and in model organisms. Here we found that 8-week OLE treatment (50 mg/kg of diet) to 6-month-old TgCRND8 mice rescued to control values PARP1 activation and the levels of its product, PAR. In N2a neuroblastoma cells, PARP1 activation and PAR formation upon exposure to N-methyl-N'-nitro-N-nitrosoguanidine (MNNG) were abolished by pretreatment for 24 h with either OLE (100μM) or PARP inhibitors. A significant reduction of the NAD+ content, compared to controls, was found in N2a cells exposed to MNNG (100μM) for 90 min; the latter was slightly attenuated by cell treatment for 24 h with PJ-34 or with OLE. In vitro and in vivo, the OLE-induced reduction of PARP1 activation was paralleled by the overexpression of Sirtuin1 (SIRT1), and, in vivo, by a decrease of NF-κB and the pro-apoptotic marker p53. In N2a cells, we also found that OLE potentiates the MNNG-induced increase of Beclin1 levels. In conclusion, our data show that OLE treatment counteracts neuronal damage through modulation of the PARP1-SIRT1 interplay.

A Potential VEP Biomarker for Mild Cognitive Impairment: Evidence from Selective Visual Deficit of Higher-Level Dorsal Pathway. - Yamasaki, Takao; Horie, Shizuka; Ohyagi, Yasumasa; Tanaka, Eri; Nakamura, Norimichi; Goto, Yoshinobu; Kanba, Shigenobu; Kira, Jun-Ichi; Tobimatsu, Shozo (J Alzheimers Dis, 2016)
Visual dysfunctions are common in Alzheimer's disease (AD). Our aim was to establish a neurophysiological biomarker for amnestic mild cognitive impairment (aMCI). Visual evoked potentials (VEPs) were recorded in aMCI patients who later developed AD (n = 15) and in healthy older (n = 15) and younger controls (n = 15). Visual stimuli were optimized to separately activate lower and higher levels of the ventral and dorsal streams. We compared VEP parameters across the three groups of participants and conducted a linear correlation analysis between VEPs and data from neuropsychological tests. We then used a receiver operating characteristic (ROC) analysis to discriminate those with aMCI from those who were healthy older adults. The latency and phase of VEPs to lower-level stimuli (chromatic and achromatic gratings) were significantly affected by age but not by cognitive decline. Conversely, VEP latencies for higher-ventral (faces and kanji-words) and dorsal (kana-words and optic flow motion) stimuli were not affected by age, but they were significantly prolonged in aMCI patients. Interestingly, VEPs for higher-dorsal stimuli were related to outcomes of neuropsychological tests. Furthermore, the ROC analysis showed that the highest areas under the curve were obtained for VEP latencies in response to higher-dorsal stimuli. These results suggest aMCI-related functional impairment specific to higher-level visual processing. Further, dysfunction in the higher-level of the dorsal stream could be an early indicator of cognitive decline. Therefore, we conclude that VEPs associated with higher-level dorsal stream activity can be a sensitive biomarker for early detection of aMCI.

PRNP P39L Variant is a Rare Cause of Frontotemporal Dementia in Italian Population. - Oldoni, Emanuela; Fumagalli, Giorgio G; Serpente, Maria; Fenoglio, Chiara; Scarioni, Marta; Arighi, Andrea; Bruno, Giuseppe; Talarico, Giuseppina; Confaloni, Annamaria; Piscopo, Paola; Nacmias, Benedetta; Sorbi, Sandro; et al. (J Alzheimers Dis, 2016)
The missense P39L variant in the prion protein gene (PRNP) has recently been associated with frontotemporal dementia (FTD). Here, we analyzed the presence of the P39L variant in 761 patients with FTD and 719 controls and found a single carrier among patients. The patient was a 67-year-old male, with a positive family history for dementia, who developed apathy, short term memory deficit, and postural instability at 66. Clinical and instrumental workup excluded prion disease. At MRI, bilateral frontal lobe atrophy was present. A diagnosis of FTD was made, with a mainly apathetic phenotype. The PRNP P39L mutation may be an extremely rare cause of FTD (0.13%).
Keywords: Aged; Atrophy; Frontal Lobe; Frontotemporal Dementia; Genetic Predisposition to Disease; Humans; Italy; Language; Magnetic Resonance Imaging; Male; Memory Disorders; Memory, Short-Term; Neuropsychological Tests; Prion Proteins; Prions; Temporal Lobe

Promising Role of Neuromodulation in Predicting the Progression of Mild Cognitive Impairment to Dementia. - Naro, Antonino; Corallo, Francesco; De Salvo, Simona; Marra, Angela; Di Lorenzo, Giuseppe; Muscarà, Nunzio; Russo, Margherita; Marino, Silvia; De Luca, Rosaria; Bramanti, Placido; Calabrò, Rocco Salvatore (J Alzheimers Dis, 2016)
The differential diagnosis of mild cognitive impairment (MCI) and Alzheimer's disease (AD) is not always straightforward, and the rate of progression of MCI to dementia is not negligible. Thus, there is a need for para-clinical approaches that can improve the differential diagnosis and identify patients that are at risk of progression. There is a growing interest, at present, in the role of the deterioration of brain oscillations as a predictor of MCI-to-AD conversion. For this reason, we experimentally modulated γ-band oscillations (GBO) in a sample of MCI and AD patients and an age-matched healthy elderly group, using a transcranial alternating current stimulation (tACS) protocol that was applied to different cortical sites. We correlated the after-effects of tACS on the GBO and the neuropsychological data, in an attempt to differentiate MCI from AD patients and identify, among the MCI patients, those that could be at potential risk of MCI-to-dementia conversion. MCI patients showed a partial GBO increase and improvement in some neuropsychological tests whereas AD individuals did not show significant tACS after-effects. Notably, some MCI subjects lacked significant neuropsychological and electrophysiological after-effects, similar to AD individuals. In a two-year follow-up, such MCI individuals had converted into AD. Therefore, our data suggest that tACS may support the clinical differential diagnosis of MCI and AD and identify MCI patients who could be at risk of developing dementia. This prediction index may help the clinician to adopt a better prevention/follow-up strategy in such a disabling neurodegenerative disease.

Protein Kinase Activity Decreases with Higher Braak Stages of Alzheimer's Disease Pathology. - Rosenberger, Andrea F N; Hilhorst, Riet; Coart, Elisabeth; García Barrado, Leandro; Naji, Faris; Rozemuller, Annemieke J M; van der Flier, Wiesje M; Scheltens, Philip; Hoozemans, Jeroen J M; van der Vies, Saskia M (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by a long pre-clinical phase (20-30 years), during which significant brain pathology manifests itself. Disease mechanisms associated with pathological hallmarks remain elusive. Most processes associated with AD pathogenesis, such as inflammation, synaptic dysfunction, and hyper-phosphorylation of tau are dependent on protein kinase activity. The objective of this study was to determine the involvement of protein kinases in AD pathogenesis. Protein kinase activity was determined in postmortem hippocampal brain tissue of 60 patients at various stages of AD and 40 non-demented controls (Braak stages 0-VI) using a peptide-based microarray platform. We observed an overall decrease of protein kinase activity that correlated with disease progression. The phosphorylation of 96.7% of the serine/threonine peptides and 37.5% of the tyrosine peptides on the microarray decreased significantly with increased Braak stage (p-value <0.01). Decreased activity was evident at pre-clinical stages of AD pathology (Braak I-II). Increased phosphorylation was not observed for any peptide. STRING analysis in combination with pathway analysis and identification of kinases responsible for peptide phosphorylation showed the interactions between well-known proteins in AD pathology, including the Ephrin-receptor A1 (EphA1), a risk gene for AD, and sarcoma tyrosine kinase (Src), which is involved in memory formation. Additionally, kinases that have not previously been associated with AD were identified, e.g., protein tyrosine kinase 6 (PTK6/BRK), feline sarcoma oncogene kinase (FES), and fyn-associated tyrosine kinase (FRK). The identified protein kinases are new biomarkers and potential drug targets for early (pre-clinical) intervention.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Female; Hippocampus; Humans; Male; Middle Aged; Phosphorylation; Protein Kinases; Protein-Serine-Threonine Kinases; Severity of Illness Index

Quantitative Neuroimaging Software for Clinical Assessment of Hippocampal Volumes on MR Imaging. - Ahdidan, Jamila; Raji, Cyrus A; DeYoe, Edgar A; Mathis, Jedidiah; Noe, Karsten Ø; Rimestad, Jens; Kjeldsen, Thomas K; Mosegaard, Jesper; Becker, James T; Lopez, Oscar (J Alzheimers Dis, 2016)
BACKGROUND: Multiple neurological disorders including Alzheimer's disease (AD), mesial temporal sclerosis, and mild traumatic brain injury manifest with volume loss on brain MRI. Subtle volume loss is particularly seen early in AD. While prior research has demonstrated the value of this additional information from quantitative neuroimaging, very few applications have been approved for clinical use. Here we describe a US FDA cleared software program, NeuroreaderTM, for assessment of clinical hippocampal volume on brain MRI. OBJECTIVE: To present the validation of hippocampal volumetrics on a clinical software program. METHOD: Subjects were drawn (n = 99) from the Alzheimer Disease Neuroimaging Initiative study. Volumetric brain MR imaging was acquired in both 1.5 T (n = 59) and 3.0 T (n = 40) scanners in participants with manual hippocampal segmentation. Fully automated hippocampal segmentation and measurement was done using a multiple atlas approach. The Dice Similarity Coefficient (DSC) measured the level of spatial overlap between NeuroreaderTM and gold standard manual segmentation from 0 to 1 with 0 denoting no overlap and 1 representing complete agreement. DSC comparisons between 1.5 T and 3.0 T scanners were done using standard independent samples T-tests. RESULTS: In the bilateral hippocampus, mean DSC was 0.87 with a range of 0.78-0.91 (right hippocampus) and 0.76-0.91 (left hippocampus). Automated segmentation agreement with manual segmentation was essentially equivalent at 1.5 T (DSC = 0.879) versus 3.0 T (DSC = 0.872). CONCLUSION: This work provides a description and validation of a software program that can be applied in measuring hippocampal volume, a biomarker that is frequently abnormal in AD and other neurological disorders.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Hippocampus; Humans; Image Interpretation, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Software

The Role of Cerebrovascular Disease in Amyloid Deposition. - Noh, Young; Seo, Sang Won; Jeon, Seun; Lee, Jong Min; Kim, Jae Seung; Lee, Jae-Hong; Kim, Jung-Hyun; Kim, Geon Ha; Ye, Byoung Seok; Cho, Hanna; Kim, Hee Jin; Yoon, Cindy W; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Some patients clinically diagnosed with subcortical vascular cognitive impairment (SVCI) have co-morbidity with AD pathology. OBJECTIVE: We investigated topographical differences in amyloid burden between SVCI and Alzheimer's disease type cognitive impairment (ADCI) using [11C] Pittsburgh compound B (PiB) positron emission tomography (PET). The purpose of this study was to investigate the role of cerebrovascular disease (CVD) in amyloid deposition. METHODS: We recruited 44 patients with SVCI and 44 patients with ADCI (amnestic mild cognitive impairment or Alzheimer's disease) with absent or minimal white matter hyperintensities, all with PiB-positive PET scans [PiB+]. As controls, we included 13 participants with normal cognition and PiB-negative scans. We divided the SVCI and ADCI patients into three groups according to global PiB retention ratio of SVCI, and then compared the tertiles in terms of the distribution of PiB retention using statistical parametric mapping analyses. Lobar to global PiB retention ratio and asymmetry indices were also compared between SVCI and ADCI groupsResults: Compared to PiB+ ADCI patients, PiB+ SVCI patients exhibited: 1) increased left-right asymmetry, and increased anterior-posterior difference; and 2) increased PiB retention in the parietal cortex, the occipital cortex and the precuneus-posterior cingulate cortex. In contrast, ADCI patients showed increased PiB retention in the striatum. When stratified by level of PiB retention, each group showed different characteristics. CONCLUSION: Our results showed that the distribution of amyloid deposition differed between patients with PiB+ SVCI and ADCI. These suggest that CVD contribute to and alter the known progression pattern in amyloid deposition in Alzheimer's disease.

Sirtuin 2 Inhibition Improves Cognitive Performance and Acts on Amyloid-β Protein Precursor Processing in Two Alzheimer's Disease Mouse Models. - Biella, Gloria; Fusco, Federica; Nardo, Emanuele; Bernocchi, Ottavia; Colombo, Alessio; Lichtenthaler, Stefan F; Forloni, Gianluigi; Albani, Diego (J Alzheimers Dis, 2016)
The neuropathological hallmarks of Alzheimer's disease (AD) are extracellular plaques built up by the accumulation of the amyloid-β protein precursor (AβPP)-derived peptide β (Aβ), and intracellular tangles of hyperphosphorylated tau protein. Sirtuin 2 (SIRT2) is a member of the sirtuin family, featuring conserved enzymes with deacetylase activity and involved in several cell molecular pathways. We investigated the importance of SIRT2 inhibition in AD. We inhibited SIRT2 by small molecules (AGK-2, AK-7) and examined AβPP metabolism in H4-SW neuroglioma cells overexpressing AβPP and two AD transgenic mouse models (3xTg-AD and APP23). The in vitro studies suggested that the inhibition of SIRT2 reduced Aβ production; in vivo data showed an improvement of cognitive performance in the novel object recognition test, and an effect on AβPP proteolytic processing leading to a reduction of soluble β-AβPP and an increase of soluble α-AβPP protein. In 3xTg-AD mice, we noticed that total tau protein level rose. Overall, our pre-clinical data support a role for SIRT2 inhibition in the improvement of cognitive performance and the modulation of molecular mechanisms relevant for AD, thus deserving attention as possible therapeutic strategy.

The Societal Cost of Dementia in Singapore: Results from the WiSE Study. - Abdin, Edimansyah; Subramaniam, Mythily; Achilla, Evanthia; Chong, Siow Ann; Vaingankar, Janhavi Ajit; Picco, Louisa; Sambasivam, Rajeswari; Pang, Shirlene; Chua, Boon Yiang; Ng, Li Ling; Chua, Hong Choon; Heng, Derrick; et al. (J Alzheimers Dis, 2016)
BACKGROUND: There is currently limited evidence on the economic burden that dementia exerts on multi-ethnic Asian populations. OBJECTIVE: The present study aimed to estimate the economic cost of dementia in Singapore. METHODS: We used data from the Well-being of the Singapore Elderly study, a nationally representative survey of the older Singapore Resident population aged 60 years and above. Generalized linear modeling was used to estimate factors associated with costs. RESULTS: The total cost of dementia in 2013 was estimated at S$532 million (95% CI, S$361 million to S$701 million) while the annual cost per person was estimated at S$10,245 per year (95% CI, S$6,954 to S$12,495). Apart from dementia, higher total societal cost were also significantly associated with older age, Indian ethnicity, and those who were diagnosed with heart problems, stroke, diabetes or depression, whereas being divorced/separated, lower education, and those who were diagnosed with hypertension were significantly associated with lower total societal cost. CONCLUSION: The study provides a rich body of information on healthcare utilization and cost of dementia, which is essential for future planning of services for the elderly population.
Keywords: Adult; Aged, 80 and over; Cost of Illness; Dementia; Female; Humans; Linear Models; Male; Middle Aged; Singapore

Standardized Uptake Value Ratio-Independent Evaluation of Brain Amyloidosis. - Chincarini, Andrea; Sensi, Francesco; Rei, Luca; Bossert, Irene; Morbelli, Silvia; Guerra, Ugo Paolo; Frisoni, Giovanni; Padovani, Alessandro; Nobili, Flavio (J Alzheimers Dis, 2016)
The assessment of in vivo18F images targeting amyloid deposition is currently carried on by visual rating with an optional quantification based on standardized uptake value ratio (SUVr) measurements. We target the difficulties of image reading and possible shortcomings of the SUVr methods by validating a new semi-quantitative approach named ELBA. ELBA involves a minimal image preprocessing and does not rely on small, specific regions of interest (ROIs). It evaluates the whole brain and delivers a geometrical/intensity score to be used for ranking and dichotomic assessment. The method was applied to adniimages 18F-florbetapir images from the ADNI database. Five expert readers provided visual assessment in blind and open sessions. The longitudinal trend and the comparison to SUVr measurements were also evaluated. ELBA performed with area under the roc curve (AUC) = 0.997 versus the visual assessment. The score was significantly correlated to the SUVr values (r = 0.86, p < 10-4). The longitudinal analysis estimated a test/retest error of ≃2.3%. Cohort and longitudinal analysis suggests that the ELBA method accurately ranks the brain amyloid burden. The expert readers confirmed its relevance in aiding the visual assessment in a significant number (85) of difficult cases. Despite the good performance, poor and uneven image quality constitutes the major limitation.

Strong Impact of Chronic Cerebral Hypoperfusion on Neurovascular Unit, Cerebrovascular Remodeling, and Neurovascular Trophic Coupling in Alzheimer's Disease Model Mouse. - Shang, Jingwei; Yamashita, Toru; Zhai, Yun; Nakano, Yumiko; Morihara, Ryuta; Fukui, Yusuke; Hishikawa, Nozomi; Ohta, Yasuyuki; Abe, Koji (J Alzheimers Dis, 2016)
Although chronic cerebral hypoperfusion (CCH) may affect Alzheimer's disease (AD) pathogenesis, the mechanism remains elusive. In the present study, we investigated the role of CCH on an AD mouse model in neurovascular unit, cerebrovascular remodeling, and neurovascular trophic coupling. Moreover, examined protective effect of galantamine. Alzheimer's disease transgenic mice (APP23) were subjected to bilateral common carotid arteries stenosis with ameroid constrictors for slowly progressive cerebral hypoperfusion. CCH exacerbated neuronal loss and decrease of α7 subunit of nicotinic acetylcholine receptors (α7-nAChRs) expression in hippocampus and thalamus at 12 months. Meanwhile, CCH greatly induced advanced glycation end products expression, and blood-brain barrier leakage through observing IgG and MMP9 expressions. Furthermore, a significant number of dramatic enlarged cerebral vessels with remodeling, BDNF/TrkB decreased in neurovascular trophic coupling. The present study demonstrated that CCH strongly enhanced primary AD pathology including neurodegeneration, neurovascular unit disruption, cerebrovascular remodeling and neurovascular trophic coupling damage in AD mice, and that galantamine treatment greatly ameliorated such neuropathologic abnormalities.

A Systematic Review and Meta-Analysis of On-Road Simulator and Cognitive Driving Assessment in Alzheimer's Disease and Mild Cognitive Impairment. - Hird, Megan A; Egeto, Peter; Fischer, Corinne E; Naglie, Gary; Schweizer, Tom A (J Alzheimers Dis, 2016)
BACKGROUND: Many individuals with Alzheimer's disease (AD) and mild cognitive impairment (MCI) are at an increased risk of driving impairment. There is a need for tools with sufficient validity to help clinicians assess driving ability. OBJECTIVE: Provide a systematic review and meta-analysis of the primary driving assessment methods (on-road, cognitive, driving simulation assessments) in patients with MCI and AD. METHODS: We investigated (1) the predictive utility of cognitive tests and domains, and (2) the areas and degree of driving impairment in patients with MCI and AD. Effect sizes were derived and analyzed in a random effects model. RESULTS: Thirty-two articles (including 1,293 AD patients, 92 MCI patients, 2,040 healthy older controls) met inclusion criteria. Driving outcomes included: On-road test scores, pass/fail classifications, errors; caregiver reports; real world crash involvement; and driving simulator collisions/risky behavior. Executive function (ES [95% CI]; 0.61 [0.41, 0.81]), attention (0.55 [0.33, 0.77]), visuospatial function (0.50 [0.34, 0.65]), and global cognition (0.61 [0.39, 0.83]) emerged as significant predictors of driving performance. Trail Making Test Part B (TMT-B, 0.61 [0.28, 0.94]), TMT-A (0.65 [0.08, 1.21]), and Maze test (0.88 [0.60, 1.15]) emerged as the best single predictors of driving performance. Patients with very mild AD (CDR = 0.5) mild AD (CDR = 1) were more likely to fail an on-road test than healthy control drivers (CDR = 0), with failure rates of 13.6%, 33.3% and 1.6%, respectively. CONCLUSION: The driving ability of patients with MCI and AD appears to be related to degree of cognitive impairment. Across studies, there are inconsistent cognitive predictors and reported driving outcomes in MCI and AD patients. Future large-scale studies should investigate the driving performance and associated neural networks of subgroups of AD (very mild, mild, moderate) and MCI (amnestic, non-amnestic, single-domain, multiple-domain).

Time trends in antipsychotic drug use in patients with dementia: a nationwide study. - Nørgaard, Ane; Jensen-Dahm, Christina; Gasse, Christiane; Hansen, Hanne Vibe; Waldemar, Gunhild (J Alzheimers Dis, 2016)
BACKGROUND: Antipsychotics are often used to treat neuropsychiatric symptoms in dementia, but the evidence for effect is limited. Antipsychotics have been associated with increased risk of adverse events and mortality in patients with dementia, leading to safety regulations worldwide. OBJECTIVE: To investigate time trends in use of antipsychotics and other psychotropic drugs in dementia care. METHODS: The study included longitudinal data on all Danish residents ≥65 years. The study population was defined on January 1 of each year from 2000-2012. Data included prescriptions, discharge diagnoses, and somatic and psychiatric comorbidities. Multivariate time trend analyses of psychotropic drug use in patients with dementia within 4-year age bands were performed. RESULTS: Overall, among patients with dementia the prevalence of antipsychotic drug use decreased from 31.3% in 2000 to 20.4% in 2012. The decreasing use of antipsychotics was accompanied by decreasing use of anxiolytics and hypnotics/sedatives, but an increase in the use of antidepressants from 43.3% in 2000 to 53.8% in 2012. These changes were significant across almost all age groups. Treatment intensity among patients using antipsychotics increased as the annual median number of defined daily doses (DDD) increased from 33.3 to 42.0 DDD. CONCLUSIONS: The changing patterns of psychotropic drug use may be caused by warnings against use of antipsychotics. Further research is needed to explore the implications for patient safety.
Keywords: Aged; Aged, 80 and over; Anti-Anxiety Agents; Antidepressive Agents; Antipsychotic Agents; Dementia; Denmark; Drug Prescriptions; Female; Homes for the Aged; Humans; Hypnotics and Sedatives; Longitudinal Studies; Male; Multivariate Analysis; Nursing Homes; Registries

Tract-Specific Correlates of Neuropsychological Deficits in Patients with Subcortical Vascular Cognitive Impairment. - Jung, Na-Yeon; Han, Cheol E; Kim, Hee Jin; Yoo, Sang Wook; Kim, Hee-Jong; Kim, Eun-Joo; Na, Duk L; Lockhart, Samuel N; Jagust, William J; Seong, Joon-Kyung; Seo, Sang Won (J Alzheimers Dis, 2016)
The white matter tract-specific correlates of neuropsychological deficits are not fully established in patients with subcortical vascular cognitive impairment (SVCI), where white matter tract damage may be a critical factor in cognitive impairment. The purpose of this study is to investigate the tract-specific correlates of neuropsychological deficits in SVCI patients using tract-specific statistical analysis (TSSA). We prospectively recruited 114 SVCI patients, and 55 age-, gender-, and education-matched individuals with normal cognition (NC). All participants underwent diffusion weighted imaging and neuropsychological testing. We classified tractography results into fourteen major fiber tracts and analyzed group comparison and correlation with cognitive impairments. Relative to NC subjects, SVCI patients showed decreased fractional anisotropy values in bilateral anterior-thalamic radiation, cingulum, superior-longitudinal fasciculus, uncinate fasciculus, corticospinal tract, and left inferior-longitudinal fasciculus. Focal disruptions in specific tracts were associated with specific cognitive impairments. Our findings suggest that disconnection of specific white matter tracts, especially those neighboring and providing connections between gray matter regions important to certain cognitive functions, may contribute to specific cognitive impairments in SVCI.
Keywords: Aged; Brain; Cerebrovascular Disorders; Cognitive Dysfunction; Diffusion Magnetic Resonance Imaging; Diffusion Tensor Imaging; Female; Gray Matter; Humans; Male; Neural Pathways; Neuropsychological Tests; White Matter

Unstable Body Mass Index and Progression to Probable Alzheimer's Disease Dementia in Patients with Amnestic Mild Cognitive Impairment. - Ye, Byoung Seok; Jang, Eun Young; Kim, Seong Yoon; Kim, Eun-Joo; Park, Sun Ah; Lee, Yunhwan; Hong, Chang Hyung; Choi, Seong Hye; Yoon, Bora; Yoon, Soo Jin; Na, Hae Ri; Lee, Jae-Hong; et al. (J Alzheimers Dis, 2016)
BACKGROUND AND OBJECTIVE: We investigated the influence of body mass index (BMI) status at baseline and changes in BMI over a follow-up period on the development of dementia in amnestic mild cognitive impairment (aMCI) patients. METHODS: The longitudinal data of 747 aMCI patients were used to investigate the relationships among baseline BMI status, subsequent changes in BMI (median follow-up duration: 1.6 years, interquartile range: 1.0-2.3 years), and risk of progression to probable Alzheimer's disease dementia (pADD). The aMCI patients were classified into underweight, normal weight, overweight, and obese subgroups, and further categorized into increased BMI, stable BMI, and decreased BMI subgroups during follow-up using a 4% mean annual change in BMI cut-off value. RESULTS: Compared to the normal weight group, the underweight group had a higher risk of pADD (hazard ratio [HR]: 1.89, 95% confidence interval [CI]: 1.07-3.37) while the obese group had a lower risk (HR: 0.70, 95% CI: 0.49-0.999). After controllingfor baseline BMI status, the decreased BMI (HR: 2.29, 95% CI: 1.41-3.72) and increased BMI (HR: 3.96, 95% CI: 2.62-6.00) groups were at increased risk of progression to pADD. CONCLUSIONS: Our findings suggested that underweight at baseline was associated with a higher risk of progression to pADD, while obesity at baseline predicted a lower risk. Furthermore, significant changes in BMI during the follow-up period reflected an increased risk of progression to pADD, regardless of BMI status at baseline.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Body Mass Index; Body Weight; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Kaplan-Meier Estimate; Longitudinal Studies; Male; Neuropsychological Tests; Registries

Validation of the Spanish version of the Baylor Profound Mental Status Examination. - Salmerón, Sergio; Huedo, Isabel; López-Utiel, Melisa; Soler-Moratalla, Isabel; Flores-Ruano, Teresa; Fernández-Sánchez, Miguel; Noguerón, Alicia; Doody, Rachelle S; Abizanda, Pedro (J Alzheimers Dis, 2016)
BACKGROUND: There are no short valid instruments to evaluate cognitive status in severe Alzheimer's disease (AD) patients in the Spanish language. OBJECTIVE: To validate the Spanish version of the Baylor Profound Mental Status Examination (BPMSE-Sp). METHODS: The Baylor Profound Mental Status Examination (BPMSE) was translated to Spanish and back translated. Validation was conducted in 100 patients with severe probable AD with a Mini-Mental State Examination (MMSE) <12. We assessed internal consistency (Cronbach's alpha), concurrent validity (Pearson's correlations) with the MMSE, Severe Impairment Battery (SIB), Neuropsychiatric Inventory Short Form (NPI-Q) and the Functional Assessment Staging and reliability. RESULTS: The mean age of patients was 84.9; 74% were female; 64% were institutionalized. The mean MMSE was 5.6; the mean BPMSE-Sp was 13.6; the mean BPMSE-Sp behavior was 1.2; the mean SIB was 42.2; and the mean NPI-Q was 4.7. BPMSE-Sp presented good internal consistency (Cronbach α= 0.84). There were significant correlations between the BPMSE-Sp and MMSE (r = 0.86, p <  0.001), and between the BPMSE-Sp and SIB (r = 0.92, p <  0.001). Inter-rater and test-retest reliability were in both cases excellent, ranging between 0.96 and 0.99 (p <  0.001). BPMSE-Sp had fewer floor and ceiling effects than the MMSE. CONCLUSIONS: The BPMSE-Sp is a valid tool for use in daily practice and research in the evaluation of cognitive function of patients with severe AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Cognition Disorders; Female; Humans; Language; Male; Mental Status Schedule; Neuropsychological Tests; Reproducibility of Results; Severity of Illness Index; Spain

The Vanderbilt Memory & Aging Project: Study Design and Baseline Cohort Overview. - Jefferson, Angela L; Gifford, Katherine A; Acosta, Lealani Mae Y; Bell, Susan P; Donahue, Manus J; Davis, L Taylor; Gottlieb, JoAnn; Gupta, Deepak K; Hohman, Timothy J; Lane, Elizabeth M; Libon, David J; Mendes, Lisa A; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Vascular health factors frequently co-occur with Alzheimer's disease (AD). A better understanding of how systemic vascular and cerebrovascular health intersects with clinical and pathological AD may inform prevention and treatment opportunities. OBJECTIVE: To establish the Vanderbilt Memory & Aging Project, a case-control longitudinal study investigating vascular health and brain aging, and describe baseline methodology and participant characteristics. METHODS: From September 2012 to November 2014, 335 participants age 60- 92 were enrolled, including 168 individuals with mild cognitive impairment (MCI, 73±8 years, 41% female) and 167 age-, sex-, and race-matched cognitively normal controls (NC, 72±7 years, 41% female). At baseline, participants completed a physical and frailty examination, fasting blood draw, neuropsychological assessment, echocardiogram, cardiac MRI, and brain MRI. A subset underwent 24-hour ambulatory blood pressure monitoring and lumbar puncture for cerebrospinal fluid (CSF) collection. RESULTS: As designed, participant groups were comparable for age (p = 0.31), sex (p = 0.95), and race (p = 0.65). MCI participants had greater Framingham Stroke Risk Profile scores (p = 0.008), systolic blood pressure values (p = 0.008), and history of left ventricular hypertrophy (p = 0.04) than NC participants. As expected, MCI participants performed worse on all neuropsychological measures (p-values < 0.001), were more likely to be APOEɛ4 carriers (p = 0.02), and had enhanced CSF biomarkers, including lower Aβ42 (p = 0.02), higher total tau (p = 0.004), and higher p-tau (p = 0.02) compared to NC participants. CONCLUSION: Diverse sources of baseline and longitudinal data will provide rich opportunities to investigate pathways linking vascular and cerebrovascular health, clinical and pathological AD, and neurodegeneration contributing to novel strategies to delay or prevent cognitive decline.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Blood Pressure Monitoring, Ambulatory; Brain; Case-Control Studies; Cerebral Angiography; Cognitive Dysfunction; Echocardiography; Epidemiologic Research Design; Female; Follow-Up Studies; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Research Design

Vascular Health Indices and Cognitive Domain Function: Singapore Longitudinal Ageing Studies. - Lim, Shir Lynn; Gao, Qi; Nyunt, Ma Shwe Zin; Gong, Lingli; Lunaria, Josephine B; Lim, May Li; Ling, Audrey; Lam, Carolyn Su-Ping; Richards, Arthur Mark; Ling, Lieng Hsi; Ng, Tze Pin (J Alzheimers Dis, 2016)
BACKGROUND: Few studies have comprehensively evaluated the relationship between vascular disease and cognition of older adults without cardiac disease. OBJECTIVE: We explored the associations of structural atherosclerosis, vascular stiffness, and reactivity with global, memory, attention, language, visuospatial ability, and executive function in community-dwelling, non-demented older Asians without cardiac diseases. METHODS: Cognition was assessed by Mini-Mental State Examination (MMSE) (n = 308) and detailed neuropsychological tests (n = 155). Vascular measures included carotid intima-media thickness; aortic stiffness [carotid-femoral pulse wave velocity (CFPWV), aortic augmentation index (AI), and aortic pulse pressure (PP)]; carotid stiffness [elasticity modulus (Ep), beta index (β), arterial compliance (AC), carotid AI]; and endothelial function [reactive hyperemia index (RHI)]. Multivariable analyses controlled for potential confounding by demographics, apolipoprotein E genotype and cardiovascular risk factors. RESULTS: The participants' mean age was 63.0 ± 6.1 years. Inverse associations with MMSE were found for AC (β= 0.128, p = 0.019), Ep (β= -0.151, p = 0.008), β index (β= -0.122, p = 0.029), carotid stiffness z-score (β= -0.154, p = 0.007); with executive function for CFPWV (β= -0.209, p = 0.026), AC (β= 0.214, p = 0.005), Ep (β= -0.160, p = 0.050), β index (β= -0.165, p = 0.041), and both aortic (β= -0.229, p = 0.010) and carotid (β= -0.208, p = 0.010) stiffness z-scores; with verbal memory for AI (β= -0.229, p = 0.004) and aortic (β= -0.263, p = 0.004) stiffness z-score; with language for AI (β= -0.155, p = 0.025), aortic stiffness z-score (β= -0.196, p = 0.011). RHI positively correlated with visuospatial ability (β= 0.195, p = 0.013) and executive function (β= 0.151, p = 0.045). CONCLUSION: The results support a link between systemic vascular health and neurocognitive function in older Asian adults. Subclinical noninvasive measures of arterial stiffness and reactivity may identify individuals vulnerable to cognitive impairment.
Keywords: Aged; Blood Flow Velocity; Blood Pressure; Cardiovascular Diseases; Carotid Intima-Media Thickness; Cognitive Aging; Female; Humans; Longitudinal Studies; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Singapore; Vascular Stiffness

White Matter and Hippocampal Volume Predict the Risk of Dementia in Patients with Cerebral Small Vessel Disease: The RUN DMC Study. - van Uden, Ingeborg W M; van der Holst, Helena M; Tuladhar, Anil M; van Norden, Anouk G W; de Laat, Karlijn F; Rutten-Jacobs, Loes C A; Norris, David G; Claassen, Jurgen A H R; van Dijk, Ewoud J; Kessels, Roy P C; de Leeuw, Frank-Erik (J Alzheimers Dis, 2016)
BACKGROUND: The relationship between cerebral small vessel disease (SVD) and dementia has been studied without considering white matter (WM) volume, the microstructural integrity of the WM surrounding the SVD, and grey matter (GM). OBJECTIVE: We prospectively investigated the relationship between these structures and the risk of dementia, and formed a prediction model to investigate which characteristics (macro- or microstructural) explained most of the variance. METHODS: The RUN DMC study is a prospective cohort study among 503 non-demented participants with an age between 50 and 85 years at baseline, with baseline assessment in 2006 and follow-up assessment in 2012. Two were lost to follow-up (yielding a 99.6% response-rate). Cox regression analysis was used, to calculate hazard ratios for dementia, of baseline MRI characteristics. Tract-Based Spatial Statistics (TBSS) analysis was used to assess the added value of microstructural integrity of the WM. RESULTS: Mean age at baseline was 65.6 years (SD 8.8) and 56.8% was male. 43 participants developed dementia (8.6%), resulting in a 5.5-year cumulative risk of 11.1% (95% CI 7.7-14.6). Low WM and hippocampal volume are significant predictors for dementia. WM, WM hyperintensities, and hippocampal volume explained most of the variance. TBSS analyses showed no additional value of diffusion parameters. CONCLUSIONS: WM and hippocampal volume were the main predictors for the development of incident dementia at 5-year follow-up in elderly with SVD. There was no additional diagnostic value of the diffusion tensor imaging parameters on top of the macrostructural characteristics.
Keywords: Aged; Cerebral Small Vessel Diseases; Cohort Studies; Dementia; Diffusion Tensor Imaging; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Statistics, Nonparametric; White Matter

The Zebrafish Equivalent of Alzheimer's Disease-Associated PRESENILIN Isoform PS2V Regulates Inflammatory and Other Responses to Hypoxic Stress. - Ebrahimie, Esmaeil; Moussavi Nik, Seyyed Hani; Newman, Morgan; Van Der Hoek, Mark; Lardelli, Michael (J Alzheimers Dis, 2016)
Dominant mutations in the PRESENILIN genes PSEN1 and PSEN2 cause familial Alzheimer's disease (fAD) that usually shows onset before 65 years of age. In contrast, genetic variation at the PSEN1 and PSEN2 loci does not appear to contribute to risk for the sporadic, late onset form of the disease (sAD), leading to doubts that these genes play a role in the majority of AD cases. However, a truncated isoform of PSEN2, PS2V, is upregulated in sAD brains and is induced by hypoxia and high cholesterol intake. PS2V can increase γ-secretase activity and suppress the unfolded protein response (UPR), but detailed analysis of its function has been hindered by lack of a suitable, genetically manipulable animal model since mice and rats lack this PRESENILIN isoform. We recently showed that zebrafish possess an isoform, PS1IV, that is cognate to human PS2V. Using an antisense morpholino oligonucleotide, we can block specifically the induction of PS1IV that normally occurs under hypoxia. Here, we exploit this ability to identify gene regulatory networks that are modulated by PS1IV. When PS1IV is absent under hypoxia-like conditions, we observe changes in expression of genes controlling inflammation (particularly sAD-associated IL1B and CCR5), vascular development, the UPR, protein synthesis, calcium homeostasis, catecholamine biosynthesis, TOR signaling, and cell proliferation. Our results imply an important role for PS2V in sAD as a component of a pathological mechanism that includes hypoxia/oxidative stress and support investigation of the role of PS2V in other diseases, including schizophrenia, when these are implicated in the pathology.

δ Scores are Exportable Across Cultural and Linguistic Boundaries. - Royall, Donald R; Palmer, Raymond F; Matsuoka, Teruyuki; Kato, Yuka; Taniguchi, Shogo; Ogawa, Mayu; Fujimoto, Hiroshi; Okamura, Aiko; Shibata, Keisuke; Nakamura, Kaeko; Nakaaki, Shutaro; Koumi, Hiroyuki; et al. (J Alzheimers Dis, 2016)
The latent variable "δ", can accurately diagnose dementia. Its generalizability across populations is unknown. We constructed a δ homolog ("dT2J") in data collected by the Texas Alzheimer's Research and Care Consortium (TARCC). From this, we calculated a composite d-score "d". We then tested d's generalizability across random subsets of TARCC participants and to a convenience sample of elderly Japanese persons with normal cognition (NC), mild cognitive impairment (MCI), and dementia (AD) (n = 176). dT2J was indicated by Instrumental Activities of Daily Living and psychometric measures. Embedded in this battery were the Mini-Mental Status Examination (MMSE) and an executive clock-drawing task (CLOX). Only MMSE and CLOX were available in both TARCC and the Japanese cohort. Therefore, a second composite variable, "T2J", was constructed solely from the factor loadings of CLOX and MMSE on d. The diagnostic accuracy of T2J was estimated in the validation sample, the remainder of the TARCC cohort, and in the Japanese sample. The areas under the receiver operating curve (AUC; ROC) for T2J were compared in each sample, and against d in TARCC. The AUCs for T2J were statistically indiscriminable within TARCC, and in Japanese persons. In Japanese persons, AUCs for T2J were 0.97 for the discrimination between AD versus NC, 0.86 for AD versus MCI, and 0.79 for NC versus MCI. The AUCs for T2J in Japanese persons were higher than any individual psychometric measure in that sample. Valid d-score composites can be abstracted from a subset of δ's indicators. Moreover, those composites are exportable across cultural and linguistic boundaries.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Cognitive Dysfunction; Cohort Studies; Culture; Executive Function; Female; Humans; Linguistics; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Psychometrics; Reproducibility of Results; ROC Curve; Texas

Amyloid-β and Tau Dynamics in Human Brain Interstitial Fluid in Patients with Suspected Normal Pressure Hydrocephalus. - Herukka, Sanna-Kaisa; Rummukainen, Jaana; Ihalainen, Jouni; von Und Zu Fraunberg, Mikael; Koivisto, Anne M; Nerg, Ossi; Puli, Lakshman K; Seppälä, Toni T; Zetterberg, Henrik; Pyykkö, Okko T; Helisalmi, Seppo; Tanila, Heikki; et al. (J Alzheimers Dis, 2015)
Background: Amyloid-β (Aβ1-42), total tau (T-tau), and phosphorylated tau (P-tau181) in the cerebrospinal fluid (CSF) are the most promising biomarkers of Alzheimer's disease (AD). Still, little is known about the dynamics of these molecules in the living brain. In a transgenic mouse brain, soluble Aβ decreases with increasing age and advanced Aβ pathology as seen similarly in CSF. Objective: To assess the relationship between AD-related pathological changes in human brain tissue, ventricular and lumbar CSF, and brain interstitial fluid (ISF). Methods: Altogether 11 patients with suspected idiopathic normal pressure hydrocephalus underwent frontal cortical brain biopsy, 24-h intraventricular pressure monitoring, and a microdialysis procedure. AD-related biomarkers were analyzed from brain tissue, CSF, and ISF. Results: ISF T-tau levels decreased strongly within the first 12 h, then plateauing until the end of the experiment. Aβ1-42 and P-tau181 remained stable during the experiment (n = 3). T-tau and P-tau were higher in the ISF than in ventricular or lumbar CSF, while Aβ1-42 levels were within similar range in both CSF and ISF samples. ISF P-tau correlated with the ventricular CSF T-tau (r = 0.70, p = 0.017) and P-tau181 (r = 0.64, p = 0.034). Five patients with amyloid pathology in the brain biopsy tended to reveal lower ISF Aβ1-42 levels than those six without amyloid pathology. Conclusions: This is the first study to report ISF Aβ and tau levels in the human brain without significant brain injury. The set-up used enables sampling from the brain ISF for at least 24 h without causing adverse effects due to the microdialysis procedure to follow the dynamics of the key molecules in AD pathogenesis in the living brain at various stages of the disease.

Body Mass Index and Mortality Rate in Korean Patients with Alzheimer's Disease. - Jang, Hyemin; Kim, Jong Hun; Choi, Seong Hye; Lee, Yunhwan; Hong, Chang Hyung; Jeong, Jee Hyang; Han, Hyun Jeong; Moon, So Young; Park, Kyung Won; Han, Seol-Hee; Park, Kee Hyung; Kim, Hee Jin; et al. (J Alzheimers Dis, 2015)
Background: A relationship between body weight, cognitive impairment, and the onset of Alzheimer's disease (AD) was recently reported. However, to our knowledge, no studies have investigated the relationship between body weight and mortality in Asian AD patients. Objective: We evaluated the relationship between body mass index (BMI) and mortality rate in Korean AD cohorts. Methods: Participants were consecutively included from two Korean representative registries: 579 AD patients from Samsung Medical Center and 1911 AD patients from the Clinical Research Center for Dementia of South Korea study. We combined these two AD cohorts to evaluate the association between BMI and mortality. BMI was used to categorize the participants into underweight, normal-weight, overweight, and obesity subgroups. All deaths were confirmed through the nationwide mortality database of Statistics Korea. Results: 53 of 181 (29.3%), 208 of 1,127 (18.5%), 88 of 626 (14.1%), and 115 of 556 (20.7%) patients died in the underweight, normal-weight, overweight, and obese subgroups during 43.7 months of follow-up. The time-dependent cox proportional hazards model showed that, relative to the normal-weight subgroup, the underweight group had higher mortality (HR 1.82 (95% CI, 1.07-3.09)) while overweight group had lower mortality rate (HR 0.60 (95% CI, 0.38-0.95)) The effects of underweight and overweight were prominent in younger and older elderly group, respectively. However, there were no interactive effects of dementia severity or gender and BMI on survival rate. Conclusion: Relative to AD patients of normal weight, those who were underweight had an increased mortality rate, and overweight predicted decreased mortality in AD patients. Furthermore, our findings may help facilitate mortality stratification in AD patients by using baseline BMI.

Buccal Cell Cytokeratin 14 Correlates with Multiple Blood Biomarkers of Alzheimer's Disease Risk. - Leifert, Wayne R; Nguyen, Tori; Rembach, Alan; Martins, Ralph; Rainey-Smith, Stephanie; Masters, Colin L; Ames, David; Rowe, Christopher C; Macaulay, S Lance; François, Maxime; Fenech, Michael F (J Alzheimers Dis, 2015)
Mild cognitive impairment (MCI) may reflect early stages of neurodegenerative disorders such as Alzheimer's disease (AD). Our hypothesis was that cytokeratin 14 (CK14) expression could be used with blood-based biomarkers such as homocysteine, vitamin B12, and folate to identify individuals with MCI or AD from the Australian Imaging, Biomarkers and Lifestyle (AIBL) flagship study of aging. Buccal cells from 54 individuals were analyzed by a newly developed method that is rapid, automated, and quantitative for buccal cell CK14 expression levels. CK14 was negatively correlated with plasma Mg2 + and LDL, while positively correlated with vitamin B12, red cell hematocrit/volume, and basophils in the MCI group and positively correlated with insulin and vitamin B12 in the AD group. The combined biomarker panel (CK14 expression, plasma vitamin B12, and homocysteine) was significantly lower in the MCI (p = 0.003) and AD (p = 0.0001) groups compared with controls. Receiver-operating characteristic curves yielded area under the curve (AUC) values of 0.829 for the MCI (p = 0.002) group and 0.856 for the AD (p = 0.0003) group. These complex associations of multiple related parameters highlight the differences between the MCI and AD cohorts and possibly an underlying metabolic pathology associated with the development of early memory impairment. The changes in buccal cell CK14 expression observed in this pilot study supports previous results suggesting the peripheral biomarkers and metabolic changes are not restricted to brain pathology alone in MCI and AD and could prove useful as a potential biomarker in identifying individuals with an increased risk of developing MCI and eventually AD.

Clinical Benefits for Older Alzheimer's Disease Patients: Okayama Late Dementia Study (OLDS). - Matsuzono, Kosuke; Yamashita, Toru; Ohta, Yasuyuki; Hishikawa, Nozomi; Sato, Kota; Kono, Syoichiro; Deguchi, Kentaro; Nakano, Yumiko; Abe, Koji (J Alzheimers Dis, 2015)
BACKGROUND/OBJECTIVE: There are few reports on the effects of anti-Alzheimer's disease (AD) drugs on older AD patients, and possible differences based on gender in a real world setting. METHODS: "Okayama Late Dementia Study (OLDS)" is a retrospective clinical cohort study focusing on older AD patients (n = 373; age≥75 years) treated with monotherapy donepezil (n = 55), galantamine (n = 222), rivastigmine (n = 63), or memantine (n = 33). The patients were evaluated as an entire group and separated by gender, using seven batteries for dementia assessment at baseline and at 3, 6, and 12 months of drug therapy. RESULTS: All four drugs preserved cognitive and affective functions until 12 months, except for Frontal Assessment Battery (FAB) with memantine ( *p <  0.05 versus baseline). Donepezil monotherapy significantly improved Hasegawa Dementia Rating Scale-Revised (HDS-R) at 3 months ( *p <  0.05), and memantine (3 and 6 months,  *p <  0.05) and rivastigmine (3 months,  **p <  0.01) improved Abe's Behavior and Psychological Symptom of Dementia Score (ABS), respectively. Activities of daily living (ADL) became significantly worse with galantamine at 12 months ( *p <  0.05). Male Mini-Mental State Examination scores became worse at 12 months with donepezil ( *p <  0.05), as did female Geriatric Depression Scale scores at 6 months ( *p <  0.05). Male HDS-R and ABS scores were preserved in the galantamine group until 12 months. Female ABS scores with memantine improved at 6 months ( *p <  0.05), while male ADL scores became worse with rivastigmine at 12 months ( *p <  0.05). CONCLUSION: OLDS revealed that anti-AD drugs were effective even for older AD patients, and the clinical benefits of each drug showed a small difference with regard to gender.

Cognitive Function and Its Relationship with Macular Pigment Optical Density and Serum Concentrations of its Constituent Carotenoids. - Kelly, David; Coen, Robert F; Akuffo, Kwadwo Owusu; Beatty, Stephen; Dennison, Jessica; Moran, Rachel; Stack, Jim; Howard, Alan N; Mulcahy, Riona; Nolan, John M (J Alzheimers Dis, 2015)
BACKGROUND: Macular pigment (MP) levels correlate with brain concentrations of lutein (L) and zeaxanthin (Z), and have also been shown to correlate with cognitive performance in the young and elderly. OBJECTIVE: To investigate the relationship between MP, serum concentrations of L and Z, and cognitive function in subjects free of retinal disease with low MP (Group 1, n = 105) and in subjects with AMD (Group 2, n = 121). METHODS: MP was measured using customized heterochromatic flicker photometry and dual-wavelength autofluorescence; cognitive function was assessed using a battery of validated cognition tests; serum L and Z concentrations were determined by HPLC. RESULTS: Significant correlations were evident between MP and various measures of cognitive function in both groups (r = -0.273 to 0.261, p≤0.05, for all). Both serum L and Z concentrations correlated significantly (r = 0.187, p≤0.05 and r = 0.197, p≤0.05, respectively) with semantic (animal) fluency cognitive scores in Group 2 (the AMD study group), while serum L concentrations also correlated significantly with Verbal Recognition Memory learning slope scores in the AMD study group (r = 0.200, p = 0.031). Most of the correlations with MP, but not serum L or Z, remained significant after controlling for age, gender, diet, and education level. CONCLUSION: MP offers potential as a non-invasive clinical biomarker of cognitive health, and appears more successful in this role than serum concentrations of L or Z.

Comprehensive Gene- and Pathway-Based Analysis of Depressive Symptoms in Older Adults. - Nho, Kwangsik; Ramanan, Vijay K; Horgusluoglu, Emrin; Kim, Sungeun; Inlow, Mark H; Risacher, Shannon L; McDonald, Brenna C; Farlow, Martin R; Foroud, Tatiana M; Gao, Sujuan; Callahan, Christopher M; Hendrie, Hugh C; et al. (J Alzheimers Dis, 2015)
Depressive symptoms are common in older adults and are particularly prevalent in those with or at elevated risk for dementia. Although the heritability of depression is estimated to be substantial, single nucleotide polymorphism-based genome-wide association studies of depressive symptoms have had limited success. In this study, we PERFORMED genome-wide gene- and pathway-based analyses of depressive symptom burden. Study participants included non-Hispanic Caucasian subjects (n = 6,884) from three independent cohorts, the Alzheimer's Disease Neuroimaging Initiative (ADNI), the Health and Retirement Study (HRS), and the Indiana Memory and Aging Study (IMAS). Gene-based meta-analysis identified genome-wide significant associations (ANGPT4 and FAM110A, q-value = 0.026; GRM7-AS3 and LRFN5, q-value = 0.042). Pathway analysis revealed enrichment of association in 105 pathways, including multiple pathways related to ERK/MAPK signaling, GSK3 signaling in bipolar disorder, cell development, and immune activation and inflammation. GRM7, ANGPT4, and LRFN5 have been previously implicated in psychiatric disorders, including the GRM7 region displaying association with major depressive disorder. The ERK/MAPK signaling pathway is a known target of antidepressant drugs and has important roles in neuronal plasticity, and GSK3 signaling has been previously implicated in Alzheimer's disease and as a promising therapeutic target for depression. Our results warrant further investigation in independent and larger cohorts and add to the growing understanding of the genetics and pathobiology of depressive symptoms in aging and neurodegenerative disorders. In particular, the genes and pathways demonstrating association with depressive symptoms may be potential therapeutic targets for these symptoms in older adults.

The GLP-1 Receptor Agonist Liraglutide Improves Memory Function and Increases Hippocampal CA1 Neuronal Numbers in a Senescence-Accelerated Mouse Model of Alzheimer's Disease. - Hansen, Henrik H; Fabricius, Katrine; Barkholt, Pernille; Niehoff, Michael L; Morley, John E; Jelsing, Jacob; Pyke, Charles; Bjerre Knudsen, Lotte; Farr, Susan A; Vrang, Niels (J Alzheimers Dis, 2015)
Recent studies indicate that glucagon-like peptide 1 (GLP-1) receptor agonists, currently used in the management of type 2 diabetes, exhibit neurotrophic and neuroprotective effects in amyloid-β (Aβ) toxicity models of Alzheimer's disease (AD). We investigated the potential pro-cognitive and neuroprotective effects of the once-daily GLP-1 receptor agonist liraglutide in senescence-accelerated mouse prone 8 (SAMP8) mice, a model of age-related sporadic AD not dominated by Aβ plaques. Six-month-old SAMP8 mice received liraglutide (100 or 500 μg/kg/day, s.c.) or vehicle once daily for 4 months. Vehicle-dosed age-matched 50% back-crossed as well as untreated young (4-month-old) SAMP8 mice were used as control groups for normal memory function. Vehicle-dosed 10-month-old SAMP8 mice showed significant learning and memory retention deficits in an active-avoidance T-maze, as compared to both control groups. Also, 10-month-old SAMP8 mice displayed no immunohistological signatures of Aβ plaques or hyperphosphorylated tau, indicating the onset of cognitive deficits prior to deposition of amyloid plaques and neurofibrillary tangles in this AD model. Liraglutide significantly increased memory retention and total hippocampal CA1 pyramidal neuron numbers in SAMP8 mice, as compared to age-matched vehicle-dosed SAMP8 mice. In conclusion, liraglutide delayed or partially halted the progressive decline in memory function associated with hippocampal neuronal loss in a mouse model of pathological aging with characteristics of neurobehavioral and neuropathological impairments observed in early-stage sporadic AD.

Identification of Novel Tau Interactions with Endoplasmic Reticulum Proteins in Alzheimer's Disease Brain. - Meier, Shelby; Bell, Michelle; Lyons, Danielle N; Ingram, Alexandria; Chen, Jing; Gensel, John C; Zhu, Haining; Nelson, Peter T; Abisambra, Jose F (J Alzheimers Dis, 2015)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder that is pathologically characterized by the formation of extracellular amyloid plaques and intraneuronal tau tangles. We recently identified that tau associates with proteins known to participate in endoplasmic reticulum (ER)-associated degradation (ERAD); consequently, ERAD becomes dysfunctional and causes neurotoxicity. We hypothesized that tau associates with other ER proteins, and that this association could also lead to cellular dysfunction in AD. Portions of human AD and non-demented age matched control brains were fractionated to obtain microsomes, from which tau was co-immunoprecipitated. Samples from both conditions containing tau and its associated proteins were analyzed by mass spectrometry. In total, we identified 91 ER proteins that co-immunoprecipitated with tau; 15.4% were common between AD and control brains, and 42.9% only in the AD samples. The remainder, 41.8% of the proteins, was only seen in the control brain samples. We identified a variety of previously unreported interactions between tau and ER proteins. These proteins participate in over sixteen functional categories, the most abundant being involved in RNA translation. We then determined that association of tau with these ER proteins was different between the AD and control samples. We found that tau associated equally with the ribosomal protein L28 but more robustly with the ribosomal protein P0. These data suggest that the differential association between tau and ER proteins in disease could reveal the pathogenic processes by which tau induces cellular dysfunction.

Long-Term Interrelationship between Brain Metabolism and Amyloid Deposition in Mild Cognitive Impairment. - Kemppainen, Nina; Joutsa, Juho; Johansson, Jarkko; Scheinin, Noora M; Någren, Kjell; Rokka, Johanna; Parkkola, Riitta; Rinne, Juha O (J Alzheimers Dis, 2015)
The aim of this longitudinal positron emission tomography (PET) study was to evaluate the interrelationship between brain metabolism and amyloid accumulation during the disease process from mild cognitive impairment (MCI) to Alzheimer's disease (AD). Nine MCI patients, who converted to AD between two and five years, and nine healthy subjects underwent [11C]PIB and [18F]FDG PET scans at baseline and at 5 years. [11C]PIB uptake was clearly higher in MCI patients at baseline compared to controls and spread extensively to the cerebral cortex during the conversion to AD. [18F]FDG uptake was reduced especially in the temporal-parietal regions in MCI compared to controls at baseline, and widely over the cortex at the 5-year follow-up. The reduction in metabolism during the follow-up was significant in the posterior brain regions. In addition, brain amyloid load was positively associated with metabolism in posterior brain regions in MCI, but not after conversion to AD. The results suggest that there are interactions between brain amyloid accumulation and metabolism during the AD process, including a possible compensatory upregulation of posterior brain metabolism in the early phase.

Advancing research diagnostic criteria for Alzheimer's disease: the IWG-2 criteria. - Dubois, Bruno; Feldman, Howard H; Jacova, Claudia; Hampel, Harald; Molinuevo, José Luis; Blennow, Kaj; DeKosky, Steven T; Gauthier, Serge; Selkoe, Dennis; Bateman, Randall; Cappa, Stefano; Crutch, Sebastian; et al. (Lancet Neurol, 2014)
In the past 8 years, both the International Working Group (IWG) and the US National Institute on Aging-Alzheimer's Association have contributed criteria for the diagnosis of Alzheimer's disease (AD) that better define clinical phenotypes and integrate biomarkers into the diagnostic process, covering the full staging of the disease. This Position Paper considers the strengths and limitations of the IWG research diagnostic criteria and proposes advances to improve the diagnostic framework. On the basis of these refinements, the diagnosis of AD can be simplified, requiring the presence of an appropriate clinical AD phenotype (typical or atypical) and a pathophysiological biomarker consistent with the presence of Alzheimer's pathology. We propose that downstream topographical biomarkers of the disease, such as volumetric MRI and fluorodeoxyglucose PET, might better serve in the measurement and monitoring of the course of disease. This paper also elaborates on the specific diagnostic criteria for atypical forms of AD, for mixed AD, and for the preclinical states of AD.
Keywords: Alzheimer Disease; Biomarkers; Humans; International Cooperation; Phenotype; Practice Guidelines as Topic; Societies, Medical

Plasma phospholipids identify antecedent memory impairment in older adults. - Mapstone, Mark; Cheema, Amrita K; Fiandaca, Massimo S; Zhong, Xiaogang; Mhyre, Timothy R; MacArthur, Linda H; Hall, William J; Fisher, Susan G; Peterson, Derick R; Haley, James M; Nazar, Michael D; Rich, Steven A; et al. (Nat Med, 2014)
Alzheimer's disease causes a progressive dementia that currently affects over 35 million individuals worldwide and is expected to affect 115 million by 2050 (ref. 1). There are no cures or disease-modifying therapies, and this may be due to our inability to detect the disease before it has progressed to produce evident memory loss and functional decline. Biomarkers of preclinical disease will be critical to the development of disease-modifying or even preventative therapies. Unfortunately, current biomarkers for early disease, including cerebrospinal fluid tau and amyloid-β levels, structural and functional magnetic resonance imaging and the recent use of brain amyloid imaging or inflammaging, are limited because they are either invasive, time-consuming or expensive. Blood-based biomarkers may be a more attractive option, but none can currently detect preclinical Alzheimer's disease with the required sensitivity and specificity. Herein, we describe our lipidomic approach to detecting preclinical Alzheimer's disease in a group of cognitively normal older adults. We discovered and validated a set of ten lipids from peripheral blood that predicted phenoconversion to either amnestic mild cognitive impairment or Alzheimer's disease within a 2-3 year timeframe with over 90% accuracy. This biomarker panel, reflecting cell membrane integrity, may be sensitive to early neurodegeneration of preclinical Alzheimer's disease.
Keywords: Aged; Alzheimer Disease; Asparagine; Biomarkers; Carnitine; Cohort Studies; Dipeptides; Female; Humans; Longitudinal Studies; Lysophosphatidylcholines; Malates; Male; Memory Disorders; Metabolome; Mild Cognitive Impairment; Neuropsychological Tests; Phosphatidylcholines; Phosphatidylinositols; Phospholipids; Proline; Prospective Studies; Sensitivity and Specificity; Sphingomyelins; Ursodeoxycholic Acid

Two phase 3 trials of bapineuzumab in mild-to-moderate Alzheimer's disease. - Salloway, Stephen; Sperling, Reisa; Fox, Nick C; Blennow, Kaj; Klunk, William; Raskind, Murray; Sabbagh, Marwan; Honig, Lawrence S; Porsteinsson, Anton P; Ferris, Steven; Reichert, Marcel; Ketter, Nzeera; et al. (N Engl J Med, 2014)
BACKGROUND: Bapineuzumab, a humanized anti-amyloid-beta monoclonal antibody, is in clinical development for the treatment of Alzheimer's disease. METHODS: We conducted two double-blind, randomized, placebo-controlled, phase 3 trials involving patients with mild-to-moderate Alzheimer's disease--one involving 1121 carriers of the apolipoprotein E (APOE) ε4 allele and the other involving 1331 noncarriers. Bapineuzumab or placebo, with doses varying by study, was administered by intravenous infusion every 13 weeks for 78 weeks. The primary outcome measures were scores on the 11-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog11, with scores ranging from 0 to 70 and higher scores indicating greater impairment) and the Disability Assessment for Dementia (DAD, with scores ranging from 0 to 100 and higher scores indicating less impairment). A total of 1090 carriers and 1114 noncarriers were included in the efficacy analysis. Secondary outcome measures included findings on positron-emission tomographic amyloid imaging with the use of Pittsburgh compound B (PIB-PET) and cerebrospinal fluid phosphorylated tau (phospho-tau) concentrations. RESULTS: There were no significant between-group differences in the primary outcomes. At week 78, the between-group differences in the change from baseline in the ADAS-cog11 and DAD scores (bapineuzumab group minus placebo group) were -0.2 (P=0.80) and -1.2 (P=0.34), respectively, in the carrier study; the corresponding differences in the noncarrier study were -0.3 (P=0.64) and 2.8 (P=0.07) with the 0.5-mg-per-kilogram dose of bapineuzumab and 0.4 (P=0.62) and 0.9 (P=0.55) with the 1.0-mg-per-kilogram dose. The major safety finding was amyloid-related imaging abnormalities with edema among patients receiving bapineuzumab, which increased with bapineuzumab dose and APOE ε4 allele number and which led to discontinuation of the 2.0-mg-per-kilogram dose. Between-group differences were observed with respect to PIB-PET and cerebrospinal fluid phospho-tau concentrations in APOE ε4 allele carriers but not in noncarriers. CONCLUSIONS: Bapineuzumab did not improve clinical outcomes in patients with Alzheimer's disease, despite treatment differences in biomarkers observed in APOE ε4 carriers. (Funded by Janssen Alzheimer Immunotherapy and Pfizer; Bapineuzumab 301 and 302 ClinicalTrials.gov numbers, NCT00575055 and NCT00574132, and EudraCT number, 2009-012748-17.).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal, Humanized; Apolipoproteins E; Biomarkers; Brain; Cognition; Double-Blind Method; Edema; Female; Humans; Intention to Treat Analysis; Male; Middle Aged; Neuropsychological Tests; Phosphorylation; Positron-Emission Tomography; Severity of Illness Index; tau Proteins; Treatment Failure

Anti-amyloid β autoantibodies in cerebral amyloid angiopathy-related inflammation: implications for amyloid-modifying therapies. - Piazza, Fabrizio; Greenberg, Steven M; Savoiardo, Mario; Gardinetti, Margherita; Chiapparini, Luisa; Raicher, Irina; Nitrini, Ricardo; Sakaguchi, Hideya; Brioschi, Monica; Billo, Giuseppe; Colombo, Antonio; Lanzani, Francesca; et al. (Ann Neurol, 2013)
OBJECTIVE: Cerebral amyloid angiopathy-related inflammation (CAA-ri) is characterized by vasogenic edema and multiple cortical/subcortical microbleeds, sharing several aspects with the recently defined amyloid-related imaging abnormalities (ARIA) reported in Alzheimer's disease (AD) passive immunization therapies. Herein, we investigated the role of anti-amyloid β (Aβ) autoantibodies in the acute and remission phases of CAA-ri. METHODS: We used a novel ultrasensitive technique on patients from a retrospective multicenter case-control study, and evaluated the anti-Aβ autoantibody concentration in the cerebrospinal fluid (CSF) of 10 CAA-ri, 8 CAA, 14 multiple sclerosis, and 25 control subjects. Levels of soluble Aβ40, Aβ42, tau, P-181 tau, and APOE genotype were also investigated. RESULTS: During the acute phase of CAA-ri, anti-Aβ autoantibodies were specifically increased and directly correlated with Aβ mobilization, together with augmented tau and P-181 tau. Following clinical and radiological remission, autoantibodies progressively returned to control levels, and both soluble Aβ and axonal degeneration markers decreased in parallel. INTERPRETATION: Our data support the hypothesis that the pathogenesis of CAA-ri may be mediated by a selective autoimmune reaction against cerebrovascular Aβ, directly related to autoantibody concentration and soluble Aβ. The CSF dosage of anti-Aβ autoantibodies with the technique here described can thus be proposed as a valid alternative tool for the diagnosis of CAA-ri. Moreover, given the similarities between ARIA developing spontaneously and those observed during immunization trials, anti-Aβ autoantibodies can be considered as novel potential biomarkers in future amyloid-modifying therapies for the treatment of AD and CAA.
Keywords: Adult; Aged; Amyloid beta-Peptides; Apolipoproteins E; Autoantibodies; Brain; Case-Control Studies; Cerebral Amyloid Angiopathy; Female; Humans; Inflammation; Male; Middle Aged; Peptide Fragments; Phosphorylation; Retrospective Studies; Steroids; tau Proteins

Integrated systems approach identifies genetic nodes and networks in late-onset Alzheimer's disease. - Zhang, Bin; Gaiteri, Chris; Bodea, Liviu-Gabriel; Wang, Zhi; McElwee, Joshua; Podtelezhnikov, Alexei A; Zhang, Chunsheng; Xie, Tao; Tran, Linh; Dobrin, Radu; Fluder, Eugene; Clurman, Bruce; et al. (Cell, 2013)
The genetics of complex disease produce alterations in the molecular interactions of cellular pathways whose collective effect may become clear through the organized structure of molecular networks. To characterize molecular systems associated with late-onset Alzheimer's disease (LOAD), we constructed gene-regulatory networks in 1,647 postmortem brain tissues from LOAD patients and nondemented subjects, and we demonstrate that LOAD reconfigures specific portions of the molecular interaction structure. Through an integrative network-based approach, we rank-ordered these network structures for relevance to LOAD pathology, highlighting an immune- and microglia-specific module that is dominated by genes involved in pathogen phagocytosis, contains TYROBP as a key regulator, and is upregulated in LOAD. Mouse microglia cells overexpressing intact or truncated TYROBP revealed expression changes that significantly overlapped the human brain TYROBP network. Thus the causal network structure is a useful predictor of response to gene perturbations and presents a framework to test models of disease mechanisms underlying LOAD.
Keywords: Adaptor Proteins, Signal Transducing; Alzheimer Disease; Animals; Bayes Theorem; Brain; Gene Regulatory Networks; Humans; Membrane Proteins; Mice; Microglia

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Modeling Alzheimer's disease with iPSCs reveals stress phenotypes associated with intracellular Aβ and differential drug responsiveness. - Kondo, Takayuki; Asai, Masashi; Tsukita, Kayoko; Kutoku, Yumiko; Ohsawa, Yutaka; Sunada, Yoshihide; Imamura, Keiko; Egawa, Naohiro; Yahata, Naoki; Okita, Keisuke; Takahashi, Kazutoshi; Asaka, Isao; et al. (Cell Stem Cell, 2013)
Oligomeric forms of amyloid-β peptide (Aβ) are thought to play a pivotal role in the pathogenesis of Alzheimer's disease (AD), but the mechanism involved is still unclear. Here, we generated induced pluripotent stem cells (iPSCs) from familial and sporadic AD patients and differentiated them into neural cells. Aβ oligomers accumulated in iPSC-derived neurons and astrocytes in cells from patients with a familial amyloid precursor protein (APP)-E693Δ mutation and sporadic AD, leading to endoplasmic reticulum (ER) and oxidative stress. The accumulated Aβ oligomers were not proteolytically resistant, and docosahexaenoic acid (DHA) treatment alleviated the stress responses in the AD neural cells. Differential manifestation of ER stress and DHA responsiveness may help explain variable clinical results obtained with the use of DHA treatment and suggests that DHA may in fact be effective for a subset of patients. It also illustrates how patient-specific iPSCs can be useful for analyzing AD pathogenesis and evaluating drugs.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cell Differentiation; Cerebral Cortex; Docosahexaenoic Acids; Humans; Induced Pluripotent Stem Cells; Intracellular Space; Models, Biological; Mutant Proteins; Neurons; Oxidative Stress; Phenotype; Protein Structure, Quaternary

An epigenetic blockade of cognitive functions in the neurodegenerating brain. - Gräff, Johannes; Rei, Damien; Guan, Ji-Song; Wang, Wen-Yuan; Seo, Jinsoo; Hennig, Krista M; Nieland, Thomas J F; Fass, Daniel M; Kao, Patricia F; Kahn, Martin; Su, Susan C; Samiei, Alireza; et al. (Nature, 2012)
Cognitive decline is a debilitating feature of most neurodegenerative diseases of the central nervous system, including Alzheimer's disease. The causes leading to such impairment are only poorly understood and effective treatments are slow to emerge. Here we show that cognitive capacities in the neurodegenerating brain are constrained by an epigenetic blockade of gene transcription that is potentially reversible. This blockade is mediated by histone deacetylase 2, which is increased by Alzheimer's-disease-related neurotoxic insults in vitro, in two mouse models of neurodegeneration and in patients with Alzheimer's disease. Histone deacetylase 2 associates with and reduces the histone acetylation of genes important for learning and memory, which show a concomitant decrease in expression. Importantly, reversing the build-up of histone deacetylase 2 by short-hairpin-RNA-mediated knockdown unlocks the repression of these genes, reinstates structural and synaptic plasticity, and abolishes neurodegeneration-associated memory impairments. These findings advocate for the development of selective inhibitors of histone deacetylase 2 and suggest that cognitive capacities following neurodegeneration are not entirely lost, but merely impaired by this epigenetic blockade.
Keywords: Acetylation; Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Epigenesis, Genetic; Gene Expression Regulation; Gene Knockdown Techniques; Hippocampus; Histone Deacetylase 2; Histones; Humans; Hydrogen Peroxide; Memory Disorders; Mice; Neurodegenerative Diseases; Neuronal Plasticity; Peptide Fragments; Phosphorylation; Promoter Regions, Genetic; Receptors, Glucocorticoid; RNA Polymerase II

National Institute on Aging-Alzheimer's Association guidelines for the neuropathologic assessment of Alzheimer's disease. - Hyman, Bradley T; Phelps, Creighton H; Beach, Thomas G; Bigio, Eileen H; Cairns, Nigel J; Carrillo, Maria C; Dickson, Dennis W; Duyckaerts, Charles; Frosch, Matthew P; Masliah, Eliezer; Mirra, Suzanne S; Nelson, Peter T; et al. (Alzheimers Dement, 2012)
A consensus panel from the United States and Europe was convened recently to update and revise the 1997 consensus guidelines for the neuropathologic evaluation of Alzheimer's disease (AD) and other diseases of brain that are common in the elderly. The new guidelines recognize the pre-clinical stage of AD, enhance the assessment of AD to include amyloid accumulation as well as neurofibrillary change and neuritic plaques, establish protocols for the neuropathologic assessment of Lewy body disease, vascular brain injury, hippocampal sclerosis, and TDP-43 inclusions, and recommend standard approaches for the workup of cases and their clinico-pathologic correlation.
Keywords: Alzheimer Disease; Brain; Consensus Development Conferences, NIH as Topic; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

A paravascular pathway facilitates CSF flow through the brain parenchyma and the clearance of interstitial solutes, including amyloid β. - Iliff, Jeffrey J; Wang, Minghuan; Liao, Yonghong; Plogg, Benjamin A; Peng, Weiguo; Gundersen, Georg A; Benveniste, Helene; Vates, G Edward; Deane, Rashid; Goldman, Steven A; Nagelhus, Erlend A; Nedergaard, Maiken (Sci Transl Med, 2012)
Because it lacks a lymphatic circulation, the brain must clear extracellular proteins by an alternative mechanism. The cerebrospinal fluid (CSF) functions as a sink for brain extracellular solutes, but it is not clear how solutes from the brain interstitium move from the parenchyma to the CSF. We demonstrate that a substantial portion of subarachnoid CSF cycles through the brain interstitial space. On the basis of in vivo two-photon imaging of small fluorescent tracers, we showed that CSF enters the parenchyma along paravascular spaces that surround penetrating arteries and that brain interstitial fluid is cleared along paravenous drainage pathways. Animals lacking the water channel aquaporin-4 (AQP4) in astrocytes exhibit slowed CSF influx through this system and a ~70% reduction in interstitial solute clearance, suggesting that the bulk fluid flow between these anatomical influx and efflux routes is supported by astrocytic water transport. Fluorescent-tagged amyloid β, a peptide thought to be pathogenic in Alzheimer's disease, was transported along this route, and deletion of the Aqp4 gene suppressed the clearance of soluble amyloid β, suggesting that this pathway may remove amyloid β from the central nervous system. Clearance through paravenous flow may also regulate extracellular levels of proteins involved with neurodegenerative conditions, its impairment perhaps contributing to the mis-accumulation of soluble proteins.
Keywords: Amyloid beta-Peptides; Animals; Aquaporin 4; Astrocytes; Biological Transport; Brain; Cerebral Ventricles; Cerebrospinal Fluid; Extracellular Fluid; Imaging, Three-Dimensional; Male; Mice; Mice, Inbred C57BL; Microscopy, Fluorescence, Multiphoton; Water

Gamma-secretase activating protein is a therapeutic target for Alzheimer's disease. - He, Gen; Luo, Wenjie; Li, Peng; Remmers, Christine; Netzer, William J; Hendrick, Joseph; Bettayeb, Karima; Flajolet, Marc; Gorelick, Fred; Wennogle, Lawrence P; Greengard, Paul (Nature, 2010)
Accumulation of neurotoxic amyloid-beta is a major hallmark of Alzheimer's disease. Formation of amyloid-beta is catalysed by gamma-secretase, a protease with numerous substrates. Little is known about the molecular mechanisms that confer substrate specificity on this potentially promiscuous enzyme. Knowledge of the mechanisms underlying its selectivity is critical for the development of clinically effective gamma-secretase inhibitors that can reduce amyloid-beta formation without impairing cleavage of other gamma-secretase substrates, especially Notch, which is essential for normal biological functions. Here we report the discovery of a novel gamma-secretase activating protein (GSAP) that drastically and selectively increases amyloid-beta production through a mechanism involving its interactions with both gamma-secretase and its substrate, the amyloid precursor protein carboxy-terminal fragment (APP-CTF). GSAP does not interact with Notch, nor does it affect its cleavage. Recombinant GSAP stimulates amyloid-beta production in vitro. Reducing GSAP concentrations in cell lines decreases amyloid-beta concentrations. Knockdown of GSAP in a mouse model of Alzheimer's disease reduces levels of amyloid-beta and plaque development. GSAP represents a type of gamma-secretase regulator that directs enzyme specificity by interacting with a specific substrate. We demonstrate that imatinib, an anticancer drug previously found to inhibit amyloid-beta formation without affecting Notch cleavage, achieves its amyloid-beta-lowering effect by preventing GSAP interaction with the gamma-secretase substrate, APP-CTF. Thus, GSAP can serve as an amyloid-beta-lowering therapeutic target without affecting other key functions of gamma-secretase.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Benzamides; Cell Line; Disease Models, Animal; Gene Knockdown Techniques; Humans; Imatinib Mesylate; Mice; Peptide Fragments; Piperazines; Proteins; Pyrimidines; Receptor, Notch1; RNA Interference

Genetic evidence implicates the immune system and cholesterol metabolism in the aetiology of Alzheimer's disease. - Jones, Lesley; Holmans, Peter A; Hamshere, Marian L; Harold, Denise; Moskvina, Valentina; Ivanov, Dobril; Pocklington, Andrew; Abraham, Richard; Hollingworth, Paul; Sims, Rebecca; Gerrish, Amy; Pahwa, Jaspreet Singh; et al. (PLoS One, 2010)
BACKGROUND: Late Onset Alzheimer's disease (LOAD) is the leading cause of dementia. Recent large genome-wide association studies (GWAS) identified the first strongly supported LOAD susceptibility genes since the discovery of the involvement of APOE in the early 1990s. We have now exploited these GWAS datasets to uncover key LOAD pathophysiological processes. METHODOLOGY: We applied a recently developed tool for mining GWAS data for biologically meaningful information to a LOAD GWAS dataset. The principal findings were then tested in an independent GWAS dataset. PRINCIPAL FINDINGS: We found a significant overrepresentation of association signals in pathways related to cholesterol metabolism and the immune response in both of the two largest genome-wide association studies for LOAD. SIGNIFICANCE: Processes related to cholesterol metabolism and the innate immune response have previously been implicated by pathological and epidemiological studies of Alzheimer's disease, but it has been unclear whether those findings reflected primary aetiological events or consequences of the disease process. Our independent evidence from two large studies now demonstrates that these processes are aetiologically relevant, and suggests that they may be suitable targets for novel and existing therapeutic approaches.
Keywords: Alzheimer Disease; Apolipoproteins E; Cholesterol; Chromosome Mapping; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Immune System; Polymorphism, Single Nucleotide

Memory impairment in transgenic Alzheimer mice requires cellular prion protein. - Gimbel, David A; Nygaard, Haakon B; Coffey, Erin E; Gunther, Erik C; Laurén, Juha; Gimbel, Zachary A; Strittmatter, Stephen M (J Neurosci, 2010)
Soluble oligomers of the amyloid-beta (Abeta) peptide are thought to play a key role in the pathophysiology of Alzheimer's disease (AD). Recently, we reported that synthetic Abeta oligomers bind to cellular prion protein (PrP(C)) and that this interaction is required for suppression of synaptic plasticity in hippocampal slices by oligomeric Abeta peptide. We hypothesized that PrP(C) is essential for the ability of brain-derived Abeta to suppress cognitive function. Here, we crossed familial AD transgenes encoding APPswe and PSen1DeltaE9 into Prnp-/- mice to examine the necessity of PrP(C) for AD-related phenotypes. Neither APP expression nor Abeta level is altered by PrP(C) absence in this transgenic AD model, and astrogliosis is unchanged. However, deletion of PrP(C) expression rescues 5-HT axonal degeneration, loss of synaptic markers, and early death in APPswe/PSen1DeltaE9 transgenic mice. The AD transgenic mice with intact PrP(C) expression exhibit deficits in spatial learning and memory. Mice lacking PrP(C), but containing Abeta plaque derived from APPswe/PSen1DeltaE9 transgenes, show no detectable impairment of spatial learning and memory. Thus, deletion of PrP(C) expression dissociates Abeta accumulation from behavioral impairment in these AD mice, with the cognitive deficits selectively requiring PrP(C).
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Avoidance Learning; Brain; Disease Models, Animal; Maze Learning; Memory; Mice; Mice, Inbred C57BL; Mice, Transgenic; Nerve Degeneration; Presenilin-1; PrPC Proteins; Random Allocation; Serotonin; Survival Analysis